Alkylation of benzene with alpha-olefins over zirconia supported 12-silicotungstic acid - Sawant, D. P.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
Liquid phase alkylation of benzene to linear alkyl benzene (LAB) with alpha-olefins has been investigated with 12-silicotungstic acid supported on zirconia (STA/ZrO2) as the catalyst. Among the catalysts, 15 wt.% STA/ZrO2 calcined at 750 degrees C was found to be most active than others in the alkylation reaction. The total amount of acid sites of different STA loaded catalysts were estimated by TPD of NH3 and 15 wt.% STA/ZrO2 calcined at 750 degrees C was found to have the highest acidity and more active in the reaction. The optimization of reaction conditions of alkylation of benzene with 1-dodecene was performed with 15 wt.% STA/ZrO2 calcined at 750 degrees C by varying catalyst concentration (1-5 wt.% of reaction mixture); temperature, 373-423 K and benzene: 1-dodecene (1-dd) molar ratio, 5-15 in a Parr autoclave under N-2 pressure. Under the optimized reaction conditions, conversion of 1-dodecene (50.8%) gave high selectivity to 2-phenyl dodecane (47.1%) and the remaining 3-, 4-, 5- and 6-phenyldodecanes in 4 h. The reaction was found to be heterogeneously catalyzed and no contribution from homogeneous (leached) STA into the reaction medium. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 1-dodecene; 12-silicotungstic acid; Alkylation; Benzene; LAB; Zirconia

Benzylation of benzene and other aromatics by benzyl chloride over mesoporous AlSBA-15 catalysts - Vinu, A.; Sawant, D. P.; Ariga, Katsuhiko; Hartmann, Martin; Halligudi, Shivappa B. (Microporous and Mesoporous Materials, 2005)
Aluminum-containing mesoporous molecular sieves AISBA-15 with different n(Si)/n(Al), ratios and AIMCM-41 have been synthesized hydrothermally and characterized in detail by physicochemical methods, viz. XRD, N(2) adsorption and (27)Al NMR spectroscopy. The low angle XRD and N2 adsorption measurements reveal that the structural order of SBA-15 was retained after the incorporation of Al. The increase of the unit cell parameter with increasing aluminum content and (27)Al MAS NMR spectroscopy confirm the incorporation of aluminum in the framework. Benzylation of benzene and substituted benzenes reaction employing benzyl chloride as the alkylating agent over AISBA-15 and AIMCM-41 have been investigated. The influence of various reaction parameters such as reaction temperature, reactant feed ratio and catalyst amount affecting the activity and selectivity of AISBA-15, have been studied. Among the mesoporous catalysts studied, AISBA-15(45), where the number in parentheses indicates the molar nsilnA, ratio, shows both high conversion and high selectivity for the benzylation of benzene. The activity of this catalyst for the benzylation of different aromatic compounds is in the following order: benzene > toluene > p-xylene > mesitylene > anisole. Kinetics of the benzene benzylation over different catalysts have also been investigated. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Alkylation; AlSBA-15; Benzylation; SBA-15

Biphenyl hydrogenation over supported transition metal catalysts under supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, C. V.; Sato, O.; Shirai, M. (Applied Catalysis A - General, 2005)
Catalytic hydrogenation of biphenyl to bicyclohexyl, an organic hydrogen storage medium, was examined over supported transition metal catalysts in supercritical carbon dioxide solvent. The yield of bicyclohexyl was almost 100% over the charcoal-supported rhodium (Rh/C) and ruthenium (Ru/C) catalysts at the temperature of 323 K, which was much lower than that required for biphenyl hydrogenation in organic solvents (573 K). The initial activity was higher over the Rh/C catalyst, while the initial selectivity to bicyclohexyl was higher over the Ru/C catalyst. The conversion of biphenyl increased with increase in hydrogen and carbon dioxide pressures, while the selectivity to bicyclohexyl was independent of hydrogen and carbon dioxide pressures over both catalysts. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: bicyclohexyl; biphenyl; charcoal-supported rhodium catalyst; charcoal-supported ruthenium catalyst; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide

Bis(2-[alpha-hydroxyethyl]benzimidazolato)copper(II) anchored onto chloromethylated polystyrene for the biomimetic oxidative coupling of 2-aminophenol to 2-aminophenoxazine-3-one - Maurya, Mannar R.; Sikarwar, S.; Joseph, Trissa; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
2-(alpha-Hydroxyethyl)benzimidazole (Hhebmz) has been covalently anchored to chloromethylated polystyrene cross-linked with 5% divinylbenzene. This polymer-anchored chelating resin reacts with cupric acetate in presence of Hhebmz to give polymer-anchored copper(II) complex PS-[Cu(hebmz)(2)]. Elemental analyses, FT-IR, electronic, scanning electron micrographs (SEM) and TGA-DTA pattern have been used to characterize the complex. Oxidative coupling of 2-aminophenol (OAP) to 2-aminophenoxazine-3-one (APX) catalyzed by PS-[Cu(hebmz)(2)] in presence of air at 70 degrees C in DMF gave 62% substrate conversion over a period of 8 h. Kinetics of the above reaction indicated that the rate of oxidative coupling of OAP has a first order dependence with respect to substrate, catalyst and air pressure (dissolved O-2) concentrations in the range of conditions evaluated. Based on these observations, a plausible mechanism for the above reaction has been proposed. From, the study on the effect of temperature on the rates of oxidative coupling, an activation energy 34.2 kcal/degree mole was evaluated from Arrhenius plot of -ln rate versus 1/T. Enthalpy, entropy and free energy were calculated using standard thermodynamic equations for the above reaction. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 2-aminophenol; 2-aminophenoxazine-3-one; bis(2-[alpha-hydroxyethyl]benzimidazolato)copper(II); chloromethylated polystyrene; oxidative coupling

Bronsted acidic ionic liquids: a green, efficient and reusable catalyst system and reaction medium for fischer esterification - Joseph, Trissa; Sahoo, S.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
Bronsted acidic ionic liquid containing nitrogen-based organic cations 1-methylimidazole and 1-butyl-3-methylimidazolium and inorganic anions of the type BF4-, PF6- and PTSA(-) has been synthesized in good yields and used as a catalysts and reaction medium for Fischer esterification of alcohols with acids. These were characterized using FTIR and NMR spectroscopy. Ionic liquids as catalyst afforded good alcohol conversion and excellent ester selectivity. Fischer esterification of acetic acid with benzyl alcohol with different Bronsted acidic ionic liquids was carried out. Maximum substrate conversion 100 % and product selectivity 100 % was observed on using [BMIM](+)PTSAas catalyst over a period of 2 h. The ester was easily separated from the reaction mixture and the ionic liquid was reused four times after removing water. No significant loss in catalytic activity was observed on recycling. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: acids; alcohol and reaction medium; Fischer esterification; Ionic liquid

Comparison of the pervaporation separation of a water-acetonitrile mixture with zeolite-filled sodium alginate and poly(vinyl alcohol)-polyaniline semi-interpenetrating polymer network membranes - Naidu, B. V. K.; Bhat, S. D.; Sairam, M.; Wali, A. C.; Sawant, D. P.; Halligudi, Shivaraj B.; Mallikarjuna, N. N.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The pervaporation (PV) separation performance of ZSM-5- and Na-Y-type zeolite-filled sodium alginate (NaAlg) membranes were compared with those of pure NaAlg and semi-interpenetrating polymer network (semi-IPN) membranes of poly(vinyl alcohol) (PVA) with polyaniline (PANI) for the dehydration of acetonitrile. The PV separation characteristics of the zeolite-filled membranes showed a dependence on the nature of the zeolites. The variation of the acidity function of the ZSM-5 zeolite had an influence on the flux and selectivity of the membranes when compared to unfilled membranes. The crosslinked membranes were characterized by differential scanning calorimetry, X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. Increasing the PANI content of the semi-IPN network increased the separation selectivity. Among the NaAlg membranes, the plain NaAlg membrane showed the highest selectivity of 414 at 30 mass % water in the feed mixture, whereas the Na-Y- and ZSM-5 (40)-filled NaAlg membranes exhibited much lower values of selectivity, that is, 7.3 and 4.3, respectively for 30 mass % water in the feed. When the flux and selectivity data of ZSM-5 (250)-filled NaAlg membranes were compared with that of Na-Y- or ZSM-5 (40)-filled NaAlg membranes, a noticeable increase in the selectivity for the ZSM-5 (250)filled NaAlg membrane was observed, but a somewhat comparable flux was observed compared to the plain NaAlg membrane. For the first time, PANI was polymerized with PVA to yield a semi-IPN. The total flux and water flux increased systematically, whereas the selectivity decreased greatly from 251.87 to 5.95 with increasing amounts of water in the feed. (c) 2005 Wiley Periodicals, Inc.
Keywords: Diffusion; interpenetrating network (IPN); zeolites

Copper(II) ion-exchanged montmorillonite as catalyst for the direct addition of N-H bond to CC triple bond - Joseph, Trissa; Shanbhag, G. V.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
An efficient synthesis of phenyl-(1-phenylethylidene)amine using copper-exchanged montmorillonite clay (Cu K-10) is demonstrated. The catalyst was characterized using UV-vis, XRD, BET surface area measurements, pyridine adsorption etc. The XRD and surface area measurement show that the structural characteristics of the support montmorillonite K-10 (K-10) are preserved after Cu exchange. The hydroamination of phenyl acetylene with aniline was carried out in toluene under reflux condition in N-2 atmosphere at 393 K. The reaction is highly regio-selective for only Markovnikoff's addition of an-tine to CC multiple bond and proceeded smoothly to completion. The reaction conditions were optimized to obtain complete conversion with respect to phenyl acetylene. Reaction data showed that the activity of the catalyst in hydroamination reaction is greater at higher reaction temperatures and nonpolar solvents and NZ pressure promotes the reaction drastically. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: alkyne; Aniline; Catalyst; hydroamination; K-10 montmorillonite clay; phenyl acetylene

Direct synthesis of well-ordered and unusually reactive FeSBA-15 mesoporous molecular sieves - Vinu, A.; Sawant, D. P.; Ariga, Katsuhiko; Hossain, K. Z.; Halligudi, Shivappa B.; Hartmann, Martin; Nomura, M. (Chemistry of Materials, 2005)
Large-pore hexagonal SBA-15 molecular sieves partially substituted with iron(III) have been synthesized for the first time in highly acidic media. The degree of iron(III) incorporation into SBA-15 can easily be controlled by a simple adjustment of the molar ratio of water and hydrochloric acid. All the materials have been characterized by XRD, N-2 adsorption, UV-Vis DRS, ESR, and XANES spectroscopy. The characterization of the FeSBA-15 materials by UV-Vis DRS, ESR, and XANES spectroscopies suggests that the iron atoms are highly dispersed and mostly occupy isolated tetrahedral sites. XANES studies revealed that the proportion of tetrahedrally coordinated Fe atoms decreases with decreasing n(Si)/n(Fc) ratios. Benzylation of benzene (or substituted benzenes) using benzyl chloride as the alkylating agent over FeSBA-15 with different n(Si)/n(Fe) ratios was investigated as was the same reaction using AISBA-15 as catalyst. The influence of parameters such as reaction temperature, reactant feed ratio, and the presence of electron-donating substituents on the activity and selectivity of AISBA-15 was studied. Under optimized reaction conditions, the FeSBA-15 catalyst showed a superior catalytic performance in the benzylation of benzene and other aromatics using benzyl chloride, with a clean conversion of benzyl chloride to the monoalkylated product (100% selectivity) with a very high rate constant when compared to other mesoporous materials such as AISBA-15 and FeHMS. Interestingly, use of FeSBA-15(21) resulted in quantitative conversion of benzyl chloride with a high rate constant of 2420.5 x 10(-4) min(-1) under the optimized reaction conditions.

Diversity oriented synthesis of tricyclic compounds from glycals using the ferrier and the pauson-khand reactions - Hotha, Srinivas; Tripathi, A. (Journal of Combinatorial Chemistry, 2005)
Diversity oriented synthesis of tricyclic compounds was achieved using a combination of the Ferrier reaction and the Pauson-Khand reaction. Ferrier reaction was effected using NbCl5, and the Pauson-Khand reaction was carried out using CO2(CO)(8), acetonitrile-dimethoxyethane. Michael additions using various alkyl, aryl, and heterocyclic thiols were also performed successfully. The Ferrier, Pauson-Khand, and Michael addition reactions were found to be highly diastereoselective.

Efficient and improved method for the Biginelli reaction using solid superacid (sulphated SnO2) - Bhosale, R. S.; Hashmi, A. M.; Zubaidha, P. K.; Dongare, Mohan K. (Heterocyclic Communications, 2005)
One-pot synthesis of 3,4-dihydropyrimidin-2(1H)-one (DHPM) has been effected efficiently by coupling of the three components, aldehyde, ethyl acetoacetate and urea/thiourea in the presence of solid Superacid (sulphated SnO2). The method presented herein is attractive with respect to yield, reaction time, workup procedure and reusable catalyst.
Keywords: Biginelli; DHPM; sulphated SnO2

Efficient method for the synthesis of methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate - Salunke, D. B.; Hazra, Braja G.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Pore, V. S. (Tetrahedron, 2005)
The synthesis of methyl 11 alpha-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate, methyl 11 beta-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate and methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate have been achieved. Mechanistic aspects for the decomposition of steroidal azidoketones to its enamines are discussed. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 11-aminosteroid; 11-azidosteroid; base catalyzed epimerization; HIV-1 protease inhibitors; steroidal enamines

Enhanced selectivity to decalin in naphthalene hydrogenation under supercritical carbon dioxide - Hiyoshi, Norihito; Miura, R.; Rode, C. V.; Sato, O.; Shirai, M. (Chemistry Letters, 2005)
A charcoal-supported rhodium catalyst was highly active and selective to decalin for the hydrogenation of naphthalene at very low temperature (333 K) under supercritical carbon dioxide.

Expedient synthesis of 1,2,3-triazole-fused tetracyclic compounds by intramolecular Huisgen ('click') reactions on carbohydrate-derived azido-alkynes - Hotha, Srinivas; Anegundi, Ramakrishna I.; Natu, A. A. (Tetrahedron Letters, 2005)
An efficient, practical and convenient synthesis of 1,2,3-triazole-fused tetracyclic compounds was achieved by intramolecular 1,3-dipolar cycloaddition of carbohydrate-derived azido-alkynes. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; Click chemistry; Cycloaddition; diversity oriented synthesis; Huisgen reaction

Formation of nanosized zirconia-supported 12-tungstophosphoric acid in mesoporous silica SBA-15: a stable and versatile solid acid catalyst for benzylation of phenol - Sawant, D. P.; Vinu, A.; Jacob, Nalini E.; Lefebvre, F.; Halligudi, Shivappa B. (Journal of Catalysis, 2005)
A nanosized zirconia-supported 12-tungstophosphoric acid (TPA) in SBA-15 composite was prepared by wet impregnation of TPA/ZrO2 nanoparticles inside the mesoporous channels of SBA-15. The resulting composite material was calcined at 1123 K and characterized by elemental analysis, powder X-ray diffraction, nitrogen adsorption isotherms, transmission electron microscopy (TEM), scanning electron microscopy (SEM), solid-state P-31 CP-MAS NMR, Si-29 MAS NMR, UV-vis diffuse reflectance spectra, FTIR, TPD of ammonia, FTIR pyridine adsorption, and thermogravimetric analysis (TG-DTG). The synthesized TPA/ZrO2/SBA-15 showed a well-ordered hexagonal inesoporous structure and mesoporous support SBA-15 stabilized ZrO2-t (tetragonal) phase with crystal size in the range of 3-4 nm. SBA-15 was a better support than MCM-41 and MCM-48 because it retained its mesostructure even after high TPA loading and high calcination temperatures. Mesoporous silica support plays an important role in stabilizing the catalytically active tetragonal phase of zirconia, which gave the most active catalysts. The catalysts were examined for their catalytic activities in the liquid phase benzylation of phenol with benzyl alcohol and the catalyst 15 wt% TPA/ 22.4 wt% ZrO2/SBA-15 calcined at 1123 K was found to have high acidity and to be 10 times more active than neat TPA/ZrO2 Under the reaction conditions studied in benzylation of phenol. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: nanosized; phenol benzylation reaction; terragonal phase; TPA/ZrO2

Gold nanoparticle networks with photoresponsive interparticle spacings - Sidhaye, D. S.; Kashyap, Sudhir; Sastry, M.; Hotha, Srinivas; Bhagavatula L. V. Prasad (Langmuir, 2005)
Photoresponsive gold nanoparticle networks were prepared by functionalizing them with azobenzene derivatives. A network can be formed when a linker molecule constituting the azobenzene moiety suitably derivatized on either side with gold surface sensitive groups such as thiols and amines is added to the nanoparticle solution. It is shown that the interparticle spacing in the networks could be controlled by the reversible trans-cis isomerization of the azobenzene moiety induced by UV and visible light, respectively. The photoinduced variation in the interparticle spacings is inferred by the changes in the optical spectra of the gold nanoparticles which display a red or blue shift in the surface plasmon resonance peak depending on a decrease or increase in the interparticle spacing, respectively. Transmission electron microscopy images are in consonance with the evidence from the optical spectra.

Growth of PbS nanopyramidal particulate films for potential applications in quantum-dot photovoltaics and nanoantennas - Hawaldar, Ranjit R.; Mulik, Uttam P.; Patil, K.; Pasricha, R.; Sathaye, S.; Lewis, A.; Amalnerkar, Dinesh P. (Materials Research Bulletin, 2005)
We report a simple interfacial process called the liquid-liquid interface reaction technique (LLIRT) that leads to the formation of nanosized PbS particulate films with hitherto unreported pyramidal morphology. The resultant PbS films were characterized by transmission electron microscopy (TEM) with selected area electron diffraction (SAED), X-ray diffractometery (XRD), atomic force microscopy (AFM), near field scanning optical microscopy (NSOM) and UV-vis spectroscopy. The pyramidal morphology is speculated to originate from the preferred orientation of the 2 2 0 plane of cubic PbS. Our nanopyramidal PbS particulate films display remarkably sharp excitonic peak centered around 656 nm that accounts for a band gap of 1.8 eV suggesting, in turn, their potential application in QD photovoltaics. Interestingly, the feasibility of such nanopyramids to potentially act as nanoantennas (as revealed by the NSOM) is also suggested. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Atomic force microscopy; Chemical synthesis; Electron microscopy; Nanostructures; Optical properties

Highly active and selective AlSBA-15 catalysts for the vapor phase tert-butylation of phenol - Vinu, A.; Devassy, Biju M.; Halligudi, Shivaraj B.; Bohlmann, W.; Hartmann, Martin (Applied Catalysis A-General, 2005)
Hexagonally ordered mesoporous AISBA-15 catalysts having n(Si)/(nA]) ratios from 7 to 215 have been synthesized hydrothermally using a cheap non-ionic block copolymer as the structure-directing agent. The obtained materials were analyzed by XRD and nitrogen adsorption to determine the structural order and the textural properties. It has been observed by Al-27 MAS NMR spectroscopy that aluminum atoms are exclusively in tetrahedral coordination for all samples except AISBA-15(7), where octahedral aluminum has been detected to some extent. Temperature-programmed desorption of pyridine showed that AISBA-15(45) has a higher number of strong acid sites as compared to other mesoporous materials such as FeMCM-41, AIMCM-41 and FcAlMCM-41. The catalyst AlSBA-15(45)showed superior performance in the acid-catalyzed tertiary butylation of phenol employing tert-butanol as the alkylation agent. A high phenol conversion of 86.3% is observed for this catalyst at a reaction temperature of 150 degrees C. Over AISBA-15(45), the 4-TBP yield amounts to 40.5% and the 2,4-DTBP yield corresponds to 37.9%. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Acidity; AlSBA-15; aluminum incorporation; butylation of phenol; SBA-15

Hydrophobically modified poly(acrylic acid) using 3-pentadecylcyclohexylamine: synthesis and rheology - Shedge, A. S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique; Pcrrin, P.; Chassenieux, Christophe; Badiger, Manohar V. (Macromolecular Chemistry and Physics, 2005)
Hydrophobically modified poly(acrylic acid) was synthesized using 3-pentadecylcyclohexylamine (3-PDCA), which was in turn synthesized from 3-pentadecylphenol, one of the components of cashew-nut shell liquid (CNSL), a renewable resource material. H-1 NMR spectra confirmed the incorporation of 3-PDCA onto PAA and a series of HMPs with three different molar concentrations, viz. congruent to 3, 5 and 7 mol-% of 3-PDCA, were synthesized. An increase in viscosity with increasing hydrophobic content was observed by rheological measurements. The critical association concentrations were determined using an Ubbelohde viscometer and a controlled stress rheometer. The stability of HMPs towards temperature and shear was studied. Rheological measurements showed that there was a steady increase in viscosity with increase in hydrophobe content due to the formation of reversible networks. These polymers exhibited gel-like behavior at low concentrations (greater than or equal to2 wt.-%) with an apparent yield stress (ca. 10 Pa) and showed shear thinning properties (non-Newtonian). However, below a critical concentration, c [eta], they showed Newtonian behavior.
Keywords: 3-pentadecylcyclohexylamine (3-PDCA); hydrophobically modified polymers (HMPs); poly(acrylic acid); reversible associations; Rheology

Insight into the mechanism of selective mono-N-methylation of aniline on Cu1-xZnxFe2O4: a DRIFTS study - Vijayaraj, M.; Murugan, B.; Shubhangi B. Umbarkar; Hegde, S. G.; Gopinath, Chinnakonda S. (Journal of Molecular Catalysis A - Chemical, 2005)
Mechanism of selective mono-N-methylation of aniline with methanol on Cu1-xZn2FeO4 catalysts was investigated in detail. The interaction of reactants (aniline. methanol and methanol: aniline) and possible products (N-methylaniline (NMA), N,N-dimethylaniline (DMA) and o-toluidine (OT)) on catalysts surface was studied by temperature-dependent in situ FTIR spectroscopy. Methanol adsorbs dissociatively over catalysts surface at 373 K as methoxy species and is oxidized to formate species at high temperature through dioxymethylene and/or formaldehyde as a surface intermediate species. On the other hand, adsorption of aniline:methanol mixtures shows that methanol oxidation was completely hindered in the presence of aniline. Aniline adsorbs on the Lewis acid sites at <= 373 K with phenyl ring oriented in a perpendicular manner to the catalyst surfaced however, N-H bond scission occurs above 373 K. A comparison of adsorbed NMA and methanol: am line (3:1) mixture on Cu0.5Zn0.5Fe2O4 shows NMA forms from the reaction mixture at 473 K. However, maximum activity at 573 K in catalytic reaction studies suggests that desorption limits the methylation kinetics. FTIR study displays stable aniline and methyl species on ZnFe2O4 even at 573 K; however. no methyl species is detected on Cr0.95Zn0.05Fe2O4 at 473 K due to methanol reforming reaction and that limits the overall reaction and hence low catalytic activity. It is proposed that methanol is protonated on catalysts surface by the labile H+ due to N-H bond scission. Co-adsorption of acidity probes with aniline and methanol indicates that aniline methylation takes place at single acid-base site. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Aniline; Cu1-xZnxFe2O4; desorption limited; DRIFT; IR; Methanol; N-methylaniline; N-methylation; reaction mechanism

Kunitz trypsin inhibitor from chickpea (Cicer arietinum L.) that exerts anti-metabolic effect on podborer (Helicoverpa armigera) larvae - Srinivasan, A.; Giri, Ashok P.; Harsulkar, Abhay M.; Gatehouse, J. A.; Gupta, Vidya S. (Plant Molecular Biology, 2005)
Chickpea (Cicer arietinum L.) seeds contain Bowman-Birk proteinase inhibitors, which are ineffective against the digestive proteinases of larvae of the insect pest Helicoverpa armigera. We have identified and purified a low expressing proteinase inhibitor (PI), distinct from the Bowman-Birk Inhibitors and active against H. armigera gut proteinases (HGP), from chickpea seeds. N-terminal sequencing of this HGP inhibitor revealed a sequence similar to reported pea (Pisum sativum) and chickpea alpha-L-fucosidases and also homologous to legume Kunitz inhibitors. The identity was confirmed by matrix assisted laser desorption ionization - time of flight analysis of tryptic peptides and isolation of DNA sequence coding for the mature protein. Available sequence data showed that this protein forms a distinct phylogenetic cluster with Kunitz inhibitors from Glycine max, Medicago truncatula, P. sativum and Canavalia lineata. The isolated coding sequence was cloned into a yeast expression vector and produced as a recombinant protein in Pichia pastoris. alpha-L-fucosidase activity was not detectable in purified or recombinant protein, by solution assays. The recombinant protein did not inhibit chymotrypsin or subtilisin activity but did exhibit stoichiometric inhibition of trypsin, comparable to soybean Kunitz trypsin inhibitor. The recombinant protein exhibited higher inhibition of total HGP activity as compared to soybean kunitz inhibitor, even though it preferentially inhibited HGP-trypsins. H. armigera larvae fed on inhibitor-incorporated artificial diet showed significant reduction in average larval weight after 18 days of feeding demonstrating potent antimetabolic activity. The over-expression of this gene in chickpea could act as an endogenous source of resistance to H. armigera.
Keywords: Chickpea; Cicer arietinum; fucosidase; Helicoverpa armigera; Kunitz; Proteinase inhibitor

Larvicidal activity of acacia nilotica extracts and isolation of D-pinitol - a bioactive carbohydrate - Chaubal, Rohini; Pawar, P. V.; Hebbalkar, G. D.; Tungikar, V. B.; Puranik, Vedavati G.; Deshpande, V. H.; Deshpande, N. R. (Chemistry & Biodiversity, 2005)
A low-molecular-weight, sugar-like compound other than glucose, fructose, sucrose, or myo-inositol showing lipophilic nature was isolated from the EtOH extract of Acacia nilotica. The structure of the compound was determined by spectral methods. This alicyclic polyalcohol was found to be D-pinitol (- 3-O-methyl-D-chiro-inositol; 1). The configuration of the compound was confirmed by single-crystal X-ray analysis. The compound I is known from Soybean, Australian mangroves, Fagonia indica, A rachis hypogaea, etc., but we have isolated this compound for the first time from the aerial parts of A. nilotica. Very few references have been cited for compound I for its entomological activity, and there are no reports on mosquitoes. Therefore, the crude extracts of A. nilotica were tested for its biological activity against mosquito larvae. Acetone extract at 500-ppm concentration showed chronic toxicity against Aedes aegypti and Culex quinquefasciatus IVth instar mosquito larvae. Such a biological activity has been observed for the first time for this plant. This study could be a stepping stone to a solution for destroying larval species as well as consumption of such a widely grown, problem weed, A. nilotica. This larvicidal agent, since it is derived from plant, is eco-friendly, cost effective, non-hazardous to nontarget organisms and would be safe unlike commercially available insecticides.

Liquid-phase alkylation of phenol with long-chain olefins over WOx/ZrO2 solid acid catalysts - Sarish, S.; Devassy, Biju M.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The liquid-phase alkylation of phenol with 1-dodecene was carried out over WOx/ZrO2 solid acid catalysts. The catalysts were prepared by wet impregnation method using zirconium oxyhydroxide and ammonium metatungstate. Catalysts with different WO3 loading (5-30 wt.%) were prepared and calcined at 800 degrees C and catalyst with 15% WO3 was calcined from 700-850 degrees C. All the catalysts were characterized by surface area, XRD, and FTIR. The catalyst with 15% WO3 calcined at 800 degrees C (15 WZ-800) was found to be the most active in the reaction. The effect of temperature, molar ratio and catalyst weight on dodecene conversion and products selectivity was studied in detail. Under the optimized reaction conditions of 120 degrees C, phenol/1-dodecene molar ratio 2 and time 2 h, the catalyst 15 WZ-800 gave > 99% dodecene conversion with 90% dodecylphenol selectivity. Comparison of the catalytic activity of 15 WZ-800 with sulfated zirconia calcined at 500 degrees C (SZ-500) and HP zeolite showed that activity of SZ-500 was lower than that of 15 WZ-800, while HP zeolite showed negligible activity. It is observed that the presence of water in the reaction mixture was detrimental to the catalytic activity of WOx/ZrO2. The catalyst 15 WZ-800 also found to be an efficient catalyst for alkylation of phenol with long-chain olefins like 1-octene and 1-decene. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Alkylation; long-chain olefins; phenol; tungsten oxide; Zirconia

Miscibility of chitosan-hydroxyethylcellulose blends in aqueous acetic acid solutions at 35 degrees C - Wali, A. C.; Naidu, B. V. K.; Mallikarjuna, N. N.; Sainkar, S. R.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The miscibility of blends of chitosan and hydroxyethylcellulose in a 2% acetic acid solution was studied by viscometry, densitometry, and refractometry at 35 degrees C. The data suggest that the blends were completely miscible in all proportions. Further, the membranes were fabricated from concentrated blend solutions. The solid-state compatibility of the blends was confirmed by scanning electron microscopy. (c) 2005 Wiley Periodicals, Inc.
Keywords: blends; miscibility; refractive index; viscosity

Modeling of rotary desiccant wheels - Harshe, Yogesh M.; Utikar, R. P.; Ranade, V. V.; Pahwa, D. (Chemical Engineering & Technology, 2005)
Rotary desiccant wheels are widely used in dehumidification and energy recovery applications. In this work, we have developed a 2D, steady state model of a rotary desiccant wheel. Mass and energy balance equations for the air streams and the desiccant wheels were developed. The hydraulic diameter and surface area for heat and mass transfer were calculated based on knowledge of the flute geometry. Appropriate correlations for the Sherwood number and Nusselt number were used to estimate heat and mass transfer coefficients. The model is capable of predicting steady state behavior of desiccant wheels having at the most three sections (process, purge, and regeneration). The mathematical model was validated using a real desiccant wheel, and the calculation results are in reasonable agreement with the experimental data. Based on this model, the temperature and humidity profiles in the wheel during both the dehumidification and the regeneration processes are analyzed. The simulated results were used to gain an insight into the operation of desiccant wheels. The model and the presented results will be useful for optimizing dehumidification and energy recovery applications.
Joint 5th International Symposium on Catalysis in Multiphase Reactors/4th International Symposium on Multifunctional Reactors, Portoroz-Portorose, SLOVENIA, JUN 15-18, 2005
Keywords: 1; 4-benzodioxan-2-carboxylate; 4-benzodioxan-2-carboxylic acid; doxazosin; enantio selectivity; enantiomeric ratio; ethyl 1; ethyl acetate; Lipases; transesterfication

Molecular dynamics simulations of H2O with sites of Cu-I-FAU and Cu-II-FAU - Berthomieu, D.; Krishnamurty, S.; Heine, Thomas; Goursot, A. (Studies in surface science and catalysis, 2005)
A Born Oppenheimer molecular dynamic (BOMD) approach was chosen to study the interaction of water molecules with Cu-FAU models. We have compared the reactivity of Cu-I and Cu-II with the zeolite and compared the results to those calculated for Na. This Study shows a decrease of the coordination with time for Cu-I whereas there is not a significant change for Cu-II. BOMD shows also that, in the presence of water, Na+ may lead to easier cation exchange than for transition metal cations.
3rd Conference of the Federation-of-European-Zeolite-Association, Prague, CZECH REPUBLIC, AUG 23-29, 2005

Nanostructured tin oxide: synthesis and gas-sensing properties - Niranjan, R. S.; Hwang, Young Kyu; Kim, D. K.; Jhung, S. H.; Chang, J. S.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2005)
Pure and Ru-doped nanostructured SnO2 sensing materials were synthesized using a modified Pechini route. Incorporation of Ru in SnO2 results in the reduction of particle size (8.3 nm) compared with that of the pure SnO2 (28.2 nm). Moreover, the sensor exhibited a reasonably good sensitivity towards both H-2 and liquified petroleum gas (LPG). The effect of Ru incorporation, operating temperature, and gas concentration on the structure, morphology, and sensitivity is discussed using the results of X-ray diffraction (XRD), and scanning electron microscopy (SEM) along with sensing performance. © 2005 Elsevier B.V. All rights reserved.
Keywords: hydrogen and hydrocarbon sensor; Nanostructure; ruthenium; tin oxide

Niobium(V) chloride catalyzed microwave assisted synthesis of 2,3-unsaturated O-glycosides by the Ferrier reaction - Hotha, Srinivas; Tripathi, A. (Tetrahedron Letters, 2005)
NbCk catalyzes the Ferrier reaction of per-O-acetylated glycals with primary, secondary, altylic, benzylic and monosaccharide alcohols to give 2,3-unsaturated alpha-glycosides in short reaction times under microwave irradiation conditions. (c) 2005 Elsevier Ltd. All rights reserved.

Novel polymer-inorganic solid-state reaction for the synthesis of CdS nanocrystallites - Kanade, K. G.; Hawaldar, Ranjit R.; Pasricha, R.; Radhakrishnan, S.; Seth, T.; Mulik, Uttam P.; Kale, B. B.; Amalnerkar, Dinesh P. (Materials Letters, 2005)
We offer a novel polymer-inorganic solid-state reaction route for the in situ generation of nanochalcogenide semiconductor in the network of polymer which itself acts as a chalcogen source. We have exemplified feasibility of this route by reacting CdI2 with engineering thermoplastic polyphenylene sulphide (PPS). These two reactants in 1:1 and 10:1 molar ratios were simply heated at the crystalline melting temperature of PPS. The resultant products were characterized by X-ray diffractometry, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM, with selected area electron diffraction). The prima facie observations revealed the formation of cubic nanocrystallites of US with the particle size ranging from 6 to 20 nm entrapped in modified (cyclized) PPS matrix when the reactants were taken in 10:1 molar ratio. A tentative mechanism has been suggested for such hitherto unattempted solid-state reaction. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: CdS nanocrystallites; Semiconductor; solid-state reaction; Thermoplastic polymer matrix

Oxyfunctionalization of limonene using vanadium complex anchored on functionalized SBA-15 - Joseph, Trissa; Halligudi, Shivappa B. (Journal of Molecular Catalysis A-Chemical, 2005)
VO(Salten) complexes, where Salten = 3-[N,N'-bis-3(salicylidenamino)ethyltriamine], have been covalently anchored on to functionalized SBA-15. The formation and integrity of the complex have been confirmed by elemental analysis, Fr-IR, X-ray diffraction (XRD) and BET measurements and the complex was used for the oxyfunctionalization of limonene in presence of urea hydroperoxide (UHP) as the oxidizing agent. The oxyfunctionalization of limonene resulted in limonene oxide, carvone, carvacrol and carveol. Anchored complex showed better catalytic activity than the neat complex, while the neat complexes has deactivated in the reaction due to formation of inactive alpha-oxo-bridged dimers, the covalently anchored complexes remained stable throughout the reaction. The anchored complex could be easily separated from the products and could be reused. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: covalently anchored vanadium complex; functionalized Si-SBA-15; limonene; oxofunctionalization; UHP

Partial ring hydrogenation of naphthols over supported metal catalysts in supercritical carbon dioxide solvent - Mine, Eiichi; Haryu, E.; Arai, K.; Sato, T.; Sato, O.; Sasaki, A.; Rode, C. V.; Shirai, M. (Chemistry Letters, 2005)
Selective ring hydrogenation of naphthols to tetrahydronaphthols and tetralones proceeded at 323 K over a charcoal supported rhodium catalyst in supercritical carbon dioxide.

Photoluminescent core-shell particles of organic dye in silica - Ethiraj, Anita S.; Hebalkar, Neha; Kharrazi, Sharmin; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Journal of Luminescence, 2005)
Using a single silica precursor, Rhodamine 6G organic dye molecules have been entrapped in silica particles resulting into core-shell particles of similar to 500 nm diameter. Energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy analysis reveals that dye molecules are trapped inside the silica particles. Photoluminescence investigations show that highly luminescent and photostable core-shell particles are formed. Such core-shell particles can be easily suspended in water and would be useful for a variety of applications. However, there is a blue shift in the photolumineseence wavelength in case of core-shell particles compared to bare dye powder sample. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: core-shell; Luminescence; Nanoparticles; photoemission; RH06G dye; tetraethylorthosilicate (TEOS)

Self-assembly of nanostructured PbS for solar photovoltaic applications - Hawaldar, Ranjit R.; Kanade, K. G.; Patil, K. R.; Sathaye, S. D.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Materials Chemistry and Physics, 2005)
In the present communication, the self-assembly of nanocrystalline PbS at the liquid-liquid interface is reported. The PbS nanocrystals were, subsequently, transformed in the form of thin films by dip coating. The resultant Q-PbS films were characterized by SEM-EDAX, TEM-SAED, XRD, XPS and UV-vis Spectroscopy. Pyramidal features at the nanometer scale, preferred orientation along (2 2 0) and (4 0 0) planes of cubic structure and a sharp excitonic peak at 656 run are the salient aspects of this work. The band-gap of the order of 1.8 eV (associated with the excitonic feature) is ideally suited for solar photovoltaic applications. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid interface; nanopyramid; Nanostructures; PbS

Silicotungstate-modified zirconia as an efficient catalyst for phenol tert-butylation - Devassy, Biju M.; Shanbhag, G. V.; Mirajkar, Subhash P.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The alkylation of phenol with tert-butanol was investigated using zirconia modified with silicotungstic acid (STA) as catalysts. The catalysts with different STA loading (5-25 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 350 to 850 degrees C) were prepared and characterized by X-ray diffraction and NH3-TPD measurements. The XRD results indicate that STA stabilizes the tetragonal phase of zirconia. The catalyst with 15% STA on ZrO2 calcined at 750 degrees C shows the highest acidity and hence highest activity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), phenol conversion was 95.4% with selectivity to 2-tert-butyl phenol 4.3%, 4-tert-butyl phenol 59.2% and 2,4-di-tert-butyl phenol 35.8%. The reaction was studied as a function of time for 50 It without appreciable change in phenol conversion and product selectivity. The deactivated catalyst could be regenerated by calcination with out appreciable lose in catalytic activity and product selectivity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phenol; Silicotungstic acid; tert-butylation; Zirconia

On the single-root approach within the framework of coupled-cluster theory in fock space - Horny, L; Schaefer, HF; Hubac, I; Pal, S (Chemical Physics, 2005)
A thorough formulation of Fock Space Brillouin-Wigner Coupled Cluster method is presented following previous developments [N.D.K. Petraco, L Horny, H.F. Schaefer, I. Hubac, J. Chem. Phys. 117 (2002) 9580]. The new method is designed to avoid the intruder states problem, and introduces the single-root solution feature which has not been considered yet within valence-universal methods. The explicit equations for the (0,1) sector of the Fock space are introduced. (C) 2005 Elsevier B.V. All rights reserved.

Stereoselective synthesis of (2R, 3S, 22R, 23E)-6, 6-ethylenedioxy-22-hydroxy-2, 3-isopropylidenedioxy-24-methyl-5 alpha-cholest-23-ene: An intermediate for the synthesis of castasterone, dolichosterone and brassinolide - Hazra, Braja G.; Kumar, T. P.; Pore, V. S. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2005)

Stereoselective synthesis of spiroannulated cyclopentenones by the Pauson-Khand reaction on carbohydrate derived enynes - Hotha, Srinivas; Maurya, S. K.; Gurjar, M. K. (Tetrahedron Letters, 2005)
The stereoselective synthesis of spiroannulated cyclopentenones by the Pauson-Khand reactions on hexose and pentose derived enynes was achieved under carbon monoxide free conditions using a stoichiometric quantity of Co-2(CO)(8). The cobalt complex of the alkyne was cleaved using dimethoxyethane-acetonitrile at 85 degrees C to furnish spiroarmulated cyclopentenones in 75-94% yields. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; cyclopentenone; diversity oriented synthesis; Pauson-Khand reaction

Structural rationalisation of co-crystals formed between trithiocyanuric acid and molecules containing hydrogen bonding functionality - Ahn, Sung-Hoon; PrakashaReddy, J.; Kariuki, B. M.; Chatterjee, S.; Ranganathan, A.; Pedireddi, V. R.; Rao, C. N. R.; Harris, Kenneth D. M. (Chemistry - A European Journal, 2005)
Crystallisation of trithiocyanuric acid (TTCA) from various organic solvents that have hydrogen bonding capability (acetone, 2-butanone, dimethylformamide, dimethyl sulfoxide, methanol and acetonitrile) leads to the formation of co-crystals in which the solvent molecules are incorporated together with TTCA in the crystal structure. Structure determination by single-crystal X-ray diffraction reveals that these co-crystals can be classified into different groups depending upon the topological arrangement of the TTCA molecules in the crystal structure. Thus, three different types of single-tape arrangements of TTCA molecules and one type of double-tape arrangement of TTCA molecules are identified. In all co-crystals, hydrogen-bonding interactions are formed through the involvement of N-H bonds of TTCA molecules in these tapes and the other molecule in the co-crystal. Detailed rationalisation of the structural properties of these co-crystals is presented.
Symposium on Chemistry-A European Conference - Stimulating Concepts in Chemistry, Inst Sci Ingenierie Supramoleculaires, Strasbourg, FRANCE, APR 15, 2005
Keywords: crystal engineering; hydrogen bonds; nitrogen heterocycles; structure elucidation

Studies on effect of silane coupling agent on the mechanical properties of clay filled natural rubber - Alkadasi, N. A. N.; Sarwade, B. D.; Kapadi, U. R.; Hundiwale, D. G. (Journal of the Indian Chemical Society, 2005)
Effect of treatment of coupling agents bis(3-triethoxvsilylpropyl)tetrasulphide (Si-69)] on mechanical properties of composites made from natural rubber and clay is reported here. The treatment resulted in enhancement of mechanical properties of composites of the said rubber when compared with untreated clay composites separately. The properties under consideration were tensile strength, modulus at 100% and 400%, Young's modulus, elongation at break, hardness, etc. Tensile strength was improved by 118.75%, modulus at 400% was found to improve by 422% while Young's modulus also was improved by 133% when compared with untreated clay composites at 0.42 volume fraction.

Study of correlation of structural and surface properties with electrochemical behaviour in carbon aerogels - Hebalkar, Neha; Arabale, G.; Sainkar, S. R.; Pradhan, S. D.; Mulla, Imtiaz S.; Vijayamohanan, K.; Ayyub, P.; Kulkarni, S. K. (Journal of Materials Science, 2005)
Carbon aerogel is a promising material for electrochemical double layer capacitors. In this paper carbon aerogels prepared by subcritical drying method are investigated for the change in the structure and surface properties at different pyrolysis temperatures. The important relations between structure, morphology, surface area and electrical properties were studied using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), surface area measurement and cyclic voltametry. It is shown that structure and the surface functional groups play important role in enhancement of electrochemical capacitance. The specific capacitance achieved was 114 F/gm which is quite large value for subcritically prepared carbon aerogels without any kind of activation process. (c) 2005 Springer Science + Business Media, Inc.

Synthesis and analysis of ZnO and CdSe nanoparticles - Ashtaputre, S. S.; Deshpande, Aparna; Marathe, Sayali; Wankhede, M. E.; Chimanpure, J.; Pasricha, R.; Urban, J.; Haram, Santosh K.; Gosavi, S. W.; Kulkarni, S. K. (Pramana-Journal of Physics, 2005)
Zinc oxide and cadmium selenide particles in the nanometer size regime have been synthesized using chemical routes. The particles were capped using thioglycerol in case of ZnO and 2-mercaptoethanol in case of CdSe to achieve the stability and avoid the coalescence. Zinc oxide nanoparticles were doped with europium to study their optical properties. A variety of techniques like UV-Vis absorption spectroscopy, X-ray diffraction (XRD), photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and transmission electron microscopy (TEM) were used to carry out structural and spectroscopic characterizations of the nanoparticles.
1st National Conference on Nanoscience and Technology, Pune, INDIA, MAR 07-08, 2005
Keywords: chemical capping; Doping; Nanoparticles; photoluminescence

Synthesis and swelling behaviour of hydrophobically modified responsive polymers in dilute aqueous solutions - Iyer, N. P.; Hourdet, Dominique; Badiger, Manohar V.; Chassenieux, Christophe; Perrin, P.; Wadgaonkar, P. (Polymer, 2005)
New series of associating polymers were synthesised in order to investigate opposite behaviours of hydrophobically modified water-soluble polymers and thermoresponsive water-soluble polymers carrying LCST stickers. On the basis of a poly(acrylic acid) backbone, amino-terminated poly(N-isopropylacrylamide), poly(ethylene oxide-co-propylene oxide) and/or dodecyl chains were grafted following a reaction of condensation activated by carbodiimide. Two homologous series of well-defined single grafted and double grafted copolymers were obtained, with double grafted chains containing both C12 and LCST grafts. The dilute solution properties of these copolymers were carefully studied by capillary viscometry. At low salt concentration and below the LCST of the grafts, the swelling properties of macromolecular chains are controlled either by intramolecular associations between hydrophobes, excluded volume effect exerted by hydrophilic grafts or by a balance between these opposite interactions. The deswelling of macromolecular chains, induced by hydrophobic interactions, is amplified at higher ionic strength and more particularly above the transition temperature of the side chains. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: associating polymers; poly(acrylic acid); viscometry

Synthesis, characterization and catalytic potentials of polymer anchored copper(II), oxovanadium(IV) and dioxomolybdenum(VI) complexes of 2-(alpha-hydroxymethyl)benzimidazole - Maurya, Mannar R.; Sikarwar, S.; Joseph, Trissa; Manikandan, Palanichamy; Halligudi, Shivappa B. (Reactive & Functional Polymers, 2005)
{2-(alpha-Hydroxymethyl)benzimidazole (Hhmbmz) has been covalently anchored to chloromethylated polystyrene cross-linked with 5% divinylbenzene. This chelating resin reacts with cupric acetate, vanadyl sulphate and [MoO(2)-(acac)(2)] (Hacac = acetylacetone) in presence of Hhmbmz to give complexes PS-[Cu(hmbmz)(2)], PS-[VO(hmbmz)(2)] and PS-[MoO(2)(hmbmz)(2)] (where
Keywords: 2-(alpha-hydroxymethyl)benzimidazole; oxidation of styrene and ethyl benzene; oxidative bromination of salicylaldehyde; polymer anchored-complexes

Synthesis of linear alkyl benzenes over zirconia-supported 12-molybdophosphoric acid catalysts - Devassy, Biju M.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated using zirconia-supported 12-molybdophosphoric acid (MPA) as catalyst. The catalysts with different MPA loading (5-25 wt.% calcined at 700 degrees C) and calcination temperature (15 wt.% calcined from 500 to 750 degrees C) were prepared by suspending zirconium oxyhydroxide in methanol solution of MPA followed by drying and calcination. These catalysts were characterized by X-ray diffraction, and P-31 MAS NMR spectroscopy measurements. The XRD results indicated that MPA stabilizes the tetragonal phase of zirconia. 3 1 P MAS NMR spectra show that the nature of phosphorous species depend on MPA loading and calcination temperature, and it show the existence of three types of phosphorous species, one is the Keggin unit and the other is the decomposition product of MPA and third one an unidentified species. FTIR pyridine adsorption on 15% MPA catalyst calcined at 700 degrees C showed the presence both Bronsted and Lewis acidity. Under the reaction conditions of 83 C, benzene/1-olefin molar ratio of 10 (time, 1 h), the most active catalyst, 15% MPA calcined at 700 C gave more than 90% olefin conversion with selectivity to 2-phenyl octane, 55% and 2-phenyl dodecane, 45%. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 12-molybdophosphoric acid; benzene alkylation; linear alkyl benzene; Zirconia

tert-Butylation of p-cresol over WOx/ZrO2 solid acid catalysts - Sarish, S.; Devassy, Biju M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The tert-butylation of p-cresol with tert-butanol was carried out over WO3/ZrO2 catalysts under flow conditions, The catalysts were prepared by wet impregnation method using zirconium oxyhydroxide and ammonium metatungstate. Catalysts with different WO3 loading (5-30 wt.%) were prepared and calcined at 800 degrees C and catalyst with 15% WO,, was calcined from 600 to 900 C. The catalysts were characterized by surface area, XRD, FTIR and TEM. The catalyst 15% WO3/ZrO2 calcined at 800 degrees C found to be the most active in the reaction. The effect of temperature, space velocity and molar ratio of the reactants on the conversion of p-cresol and products selectivities were studied. Under the optimized reaction conditions of 130 degrees C, tert-butanol/p-cresol molar ratio of 3 and flow rate of 10 ml h(-1). p-cresol conversion was 69.8% with selectivity to 2-tert-butyl-p-cresol 92.4%, 2,6-di-tert-butyl-p-cresol 6.3% and p-cresol tert-butyl ether 1.3%. The catalytic activity is compared with sulfated zirconia, USY, H beta zeolites and montmorillonite K-10 under the optimized reaction conditions The activity of sulfated zirconia is lower than that of 15% WO3/ZrO2 catalyst calcined at 800 C and other catalysts showed very low activity, (c) 2005 Elsevier B.V.. All rights reserved.
Keywords: p-Cresol; tert-butylation; tungsten oxide; Zirconia

Thermoreversible behavior of associating polymer solutions: thermothinning versus thermothickening - Hourdet, Dominique; Gadgil, Jayant; Podhajecka, K.; Badiger, Manohar V.; Brulet, A.; Wadgaonkar, P. P. (Macromolecules, 2005)
Self-assembling properties of poly(sodium acrylate) grafted with dodecyl [C12], PAAgC12, or poly(N-isopropylacrylamide) [PNIPA] side chains, PAAgPNIPA, were studied in unentangled semidilute aqueous solution. While PAAgC12 self-associates through hydrophobic interactions, the gelation of PAAgPNIPA is triggered by heating in response to the lower critical solution temperature of PNIPA (LCST similar to 32 degrees C). The local structure of the physical networks was investigated by small-angle neutron scattering, and the scattering patterns were described using a polydisperse sphere model taking into account hard-sphere interactions. This model allow us to draw a realistic picture of physical gels with quantitative information concerning the size of hydrophobic cores, the volume fraction of stickers in the aggregates, the fraction of stickers which take part in the aggregation process, the range of repulsive interactions, and the structural modifications induced by temperature. The description of the network is in good agreement with complementary data obtained from DSC and C-13 NMR. In the present work, a special emphasis has been given to the important relationship existing between the viscoelastic properties of associating polymer solutions and the binding energy of stickers leaving temporarily the micellar junction. Depending on the endothermic or exothermic nature of the disengagement process of the sticker (heat of demicellization), the relaxation time of the network and the viscoelastic properties will either decrease or increase with the temperature. The consequence is that aqueous solutions of PAAgC12 and PAAgPNIPA exhibit opposite rheological properties with the temperature, namely thermothinning and thermothickening. By mixing these two copolymers, we show that intermediate properties can be obtained but in that case a microphase-separated network is obtained as a result of copolymer segregation.

Thidiazuron-induced morphogenesis in tamarind seedlings - Mehta, Urmil J.; Sahasrabudhe, N.; Hazra, Sulekha (In Vitro Cellular & Developmental Biology-Plant, 2005)
Germination of tamarind seeds in medium containing thidiazuron (TDZ) resulted in induction of nodular protrusions in and around the cotyledonary node meristem. The structures developed radially in well-defined circles and subsequently spread towards the cotyledonary bridge and also in the proximal part of the hypocotyl. The structures developed into shoots on transfer to medium devoid of growth regulators. Histological studies revealed that the protrusions initiated from the nodal meristem and extended to the non-meristematic region between the two meristems and also in the proximal part of the hypocotyl in seedlings germinated in 9.08 mu M TDZ. Newly formed cell layers and less-differentiated meristematic protrusions were also seen. With the increase in the distance from the meristem, the buds were less differentiated; in the proximal part of the hypocotyl only the multiple layers of meristematic cells were noted. With extension of the period of incubation, the TDZ-induced meristematic activity extended laterally in circles towards the neighboring region. The radial spread of the meristematic activity from the center of the nodal meristem was also evident at 18.16 mu M TDZ. From the pattern of the morphogenic development and the histological studies it may be hypothesized that in tamarind, TDZ influences the existing meristems specifically. Subsequently de novo organogenesis is triggered in the neighboring cells.
Keywords: Caulogenesis; Histology; morphogenesis; protrusions; thidiazuron

Unraveling biochemical properties of cockroach (Periplaneta americana) proteinases with a gel X-ray film contact print method - Hivrale, Vandana K.; Chougule, Nanasaheb P.; Chhabda, Pavan J.; Giri, Ashok P.; Kachole, M. S. (Comparative Biochemistry and Physiology B-Biochemistry & Molecular Biology, 2005)
Eleven proteinase activity bands were detected in American cockroach (Periplaneta americana) gut. These were partially purified and characterized using a gel X-ray film contact print method. Cockroach gut proteinases (CGPs) show activity over a broad range of pH with maximum activity between pH 6 and 10, and optimal activity at 50-70 degrees C. CGPs were partially purified by preparative gel electrophoresis and analyzed using synthetic substrates and inhibitors. Four of the proteases exhibited chymotrypsin-like (C1 to C4) activity and seven trypsin-like (T I to T7) activity. Accuracy of the gel X-ray film contact print method is confirmed by including bovine chymotrypsin in CGP analysis. Inhibition of CGPs with different plant proteinaceous proteinase inhibitors allowed identification of potential CGP inhibitors. Our results imply that presence of several CGP activity bands, and their stability and activity over a broad pH and temperature range might contribute to adaptation of P americana to extreme environmental conditions and the polyphagous nature of the species. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: activity visualization; cockroach; gut enzymes; Periplaneta americana; plant proteinase inhibitors; Proteinases

Zirconia-supported 12-tungstophosphoric acid as a solid catalyst for the synthesis of linear alkyl benzenes - Devassy, Biju M.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated with zirconia-supported 12-tungstophosphoric acid (TPA) as catalysts. We prepared the catalysts, with different TPA loading (5-20 wt% calcined at 750 degrees C) and calcination temperatures (15 wt% calcined from 650 to 850 degrees C), by suspending hydrous zirconia in a methanol solution of TPA, followed by drying and calcination. These catalysts were characterized by X-ray diffraction, DTG-DTA, FTIR pyridine adsorption, NH3-TPD, and P-31, MAS NMR spectroscopy measurements. The catalyst with optimum TPA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents and characterized by P-31 MAS NMR spectroscopy. The XRD results indicate that TPA stabilizes the tetragonal phase of zirconia. The catalysts show both Bronsted and Lewis acidity, and 15% TPA on zirconia calcined at 750 degrees C shows the highest acidity. P-31 MAS NMR spectra show two types of phosphorous species: one is the Keggin unit and the other is the decomposition product of TPA. The relative amount of each depends on TPA loading, calcination temperature, and the solvent used for the catalyst preparation. Under reaction conditions of 84 degrees C and a benzene/1-olefin molar ratio of 10 (time 1 h), the most active catalyst, 15% TPA, calcined at 750 degrees C, gave more than 98% olefin conversion with selectivity for 2-phenyl octane (53.5%) and 2-phenyl dodecane (47%). (c) 2004 Elsevier Inc. All rights reserved.
Keywords: 12-tungstophosphoric acid; linear alkyl benzene; solvent effect; Zirconia

Zirconia-supported phosphotungstic acid as catalyst for alkylation of phenol with benzyl alcohol - Devassy, Biju M.; Shanbhag, G. V.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of phenol with benzyl alcohol was carried out using zirconia-supported phosphotungstic acid (PTA) as catalyst. The catalysts with different PTA loadings (5-20 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 650 to 850 degrees C) were prepared and characterized by (31)p MAS NMR and FT-IR pyridine adsorption spectroscopy. The catalyst with optimum PTA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents. 31p MAS NMR spectra of the catalysts showed two types of phosphorous species, one is the Keggin unit and the other is the decomposition product of PTA and the relative amount of each depends on PTA loading, calcination temperature and the solvent used for the catalyst preparation. The catalysts with 15% PTA on zirconia calcined at 750 degrees C showed the highest Bronsted acidity. At 130 degrees C and phenol/benzyl alcohol molar ratio of 2 (time, I h), the most active catalyst, 15% PTA calcined at 750 degrees C gave 98% benzyl alcohol conversion with 83% benzyl phenol selectivity. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Benzylation; phenol; Phosphotungstic acid; Zirconia

2,4,6-tris(2-pyridyl)-1,3,5-triazine (tptz)-derived [Ru-II(tptz)(acac)(CH3CN)](+) and mixed-valent [(acac)(2)Ru-III(mu-tptz-H+)(-)Ru-II(acac)(CH3CN)](+) - Ghumaan, Sandeep; Kar, S.; Mobin, Shaikh M.; Harish, B.; Puranik, Vedavati G.; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
Mononuclear [Ru-II(tptz)(acac:)(CH3CN)]ClO4 ((ClO4)-Cl-[1]) and mixed-valent dinuclear [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(CH3CN)]ClO4 ([5]ClO4; acac = acetylacetonate) complexes have been synthesized via the reactions of Ru-II(acac)2(CH3CN)(2) and 2,4,6-tris(2-pyridyl)-1,3,5-triazine (tptz), in 1:1 and 2:1 molar ratios, respectively. In [1]ClO4, tptz binds with the Ru-II ion in a tridentate N,N,N mode (motif A), whereas in [5]ClO4, tptz: bridges the metal ions unsymmetrically via the tridentate neutral N,N,N mode with the Ru-II center and cyclometalated N,C- state with the Ru-III site (motif F). The activation of the coordinated nitrile function in [1]ClO4 and [5]ClO4 in the presence of ethanol and alkylamine leads to the formation of iminoester ([2]ClO4 and [7]ClO4) and amidine ([4]ClO4) derivatives, respectively. Crystal structure analysis of [2]ClO4 reveals the formation of a beautiful eight-membered water cluster having a chair conformation. The cluster is H-bonded to the pendant pyridyl ring N of tptz and also with the O atom of the perchlorate ion, which, in turn, makes short (C-H––-O) contacts with the neighboring molecule, leading to a H-bonding network. The redox potentials corresponding to the (RuI)-I-I state in both the mononuclear {[(acac)(tptz)Ru-II-N=-C-CH3]ClO4 ([1]ClO4) >> [(acac)(tptz)Ru-II-NH=C(CH3)-OC2H5]ClO4 ([2]ClO4) > [(acac)(tptz)(RuNH2)-N-II-C6H4(CH3)]ClO4 ([3]ClO4) > [(acac)(tptz)Ru-II-NH=C(CH3)-NHC2H5]ClO4 ([4]ClO4)} and dinuclear {[(acac)(2)Ru-III-{mu-tptz-H+)(-)}Ru-II(acac)(N equivalent to C-CH3)]ClO4 {(mu-tptz-H+)(-)}Ru-II(acac)(N equivalent to C-CH3)]ClO4 ([5]ClO4), [(acac)(2)Ru-III[(mu-tptz-H+(N-O ([6]ClO4), [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(NH=C(CH3)-OC2H5)]ClO4( [7]ClO4), and [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(NC4H4N)]ClO4 ([8]ClO4), complexes vary systematically depending on the electronic nature of the coordinated sixth ligands. However, potentials involving the Ru-III center in the dinuclear complexes remain more or less invariant. The mixed-valent (RuRuIII)-Ru-II species ([5]ClO4-[8]ClO4) exhibits high comproportionation constant (K-c) values of 1.1 X 10(12)-2 x 109, with substantial contribution from the donor center asymmetry at the two metal sites. Complexes display Ru-II- and Ru-III-based metal-to-ligand and ligand-to-metal charge-transfer transitions, respectively, in the visible region and ligand-based transitions in the UV region. In spite of reasonably high K, values for [5]ClO4[8]ClO4, the expected intervalence charge-transfer transitions did not resolve in the tpical near-IR region up to 2000 nm. The paramagnetic (RuRuIII)-Ru-II species ([5]ClO4-[8]ClO4) displays rhombic electron paramagnetic resonance (EPR) spectra at 77 K (< g > similar to 2.15 and Delta g similar to 0.5), typical of a low-spin Ru-III ion in a distorted octahedral environment. The one-electron-reduced tptz complexes [RuII(tptz center dot-)(acac)(CH3CN)] (1) and [(acac)(2)Ru-III{mu-tptz-H+)(center dot 2-)}-Ru-II(acac)(CH3CN)] (5), however, show a free-radical-type EPR signal near g = 2.0 with partial metal contribution.

Adsorption of methanol on Si(100)/SiO(2)and mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Ravi, V.; Jacob, Nalini E.; Patil, K. R. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of methanol on SiO(100)/SiO2 substrate and mesoporous SBA-15 has been studied by using Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is employed to study the adsorption kinetics of methanol on SiO(100)/SiO2 and thermal stability of adlayer. Thermogravimetric (TGA) technique is used to understand the thermal behavior of methanol layer on SBA-15. Adsorption kinetics fit fairly well with Langmuir isotherms giving adsorption rate constant, k(a) = 0.0021 W s(-1). FTIR results show formation of methoxy silicon (SiOCHA silicon polyhydride (SiH2), carboxylate, molecular water and hydroxyl groups on Si(100)/SiO2 surface and only methoxy silicon on SBA-15. XPS results confirm methanol adsorption and support FTIR results. The methanol adlayers are found to be thermally stable up to a temperature of similar to 262 degrees C on both Si(100)/SiO2 and SBA-15 and decompose between 262 and 450 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; desorption; kinetics; Methanol; SBA-15; Si(100)/SiO2; thermal stability

Adsorption of octadecyltrichlorosilane on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Sawant, Dhanashri P.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B.; Pradhan, S. D. (Applied Surface Science, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on mesoporous SBA-15 has been studied by using Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermo-gravimetric analysis (TGA) techniques. BET surface area analysis shows decrease of surface area from 930 to 416 m(2)/g after OTS adsorption. SEM pictures show close attachment of SBA-15 particles. EDAX measurements show increase of carbon weight percentage and decrease of oxygen and silicon weight percentage. XPS results closely support EDAX analysis. FTIR spectra shows presence of methyl (-CH3) and methylene (-CH2) bands and oriented OTS monolayer on SBA-15. Thermo-gravimetric analysis shows that the OTS adsorbed on SBA-15 are stable up to a temperature of 230 degrees C and that the OTS monolayers decompose between 230 and 400 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; OTS; SBA-15; Self-assembly; thermal stability

Amino functionalized novel cholic acid derivatives induce HIV-1 replication and syncytia formation in T cells - Salunke, Deepak B.; Ravi, D. S.; Pore, V. S.; Mitra, Debashis; Hazra, Braja G. (Journal of Medicinal Chemistry, 2006)
Synthesis of C-11 azido/amino functionalized cholic acid derivatives has been achieved in excellent yields. Contrary to the previous prediction of analogous compounds to be HIV-1 protease inhibitors, in the present study these novel cholic acid derivatives induced host cell fusion during the progress of HIV-1 infection and produced multinucleated giant cells. This is the first report of syncytia induction and enhancement of viral replication in HIV-1 infected T cells by cholic acid derivatives.

Characterization of Cd1-xZnxSe thin films deposited at low temperature by chemical route - Hankare, P. P.; Chate, P. A.; Asabe, M. R.; Delekar, S. D.; Mulla, Imtiaz S.; Garadkar, K. M. (Journal of Materials Science-Materials in Electronics, 2006)
Optoelectronic technologically important pseudo-binary Cd1-xZnxSe thin films with a variable composition ( 0 < x < 1) has been developed by chemical bath deposition method. The objective to study growth kinetics, physical, microscopic, compositional, optical, electrical and structural changes. Cd1-xZnxSe have been deposited on non-conducting glass substrate in tartarate bath containing Cd+2 and Zn+2 ions with sodium selenosulphate with an aqueous alkaline medium at 278 K. The quality and the thickness of the films are depends upon deposition temperature, deposition time and pH, etc. X-ray diffraction (XRD), atomic absorption spectroscopy, optical absorption, scanning electron microscopy and thermoelectric technique characterized the films. The XRD study indicates the polycrystalline nature in single cubic phase over whole range of composition. Analysis of absorption spectra gave direct type band gap, the magnitude of which increases non-linearly as zinc content in the film is increased and dc electrical conductivity at room temperature was found to decreases from 10(-7) to 10(-8) (Omega cm)(-1). All the films show n-type conductivity. The promising features observed are the formation of continuous solid solutions in a single cubic phase.

Chemoselective anti-Markovnikov hydroamination of alpha,beta-ethylenic compounds with amines using montmorillonite clay - Joseph, Trissa; Shanbhag, G. V.; Sawant, D. P.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A-Chemical, 2006)
The catalytic activity of montmorillonite clays as a catalyst for the hydroamination of alpha,beta-ethylenic compounds with amines was tested. Aniline and substituted amines reacted with alpha,beta-ethylenic compounds in the presence of catalytic amount of commercially available clay to afford exclusively anti-Markovnikov adduct in excellent yields. Aniline reacted with ethyl acrylate to yield only anti-Markovnikov adduct N-[2-(ethoxycarbonyl)ethyl] aniline (mono-addition product). No Markovnikov adduct (N-[1-(ethoxycarbonyl)ethyl]aniline and double addition product N,N-bis[2-(ethoxycarbonyl)ethyl]aniline were formed under selected reaction conditions. For a better exploitation of the catalytic activity in terms of increased activity and improved selectivity for the mono-addition product, the reaction parameters were optimized in terms of temperature, solvent, reactant mole ratio. Under optimized reaction conditions, montmorillonite clay K-10 showed a superior catalytic performance in the hydroamination of ethyl acrylate with aniline with a conversion of aniline to mono-addition product (almost 100% chemoselectivity) with a high rate constant 0.3414 min(-1) compared to the reported protocols. The dependence of conversion of aniline over different types of montmorillonite clays (K-10, K-20, K-30, Al-Pillared clay and untreated clay) has also been discussed. The activities of clay for the hydroamination of different aromatic and aliphatic amines have also been investigated. Under harsh reaction conditions (increased temperature and long reaction time) small amounts of di-addition products were observed. The kinetics data has been interpreted using the initial rate approach model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alpha; amines; anti-Markovnikov addition product; beta-ethylenic compounds; chemo-selective; hydroamination; K-10 montmorillonite clay

Contrasting solid-state structures of trithiocyanuric acid and cyanuric acid - Guo, F.; Cheung, E. Y.; Harris, Kenneth D. M.; Pedireddi, V. R. (Crystal Growth & Design, 2006)
Although trithiocyanuric acid (TTCA) has been investigated widely as an agent in the formation of molecular cocrystals, the crystal structure of pure TTCA has never been determined. Attempts to grow crystals of pure TTCA by crystallization from solution invariably lead to the formation of solvate cocrystals, and desolvation of these materials leads to polycrystalline powder samples. In this paper, we report the structure determination of pure TTCA directly from powder X-ray diffraction data, using the direct-space genetic algorithm technique for structure solution followed by Rietveld refinement. The structure presents interesting contrasts to that of the oxygen analogue, cyanuric acid, and alludes to the possibility that both compounds might be capable of exhibiting polymorphism.

Control of stereoselectivity in 4-tert-butylphenol hydrogenation over a carbon-supported rhodium catalyst by carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Ebina, Takeo; Shirai, Masayuki (Chemistry Letters, 2006)
cis-4-tert-Butylcyclohexanol was obtained with a high cis ratio (cis/(cis + trans) = 0.9) in the hydrogenation of 4-tert-butylphenol over a carbon-supported rhodium catalyst along with hydrochloric acid in supercritical carbon dioxide solvent.

Cyanuric chloride: Trichloro-1,3,5-triazine - Haval, Kishan P. (Synlett, 2006)

Differentially expressed gene transcripts in roots of resistant and susceptible chickpea plant (Cicer arietinum L.) upon Fusarium oxysporum infection - Nimbalkar, Suhas B.; Harsulkar, Abhay M.; Giri, Ashok P.; Sainani, Mohini N.; Franceschi, Vincent R.; Gupta, Vidya S. (Physiological and Molecular Plant Pathology, 2006)
Differentially expressed genes in chickpea, (Cicer arietinum L.) during root infection by Fusarium oxysportan f sp. ciceri Racel, were identified using cDNA-RAPD and cDNA-AFLP approaches. The former employed decamer primers on cDNA template and revealed nine differentially expressed transcripts in the resistant-infected chickpea variety. Among the 2000 transcript-derived fragments (TDFs) screened by cDNA-AFLP, 273 were differentially expressed in chickpea roots during Fusaritan infection. Only 13.65% of the TDFs were differentially regulated during pathogen challenge, while the other 86% were expressed non-differentially during the process of pathogen infection in chickpea roots. Nineteen TDFs, which expressed differentially in the resistant-infected chickpea variety were cloned and sequenced. Two of these TDFs were similar to transcription factors like WRKY proteins and 14-3-3 proteins, while three TDFs represented the NBS-LRR-type gene sequences. Two TDFs had sequence identity to genes known to have function in defense. The RAPID TDF CaFRi60 showed sequence identity to gamma-glutamyl-cysteine synthetase. Among the TDFs examined by cDNA-AFLP, 19 were confirmed by Reverse Northern blot to be differentially expressed. The data confirms the effectiveness of the cDNA-AFLP technique in detecting differentially expressed genes during pathogenesis. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: cDNA-AFLP; Chickpea; Cicer arietinum; differentially expressed genes; fusarium oxysporum; Transcriptome

Effect of annealing on properties of ZrSe2 thin films - Hankare, P. P.; Asabe, M. R.; Kokate, A. V.; Delekar, S. D.; Sathe, D. J.; Mulla, Imtiaz S.; Chougule, B. K. (Journal of Crystal Growth, 2006)
Thin films of ZrSe2 have been prepared on stainless steel and fluorine-doped tin oxide-coated glass substrates using electrodeposition technique at potentiostatic mode. Double-distilled water containing precursors Zr and Se with ethylene diamine tetra-acetic acid disodium salt as a complexing agent was used to obtain good quality deposits by controlling the rate of reaction. The preparative parameters such as concentration of bath, deposition time, bath temperature, pH of the bath and annealing temperature have been optimized using photoelectrochernical (PEC) technique. The films deposited at optimum preparative parameters are annealed at different temperatures. The film annealed at 200 degrees C shows more photosensitivity. The as-deposited and annealed films at 200 degrees C have been characterized by X-ray diffraction (XRD), energy dispersive analysis by X-ray (EDAX), optical absorption and scanning electron microscopy (SEM). The XRD analysis of the as-deposited and annealed films showed the presence of polycrystalline nature with hexagonal crystal structure. EDAX study reveals that deposited films are almost stoichiometric. Optical absorption study shows the presence of direct transition and band gap energies are found to be 1.5 and 1.38 eV, respectively, for the as-deposited and annealed films. SEM study revels that the grains are uniformly distributed over the surface of substrate for the as-deposited as well as annealed film, which indicates formation of good and compact type of crystal structure. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: band gap; EDAX; Electrodeposition; PEC; SEM; XRD; ZrSe2 thin films

Effect of calcination temperature on the catalytic activity of zirconia-supported heteropoly acids - Devassy, Biju M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Zirconia-supported silicotungstic acid (15% STA) catalyst with different calcination temperatures (600-850 degrees C) was prepared by suspending zirconium oxyhydroxide in methanol solution of STA followed by drying and calcination. These catalysts were characterized by XRD, FTIR pyridine adsorption and DRUV-vis spectroscopy. The catalysts showed both Bronsted as well as Lewis acidity and 15% STA on zirconia calcined at 750 degrees C (15 SZ-750) had the highest Bronsted acidity. Characterization of 15 SZ-750 catalyst by Raman spectroscopy showed the presence of zirconia-anchored mono-oxotungstate as the major tungsten species present in this catalyst. These catalysts were used in benzoylation of veratrole with benzoic anhydride and 15 SZ-750 catalyst showed the highest activity. For catalyst with support calcined at different temperatures before HPA impregnation, catalytic activity decreases as the support calcination temperature increases due to the decrease in Bronsted acidity. Comparison of the catalytic activity of 15 SZ-750 with that of zirconia-supported phosphotungstic acid (15%, calcined at 750 degrees C, 15 PZ-750) in benzoylation of veratrole with benzoic anhydride, acylation of anisole with acetic anhydride and in alkylation of diphenylether with 1-dodecene showed that 15 SZ-750 catalyst has higher activity and deactivation resistance due to its higher Bronsted acidity. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Alkylation; Anisole; diphenylether; Phosphotungstic acid; Silicotungstic acid; veratrole; Zirconia

Effect of thermal annealing on Fe40Ni38B18Mo4 thin films: modified Herzer model for magnetic evolution - Hysen, T.; Deepa, S.; Saravanan, S.; Ramanujan, R. V.; Avasthi, D. K.; Joy, Pattayil Alias; D Kulkarni, S.; Anantharaman, Maliemadom R. (Journal of Physics D-Applied Physics, 2006)
Magnetic properties of nano-crystalline soft magnetic alloys have usually been correlated to structural evolution with heat treatment. However, literature reports pertaining to the study of nano-crystalline thin films are less abundant. Thin films of Fe40Ni38B18Mo4 were deposited on glass substrates under a high vacuum of approximate to 10(-6) Torr by employing resistive heating. They were annealed at various temperatures ranging from 373 to 773K based on differential scanning calorimetric studies carried out on the ribbons. The magnetic characteristics were investigated using vibrating sample magnetometry. Morphological characterizations were carried out using atomic force microscopy (AFM), and magnetic force microscopy (MFM) imaging is used to study the domain characteristics. The variation of magnetic properties with thermal annealing is also investigated. From AFM and MFM images it can be inferred that the crystallization temperature of the as-prepared films are lower than their bulk counterparts. Also there is a progressive evolution of coercivity up to 573 K, which is an indication of the lowering of nano-crystallization temperature in thin films. The variation of coercivity with the structural evolution of the thin films with annealing is discussed and a plausible explanation is provided using the modified random anisotropy model.

Haval-Argade contrathermodynamic rearrangement of alkylidenesuccinimides to alkylmaleimides via the corresponding isoimides: a general approach to alkyl and dialkyl substituted maleimides - Haval, Kishan P.; N. P. Argade (Tetrahedron, 2006)
A simple and efficient access to alkyl and dialkyl substituted maleimides has been demonstrated via the new contrathermodynamic rearrangement of (E)-alkylidenesuccinimides to alkylinaleimides. The (E)-alkylidenesuccinimides obtained from the Wittig-condensation of N-arylmaleimide with aliphatic aldehydes oil regioselective hydrolysis furnished the corresponding (E)-alkylidenesuccinanilic acids in 95-98% yields. The beta-alkylidenesuccinanilic acids oil treatment with cyanuric chloride in the presence of triethylamine gave the corresponding beta-alkylisomaleimides in 78-80% yields via the beta-alkylideneisosuccinimides with the exocyclic to endocyclic carbon-carbon double bond migration. The kinetically controlled products alkylisomaleimides in refluxing acetic acid furnished the thermodynamically controlled alkylinaleimides in 98% yield. The Wittig condensation of alkyl substituted isomaleimides/maleimides with aliphatic aldehydes gave the desired dialkyl substituted maleimides in high yields. A conversion of alpha-methylenesuccinanilic acids to alpha-methylisomaleimides has also been described, with 90% yield. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alkyl and dialkylmaleimides; contrathermodynamic rearrangement; isomaleimides; maleimides; wittig coupling

Heteropoly acid supported on titania as solid acid catalyst in alkylation of p-cresol with tert-butanol - Kumbar, Suresh M.; Shanbhag, G. V.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Butylation of p-cresol with tert-butanol was investigated on titania modified with 12-tungstophosphoric acid (TPA/TiO2) catalyst under vapor phase conditions. Catalysts with different TPA loadings (10-25 wt.%) and calcination temperatures (650-750 degrees C) were prepared by suspending titanium hydroxide in methanol solution of TPA followed by drying and calcination. These catalysts were characterized by surface area, XRD, P-31 MAS NMR, XPS, NH3-TPD, and FTIR pyridine adsorption. XRD results indicated that the presence of TPA retarded the crystallization of titania and stabilized TiO2 in anatase phase. P-31 MAS NMR indicated the presence of TPA in various forms (dispersed, highly fragmented and Keggin intact). These catalysts showed both Bronsted and Lewis acidity, and 20% TPA on TiO2 calcined at 700 degrees C (from here after words 20% TT 700) had the highest Bronsted as well as total acidity. Further, the catalytic activities were examined in tert-butylation of p-cresol with tent-butanol. The catalytic activity depended on TPA coverage, and the highest activity corresponded to the monolayer of TPA on titania. The most active catalyst 20% TT-700 gave 82% conversion of p-cresol and 89.5% selectivity towards 2-tert-butyl cresol (TBC), 2,6-di-tert-butyl cresol (DTBC) 7.5% and cresol-tert-butyl ether (CTBE) 3% under optimized conditions. The activity was always higher than that of WO3/ZrO2, sulfated zirconia (SZ), USY, H-beta zeolites and montmorillonite K-10 (K-10mont) under similar conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2; 2-tert-butyl-p-cresol; 6-di-tert-butyl-p-cresol; Alkylation; heteropoly acid; p-Cresol; tert-butanol; titania

High-throughput screening of RNA polymerase inhibitors using a fluorescent UTP analog - Bhat, Jyothi; Rane, Rajendra; Solapure, Suresh M.; Sarkar, Dhiman; Sharma, Umender; Harish, M. N.; Lamb, Sarah; Plant, Darren; Alcock, Peter; Peters, Steve; Barde, Shubhada; Roy, Raman K. (Journal of Biomolecular Screening, 2006)
RNA polymerase (RNAP) is a well-validated target for the development of antibacterial and antituberculosis agents. Because the purification of large quantities of native RNA polymerase from pathogenic mycobacteria is hazardous and cumbersome, the primary screening was carried out using Escherichia coli RNAP. The authors have developed a high-throughput screening (HTS) assay to screen for novel inhibitors of RNAP. In this assay, a fluorescent analog of UTP, gamma-amino naphthalene sulfonic acid (gamma-AmNS) UTP, was used as one of the nucleotide substrates. Incorporation of UMP in RNA results in the release of gamma-AmNS-PPi, which has higher intrinsic fluorescence than (gamma-AmNS) UTP. The assay was optimized in a 384-well format and used to screen 670,000 compounds at a concentration of 10 mu M. About 0.1% of the compounds showed more than 60% inhibition in the primary HTS. All the primary actives tested for dose response using the same assay had an EC50 below 100 mu M. Eighty percent of the primary HTS actives obtained using E. coli RNAP showed comparable activity against Mycobacterium smegmatis RNAP in the conventional radioactive assay. Activity of hits selected for the hit-to-lead optimization was also confirmed against Mycobacterium bovis RNAP which has > 99% sequence identity with Mycobacterium tuberculosis RNAP subunits.

Influence of extended pi-conjugation units on carrier mobilities in conducting polymers - Harima, Yutaka; Kim, D. H.; Tsutitori, Y.; Jiang, Xiaoqing; Patil, R.; Ooyama, Y.; Ohshita, J.; Kunai, A. (Chemical Physics Letters, 2006)
Carrier mobilities in thin films of copolymers with repeat units consisting of oligothiophenes bridged by Si atoms are measured over a range of doping levels, where the numbers of thienylenes in the repeat unit are 7, 8, 10, 12, and 14. The mobilities for these polymer films increased with the increase in doping level and the mobility enhancement followed an increasing order of the pi-conjugation length. The magnitude of the mobility increase for the Si polymer comprising 14 thiophene units reached ca. 10(4), implying that this pi-conjugation length is almost sufficient to reproduce transport properties of polythiophenes. (c) 2006 Elsevier B.V. All rights reserved.

Low temperature hydrogenation of tetralin over supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Shirai, Masayuki (Applied Catalysis A-General, 2006)
Hydrogenation of tetralin was studied over supported rhodium catalysts in supercritical carbon dioxide solvent at 333 K. The results were compared with those in an organic solvent and under neat conditions. Higher cis-decalin yield was obtained in supercritical carbon dioxide solvent than under non-supercritical conditions. It was observed that higher hydrogen concentration at the surface in supercritical carbon dioxide solvent led to fast direct hydrogenation of tetralin to cis-decalin; the flipping of the intermediate, octalin, to give trans-decalin could be prevented. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cis-decalin; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide; supported rhodium catalysts; tetralin

Mesoporous molecular sieve (MCM-41)-filled sodium alginate hybrid nanocomposite membranes for pervaporation separation of water-isopropanol mixtures - Bhat, S. D.; Naidu, B. V. K.; Shanbhag, G.; Halligudi, Shivaraj B.; Sairam, M.; Aminabhavi, Tejraj M. (Separation of Purification Technology, 2006)
Sodium alginate (NaAlg) and the inesoporous molecular sieve (MCM-41)-filled NaAlg nanocomposite membranes have been prepared by solution casting and crosslinked with glutaraldehyde. Pervaporation performance of the MCM-41-filled NaAlg membranes has been tested and compared with plain NaAlg membrane for dehydrating isopropanol at 30 degrees C. In the studied feed composition range of 10-50 mass% of water, 20 mass% MCM-41-loaded NaAlg membrane gave the highest selectivity ranging between 29,991 and 3332 in the range of feed water compositions of 10-50 mass%. Flux for the plain NaAlg membrane ranged between 0.067 and 0.340 kg/(m(2)h), while for 20 mass% MCM-41-filled NaAlg membrane, flux increased to 0.110 and 0.555 kg/(m(2)h). To the best of our knowledge, this is the first study reported on the membrane forming properties of an admixed hybrid composite of a mesoporous molecular sieve (MCM-41) with NaAlg used in dehydration of isopropanol, yielding high selectivity to water at higher loadings of the molecular sieve as a filler. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: flux and selectivity; nanocomposite membranes; pervaporation; sodium alginate; water-isopropanol

Novel chemical synthetic route and characterization of zinc selenide thin films - Hankare, P. P.; Chate, P. A.; Delekar, S. D.; Asabe, M. R.; Mulla, Imtiaz S. (Journal of Physics and Chemistry of Solid, 2006)
Zinc selenide (ZnSe) thin film have been deposited using chemical bath method on non-conducting glass substrate in a tartarate bath containing zinc sulfate, ammonia, hydrazine hydrate, sodium selenosulfate in an aqueous alkaline medium at 333 K. The deposition parameter of the ZnSe thin film is interpreted in the present investigation. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), optical absorption, electrical measurements, atomic absorption spectroscopy (AAS). The ZnSe thin layers grown with polycrystalline zinc blende system along with some amorphous phase present in ZnSe film. The direct optical band gap `E-g' for the film was found to be 2.81 eV and electrical conductivity in the order of 10(-8)(Omega cm)(-1) with n-type conduction mechanism. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: chalcogenides; electronic materials

Novel series of oligomers from 4-aminomethyl-tetrahydrofuran-2-carboxylates with 2,4-cis and 2,4-trans stereochemistry - Edwards, Alison A.; Sanjayan, Gangadharar J.; Hachisu, Shuji; Tranter, George E.; Fleet, George W. J. (Tetrahedron, 2006)
Two tetrahydrofuran-based y-amino acids [2,4-cis and 2,4-trans] were subjected to iterative peptide-coupling procedures to afford dimeric, tetrameric and hexameric carbopeptoids in good yield. These homooligomers were prepared for secondary structural study-to ascertain the conformational preference inherent in the monomer units. The L-xylo oligomers were protected with triethylsilyl ethers to increase the range of solvents suitable for structural investigation. Initial secondary structure data indicate the presence of hydrogen-bonded conformations in the L-ribo series. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Foldamers; gamma amino acids; Peptidomimetics; sugar amino acids

Phenol tert-butylation over zirconia-supported 12-molybdophosphoric acid catalyst - Devassy, Biju M.; Shanbhag, G.V.; Halligudi, S.B. (Journal of Molecular Catalysis A-Chemical, 2006)
The alkylation of phenol with tert-butanol was investigated using zirconia-supported 12-molybdophosphoric acid (MPA) as catalyst. The catalysts with different MPA loading (5-25 wt.% calcined at 700 degrees C) and calcination temperature (15 wt.% calcined from 500 to 750 degrees C) were prepared by suspending zirconium oxyhydroxide in methanol solution of MPA followed by drying and calcination. These catalysts were characterized by X-ray diffraction and (31)p MAS NMR spectroscopy measurements. The XRD results indicated that MPA stabilizes the tetragonal phase of zirconia. (31)p MAS NMR spectra showed the presence of three types of phosphorous species, phosphomolybdate in interaction with zirconia, decomposition product of MFPA and an unidentified species. IFTIR pyridine adsorption on 15% MPA catalyst calcined at different temperatures showed the presence of both Bronsted and Lewis acidity and the catalyst calcined at 700 degrees C showed the highest relative Bronsted acidity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), the phenol conversion was 80.6% at 2 h (selectivity to 2-TBP 11.5%, 2,4-DTBP 55.2%, and 4-TBP 25.7%), which decreased slowly with time and at 31 h, it was 58.5% (selectivity to 2-TBP 15.2%, 2,4-DTBP 41.6%, and 4-TBP 38.4%). The major reason for the catalyst deactivation was the reduction and leaching of MPA from the catalyst surface. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 12-molybdophosphoric acid; phenol; tert-butylation; Zirconia

Photocatalytic degradation of organic contaminants in water by ZnO nanoparticles: revisited - Hariharan, C. (Applied Catalysis A-General, 2006)
Nanoscale photocatalysts have attracted much attention due to their high surface area to volume ratios. This work investigates the photodegradation of organic contaminants using the fluorescence emission characteristics of ZnO nanoparticles (ZnO-nano) in aqueous solutions. This is accomplished by preparing nanocrystalline ZnO; the presence of organic contaminants in water is readily detected from the quenching of fluorescence observed from ZnO semiconductor films. Photolysis of ZnO thin films immersed into an aqueous system containing organic contaminants results in the degradation of the contaminants. A comprehensive study has been done involving several organic contaminants in water (like aliphatic and aromatic chloro compounds as well as some commonly used aromatic solvents) to check the suitability of ZnO-nano as an efficient photocatalyst. The ZnO nanoparticles not only serve as a better catalytic system compared to bulk ZnO and commercially available Degussa TiO2 in achieving degradation of the added contaminants, but unlike other semiconductor systems can also act as a non-specific sensor for the presence of these common contaminants in water. A total cleanup of a cocktail of contaminants in water was also achieved using the ZnO-nano. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Nanoparticles; organic contaminants and photocatalysis; Semiconductor; ZnO

Photoelectrochemical properties of electrochemically deposited CdIn2S4 thin films - Kokate, A. V.; Asabe, M. R.; Delekar, S. D.; Gavali, L. V.; Mulla, Imtiaz S.; Hankare, P. P.; Chougule, B. K. (Journal of Physics and Chemistry of Solids, 2006)
Thin films of CdIn2S4 have been deposited on to stainless steel and fluorine-doped tin oxide (FTO)-coated glass substrates from aqueous acidic bath using an electrodeposition technique. Ethylene diamine tetra-acetic acid (EDTA) disodium salt is used as complexing agent to obtain good-quality deposits by controlling the rate of the reaction. The different preparative parameters like concentration of bath, deposition time, bath temperature, pH of the bath have been optimized by the photoelectrochemical (PEC) technique in order to get good-quality photosensitive material. Different techniques have been used to characterize CdIn2S4 thin films. Optical absorption shows the presence of direct transition with band gap energy 2.17 eV. The X-ray diffraction (XRD) analysis of the as-deposited and annealed films showed the presence of polycrystalline nature. Energy-dispersive analysis by X-ray (EDAX) study for the sample deposited at optimized preparative parameters shows that the In-to-Cd ratio is almost 2 and S-to-Cd ratio is almost 4. Scanning electron microscopy (SEM) for samples deposited at optimized preparative parameters reveals that spherical grains are uniformly distributed over the surface of the substrate indicates the well-defined growth of polycrystalline CdIn2S4 thin film. PEC characterization of the films is carried out by studying photoresponse, spectral response and photovoltaic output characteristics. The fill factor (ff) and power conversion efficiency (eta) of the cell are 69 and 2.94%, respectively. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Thin films; X-ray diffraction

Propargyl glycosides as stable glycosyl donors: anomeric activation and glycoside syntheses - Hotha, Srinivas; Kashyap, Sudhir (Journal of the American Chemical Society, 2006)

Ring hydrogenation of naphthalene and 1-naphthol over supported metal catalysts in supercritical carbon dioxide solvent - Shirai, M.; Rode, C. V.; Mine, Eiichi; Sasaki, A.; Sato, O.; Hiyoshi, Norihito (Catalysis Today, 2006)
Catalytic ring hydrogenations of naphthalene and 1-naphthol were studied over several supported metal catalysts in supercritical carbon dioxide solvent at low temperature. Higher concentration of hydrogen in supercritical carbon dioxide and lower reaction temperature were responsible for higher catalyst activity and selectivities to the desired partial ring hydrogenated products as compared with those observed in organic solvent for the same catalyst. (c) 2006 Elsevier B.V. All rights reserved.
8th International Conference on Carbon Dioxide Utilization, Univ Oslo, Oslo, NORWAY, JUN 20-23, 2005
Keywords: 1-naphthol; Hydrogenation; Naphthalene; Supercritical carbon dioxide; supported metal catalyst

Selective hydrogenation of naphthols to tetralones over supported palladium catalysts in supercritical carbon dioxide solvent - Mine, Eiichi; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2006)
Naphthols were selectively hydrogenated to the corresponding tetralones over supported palladium metal catalysts in super-critical carbon dioxide solvent.

Shape selective synthesis of long-chain linear alkyl benzene (LAB) with AIMCM-41/beta zeolite composite catalyst - Bordoloi, Ankur; Devassy, Biju M.; Niphadkar, P. S.; Joshi, P. N.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
The liquid-phase alkylation of benzene with long-chain olefins such as 1-decene, 1-octene and 1-dodecene was carried out over AIMCM-41/Beta zeolite composite material as catalyst. The catalyst was prepared by seeding method and characterized by XRD, N-2 sorption, FTIR pyridine adsorption, NH3-TPD and SEM. Powder XRD of AlMCM-41/Beta zeolite composite material showed the co-existence of well-structured microporous and mesophase of AlMCM-41. The typical textural characteristics of micro- and meso-structured phases were observed in the composite material. The effect of temperature, reactant molar ratios and catalyst weight on 1-dodecene conversion and products selectivity was studied. The composite catalyst was found to be the highly selective towards the formation 2-dodecylbenzene. Under the reaction conditions of 120 degrees C, benzene/1-dodecene molar ratio 10 and time 2h, the catalyst gave 48% dodecene conversion with 76%, 2-dodecylbenzene selectivity. Significant improvement in catalytic activity has been achieved by composite material as compared to Al-MCM-41. Although zeolite beta and composite material gave similar conversion of dodecene, the composite material showed higher selectivity towards 2-dodecylbenzene, which could be due to higher diffusibility of 2-dodecylbenzene isomer in the composite material. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AIMCM-41/beta zeolite composite; Alkylation; Benzene; long-chain olefins

Stereoselective syntheses of unnatural steroidal C(20R) aldehydes by ionic hydrogenation of C-20 tertiary alcohols - Shingate, Bapurao B.; Hazra, Braja G.; Pore, Vandana S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron Letters, 2006)
Syntheses of three unnatural steroidal C(20R) aldehydes have been realised from 16-dehydropregnenol one acetate. The salient feature of the synthesis is the ionic hydrogenation of C-20 tertiary alcohols leading to the formation of the C(20R) unnatural isomer with complete stereoselectivity. Oxidative hydrolysis of the dithiane moiety furnished the C(20R) aldehydes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-dithiane; ionic hydrogenation; oxidative hydrolysis; stereoselective synthesis; unnatural C-20 aldehydes

Synthesis and characterization of novel hydrophobically end-capped poly(ethylene oxide)s [PEOs] - Badiger, Manohar V.; Kadam, Vijay S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique (Macromolecular Symposia, 2006)
We report on the synthesis and characterization of a novel hydrophobically modified end-capped poly(ethylene oxide)s. The end-capping agent of this polymer was designed and synthesised from a renewable resource material namely, gallic acid (i.e. 3,4,5-trihydroxybenzoic acid), the byproduct of tannin industry. The hydroxyl groups at 3, 4 and 5 positions of gallic acid provide an opportunity for varying the hydrophobicity of the compound. The hydrophobic end-capping compound, 3,4,5tridodecyloxy bezoylazide was prepared from gallic acid and PEGS with different chain lengths (of number average molecular weights, 10000 and 35000 g/mol) were endcapped. using 3,4,5-tridodecyloxybenzoyl azide. The quantitative analysis of end-capping in the polymers was demonstrated by H-1-NMR spectroscopy and the rheological studies were carried out in the surfactant solutions.
Indo-French Symposium on Fibrillar Networks as Advanced Materials, Inst Charles Sadron, Strasbourg, FRANCE, SEP 21-23, 2005
Keywords: end-capped PEOs; hydrophobically modified polymers; water-soluble polymers

Synthesis, characterization, and molecular modeling studies of novel polyurethanes based on 2,2 '-[ethane-1,2-diylbis(nitrilomethylylidene)]diphenol and 2,2 '-[hexane-1,6-diylbis(nitrilomethylylidene)]diphenol hard segments - Raghu, A. V.; Gadaginamath, G. S.; Jawalkar, S. S.; Halligudi, Shivaraj B.; Aminabhavi, T. A. (Journal of Polymer Science Part A-Polymer Chemistry, 2006)
Novel polyurethanes (PUS) based on 2,2 `-[ethane-1,2-diylbis(nitrilomethylylidene)]diphenol and 2,2 `-[hexane-1,6-diylbis(nitrilomethylylidene)]diphenol as hard segments containing four aromatic diisocyanates (4,4 `-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) have been prepared. Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1 NMR and C-13 NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis have been used to determine the structural characterization and thermal properties of the segmented PUS. All the PUS contain domains of both semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties have been calculated with the group contribution method. Molecular dynamics simulations have been performed on all the PUS to estimate the cohesive energy density and solubility parameter values, which compare well with the values calculated with the group contribution method. Furthermore, the simulation protocols have been applied to the PUS to produce X-ray diffraction plots to determine the phase morphology of the PUS. The surface properties of the PUS have been estimated from the simulation protocols. (c) 2006 Wiley Periodicals, Inc.
Keywords: amorphous; hard segments; molecular dynamics; Morphology; polyurethanes; Schiff base containing polymers; Thermal properties

Synthesis of 4-aminomethyl-tetrahydrofuran-2-carboxylates with 2,4-cis and 2,4-trans relationships - Edwards, Alison A.; Sanjayan, Gangadhar J.; Hachisu, Shuji; Soengas, Raquel; Stewart, Alistair; Tranter, George E.; Fleet, George W. J. (Tetrahedron, 2006)
Templated tetrahydrofuran-based gamma-azido esters were prepared with the C-2 and C-4 functionalities in cis and trans relative configurations. This was achieved by ring contraction of the suitably protected 2-O-triflates of pentono-1,5-lactones (D-ribose and L-arabinose) with subsequent introduction of the azide via the 4-O-triflate. Access to a corresponding beta-azido ester was achieved in good yield. Little elimination product was observed by introduction of the azide via the 3-O-triflate. These azido esters are scaffolds. which may be predisposed to adopt secondary structural motifs, for example. for use as peptidomimetics; they may also be utilised for the preparation of stereodiverse compound libraries. (c) 2006 Elsevier Ltd All rights reserved.
Keywords: gamma amino acids; Peptidomimetics; scaffolds; sugar amino acids

Synthesis of cadmium selenide thin films at low-temperature by simple chemical route and their characterization - Hankare, P. P.; Delekar, S. D.; Asabe, M. R.; Chate, P. A.; Bhuse, V. M.; Khomane, A. S.; Garadkar, K. M.; Sarwade, B. D. (Journal of Physics and Chemistry of Solids, 2006)
Crystalline CdSe thin film has been deposited using appropriate precursor solution containing cadmium sulfate octahydrate, tartaric acid, potassium hydroxide, ammonia and sodium selenosulfate. The effect of parameters such as bath composition, deposition temperature, pH of the solution, speed of the rotation and the specificity of complexing agent on growth process is studied. The `as-deposited' CdSe thin film was found to be red in color, specularly reflective and well adherent to the glass substrate. The crystalline phase of the deposited sample was hexagonal wurtzite-type. The analysis of optical absorption data shows energy band gap energy (E-g) 2.01 eV. The morphological study and compositional analysis of film sample have been discussed. The electrical resistivity of CdSe thin film was found to the order of 10(6) Omega cm. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: XRD

Synthesis of spiroannulated dihydroisobenzofuranylated monosaccharides - Maurya, S. K.; Hotha, Srinivas (Tetrahedron Letters, 2006)
An efficient synthesis of spiroannulated dihydroisobenzofurans is achieved using easily accessible carbohydrate-derived furanyl propargyl ethers via an AuCl3 promoted intramolecular Diels-Alder (IMDA) reaction. The scope of the spiroannulation protocol was demonstrated using a diverse range of pentofuranosyl, hexofuransoyl and hexopyranosyl derived substrates in order to synthesize spiroannulated dihydroisobenzofurans. The reaction is high yielding, moisture tolerant, fast and uses only a catalytic amount of AuCl3. (c) 2006 Elsevier Ltd. All rights reserved.

Well-defined poly(4-vinylbenzocyclobutene): synthesis by living anionic polymerization and characterization - Sakellariou, G.; Baskaran, D.; Hadjichristidis, Nikos; Mays, Jimmy W. (Macromolecules, 2006)
Living anionic polymerization of 4-vinylbenzocylobutene was performed in benzene at room temperature using sec-butyllithium as the initiator. Results of the kinetic studies indicated the termination- and transfer-free nature of the polymerization. Homopolymers with predictable molecular weights and narrow molecular weight distributions were produced, excluding the interference of the cyclobutene rings during initiation and propagation. Thermogravimetric analysis of poly( 4-vinylbenzocyclobutene) in air showed a small weight gain at similar to 200 degrees C, a rapid decomposition at similar to 455 degrees C, and a gradual decomposition at similar to 566 degrees C. This behavior was attributed to the formation of radicals from the pendent benzocyclobutene functionality through o-quinodimethane intermediates and simultaneous decomposition/ cross-linking reactions at high temperature. The living nature of the polymerization was also examined via sequential copolymerization with butadiene to form diblock copolymers.

Adsorption of methanol on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B. (Materials Letter, 2007)
The adsorption of methanol onmesoporous SBA-15 has been studiedbyrising Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray photoclectrom spectroscopy (XPS) and tbennogravimettic analysis (TGA). The BET surface area analysis shows decreases of the surface area from 387 to 383 m(2)/g, pore volume from 0.88 to 0.81 cm(3)/g and pore diameter from 9.07 to 8.4 mm after methanol adsorption. The appearance of strong IR bands at 2862 and 2964cm(-1) due to methyl (-CH3) symmetric and asymmetric stretching demonstrate the presence of methanol and evidence of successful methanol adsorption. XPS results show increase of carbon and oxygen content on the surface of SBA-15. Thermogravirriettic analysis shows that the methanol adsorbed on SBA-15 is stable up to a temperature of 265 degrees C and that the methanol adlayers decompose between 265 and 588 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Electron microscopy; Methanol; SBA-15; Surfaces; thermal stability

Analysis of mitochondrial DNA sequences in childhood encephalomyopathies reveals new disease-associated variants - Wani, Aijaz A.; Ahanger, Sajad H.; Bapat, Sharmila A.; Rangrez, Ashraf Y.; Hingankar, Nitin; Suresh, C. G.; Barnabas, Shama; Patole, Milind S.; Shouche, Yogesh S. (Plos One, 2007)
Background. Mitochondrial encephalomyopathies are a heterogeneous group of clinical disorders generally caused due to mutations in either mitochondrial DNA (mtDNA) or nuclear genes encoding oxidative phosphorylation (OXPHOS). We analyzed the mtDNA sequences from a group of 23 pediatric patients with clinical and morphological features of mitochondrial encephalopathies and tried to establish a relationship of identified variants with the disease. Methodology/Principle Findings. Complete mitochondrial genomes were amplified by PCR and sequenced by automated DNA sequencing. Sequencing data was analyzed by SeqScape software and also confirmed by BLASTn program. Nucleotide sequences were compared with the revised Cambridge reference sequence (CRS) and sequences present in mitochondrial databases. The data obtained shows that a number of known and novel mtDNA variants were associated with the disease. Most of the non-synonymous variants were heteroplasmic (A4136G, A9194G and T11916A) suggesting their possibility of being pathogenic in nature. Some of the missense variants although homoplasmic were showing changes in highly conserved amino acids (T3394C, T3866C, and G9804A) and were previously identified with diseased conditions. Similarly, two other variants found in tRNA genes (G5783A and C8309T) could alter the secondary structure of Cys-tRNA and Lys-tRNA. Most of the variants occurred in single cases; however, a few occurred in more than one case (e. g. G5783A and A10149T). Conclusions and Significance. The mtDNA variants identified in this study could be the possible cause of mitochondrial encephalomyopathies with childhood onset in the patient group. Our study further strengthens the pathogenic score of known variants previously reported as provisionally pathogenic in mitochondrial diseases. The novel variants found in the present study can be potential candidates for further investigations to establish the relationship between their incidence and role in expressing the disease phenotype. This study will be useful in genetic diagnosis and counseling of mitochondrial diseases in India as well as worldwide.

Au-Pt nanoparticles in amine functionalized MCM-41: catalytic evaluation in hydrogenation reactions - Joseph, Trissa; Kumar, K. Vijay; Ramaswamy, A. V.; Halligudi, Shivaraj B. (Catalysis Communications, 2007)
Nano-sized Au-Pt nanoparticles (Au-Pt-bi-MNPs) have been synthesized by the simultaneous reduction of HAuCl4 and HPtCl6 by NaBH4 inside the channels of amine functionalized Si-MCM-41 (NH2-Si-MCM-41) at ambient conditions. These materials were characterized using chemical analysis, UV-vis, XPS, XRD, FT-IR, Surface area and TEM analysis. The size of these alloyed nanoparticles (bi-MNPs) were found in the range of 2-4 nm. These nanoparticles were evaluated to study their catalytic activities towards hydrogenation of aromatic nitro compounds. The catalytic activity of the Au-Pt bi-MNPs was found to be superior to monometallic An nanoparticles. (c) 2006 Published by Elsevier B.V.
Keywords: amine-functionalized MCM-41; Au-Pt nanoparticles; Catalytic hydrogenation

Catalytic performances of silicotungstic acid/zirconia supported SBA-15 in an esterification of benzyl alcohol with acetic acid - Sawant, Dhanashri P.; Vinu, A.; Justus, Josena; Srinivasu, P.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Liquid phase esterification of benzyl alcohol (BA) to benzyl acetate (Peach fragrance) with an acetic acid (AA) has been investigated with 12-silicotungstic acid supported on zirconia embedded inside SBA-15 (STA/ZrO2/SBA- 15) as the catalyst. Catalysts were unambiguously characterized by XRD, N-2 adsorption-desorption, FF-IR pyridine adsorption techniques and the total amount of acidity of different STA loaded catalysts was estimated by TPD of NH3. The optimization of reaction conditions of an esterification of BA with AA was performed with 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K by varying catalyst concentration (1-10 wt.% of reaction mixture); temperature, 353-383 K and AA:BA molar ratio as 0.5-3. The 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K was found to have the highest acidity and more active in the reaction. Under the optimized reaction conditions, the 15 wt.% STA/22.4 wt.%ZrO2/SBA-15 calcined at 1123 K gave 59% BA conversion with selectivity for benzyl acetate as high as 96% within 2 h of reaction time. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: 12-silicotungstic acid; Benzyl acetate; Benzyl alcohol; Esterification; SBA-15

Characterization of nano-sized CdS-Ag2S core-shell nanoparticles using XPS technique - Hota, G.; Idage, Susheela B.; Khilar, Kartic C. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2007)
This paper reports the use of X-ray photoelectron spectroscopy (XPS) method for the characterization of surface composition of core and shell nanoparticles. The core and shell nanoparticles were synthesized using sodium bis(2-ethylhexyl) sulfosuccinate (AOT)/n-heptane/water microemulsion technique. The post-core and partial microemulsion methods have shown promise for core and shell formation and enhanced stability and sphericity of the semiconductor nanoparticles. In addition to above technique, the core-shell nanoparticles have also been characterized using SEM-elemental detection X-ray analysis (EDAX) and results are discussed. The XPS studies of US, Ag2S, and CdS-Ag2S nanoparticles prepared by post-core/partial microemulsion methods were carried out and results are compared with physical mixing of US and Ag2S nanoparticles. The Ag/Cd atomic ratio is found to be 5 and 10 as determined by XPS methods for nanoparticles prepared by using post-core and partial microemulsion methods, respectively. These results show the formation of core and shell nanoparticles. (c) 2006 Elsevier B.V. All rights reserved.

Controlled aggregation of gold nanoparticle networks induced by alkali metal ions - Tamang, Sudarsan; Hotha, Srinivas; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2007)
Gold nanoparticle networks were obtained by linking them with cysteine modified triethyleneglycols. The oligo-ether linker molecule initially having a linear structure probably adopts a crown ether type structure upon complexation with alkali metal ions that leads to a controlled aggregation of the network. The extent of aggregation depends on the degree of conformational change in the molecule upon complexation with the metal ion, which in turn is governed by the metal ion radius leading to a dependence of red shift of the surface plasmon resonance on the metal ion radius. Since this network is present in the organic solvent they also act as phase transferring agent for the alkali metal ions from aqueous to organic media.
Keywords: Aggregation; Alkali Metal Ions; Au Nanoparticles; Crown Ether; Surface Plasmon Resonance

Controlled covalent functionalization of multiwalled carbon nanotubes using [4+2] cycloaddition of benzocyclobutenes - Sakellariou, Georgios; Ji, Haining; Mays, Jimmy W.; Hadjichristidis, Nikos; Baskaran, Durairaj (Chemistry of Materials, 2007)

Copper phthalocyanine films deposited by liquid-liquid interface recrystallization technique (LLIRCT) - Patil, K. R.; Sathaye, S. D.; Hawaldar, Ranjit R.; Sathe, B. R.; Mandale, A. B.; Mitra, A. (Journal of Colloid and Interface Science, 2007)
The simple recrystallization process is innovatively used to obtain the nanoparticles of copper phthalocyanine by a simple method. Liquid-liquid interface recrystallization technique (LLIRCT) has been employed successfully to produce small sized copper phthalocyanine nanoparticles with diameter between 3-5 nm. The TEM-SAED studies revealed the formation of 3-5 nm sized with beta-phase dominated mixture of alpha and beta copper phthalocyanine nanoparticles. The XRD, SEM, and the UV-vis studies were further carried out to confirm the formation of copper phthalocyanine thin films. The cyclic voltametry (CV) studies conclude that redox reaction is totally reversible one electron transfer process. The process is attributed to Cu(II)/Cu(I) redox reaction. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: Copper phthalocyanine; cyclic voltametry; nanoparticulate films

Copper(II) ion exchanged A1SBA-15: a versatile catalyst for intermolecular hydroamination of terminal alkynes with aromatic amines - Shanbhag, Ganapati V.; Joseph, Trissa; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
The hydroarnination reaction offers a very attractive route for the synthesis of alkylated amines and their derivatives with no byproduct formation. AISBA-15 was synthesized by isomorphous substitution of aluminum into the framework of SBA-15, which induces the Bronsted acid sites, and these were exchanged with metal ions such as Cu2+, Zn2+, and Pd2+. The catalysts were characterized by XRD, N-2-sOrption, SEM, TEM, acidity measurements by FT-IR pyridine adsorption, H-2-TPR, (27)AI MAS NMR, and Si-29 MAS NMR. Hydroamination of phenylacetylene (PhAc) with 2,4-xylidine has been used as a test reaction, which gave N-(1-phenylethylidene)-2,4-dimethylaniline with no byproduct formation. CuAlSBA-15 and CuAIMCM-41 showed around three times greater activity in hydroamination of PhAc compared with Cu-clay and Cu-beta, due to the moderate Lewis acidity of Cu2+ present in mesoporous supports. The performance of the CuAlSBA-15 was also determined with different alkynes and amines to evaluate the catalyst's general applicability in hydroamination reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: A1SBA-15; addition; alkyne; Amine; Copper catalyst; heterogeneous; hydroamination; ion exchange; Mesoporous

Correlation between mobility enhancement and conformational change in polyaniline and its derivatives: polaron lattice formation - Harima, Yutaka; Ogawa, Fumiyuki; Patil, Rahul; Jiang, Xiaoqing (Electrochimica Acta, 2007)
Conformational changes in polyaniline, poly(methyl aniline), and poly(methoxyaniline) are studied in perchloric acid and acetonitrile by means of an in situ reflection technique with oxidation level as a parameter. Stretching of polymer chains leading to enhancement of specular reflection at the polymer-coated electrodes is found to be well correlated with the increase in carrier mobility. The concomitant change in mobility and chain conformation observed with the polyaniline family is explained in terms of the formation of polaron lattice at increased oxidation levels. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Conformation; polyaniline; reflection; scattering : mobility

Development of transdermal drug-delivery films with castor-oil-based polyurethanes - Shelke, Namdev B.; Sairam, Malladi; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
Two different types of polyurethanes (PUs) were prepared with castor oil, ethylene glycol, isophorene diisocyanate and castor oil, and isophoren diisocyanate and poly(ethylene glycol) (400 or 600). PU films were prepared and characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, and gel permeation chromatography. We prepared transdermal patches by loading different amounts of drug, plasticizer, and penetration enhancer. In vitro drug permeability through the castor-oil-based aliphatic PU patches was examined with a Keshary-Chien diffusion cell. The effect of castor oil on the film-forming properties and the effect of penetration enhancers on diffusion characteristics of indomethacin (IDM) drug through the castor-oil-based PU were investigated. Prolonged release of IDM was observed from the prepared PU patches. In vitro drug diffusion revealed that slow and prolonged release of IDM was achieved in the absence of penetration enhancers. The use of penetration enhancers showed a significant effect on drug diffusion. (c) 2006 Wiley Periodicals, Inc.
Keywords: castor oil; drug delivery; polyurethane; transdermal

Effect of pretreatment conditions on the catalytic activity of nano-sized TPA/ZrO2 dispersed in SBA-15 channels in acetylation reactions - Sawant, Dhanashri P.; Hartmann, Martin; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2007)
Acetylation of an aromatic compounds such as veratrole (1,2-dimethoxybenzene), anisole, thioanisole, isobutyl benzene and 2-methoxynaphthalene with acetic anhydride has been investigated over a nano-sized 12-tungstophosphoric acid (TPA)/22.4 wt.%ZrO2/SBA- 15 catalysts in the liquid phase conditions. Catalysts with different (%) TPA and zirconia loadings calcined at different temperatures were prepared by wet-impregnation and characterized by XRD, N-2 adsorption-desorption, FT-Rarnan, X-ray photoelectron spectroscopy (XPS). The acidic behavior of the catalyst was studied by TPD of ammonia and FT-IR pyridine adsorption. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/SBA- 15 calcined at 1123 K had the highest acidity and was the most active catalyst in veratrole acetylation with acetic anhydride. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: acetylation; SBA-15; TPA/ZrO2; veratrole; wet-impregnation

Electronic structure of spherical quantum dots using coupled cluster method - Heidari, Ideh; Pal, Sourav; Pujari, B. S.; Kanhere, Dilip G. (Journal of Chemical Physics, 2007)
2, 6, 12, and 20 electron quantum dots have been studied using coupled cluster at singles and doubles level and extensive multireference coupled cluster (MRCC) method. A Fock-space version of MRCC (FSMRCC) containing single hole-particle excited determinants has been used to calculate low-lying excited states of the above system. The ionization potential and electron affinity are also calculated. The effect of correlation energy on excitation energy and charge density is shown by calculating them at the high density region (low value of density parameter r(s)) and at the low density region (high value of density parameter r(s)). (c) 2007 American Institute of Physics.

Enforcing periodic secondary structures in hybrid peptides: a novel hybrid foldamer containing periodic gamma-turn motifs - Baruah, Pranjal K.; Sreedevi, N. K.; Gonnade, Rajesh G.; Ravindranathan, Sapna; Damodaran, Krishnan; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2007)
{This note describes the design, synthesis, and conformational studies of a novel hybrid foldamer that adopts a definite compact, three-dimensional structure determined by a combined effect of the special conformational properties of the foldamer constituents. The striking feature of this de novo designed foldamer is its ability to display periodic gamma-turn conformations stabilized by intramolecular hydrogen bonds. Conformational investigations by single-crystal X-ray studies, solution-state NMR, and ab initio MO theory at the HF/6-31G*
Keywords: ammonia-TPD; benzylation reaction; Ce-Al-MCM-41; Friedel-Crafts alkylation; pyridine-FrIR

Highly photostable dye entrapped core-shell particles - Ethiraj, Anita S.; Kharrazi, Sharmin; Hebalkar, Neha; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Materials Letters, 2007)
Organic dye namely Coumarin 7 has been entrapped in silica particles using a single silica precursor viz. tetraethylorthosilicate. Both bare Coumarin 7 dye and dye incorporated core-shell particles were studied. Investigations of these core-shell composites were carried out using different characterization techniques such as energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy. It has been shown that the photostability of dye molecules is improved along with an increase in photoluminescence. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: core-shell; coumarin 7 dye; Luminescence; photostability; tetraethylorthosilicate

Influence of film structure on mobilities of charge carriers in conducting polymers - Harima, Yutaka; Jiang, Xiaoqing; Patil, Rahul; Komaguchi, Kenji; Mizota, Haruo (Electrochimica Acta, 2007)
Two sorts of poly(3-hexylthiophene) (PHT) films with the same chemical compositions were prepared, and their electrochemical, spectroscopic, and transport properties were studied with a special interest in a possible influence of film structure on mobilities of charge carriers. One of the PHT films was electrochemically synthesized using 3-hexylthiophene as a monomer (as-grown film) and the other was obtained by dissolving the as-grown film in chloroform and then casting the polymer solution (cast film). A clear difference was observed in the mobility versus doping level plot between the two sorts of PHT films, demonstrating that the difference is caused only by a distinction in film structure. An initial decreasing feature of the mobility plot observed for the cast films was accounted for in terms of swelling of the films at an early stage of doping. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Doping; electrosynthesis; mobility; poly(3-hexylthiophene); swelling

Low temperature synthesis of magnetite and maghemite nanoparticles - Bhagwat, Shrikant; Singh, Hema; Athawale, Anjali; Hannoyer, Beatrice; Jouen, Samuel; Lefez, Benoit; Kundaliya, Darshan; Pasricha, Renu; Kulkarni, Shailaja; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2007)
We report on the synthesis of iron oxide nanoparticles below 100 degrees C by a simple chemical protocol. The uniqueness of the method lies in the use of Ferrous ammoniurn sulphate (in conjugation with FeCl3) which helps maintain the stability of Fe-2+ state in the reaction sequence thereby controlling the phase formation. Hexamine was added as the stabilizer. The nanoparticles synthesized at three different temperatures viz, 5 degrees, 27 degrees, and 95 degrees C are characterized by several techniques. Generally, when a mixture of Fe3+ and Fe2+ is added to sodium hydroxide, alpha-Fe2O3 (the anti-ferromagnetic phase) is formed after the dehydration process of the hydroxide. In our case however, the phases formed at all the three temperatures were found to be ferro (ferri) magnetic, implying modification of the formation chemistry due to the specifics of our method. The nanoparticles synthesized at the lowest temperature exhibit magnetite phase, while increase in growth temperature to 95 degrees C leads to the maghemite phase.
Keywords: low temperature synthesis; maghemite; magnetite; Nanoparticles

Micropropagation of mature pongamia pinnata pierre - Sujatha, K.; Hazra, Sulekha (In Vitro Cellular & Developmental Biology-Plant, 2007)
Murashige and Skoog's (MS) basal medium with benzylaminopurine (BA), kinetin (KN), zeatin (Z), and thidiazuron (TDZ) were tested for induction of multiple shoots from mature-tree-derived axillary meristems of Pongamia pinnata. Sprouting of buds was 64% on medium devoid of plant growth regulators (PGR). Incorporation of BA, KN, or Z was ineffective in enhancing sprouting frequency or induction of multiple shoots. Sprouting was completely suppressed in the presence of TDZ. Caulogenic buds appeared in nodal meristems of these explants after withdrawal of TDZ. The number of shoot buds was more on explants precultured in higher concentrations. At higher concentrations of this PGR, a swelling developed at the axil. Multiple shoot primordia appeared and differentiated from this swelling after culturing these explants on MS medium for six passages of 2 wk each. Shoots were harvested and cultured on 0.45 mu M TDZ for further proliferation. Primary explants after harvesting of shoots were identified as `stump'. Reculturing of stumps on 0.45 mu M TDZ produced more shoots. This step was followed for six cycles to obtain additional shoots in each cycle. Shoots maintained on 0.45 mu M TDZ elongated and rooted (70%) on growth regulator-free medium. Rooted shoots (65%) survived transfer to a sand/soil mixture. This report describes the protocol for micropropagation of P. pinnata using mature-tree-derived nodal meristems. Recycling of mature stock to produce a stream of useable shoots for subculturing and eventual stabilization is of great value and can possibly be generalized as an isolation protocol especially for woody species. Repeated proliferation of caulogenic buds from the same origin may also find application in rescue of endangered germplasm.
Keywords: Biodiesel; Pongam; Pongamia; shoot differentiation; thidiazuron

New technique to study kinetics of chain conformation in polyaniline films - Harima, Yutaka; Kishimoto, Kazuya; Ogawa, Fumiyuki; Jiang, Xiaoqing; Patil, Rahul (Polymer Journal, 2007)
Keywords: Conformation; kinetics; laser; polyaniline; reflection

One-step synthesis of SBA-15 containing tungsten oxide nanoclusters: a chemoselective catalyst for oxidation of sulfides to sulfoxides under ambient conditions - Bordoloi, Ankur; Vinu, Ajayan; Halligudi, Shivaraj B. (Chemical Communications, 2007)
Tungsten oxide nanoclusters supported highly ordered mesoporous SBA-15 material has been successfully synthesized in a single step using a non-ionic surfactant as a template and used for the selective oxidation of sulfur compounds, giving excellent yields at room temperature with exceptional catalyst recyclability.

Organotin-oxometalate coordination polymer catalyzed oxyfunctionalization of monoterpenes - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Keywords: Heck reaction; kinetics; Palladacycle

Oxyfunctionalisation of adamantane using inorganic-organic hybrid materials based on isopoly and heteropoly anions: kinetics and mechanistic studies - Bordoloi, Ankur; Vinu, Ajayan; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2007)
{Oxyfunctionalisation of adamantane with 30% aq.H2O2 in butyronitrile solvent was efficiently catalyzed by inorganic-organic hybrid materials synthesized by the immobilisation of isopoly (WOx = sodium tungstate
Keywords: adamantane; inorganic-organic hybrid materials; oxyfunctionalisation; vanadium (V) superoxo intermediate

Preparation and evaluation of cellulose acetate butyrate and poly(ethylene oxide) blend microspheres for gastroretentive floating delivery of repaglinide - Rokhade, Ajit P.; Patil, Sangamesh A.; Belhekar, Anagha A.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
In this study, hollow microspheres of cellulose acetate butyrate (CAB) and poly(ethylene oxide) (PEO) were prepared by emulsion-solvent evaporation method. Repaglinide was successfully encapsulated into floating microspheres. Various formulations were prepared by varying the ratio of CAB and PEO, drug loading and concentration of poly(vinyl alcohol) (PVA) solution. Encapsulation of the drug up to 95% was achieved. The microspheres tend to float over the simulated gastric media for more than 10 h. The micromeritic properties of microspheres reveal the excellent flow and good packing properties. The % buoyancy of microspheres was found to be up to 87. SEM showed that microspheres have many pores on their surfaces. Particle size ranges from 159 to 601 mu m. DSC and X-RD revealed the amorphous dispersion in the polymer matrix. In vitro release experiments were performed in simulated gastric fluid. In vitro release studies indicated the dependence of release rate on the extent of drug loading and the amount of PEO in the microspheres; slow release was extended up to 12 h. The release data were fitted to an empirical equation to compute the diffusional exponent (n), which indicated that the release mechanism followed the non-Fickian trend. (C) 2007 Wiley Periodicals, Inc.
Keywords: cellulose acetate butyrate; Controlled release; floating drug delivery; microspheres; repaglinide

Propargyl 1,2-orthoesters as glycosyl donors: stereoselective synthesis of 1,2-trans glycosides and disaccharides - Sureshkumar, Gopalsamy; Hotha, Srinivas (Tetrahedron Letters, 2007)
Propargyl 1,2-orthoesters are identified as glycosyl donors. Various glycosides and disaccharides were synthesized in a stereoselective manner using AuBr3 as the promoter. AuBr3 may activate the alkyne resulting in the formation of a 1,2-dioxolenium ion and also behaves as a Lewis acid to facilitate the attack of the glycosyl acceptor. The versatility of the protocol was demonstrated using a panel of aglycones comprising aliphatic, alicyclic, steroidal and sugar alcohols. (C) 2007 Elsevier Ltd. All rights reserved.

Selective oxidation of anthracene using inorganic-organic hybrid materials based on molybdovanadophosphoric acids - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
{Inorganic-organic hybrid materials were synthesized by immobilization of molybdovanadophosphoric acids onto mesoporous silicas, such as MCM-41, MCM-48, and SBA-15, through an organic linker. 12-Molybdovanadophosphoric acids of the general formula H3+xPMO12-xVxO40 (x = 0-3).nH(2)O, such as H-4[
Keywords: EPDM; Photostabilization; polymeric HALS

Spider silk as an active scaffold in the assembly of gold nanoparticles and application of the gold-silk bioconjugate in vapor sensing - Singh, Amit; Hede, Shantesh; Sastry, Murali (Small, 2007)
Spider silk is being viewed with interest by materials scientists due to its excellent resilience and mechanical properties. In this paper we show that spider silk is an excellent scaffold for the one-step synthesis and assembly of gold nanoparticles. Formation of a gold nanoparticle-spider-silk bioconjugate material is accomplished by simple reaction of the fibers with aqueous chloroauric acid. The gold nanoparticles thus formed are strongly bound to the spider-silk fiber surface enabling study of the electrical properties of the nano bioconjugate. Using the well-known contraction/expansion behavior of the fibers in solvents of varying polarity, we show that exposure of the gold nanoparticle-spider silk bioconjugate to vapors of methanol and chloroform leads to changes in electrical transport through the nanoparticles and thus, the possibility of developing a vapor sensor. The bioconjugate shows excellent response time and cycling efficiency to methanol vapors. The activation energy of electron transport from one gold nanoparticle to another in the nanobiocojugate was determined from temperature-dependent electron-transport measurements to be approximately 1.7 eV.
Keywords: bioconjugates; Gold; Nanoparticles; sensors; spider silk

Stereoselective hydrogenation of tert-butylphenols over charcoal-supported rhodium catalyst in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, Chandrashekhar V.; Sato, Osamu; Tetsuka, Hiroyuki; Shirai, Masayuki (Journal of Catalysis, 2007)
Hydrogenation of 2-, 3-, and 4-tert-butylphenols was studied over a charcoal- supported rhodium catalyst in supercritical carbon dioxide (scCO(2)) solvent, and the results were compared with those in organic solvents. In the hydrogenation of 4-tert-butylphenol, a higher cis ratio for 4-tert-butylcyclohexanol (0.79) was obtained in scCO(2) (10 MPa) than in 2-propanol (0.70) and cyclohexane (0.64) under similar conditions of hydrogen pressure (2 MPa) and temperature (313 K). In the case of 2-tert-butylphenol, the cis ratio for 2-tert-butylcyclohexanol was as high as 0.95 in both scCO(2) and 2-propanol (hydrogen pressure, 2 MPa; reaction temperature, 313 K). In the case of hydrogenation of 3-tert-butylphenol, the cis ratio decreased with the progression of consecutive hydrogenation of 3-tert-butylcyclohexanone intermediate. In addition, the stereoselectivity to cis-tert-butylcyclohexanols in scCO(2) was improved in the presence of hydrochloric acid. It was found that the protons of hydrochloric acid accelerated the hydrogenation of the intermediates, tert-butylcyclohexanones, to the corresponding cis-tert-butylcyclohexanols. The hydrogenation mechanism of tert-butylphenols, particularly the enhanced selectivity to cis-tert-butylcyclohexanols in scCO(2), is postulated based on the observed reaction profiles. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: charcoal-supported rhodium catalyst; stereoselective hydrogenation; supercritical carbon dioxide solvent; tert-butylcyclohexanol

Syntheses of 1,2-amino alcohols and their applications for oxazaborolidine catalyzed enantioselective reduction of aromatic ketones - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S. (Australian Journal of Chemistry, 2007)
Six new chiral 1,2-amino alcohol derivatives have been synthesized starting from (1R, 2R)-2-amino-1-phenylpropane-1,3- diol. Asymmetric reduction of aryl ketones with in-situ generated oxazaborolidine from these amino alcohol derivatives and BH3 center dot Me2S afforded secondary alcohols with good yield and moderate to high enantiomeric excess.

Synthesis and characterization of new aromatic polyesters containing biphenyl side groups - Honkhambe, Pandurang N.; Avadhani, C. V.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2007)
Aromatic polyesters containing biphenyl side groups were synthesized by phase-transfer catalyzed interfacial polycondensation of 1-(4-biphenylyl)-1,1-bis(4-hydroxyphenyl) ethane (BBHPE) with terephthaloyl chloride (TPC), isophthaloyl chloride (IPC), and a mixture of TPC/IPC (50: 50 mol ratio). Copolyesters were synthesized by utilizing different molar proportions of BBHPE and 4,4-isopropylidenediphenol (BPA) with IPC and TPC. The inherent viscosities of polyesters were in the range 0.44-1.26 dL/g. All the polyesters were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methyl-2-pyrrolidmone. Tough, transparent, and flexible films could be cast from chloroform solutions of these polyesters. WAXD measurements indicated that all the polyesters and copolyesters were amorphous in nature. Glass transition temperature of polyesters were in the range 198-256 degrees C, while the initial degradation temperature of polyesters were in the range 444-481 degrees C. Copolyesters derived from BBHPE exhibited improved solubility and higher glass transition temperatures compared to the corresponding polyesters based on BPA. (c) 2007 Wiley Periodicals, Inc.
Keywords: Aromatic polyesters; biphenyl side groups

Synthesis and characterization of novel polyurethanes based on 4,4 `-[1,4-phenylenedi-diazene-2,1-dlyl] bis(2-carboxyphenol) and 4,4 `-[1,4-phenylenedi-diazene-2,1-diyl] bis(2-chlorophenol) hard segments - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Reactive & Functional Polymers, 2007)
Eight novel polyurethanes (PUs) based on 4,4'-[1,4-phenylenedi-diazene-2,1-diyl]bis(2-carboxyphenot) and 4,4'-[1,4phenylenedi-diazene-2,1-diyl]bis(2-chloro- phenol) as hard segments with four diisocyanates viz., 4,4-diphenyl-methane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate were prepared. Structural and thermal characterization of the segmented PUs were determined by FT-IR, UV spectrophotometry, fluoroscence spectroscopy, H-1 NMR, C-13 NMR spectroscopy and DTA/TGA analysis. All the PUs contain domains of semi-crystalline and amorphous structures, as indicated by X-ray diffraction. PUs were soluble in polar aprotic solvents like N-methyl-2-pyrrolidone (NMP), dimethyl formamide (DMF) and dimethylsulfoxide (DIVISO). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: azo polymers; fluorescence; hard segments; Morphology; phase separation; polyurethanes; spectroscopy; Thermal properties

Synthesis, characterization, and acoustic properties of new soluble polyurethanes based on 2,2 `-[1,4-phenylenebis(nitrilomethylylidene)diphenol and 2,2 `-[4,4 `-methylene-di-2-methylphenylene-1,1 `-bis(nitrilomethylylidene)]diphenol - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
Eight novel polyurethanes based on 2,2'-[1,4-phenylenebis(nitrilomethylylidene)]diphenol and 2,2-[4,4'methylene-di-2-methylphenylene-1,1'-bis(nitrilomethylylidene) ]diphenol acting as hard segments with two aromatic and two aliphatic diisocyanates (4,4'-diphenytmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) were prepared and characterized with Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1-NMR and C-13-NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis. All the polyurethanes contained domains of semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties and solubility parameters were calculated with the group contribution method. (c) 2007 Wiley Periodicals, Inc.
Keywords: infrared spectroscopy; NMR; phase behavior; polyurethanes; Thermal properties

Synthesis of C-2 methylene glycosides from C-2 propargyloxymethyl glycals exploiting the alkynophilicity of AuCl3 - Kashyap, Sudhir; Vidadala, Srinivasa Rao; Hotha, Srinivas (Tetrahedron Letters, 2007)
C-2 Methylene glycosides were synthesized from C-2 propargyloxymethyl glycals in a stereoselective manner using a catalytic quantity of AuCl3. The Au-catalyzed reaction was explored using various aglycones. The current protocol enables the preparation of C-2 methylene glycosides, tolerates diverse functional groups and is fast, catalytic and mild. (c) 2007 Elsevier Ltd. All rights reserved.
21st Carbo Symposium 2006, Univ Delhi, Delhi, INDIA, NOV 26-29, 2006

Synthesis of natural fimbrolides - Haval, Kishan P.; N. P. Argade (Synthesis-Stuttgart, 2007)

Synthesis, structure, and reactivity of diazoketiminato complexes of platinum(II) and palladium(II): cytotoxic properties of a platinum complex - Pratihar, Jahar Lal; Shee, Biswaranjan; Pattanayak, Poulami; Patra, Debprasad; Bhattacharyya, Arindam; Puranik, Vedavati G.; Hung, C. H.; Chattopadhyay, Surajit (European Journal of Inorganic Chemistry, 2007)
{Reaction of the 2-(arylazo)anilines Ar-N = N-C6H4NH2 [
19th International Symposium on Chemical Reaction Engineering (ISCRE 19), Pottsdam, GERMANY, SEP, 2006
Keywords: CFD; hydro processing; scale-down; scale-up; trickle bed

Transport study on as-grown and cast films of electrogenerated poly(3-hexylthiophene) - Jiang, Xiaoqing; Harima, Yutaka; Patil, Rahul (Materials Letter, 2007)
Two kinds of poly(3-hexylthiophene) films with identical chemical compositions are prepared. One of the films is obtained by electropolymerization of 3-hexylthiophene (as-grown film) and the other is prepared by casting a solution dissolving the as-grown film (cast film). A clear difference is found in the mobility vs. doping level plots between the as-grown and cast films and its reason is discussed. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: mobility; poly(3-hexylthiophene); swelling; thin film; transport mechanism

Tungstophosphoric acid and zirconia supported on mesoporous silica catalyst in veratrole acetylation - Halligudi, Shivaraj B. (From ZEOLITES to Porous Mof Materials: The 40th Anniversary of International ZEOLITE Conference, Proceedings of The 15th International ZEOLITE Conference, 2007)
Tungstophosphoric acid (TPA) over zirconia dispersed uniformly in mesoporous silica (MS) channels of MCM-41 and MCM-48 was synthesised and tested for its catalytic activity in veratrole acetylation. Catalysts with different TPA loadings (5 to 50 wt.%) on 22.4 wt.% ZrO(2)/MCM-41 and 15 wt.% TPA on different zirconia loadings (10-70 wt.%)/MCM-41 were prepared and calcined at 1123 K. Catalysts were characterised by known techniques. Mesoporous silica supports play an important role in stabilising catalytically active TPA along with tetragonal phase of zirconia. Among the catalysts, 15 wt.% TPA/22.4 wt.% ZrO(2)/MCM-41 calcined at 1123 K was found to have the highest acidity and be at least four times more active than neat 15 wt.% TPA/ZrO(2) in veratrole acetylation to acetoveratrone by acetic anhydride.
15th International Zeolite Conference, Beijing, PEOPLES R CHINA, AUG 12-17, 2007

Tungstophosphoric acid supported on titania: a solid acid catalyst in benzylation of phenol with benzylalcohol - Kumbar, Suresh M.; Halligudi, Shivaraj B. (Catalysis Communictions, 2007)
{Benzylation of phenol with benzylalcohol was carried out in liquid phase over tungstophosphoric acid (TPA) supported on titania. The catalysts were prepared with different TPA (10-25%) loading by wet impregnation method, were calcined at 700 degrees C and characterized by XRD, surface area, FTIR and acidity of the catalysts was measured by temperature programmed desorption of NH(3)-TPD, FTIR pyridine adsorption. The catalysts have been represented by a general formula as xPTiO(2)-Y (where x = wt%
Keywords: benzyl ether; benzyl phenol; benzylalcohol; Heteropolyacid; phenyl benzyl ether; titania; tungstophosphoric acid

Tungstophosphoric acid supported over zirconia in mesoporous channels of MCM-41 as catalyst in veratrole acetylation - Sawant, Dhanashri P.; Vinu, A.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Tungstophosphoric acid (TPA) over zirconia dispersed uniformly in mesoporous silica (MS) channels of MCM-41 and MCM-48 were synthesized and tested for their catalytic activity in veratrole acetylation. Catalysts with different TPA loadings (5-50 wt.%) on 22.4 wt.%ZrO2/MCM-41 and 15 wt.%TPA on different zirconia loadings (10-70 wt.%)/MCM-41 were prepared and calcined at 1123 K. The physico-chemical characterization of the supported catalysts was done by powder X-ray diffraction (XRD), surface area measurement (BET), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transformed-infrared (FT-IR) spectroscopy, UV-vis diffuse reflectance spectra, Temperature programmed desorption (TPD) of ammonia, FT-IR pyridine adsorption and (31) P cross polarization-magic angle spinning (CP-MAS) NMR spectroscopy. The mesoporous silica supports play an important role in stabilizing catalytically active TPA along with tetragonal phase of zirconia. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/MCM-41 calcined at 1123 K was found to have highest acidity and at least four times more active than neat 15 wt.%TPA/ZrO2 in veratrole acetylation to acetoveratrone by acetic anhydride. Reaction conditions were evaluated with 15 wt.%TPA/22.4 wt:%ZrO2/MCM-41 calcined at 1123 K to get higher conversion of acetic anhydride to acetoveratrone. The reaction was found to be heterogeneously catalyzed and no contribution from homogeneous (leached) TPA into the medium under the reaction conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acetoveratrone; acetylation; MCM-41; TPA/ZrO2; veratrole

Unprecedented two-dimensional polymeric [Zn(OOC-C6H4-COO)(2)](2_)(n)[+H3N-(CH2)(3)-NH(3])(+)n system bearing one-dimensional chain of zinc(II) bis(phthalate) dianions held by propane-1,3-diammonium cations: crystal structure, thermal and fluorescent pr - Padmanabhan, A.; Joseph, K. C.; Puranik, Vedavati G.; Huang, Xiaoying; Li, Jing (Solid State Sciences, 2007)
A novel zinc(II) phthalate compound, [Zn{C6H4(COO)(2)}(2)](n)(2-)[NH3-(CH2)(3)-NH3](n)(2+), 1 Which contains four different phthalate moieties coordinated to the Zn(II) ion through one each of their carboxyl ate moieties in a eta(1)-form and each phthalate moiety acting as a bridging unit with an overall tetrahedral geometry around the metal ion has been prepared and structurally characterized. The structure is unique in the sense that the dianionic moieties [Zn{C6H4(COO)(2)}(2)](2-) form an infinite one-dimensional network composed of 14-membered cyclic units interconnected in a way that they are disposed alternatively in almost perpendicular planes. The dicationic [NH3-(CH2)(3)-NH3](2+) units are seen to hold these one-dimensional chains by strong coulombic and hydrogen bond interaction, resulting in an infinite two-dimensional layered structure of 1. The compound is thermally stable up to 250 degrees C. Above this temperature it loses one equivalent of phthalate moiety along with the diammonium unit to yield Zn(II) phthalate. The thermodynamic and kinetic parameters associated with this process could be evaluated using Coats-Redfern equation which shows the activation energy Ea for the process as 305.0 kJ mol(-1), the frequency factor A as 1.49 x 10(11) s(-1) and the entropy change Delta S as -35.90 JK(-1) mol(-1). Fluorescent emission properties of 1 was studied by exciting the compound at 380 nm and also at 322 nm which were found to be the two lambda(max) corresponding to absorptions of the molecule. Interestingly, the compound gave same type of emission spectra showing a maximum around 444 nm on exciting at these two different wavelengths, indicating that the molecule comes to the first excited state from the higher excited state by a fast non-radiative process before it exhibits singlet emission to come to the ground state. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: 1; 3-diammonium; cyclic chain; fluorescent emission; layered structure; propane; zinc(II) bis(phthalate) dianion; zinc-phthatate

Accumulation of cadmium in growing peanut (Arachis hypogaea L.) seedlings - its effect on lipid peroxidation and on the antioxidative enzymes catalase and gualacol peroxidase - Kumar, Sunil; Mehta, Urmil J.; Hazra, Sulekha (Journal of Plant Nutrition and Soil Science, 2008)
In plants exposed to high metal concentrations, mechanisms to counteract the oxidative burst are crucial for its survival. To investigate the temporal sequence of physiological reactions of peanut seedlings (Arachis hypogaea L.) to cadmium exposure, seeds were cultured in increasing concentrations of CdCl(2), ranging from 50 to 300 mu M. Germination frequency was scored, and the distributions of Cd in root, stem, and leaves were determined after 2 and 4 weeks of culture. Lipid peroxidation and activities of antioxidative enzymes including catalase (CAT, EC 1.11.1.6) and guaiacol peroxiclase (GPX; EC 1.11.1.7) were estimated in these three parts of the plant. Germination of seedlings was not affected, but the growth of seedlings was severely suppressed with increasing concentrations of CdCl(2) and incubation period. Pattern of Cd distribution in the three organs varied with concentration and period of exposure to Cd. Increased lipid peroxidation was detected in all parts of the developing seedlings with increasing metal accumulation. Catalase and guaiacol peroxidase activity varied in the three parts of the seedlings with concentration of Cd and incubation period. Guaiacol peroxidase activity appears to be more active in scavenging the reactive oxygen species in developing peanut seedlings. The results of the present experiment demonstrate the advantages of a tissue-culture model system in studying the complex network of interactions of various factors in stress tolerance.
Keywords: Abiotic stress; heavy metal; stress tolerance; TBARS; thiobarbituric acid; Tissue culture

Active sites in vanadia/titania catalysts for selective aerial oxidation of beta-picoline to nicotinic acid - Srinivas, Darbha; Hoelderich, Wolfgang F.; Kujath, Steffen; Valkenberg, Michael H.; Raja, Thirumalaiswamy; Saikia, Lakshi; Hinze, Ramona; Ramaswamy, Veda (Journal of Catalysis, 2008)
Vanadia/titania catalysts with varying vanadium content were prepared by impregnation using three different titania carrier materials of varying surface area, The structure of active vanadium species for beta-picoline oxidation was investigated. Vanadium is mainly in the +5 oxidation state as revealed by electron paramagnetic resonance (EPR) and V-51 magic-angle spinning nuclear magnetic resonance (V-51 MAS NMR) spectroscopy techniques. Diffuse reflectance UV-visible (DRUV-vis) spectroscopy and spectral deconvolution enabled identification of at least five different types of vanadium oxide species in these catalysts: monomeric tetrahedral VO43-, polymeric distorted tetrahedral VO3-, square pyramidal V2O5, octahedral V2O62- and V4+ oxide species. While both VO43- and VO3- species are active in beta-picoline oxidation, the latter having a distorted tetrahedral geometry yielded the desired products-picolinaldehyde and nicotinic acid. High surface area, anatase structure for the support and dispersed, distorted tetrahedral vanadium oxide species are the key parameters determining the activity and selectivity of these oxidation catalysts. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Active vanadium species; Nicotinic acid; Oxidation of beta-picoline; Selective aerial oxidation; Spectroscopic investigations; Vanadia/titania

Alkene epoxidation catalyzed by vanadomolybdophosphoric acids supported on hydrated titania - Ingle, Rohit H.; Vinu, A.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Vanadomolybdophosphoric acids wet-impregnated oil hydrated titania (TiO(2) - xH(2)O), make ail efficient catalytic system for the epoxidation of a variety of alkenes with organic solvent extracted TBHP as the oxidant. By,in appropriate choice of solvent, the catalyst call be reused at least three times without much loss in the activity for subsequent runs. XRD shows that the heteropoly acid is uniformly dispersed over the support and up to 15 wt% loading of the heteropoly acid, no additional peak of the same call be seen in the XRD pattern of the catalyst. The reactivity varied with the nature of alkene but the major product was always the corresponding epoxide. The catalytic system is free of high temperature calcination steps and tedious multi-step procedures, normally encountered in the heter-ogenization of heteropoly acids. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alkenes; epoxidation; heteropoly acids; TBHP; titania; vanadomolybdophosphoric acids

Bacterial synthesis of copper/copper oxide nanoparticles - Hasan, Syed Saif; Singh, Sanjay; Parikh, Rasesh Y.; Dharne, Mahesh S.; Patole, Milind S.; Bhagavatula L. V. Prasad; Shouche, Yogesh S. (Journal of Nanoscience and Nanotechnology, 2008)
A bacterial mediated synthesis of copper/copper oxide nanoparticle composite is reported. A Gram-negative bacterium belonging to the genus Serratia was isolated from the midgut of Stibara sp., an insect of the Cerambycidae family of beetles found in the Northwestern Ghats of India. This is a unique bacterium that is quite specific for the synthesis of copper oxide nanoparticles as several other strains isolated from the same insect and common Indian mosquitoes did not result in nanoparticle formation. By following the reaction systematically, we could delineate that the nanoparticle formation occurs intracellularly. However, the process results in the killing of bacterial cells. Subsequently the nanoparticles leak out as the cell wall disintegrates. The nanoparticles formed are thoroughly characterized by UV-Vis, TEM, XRD, XPS and FTIR studies.
Keywords: bacterial synthesis; Nanoparticles; TEM; XPS; XRD

Bacteria-mediated precursor-dependent biosynthesis of superparamagnetic iron oxide and iron sulfide nanoparticles - Bharde, Atul A.; Parikh, Rasesh Y.; Baidakova, Marina; Jouen, Samuel; Hannoyer, Beatrice; Enoki, Toshiaki; Bhagavatula L. V. Prasad; Shouche, Yogesh S.; Ogale, Satishchandra B.; Sastry, Murali (Langmuir, 2008)
The bacterium Actinobacter sp. has been shown to be capable of extracellularly synthesizing iron based magnetic nanoparticles, namely maghemite (gamma-Fe2O3) and greigite (Fe3S4) Under ambient conditions depending on the nature of precursors used. More precisely, the bacterium synthesized maghemite when reacted with ferric chloride and iron sulfide when exposed to the aqueous solution of ferric chloride-ferrous sulfate. Challenging the bacterium with different metal ions resulted in induction of different proteins, which bring about the specific biochemical transformations in each case leading to the observed products. Maghemite and iron sulfide nanoparticles show superparamagnetic characteristics as expected. Compared to the earlier reports of magnetite and greigite synthesis by magnetotactic bacteria and iron reducing bacteria, which take place strictly under anaerobic conditions, the present procedure offers significant advancement since the reaction occurs under aerobic condition. Moreover, reaction end products can be tuned by the choice of precursors used.

Characterization of MoSe2 thin film deposited at room temperature from solution phase - Hankare, P. P.; Patil, A. A.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Manikshete, A. H.; Mulla, Imtiaz S. (Journal of Crystal Growth, 2008)
A simple, low-temperature method has been developed to synthesis molybdenum diselenide semiconductor thin films, based on the chemical reaction of conlplexed ammonium molybdate, hydrazine hydrate and sodium Selenosulphate in aqueous alkaline medium. The deposition parameter of the MoSe2 thin film is interpreted in the present investigation. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), optical absorption and electrical measurements. The deposited film was found to be polycrystalline in hexagonal form. The direct band gap `E-g' for the film was found to be 1.43eV and electrical conductivity in the order of 10(-2)(Omega cm)(-1) with n-type conduction mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Crystal morphology; Growth from solution; Inorganic compound; Polycrystalline deposition; Semiconducting materials; X-ray diffraction

Chemoselective synthesis of beta-amino acid derivatives by hydroamination of activated olefins using AISBA-15 catalyst prepared by post-synthetic treatment - Shanbhag, Ganapati V.; Kumbar, S. M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
beta-Amino acid derivatives have a wide variety of applications viz. in the synthesis of peptide analogues, precursor for amino alcohols, optically active amino acids, lactums and diamines. Chemoselective anti-Markovnikov hydroamination reaction of activated olefins was effectively used to synthesize beta-amino acid derivatives using AlSBA-15 and AlMCM-41 catalysts. These catalysts with different Si/Al ratios were synthesized by isomorphous substitution of aluminium into the framework of SBA-15, which induces the Bronsted and Lewis acid sites. The structural integrity of the catalysts was established by characterizing with XRD, N-2-sorption, TEM, NH3-TPD Al-27 MAS NMR and Si-29 MAS NMR techniques. Hydroamination of ethyl acrylate with aniline was used as a test reaction, which gave N-[2-(ethoxycarbonyl)ethyl] aniline with high selectivity. The performance of AlSBA-15 catalyst was also determined with different acrylates and amines to know the general applicability of the catalyst in hydroamination reactions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acrylate; activated olefin; addition; AlMCM-41; AlSBA-15; Amine; beta-amino acid; Catalyst; hydroamination; Mesoporous

Chiral Mn(III) salen complex immobilized onto ionic liquid modified mesoporous silica for oxidative kinetic resolution of secondary alcohols - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Tetrahedron Letters, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a chiral Mn(III) salen complex onto ionic liquid modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high enantioselectivity and activity in the oxidative kinetic resolution of secondary alcohols, and could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Mesoporous silica SBA-15; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Differential accumulation of manganese in three mature tree species (Holoptelia, Cassia, Neem) growing on a mine dump - Raju, D.; Kumar, Sunil; Mehta, Urmil J.; Hazra, Sulekha (Current Science, 2008)
Three trees, including Cassia siamea (Cassia), Azadirachta indica (Neem), Holoptelia integrifolia (Holoptelia) belonging to three different families were identified from a manganese mine tailing dump. Manganese content in dump soil and in the stem, green leaves and dry, fallen leaves of the plants was determined. Values were compared with similar samples collected from normal vegetation. Under control condition, manganese content was highest in Cassia. Distribution of metal in samples collected from the dump site revealed that Holoptelia has a special ability to accumulate high amounts of manganese under stress condition followed by Cassia and Neem. There is no literature on metal accumulation in Holoptelia. Mechanism of manganese sequestration in Holoptelia is different from the other two trees growing in the same soil.
Keywords: Azadirachta indica; Cassia siamea; Holoptelia integrifolia; hyperaccumulator; manganese; mine dump

Effect of TDZ and 2, 4-D on peanut somatic embryogenesis and in vitro bud development - Joshi, Madhumita; Sujatha, K.; Hazra, Sulekha (Plant Cell Tissue and Organ Culture, 2008)
Failure of peanut somatic embryos to convert into plantlets is attributed to the abnormal development of the plumule. Thidiazuron (TDZ) was effective in the conversion of peanut somatic embryos to plantlets by triggering morphogenetic activity in the abnormal plumules of the rooted somatic embryos. The present study aimed to induce normal embryo differentiation by culturing the embryogenic masses in embryo development medium containing 2,4-D and various concentrations of TDZ. Although this was not achieved due to restricted somatic embryo development in the presence of TDZ, bud-like projections appeared in the embryogenic masses when these were cultured in media containing combinations of 2,4-D and TDZ. These projections developed into buds, which subsequently formed shoots and plantlets. The response varied with the concentration and exposure of TDZ. At lower concentrations, the buds appeared in a defined row in the equatorial region of the explant, and with extended incubation, more and more buds appeared in rows alongside the initial row. Induction of multiple buds in a defined row in this specific site (equatorial region) suggested the presence of potent cells around this region. At higher concentrations, these projections appeared in large numbers spread over the whole upper part of the embryogenic mass starting from the equatorial region. The ability of embryogenic mass to convert into organogenic mass and to produce large number of organogenic buds provides an excellent system for basic studies and for the genetic transformation of peanut.
Keywords: Arachis hypogaea; embyogenic mass; somatic embryogenesis; thidiazuron

Enantioselective hydrogenation of olefins by chiral iridium phosphorothioite complex covalently anchored on mesoporous silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
Chiral monodentate phosphorous-based ligands have proven effective for the enantioselective hydrogenation of olefins. Binol-derived monodentate phosphorothioite (PS) ligand was synthesized from binol and thiopropyltriethoxysilane, and its iridium complex was covalently anchored to mesoporous silica supports like SBA-15, MCM-41, and MCM-48. These catalysts were characterized by different physicochemical techniques and assessed for their catalytic performances in the heterogeneous asymmetric hydrogenation of itaconic acid and its derivatives. It was found that the catalytic activities and enantioselectivities of the heterogenized iridium complex (IrPSSBA-15) in the hydrogenation reactions were comparable to its homogeneous analogue. Binol-derived monodentate phosphorothioite ligand in heterogeneously anchored form (iridium complex) is a more effective catalyst than the reported monodentate phosphorous ligand systems in the hydrogenation reactions, possibly due to the changes in electronic properties around the iridium metal center. The effects of substrate-to-catalyst molar ratio, solvents, and temperature on substrate conversions and enantioselectivities, of the products were investigated in hydrogenation reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: binol; Enantioselective hydrogenation; Immobilization; iridium complex; itaconic acid; Mesoporous silica SBA-15; monodentate ligand; phosphorothioite ligand

Enhanced conversion efficiency in dye-sensitized solar cells based on ZnO bifunctional nanoflowers loaded with gold nanoparticles - Dhas, Vivek V.; Muduli, Subas; Lee, Wonjoo; Han, Sung-Hwan; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
The ZnO nanoflowers loaded with gold (Au) nanoparticles (NPs) are synthesized by a hydrothermal route using mixed precursors and controlled conditions. The dye-sensitized solar cells based on the ZnO nanoflowers with Au NPs show power conversion efficiency of 2.5%, which is considerably higher than that of ZnO nanoflowers without Au NPs. Detailed characterizations are performed, presented, and discussed.
Keywords: crystal growth from solution; Gold; II-VI semiconductors; Nanocomposites; Nanoparticles; solar cells; wide band gap semiconductors; zinc compounds

Enhancement of glycerol conversion to acetol in high-temperature liquid water by high-pressure carbon dioxide - Yamaguchi, Aritomo; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2008)
Dehydration of glycerol to acetol proceeded in high-temperature liquid water at 573 K in a batch reactor. The acetol formation rate increased with an addition of high-pressure carbon dioxide.

Extracellular bacterial synthesis of protein-functionalized ferromagnetic Co3O4 nanocrystals and imaging of self-organization of bacterial cells under stress after exposure to metal ions - Kumar, Umesh; Shete, Ashvini; Harle, Arti S.; Kasyutich, Oksana; Schwarzacher, W.; Pundle, Archana; Poddar, Pankaj (Chemistry of Materials, 2008)
Co3O4, which crystallizes in the spinet phase at temperatures much higher than ambient temperatures, orders antiferromagnetically below its Neel temperature (similar to 40 K). However, in nanosize, it shows ferromagnetic ordering due to surface canting, disorder, imperfect oxygen atom coordination, etc. Here, for the first time, we report the synthesis of single-crystalline, ferromagnetic Co3O4 nanoparticles functionalized with proteins (size 5-7 nm) using cobalt acetate as precursor at room temperature in aqueous medium by a metal-tolerant marine bacterium isolated from the coast of the Arabian Sea. Energetically unfavorable change in the oxidation state of Co atoms from (+2 to +3) during synthesis by the bacterial strain was evidenced by X-ray photoelectron spectroscopy. The effect on the morphology of bacterial cells after exposure to the cobalt acetate was imaged by scanning electron microscopy showing cooperative, self-organized. structured colony formation, possibly due to the interbacterial communication under external stress.

Foldamers with unusual structural architecture from spirobi(indane) building blocks - Kendhale, Amol M.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
This communication demonstrates the utility of inherently rigid building blocks such as 1,1'-spirobi(indane) for generating conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

Furfural: hemicellulose/xylosederived biochemical - Mamman, Ajit Singh; Lee, Jong-Min; Kim, Yeong-Cheol; Hwang, In Taek; Park, No-Joong; Hwang, Young Kyu; Chang, Jong-San; Hwang, Jin-Soo (Biofuels Bioproducts & Biorefining-Biofpr, 2008)
Hemicellulose, the second, most common polysaccharide in nature constitutes approximately 20-35% of lignocellulosic biomass. Effective utilization of biomass, hitherto underutilized, is gaining tremendous importance for the production of energy, fuels, and chemicals. Amongst the vast array of chemicals derived from lignocellulosics, furfural is the key chemical that finds wide applications in oil refining, plastics, pharmaceutical and agrochemical industries. There is no synthetic route for the production of furfural. A few conventional technologies currently in practice for its separation and subsequent isolation are appropriately reviewed. Major disadvantages associated with processes currently used for the production of furfural based on acid-catalyzed hydrolysis have been discussed. A need to develop a process which is devoid of all the shortcomings associated with conventional process is emphasized. Several important aspects of chemistry underlying the acid hydrolysis of xylose are discussed. The importance of myriad pre-treatment steps involved to surmount the physical and chemical barriers and to liberate xylose from the confines of acid-resistant layer of lignin has been emphasized. New developments in the production of furfural from cyclodehydration of xylose using solid acid catalysts in the recent past have been reviewed appropriately in present communication. Finally, the production of furfural and furfuryl alcohol, their domestic market and export in China deserve some coverage and therefore have appropriately been discussed as well. (c) 2008 Society of Chemical Industry and John Wiley & Sons, Ltd
Keywords: acid hydrolysis; cyclodehydration; furfural; Hemicellulose; pre-treatment of lignocellulosics; Xylose

General strategy for the synthesis of natural and unnatural dialkylmaleic anhydrides - Haval, Kishan P.; N. P. Argade (Journal of Organic Chemistry, 2008)
Starting from alkylidenesuccinimides, a wide range of dialkylmaleic anhydrides have been synthesized via the generation of a carbanion on a succinimide unit and its condensation with various alkyl halides as the key reaction.

Gold mediated glycosylations: selective activation of propargyl 1,2-orthoesters in the presence of aglycones containing a propargyl moiety - Sureshkumar, Gopalsamy; Hotha, Srinivas (Chemical Communications, 2008)
Selective activation of propargyl 1,2-orthoesters in the presence of propargyl glycosides and propargyl ethers was studied; a catalytic amount of AuBr(3) activated the propargyloxy, group of the 1,2-orthoester thereby giving access to disaccharides with the propargyl group at the reducing end; furthermore, propargyl ethers were unaffected under the reaction conditions.

Heteropoly acid encapsulated SBA-15/TiO(2) nanocomposites and their unusual performance in acid-catalysed organic transformations - Sawant, Dhanashri P.; Justus, Josena; Balasubramanian, Veerappan V.; Ariga, Katsuhiko; Srinivasu, Pavuluri; Velmathi, Sivan; Halligudi, Shivappa B.; Vinu, Ajayan (Chemistry-A European Journal, 2008)
The preparation of SBA-15/TiO(2) nanocomposites with different loadings of Keggin-type 12-tungsto-phosphoric acid (TPA) nanocrystals in their mesochannels through a simple and effective vacuum impregnation method is reported for the first time. The catalysts have been characterised by various sophisticated techniques, including XRD, HRSEM, and TEM. It has been found that the acidity and the textural parameters of the nanocomposites can be controlled by simply changing the loadings of TPA and TiO(2) or the calcination temperature. TPA and TiO(2) loadings of 15 and 22.4 wt %, respectively, and a calcination temperature of 1123 K have proved to be optimal for obtaining mesoporous nanocomposite materials with the highest acidity. Moreover, the activities of these catalysts in promoting hydroamination as well as Mannich and Claisen rearrangement reactions have been extensively investigated. The results show that the amount of TPA has a great influence on the activity of the nanocomposites in all of the reactions studied. The effects of other reaction parameters, such as temperature and reaction time, on the conversion and product selectivity have also been studied in detail. A kinetic analysis of the formation of the products under various reaction conditions is presented. It has been found that the activity of the nanocomposite composed of 15 wt % TPA deposited on 22.4 wt of TiO(2) on SBA-15 in promoting the studied reaction is remarkably higher than the catalytic activities shown by pure TPA, TiO(2)-loaded SBA-15, or TPA-loaded SBA-15. The results obtained have indicated that the acidity and the structural control of the nanocomposite materials are highly critical for obtaining excellent catalytic activity, and the presented highly acidic nanocomposites are considered to show great potential for use as catalysts in promoting many acid-catalysed organic transformations.
Keywords: Bronsted acids; mesoporous materials; nanoreactors; nanotechnology; supported catalysts

Heteropoly acid-based supported ionic liquid-phase catalyst for the selective oxidation of alcohols - Bordoloi, Ankur; Sahoo, Suman; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a heteropolyacid, molybdovanadophosphoric acid, onto ionic liquid-modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high activity in the aerobic oxidation of primary and secondary alcohols to aldehydes and ketones, respectively. No overoxidation of the primary alcohols to carboxylic acids was observed. Secondary alcohols were chemoselectively oxidized to ketones in the presence of primary alcohol, hetero atom, and allyl groups. This catalyst could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Air as an oxidant; Mesoporous silica SBA-15; Molybdovanadophosphoric acid; Selective oxidation; Supported ionic liquid

Highly efficient and chemo selective catalyst system for the synthesis of blossom orange fragrance and flavoring compounds - Justus, Josena; Vinu, Ajayan; Devassy, Biju M.; Balasubramanian, Veerappan V.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
{Acetal and acylal formation reactions of organic compounds are efficiently catalyzed by zirconia-supported mixed oxide systems under liquid-phase reaction conditions. 15WZ-750 (where
Keywords: Acetal; acylal; Silicotungstic acid; tungsten oxide; tungstophosphoric acid; Zirconia

Highly selective catalytic hydrogenation of arenes using rhodium nanoparticles supported on multiwalled carbon nanotubes - Kakade, Bhalchandra A.; Sahoo, Suman; Halligudi, Shivappa B.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2008)
Rhodium nanoparticles (RhNPs; 4.9 +/- 0.4 nm) supported on multiwalled carbon nanotubes (Rh/MWNT), prepared by simple microwave treatment, show a remarkable catalytic activity for arene hydrogenation with enhanced turnover numbers of similar to 10000; disubstituted arenes show selective conversion of thermodynamically less favorable cis products (>80%). A series of arenes have been tested using various Rh-based catalysts, and a comparison of the results with that of reported rhodium catalysts shows unique selectivity under mild conditions.

Imaging the stomatal physiology of somatic embryo-derived peanut leaves by scanning electrochemical microscopy - Parthasarathy, Meera; Singh, Shweta; Hazra, Sulekha; Pillai, Vijayamohanan K. (Analytical and Bioanalytical Chemistry, 2008)
The stomatal physiology, chlorophyll distribution and photosynthetic activity of somatic embryo (SE)- and seedling-derived peanut plants grown in vitro (test tube-grown) and extra vitrum (soil-grown) are investigated using scanning electrochemical microscopy (SECM). This SECM imaging is performed in two different feedback modes, corresponding to oxygen evolution and chlorophyll distribution. More specifically, the oxygen evolution profiles of the in vitro leaves indicate important differences in leaf anatomy between the SE- and seedling-derived leaves. On the other hand, the chlorophyll distribution images show individual stomata of size ca. 27 +/- 5 mu m. Further studies on senescing (aged) leaves reveal interesting voltammograms that vary widely over the stomatal complexes and the surrounding tissues, probably due to the release of electroactive metabolites during chlorophyll breakdown when the leaves turn yellow. Thus, the present investigation could open up new opportunities for characterizing botanical systems using electroanalytical techniques. In addition, it could provide further insights into various areas of current relevance, including signal transduction, cell fate/differentiation and developmental biology.
Keywords: leaf senescence; oxygen evolution; photosynthesis; SECM; somatic embryogenesis; stomata

In situ synthesis of Pt nanoparticles in SBA-15 by encapsulating in modified template micelles: size restricted growth within the mesochannels - Prashar, Atul K.; Hodgkins, Robert P.; Kumar, Rajiv; Devi, R. Nandini (Journal of Materials Chemistry, 2008)
A truly in situ and simple method is developed for nanoparticle incorporation within the mesochannels of SBA-15 involving dispersion of metal precursors in surfactant-modified polymer micelles. The diffusion of the precursor within the micellar structure is aided by interaction with the cationic head group of the surfactant leading to a unique method to facilitate the formation of highly disperse, uniform nanoparticles molded by the walls of the mesochannels. The nanoparticle incorporated mesoporous material has a highly enhanced surface area and adsorption capabilities in comparison to its parent materials without any pore blockage which makes this method ideal for the preparation of nanocatalysts.

Inorganic-organic hybrid materials based on functionalized silica and carbon: a comprehensive understanding toward the structural property and catalytic activity difference over mesoporous silica and carbon supports - Bordoloi, Ankur; Mathew, Nevin T.; Lefebvre, F.; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2008)
Inorganic-organic hybrid materials based on functionalized silica and carbon were synthesized by anchoring molybdovanadophosphoric acid (H-5[PMo10V2O40]center dot 32.5H(2)O) onto amine-functionalized SBA-15, ethane-bridged SBA-15 and mesoporous carbon, respectively. Small angle X-ray diffraction, N-2 sorption analysis, HRTEM, SEM, IFT-IR, CP-MAS NMR were used to diagnose the mesoporous structure of inorganic-organic hybrid materials. The structural integrity of molybdovanadophosphoric acid has been found to be retained after immobilization over mesoporous materials. These inorganic-organic hybrid materials were tested in the environmentally friendly oxidation of 2-methylnaphthalene (2MN) with 30%, aqueous hydrogen peroxide. Molybdovanadophosphoric acid containing mesoporous organosilica hybrid material (ethane-bridged SBA-15) exhibited higher catalytic activities in the oxidation of 2MN to give a clean product 2-methy-1,4-naphthoquinone (menadione vitamin K3 precursor), because of the improved hydrophobicity of the material. The correlation between structural properties and catalytic activities of these hybrid materials has been well addressed in our present studies. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: 2-Methylnaphthalene; inorganic-organic hybrid materials; mesoporous carbon; mesoporous organosilica; Oxidation

Introduction to the density matrix renormalization group ansatz in quantum chemistry - Chan, Garnet Kin-Lic; Dorando, Jonathan J.; Ghosh, Debashree; Hachmann, Johannes; Neuscamman, Eric; Wang, Haitao; Yanai, Takeshi (Frontiers in Quantum Systems in Chemistry and Physics, 2008)
The Density Matrix Renormalisation Group (DMRG) is an electronic structure method that has recently been applied to ab-initio quantum chemistry. Even at this early stage, it has enabled the solution of many problems that would previously have been intractable with any other method, in particular, multireference problems with very large active spaces. Historically, the DMRG was not originally formulated from a wavefunction perspective, but rather in a Renormalisation Group (RG) language. However, it is now realised that a wavefunction view of the DMRG provides a more convenient, and in some cases more powerful, paradigm. Here we provide an expository introduction to the DMRG ansatz in the context of quantum chemistry.

Kinetics of PbCrO(4) nanorod growth by oriented attachment at the air-water interface - Hawaldar, Ranjit R.; Sathaye, Shivaram D.; Harle, Arti S.; Gholap, Ramkrishna S.; Patil, Kashinath R. (Journal of Physical Chemistry C, 2008)
Oriented attachment is a new way of crystal growth to transform preformed nanoparticles into hierarchical assemblies. Here, we demonstrate the use of liquid-liquid interfaces toward the formation of PbCrO(4) nanoparticles and their subsequent time-dependent self-assembly at the air-water interface into nanorods by oriented attachment. EDAX and XPS analysis indicate the formation of stoichiometric PbCrO(4). TEM studies at different stages of aging reveal that the transformation from nanoparticles to nanorods is kinetically governed. HRTEM analysis indicates nanorod growth along the [110] plane. UV-visible spectra reveal the presence of peaks at 425 and 515 nm for nanorods, while for the nanoparticle sample, a single peak at 425 urn is evident. As formation of ultrathin films over a large area (typically equal to or greater than 1 mu m x 1 mu m) concomitantly accompanies this approach, it can be extended to other materials as well for nanostructured device applications.

Liquid-phase synthesized mesoporous electrochemical supercapacitors of nickel hydroxide - Chang, Jinho; Park, Mira; Ham, Dukho; Ogale, S. B.; Mane, Rajaram S.; Han, Sung-Hwan (Electrochimica Acta, 2008)
Electrochemical supercapacitive (ES) properties of liquid-phase synthesized mesoporous (pore size distribution centered similar to 12 nm) and of 120 m(2)/g surface area nickel hydroxide film electrodes onto tin-doped indium oxide substrate are discussed. The amounts of inner and outer charges are calculated to investigate the contribution of mesoporous structure on charge storage where relatively higher contribution of inner charge infers good ion diffusion into matrix of nickel hydroxide. Effect of different electrolytes, electrolyte concentrations, deposit mass and scan rates on the current-voltage profile in terms of the shape and enclosed area is investigated. Specific capacitance of similar to 85 F/g at a constant current density of 0.03 A/g is obtained from the discharge curve. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: electrochemical supercapacitors; mesoporous structure; nickel hydroxide

Local electronic structure and magnetic properties of LaMn(0.5)Co(0.5)O(3) studied by x-ray absorption and magnetic circular dichroism spectroscopy - Burnus, T.; Hu, Z.; Hsieh, H. H.; Joly, V. L. Joseph; Joy, Pattayil Alias; Haverkort, M. W.; Wu, Hua; Tanaka, A.; Lin, H. -J.; Chen, C. T.; Tjeng, L. H. (Physical Review B, 2008)
We have studied the local electronic structure of LaMn(0.5)Co(0.5)O(3) using soft-x-ray absorption spectroscopy at the Co-L(3,2) and Mn-L(3,2) edges. We found a high-spin Co(2+)-Mn(4+) valence state for samples with the optimal Curie temperature. We discovered that samples with lower Curie temperatures contain low-spin nonmagnetic Co(3+) ions. Using soft-x-ray magnetic circular dichroism, we established that the Co(2+) and Mn(4+) ions are ferromagnetically aligned. We also revealed that the Co(2+) ions have a large orbital moment: morb/mspin approximate to 0.47. Together with model calculations, this suggests the presence of a large magnetocrystalline anisotropy in the material and predicts a nontrivial temperature dependence for the magnetic susceptibility.

Modeling of a fluidized bed propylene polymerization reactor operated in condensed mode - Utikar, Ranjeet P.; Harshe, Yogesh M.; Mehra, Anurag; Ranade, Vivek V. (Journal of Applied Polymer Science, 2008)
The gas-phase polymerization of propylene is one of the most widely accepted and commercially used processes for the manufacture of polypropylene (PP). Because of the highly exothermic nature of polymerization reactions, temperature runaway and subsequent polymer melting and agglomeration may occur, and the reactor has to be operated in a small operating window for safety. The addition of liquid monomer for heat removal (condensed mode) broadens the operating window and can substantially increase (by 50-100%) the capacity of given reactor hardware. This article describes the extension of a comprehensive mathematical model for the simulation of fluidized bed PP reactors to include the condensed mode of operations. The model is used to determine the influence of the operating parameters on the polymer properties and particle size distribution. The model is also used to determine the effects of two active sites and the reaction kinetics on macroscopic variables. The developed framework is useful for simulating multimonomer, multisite Ziegler-Natta-type olefin fluidized bed polymerization reactors operated under condensed mode. (C) 2008 Wiley Periodicals, Inc. J Appl Polym Sci 108: 2067-2076, 2008.
Keywords: Modeling; Polyolefins; Ziegler-Natta polymerization

Molecular association via halogen bonding and other weak interactions in the crystal structures of 11-bromo-12-oxo-5 beta-cholan derivatives - Salunke, Deepak B.; Hazra, Braja G.; Gonnade, Rajesh G.; Pore, Vandana S.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Methyl 3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 2, methyl 11 alpha-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 3, methyl 11 beta-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 4 and methyl 11,11-dibromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 5 were synthesized. The crystal structures of these molecules were resolved to study the effect of bulky bromine atom in the steroid skeleton of cholic acid with different stereo-chemical orientations at C-11 on the two-dimensional arrangement of molecules and solid-state properties. All the molecules associate only via weak intermolecular interactions in their crystal structures, notable one being the Halogen Bonded assembly (C-Br center dot center dot center dot O) in 5. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 11-Bromosteroids; Cholic acid; crystal structure; Halogen bonding

Multipoint anchoring of the [2.2.2.2]metacyclophane motif to a gold surface via self-assembly: coordination chemistry of a cyclic tetraisocyanide revisited - Toriyama, Masaharu; Maher, Tiffany R.; Holovics, Thomas C.; Vanka, Kumar; Day, Victor W.; Berrie, Cindy L.; Thompson, Ward H.; Barybin, Mikhail V. (Inorganic Chemistry, 2008)
A one-pot transformation of bis(2-isocyano-3-methylphenyl)ethane affords gram quantities of 8,16,24,32-tetraisocyano[2.2.2.2]metacyclophane ( 3). The solid state structure of 3 is remarkably close to the lowest energy conformation found on the potential energy landscape for 3 by DFT. In solution, the structure of metacyclophane 3 is mobile but can be locked in a rectangular gauche- anti- gauche- anti conformation by coordination of the isocyanide substituents to the [W(CO) 5] units to give [M] 4(mu 4-eta (1):eta (1):eta (1):eta (1)- 3) ( 5). The tetranuclear [M] 4(mu 4-eta (1):eta (1):eta (1):eta (1)- 3) motif featured in crystallographically characterized 5 may be present in several insoluble complexes of 3 previously described as mononuclear eta (4) species. A self-assembled monolayer of metacyclophane 3 is formed upon exposing a solution of 3 to the gold(111) surface with no precautions to exclude air or light. The monolayer nature of the film was confirmed by optical ellipsometry. The isocyanide stretching band for 3 shifts from 2119 cm (-1) in solution to 2175 cm (-1) upon chemisorption to metallic gold. The FTIR spectrum of the film indicates interaction of 3 with the gold surface via all four of its isocyanide anchors. No gold-facilitated oxidation of the -NC junctions was detected under ambient conditions. The energy cost associated with accessing the conformations of 3 suitable for mu 4-eta (1):eta (1):eta (1):eta (1) interaction of the molecule with the Au(111) surface is under 8 kcal/mol, a value that can be easily offset by formation of a gold-isocyanide bond. Two different mu 4-eta (1):eta (1):eta (1):eta (1) coordination arrangements of 3 with respect to gold atoms on the (111) face of the fcc Au lattice are suggested.

New route for preparation of luminescent mercaptoethanoate capped cadmium selenide quantum dots - Wankhede, Manoj E.; Inamdar, Shaukatali N.; Deshpande, Aparna; Thete, Aniket R.; Pasricha, Renu; Kulkarni, Sulabha K.; Harani, Santosh K. (Bulletin of Materials Science, 2008)
We report a synthesis of cadmium selenide quantum dots (Q-CdSe) by refluxing a mixture of cadmium acetate, selenium powder, sodium sulfite and 2-mercaptoethanol in N,N'-dimethyl formamide (DMF)/water solution. X-ray and electron diffractions suggest the formation of hexagonal phase of size quantized CdSe. Based on TEM analysis, the formation of nanoparticles with an average diameter of 3.5 +/- 0.5 nm is inferred. Their sols in DMF and dimethyl sulphoxide (DMSO) gave characteristic absorption peaks at 300 nm and 327 nm, which is attributed to the formation of high quality, size quantized CdSe particles. Extracted particles from the sol were readily redispersed in DMF and DMSO, which were diluted further with water without losing their optical and colloidal properties. FTIR spectroscopy suggested the formation of 2-mercaptoethanol thiolate on the particle surface, with free -OH groups available for linkage. Sols in DMSO and their solutions in water displayed an intense photoluminescence (PL).
National Review and Coordination Meeting on Nanoscience and Nanotechnology, Hyderabad, INDIA, 2007
Keywords: chalcogenides; Chemical synthesis; photoluminescence; semiconductor quantum dots

Non-phosgene route for the synthesis of methyl phenyl carbamate using ordered AISBA-15 catalyst - Lucas, Nishita; Amrute, Amol P.; Palraj, K.; Shanbhag, G. V.; Vinu, Ajayan; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
Methyl phenyl carbamate (MPC) has been synthesized Under liquid phase conditions from dimethyl carbonate and aniline by using mesoporous AISBA-15 catalyst. The catalyst with different Si/Al ratio was synthesized by isomorphous Substitution of aluminium into the framework of siliceous SBA-15. The structural integrity of the catalyst system was diagnosed with the help of various characterization techniques Such as X-ray diffraction, Surface analysis, and the acidity measurement has been done by TPD using ammonia as probe molecule. AISBA-15 (Si/Al = 10) exhibited highest catalytic activity in the synthesis of MPC under the reaction Conditions Studied. The effect of parameters Such as molar ratio of reactants, catalyst concentration. reaction temperature and time on the conversion of aniline was investigated. The results demonstrated that an aniline conversion of 99% and MPC selectivity of 71% were achieved when the reaction was carried out at 100 C, DMC to aniline mole ratio of 10 with 5% of catalyst (wt% of total reaction mixture) for 3 h. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: amines; Dimethyl carbonate; Mesoporous AISBA-15; Methoxycarbonylation; Methyl phenyl carbamate

Novel three dimensional cubic Fm3m mesoporous aluminosilicates with tailored cage type pore structure and high aluminum content - Srinivasu, Pavuluri; Alam, Sher; Balasubramanian, Veerappan V.; Velmathi, Sivan; Sawant, Dhanashri P.; Boehlmann, Winfred; Mirajkar, Subhash P.; Ariga, Katsuhiko; Halligudi, Shivappa B.; Vinu, Ajayan (Advanced Functional Materials, 2008)
Novel three dimensional cubic Fm3m mesoporous aluminosilicates (AIKIT-5) with very high structural order and unprecedented loadings of Al in the silica framework have been successfully prepared for the first time by using non ionic surfactant as a template in a highly acidic medium. The obtained materials have been unambiguously characterized in detail by several sophisticated techniques such as XRD, N, adsorption, HRTEM, HRSEM, EDS, elemental mapping, Al-27 MAS NMR, and NH3-TPD. We also demonstrate that the nature, and the amount of Al incorporation in the silica framework can easily be controlled by simply varying the n(H2O)/n(HCl) and the n(Si)/n(Al), ratios, and the Al sources in the synthesis gel. Among the Al sources examined, the Al isopropoxide (AiPr) is superior over other Al sources. Al-27 MAS NMR results reveal that the amount of tetrahedral Al in the framework can be controlled by simply adjusting the nSi/nAl ratio in the synthesis gel, which increases with increasing the Al incorporation. One of the interesting findings in the work is the increase of the specific surface area, specific pore volume and the pore diameter of AIKIT-5 with increasing the Al incorporation in the silica framework (up to n(Si)/n(Al), ratio of 10) while retaining the well-ordered three dimensional cage type porous structure, and the mechanism for the unusual behavior has been discussed in detail. Finally, the acidity and the catalytic activity in the acetylation of veratrole of the AIKIT-5 catalysts have been studied and the results have been compared with the several zeolites catalysts. Among the catalysts examined, AIKIT-5(10) is found to be superior over the zeolites catalysts such as mordenite, zeolite H-Y, zeolite H-beta, and ZSM-5.

Orbital optimization in the density matrix renormalization group, with applications to polyenes and ss-carotene - Ghosh, Debashree; Hachmann, Johannes; Yanai, Takeshi; Chan, Garnet Kin-Lic (Journal of Chemical Physics, 2008)

[Ru(salen)(NO)] complex encapsulated in mesoporous SBA-16 as catalyst for hydrogenation of ketones - Bordoloi, Ankur; Amrute, Amol P.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
SBA-16 mesoporous silica with cubic lm3m structure was synthesized using Pluronic F127 poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer (EO106PO70EO106) and it blends with Pluronic P123 triblock copolymer (EO20PO70EO20) as supramolecular templates. The resulting material was used for encapsulating [Ru(salen)(NO)] complex and used in the hydrogenation of ketones to the corresponding alcohols. The pore entrance size of SBA-16 was precisely tailored by silylation with diphenyldichlorosilane to trap [Ru(salen)(NO)] complex in the cage of SBA-16. Small angle XRD, N-2 sorption measurements, UV-Vis and FT-IR analysis evidences the structural integrity of mesoporous silica as well as the complex. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Encapsulation; Hydrogenation; Ketones; SBA-16; [Ru(salen)(NO)] complex

Sequence-specific unusual (1 -> 2)-type helical turns in alpha/beta-hybrid peptides - Prabhakaran, Panchami; Kale, Sangram S.; Puranik, Vedavati G.; Rajamohanan, P. R.; Chetina, Olga; Howard, Judith A. K.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2008)
This article describes novel conformationally ordered (alpha/beta-hybrid peptides consisting of repeating L-proline-anthranilic acid building blocks. These oligomers adopt a compact, right-handed helical architecture determined by the intrinsic conformational preferences of the individual amino acid residues. The striking feature of these oligomers is their ability to display an unusual periodic pseudo beta-turn network of nine-membered hydrogen-bonded rings formed in the forward direction of the sequence by 1–>2 amino acid interactions both in solid-state and in solution. Conformational investigations of several of these oligomers by single-crystal X-ray diffraction, solution-state NMR, and ab initio MO theory suggest that the characteristic steric and dihedral angle restraints exerted by proline are essential for stabilizing the unusual pseudo beta-turn network found in these oligomers. Replacing proline by the conformationally flexible analogue alanine (Ala) or by the conformationally more constrained alpha-amino isobutyric acid (Aib) had an adverse effect on the stabilization of this structural architecture. These findings increase the potential to design novel secondary structure elements profiting from the steric and dihedral angle constraints of the amino acid constituents and help to augment the conformational space available for synthetic oligomer design with diverse backbone structures.

Sol-gel synthesis of MoO(3)/SiO(2) composite for catalytic application in condensation of anisole with paraformaldehyde - Amrute, Amol P.; Bordoloi, Ankur; Lucas, Nishita; Palraj, K.; Halligudi, Shivaraj B. (Catalysis Letters, 2008)
MoO(3)/SiO(2) composite with varying amounts of MoO(3) loading (1-20 wt.%) were prepared by sol-gel method and calcined at 500 C. These catalysts were employed for the liquid phase condensation of anisole with paraformaldehyde. All the catalysts were characterized by N(2) sorption, XRD, and NH(3)-TPD. The activities of synthesized MoO(3)/SiO(2) catalysts were compared with p-toluene sulfonic acid (p-TSA), the most frequently used catalyst for the condensation reactions, and with a supported metal oxide (WO (x) /ZrO(2)). Under the similar reaction conditions, synthesized 10 wt.% MoO(3)/SiO(2) catalyst calcined at 500 C was found to be the most active in the condensation of anisole with paraformaldehyde.
Keywords: 4; 4'-Dimethoxydiphenylmethane; Condensation of anisole; MoO(3)/SiO(2) composites; Paraformaldehyde; Sol-gel synthesis

Studies in structural characterization and correlation with the catalytic activity of an efficient and stable WOx/SBA-15 nanocomposite catalyst - Bordoloi, Ankur; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A new WOx/SBA-15 nanocomposite catalyst system was developed by hydrothermal synthesis. The material was characterized by X-ray diffraction, high-resolution transmission electron microscopy, sorption analysis, FT-IR, CP-MAS NMR, XPS, and energy-dispersive X-ray analysis. Various types of aromatic and aliphatic sulfides were selectively oxidized to sulfoxides in good to excellent yields without becoming overoxidized to the sulfones using 70% aq. tert-butyl hydrogen peroxide in the presence of nanocomposite catalyst at room temperature. The catalyst could be easily recovered and reused for at least eight reaction cycles under the reaction conditions described here with no significant loss of reactivity. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: catalytic oxidation; mesoporous materials; Sulfides; Sulfoxides; tungsten oxide nanocluster

Study of a laboratory-scale froth flotation process using artificial neural networks - Kalyani, V. K.; Pallavika; Chaudhuri, Sanjay; Charan, T. Gouri; Haldar, D. D.; Kamal, K. P.; Badhe, Yogesh P.; Tambe, S. S.; Kulkarni, B. D. (Mineral Processing and Extractive Metallurgy Review, 2008)
A three-layer feed-forward artificial neural network (ANN) model, trained using the error back propagation algorithm, has been established to simulate the froth flotation process for the beneficiation of coal fines. The network model validates the experimentally observed qualitative and quantitative trends. The optimal model parameters in terms of network weights have been estimated and can be used to compute the parameters of the coal flotation process over wide-ranging experimental conditions.
Keywords: back propagation algorithm; froth flotation; laboratory-scale; neural network

Sulfur nanoparticles synthesis and characterization from H2S gas, using novel biodegradable iron chelates in w/o microemulsion - Deshpande, Aniruddha S.; Khomane, Ramdas B.; Vaidya, Bhalchandra K.; Joshi, Renuka M.; Harle, Arti S.; Kulkarni, Bhaskar D. (Nanoscale Research Letters, 2008)
Sulfur nanoparticles were synthesized from hazardous H2S gas using novel biodegradable iron chelates in w/o microemulsion system. Fe3+-malic acid chelate (0.05 M aqueous solution) was studied in w/o microemulsion containing cyclohexane, Triton X-100 and n-hexanol as oil phase, surfactant, co-surfactant, respectively, for catalytic oxidation of H2S gas at ambient conditions of temperature, pressure, and neutral pH. The structural features of sulfur nanoparticles have been characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), energy dispersive spectroscopy (EDS), diffused reflectance infra-red Fourier transform technique, and BET surface area measurements. XRD analysis indicates the presence of alpha-sulfur. TEM analysis shows that the morphology of sulfur nanoparticles synthesized in w/o microemulsion system is nearly uniform in size (average particle size 10 nm) and narrow particle size distribution (in range of 5-15 nm) as compared to that in aqueous surfactant systems. The EDS analysis indicated high purity of sulfur (> 99%). Moreover, sulfur nanoparticles synthesized in w/o microemulsion system exhibit higher antimicrobial activity (against bacteria, yeast, and fungi) than that of colloidal sulfur.
Keywords: Antimicrobial activity; H2S gas; iron chelates; sulfur nanoparticles; w/o microemulsion

Synthesis and antimicrobial activity of beta-lactam-bile acid conjugates linked via triazole - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Chavan, Pradnya S.; Deshpande, Mukund V. (Bioorganic & Medicinal Chemistry Letters, 2008)
Synthesis of novel 1,2,3-triazole-linked beta-lactam-bile acid conjugates 17-24 using 1,3-dipolar cycloaddition reaction of azido beta-lactam and terminal alkyne of bile acids in the presence of Cu( I) catalyst ( click chemistry) have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and moderate antibacterial activity against all the tested strains. (c) 2008 Elsevier Ltd. All rights reserved.

Synthesis and biological evaluation of bile acid dimers linked with 1,2,3-triazole and bis-beta-lactam - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit; Gonnade, Rajesh G. (Organic & Biomolecular Chemistry, 2008)
We report herein the synthesis and biological evaluation of bile acid dimers 11-18 linked through 1,2,3-triazole and bis-beta-lactam. The dimers 11-18 were synthesized using 1,3-dipolar cycloaddition reaction of diazido bis-beta-lactams 3, 4 and terminal alkynes 7-10 derived from cholic acid/deoxycholic acid in the presence of Cu(I) catalyst (click chemistry). These novel molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal as well as antibacterial activity against all the tested fungal and bacterial strains. Moreover, their in vitro cytotoxicities towards HEK-293 and MCF-7 cells were also established.

Synthesis and self-assembling properties of alpha,omega-hydroxy-poly(ethylene oxide) end-capped with 1-isocyanato-3-pentadecylcyclohexane - Kadam, Vijay S.; Badiger, Manohar V.; Wadgaonkar, Prakash P.; Ducouret, Guylaine; Hourdet, Dominique (Polymer, 2008)
A novel hydrophobic compound, 1-isocyanato-3-pentadecylcyclohexane (PDC) issued from a renewable resource material (Cashew Nut Shell Liquid), is used to end-cap poly(ethylene oxide) (PEO) of different molecular weights. The synthesis, characterization and self-assembling properties of these new associating polymers are reported. In aqueous solution, PDC modified PEOs self-associate into micellar structures which are characterized by neutron scattering. Using a star-polymer model with sticky hard sphere interactions, it is shown that the characteristics of the micelles mainly depend on the size of the PEO chain. In the case of PDC stickers, the aggregation number decreases from 25 to 17 with increasing molecular weight of PEO, from 10 to 20 kg/mol, respectively. The temperature directly impacts the interaction potential between the hydrophilic coronas of PEO which become less repulsive with increasing temperature. Rheological measurements, performed in dilute solution, clearly demonstrate that PEO micelles self-associate into open supramolecular structures. The correlation length of these loose clusters increases with polymer concentration and the hierarchical self-assembly follows the rules of the percolation theory. The sol/gel transition takes place at the overlap concentration of clusters. In semi-dilute solution, the viscoelastic properties of PDC end-capped PEOs are well described by the Maxwell model with a single relaxation mode. The characteristic time of the network follows an Arrhenius temperature dependence with an activation energy of 70 kJ/mol, in very good agreement with the size of PDC stickers. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Associating polymer; Hydrophobically end-capped; poly(ethylene oxide); Star micelles

Synthesis, characterization of chemically deposited indium selenide thin films at room temperature - Asabe, M. R.; Chate, P. A.; Delekar, S. D.; Garadkar, K. M.; Mulla, Imtiaz S.; Hankare, P. P. (Journal of Physics and Chemistry of Solids, 2008)
Polycrystalline In2Se3 semiconducting thin films were prepared by using relatively simple chemical bath deposition method at room temperature by the reaction between indium chloride, tartaric acid, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium. Various preparative conditions of thin film deposition are outlined. The as grown films were found to be transparent, uniform, well adherent and red in color. The films were characterized using X-ray diffraction (XRD), scanning electron microscopy, atomic absorption spectroscopy and energy dispersive atomic X-ray diffraction (EDAX). The XRD analysis of the film showed the presence of polycrystalline nature with hexagonal crystal structure. SEM study revels that the grains are homogenous, without cracks or pinholes and well covers the glass substrate. The optical absorption and electrical conductivity was measured. The direct optical band gap value for the films was found to be of the order of 2.35eV at room temperature and have specific electrical conductivity of the order of 10(-2) (Omega cm)(-1) showing n-type conduction mechanism. The utility of the adapted technique is discussed from the view-point of applications considering the optoelectric and structural data. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Semiconductor

Synthesis of 1,2,3-triazole and 1,2,3,4-tetrazole-fused glycosides and nucleosides by an intramolecular 1,3-dipolar cycloaddition reaction - Anegundi, Ramakrishna I.; Puranik, Vedavati G.; Hotha, Srinivas (Organic & Biomolecular Chemistry, 2008)
Various 1,2,3-triazole and 1,2,3,4-tetrazole fused multi-cyclic compounds were synthesized from carbohydrate derived azido-alkyne and azido-cyanide substrates. The acid sensitive 1,2-O-isopropylidene group of the furanosyl sugar was utilized for diversification to glycosides and nucleosides under Fischer glycosidation and Vorbruggen's conditions, respectively.

Synthesis of biodiesel over zirconia-supported isopoly and heteropoly tungstate catalysts - Sunita, G.; Devassy, Biju M.; Vinu, Ajayan; Sawant, Dhanashri P.; Balasubramanian, Veerappan V.; Halligudi, Shivappa B. (Catalysis Communications, 2008)
The liquid-phase synthesis of biodiesel by transesterification of sunflower oil with methanol is carried out by using zirconia-supported isopoly and heteropoly tungstates (HPAs) as catalysts. The isopoly and heteropoly tungstate catalysts were prepared by suspending zirconium oxyhydroxide in water/methanol solution of ammonium metatungstate/silicotungstic acid, phosphotungstic acid (WO3/HPA loading, 15%,,) followed by drying and calcination at 750 degrees C. The catalysts were characterized by XRD, Raman spectroscopy, IR spectroscopy, NH3-TPD and FTIR pyridine adsorption spectroscopy. XRD results indicate that the presence of isopoly and heteropoly tungstates stabilizes ZrO2 in tetragonal phase. Raman and IR spectra of the catalysts show that tungstate species exist as zirconia-anchored octahedral mono-oxotungstate. The acidity measurements by NH3-TPD and FTIR pyridine adsorption spectroscopy show that zirconia-supported phosphotungstate has the highest total acidity and zirconia-supported isopoly tungstate has the highest Bronsted acidity. The zirconia-supported isopoly tungstate shows superior catalytic performance compared to zirconia-supported heteropoly tungstate catalysts. Under the reaction conditions of 200 degrees C and methanol/oil molar ratio 15, 15% WO3/ZrO2 calcined at 750 degrees C gave 97% conversion of oil. This catalyst also efficiently catalyzes methanolysis of other vegetable oils like mustard oil and sesame oil. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Biodiesel; phosphotungstic acids; Silicotungstic acid; transesterification; tungsten oxide; Zirconia

Synthesis of chimeric tetrapeptide-linked cholic acid derivatives: impending synergistic agents - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Dodd, Robert H.; Thierry, Josiane; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit (Bioorganic & Medicinal Chemistry Letters, 2008)
Tetrapeptides derived from glycine and beta-alanine were hooked at the C-3 beta position of the modified cholic acid to realize novel linear tetrapeptide-linked cholic acid derivatives. All the synthesized compounds were tested against a wide variety of microorganisms (Gram-negative bacteria, Gram-positive bacteria and fungi) and their cytotoxicity was evaluated against human embryonic kidney (HEK293) and human mammary adenocarcinoma (MCF-7) cell lines. While relatively inactive by themselves, these compounds interact synergistically with antibiotics such as fluconazole and erythromycin to inhibit growth of fungi and bacteria, respectively, at 1-24 mu g/mL. The synergistic effect shown by our novel compounds is due to their inherent amphiphilicity. The fractional inhibitory concentrations reported are comparable to those reported for Polymyxin B derivatives. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antimicrobial activity; Cholic acid; Cytotoxicity; Synergism; Tetrapeptide

Synthesis of novel 2-alkyl substituted oleobenzimidazole derivatives using ethylene glycol as solvent - Hosamani, K. M.; Hiremath, V. B.; Keri, R. S.; Harisha, R. S.; Halligudi, Shivaraj B. (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2008)
The objective of this research was to conduct constructive organic chemistry by using ethylene glycol as an efficient solvent and to achieve yields that were comparable to or better than those in other media. The reaction parameters, such as temperature (150-200 degrees C), density, and reaction time (6 h), have been systematically studied to understand whether ethylene glycol is as an efficient solvent and can have a positive effect on the chemistry with good yields. By tuning the parameters, the yields have been optimized to around 70%-80%. Thus, a new class of 2-alkyl substituted oleo-benzimidazole derivatives have been synthesized and characterized by FTIR, (1)H NMR, (13)C NMR, MS, and elemental analysis.
Keywords: ethylene glycol; oleo-benzimidazole derivatives; oleochemistry; unusual fatty acids

Titania supported silicotungstic acid: an efficient solid acid catalyst for veratrole acylation - Waghmare, Nilesh G.; Kasinathan, Palraj; Amrute, Amol P.; Lucas, Nishita; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Titania supported silicotungstic acid (STA) with different STA loading (10-25 wt%) and calcination temperature (650-750 degrees C) were prepared by wet impregnation method. The catalysts have been represented by a general formula xSTiO(2)y (where x denotes wt%, S denotes STA and y denotes calcination temperature in degrees C). These catalysts were characterized by techniques such as X-ray diffraction, surface analysis, FTIR-pyridine and TPD-NH(3) and were used as heterogeneous solid acid catalysts in the liquid phase acylation of veratrole with acetic anhydride (Ac(2)O). It was found that 20STiO(2)700 gave the highest activity in acylation reaction due to its highest acidity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acetic anhydride; Acylation; Silicotungstic acid; titania; veratrole

Tunable surface modification of silica nanoparticles through `click' chemistry - Chandran, S. Prathap; Hotha, Srinivas; Bhagavatula L. V. Prasad (Current Science, 2008)
Tuning the surface functionality of silica nanoparticles through a `click' chemistry-based protocol is demonstrated. Pyrene, a fluorophore that displays excimer emission specifically at higher density/concentration is chosen for highlighting the fidelity of surface functionalization. The UV-visible absorbance of the pyrene chromophore capping the nanoparticle is used to determine the amount of pyrene units present on the surface of a silica nanoparticle.
Keywords: pyrene; silica nanoparticles; surface functionality; `Click' chemistry

XPS and AFM investigations on silver-based photoimageable thick film systems - Umarji, Govind; Ketkar, Supriya; Hawaldar, Ranjit R.; Gosavi, Suresh W.; Patil, Kashinath; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Microelectronics International, 2008)
Purpose - The purpose of this paper is to ascertain chemical changes occurring at various stages involved in processing of silver-based photoimageable thick films; and to determine ensuing topographical features which other wise appeared to be hindered in 2D scanning electron microscopy. Design/methodology/approach - Surface sensitive techniques, viz. X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM) were used. Findings - Interfacial adhesion of silver film with substrate (Al(2)O(3)) was specifically looked into with respect to role played by photoimaging (before and after exposure to ultra-violet light). XPS results revealed occurrence of subtle chemical changes in terms of unsaturation to saturation in C-C bonding and also an interesting C-Al bonding which presumably improves mechanical adhesion of unfired film with the alumina substrate. AFM was carried out to examine the surface roughness, particle size, and microstructure of film which are very important from the standpoint of high-frequency applications. Originality/value - Surface sensitive techniques like XPS and AFM were exclusively used in order to characterize silver-based photoimageable thick films.
Keywords: microscopy; Silver; thick film circuits; X-rays

Activity and selectivity behavior of 1,2-epoxyethylbenzne hydrogenation in carbon dioxide solvent - Rode, Chandrashekhar V.; Hiyoshi, Norihito; Mine, Eiichi; Shirai, Masayuki (Industrial & Engineering Chemistry Research, 2009)
Catalytic hydrogenation of 1,2-epoxyethylbenzene to 2-phenylethanol over charcoal-supported noble metal in carbon dioxide was studied, and the results were compared with those in heptane and methanol. Charcoal-supported palladium and platinum (Pd/C and Pt/C) catalysts were active metal species for the hydrogenation in solvents. The order of activities over palladium and platinum was heptane < carbon dioxide < methanol; however, the formation of dehydroxylated byproduct was suppressed in carbon dioxide solvent. Negative carbon dioxide pressure effect was observed over the Pd/C and Pt/C catalysts in the carbon dioxide solvent.

Challenges associated with metal chelation therapy in alzheimer's disease - Hegde, Muralidhar L.; Bharathi, P.; Suram, Anitha; Venugopal, Chitra; Jagannathan, Ramya; Poddar, Pankaj; Srinivas, Pullabhatla; Sambamurti, Kumar; Rao, Kosagisharaf Jagannatha; Scancar, Janez; Messori, Luigi; Zecca, Luigi; et al. (Journal of Alzheimers Disease, 2009)
A close association between brain metal dishomeostasis and the onset and/or progression of Alzheimer's disease ( AD) has been clearly established in a number of studies, although the underlying biochemical mechanisms remain obscure. This observation renders chelation therapy an attractive pharmacological option for the treatment of this disease. However, a number of requirements must be fulfilled in order to adapt chelation therapy to AD so that the term ``metal targeted strategies'' seems now more appropriate. Indeed, brain metal redistribution rather than brain metal scavenging and removal is the major goal of this type of intervention. The most recent developments in metal targeted strategies for AD will be discussed using, as useful examples, clioquinol, curcumin, and epigallocatechin, and the future perspectives will also be outlined.
Keywords: Alzheimer's disease; clioquinol; cuprizone; metal dishomeostasis; metal ions; nanomedicine; Parkinson's disease; polyphenols

Chemical bath deposition of CdS quantum dots on vertically aligned ZnO nanorods for quantum dots-sensitized solar cells - Lee, Wonjoo; Min, Sun Ki; Dhas, Vivek V.; Ogale, Satishchandra B.; Han, Sung-Hwan (Electrochemistry Communications, 2009)
Formation of US quantum dots (Q dots) on the vertically aligned ZnO nanorods electrode was carried out by chemical bath deposition. The diameter and thickness of ZnO nanorods are similar to 100-150 nm and similar to 1.6 mu m, respectively, and CdS Q dots on ZnO nanorods have a diameter of smaller than 15 nm. In application of the Q dots-sensitized solar cells, composite film exhibited a power conversion efficiency of 0.54% under air mass 1.5 condition (80 mW/cm(2)), and incident-photon-to-current conversion efficiency showed 18.6%. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical bath deposition; Photosensitization; quantum dots; solar cells; Wet-chemical process

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia

Concurrent In-situ formation of Ag/Ag2S nanoparticles in polymer matrix by facile polymer-inorganic solid state reaction - Waghmare, Sujata; Shinde, Manish; Gholap, Ramkrishna S.; Rao, N. Koteswara; Hawaldar, Ranjit R.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Journal of Nano Research, 2009)
We herein report the feasibility of polymer-inorganic solid-state reaction route for simultaneous in situ generation of Ag & Ag2S nanostructures in polymer network wherein an engineering thermoplastic, polyphenylene sulphide (PPS), itself acts as a chalcogen source as well as a stabilizing matrix for the resultant nanoproducts. Typical solid-state reaction was accomplished by simply heating the physical admixture of the two reactants i.e. AgNO3 and PPS by varying molar ratios mainly 1:1, 1:5, 1:15, 1:20, at the crystalline melting temperature (285 degrees C) of PPS. The synthesized nanoparticles were characterized by various physico-chemical techniques like X-ray Diffractometry, Scanning Electron Microscopy equipped with EDAX, Transmission Electron Microscopy and UV-Visible spectroscopy. The prima facie observations suggest the effective formation and subsequent entrapment of mainly nanocrystalline metallic silver (fcc) in PPS matrix for all the molar ratios chosen for the reaction. Additionally, simultaneous occurrence of nanocrystalline Ag2S (monoclinic phase) is also noticed in case of heated admixture of AgNO3: PPS with equimolar ratio. The TEM analysis reveals nanoscale polydispersity (5nm to 70nm) and prevalence of mainly spherical morphological features in all the cases with occasional indications of triangular and hexagonal morphological features depending upon the reaction molar ratio.
Keywords: Ag; Ag2S; Nanoparticles; Polymer inorganic solid -state reaction; Thermoplastic polymer matrix

Continuous hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-Methylphenol) in a fixed bed reactor - Garade, Ajit C.; Hengne, Amol M.; Deshpande, Tushar N.; Shaligram, Sayali V.; Shirai, Masayuki; Rode, Chandrashekhar V. (Journal of Chemical Engineering of Japan, 2009)
{Catalytic activity of various solid acid catalysts is evaluated for the continuous hydroxyalkylation of p-cresol to [

Copper-catalyzed synthesis of 2-unsubstituted, n-substituted benzimidazoles - Hirano, Keiichi; Biju, Akkattu T.; Glorius, Frank (Journal of Organic Chemistry, 2009)
An efficient copper-catalyzed intramolecular arylation of formamidines forming 2-unsubstituted benzimidazoles in excellent yields is reported. Sixteen examples bearing sterically demanding substituents on nitrogen like Mes, 2,6-diisopropylphenyl, or 2-tert-butylphenyl and tolerating various functional groups demonstrate the utility of this method.

Dendritic effect of ligand-coated nanoparticles: enhanced apoptotic activity of silica-berberine nanoconjugates - Halimani, Mahantappa; Chandran, S. Prathap; Kashyap, Sudhir; Jadhav, V. M.; Bhagavatula L. V. Prasad; Hotha, Srinivas; Maiti, Souvik (Langmuir, 2009)
We describe the synthesis and biological characterization of a novel prototype, namely, silica nanoconjugates bearing a covalently linked berberine, a plant alkaloid known to have antiproliferative activity. The effect of synthesized nanoconjugates on cell proliferation, the cell cycle profile, and apoptosis in the human cervical carcinoma cell line (HeLa), human hepatocellular liver carcinoma cell line (HepG2), and human embryonic kidney (HEK) 293T cell line has been studied and compared with the results obtained for free berberine. Our results show that all the nanoconjugates display higher antiproliferative activity than free berberine. The ability of these nanoconjugates to inhibit cellular proliferation is mediated by the cell cycle arrest at the G1 phase. Moreover, silica nanoconugates caused selective apoptotic arrest with a higher efficiency than free berberine followed by apoptotic cell death as shown by quantitative fluorescence-activated cell sorting analyses. Efficiency of the nanoconjugates increases upon an increase in the linker chain length, demonstrating the distinct role of the spacer chain that conjugates nanoparticles and ligands. The actual reason to show enhanced efficiency by the nanoconjugates has not been elucidated in the present study; however, we hypothesize that an increase in local concentration due to the confinement of a ligand on the nanosurface (''dendritic'' effect) might have led to the observed effect.

Effect of sintering temperature and thermoelectric power studies of the system MgFe2-xCrxO4 - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Gavali, L. V.; Sasikala, R.; Mulla, Imtiaz S. (Solid State Sciences, 2009)
Mixed metal oxides showing the spinel structure exhibit interesting structural and electrical properties. Substances with specific compositions in the system MgFe2-xCrxO4 were synthesized by the simple co-precipitation method and have been investigated by X-ray diffraction (XRD) and scanning electron microscope (SEM) to study the effect of temperature on the size of particles and grains. The infrared spectrum shows, two strong bands around 600 and 500 cm(-1). An elemental composition of one of the samples, MgFeCrO4 was found by energy dispersive X-ray spectroscopy (EDS). The thermoelectric power measurements carried out from room temperature to 500 degrees C, show both n-type and p-type behavior. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: synthesis; Temperature effect; Thermoelectric studies

Enhanced conversion efficiency in dye-sensitized solar cells based on hydrothermally synthesized TiO2-MWCNT nanocomposites - Muduli, Subas; Lee, Wonjoo; Dhas, Vivek V.; Mujawar, Sarfraj; Dubey, Megha; Vijayamohanan, K.; Han, Sung-Hwan; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2009)
A 50 % enhancement in the conversion efficiency (4.9-7.37 %) is realized in dye-sensitized solar cells Using hydrothermally synthesized TiO2-multiwalled carbon nanotube (MWCNT) nanocomposites as compared to hydrothermally synthesized TiO2 without MWCNT and Degussa P25. Several characterizations have been employed to reveal the nature of the modification imparted to the MWCNTs under hydrothermal processing conditions and the resulting TiO2-MWCNT conjugation through -COOH groups. Efficient charge transfer In the nanocomposite and efficient electron transport by MWCNT (significantly higher Incident-photon-to-current conversion efficiency) are suggested to be the possible reasons for the enhancement.
Keywords: Carbon nanotubes; charge transfer; Dye-sensitized solar cells; Hybrid composite; hydrothermal

Exploration of click reaction for the synthesis of modified nucleosides as chitin synthase inhibitors - Chaudhary, Preeti M.; Chavan, Sayalee R.; Shirazi, Fazal; Razdan, Meenakshi; Nimkar, Prachi; Maybhate, Shailaja P.; Likhite, Anjali P.; Gonnade, Rajesh G.; Hazra, Braja G.; Deshpande, Mukund V.; Deshpande, Sunita R. (Bioorganic & Medicinal Chemistry, 2009)
Click reaction approach toward the synthesis of two sets of novel 1,2,3-triazolyl linked uridine derivatives 19a-19g and 21a-21g was achieved by Cu(I)-catalyzed 1,3-dipolar cycloaddition of 5'-azido-5'-deoxy-2',3'-O-(1-methylethylidene) uridine (17) with propargylated ether of phenols 18a-18g and propargylated esters 20a-20g. Structure of one of the representative compound 19d was unambiguously confirmed by X-ray crystallography. Chitin synthase inhibition study of all these compounds 19a-19g and 21a-21g was carried out to develop antifungal strategy. Compounds 19d, 19e, 19f, and 21f were identified as potent chitin synthase inhibitors by comparing with nikkomycin. Compounds 19a, 19b, 19c, 19d, 21a, and 21b showed good antifungal activity against human and plant pathogens. Compounds 19a, 19b, 19f, 21c, 21f, and 21g were identified as lead chitin synthase inhibitors for further modi. cations by comparing results of inhibition of growth, % germ tube formation and chitin synthase activity. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-dipolar cycloaddition; 3-Triazole; 4-Disubstituted-1; 5 `-Azidouridine; Antifungal compounds; Chitin synthase activity; Click reaction; Uridine nucleosides

Functional delivery of siRNA in mice using dendriworms - Agrawal, Amit C.; Min, Dal-Hee; Singh, Neetu; Zhu, Haihao; Birjiniuk, Alona; von Maltzahn, Geoffrey; Harris, Todd J.; Xing, Deyin; Woolfenden, Stephen D.; Sharp, Phillip A.; Charest, Alain; Bhatia, Sangeeta N. (ACS Nano, 2009)

Gas sensing properties of magnesium ferrite prepared by co-precipitation method - Hankare, P. P.; Jadhav, S. D.; Sankpal, U. B.; Patil, R. P.; Sasikala, R.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2009)
Polycrystalline magnesium ferrite (MgFe(2)O(4)) was prepared by the co-precipitation method. The synthesized compound was characterized for their phase and morphology by X-ray diffraction and scanning electron microscopy, respectively. Conductance responses of the (MgFe(2)O(4)) were measured towards gases like hydrogen sulfide (H(2)S), liquefied petroleum gas (LPG), ethanol vapors (C(2)H(5)OH), SO(x), H(2), NO(x), NH(3), methanol, acetone and petrol. The gas sensing characterstics were obtained by measuring the sensitivity as a function of various controlling factors like operating temperatures and concentrations of gases. It was found that the sensor exhibited various responses towards these gases at different operating temperatures. Furthermore; the MgFe(2)O(4) based sensor exhibited a fast response and a good recovery towards petrol at temperature 250 degrees C. The results of the response towards petrol reveal that (MgFe(2)O(4)) synthesized by a simple co-precipitation method, would be a suitable material for the fabrication of the petrol sensor. (C) 2009 Published by Elsevier B.V.
Keywords: Ferrites; Gas sensor; X-ray diffraction and scanning electron microscopy

Human blood vessel-derived endothelial progenitors for endothelialization of small diameter vascular prosthesis - Ranjan, Amaresh K.; Kumar, Umesh; Hardikar, Ashutosh A.; Poddar, Pankaj; Nair, Prabha D.; Hardikar, Anandwardhan A. (Plos One, 2009)
Background: Coronary bypass graft failure as a result of acute thrombosis and intimal hyperplasia has been the major challenge in surgical procedures involving small-diameter vascular prosthesis. Coating synthetic grafts with patients' own endothelial cells has been suggested to improve the patency rate and overall success of bypass surgeries. Methodology/Principal Findings: We isolated endothelial progenitor cells (EPCs) from leftover pieces of human saphenous vein/mammary artery. We demonstrate that EPCs can be expanded to generate millions of cells under low-density culture conditions. Exposure to high-density conditions induces differentiation to endothelial cell phenotype. EPC-derived endothelial cells show expression of CD144(high), CD31, and vWF. We then assessed the ability of differentiated endothelial cells to adhere and grow on small diameter expanded polytetrafluoroethylene (ePTFE) tubings. Since ePTFE tubings are highly hydrophobic, we optimized protocols to introduce hydrophilic groups on luminal surface of ePTFE tubings. We demonstrate here a stepwise protocol that involves introduction of hydrophilic moieties and coating with defined ECM components that support adhesion of endothelial cells, but not of blood platelets. Conclusion/Significance: Our data confirms that endothelial progenitors obtained from adult human blood vessels can be expanded in vitro under xenoprotein-free conditions, for potential use in endothelialization of small diameter ePTFE grafts. These endothelialized grafts may represent a promising treatment strategy for improving the clinical outcome of small-caliber vascular grafts in cardiac bypass surgeries.

Magnetic and dielectric properties of nanophase manganese-substituted lithium ferrite - Hankare, P. P.; Patil, R. P.; Sankpal, U. B.; Jadhav, S. D.; Mulla, Imtiaz S.; Jadhav, K. M.; Chougule, B. K. (Journal of Magnetism and Magnetic Materials, 2009)
Nanocrystalline manganese-substituted lithium ferrites viz. Li0.5Fe2.5-xMnxO4 (2.5 <= x >= 0) were prepared by sol-gel autocombustion method. X-ray diffraction analysis confirmed that as the concentration of manganese increases the cubic phase changes to the tetragonal phase. The variation of saturation magnetization was studied as a function of manganese content. All the compositions indicate that they are ferrimagnetic in nature. The dielectric constant, dielectric loss tangent and ac conductivity of all samples were measured at room temperature as a function of frequency. These parameters decrease with increase in frequency for all of the samples. The substitution of manganese plays an important role in changing the structural and magnetic properties of these ferrites. The compositional variation of dielectric constant and d.c. resistivity shows an inverse trend of variation with each other. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: dielectric constant; Ferrite; Magnetization; X-ray diffraction

Mesoporous silica immobilized cobalt complex: an efficient catalyst for epoxides ring opening by aromatic amines under ambient conditions - Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shivaraj B. (Catalysis Communications, 2009)
{Cobalt complex, CobpbH(2)Cl(2)2H(2)O [where
Keywords: beta-Amino alcohols; CobpbH(2)Cl(2)2H(2)O complex; Epoxide ring opening; Immobilization; SBA-15

Methyl glycosides are identified as glycosyl donors for the synthesis of glycosides, disaccharides and oligosaccharides - Vidadala, Srinivasa Rao; Hotha, Srinivas (Chemical Communications, 2009)
Stable methyl glycosides are identified as glycosyl donors in the presence of AuBr(3) in acetonitrile; a panel of aglycones comprising aliphatic, alicyclic, steroidal and sugar alcohols are examined successfully for the glycosylation reaction and methyl glycosides of di- and tri-saccharides are converted to corresponding tri- and tetra-saccharides exploiting salient features of our novel activation protocol.

MoO3/SiO2: an efficient and selective catalyst for the synthesis 1,3-dioxolane and 1,3-dioxane - Amrute, Amol P.; Sahoo, Suman; Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shiva B. (Catalysis Communications, 2009)
A series of MoO3/SiO2 catalysts with varying amounts of MoO3 has been synthesized and the catalytic activities of these were compared with the known solid acid catalysts in the synthesis of 1,3-dioxolane. MoO3/SiO2 catalyst showed a better activity and selectivity in 1,3-dioxolane synthesis compared to the other catalysts. MoO3/SiO2 catalyst system was further successfully applied for the synthesis of 1,3-dioxanes in the Prins cyclization of olefins and formaldehyde. The proposed catalyst was thermally stable and could be recovered and reused at least in four consecutive cycles with no significant loss in the substrates conversions and products selectivities. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 1; 3-Dioxolanes; Cycloaddition; MoO3/SiO2; Prins cyclization; Sol-gel method; solid acid catalysts

Nanoparticle-mediated targeting of MAPK signaling predisposes tumor to chemotherapy - Basu, Sudipta; Harfouche, Rania; Soni, Shivani; Chimote, Geetanjali; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2009)
The MAPK signal transduction cascade is dysregulated in a majority of human tumors. Here we report that a nanoparticle-mediated targeting of this pathway can optimize cancer chemotherapy. We engineered nanoparticles from a unique hexadentate-polyD, L-lactic acid-co-glycolic acid polymer chemically conjugated to PD98059, a selective MAPK inhibitor. The nanoparticles are taken up by cancer cells through endocytosis and demonstrate sustained release of the active agent, resulting in the inhibition of phosphorylation of downstream extracellular signal regulated kinase. We demonstrate that nanoparticle-mediated targeting of MAPK inhibits the proliferation of melanoma and lung carcinoma cells and induces apoptosis in vitro. Administration of the PD98059-nanoparticles in melanoma-bearing mice inhibits tumor growth and enhances the antitumor efficacy of cisplatin chemotherapy. Our study shows the nanoparticle-mediated delivery of signal transduction inhibitors can emerge as a unique paradigm in cancer chemotherapy.
Keywords: cancer; Signal transduction

N-heterocyclic carbene-catalyzed hydroacylation of unactivated double bonds - Hirano, Keiichi; Biju, Akkattu T.; Piel, Isabel; Glorius, Frank (Journal of the American Chemical Society, 2009)
An intramolecular N-heterocyclic carbene (NHC)-catalyzed hydroacylation of unactivated double bonds is reported. Systematic variation of the catalyst structure revealed an N-mesitylthiazolylidene annulated with a seven-membered ring to be especially reactive. This NHC enables a unique C−C bond-forming reaction to afford substituted chroman-4-ones in moderate to excellent yields, even ones containing all-carbon quaternary centers.

Non-templated hydrothermal growth of anisotropic magnetite nanostructures using hexamine as the directing agent - Bhagwat, S. V.; Jouen, Samuel; Kundaliya, D. C.; Singh, H.; Jagadale, Tushar C.; Athawale, A. A.; Lofland, S. E.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2009)
Anisotropic growth of magnetite (Fe(3)O(4)) nanoparticles is achieved in a hydrothermal growth process using hexamine to play a dual role of oxide forming and directing agent. The samples are characterized by X-ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy, squid magnetometry, ferromagnetic resonance technique, diffuse reflectance spectroscopy and Mossbauer spectroscopy, which collectively establish the formation of Fe(3)O(4) phase. Anisotropic structures such as nanorods and nanotubules are revealed and these are shown to exhibit good humidity sensing properties.
Keywords: Anisotropic Nanostructures; Hexamine; hydrothermal; magnetite; Mossbauer

Novel foldamer structural architecture from cofacial aromatic building blocks - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, Pattuparampil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2009)
This communication demonstrates the utility of peri-substituted 1,8-diphenylnaphthalene as an effective building block for the construction of novel conformationally ordered synthetic oligomers displaying cofacial structural features.

Optoelectronic photoinduced charge transfer system with mu 3PhN-Ru-3 cluster functionalized single-walled carbon nanotubes - Lee, Wonjoo; Koo, Gumae; Ogale, Satishchandra B.; Han, Sung-Hwan (Journal of Materials Chemistry C, 2009)
Optoelectronic photoinduced charges have been attracting great attention lately in view of their applicability to diverse optoelectronic device systems. Here, we report the design and implementation of a charge transfer system based on triruthenium (Ru) cluster compounds on viologen modified single-walled carbon nanotubes (V-SWNTs) by an in situ preparation method. We examine the photoinduced (intensity dependent and temporal) changes in the transport properties of the Ru-cluster functionalized V-SWNT coating and identify the possible charge transfer mechanism. Furthermore, we demonstrate the applicability of such Ru-cluster functionalized V-SWNT films to photoelectrochemical cells.

Orthogonal activation of propargyl and n-pentenyl glycosides and 1,2-orthoesters - Vidadala, Srinivasa Rao; Thadke, Shivaji A.; Hotha, Srinivas (Journal of Organic Chemistry, 2009)
An orthogonal activation strategy with propargyl and n-pentenyl glycosides has been identified. According to this methodology, n-pentenyl glycosides can be selectively activated with NIS/TMSOTf in the presence of either armed or disarmed propargyl O-glycosides. In addition, we report herein that propargyl 1,2-orthoesters can be selectively activated with AuBr(3) in CH(2)Cl(2) at room temperature in the presence of n-pentenyl glycosides. Similarly, pentenyl 1,2-orthoesters can be selectively activated with NIS/Yb(OTf)(3) in the presence of propargyl glycosides.

Oxidative kinetic resolution of alcohols using chiral Mn-salen complex immobilized onto ionic liquid modified silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
The supported ionic liquid strategy has been applied for the immobilization of chiral Mn(III) salen complex onto ionic liquid modified silica. Chiral Mn(III) salen complex was immobilized over silica through a thin film of covalently anchored imidazolium ionic liquid. These catalysts were characterized by N(2) sorption, XRD, MR, DRUV-vis, and elemental analysis. The results showed that the chiral Mn(III) salen complex could be successfully immobilized onto the modified mesoporous materials and that the long-range mesoporous ordering of parent supports was maintained after the immobilization. The immobilized catalyst provided good enantioselectivity and activity in the heterogeneous catalysis of the oxidative kinetic resolution of secondary alcohol and can be recovered and recycled for four times without obvious loss of enantioselectivity and activity. Oxidative kinetic resolutions of meso-diols, hydroxyl ester and primary alcohol were also studied using this catalyst system. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Mesoporous silica; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Phase behavior of hydrogenation of 2-tert-butylphenol over a charcoal-supported rhodium catalyst in carbon dioxide solvent - Hiyoshi, Norihito; Masuda, Yoshio; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of Chemical and Engineering Data, 2009)
Catalytic hydrogenation of 2-tert-butyl phenol over a charcoal-supported rhodium catalyst in carbon dioxide solvent at 313 K was studied in a batch reactor. To elucidate the effect of carbon dioxide pressure on the initial rate of reaction, the phase behavior of the ternary (2-tert-butylphenol-carbon dioxide-hydrogen) system was separately observed with a view cell, and the calculations of vapor-liquid equilibrium and compositions in the vapor and liquid phases inside the reactor were carried out using the Peng-Robinson equation of state. The hydrogenation behavior in the carbon dioxide solvent is discussed based on the phase behavior of the ternary system.

Polyimides based on aromatic diisocyanates containing pendent flexible alkoxy chains and aromatic dianhydrides: synthesis, characterization, and liquid-crystal alignment properties - Sarkar, Anjana; Halhalli, Mahadeo R.; Kulkarni, Arun D.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2009)
Four new aromatic diisocyanates containing pendent flexible alkoxy chains, namely, 5-butyloxy-1,3-phenylenediisocyanate, 5-octyloxy-1,3-phenylenediisocyanate, 5-dodecyloxy-1,3-phenylenediisocyanate, and 5-hexadecyloxy-1,3-phenylenediisocyanate, were synthesized by Curtius rearrangement of the corresponding 5-alkoxy-1,3-phenylene diacylazides. These diisocyanates were each polycondensed with three commercially available aromatic dianhydrides: 4,4'-oxydiphthalic anhydride, 3,3',4,4'-(hexafluoroisopropylidene) diphthalic anhydride, and 3,3',4,4'-benzophenonetetracarboxylic dianhydride-in benzonitrile in the presence of 1,4-dizabicyclo[2.2.2]octane as a catalyst to obtain a series of polyimides with inherent viscosities in the range 0.16-0.43 dL/g. Except for 3,3',4, 4'-benzophenonetetracarboxylic dianhydride based polyimides, all of the polyimides were found to be soluble in dichloromethane, m-cresol, 1-methyl-2-pyrrolidinone, tetra-chloroethane, and pyridine either at room temperature or on heating and could be cast into tough, flexible, transparent films from a solution in in-cresol or tetra chloroethane. X-ray diffractograms revealed that the polyimides with longer alkoxy chains had layered structures. The glass-transition temperature of the polyimides containing pendent flexible alkoxy chains were in the range 159-246 degrees C as measured by differential scanning calorimetry. The temperature for the 10% weight loss of the polyimides was in the range 410-460 degrees C in a nitrogen atmosphere, which indicated good thermal stability. A pretilt angle of 2.97 degrees was observed for the polyimide derived from 5-octyloxy-1,, 3-phenylenediisocyanate and 4,4'-oxydiphthalic anhydride. (c) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 461-472, 2009
Keywords: High performance polymers; polyimides; Thermal properties

Polymer-embedded stannic oxide nanoparticles as humidity sensors - Hatamie, Shadie; Dhas, Vivek V.; Kale, B. B.; Mulla, Imtiaz S.; Kale, Sangeeta N. (Materials Science & Engineering C-Biomimetic and Supramolecular Systems, 2009)
Stannic oxide (SnO(2)) nanoparticles have been suspended in polyvinyl alcohol (PVA) matrix in different PVA: SnO(2) molar ratios ranging from 1:1 to 1:5 using simple chemical route. This suspension was deposited on ceramic substrate and upon drying was carefully detached from the substrate. SnO(2)-embedded self-standing, transparent and flexible thin films were hence synthesized. Transmission electron microscopy (TEM) and Xray diffraction (XRD) techniques show the rutile tetragonal structure of SnO(2) with particle size similar to 5 nm. UV-Visible spectroscopy demonstrates the band gap of 3.9 eV, which does not alter when embedded in polymer. Fourier transform infrared spectroscopy (FTIR) reveals that the properties of SnO(2) do not modify due to incorporation in the PVA matrix. The structures work as excellent humidity sensors at room temperature. For a critical PVA:SnO(2) molar ratio of 1:3, the resistance changes to five times of magnitude in 92% humidity within fraction of second when compared with resistance at 11% humidity. The sample regains its original resistance almost instantaneously after being removed from humid chamber. Nanodimensions of SnO(2) particles and percolation mechanism related to transport through polymer matrix and water molecule as a carrier has been used to understand the mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: humidity sensor; Nanoparticles; Polymer; Stannic oxide

Polymeric ladderphanes - Chou, Chih-Ming; Lee, Shern-Long; Chen, Chih-Hsien; Biju, Akkattu T.; Wang, Hsian-Wen; Wu, Yi-Lin; Zhang, Guo-Fu; Yang, Kuang-Wei; Lim, Tsong-Shin; Huang, Min-Jie; Tsai, Po-Yu; Lin, Kin-Chuan; et al. (Journal of the American Chemical Society, 2009)
A new class of polymers, which have a double-stranded polybinorbornene skeleton with multilayer planar oligoaryl linkers, defined as polymeric ladderphanes, are synthesized. The structures of these ladderphanes are determined by spectroscopic means. Photophysical studies and time-resolved fluorescence spectroscopic investigations reveal that there is a strong interaction between the chromophore linkers. Thus, Soret band splitting in the absorption spectrum of the polymer with porphyrin linker (12e), significant fluorescence quenching with oligoaryl linkers (12b−d), and excimer emission with a terphenylene-diethynylene linker (12a) are characteristic photophysical properties of these polymers. Scanning tunneling microscopy shows that polymers 12b and d exhibit a ladder-like morphology and form a supramolecular assembly leading to a two-dimensional ordered array on a highly oriented pyrolytic graphite surface.

Selective oxidation of benzyl alcohol over copper phthalocyanine immobilized on MCM-41 - Hamza, A.; Srinivas, D. (Catalysis Letters, 2009)
Copper phthalocyanine (CuPc) complexes immobilized on ``neat'' and Ti(4+) and Al(3+) containing MCM-41 mimic the functionality of metalloenzymes. These novel materials catalyze the oxidation of benzyl alcohol to selectively benzaldehyde at moderate temperatures using peroxides and molecular oxygen as oxidant. Electron paramagnetic resonance and X-ray photoelectron spectroscopic studies revealed that the acidity of the support (MCM-41) influences the electronic structure of the immobilized CuPc. On acidic supports a part of copper in CuPc got reduced from a ``formal'' +2 to +1 oxidation state. This reduction of copper in its oxidation state on different supports decreased in the order: Al-MCM-41 (Bronsted and strong Lewis acid sites) > MCM-41 (silanol sites) > Ti-MCM-41 (weak Lewis acid sites). A linear variation in catalytic activity with the concentration of Cu(1+) ions in different catalyst samples was observed. The study reveals that by suitably modifying the acidic properties of the support one can, in principle, fine-tune the electronic and catalytic properties of the active oxidation sites.
Keywords: Copper phthalocyanine; EPR; MCM-41; Selective oxidation of benzyl alcohol; UV-visible spectroscopy

Somatic embryogenesis from the axillary meristems of peanut (Arachis hypogaea L.) - Singh, Shweta; Hazra, Sulekha (Plant Biotechnology Reports, 2009)
Developmental anomalies in the plumule meristem of peanut (Arachis hypogaea L.) somatic embryos resulted in poor shoot differentiation and reduced plant recovery. Existing meristems with caulogenic potential have never been tested for embryogenesis in peanut. The present experiment was designed to test the mature zygotic embryo axis derived plumule with three meristems for somatic embryogenesis. Embryogenic masses and embryos developed from the caulogenic meristems in the axils. Exposure of 2 weeks in primary medium with 90.5 A mu M 2,4-D suppressed the shoot tip differentiation temporarily which then regained the ability to form the shoot on withdrawal of 2,4-D. Exposure of 4 weeks in primary medium with 90.5 A mu M 2,4-D suppressed the shoot tip differentiation irreversibly. No shoot formation was noted from the tips in any of the cultures which were in secondary medium with 13.6 A mu M 2,4-D. Development of somatic embryos directly from axillary meristems was confirmed histologically. Conversion frequency of these embryos was 11%. Thus, in this report, we describe a method to obtain somatic embryos from the determined organogenic buds of the axillary meristem, by culturing the nodal explant vertically on embryo induction medium. It also displays the possibility of obtaining both embryogenic and organogenic potential in two parts of the same explant simultaneously. The possibility of extending this approach for genetic transformation in in vivo system through direct DNA delivery or Agrobacterium injection in meristems can also be explored. Using Agrobacterium rhizogenes, we have demonstrated the possibility of gene transfer in the axillary meristems of seed-derived plumule explant.
Keywords: Apical meristem; Axillary meristem; Mature zygotic embryo axis; Peanut; somatic embryogenesis

Sterically controlled naphthalene homo-oligoamides with novel structural architectures - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2009)
Herein we report novel naphthalene homo-oligoamides, derived from 4-amino-3-methoxy-naphthalene-2-carboxylic acid and 4-amino-1-methoxy-naphthalene-2-carboxylic acid as monomer building blocks, that display an anti-periplanar arrangement of the naphthyl rings, primarily induced by steric interactions between adjacent groups and functionalities.

Switching the electron-donor properties of n-heterocyclic carbenes by a facile deprotonation strategy - Biju, Akkattu T.; Hirano, Keiichi; Frohlich, Roland; Glorius, Frank (Chemistry an Asian Journal, 2009)
Flip the switch! The facile and distinct variation of the electronic properties of an N-heterocyclic carbene (NHC) ligand is reported. In this process, a simple deprotonation/protonation strategy can render the NHC to be an electron-poor or an electron-rich NHC ligand: one ligand, two electronic natures.
Keywords: carbenes; electronic properties; enolates; heterocycles; ligand design

Synthesis and characterization of CoCrxFe2-xO4 nanoparticles - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Lokhande, P. D.; Gajbhiye, N. S. (Journal of Alloys and Compounds, 2009)
Spinel-phase nanocrystalline CoCrxFe2-xO4 powders (0.0 <= x <= 2.0) were synthesized by citrate-gel precursor method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM). transmission electron microscopy (TEM) and infra-red spectroscopy (FT-IR). The XRD and selected-area electron diffraction (SAED) patterns indicated that the synthesized nanoparticles have single-phase spinet structure without the presence of any other impurities. The changes in electrical and magnetic properties of different stiochiometric compositions have also been investigated. It is seen that with increase in chromium contents, the measured magnetic hysteresis loops become narrow with decreasing trend in saturation magnetization. Electrical resistivity indicated that all the compounds are semiconducting nature. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Magnetic measurements; Sintering; transmission electron microscopy; X-ray diffraction

Synthesis and characterization of new polyimides containing pendent pentadecyl chains - Sadavarte, Nilakshi V.; Halhalli, Mahadeo R.; Avadhani, C. V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2009)
A new unsymmetrical aromatic diamine, viz., 4-pentadecylbenzene-1,3-diamine was synthesized through a series of reaction steps starting from 3-pentadecylphenol. 4-Pentadecylbenzene-1,3-diamine was employed to synthesize a series of new polyimides by one-step polycondensation in m-cresol with four commercially available aromatic dianhydrides. viz., 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenone-tetracarboxylic dianhydride (BTDA), 4,4'-oxydiphthalic anhydride (ODPA) and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6-FDA). Inherent viscosities of resulting polyimides were in the range 0.33-0.67 dL/g and number average molecular weights were in the range 14,700-52,200 (GPC, polystyrene standard). Polyimides containing pendent pentadecyl chains were soluble in organic solvents such as chloroform, m-cresol, N,N-dimethylacetamide (DMAc), 1-methyl-2-pyrrolidinone (NMP), pyridine and nitrobenzene. Strong and flexible films of polyimides could be cast from their chloroform solutions. Polyimides exhibited glass transition temperature in the range 158-206 degrees C. The temperature at 10% wt. loss (T(10)). determined by TGA in nitrogen atmosphere, of polyimides was in the range 470-480 degrees C indicating good thermal stability. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Cashew nut shell liquid; Glass transition temperature; Pendant pentadecyl chain; polyimides

Synthesis and characterization of novel schiff base polyurethanes - Raghu, A. V.; Gadaginamath, G. S.; Jeong, Han Mo; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2009)
Eight different types of novel polyurethanes (PUs) were synthesized through the polyaddition reaction of 4,4'-(ethane-1,2-diylidenedinitrilo)diphenol and 4,4'(pentane-1,5-diylidenedinitrilo)diphenol with four different diisocyanates: 4,4'-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate. The resulting PUs were soluble in polar, aprotic solvents. Structures of the diols and PUs were established with Ultraviolet-visible, fluorescence, Fourier transform infrared (FTIR), (1)H-NMR, and (13)C-NMR spectroscopy data. FTIR and NMR spectral data indicated the disappearance of both hydroxyl and isocyanate groups in the PUs. The thermal properties were investigated with thermogravimetry and differential scanning calorimetry. The weight losses, glass transitions, onset temperatures, and crystalline melting temperatures were measured. All the PUs exhibited semicrystalline and amorphous morphologies, as indicated by X-ray diffraction. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 113: 2747-2754, 2009
Keywords: amorphous; Morphology; polyurethanes; synthesis; Thermal properties

Synthesis, characterization and effect of sintering temperature on magnetic properties of MgNi ferrite prepared by co-precipitation method - Hankare, P. P.; Jadhav, S. D.; Sankpal, U. B.; Chavan, Santosh S.; Waghmare, K. J.; Chougule, B. K. (Journal of Alloys and Compounds, 2009)
Mixed MgNi ferrites with composition Mg(0.5)Ni(0.5)Fe(2)O(4) where the mole fraction for Ni (x = 0, 0.25, 0.75, 0.5 and 1) were prepared by following co-precipitation method at temperature 110 degrees C and maintaining a pH of solution equal to 9.5 enable to achieve large particle surface area. The resultant materials obtained in powder form were sintered at different temperatures. Thermogravimetry (TGA), X-ray diffraction (XRD) and scanning electron microscopy, technique were applied to obtain structural parameters. The XRD patterns reveal the presence of(311) peak as the most intense one. The intensity of XRD peak increases with increase in sintering temperature. The saturation magnetization values showed increasing trend with increase in sintering temperature from 2.37 to 29.76 emu/g. These results along with the analysis of SEM micrographs are interpreted in terms of increase in particle grain size with increase in sintering temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Ferrites; FT-IR; scanning electron microscopy; X-ray diffraction

Synthesis of chiral sulfoxides by enantioselective sulfide oxidation and subsequent oxidative kinetic resolution using immobilized Ti-binol complex - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2009)
Chiral Ti-binol complex was immobilized onto ionic liquid modified SBA-15 and characterized by different physicochemical techniques. The catalyst was found to be highly enantioselective in the heterogeneous asymmetric oxidation of prochiral sulfides to sulfoxides and subsequent oxidative kinetic resolution of the sulfoxides using aqueous tert-butylhydroperoxide as the oxidant. A positive non-linear effect was observed in the oxidation-kinetic resolution of thioanisole using this supported catalyst. The supported catalyst was reused in multiple catalytic runs without any loss of enantioselectivity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Kinetic resolution; Mesoporous silica; Non-linear effect; Sulfides; Sulfoxides; Supported ionic liquid; Ti-binol

Assessment of Pongamia pinnata (L.) - a biodiesel producing tree species using ISSR markers - Sujatha, K.; Rajwade, A. V.; Gupta, V. S.; Hazra, Sulekha (Current Science, 2010)

Citrate-capped quantum dots of CdSe for the selective photometric detection of silver ions in aqueous solutions - Ingole, Pravin P.; Rajiv M. Abhyankar; Bhagavatula L. V. Prasad; Haram, Santosh K. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A simple strategy for the synthesis of water soluble, luminescent, citrate-capped CdSe quantum dots (Q-CdSe) and their applications to selective detection of silver ions are described. The steady state photoluminescence (PL) spectra show single, narrow emission band at ca. 554 nm without any contribution from the trap states. The effect of various ions including physiologically important metal ions (viz. K(+), Ca(2+), Fe(3+), Zn(2+), Mg(2+), Mn(2+), Cu(2+), Ag(+), Pb(2+) and Cd(2+)), on the PL intensity of citrate-capped Q-CdSe has been studied. Among these, selective luminescence quenching with Ag(+) ion was found to be predominant. Under the optimum conditions, the response was linear between 1.7 and 18 mu M. The quenching constant K(SV) was found to be ca. 3.4 x 10(5) M(-1). The mechanism of photoluminescence quenching of Q-CdSe by metal ions (Ag(+)) is also discussed. Based on these studies, the potential use of Q-CdSe as a luminescent probe for the selective detection of silver ion has been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: Ag(+) ions; Luminescence quenching; Luminescent probe; Q-CdSe; Tri-sodium citrate

Clicking molecular hooks on silica nanoparticles to immobilize catalytically important metal complexes: the case of gold catalyst immobilization - Ganai, Anal Kumar; Bhardwaj, Rima; Hotha, Srinivas; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
Gold mediated reactions have emerged as one of the best choices for affecting a variety of chemical transformations with a wide range of functional group tolerance. Application of such transformations to industrial processes necessitates immobilization of the Au ions into a matrix for easy separation of the catalyst after reaction. We report the synthesis and characterization of silica nanoparticles in which Au(III) has been immobilized through a 1,2,3-triazole linkage using an alkynalated picolinic acid exploiting ``click chemistry''. The Au( III) immobilized silica nanoparticle has been thoroughly characterized using FT-IR, C-13 CP MAS NMR and XPS. The utility of these particles as an easily separable catalyst for the Hashmi phenol synthesis is also reported.

Cobalt nanoparticles doped emaraldine salt of polyaniline: a promising room temperature magnetic semiconductor - Hatamie, Shadie; Kulkarni, M. V.; Kulkarni, S. D.; Ningthoujam, R. S.; Vatsa, R. K.; Kale, Sangeeta N. (Journal of Magnetism and Magnetic Materials, 2010)
Incorporation of magnetic nanoparticles in polymers with organic functional groups working as semiconducting substrate is of immense interest in the field of dilute magnetic semiconductors (DMS) and spintronics. In this article we report on synthesis and evaluation of dilutely doped (0-10 wt%) cobalt nanoparticles in emaraldine salt (ES) of polyaniline in the presence of dodecyl benzene sulfonic acid (DBSA) and p-toluene sulfonic acid (p-TSA) using a sonochemical-assisted-reduction approach as a possible DMS candidate. The X-ray diffraction pattern and high resolution transmission electron microscopy (HRTEM) image show the ES to be polycrystalline, in which 10 nm sized Co nanoparticles get embedded in its FCC structural form. From Fourier transform infrared (FT-IR) and UV-visible (UV-vis) spectroscopy studies, it is predicted that cobalt particles get electrostatically bound to the specific SO(3)(-) ion sites of ES, thereby modifying torsional degrees of freedom of the system. The applied field dependent magnetization study shows that the sample exhibits hysteresis loop with a minimal doping of 3 wt% of Co nanoparticles and increases with the amount of Co nanoparticles in ES due to dipolar interaction. The electron transport data show that with increase in Co wt% there is a gradual shift from ohmic to non-ohmic response to the sample bias, accompanied by opening of electrical hysteresis and an increased resistance. The non-linear response of higher doped systems has been attributed to the combination of direct and Fowler-Nordheim tunneling phenomena in these systems. Persistence of optical and transport properties of the polymer, with an introduction of magnetic moment in the system, envisages the system to be a fine magnetic semiconductor. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cobalt nanoparticles; Magnetic semiconductor; polyaniline

Coupling growth-factor engineering with nanotechnology for therapeutic angiogenesis - Roy, Rituparna Sinha; Soni, Shivani; Harfouche, Rania; Vasudevan, Pooja R.; Holmes, Oliver; de Jonge, Hugo; Rowe, Arthur; Paraskar, Abhimanyu; Hentschel, Dirk M.; Chirgadze, Dimitri; Blundell, Tom L.; Gherardi, Ermanno; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Therapeutic angiogenesis is an emerging paradigm for the management of ischemic pathologies. Proangiogenic Therapy is limited, however, by the current inability to deliver angiogenic factors in a sustained manner at the site of pathology. In this study, we investigated a unique nonglycosylated active fragment of hepatocyte growth factor/scatter factor, 1K1, which acts as a potent angiogenic agent in vitro and in a zebrafish embryo and a murine matrigel implant model. Furthermore, we demonstrate that nanoformulating 1K1 for sustained release temporally alters downstream signaling through the mitogen activated protein kinase pathway, and amplifies the angiogenic outcome. Merging protein engineering and nanotechnology offers exciting possibilities for the treatment of ischemic disease, and furthermore allows the selective targeting of downstream signaling pathways, which translates into discrete phenotypes.
Keywords: cardiovascular disease; HGF/SF; ischemic disease; nanoparticle; protein engineering

Cu:Al Nano catalyst for selective hydrogenolysis of glycerol to 1,2-propanediol - Mane, Rasika B.; Hengne, Amol M.; Ghalwadkar, Ajay A.; Vijayanand, Subramanian; Mohite, Pravin H.; Potdar, Hari S.; Rode, Chandrashekhar V. (Catalysis Letters, 2010)
Non-chromium Cu:Al nano catalyst prepared by simultaneous co-precipitation and digestion method without any template or stabilizer, showed three times higher activity than the bulk Cu-Cr catalyst for hydrogenolysis of glycerol in both isopropanol and water solvents, with the selectivity to 1,2-Propanediol (1,2-PDO) as high as 91% at 493 K and H(2) pressure of 7 MPa in 5 h. XRD pattern showed the presence of Cu(+) species in the activated Cu: Al nano catalyst. Although Cu(+) is catalytically inactive in glycerol hydrogenolysis reaction, the presence of Cu(+) helps to stabilize the particle size in a narrow range of 7-11 nm by inhibiting the sintering of copper particles under reaction conditions.
Keywords: 1; 2-Propanediol; Cu:Al nano catalyst; Glycerol; Selective hydrogenolysis

Elucidation of the role of hexamine and other precursors in the formation of magnetite nanorods and their stoichiometry - Singh, Hema; Bhagwat, Shrikant; Jouen, Samuel; Lefez, Benoit; Athawale, Anjali A.; Hannoyer, Beatrice; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2010)
Hexamine is known to assist anisotropic growth of metal oxides and the same is also found to be true for magnetite nanosynthesis. In this work we elucidate the role of hexamine and other precursors in the formation of magnetite nanorods by the hydrothermal route and their stoichiometry. Various others hydrolyzing agents such as sodium hydroxide (NaOH), sodium hydroxide + hexamine, ammonia (NH(3)), ammonia + formaldehyde are also studied. The synthesized nanoparticles are characterized with the help of various techniques such as X-ray diffraction (XRD), FT-IR spectroscopy, UV-VIS-NIR spectroscopy, transmission electron microscopy (TEM), Mossbauer spectroscopy and SQUID magnetization measurements. It is found that only when ferric chloride, ferrous ammonium sulfate (FAS) and hexamine are used, well defined nanorods are formed. When sodium hydroxide and hexamine are used as a hydrolyzing system nearly spherical nanoparticles with small size (similar to 13 nm) are formed, as compared to the case of sodium hydroxide alone which leads to bigger cube like nanoparticles. Interestingly the decomposition products of hexamine do not lead to nanorod formation. Thus, slow decomposition of hexamine at elevated temperature and the consequent slow rise in pH is the key to the anisotropic growth of the iron oxide system.

Enantiospecific synthesis of sex pheromone of the obscure mealybug from pantolactone via tandem conjugate addition/cyclization - Hajare, Atul K.; Datrange, Laxmikant S.; Vyas, Samir; Bhuniya, Debnath; Reddy, D. Srinivasa (Tetrahedron Letters, 2010)
An efficient synthesis of an enantiomer of insect's natural pheromone is reported starting from chiral pool D-(-)-pantolactone. Highly stereoselective tandem conjugate addition/cyclization sequence and hydrogenation of exocyclic double bond are the key steps in the present synthesis. (C) 2010 Elsevier Ltd. All rights reserved.

Enhancement of thermal stability and phase relaxation behavior of chitosan dissolved in aqueous l-lactic acid: using `silver nanoparticles' as nano filler - Rana, V. K.; Pandey, Asutosh K.; Singh, Raj Pal; Kumar, B.; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Chitosan films with various compositions of silver nanoparticles were prepared by solution casting with an aqueous solution of chitosan and l-lactic acid. The chitosan/Ag nanocomposites were characterized by wide angle Xray diffraction (WAXD) and UV-vis spectroscopy. An analysis of the surface topography and size of the Ag nanoparticles (<= 100 nm) were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. Thermogravimetric analysis (TGA/DTA) confirmed the increase in thermal stability with increasing Ag nanoparticle content in the nanocomposites. Dynamic thermal analysis (DMA) was used to examine the phase relaxation behavior of chitosan and its nanocomposites. The conductivity of chitosan/Ag nanocomposites was considered with respect to the frequency. Contact angle measurements were used to characterize the surface twistability, surface cleanliness, and hydrophilic/hydrophobic nature of the surface.
Keywords: Chitosan; conductivity; contact angle; relaxation; silver nanoparticles

Evidence for the co-existence of distorted tetrahedral and trigonal bipyramidal aluminium sites in SrAl12O19 from Al-27 NMR studies - Harindranath, K.; Viswanath, K. Anusree; Chandran, C. Vinod; Braeuniger, Thomas; Madhu, Perunthiruthy K.; Ajithkumar, Thalasseril G.; Joy, Pattayil Alias (Solid State Communications, 2010)
Strontium aluminate, SrAl12O19, is a ceramic material having the hexagonal magnetoplumbite-type structure, with multiple Al coordination environments. An earlier low-field Al-27 solid-state NMR study reported five different Al sites in this system: one AlO4, one AlO5, and three AlO6 sites; whereas a later high-field study showed that the AlO5 site is a distorted AlO4 site with a very large quadrupolar coupling constant (similar to 20 MHz). Our magic angle spinning (MAS) and 3-quantum magic angle spinning (3QMAS) NMR studies at 7.05 T unambiguously show evidence for an AlO5 site. However, evidence for the presence of a distorted AlO4 site is obtained from studies at high fields (16.4 and 17.6 T), in addition to the AlO5 site. Thus the present solid-state NMR studies give evidence for the simultaneous presence of both the five-coordinated and distorted four-coordinated sites in this system. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Local structure; MQMAS; Nuclear magnetic resonance; Strontium aluminate

Fabrication, characterization and electrochemical performance of single strand carbon fiber prepared by catalytic chemical vapor decomposition method - Joshi, Vrushali S.; Gokhale, Suresh P.; Patil, Kashinath R.; Haram, Santosh K. (Electrochimica Acta, 2010)
Preparation, fabrication and voltammetric characterizations of a single strand of carbon fiber (SSCF) electrode and their potential applications for biosensor are presented. SSCFs of diameter ca. 10 +/- 2 mu m and few millimeters in length are prepared by catalytic chemical vapor decomposition (CCVD) method. Voltammetry with potassium ferricyanide. alpha-methylferrocene methanol and hexaammineruthenium(III) chloride on SSCF electrode are used as bench marks to validate the electrode properties. Quasi-steady state voltammograms obtained were fitted into a cylindrical diffusion model From which, the standard rate constant (k(0)) and electron transfer coefficient (alpha) are obtained. The use of SSCF electrode is demonstrated for the voltammetric detection of the micromolar quantity of dopamine in the presence of large excess (ca. 200 times) of ascorbic acid, without any fouling of electrode surface. The kinetics of electron transfer are investigated. (C) 2009 Elsevier Ltd All rights reserved.
Keywords: alpha-Methylferrocene methanol; Ascorbic acid; Catalytic chemical vapor decomposition (CCVD); Cylindrical diffusion; dopamine; Hexaammineruthenium(III) chloride; Single strand carbon fiber (SSCF) electrode

Gold-catalyzed glycosidations: synthesis of 1,6-anhydro saccharides - Thadke, Shivaji A.; Hotha, Srinivas (Tetrahedron Letters, 2010)
Various 1,6-anhydro sugars are synthesized utilizing salient features of gold-catalyzed glycosidations. All the reactions occurred under mild conditions in the presence of 7 mol % of AuBr(3) enabling easy synthesis of 1,6-anhydro sugars from corresponding 6-hydroxy propargyl/methyl monosaccharides, disaccharides, and trisaccharides in good yields. (C) 2010 Elsevier Ltd. All rights reserved.

Gold-catalyzed glycosidations: unusual cleavage of the interglycosidic bond while studying the armed/disarmed effect of propargyl glycosides - Kayastha, Abhijeet K.; Hotha, Srinivas (Tetrahedron Letters, 2010)
Armed/disarmed effect of propargyl glycosides in the presence of AuBr(3) is studied. Observed that oxophilic AuBr(3) cleaves interglycosidic bond of an armed disaccharide resulting in the formation of a disaccharide and a 1,6-anhydro sugar. Trisaccharides were obtained after fine tuning the reactivity of the glycosyl donor with different protecting groups. (C) 2010 Elsevier Ltd. All rights reserved.

Harnessing structure-activity relationship to engineer a cisplatin nanoparticle for enhanced antitumor efficacy - Paraskar, Abhimanyu S.; Soni, Shivani; Chin, Kenneth T.; Chaudhuri, Padmaparna; Muto, Katherine W.; Berkowitz, Julia; Handlogten, Michael W.; Alves, Nathan J.; Bilgicer, Basar; Dinulescu, Daniela M.; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cisplatin is a first line chemotherapy for most types of cancer. However, its use is dose-limited due to severe nephrotoxicity. Here we report the rational engineering of a novel nanoplatinate inspired by the mechanisms underlying cisplatin bioactivation. We engineered a novel polymer, glucosamine-functionalized polyisobutylene-maleic acid, where platinum (Pt) can be complexed to the monomeric units using a monocarboxylato and an O –> Pt coordinate bond. We show that at a unique platinum to polymer ratio, this complex self-assembles into a nanoparticle, which releases cisplatin in a pH-dependent manner. The nanoparticles are rapidly internalized into the endolysosomal compartment of cancer cells, and exhibit an IC50 (4.25 + 0.16 mu M) comparable to that of free cisplatin (3.87 +/- 0.37 mu M), and superior to carboplatin (14.75 +/- 0.38 mu M). The nanoparticles exhibited significantly improved antitumor efficacy in terms of tumor growth delay in breast and lung cancers and tumor regression in a K-ras(LSL/+)/Pten(fl/fl) ovarian cancer model. Furthermore, the nanoparticle treatment resulted in reduced systemic and nephrotoxicity, validated by decreased biodistribution of platinum to the kidney as quantified using inductively coupled plasma spectroscopy. Given the universal need for a better platinate, we anticipate this coupling of nanotechnology and structure-activity relationship to rationally reengineer cisplatin could have a major impact globally in the clinical treatment of cancer.
Keywords: cancer; chemotherapy; nanomedicine

Highly selective claisen-schmidt condensation catalyzed by silica chloride under solvent-free reaction conditions - Hazarkhani, Hassan; Kumar, Pradeep; Kondiram, Kadam Sachin; Gadwal, Ikhlas M. Shafi (Synthetic Communications, 2010)
Silica chloride serves as a useful catalyst in the cross-aldol condensation, leading to the synthesis of a wide variety of bisarylidene cycloalkanones and chalcones. The catalyst showed high selectivity; self-condensation of ketones was not observed.
Keywords: Aldol reaction; arylidene cycloalkanone; Claisen-Schmidt; condensation; silica chloride

In situ encapsulation of pt nanoarchitectures of varying morphologies in mesoporous compounds - Prashar, Atul K.; Hodgkins, Robert P.; Chandran, Jima N.; Rajamohanan, P. R.; Devi, R. Nandini (Chemistry of Materials, 2010)
Nanoparticle morphology could be engineered and fine-tuned based on a novel in situ template method Different shapes of platinum nanoparticles were obtained from very low concentrations of precursors and could be isolated exclusively inside the mesochannels of SBA-15 This was achieved by dispersing a platinum precursor in surfactant modified polymer to different extents and using these composite materials as templates for the formation of mesoporous silica [PtCl(6)](2-) interacts with the cationic headgroup of the surfactant and facilitates the isolation of precursors within the composite template leading to the formation of nanoparticles molded by the walls of the mesochannels when calcined When this [PtCl(6)](2-)-surfactant-polymer micelle composite is aged for different duration, Pt nanoparticles of various morphologies like spheroids, nano rugby balls, and nanorods are obtained

In vitro regeneration of semecarpus anacardium L. from axenic seedling-derived nodal explants - Panda, Bhuban Mohan; Hazra, Sulekha (Trees-Structure and Function, 2010)
Semecarpus anacardium (Anacardiaceae), a deciduous forest tree, is a potent source of medicinal compounds. Poor seed viability of this species limits the conventional propagation practice. Proliferation of shoots from axillary meristem was achieved in semisolid WPM medium supplemented with BAP 4.44 mu M and KN 4.64 mu M. Factors including culture vessels, gelling agents and antioxidants were identified and optimized for proliferation and growth of shoots in vitro. Cotton-plugged culture vessels were more favorable. Phytagel 0.2% as gelling agent and activated charcoal 0.2% as antioxidant were superior to other agents and antioxidants tested. All the shoots rooted in half-strength WPM liquid medium with IBA 2.46 mu M. Rooted shoots survived (91%) in the soil-sand 1:1 mixture. Ex vitro rooting of shoots and hardening of plants were achieved in 80% of the explants in the soil-sand mixture. Hardened plants were maintained in a greenhouse. This is the first report on in vitro regeneration of Semecarpus anacardium.
Keywords: Antioxidants; Culture vessels; Ex vitro rooting; Gelling agents; Medicinal tree; micropropagation

Magnetic, dielectric and complex impedance spectroscopic studies of nanocrystalline Cr substituted Li-ferrite - Hankare, P. P.; Patil, R. P.; Sankpal, U. B.; Garadkar, K. M.; Sasikala, R.; Tripathi, A. K.; Mulla, Imtiaz S. (Journal of Magnetism and Magnetic Materials, 2010)
Nanocrystalline Li0.5Fe2.5-xCrxO4 (2.5 <= x >= 0) ferrites were prepared by a sol-gel autocombustion route. X-ray diffraction was employed to confirm the cubic spinel phase formation of the ferrites. The lattice parameter decreases with increase in Cr content. The saturation magnetization, coercivity and remanance were studied as a function of Cr content. The dielectric constant and dielectric loss were measured as a function of frequency in the frequency range 20 Hz-1 MHz. Frequency dependence of dielectric constant shows dielectric dispersion due to the Maxwell-Wagner type of interfacial polarization. In order to understand the conduction mechanism, complex impedance measurements were carried out. The substitution of chromium plays an important role in changing the dielectric and magnetic properties of lithium ferrites. (C) 2010 Published by Elsevier B.V.
Keywords: Complex impedance; dielectric response; Ferrites; Magnetic hysteresis; Sol-gel synthesis; X-ray diffraction

Measurements and molecular interactions for N,N-dimethylformamide with ionic liquid mixed solvents - Attri, Pankaj; Reddy, P. Madhusudan; Venkatesu, P.; Kumar, Anil; Hofman, T. (Journal of Physical Chemistry B, 2010)
To understand the molecular interactions between N,N-dimethylformamide (DMF) with two families of ionic liquids (ILs), we have measured thermophysical properties such as densities (rho) and ultrasonic sound velocities (a) over the whole composition range at 25 degrees C under atmospheric pressure. The excess molar volume (V(E)) and the deviation in isentropic compressibilities (Delta K(s)) were predicted using these properties as a function of the concentration of IL. These results are fitted to the Redlich-Kister polynomials. The materials investigated in the present study included two families of ILs such as ammonium salts and imidazolium salts. Diethylammonium acetate ([Et(2)NH][CH(3)COO], DEAA), triethylammonium actetate ([Et(3)NH][CH(3)COO], TEAA), triethylammonium dihydogen phosphate ([Et(3)NH][H(2)PO(4)], TEAP), and triethylammonium sulfate ([Et(3)NH][HSO(4)], TEAS) are ammonium salts and l-benzy1-3-methylimidazolium chloride (Bmiml[Cl]) belongs to the imidazolium family. The intermolecular interactions and structural effects were analyzed on the basis of the measured and the derived properties. A qualitative analysis of the results is discussed in terms of the ion dipole, ion-pair interactions, and hydrogen bonding between ILs and DMF molecules and their structural factors.

Molecular electric dipole moments using the GVVPT2 variant of multireference perturbation theory - Theis, Daniel; Khait, Yuriy G.; Pal, Sourav; Hoffmann, Mark R. (Chemical Physics Letters, 2010)
A Lagrangian approach for electric dipoles within second order Generalized Van Vleck Perturbation Theory (GVVPT2) is presented. The Lagrangian approach for this response property requires that only one, perturbation-independent, set of simultaneous equations needs to be solved. The presented formulation is demonstrated numerically on several well studied molecules at their equilibrium bond lengths and on the complete potential energy curves of the ground and first excited states of LiH. Numerical corroboration of the expected continuity for molecular properties for the GVVPT2 method is observed. It is seen that the GVVPT2 electric dipoles are in good agreement with experiment and with other high accuracy theoretical methods. (C) 2010 Elsevier B.V. All rights reserved.

Non-covalent interactions in extended systems described by the effective fragment potential method: theory and application to nucleobase oligomers - Ghosh, Debashree; Kosenkov, Dmytro; Vanovschi, Vitalii; Williams, Christopher F.; Herbert, John M.; Gordon, Mark S.; Schmidt, Michael W.; Slipchenko, Lyudmila V.; Krylov, Anna I. (Journal of Physical Chemistry A, 2010)
The implementation of the effective fragment potential (EFP) method within the Q-CHEM electronic structure package is presented. The EFP method is used to study noncovalent π-π and hydrogen-bonding interactions in DNA strands. Since EFP is a computationally inexpensive alternative to high-level ab initio calculations, it is possible to go beyond the dimers of nucleic acid bases and to investigate the asymptotic behavior of different components of the total interaction energy. The calculations demonstrated that the dispersion energy is a leading component in π-stacked oligomers of all sizes. Exchange-repulsion energy also plays an important role. The contribution of polarization is small in these systems, whereas the magnitude of electrostatics varies. Pairwise fragment interactions (i.e., the sum of dimer binding energies) were found to be a good approximation for the oligomer energy.

Novel poly(amide-hydrazide)s and copoly(amide-hydrazide)s from Bis-(4-aminobenzyl) hydrazide and aromatic diacid chlorides: synthesis and characterization - Medhi, M.; Patil, A. S.; Halhalli, Mahadeo R.; Choubey, A.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Journal of Applied Polymer Science, 2010)
A new aromatic diamine, viz., bis-(4-aminobenzyl) hydrazide (BABH), which contains preformed hydrazide and methylene linkage, was synthesized starting from alpha-tolunitrile. The BABH and intermediates involved in its synthesis were characterized by spectroscopic methods. Novel poly(amide-hydrazide)s were synthesized by low temperature solution polycondensation of BABH with isophthaloyl chloride (IPC) and terephthaloyl chloride (TPC). Furthermore, two series of copoly(amide-hydrazide)s, based on different mol % of BABH and bis-(4-aminophenyl) ether (ODA) with IPC/TPC were also synthesized. Poly(amidehydrazide)s and copoly(amide-hydrazide)s were characterized by inherent viscosity [eta(inh)], FTIR, solubility, X-ray diffraction (MUD), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The polycondensation proceeded smoothy and afforded the polymers with inherent viscosities in the range of 0.18-093 dL/g in (NMP + 4% LiCl) at 30 degrees C +/- 0.1 degrees C. These polymers dissolved in DMAc, NMP or DMSO containing LiCl. The solubility of copolymers was considerably improved in line with less crystalline nature due to random placement of constituent monomers during the copolymerization. XRD data indicated that poly(amide-hydrazide)s from BABH alone and IPC/TPC had higher crystallinity than the corresponding copoly(amide-hydrazide)s derived from a mixture of BABH and bis-(4-aminophenyl) ether (ODA). Polymers showed initial weight loss around 160 degrees C which is attributed to the cyclodehydration leading to the formation of corresponding poly(amide-oxadiazole)s. Copolyamide-hydrazides showed, T(max) between 400 and 540 degrees C which is essentially the decomposition of poly(amide-oxadiazole)s. (C) 2010 Wiley Periodicals, Inc. J App Polym Sci 116: 2441-2450, 2010
Keywords: bis-(4-aminobenzyl) hydrazide; poly(amide-hydrazide); structure-property relations; Thermogravimetric analysis (TGA); x-ray diffractograms

Pd-catalyzed one-pot chemoselective hydrogenation protocol for the preparation of carboxamides directly from azides - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Thierry, Josiane; Dodd, Robert H. (Tetrahedron Letters, 2010)
Carboxamides were obtained efficiently in high yields from azides on reaction with the corresponding pre-formed activated carboxylic acids in a single-step reductive transformation using hydrogen atmosphere (balloon) under Pd/BaSO(4) or Pd/CaCO(3) catalysis. The method is highly chemoselective and compatible with extremely labile functional groups such as benzyl carbamates, benzyl ethers, benzyl esters, and olefins. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Azide; Carboxamide; Catalytic hydrogenation; Chemoselective; Palladium; Succinimide ester

Preparation and characterization of CuInSe2 thin films by chemical bath deposition technique - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2010)
Copper indium diselenide (CIS) thin films have been deposited using a precursor solution containing copper sulphate, indium trichoride, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium at room temperature. The as grown brown colored films were found to be well adherent to glass substrates. The films were characterized by X-ray diffraction, scanning electron microscopy, atomic absorption spectroscopy, optical absorption, electrical resistivity, and thermo electric measurement techniques. The analysis of optical absorption data shows band-gap energy (E-g) to be 1.1 eV. The electrical resistivity of the thin film was found to be of the order of 10(2) (Omega cm). Thermoelectric power measurement shows n-type conduction. (C) 2010 Published by Elsevier B.V.
Keywords: CuInSe2; Optical properties; Thin films; X-ray diffraction

Relatedness of Indian flax genotypes (Linum usitatissimum L.): an inter-simple sequence repeat (ISSR) primer assay - Rajwade, Ashwini V.; Arora, Ritu S.; Kadoo, Narendra Y.; Harsulkar, Abhay M.; Ghorpade, Prakash B.; Gupta, Vidya S. (Molecular Biotechnology, 2010)
The objective of this study was to analyze the genetic relationships, using PCR-based ISSR markers, among 70 Indian flax (Linum usitatissimum L.) genotypes actively utilized in flax breeding programs. Twelve ISSR primers were used for the analysis yielding 136 loci, of which 87 were polymorphic. The average number of amplified loci and the average number of polymorphic loci per primer were 11.3 and 7.25, respectively, while the percent loci polymorphism ranged from 11.1 to 81.8 with an average of 63.9 across all the genotypes. The range of polymorphism information content scores was 0.03-0.49, with an average of 0.18. A dendrogram was generated based on the similarity matrix by the Unweighted Pair Group Method with Arithmetic Mean (UPGMA), wherein the flax genotypes were grouped in five clusters. The Jaccard's similarity coefficient among the genotypes ranged from 0.60 to 0.97. When the omega-3 alpha linolenic acid (ALA) contents of the individual genotypes were correlated with the clusters in the dendrogram, the high ALA containing genotypes were grouped in two clusters. This study identified SLS 50, Ayogi, and Sheetal to be the most diverse genotypes and suggested their use in breeding programs and for developing mapping populations.
Keywords: ALA; Alpha linolenic acid; Diversity assessment; Linseed; Oil content; Omega-3 fatty acid

Room temperature synthesis of rutile TiO2 hierarchical nanoneedle flower morphology for dye sensitized solar cell - Hyam, Rajeshkumar S.; Bhosale, Reshma K.; Lee, Wonjoo; Han, Sung-Hwan; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2010)
Rutile TiO2 nanoneedle flowers (representing concurrent nano-micro hierarchical morphology) with high shape anisotropy ratio are synthesized at room temperature by using a simple and efficient one step electrochemical process of anodic dissolution. This process employs highly acidic bath of perchloric acid (pH < 2) and a large current density on the surface of Titanium foil to form nanostructures. The diameter and length of rutile TiO2 nanoneedle is similar to 8 nm and 100 nm respectively (aspect ratio > 10). Dye sensitized solar cell (DSSC) configured using such rutile TiO2 flowers is shown to exhibit IPCE of 30% and power conversion efficiency of similar to 3.6%.
Keywords: Anodization; DSSC; Nanoneedles; Rutile TiO2

Selective hydrogenolysis of glycerol to 1,2-propanediol: comparison of batch and continuous process operations - Rode, Chandrashekhar V; Ghalwadkar, Ajay A.; Mane, R. B.; Hengne, Amol M.; Jadkar, Sachin T.; Biradar, Narayan S. (Organic Process Research & Development, 2010)
The screening of copper chromite catalysts with various promoters such as Al, Zn, and Ba for glycerol hydrogenolysis to 1,2-propanediol (1,2-PDO) in a batch reaction showed that Cu-Cr (Ba) catalyst gave the highest conversion of 34% and selectivity of 84% to 1,2-PDO. In a continuous operation (23 g catalyst bed) the same catalyst showed higher conversion of glycerol and selectivity for 1,2-PDO of 65% and > 90%, respectively, with an on-stream activity of similar to 800 h. Better performance in a continuous operation could be due to the in situ activation of the catalyst, suppression of glycerol cracking to ethylene glycol, as well as excessive hydrogenation of 1,2-PDO to 2-propanol due to lower contact time of 1.3 h as compared to that in a batch operation (5 h). Effects of various process parameters on conversion and selectivity also have been compared for batch and continuous operations.

Synthesis and characterization of nanocrystalline zinc substituted nickel ferrites - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Sasikala, R.; Tripathi, A. K.; Garadkar, K. M. (Journal of Alloys and Compounds, 2010)
Nanocrystalline zinc substituted nickel ferrites, Ni(1-x)Zn(x)Fe(2)O(4) (0.0 <= x <= 1.0) have been prepared by citrate gel auto-combustion method. The effect of zinc ion content on structural, electrical transport and magnetic properties has been studied. The X-ray diffraction (XRD) pattern revealed that, all the compositions possess single-phase spinel structure. The nano-sized grain structure formation was confirmed by transmission electron microscopy (TEM). The dc electrical resistivity shows the samples are semiconducting in nature. The magnetic measurements showed that the composition Ni(0.6)Zn(0.4)Fe(2)O(4) has maximum saturation magnetization (M(s)) while high coersivity (Hc) for ZnFe(2)O(4). Thermoelectric power measurement study showed that the compounds, with x <= 0.4 are p-type and for x > 0.4 behaves n-type conduction mechanism. (C) 2010 Published by Elsevier B.V.
Keywords: Electron microscopy; Magnetic; Sintering; X-ray diffraction

Synthesis and characterization of new aromatic polyesters containing cardo decahydronaphthalene groups - Honkhambe, Pandurang N.; Bhairamadgi, Nagendra S.; Biyani, Mahesh V.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (European Polymer Journal, 2010)
Three cardo bisphenols containing decahydronaphthalene group viz., 4,4'-(octahydro-2(1H)-naphthylidene)bisphenol, 4,4'-(octahydro-2(1H)-naphthylidene)bis-3-methylphenol and 4,4'-(octahydro-2(1H)-naphthylidene)bis-3,5-dimethylphenol were synthesized starting from commercially available 2-naphthol and were utilized for synthesis of new aromatic polyesters by phase transfer-catalyzed interfacial polycondensation with isophthaloyl chloride, terephthaloyl chloride and a mixture of isophthaloyl chloride and terephthaloyl chloride (50:50 mol %). Inherent viscosities and number average molecular weights (M(n)) of polyesters were in the range 0.35-0.84 dL/g and 13300-48,500 (Gel Permeation Chromatography, polystyrene standard), respectively. Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methy1-2-pyrrolidinone at room temperature and could be cast into tough, transparent and flexible films from their chloroform solutions. Wide-angle X-ray diffraction measurements revealed the amorphous nature of polyesters. The glass transition temperature of polyesters was in the range 207-287 degrees C. The temperature at 10% weight loss (T(10)), determined from thermogravimetric analysis of polyesters, was in the range 425-460 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: bisphenol; Cardo; Decahydronaphthalene; polyester; Structure-property relationship

Synthesis and characterization of new aromatic polyesters containing pendent naphthyl units - Honkhambe, Pandurang N.; Biyani, Mahesh V.; Bhairamadgi, Nagendra S.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2010)
Two bisphenols, viz., 4,4'-[1-(2-naphthaleny-1)ethylidene]bisphenol and 4,4'-[1-(2-naphthalenyl) ethylidene]bis-3-methylphenol were prepared by condensation of commercially available 2-acetonaphthanone with phenol and o-cresol, respectively. A series of new aromatic polyesters containing pendent naphthyl units was synthesized by phase-transfer-catalyzed interfacial polycondensation of these bisphenols with isophthaloyl chloride, terephthaloyl chloride, and a mixture of isophthaloyl chlorideiterephthaloyl chloride (50 : 50 mol %). Inherent viscosities of polyesters were in the range 0.83-1.76 dL g(-1), while number average molecular weights (M(n)) were in the range 61,000-235,000 g mol(-1). Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, m-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetarnide, and 1-methyl-2-pyrrolidinone at room temperature. Tough, transparent, and flexible films were cast from a solution of polyesters in chloroform. X-Ray diffraction measurements displayed a broad halo at 20 congruent to 19 degrees indicating the amorphous nature of polyesters. Glass transition temperatures of polyesters were in the range 209-259 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of polyesters was in the range 435-500 degrees C indicating their good thermal stability. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 2545-2552, 2010
Keywords: Aromatic polyesters; bisphenol; interfacial polycondensation; pendent naphthyl units

Synthesis and characterization of nickel selenide thin films deposited by chemical method - Hankare, P. P.; Jadhav, B. V.; Garadkar, K. M.; Chate, P. A.; Mulla, Imtiaz S.; Delekar, S. D. (Journal of Alloys and Compounds, 2010)
Nickel selenide thin films have been deposited using chemical bath method on non-conducting glass substrates in a tartarate bath containing nickel sulphate octahydrate, hydrazine hydrate, sodium seleno-sulphate in an aqueous alkaline medium. The grown films were uniform, well adherent and black in color. The films were characterized using X-ray diffraction, scanning electron microscopy, optical absorption and electrical measurements. The nickel selenide thin film revealed polycrystalline nature with hexagonal system. The direct optical band gap of the film was found to be 1.61 eV. Electrical resistivity of film was observed in the order of 10(3) (Omega cm) with p-type conduction mechanism. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Crystal growth; Semiconductors; Thin films; X-ray diffraction

Synthesis of aculeatins A and B via iterative hydrolytic kinetic resolution - Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A simple and concise approach for the synthesis of aculeatins A and B starting from (+/-)-epichlorohydrin is described. The synthetic strategy features Jacobsen's hydrolytic kinetic resolution and a Linchpin coupling as key steps.
Keywords: aculeatins; Epoxide; Hydrolytic kinetic resolution; Linchpin coupling; spirocyclization

Template assisted highly ordered novel self assembly of micro-reservoirs and its replication - Hire, Santosh L.; Shelke, Manjusha V.; Kale, Vinayak S.; Galopin, Elisabeth; Kulkarni, Mohan G.; Boukherroub, Rabah; Ogale, Satishchandra B. (Lab on a Chip, 2010)
A novel method is developed for template assisted fabrication of a regular assembly of microcavity arrays. Simple micropatterns on PDMS mold are used to create complex geometries via solvent vapor back pressure in a biodegradable polymer. Cavities are in turn replicated in complimentary PDMS mushroom like microstructures.

Tensile properties, cell adhesion, and drug release behavior of chitosan-silver-gelatin nanohybrid films and scaffolds - Rana, V. K.; Kushwaha, Omkar S.; Singh, RajPal; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Drug-loaded nanohybrid films and porous scaffolds were prepared using chitosan, Ag nanoparticles and gelatin using a solution casting and freeze-drying method, respectively. Gelatin was used to incorporate the cell onto the surface of the scaffolds and the nanohybrid films. 1-[2-hydroxyethyl]-2-methyl-5-nitroimidazole) (Metronidazole (MTZ) was used as a model drug. The small percentage of Ag nanoparticles in the nanohybrid films and scaffolds produced significantly higher cell proliferation and levels of drug release. The tensile properties showed improvement in strength by Ag nanoparticles reinforcement at the expense of elongation.
Keywords: carcinogenic metronidazole; cell proliferation; chitosan-Ag-gelatin nanohybrids; drug release; nano-hybrids; scaffolds

Asymmetric total synthesis of (2S,3S)-3-hydroxypipecolic acid - Chavan, Subhash P.; Dumare, Nilesh B.; Harale, Kishor R.; Kalkote, Uttam R. (Tetrahedron Letters, 2011)
A synthetic route to (2S,3S)-3-hydroxypipecolic acid was achieved from readily available nonchiral pool starting material cis-2-butene-1,4-diol and involved Claisen orthoester rearrangement, Sharpless asymmetric dihydroxylation and intramolecular lactamisation of azido lactone as the key steps. (C) 2010 Elsevier Ltd. All rights reserved.

Biochemical characterisation of alpha-amylase inhibitors from achyranthes aspera and their interactions with digestive amylases of coleopteran and lepidopteran insects - Hivrale, Vandana K.; Chougule, Nanasaheb P.; Giri, Ashok P.; Chhabda, Pavan J.; Kachole, Andmanvendra S. (Journal of the Science of Food and Agriculture, 2011)
BACKGROUND: Starchy seeds are an important food and a source of dietary ingredients in many countries. However, they suffer from extensive predation by bruchids (weevils) and other pests. alpha-Amylase inhibitors are attractive candidates for the control of seed weevils, as these insects are highly dependent on starch as an energy source. RESULTS: A proteinaceous alpha-amylase inhibitor from the seeds of Achyranthes aspera was identified, purified and characterised. In electrophoretic analysis, two prominent amylase inhibitor activity bands (AI1 and AI2) were detected. The inhibitor was purified 9.99-fold with 1206.95 total amylase inhibitor units mg(-1) protein. The molecular weight of the purified inhibitor was around 6 kDa. The isolated alpha-amylase inhibitor was found to be resistant to heat and proteolysis. Feeding analysis of Callosobruchus maculatus larvae on a diet containing seed powder of A. aspera revealed that survival of the larvae was severely affected, with the highest mortality rate occurring on the fifth day of feeding. The isolated inhibitor inhibited the majority of amylase isoforms of C. maculatus, Tribolium confusum and Helicoverpa armigera in electrophoretic analysis and solution assays. CONCLUSION: The information obtained in the present investigation could be useful for a genetic engineering approach that would make seeds resistant to storage pest infestations. (C) 2011 Society of Chemical Industry
Keywords: Achyranthes aspera; Amylase inhibitors; amylases; Callosobruchus maculatus; Tribolium confusum

Chlorate ion mediated rutile to anatase reverse phase transformation in the TiO2 nanosystem - Bhosale, Reshma; Hyam, Rajeshkumar S.; Dhanya, P.; Ogale, Satishchandra B. (Dalton Transactions, 2011)
Rutile TiO2 nanoneedles (8 nm x 100 nm) synthesized at room temperature by anodization in perchloric acid (pH < 1) are shown to undergo an interesting reverse phase transformation to anatase nanoparticles (8 nm) at 300 degrees C only if the chlorate ions are maintained in the ambient medium. When chlorate ions are removed by multiple washing, the rutile phase and the needle morphology are maintained. The mechanism of formation of the ion-stabilized solid and its thermal evolution is discussed.

Comparative genomics of the pathogenic ciliate Ichthyophthirius multifiliis, its free-living relatives and a host species provide insights into adoption of a parasitic lifestyle and prospects for disease control - Coyne, Robert S.; Hannick, Linda; Shanmugam, Dhanasekaran; Hostetler, Jessica B.; Brami, Daniel; Joardar, Vinita S.; Johnson, Justin; Radune, Diana; Singh, Irtisha; Badger, Jonathan H.; Kumar, Ujjwal; Saier, Milton; et al. (Genome Biology, 2011)
Background: Ichthyophthirius multifiliis, commonly known as Ich, is a highly pathogenic ciliate responsible for 'white spot', a disease causing significant economic losses to the global aquaculture industry. Options for disease control are extremely limited, and Ich's obligate parasitic lifestyle makes experimental studies challenging. Unlike most well-studied protozoan parasites, Ich belongs to a phylum composed primarily of free-living members. Indeed, it is closely related to the model organism Tetrahymena thermophila. Genomic studies represent a promising strategy to reduce the impact of this disease and to understand the evolutionary transition to parasitism. Results: We report the sequencing, assembly and annotation of the Ich macronuclear genome. Compared with its free-living relative T. thermophila, the Ich genome is reduced approximately two-fold in length and gene density and three-fold in gene content. We analyzed in detail several gene classes with diverse functions in behavior, cellular function and host immunogenicity, including protein kinases, membrane transporters, proteases, surface antigens and cytoskeletal components and regulators. We also mapped by orthology Ich's metabolic pathways in comparison with other ciliates and a potential host organism, the zebrafish Danio rerio. Conclusions: Knowledge of the complete protein-coding and metabolic potential of Ich opens avenues for rational testing of therapeutic drugs that target functions essential to this parasite but not to its fish hosts. Also, a catalog of surface protein-encoding genes will facilitate development of more effective vaccines. The potential to use T. thermophila as a surrogate model offers promise toward controlling 'white spot' disease and understanding the adaptation to a parasitic lifestyle.

Convenient formal synthesis of (2S,3S)-3-hydroxy pipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Dumare, Nilesh B.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2011)
A convenient synthesis of (2S,3S)-3-hydroxy pipecolic acid starting from inexpensive and easily available L-(+)-tartaric acid has been described. (C) 2011 Elsevier Ltd. All rights reserved.

Enantiospecific route to (+)-(1R, 3S)-cis-chrysanthemic acid from (-)-D-pantolactone(1) - Hajare, Atul K.; Datrange, Laxmikant S.; Murthy, Y. L. N.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2011)
In this paper, a novel route for the synthesis of (+)-(1R,3S)-cis-chrysanthemic acid is described. The use of readily available (-)-D-pantolactone as a starting point, application of ring-closing metathesis to form the cyclopentene intermediate, and Haller-Bauer/Grob-type fragmentation to form the target compound are the highlights of the present synthesis.
Keywords: alkenes; Metathesis; ring closure; stereoselective synthesis; Wittig reaction

Enhanced DNA binding of 9-omega-amino alkyl ether analogs from the plant alkaloid berberine - Islam, Md Maidul; Basu, Anirban; Hossain, Maidul; Sureshkumar, Gopalsamy; Hotha, Srinivas; Kumar, Gopinatha Suresh (DNA and Cell Biology, 2011)
To understand the structure-activity relationship of isoquinoline alkaloids, absorption, fluorescence, circular dichroism, and thermodynamics were employed to study the interaction of five C-9-omega-amino alkyl ether analogs from the plant alkaloid berberine with double-stranded calf thymus DNA. The C-9 derivatization resulted in dramatic enhancements in the fluorescence emission of these compounds. The most remarkable changes in the spectral and binding properties were in the BC4 and BC5 derivatives. Interactions of these analogs, which have an additional recognition motif with DNA, were evaluated through different spectroscopic and calorimetric titration experiments. The analogs remarkably enhanced the DNA binding affinity and the same was directly dependent on the alkyl chain length. The analog with six alkyl chains enhanced the DNA binding affinity by about 33 times compared with berberine. The binding became more entropically driven with increasing chain length. These results may be of potential use in the design of berberine derivatives and understanding of the structure-activity relationship for improved therapeutic applications.

Enhanced DSSC performance with high surface area thin anatase TiO2 nanoleaves - Dhas, Vivek V.; Muduli, Subas; Agarkar, Shruti A.; Rana, Abhimanyu; Hannoyer, Beatrice; Banerjee, Rahul; Ogale, Satishchandra B. (Solar Energy, 2011)
Thin anatase TiO2 nanoleaves (NLs) with high surface area (similar to 93 m(2)/g) are synthesized by hydrothermal route and dye-sensitized solar cells (DSSC) made using such NLs are compared with those made with hydro-thermally synthesized TiO2 nanoparticles and the Degussa P25 powder. The NLs-based DSSCs show increment of 16% and 24% in the total conversion efficiency over the cells made with NPs and P25 respectively. Interestingly, the highest increment in the conversion efficiency (similar to 35%) is achieved for cells made using a 50:50 (wt/wt) mixture of NLs and NPs. In this case the dye loading is found to be >50% higher than the case of NP films. Moreover the DC resistance of diffusion of I-3(-) in electrolyte (as revealed by the electrochemical impedance spectroscopy) is substantially lower than the NP film case, other cell parameters being nominally comparable. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dye-sensitized solar cells; Electrochemical impedance spectroscopy; hydrothermal

Evidence of lateral heat transfer during laser assisted atom probe tomography analysis of large band gap materials - Bachhav, Mukesh N.; Danoix, R.; Vurpillot, F.; Hannoyer, Beatrice; Ogale, Satishchandra B.; Danoix, F. (Applied Physics Letters, 2011)
Investigation of wustite (FeO), iron (Fe), and silicon (Si) specimens by infrared laser assisted three dimensional atom probe tomography shows evidence of confined surface absorption of the laser energy as the mechanism of laser assisted field evaporation for high band gap materials. The absorption region is shown to be located on the laser illumination side, close to the specimen apex. A simple model based on thermal diffusivity and spatial extent of the absorption region is derived and applied to the experimental results. The values of thermal diffusivity thus obtained are in good agreement with the published data. (C) 2011 American Institute of Physics. [doi:10.1063/1.3622647]

Facile synthesis of unusual glycosyl carbamates and amino acid glycosides from propargyl 1,2-orthoesters as glycosyl donors - Shaikh, Ashif Y.; Sureshkumar, Gopalsamy; Pati, Debasish; Sen Gupta, Sayam; Hotha, Srinivas (Organic & Biomolecular Chemistry, 2011)
Propargyl 1,2-O-orthoesters are exploited for the synthesis of 1,2-trans O-glycosides of protected amino acids. N-Fmoc- and N-Cbz protected serine/threonine - benzyl/methyl esters reacted well with glucosyl-, galactosyl-, mannosyl- and lactosyl- derived propargyl 1,2-orthoesters affording respective 1,2-trans glycosides in good yields under AuBr(3)/4 angstrom MS Powder/CH(2)Cl(2)/rt. t-Boc serine derivative gave serine 1,2-orthoester and glycosyl carbamate. Optimized conditions enabled preparation of new glycosyl carbamates from N-Boc protected amines in a single step using gold catalysts and propargyl 1,2-orthoesters in excellent yields.

Fluorescence resonance energy transfer from tryptophan to folic acid in micellar media and deionised water - Mote, U. S.; Patil, S. R.; Bhosale, Siddharth H.; Han, Sung-Hwan; Kolekar, G. B. (Journal of Photochemistry and Photobiology B-Biology, 2011)
The fluorescence resonance energy transfer (FRET) from tryptophan (Trp) to folic acid (FA) in aqueous sodiumdodecyl sulphate, cetyltrimethyl ammonium bromide, and Brij-35 as well as deionised water was investigated using steady state and time resolved fluorescence techniques. The data obtained from steady state fluorescence spectral studies and time resolved measurement indicated that the FRET from Trp to FA occurred most effectively in aqueous sodium dodecyl sulphate micellar solutions. The distance between Trp and FA were evaluated. Binding constant, number of binding sites and thermodynamic parameters were determined for Trp-FA interactions in deionised water. The values of the thermodynamic parameters suggest that the hydrophobic forces and hydrogen bonding are the key interacting forces between Trp-FA interaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Fluorescence quenching; Fluorescence resonance energy transfer (FRET); Folic acid; Foster theory; Stern-Volmer plot; Tryptophan

From graphite oxide to highly water dispersible functionalized graphene by single step plant extract-induced deoxygenation - Mhamane, Dattakumar; Ramadan, Wegdan; Fawzy, Manal; Rana, Abhimanyu; Dubey, Megha; Rode, Chandrashekhar; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra (Green Chemistry, 2011)
We report a single step facile synthesis of highly water dispersible functionalized graphene nanosheets by plant extract-induced deoxygenation of graphite oxide (GO). The results of various characterizations reveal that the properties of such plant extract-converted graphene nanosheets (PCGN) are comparable to chemically converted graphene nanosheets (CCG). These results open a green route to the emerging graphene-based technologies.

Gold catalyzed glycosidations for the synthesis of sugar acrylate/acrylamide hybrids and their utility - Thadke, Shivaji A.; Kar, Mritunjoy; Sen Gupta, Sayam; Hotha, Srinivas (Carbohydrate Research, 2011)
Propargyl glyco 1,2-orthoesters were exploited for the efficient synthesis of interesting glycomonomers such as glyco-acrylates and acrylamides using gold catalysts. It was observed that propargyl glyco 1,2-orthoesters with hydroxyethyl acrylates gives very good yield of the corresponding glyco-acrylates in a single step in the presence of catalytic amount of gold(III) catalyst; whereas, gold catalyzed glycosidation reaction on hydroxyethyl acrylamides was found to yield the corresponding acrylamidoyl 1,2-orthoester which was then converted to the corresponding glycol-acrylamide in the presence of catalytic amount of TMSOTf. Synthesized glyco-acrylate/acrylamide monomers are shown to undergo thiolate addition as well as free radical polymerization (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; Glycoacrylamides; Glycoacrylates; Glycopolymers; glycosylation; Gold

Growth and structural properties of Mg-N (N=10-56) clusters: density functional theory study - Heidari, Ideh; De, Sandip; Ghazi, S. M.; Goedecker, Stefan; Kanhere, Dilip G. (Journal of Physical Chemistry A, 2011)
Using the minima hopping global geometry optimization method on density functional potential energy surface, we have studied the structural and electronic properties of magnesium clusters for a size range of Mg-N where N = 10-56. Our exhaustive search reveals that most of our global minima are nonsymmetric in the size range above N = 20. We elucidate the evolutionary trend of the entire series and present more details about the peculiar growth of the clusters. For N> 20, it is possible to divide the cluster into two regions: the core region and the surface region. It turns out that the growth follows a peculiar cyclic pattern where the core and surface grow alternatively. The surface energy, as a function of number of atoms shows a clear signature as the number of atoms in the core increases by one. We have also carried out stability analysis and the stable sizes(magic numbers) agree very well with the experimental magic numbers reported by Diederich [J. Chem. Phys. 2011, 134, 124302]. We point out the similarities and differences between our results and sodium clusters.

Halogen bonding in 2,5-dichloro-1,4-benzoquinone: insights from experimental and theoretical charge density analysis - Hathwar, Venkatesha R.; Gonnade, Rajesh G.; Munshi, Parthapratim; Bhadbhade, Mohan M.; Row, Tayur N. Guru (Crystal Growth & Design, 2011)
Experimental charge density distribution in 2, 5-dichloro-1, 4-benzoquinone has been carried out using high resolution X-ray diffraction data at 90 K to quantitatively evaluate the nature of C-Cl center dot center dot center dot O=C halogen bond in molecular crystals. Additionally, the halogen bond is studied from geometrical point of view and the same has been visualized using Hirshfeld surface analysis. The obtained results from experimental charge density analysis are compared with periodic quantum calculations using B3LYP 6-31G(d,p) level of theory. The topological values at bond critical point, three-dimensional static deformation density features and electrostatic potential isosurfaces unequivocally establish the attractive nature of C-Cl center dot center dot center dot O=C halogen bond in crystalline lattice.

Hierarchical mesoporous bio-polymer/silica composites co-templated by trimethyl chitosan and a surfactant for controlled drug delivery - Rana, Vijay Kumar; Park, Sung Soo; Parambadath, Surendran; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Medchemcomm, 2011)
In this communication, we report the facile synthesis of hierarchical mesoporous bio-polymer/silica composite materials with bimodal mesopores using a dual-template of the cationic N,N,N-trimethyl chitosan (TMCs) and the anionic sodium dodecyl sulfate (SDS) via one-step synthetic strategy. Tetraethoxysilane (TEOS) was used as a silica source. The nitrogen adsorption/desorption measurements and transmission electron microscopy analysis showed the hierarchical structure of the mesoporous bio-polymer/silica composites with bimodal mesopores having an average pore size of 5-7 nm with the visible voids between the silica nanoparticles, which allow the mesoporous bio-polymer/silica composites to encapsulate a large number of guest drug molecules, Ibuprofen (IBU) or 5-fluorouracil (5-FU), due to their high surface area and pore volume. In addition, the mesoporous chitosan-silica composites also had a long term biocompatibility for the target release of the drug molecules to the CEM cells, MCF cells, etc. as well as a pH sensitive controlled release behavior of the drug molecules.

Investigation of wustite (Fe1-xO) by femtosecond laser assisted atom probe tomography - Bachhav, Mukesh N.; Danoix, R.; Danoix, F.; Hannoyer, Beatrice; Ogale, Satishchandra B.; Vurpillot, F. (Ultramicroscopy, 2011)
In this paper, we report results obtained from laser assisted three-dimensional (3-D) atom probe tomography (APT) on wustite (Fe1-xO). Oxides are generally insulating and hence hard to analyse in conventional electrical assisted APT. To overcome this problem, femtosecond laser pulses are used instead of voltage pulses. Here we discuss some aspects of pulsed laser field evaporation and optimization of parameters to achieve better chemical accuracy. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Atom probe tomography; Laser assisted field evaporation; Wustite

Isobutrin from butea monosperma (flame of the forest): a promising new natural sensitizer belonging to chalcone class - Agarkar, Shruti A.; Kulkarni, Roshan R.; Dhas, Vivek V.; Chinchansure, Ashish A.; Hazra, Partha; Joshi, Swati P.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2011)
In this work, ``isobutrin'', an ecofriendly sensitizer that is extracted from Butea monosperma (commonly known as ``Flame of the Forest'') flowers, is introduced. It is a bright yellow pigment belonging to the chalcone class and is examined as a sensitizer for optoelectronic applications. It is observed that chelation of this dye with Ti ions results into a strong dye-TiO(2) charge transfer (DTCT) band in the visible region. This Ti-Isobutrin chelate is stable, irreversible and its formation is studied using Benesi-Hildebrand plot. The locations of HOMO-LUMO states of the Ti-isobutrin chelate and the corresponding band alignment with TiO(2) are obtained. Also, a thermal stability test revealed that isobutrin is stable above 100 degrees C.
Keywords: Butea monosperma; chalcone; dye-sensitized solar cell; isobutrin; sensitizer; TiO(2)

Maghemite (hematite) core (shell) nanorods via thermolysis of a molecular solid of Fe-complex - Chaudhari, N. S.; Warule, S. S.; Muduli, Subas; Kale, B. B.; Jouen, Samuel; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Dalton Transactions, 2011)
An Fe-metal complex with 2'-hydroxy chalcone (2'-HC) ligands [Fe(III) (2'-hydroxy chalcone) 3] is synthesized by a chemical route and is subjected to different thermal treatments. Upon thermolysis in air at 450 degrees C for 3 h the complex yields maghemite (gamma-Fe(2)O(3)) nanorods with a thin hematite (alpha-Fe(2)O(3)) shell. X-Ray diffraction (XRD), Mossbauer spectroscopy, diffuse reflectance spectroscopy (UV-DRS), high resolution transmission electron microscopy (HR-TEM), field emission scanning electron microscopy (FE-SEM) and vibrating sample magnetometry (VSM) are used to characterize the samples. The stability of the ligand and the Fe-complex is further examined by using thermogravimmetric/differential thermal analysis (TGA/DTA). We suggest a residual ligand controlled mechanism for the formation of an anisotropic nanostructure in a crumbling molecular solid undergoing ligand decomposition. Since the band gap of iron oxide is in the visible range, we explored the use of our core shell nano-rod sample for photocatalytic activity for H(2) generation by H(2)S splitting under solar light. We observed high photocatalytic activity for hydrogen generation (75 ml h(-1)).

Magnetite/CdTe magnetic-fluorescent composite nanosystem for magnetic separation and bio-imaging - Kale, Anup; Kale, Sonia; Yadav, Prasad; Gholap, Haribhau; Pasricha, Renu; Jog, Jyoti Prakash; Lefez, Benoit; Hannoyer, Beatrice; Shastry, Padma; Ogale, Satishchandra B. (Nanotechnology, 2011)
A new synthesis protocol is described to obtain a CdTe decorated magnetite bifunctional nanosystem via dodecylamine (DDA) as cross linker. High resolution transmission electron microscopy (HRTEM), energy-dispersive x-ray spectroscopy (EDAX), vibrating sample magnetometry (VSM), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance spectroscopy (DRS) and fluorescence microscopy are used to characterize the constitution, size, composition and physical properties of these superparamagnetic-fluorescent nanoparticles. These CdTe decorated magnetite nanoparticles were then functionalized with anti-epidermal growth factor receptor (EGFR) antibody to specifically target cells expressing this receptor. The EGFR is a transmembrane glycoprotein and is expressed on tumor cells from different tissue origins including human leukemic cell line Molt-4 cells. The magnetite-CdTe composite nanosystem is shown to perform excellently for specific selection, magnetic separation and fluorescent detection of EGFR positive Molt-4 cells from a mixed population. Flow cytometry and confocal laser scanning microscopy results show that this composite nanosystem has great potential in antibody functionalized magnetic separation and imaging of cells using cell surface receptor antibody.

Novel route for rapid biosynthesis of lead nanoparticles using aqueous extract of Jatropha curcas L. latex - Joglekar, Shriram; Kodam, Kisan M.; Dhaygude, Mayur; Hudlikar, Manish (Materials Letters, 2011)
We are reporting a novel, low-cost and eco-friendly route for rapid synthesis of lead nanoparticles by using 0.5% aqueous extract of Jatropha curcas L latex. Lead nanoparticles were characterized initially by UV-vis spectroscopy and shown distinct peak at 218 nm. This peak was highly specific for lead nanoparticles. Formation of Pb (0) was confirmed by X-ray diffraction technique (XRD).Transmission electron microscopy (TEM) was performed for estimating the size and shape of nanoparticles. The average size of lead nanoparticles was found to be in the range of 10 to 12.5 nm. Energy dispersive analysis of X-rays (EDAX) showed distinct peaks of lead. Fourier Transform Infrared Spectroscopy (FTIR) were performed to find the role of cyclic peptides namely curcacycline A (an octapeptide) and curcacycline B (a nonapeptide) as a possible reducing and capping agents present in the latex of Jatropha curcas L. Lead nanoparticles formed by the above method were monodisperse. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: FTIR; Latex; Lead nanoparticles; Nanoparticles

One-step in situ synthesis of NHx-adsorbed rhodium nanocrystals at liquid-liquid interfaces for possible electrocatalytic applications - Patil, V. S.; Krishna, S. R.; Hawaldar, Ranjit R.; Gaikwad, A. B.; Sathaye, S. D.; Patil, K. R. (Journal of Colloid and Interface Science, 2011)
Nearly monodisperse rhodium nanoparticles with adsorbed NHx were synthesized at the CCl4-water interface. The presence of NHx-adsorbed species was confirmed by energy-dispersive X-ray analysis (EDX) and X-ray photoelectron spectroscopy (XPS) studies. The synthesis of controlled size 2-38 nm rhodium particles was studied as a function of reducing agent concentration by transmission electron microscopy (TEM). HRTEM confirmed the formation of rhodium nanoparticles having fringe spacing consistent with reported Rh (1 1 1) planes. The continuity of these films over an area of 1 x 1 pm was revealed by atomic force microscopy (AFM) studies. The electrocatalytic application of these nanostructure Rh-NHx), thin films for formaldehyde oxidation in 0.5 M NaOH was investigated by cyclic voltammetry. The Rh nanoparticles formed by the present strategy are expected to be useful for other catalytic applications also. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Hydrazine hydrate; Liquid-liquid interface; Nanoparticles; Rhodium; Thin films

Ordered mesoporous silica as supports in the heterogeneous asymmetric catalysis - Sahoo, Suman; Bordoloi, Ankur; Halligudi, Shivaraj B. (Catalysis Surveys from Asia, 2011)
Enantioselective synthesis of organic compounds has been studied by homogeneous catalysts for several years. However, these catalysts have yet to make a significant impact on industrial scales for fine chemical synthesis. A primary reason is the designing of a homogeneous asymmetric catalyst, which requires relatively bulky ligands and catalyst recovery and recycling often causes problems. One of the convincing ways to overcome this problem is to immobilise the asymmetric catalyst onto a solid support and the resulting heterogeneous asymmetric catalyst system can, in principle, be readily re-used. A large number of supports such as inorganic oxides including zeolites, alumina, zirconia, silica and organic polymers have been employed as supports in heterogeneous asymmetric catalysis. Therefore, in this review article we have summarized the work done by us in our laboratory on the immobilization of chiral transition metal complexes such as Ru, Ir, Mn and Ti onto ordered mesoporous silica and its asymmetric catalysis. All these immobilized catalysts were well characterized by different physicochemical techniques to confirm the structural retention of the support as well as the active metal complex after immobilization. This report includes our asymmetric catalytic investigations in enantioselective reactions such as hydrogenation of ketones, olefins, oxidation of sulfides and oxidative kinetic resolution of alcohols and sulfoxides through immobilized heterogeneous catalyst systems.
Keywords: Enantioselective hydrogenation; Enantioselective oxidation; Immobilization; Mesoporous silica; Oxidative kinetic resolution

Organocatalytic enantioselective approach to the synthesis of verbalactone and (R)-massoialactone - Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2011)
The organocatalytic enantioselective synthesis of verbalactone and (R)-massoialactone is described. The requisite stereogenic centers of the target molecules were constructed using L-proline-catalyzed alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination. Yamaguchi macrolactonization and ring-closing metathesis were employed as key steps in the syntheses.
Keywords: alpha-aminoxylation; Horner-Wadsworth-Emmons olefination; L-proline; massoialactone; Ring-closing metathesis; verbalactone; Yamaguchi macrolactonization

Photoelectrochemical applications of In2Se3 thin films by chemical deposition - Hankare, P. P.; Rathod, K. C.; Asabe, M. R.; Jadhav, A. V.; Helavi, V. B.; Chavan, Santosh S.; Garadkar, K. M.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Indium selenide films have been synthesized by chemical bath deposition method onto stainless steel plate. The configuration of fabricated cell is n-In2Se3| NaOH(1 M) + S(1 M) + Na2S(1 M) |C-(graphite). Characterization of the photoelectrochemical cell was carried out by studying X-ray diffraction, current-voltage and capacitance-voltage characteristics in the dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that the In2Se3 thin films are n-type semiconductor. The junction ideality factor was found to be 3.24. The flat band potential and the barrier height were found to be 0.720 V and 0.196 eV, respectively. From the study of power output characteristics, open circuit voltage, short circuit current, fill factor and efficiency were found to be 310 mV, 20 mu A, 37.64 and 0.61%, respectively. Photoresponse studies show that the lighted ideality factor is 2.78. Maximum current was observed at 575 nm.

Poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing cardo decahydronaphthalene groups: synthesis and characterization - Honkhambe, Pandurang N.; Pasale, Sharad K.; Bhairamadgi, Nagendra S.; Kumbhar, Kishor P.; Salunkhe, Manikrao M.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
New poly(ether ether ketone)s and poly (ether ether ketone ketone) s were synthesized by polycondensation of each of the three bisphenols, viz., 4,4'-(octahydro-2(1H)-naphthylidene) bisphenol, 4,4'-(octa-hydro-2(1H)-naphthylidene) bis-3-methylphenol, and 4,4'(octahydro-2(1H)-naphthylidene) bis-3,5-dimethylphenol with 4,4'-difluorobenzophenone and 1,3-bis(4-fluorobenzoyl) benzene in a mixture of N,N-dimethylacetamide and toluene [1 : 1 (v/v)] in the presence of anhydrous potassium carbonate. Inherent viscosities of poly(ether ether ketone) s and poly (ether ether ketone ketone) s were in the range 0.32-0.80 dL/g and number-average molecular weights were in the range 16,100-55,900 g/mol. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, and 1-methyl-2-pyrrolidinone at room temperature and could be cast into tough, transparent, and flexible films from their chloroform solutions. Wide angle x-ray diffraction measurements revealed the amorphous nature of poly(ether ether ketone) s and poly (ether ether ketone ketone) s. The glass transition temperature poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 185-251 degrees C. The temperature at 10% weight loss, determined from thermogravimetric analysis, of poly(ether ether ketone) s and poly(ether ether ketone ketone) s in nitrogen atmosphere was in the range 462-493 degrees C indicating their good thermal stability. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1607-1613, 2011
Keywords: bisphenol; cardo decahydronaphthalene; poly(ether ether ketone ketone)s; poly(ether ether ketone)s; Polycondensation; Thermal properties

Propargyl/methyl furanosides as potential glycosyl donors - Vidadala, Srinivasa Rao; Gayatri, Gaddamannugu; Sastry, G. Narahari; Hotha, Srinivas (Chemical Communications, 2011)
Transfuranosylations are not well studied though many similar studies exist for transpyranosylation; herein, we report that propargyl/methyl D-ribf- and D-lyxf- give only 1,2-trans glycosides whereas D-araf- and D-xylf- result in a mixture of 1,2-trans and 1,2-cis glycosides; observed facts are rationalised by computational studies.

Role of promoters in copper chromite catalysts for hydrogenolysis of glycerol - Mane, R. B.; Ghalwadkar, Ajay A.; Hengne, Amol M.; Suryawanshi, Y. R.; Rode, C. V. (Catalysis Today, 2011)
Various copper chromite catalysts with and without promoters were prepared by simultaneous co-precipitation and digestion technique and the role of promoters (Al, Ba and Zn) was investigated for hydrogenolysis of glycerol to 1,2-propylene glycol (1,2-PG) in both batch and continuous operations. Among various promoters studied, copper chromite catalyst with Ba as a promoter showed the highest activity and selectivity of 85% to 1,2-PG. This catalyst was found to be active for more than 800 h in a continuous operation also. Ammonia TPD results showed that barium promoted copper chromite catalyst had the highest acidity which facilitates the dehydration of glycerol to acetol which is the first step in hydrogenolysis of glycerol to 1,2-PG. The effect of barium content and variation in the promoters combination was also studied. (C) 2010 Elsevier B.V. All rights reserved.
1st Joint International Conference of the 8th Tokyo Conference on Advanced Catalytic Science and Technology/5th Asia Pacific Congress on Catalysis, Sapporo, JAPAN, JUL 18-23, 2010
Keywords: 1; 2-Propylene glycol; Acetol; Ammonia TPD; Glycerol hydrogenolysis; Surface acidity

RuCl3-TBHP mediated allylic oxidation of Delta(8(9)) lanosterol derivatives - Shingate, Bapurao B.; Hazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S. (Tetrahedron Letters, 2011)
A variety of Delta(8(9))-lanosterol derivatives were converted into 7,11-dienones using t-butyl hydroperoxide in the presence of ruthenium chloride (RuCl3) in good yields. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Allylic oxidation; Oxygenated steroids; Ruthenium chloride; Steroidal ketones; t-Butyl hydroperoxide

Stereoselective synthesis of (-)-galantinic acid - Dubey, Abhishek; Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2011)
An efficient and highly concise synthesis of (-)-galantinic acid has been achieved using an asymmetric allylation reaction of Garner's aldehyde.
Keywords: Amino alcohol; Chiral pool; iterative asymmetric allylation; Oxidation; stereoselective synthesis

Synthesis and characterization of chemically deposited nickel substituted CdSe thin film - Hankare, P. P.; Jadhav, B. V.; Chate, P. A.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2011)
The technologically important Cd(0.5)Ni(0.5)Se thin film has been developed by solution growth technique on non-conducting glass substrate in tartarate bath containing Cd(+2), Ni(+2) ions and sodium selenosulphate in an aqueous alkaline medium at room temperature. Various preparative conditions of the thin films are outlined. The films were characterized by X-ray diffraction, scanning electron microscope, optical absorption and electrical measurements. The X-ray diffraction study indicates that the film is polycrystalline in nature with hexagonal phase. Scanning electron micrograph shows that the film is homogeneous with well-defined grains. The films have high optical absorption coefficient. Thermoelectric power measurement shows p-type conduction mechanism. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Crystal growth; Electrical conductivity; thin film

Synthesis and characterization of cobalt substituted zinc ferri-chromites prepared by sol-gel auto-combustion method - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Patil, R. P.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Mixed metal oxides having spinel structure shows interesting structural properties. In the present investigation, cobalt substituted zinc ferri-chromites were prepared by sol-gel auto-combustion method. The completion of solid state reaction and the formation of spinel phase were identified using X-ray diffraction technique. All the compounds exhibit cubic spinel symmetry and lattice constant shows an irregular trend with substitution of Co. Infra-red spectral studies shows an two strong bands, one around 600 cm(-1) which is attributed to the intrinsic vibrations of tetrahedral complexes and the other at 400 cm(-1) is due to octahedral one. The morphology and size of the particles was found out by scanning electron microscopy while the elemental compositions by elemental dispersive X-ray spectroscopy. The various compounds of the present system Zn1-xCoxFeCrO4 were also investigated for their thermal and electronic studies.

Synthesis and characterization of organo-soluble poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing pendant pentadecyl chains - More, Arvind S.; Pasale, Sharad K.; Honkhambe, Pandurang N.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
Poly(ether ether ketone)s and poly(ether ether ketone ketone) s containing pendant pentadecyl chains were synthesized by polycondensation of each of the two bisphenol monomers viz, 1,1,1-[bis(4-hydroxyphenyl)-4'-pentadecylphenyl] ethane and 1,1-bis(4-hydroxyphenyl)-3-pentadecyl cyclohexane with activated aromatic dihalides namely, 4,4'-difluorobenzophenone, and 1,3-bis(4-fluorobenzoyl) benzene in a solvent mixture of N,N-dimethylacetamide and toluene, in the presence of anhydrous potassium carbonate. Polymers were isolated as white fibrous materials with inherent viscosities and number average molecular weights in the range 0.70-1.27 dL g(-1) and 76,620-1,36,720, respectively. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were found to be soluble at room temperature in organic solvents such as chloroform, dichloromethane, tetrahydrofuran, and pyridine and could be cast into tough, transparent, and flexible films from their solutions in chloroform. Wide angle X-ray diffraction patterns exhibited a broad halo at around 2 theta = similar to 19 degrees indicating that the polymers containing pentadecyl chains were amorphous in nature. In the small-angle region, diffuse reflections of a typically layered structures resulting from the packing of pentadecyl side chains were observed. The temperature at 10% weight loss, obtained from TG curves, for poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 416-459 degrees C, indicating their good thermal stability. A substantial drop in glass transition temperatures (68-78 degrees C) was observed for poly(ether ether ketone) s and poly(ether ether ketone ketone) s due to ``internal plasticization'' effect of flexible pendant pentadecyl chains. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 121: 3689-3695, 2011
Keywords: alkyl side-chain; Cashew nut shell liquid; CNSL; pentadecyl; poly(arylene ether)s; poly(ether ketone)s; polyethers; renewable

Synthesis and characterization of soluble polyamides from bis-[(4 `-aminobenzyl)-4-benzamide] ether and various diacids - Patil, A. S.; Sayyed, M. M.; Bhairamadgi, Nagendra S.; Han, Sung-Hwan; Maldar, Noormahamad N. (Polymer Bulletin, 2011)
New aromatic diamine containing preformed amide, ether, and methylene; bis-[(4'-aminobenzyl)-4-benzamide] ether (BABE), was synthesized and characterized by FT-IR, NMR, and mass spectrometry. Aromatic-aliphatic polyamides were prepared from BABE with aliphatic/aromatic diacids via Yamazaki's polymerization. The polyamides were characterized by FT-IR, (1)H NMR, inherent viscosity [eta(inh)], solubility tests, differential scanning calorimetry [DSC], thermogravimetric analysis [TGA], and X-ray diffraction [XRD]. Polyamides had inherent viscosities 0.35-0.84 dL/g, soluble in aprotic polar solvents like N-methyl-2-pyrrolidone, N, N-dimethyl acetamide and dimethyl sulphoxide containing LiCl due to an amorphous to partially crystalline morphology; as XRD patterns indicated. DSC analysis of polyamides showed glass transition temperatures 166-268 A degrees C. Polyamides showed high thermal stability as they did not degrade below 300 A degrees C, had 10% weight loss temperature higher than 375 A degrees C, and the char yields at 900 A degrees C were 22-55%; indicating potential applications as engineering materials.
Keywords: Aryl-ether and methylene linkages; Bis-[(4 `-aminobenzyl)-4-benzamide] ether; Direct phosphorylative polycondensation; Soluble aromatic-aliphatic polyamides; Thermal properties

Synthesis and drug-delivery behavior of chitosan-functionalized graphene oxide hybrid nanosheets - Rana, Vijay Kumar; Choi, Myeon-Cheon; Kong, Jin-Yeon; Kim, Gwang Yeon; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Macromolecular Materials and Engineering, 2011)
Chitosan-functionalized graphene oxides (FGOCs) were successfully synthesized. FGOCs were found to significantly improve the solubility of the GO in aqueous acidic media. The presence of organic groups was confirmed by means of XPS and TGA. Restoration of the sp(2) carbon network and exfoliation of graphene sheets were confirmed by Raman spectroscopy, UV-visible spectroscopy and WAXD. The SEM and AFM investigations of the resultant FGOCs showed that most of the graphene sheets were individual and few were layered. Controlled release behavior of Ibuprofen and 5-fluorouracil was then investigated. We found that FGOCs are a promising new material for biological and medical applications.
Keywords: Biocompatibility; Chitosan; drug delivery systems; functionalization of polymers; solution properties

Synthesis and photopolymerization kinetics of linear alicyclic urethane acrylate macromonomer in presence of reactive diluents - Harikrishna, Reghunathan; Bhosle, Sonali Madhavrao; Ponrathnam, S.; Rajan, C. R. (Journal of Materials Science, 2011)
This study deals with the photopolymerization of a macromonomer in the presence of reactive diluents using Photo Differential Scanning Calorimetry or Photo DSC. The kinetic profiles of these systems showed that the rate of photopolymerization rapidly increases at very early stages of the reaction. The rate of reaction was further found to increase with the addition of crosslinking agents. The addition of trifunctional crosslinking agent to the macromonomeric formulation resulted in a higher polymerization rate and conversion than that of a difunctional crosslinking agent. From the heat flow profiles, the kinetic parameters such as induction time, time to attain peak maximum, rate of maximum polymerization, and final conversion were noted for all the formulations. The initiation of photopolymerization was found to depend on the functionality while the in situ viscosity controlled the time scale for reaction diffusion which resulted in varying levels of conversions. Other parameters such as effect of temperature and concentration of photoinitiator on photocuring kinetics are also discussed.

Synthesis, electronic structure, DNA and protein binding, DNA cleavage, and anticancer activity of fluorophore-labeled copper(II) complexes - Bhat, Satish S.; Kumbhar, Anupa A.; Heptullah, Hussain; Khan, Ayesha A.; Gobre, Vivekanand V.; Gejji, Shridhar P.; Puranik, Vedavati G. (Inorganic Chemistry, 2011)
Two mononuclear fluorophore-labeled copper(II) complexes [Cu(nip)(acac)](+) (2) and [Cu(nip)(2)](2+) (3), where fluorophore is 2-(naphthalen-1-yl)-1H-imidazo[4,5-f][1,10]phenanthroline (nip) (1) and acac is acetylacetone, have been synthesized aid characterized by various techniques. The ligand 1 and complex 2 are structurally characterized by single-crystal X-ray diffraction. The coordination geometries around the copper are square planar in solid as well as solution state as evidenced by electron paramagnetic resonance (EPR) spectroscopy. The density functional calculations carried out on 1-3 have shown that electron-rich regions in the highest occupied orbital are localized on the naphthalene end partly on the phenanthroline moiety. Both complexes 2 and 3 in dimethyl sulfoxide (DMSO) exhibit near square planar structure around the metal ion in their ground state. Time-dependent density functional theory (TD-DFT) calculations reveal that Cu(II) ion in complex 2 shows tetrahedral coordination around the metal while 3 retains its square planar geometry in the lowest excited state. The interaction of complexes with calf-thymus DNA (CT DNA) has been explored by using absorption, emission, thermal denaturation, and viscosity studies, and the intercalating mode of DNA binding has been proposed. The complexes cleave DNA oxidatively without any exogenous additives. The protein binding ability has been monitored by quenching of tryptophan emission in the presence of complexes using bovine serum albumin (BSA) as model protein. The compounds showed dynamic quenching behavior. Further, the anticancer activity of the complexes on MCF-7 (human breast cancer), HeLa (human cervical cancer), HL-60 (human promyelocytic leukemia), and MCF-12A (normal epithelial) cell lines has been studied. It has been observed that 3 exhibits higher cytotoxicity than 2, and the cells undergo apoptotic cell death.

Synthesis of glycopolypeptides by the ring opening polymerization of O-glycosylated-alpha-amino acid N-carboxyanhydride (NCA) - Pati, Debasis; Shaikh, Ashif Y.; Hotha, Srinivas; Sen Gupta, Sayam (Polymer Chemistry, 2011)
The novel synthesis of O-glycosylated lysine-NCA from a stable glycosyl donor and a commercially available protected amino acid in very high yield is reported. These O-glycosylated lysine-NCA monomers underwent ring opening polymerization using simple primary amine initiators to form well defined, high molecular weight homoglycopolypeptides and diblock co-glycopolypeptides. The synthesis of azide labelled end functionalized glycopolypeptides and amphiphilic diblock copolypeptides is also reported. This methodology represents an easy and practical route to the synthesis of O-glycosylated polypeptides with 100% glycosylation.

Synthesis of gold nanoparticles by various leaf fractions of Semecarpus anacardium L. tree - Raju, D.; Mehta, Urmil J.; Hazra, Sulekha (Trees-Structure and Function, 2011)
Gold nanoparticles (NPs) were synthesized using Semecarpus anacardium leaf extracts in water and the green biomass. Extract prepared at ambient condition by crushing the leaves in deionized water is identified as `green extract', and that by boiling the leaf pieces as `boiled extract'. The mass remaining after separating the `green extract' is identified as `green biomass'. These components triggered rapid reduction of Au(III) to Au (0) in HAuCl4 solution indicating the natural ability of the leaves of S. anacardium to synthesize NPs in ambient conditions. Green extract produced more NPs compared to the boiled extract suggesting denaturization of some of the useful factors due to boiling. NPs were quantified using UV and ICP-AES analysis. These were characterized using Transmission electron microscopy, Fourier transform infrared spectroscopy and X-ray diffraction. TEM images of the particles formed with green extract, boiled extract and green biomass showed that the particles were of different shapes and sizes.
Keywords: Biosynthesis; gold nanoparticles; Green extract; Semecarpus; TEM

Synthesis of molluscicidal agent cyanolide a macrolactone from D-(-)-pantolactone - Hajare, Atul K.; Ravikumar, Velayutham; Khaleel, Shaik; Bhuniya, Debnath; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2011)
An efficient synthesis of potent molluscicidal agent cyanolide A, a glycosidic 16-membered macrolide, starting from D-(-)-pantolactone is reported. Highly stereoselective aldol, oxa-Michael addition, and Yamaguchi macrolactonization are the key steps in the present synthesis.

Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.

Chemical deposition of CuInSe2 thin films by photoelectrochemical applications - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2012)
Copper indium diselenide films have been synthesized by chemical bath deposition method. The configuration of fabricated cell is n-CuInSe2|NaOH (1 M) + S (1 M) + Na2S (1 M)|C-(graphite). The photoelectrochemical cell characterization of the films is carried out by studying current-voltage characteristics in dark, capacitance-voltage in dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that CuInSe2 thin films are n-type conductivity. The junction ideality factor is found to be 3.81. The flat band potential is found to be 0.763 V. The barrier height value is found to be 0.232 eV. The study of power output characteristic shows open circuit voltage, short circuit current, fill factor and efficiency are found to be 310 mV, 20 mu A, 42.12% and 0.82%, respectively. Photoresponse shows lighted ideality factor which is 2.92. Spectral response shows the maximum current observed at 650 nm. (C) 2011 Published by Elsevier B.V.
Keywords: Chemical bath deposition; Flat band potential; Photo response; Power output; Spectral response

Comparative genomics of the apicomplexan parasites toxoplasma gondii and neospora caninum: coccidia differing in host range and transmission strategy - Reid, Adam James; Vermont, Sarah J.; Cotton, James A.; Harris, David; Hill-Cawthorne, Grant A.; Koenen-Waisman, Stephanie; Latham, Sophia M.; Mourier, Tobias; Norton, Rebecca; Quail, Michael A.; Sanders, Mandy; Shanmugam, Dhanasekaran; et al. (Plos Pathogens, 2012)
Toxoplasma gondii is a zoonotic protozoan parasite which infects nearly one third of the human population and is found in an extraordinary range of vertebrate hosts. Its epidemiology depends heavily on horizontal transmission, especially between rodents and its definitive host, the cat. Neospora caninum is a recently discovered close relative of Toxoplasma, whose definitive host is the dog. Both species are tissue-dwelling Coccidia and members of the phylum Apicomplexa; they share many common features, but Neospora neither infects humans nor shares the same wide host range as Toxoplasma, rather it shows a striking preference for highly efficient vertical transmission in cattle. These species therefore provide a remarkable opportunity to investigate mechanisms of host restriction, transmission strategies, virulence and zoonotic potential. We sequenced the genome of N. caninum and transcriptomes of the invasive stage of both species, undertaking an extensive comparative genomics and transcriptomics analysis. We estimate that these organisms diverged from their common ancestor around 28 million years ago and find that both genomes and gene expression are remarkably conserved. However, in N. caninum we identified an unexpected expansion of surface antigen gene families and the divergence of secreted virulence factors, including rhoptry kinases. Specifically we show that the rhoptry kinase ROP18 is pseudogenised in N. caninum and that, as a possible consequence, Neospora is unable to phosphorylate host immunity-related GTPases, as Toxoplasma does. This defense strategy is thought to be key to virulence in Toxoplasma. We conclude that the ecological niches occupied by these species are influenced by a relatively small number of gene products which operate at the host-parasite interface and that the dominance of vertical transmission in N. caninum may be associated with the evolution of reduced virulence in this species.

Controlled release of nutrients to mammalian cells cultured in shake flasks - Hegde, Swati; Pant, Tejal; Pradhan, Ketaki; Badiger, Manohar V.; Gadgil, Mugdha (Biotechnology Progress, 2012)
Though cell culture-based protein production processes are rarely carried out under batch mode of operation, cell line and initial process development operations are usually carried out in batch mode due to simplicity of operation in widely used scale down platforms like shake flasks. Nutrient feeding, if performed, is achieved by bolus addition of concentrated feed solution at different intervals, which leads to large transient increases in nutrient concentrations. One negative consequence is increased waste metabolite production. We have developed a hydrogel-based nutrient delivery system for continuous feeding of nutrients in scale down models like shake flasks without the need for manual feed additions or any additional infrastructure. Continuous delivery also enables maintaining nutrient concentrations at low levels, if desired. The authors demonstrate the use of these systems for continuous feeding of glucose and protein hydrolysate to a suspension Chinese Hamster Ovary (CHO) culture in a shake flask. Glucose feeding achieved using the glucose-loaded hydrogel resulted in a 23% higher integral viable cell density and an 89% lower lactate concentration at the end of the culture when compared with a bolus-feed of glucose. (c) 2011 American Institute of Chemical Engineers Biotechnol. Prog., 2012

Controlled synthesis of O-glycopolypeptide polymers and their molecular recognition by lectins - Pati, Debasis; Shaikh, Ashif Y.; Das, Soumen; Nareddy, Pavan Kumar; Swamy, Musti J.; Hotha, Srinivas; Sen Gupta, Sayam (Biomacromolecules, 2012)
The facile synthesis of high molecular weight water-soluble O-glycopolypeptide polymers by the ring-opening polymerization of their corresponding N-carboxyanhydride (NCA) in very high yield (overall yield > 70%) is reported. The per-acetylated-O-glycosylated lysine-NCA monomers, synthesized using stable glycosyl donors and a commercially available protected amino acid in very high yield, was polymerized using commercially available amine initiators. The synthesized water-soluble glycopolypeptides were found to be alpha-helical in aqueous solution. However, we were able to control the secondary conformation of the glycopolypeptides (alpha-helix vs nonhelical structures) by polymerizing raceznic amino acid glyco NCAs. We have also investigated the binding of the glycopolypeptide poly(alpha-manno-O-lys) with the lectin Con-A using precipitation and hemagglutination assays as well as by isothermal titration calorimetry (ITC). The ITC results clearly show that the binding process is enthalpy driven for both alpha-helical and nonhelical structures, with negative entropic contribution. Binding stoichiometry for the glycopolypeptide poly(alpha-manno-O-lys) having a nonhelical structure was slightly higher as compared to the corresponding polypeptide which adopted an alpha-helical structure.

Cu-ZrO2 nanocomposite catalyst for selective hydrogenation of levulinic acid and its ester to gamma-valerolactone - Hengne, Amol M.; Rode, Chandrashekhar V. (Green Chemistry, 2012)
Several copper based catalysts were prepared, characterized and evaluated for the hydrogenation of levulinic acid and its methyl ester. Among these, nanocomposites of Cu-ZrO2 and Cu-Al2O3 quantitatively catalyzed the hydrogenation of levulinic acid and its methyl ester to give 90-100% selectivity to gamma-valerolactone in methanol and water respectively. Both the Cu-ZrO2 and Cu-Al2O3 nanocomposites were prepared by the co-precipitation method using mixed precursors under controlled conditions. XRD results showed that the main active phase of the reduced Cu-ZrO2 catalyst was metallic copper and particle size was found to be of 10-14 nm by HRTEM. The active metal leaching was at a maximum for the Cu-Al2O3 catalyst in a water medium due to the formation of a copper-carboxylate complex that was blue in colour. Surprisingly, copper leaching was completely suppressed in the case of the Cu-ZrO2 catalyst in methanol in spite of the substrate loading was increased from 5 to 20% w/w. The excellent recyclability of the Cu-ZrO2 catalyst with complete LA conversion and > 90% GVL selectivity makes it a sustainable process having a commercial potential.

Electrostatic grafting of a triphenylphosphine sulfonate on SBA-15: application in palladium catalyzed hydrogenation - Wang, Lei; Dehe, Daniel; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Zhou, Zhou; Hartmann, Martin; Taylor, Robin N. Klupp; Singh, Anand Pal; Jia, Mingjun; Thiel, Werner R. (Catalysis Science & Technology, 2012)
A novel strategy for the immobilization of a sulfonate functionalized triphenylphosphine ligand by ion-ion interactions on an imidazolium modified SBA-15 is presented. A support containing electrostatically grafted triphenylphosphine as the ligand was reacted with PdCl2( CNPh)(2) and the resulting hybrid material catalyzed olefin hydrogenation under mild conditions. The catalyst exhibits excellent activity, selectivity and stability and it can be reused for at least ten times without any loss of activity. An analogous but covalently grafted palladium system does not show any hydrogenation activity under the same conditions. TEM images of the used catalyst clearly prove the absence of palladium nanoparticles. Additionally, XPS investigations prove that palladium( 0) is formed and the phosphine is oxidized. By AAS no palladium contamination down to 0.5 X 10(-4) mmol could be detected in the products and further leaching tests verified the reaction to be truly heterogeneous. This concept of non-covalent immobilization guarantees a tight bonding of the catalytically active species to the surface in combination with a high mobility, which should be favorable for other catalyses, too.

Enantio- and diastereocontrolled conversion of chiral epoxides to trans-cyclopropane carboxylates: application to the synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II - Kumar, Pradeep; Dubey, Abhishek; Harbindu, Anand (Organic & Biomolecular Chemistry, 2012)
An efficient high yielding improved method for the enantio- and diastereoselective cyclopropanation of chiral epoxides using triethylphosphonoacetate and base (Wadsworth-Emmons cyclopropanation) is reported. The utility of this protocol is illustrated by concise and practical synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II, a cyclopropane containing natural products.

Engineered glucose to generate a spectroscopic probe for studying carbohydrate biology - Tripathi, Ashish; Singh, Vibha; Aishwarya, K. G.; Aradhyam, Gopala Krishna; Hotha, Srinivas (Advances in Experimental Medicine and Biology, 2012)
International Symposium on the Biochemical Role of Eukaryotic Cell Surface Macromolecules, Trivandrum, INDIA, JAN, 2011

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

Expanding the structural repertoire of beta/alpha Ant-Pro (anthranilic acid-proline) oligomers into gamma/alpha 2-Amb-Pro (2-aminomethyl benzoic acid-proline) oligomers - Ramesh, Veera V. E.; Priya, Gowri; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Tetrahedron, 2012)
In this article, we report a novel class of heterogeneous synthetic oligomers featuring the conformationally constrained amino acid residues - 2-aminomethyl benzoic acid (2-Amb) and proline (Pro) in repeating sequences. Oligomers as large as hexadecamers featuring the conformationally restricted gamma/alpha 2-Amb-Pro motif have been assembled using solution-phase Boc strategy, following multi-step synthetic sequences starting from the commercially available O-toluic acid. EDC-mediated peptide coupling has been found to be optimum for the assembly of the relatively non-polar oligomers, which could be readily purified by the standard column chromatographic purification procedures. This study offers considerable prospects of expanding the structural repertoire of beta/alpha Ant-Pro motif, which has been described earlier to assume right-handed helical architecture displaying robust nine-membered-ring closed network of hydrogen-bonding interactions, into gamma/alpha 2-Amb-Pro motif. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Foldamer; Peptides; Proline; Synthetic oligomers

First total synthesis of seimatopolide B - Nookaraju, U.; Harbindu, Anand; Bhise, Ankushkumar D.; Sharma, Brijesh M.; Kumar, Pradeep (RSC Advances, 2012)
The first enantioselective total synthesis of seimatopolide B has been achieved, using ring-closing metathesis and DCC (N,N'-dicyclohexylcarbodiimide) coupling as key steps. The stereogenic centres were generated by means of iterative hydrolytic kinetic resolution (HKR) of racemic epoxides.

Fluorescent superparamagnetic iron oxide core-shell nanoprobes for multimodal cellular imaging - Smitha, Sasidharan; Haseena, Vadakkenchery S.; Narayanan, Tharangattu N.; Mary, Antony P. Reena; Ajayan, Pulickel M.; Puthumana, Jayesh; Aziz, Anas A.; Aburto, Rebeca R.; Mani, Sendurai A.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Materials Express, 2012)
Multimodal imaging agents that combine magnetic and fluorescent imaging capabilities are desirable for the high spatial and temporal resolution. In the present work, we report the synthesis of multifunctional fluorescent ferrofluids using iron oxide as the magnetic core and rhodamine B as fluorochrome shell. The core-shell structure was designed in such a way that fluorescence quenching due to the inner magnetic core was minimized by an intermediate layer of silica. The intermediate passive layer of silica was realized by a novel method which involves the esterification reaction between the epoxy group of prehydrolysed 3-Glyidoxypropyltrimethoxysilane and the surfactant over iron oxide. The as-synthesized ferrofluids have a high saturation magnetization in the range of 62-65 emu/g and were found to emit light of wavelength 640 nm (lambda(excitation) = 446 nm). Time resolved life time decay analysis showed a bi-exponential decay pattern with an increase in the decay life time in the presence of intermediate silica layer. Cytotoxicity studies confirmed the cell viability of these materials. The in vitro MRI imaging illustrated a high contrast when these multimodal nano probes were employed and the R2 relaxivity of these sample was found to be 334 mM(-1)s(-1) which reveals its high potential as a T2 contrast enhancing agent.
Keywords: GPTMS; MRI Imaging; Multimodal Imaging; SPION; T2 Contrast Agent

Formal synthesis of (-)-stemoamide using a useful epimerization at C-8 - Chavan, Subhash P.; Harale, Kishor R.; Puranik, Vedavati G.; Gawade, Rupesh L. (Tetrahedron Letters, 2012)
The formal synthesis of (-)-stemoamide was achieved starting from L-pyroglutamic acid. The key steps used are the allylation using BF3 center dot OEt2, ring closing metathesis, allylic oxidation and a novel epimerization at C8. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Allylation; Allylic oxidation; Pyroglutamic acid; Ring closing metathesis; Stemoamide

From small aromatic molecules to functional nanostructured carbon by pulsed laser-induced photochemical stitching - Gokhale, R. R.; Thakare, V. P.; Warule, S.; Lefez, Benoit; Hannoyer, Beatrice; Jog, Jyoti Prakash; Ogale, S. B. (AIP Advances, 2012)
A novel route employing UV laser pulses (KrF Excimer, 248 nm) to cleave small aromatic molecules and stitch the generated free radicals into functional nanostructured forms of carbon is introduced. The process differs distinctly from any strategies wherein the aromatic rings are broken in the primary process. It is demonstrated that this pulsed laser-induced photochemical stitching (PLPS) process when applied to routine laboratory solvents (or toxic chemical wastes when discarded) Chlorobenzene and o-Dichlorobenzene yields Carbon Nanospheres (CNSs) comprising of graphene-like sheets assembled in onion-like configurations. This room temperature process implemented under normal laboratory conditions is versatile and clearly applicable to the whole family of haloaromatic compounds without and with additions of precursors or other nanomaterials. We further bring out its applicability for synthesis of metal-oxide based carbon nanocomposites. Copyright 2012 Author(s). This article is distributed under a Creative Commons Attribution 3.0 Unported License. [http://dx.doi.org/10.1063/1.4721268]

Green approach towards size controlled synthesis of biocompatible antibacterial metal nanoparticles in aqueous phase using lysozyme - Kumar, Umesh; Ranjan, Amaresh K.; Sharan, Chandrashekhar; Hardikar, Anandwardhan A.; Pundle, Archana; Poddar, Pankaj (Current Nanoscience, 2012)
Inspired by array of proteins present in nature, we choose lysozyme (hen egg protein) as a model system to synthesize nanoparticles of noble metals to understand the mechanism of interaction as well as to use them for potential applications such as potent antibacterial agents. Lysozyme is a very well studied biomolecule containing aromatic amino acids like tryptophan and tyrosine. Tyrosine has phenoxy group which is considered to be responsible for interacting with the metal ions. Lysozyme can be suitably modified by treatment with N-bromosuccinimide/N-acetylimidazole to obtain tight control over size distribution of nanoparticles. Here we report the direct synthesis of nanocrystals of gold and silver at controlled pH and light conditions without using any known reducing agents. Out of these, synthesis of gold nanoparticles is assisted by the presence of low concentration of Ag+ ions through the galvanic exchange. It is remarkable to note that the structure of protein is not changed drastically as seen by the FTIR studies. As-synthesized lysozyme capped nanoparticles prepared by this method are biocompatible and retain antibacterial property.
Keywords: Antibacterial; Biocompatible; Gold; lysozyme; Nanoparticles; Silver

Green synthesis of TiO2 nanoparticles by using aqueous extract of Jatropha curcas L. latex - Hudlikar, Manish; Joglekar, Shriram; Dhaygude, Mayur; Kodam, Kisan M. (Materials Letters, 2012)
Present study deals with a green synthesis of TiO2 nanoparticles by using 0.3% aqueous extract prepared from latex of Jatropha curcas L. TiO2 nanoparticles were characterized by X-ray diffraction (XRD), Selected Area Electron Diffraction (SAED), Transmission Electron Microscopy (TEM), Energy Dispersive Analysis of X-rays (EDAX) and Fourier Transform Infrared Spectroscopy (FTIR). Fourier Transform Infrared Spectroscopy (FTIR) were performed to find the role of curcain (enzyme), cyclic peptides namely curcacycline A (an octapeptide) and curcacycline B (a nonapeptide) as a possible reducing and capping agents, present in the latex of J. curcas L. The average size of TiO2 nanoparticles was found to be in the range of 25 to 100 nm. Our result shows that there are two broad categories of nanoparticles, first having diameter from 25 to 50 nm which are mostly spherical in shape and second having some larger and uneven shapes. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Electron microscopy; Fourier Transform Infrared Spectroscopy (FTIR); Nanostructures

Heterocyclic tri-urea isocyanurate bridged groups modified periodic mesoporous organosilica synthesized for Fe(III) adsorption - Rana, Vijay Kumar; Selvaraj, M.; Parambadath, Surendran; Chu, Sang-Wook; Park, Sung Soo; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Solid State Chemistry, 2012)
To achieve a high level of heavy metal adsorption, 1,1',1 `'-(1,3,5-triazine-2,4,6-triyl)tris(3-(3-(triethoxysilyl) propyl)urea) (TTPU) was synthesized as a novel melamine precursor and incorporated on the silica surface of periodic mesoporous organosilica (PMO). The melamine modified PMOs (MPMOs) were synthesized under acidic conditions using TTPU, tetraethylorthosilicate (TEOS) and Pluronic P123 as a template and the modified PMOs were characterized using the relevant instrumental techniques. The characteristic materials were used as adsorbents for the adsorption of Fe(III) ions. Fe(III) adsorption studies revealed MPMO-7.5 to be a good absorbent with higher adsorption efficiency than other MPMOs. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Adsorption efficiency; Fe(III) adsorption; Melamine; Periodic mesoporous organosilica (PMO)

In vitro morphogenic response in cotyledon explants of semecarpus anacardium L. - Panda, Bhuban Mohan; Hazra, Sulekha (Plant Biotechnology Reports, 2012)
Three different morphogenic responses-caulogenesis, direct somatic embryogenesis, and callusing-were noted in cotyledon explants of Semecarpus anacardium L. cultured in woody plant medium (WPM) containing thidiazuron (TDZ). Thidiazuron, at all concentrations tested, induced organogenic as well as embryogenic responses. The organogenic buds differentiated to shoots and the embryogenic mass (EM) gave rise to globular embryos which differentiated up to cotyledon-stage embryos on repeated culture in growth regulator (GR)-free WPM medium containing 0.2% activated charcoal after the removal of TDZ. The organogenic and embryogenic responses were optimal in 9.08 mu M TDZ after the removal of TDZ. Elongated shoots rooted in half-strength liquid WPM medium with 2.46 mu M indole butyric acid. Plants were successfully acclimatized and transferred to soil. Histological studies confirmed the direct origin of the organogenic buds from the cotyledon explants. The EMs produced somatic embryos on repeated culture in charcoal incorporated GR-free medium. Morphogenic callus formation from the cotyledon explants was also noted. This callus on repeated culture in WPM medium with charcoal differentiated into somatic embryos. Repetitive somatic embryogenesis was evident from direct and indirectly formed primary embryos. The somatic embryos did not convert into plantlets, though sporadic germination of embryos was observed through the emergence of roots.
Keywords: callus; Caulogenesis; Globular embryos; Growth regulator; Histology; somatic embryogenesis

Kinetic analysis of 4-isopropylphenol hydrogenation over activated carbon-supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Green Chemistry, 2012)
Hydrogenation behavior of 4-isopropylphenol to 4-isopropylcyclohexanol over activated carbon-supported rhodium catalysts in supercritical carbon dioxide (scCO(2)) at 313 K was studied in a batch reactor and the results were compared with those in 2-propanol. Higher yields of cis-4-isopropylcyclohexanol were obtained in scCO(2) than in 2-propanol, and the formation of a byproduct, isopropylcyclohexane, was suppressed in scCO(2). The catalyst modification with hydrochloric or phosphoric acid enhanced the yield of cis-4-isopropylcyclohexanol in both scCO(2) and 2-propanol solvents. Kinetic analyses of the reaction profiles revealed higher reaction rates in scCO(2) than those in 2-propanol for the 4-isopropylcyclohexanol formation both by the direct hydrogenation of 4-isopropylphenol and by the consecutive hydrogenation of 4-isopropylcyclohexanone, and also revealed that the addition of hydrochloric acid increased the consecutive hydrogenation rate of 4-isopropylcyclohexanone to cis-4-isopropylcyclohexanol, which reduced the total reaction time needed for the complete hydrogenation of 4-isopropylphenol to 4-isopropylcyclohexanol.

Laser synthesized super-hydrophobic conducting carbon with broccoli-type morphology as a counter-electrode for dye sensitized solar cells - Gokhale, Rohan; Agarkar, Shruti A.; Debgupta, Joyashish; Shinde, Deodatta; Lefez, Benoit; Banerjee, Abhik; Jog, Jyoti Prakash; More, Mahendra A.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Nanoscale, 2012)
A laser photochemical process is introduced to realize superhydrophobic conducting carbon coatings with broccoli-type hierarchical morphology for use as a metal-free counter electrode in a dye sensitized solar cell. The process involves pulsed excimer laser irradiation of a thin layer of liquid haloaromatic organic solvent o-dichlorobenzene (DCB). The coating reflects a carbon nanoparticle-self assembled and process-controlled morphology that yields solar to electric power conversion efficiency of 5.1% as opposed to 6.2% obtained with the conventional Pt-based electrode.

Latex-mediated synthesis of ZnS nanoparticles: green synthesis approach - Hudlikar, Manish; Joglekar, Shriram; Dhaygude, Mayur; Kodam, Kisan M. (Journal of Nanoparticle Research, 2012)
A low-cost, green synthesis of ZnS nanoparticles is reported using 0.3 % latex solution prepared from Jatropha curcas L. ZnS nanoparticles were characterized by X-ray diffraction, selected area electron diffraction, transmission electron microscopy, energy dispersive analysis of X-rays, UV-vis optical absorption and photoluminescence techniques. Fourier Transform Infrared Spectroscopy was performed to find the role of cyclic peptides namely curcacycline A (an octapeptide), curcacycline B (a nonapeptide) and curcain (an enzyme) as a possible reducing and stabilizing agents present in the latex of J. curcas L. The average size of ZnS nanoparticles was found to be 10 nm. Latex of J. curcas L. itself acts as a source of sulphide (S-2) ions that are donated to Zn ions under present experimental conditions. Source of sulphide (S-2) ions is still unclear, but we speculate that cysteine or thiol residues present in enzyme curcain may be donating these sulphide (S-2) ions.
Keywords: green synthesis; Latex; ZnS nanoparticles

Mapping of tms8 gene for temperature-sensitive genic male sterility (TGMS) in rice (Oryza sativa L.) - Hussain, Appibhai J.; Ali, Jauhar; Siddiq, Ebrahimali A.; Gupta, Vidya S.; Reddy, Umesh K.; Ranjekar, Prabhakar K. (Plant Breeding, 2012)
Genetic analysis of F-2 and backcross populations of an induced temperature-sensitive genic male sterility (TGMS) mutant source F 61 with normal pollen parents revealed that TGMS trait was controlled by a single recessive gene. Molecular tagging of TGMS trait was attempted using polymorphic randomly amplified polymorphic DNA (RAPD) and simple sequence repeats (SSR) markers through bulked segregant analysis. The RAPD primers UBC 345830, UBC 313927, microsatellites RM224 and RM21 produced putative markers, which differentiate parents and bulks from sterile parent and sterile bulks. The RAPD analysis of individual F-2 plants with the primer UBC345(830) showed perfect marker-phenotype cosegregation. The 830-bp RAPD fragment, which segregated with TGMS locus at a distance of 1.33 cM, was eluted and cloned, and sequence information was used for designing sequence-characterized amplified region (SCAR) primer, which cosegregated with TGMS locus at a distance of 0.8 cM. TGMS locus was mapped onto chromosome 11 using RM21 and RM224, flanking it at a distance of 4.3 and 3.0 cM, respectively. The DNA markers tightly linked to TGMS gene (tms8) in F 61 can be cost effectively used for marker-assisted selection of TGMS trait.
Keywords: Bulked segregant analysis; randomly amplified polymorphic DNA; rice; sequence-characterized amplified region; SSR; temperature-sensitive genic male sterility

Micropropagation of semecarpus anacardium L.: a medicinally important tree species - Panda, Bhuban Mohan; Hazra, Sulekha (Plant Biosystems, 2012)
Semecarpus anacardium L., a deciduous forest tree, is a source of medicinal compounds. Poor seed-viability restricts the conventional propagation. Micropropagation protocol is standardized for this species. Shoot culture-derived nodal explants were cultured in woody plant media supplemented with thidiazuron (TDZ). Shoot differentiation from meristem was limited. Meristems swelled to form meristematic mass in higher concentrations of TDZ. Swelling of meristem was attributed to the proliferation of meristematic cells. Development of shoots from meristematic mass on withdrawal of TDZ in culture medium indicated the inhibitory influence of TDZ on differentiation of buds to form shoots. Harvesting the primary shoot, leads to appearance of additional shoot buds which elongated on repeated transfer of explants in a medium devoid of growth regulator every four weeks. Optimum (17) number of shoots obtained from each meristem in explants pre-cultured in TDZ 2.27 mu M and re-cultured in growth regulator free medium for seven cycles (28 weeks). This confirms the stimulatory influence of TDZ on proliferation of meristem and inhibitory influence on shoot differentiation. All shoots, rooted in the medium with Indole butyric acid 2.46 mu M. Plantlets survived on transfer to sand: soil (1: 1) mixture and acclimatized. This is the first report on micropropagation of S. anacardium from seedling derived nodal buds using TDZ.
Keywords: Meristematic; micropropagation; Semecarpus anacardium L.; thidiazuron

MOF derived porous carbon-Fe3O4 nanocomposite as a high performance, recyclable environmental superadsorbent - Banerjee, Abhik; Gokhale, Rohan; Bhatnagar, Sumit; Jog, Jyoti Prakash; Bhardwaj, Monika; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Materials Chemistry, 2012)
A high surface area carbon composite with Fe3O4 nanoparticles is synthesized by pyrolysis of an iron containing Metal Organic Framework (MOF). The composite can be prepared by annealing the MOF at different temperatures (500 degrees C and 600 degrees C), each case exhibiting unique properties in terms of the hydrophobic behaviour and surface area, resulting in specific applicability domains. We highlight the exceptional behaviour of this material as a magnetically separable and recyclable superadsorbent for removal and recovery of environmental pollutants (oil/hydrocarbon and dye/phenol).

Nanocomposite silica surfactant microcapsules by evaporation induced self assembly: tuning the morphological buckling by modifying viscosity and surface charge - Sen, D.; Bahadur, Jitendra; Mazumder, S.; Verma, G.; Hassan, P. A.; Bhattacharya, S.; Vijai, K.; Doshi, Pankaj (Soft Matter, 2012)
Nanocomposite microcapsules of silica and surfactants have been synthesized using evaporation induced self-assembly through spray drying. It was established using electron microscopy and small-angle neutron/X-ray scattering experiments that the viscosity of the virgin dispersion and surface charge of colloidal components play a significant role in the buckling of spray droplets during drying. Hollow spherical grains are realized at relatively low viscosity and higher surface charge while mushroom like grains manifest at higher viscosity and lower surface charge. In the intermediate conditions, deformed doughnut shaped microcapsules are obtained. Scattering experiments establish the presence of the organization of micelle like aggregates of surfactants in the dried grains and also corroborate with the observations from electron microscopy. A plausible mechanism regarding the chronological pathways of morphological transformation is illustrated. Computer simulation, based on buckling of an elastic shell using a surface evolver, has been attempted in order to corroborate the experimental results.

Novel anti-inflammatory activity of epoxyazadiradione against macrophage migration inhibitory factor inhibition of tautomerase and proinflammatory activities of macrophage migration inhibitory factor - Alam, Athar; Haldar, Saikat; Thulasiram, Hirekodathakallu V.; Kumar, Rahul; Goyal, Manish; Iqbal, Mohd Shameel; Pal, Chinmay; Dey, Sumanta; Bindu, Samik; Sarkar, Souvik; Pal, Uttam; Maiti, Nakul C.; et al. (Journal of Biological Chemistry, 2012)
Macrophage migration inhibitory factor (MIF) is responsible for proinflammatory reactions in various infectious and noninfectious diseases. We have investigated the mechanism of anti-inflammatory activity of epoxyazadiradione, a limonoid purified from neem (Azadirachta indica) fruits, against MIF. Epoxyazadiradione inhibited the tautomerase activity of MIF of both human (huMIF) and malaria parasites (Plasmodium falciparum (PfMIF) and Plasmodium yoelii (PyMIF)) non-competitively in a reversible fashion (K-i, 2.11-5.23 mu M). Epoxyazadiradione also significantly inhibited MIF (huMIF, PyMIF, and PfMIF)-mediated proinflammatory activities in RAW 264.7 cells. It prevented MIF-induced macrophage chemotactic migration, NF-kappa B translocation to the nucleus, up-regulation of inducible nitric-oxide synthase, and nitric oxide production in RAW 264.7 cells. Epoxyazadiradione not only exhibited anti-inflammatory activity in vitro but also in vivo. We tested the anti-inflammatory activity of epoxyazadiradione in vivo after co-administering LPS and MIF in mice to mimic the disease state of sepsis or bacterial infection. Epoxyazadiradione prevented the release of proinflammatory cytokines such as IL-1 alpha, IL-1 beta, IL-6, and TNF-alpha when LPS and PyMIF were co-administered to BALB/c mice. The molecular basis of interaction of epoxyazadiradione with MIFs was explored with the help of computational chemistry tools and a biological knowledge base. Docking simulation indicated that the binding was highly specific and allosteric in nature. The well known MIF inhibitor (S, R)-3-(4-hydroxyphenyl)-4,5-dihydro-5-isoxazole acetic acid methyl ester (ISO-1) inhibited huMIF but not MIF of parasitic origin. In contrast, epoxyazadiradione inhibited both huMIF and plasmodial MIF, thus bearing an immense therapeutic potential against proinflammatory reactions induced by MIF of both malaria parasites and human.

Novel route for rapid biosynthesis of copper nanoparticles using aqueous extract of Calotropis procera L. latex and their cytotoxicity on tumor cells - Harne, Shrikant; Sharma, Ashwinikumar; Dhaygude, Mayur; Joglekar, Shriram; Kodam, Kisan M.; Hudlikar, Manish (Colloids and Surfaces B-Biointerfaces, 2012)
This paper accounts for novel, low-cost, eco-friendly route for rapid biosynthesis of copper nanoparticles. Cysteine proteases present in the latex of Calotropis procera L. were used to fabricate copper nanoparticles from copper acetate. Copper nanoparticles were initially characterized by transmission electron microscopy (TEM) and X-ray diffraction technique (XRD). Transmission electron microscopy (TEM) was used to estimate the size and shape of nanoparticles. The average size of copper nanoparticles was found to be 15 +/- 1.7 nm. Energy dispersive analysis of X-rays (EDAX) showed distinct peaks of copper. Fourier transform infrared spectroscopy (FTIR) was performed to confirm capping behavior of the latex proteins that contributed to long term stability of copper nanoparticles (6 months) in aqueous medium. Copper nanoparticles synthesized by above method were monodisperse type. Cytotoxicity studies of latex stabilized copper nanoparticles were carried out on HeLa, A549 and BHK21 cell lines by MTT dye conversion assay. HeLa, A549 and BHK21 cells showed excellent viability even at 120 mu M concentration of copper nanoparticles. This shows that copper nanoparticles synthesized by above method hold excellent biocompatibility. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biocompatible; Copper nanoparticles; FTIR; Latex; Tumor cells; X-ray diffraction technique (XRD)

Photocatalytic degradation of phosphamidon using Ag-doped ZnO nanorods - Korake, Prakash V.; Sridharkrishna, R.; Hankare, P. P.; Garadkar, K. M. (Toxicological and Environmental Chemistry, 2012)
The photocatalytic degradation of the organo-phosphorous pesticide phosphamidon at low concentration in aqueous solution on Ag-doped ZnO nanorods was investigated. Nanosized Ag-doped ZnO rods were synthesized by using a microwave assisted aqueous method. High molecular weight polyvinyl alcohol was used as a stabilizing agent. Composition and structure were investigated using energy-dispersive X-ray spectroscopy (EDAX) and X-ray diffraction (XRD). The XRD pattern reveals that ZnO nanorods are of hexagonal wurtzite structure. The average crystallite size calculated from Scherrer's relation was found to be 30 nm. The effects of catalyst loading, pH value, and initial concentration of phosphamidon on the photocatalytic degradation efficiency using Ag-doped ZnO nanorods as a photocatalyst have been discussed. The results revealed that Ag-doped ZnO nanorods with a diameter of 30 nm showed highest photocatalytic activity at a surface density of 1 g dm(-3). The catalyst doped with 0.2 mol% Ag is effective for the degradation of phosphamidon with visible light. This opens a new possibility to decompose pesticides that are present in wastewater.
Keywords: Ag-doped zinc oxide; phosphamidon; Photocatalysis; Photodegradation

Photopolymerization kinetics of 2-phenylethyl (meth) acrylates studied by photo DSC - Ghorpade, Ravindra V.; Bhosle, Sonali Madhavrao; Ponrathnam, S.; Rajan, C. R.; Chavan, Nayaku; Harikrishna, Reghunathan (Journal of Polymer Research, 2012)
The present work deals with the photopolymerization of 2-phenylethyl (meth)acrylates and estimation of their kinetic parameters. Formulations were made by independently homogenizing the monomers with photoinitiators of two different classes. Two different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using differential photocalorimetry (DPC) or photo DSC under polychromatic radiation. The heat flow against time was recorded for all formulations under isothermal conditions and the rates of polymerization as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, the methacrylate formulations showed a higher conversion than acrylate formulations. Other parameters such as induction time, maximum rate and conversion attained as well as the time to attain peak maximum were noted. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic models are discussed.
Keywords: Bimolecular termination model; Photo DSC; Photopolymerization; Variable autocatalytic model

Preferential oxidation of CO on Ni/CeO2 catalysts in the presence of excess H-2 and CO2 - Malwadkar, Sachin S.; Bera, Parthasarathi; Hegde, M. S.; Satyanarayana, C. V. V. (Reaction Kinetics Mechanisms and Catalysis, 2012)
Preferential oxidation of CO (CO-PROX) was carried out over Ni supported on CeO2 prepared by the co-precipitation method. The influence of metal loadings (2.5, 5 and 10 wt.% Ni) and the reaction conditions such as reaction temperature and feed composition on CO oxidation and oxidation selectivity were evaluated by using dry reformate gas. No other reactions like CO or CO2 methanation, coking, reverse water gas shift (RWGS) reaction is observed in the temperature range of 100-200 A degrees C on these catalysts. Hydrogen oxidation dominates over CO oxidation above the temperature of 200 A degrees C. An increase in oxygen leads to an increase in CO conversion but a simultaneous decrease in the O-2 selectivity. It has been noticed that 5 and 10 % Ni/CeO2 show better catalytic activity towards CO-PROX reaction. These catalysts were characterized by S-BET, XRD, TEM, XPS and H-2-TPR.
Keywords: CeO2; CO-PROX; fuel cells; Methanation; Ni

Rapid self-healing hydrogels - Phadke, Ameya; Zhang, Chao; Arman, Bedri; Hsu, Cheng-Chih; Mashelkar, Raghunath Anant; Lele, Ashish K.; Tauber, Michael J.; Arya, Gaurav; Varghese, Shyni (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Synthetic materials that are capable of autonomous healing upon damage are being developed at a rapid pace because of their many potential applications. Despite these advancements, achieving self-healing in permanently cross-linked hydrogels has remained elusive because of the presence of water and irreversible cross-links. Here, we demonstrate that permanently cross-linked hydrogels can be engineered to exhibit self-healing in an aqueous environment. We achieve this feature by arming the hydrogel network with flexible-pendant side chains carrying an optimal balance of hydrophilic and hydrophobic moieties that allows the side chains to mediate hydrogen bonds across the hydrogel interfaces with minimal steric hindrance and hydrophobic collapse. The self-healing reported here is rapid, occurring within seconds of the insertion of a crack into the hydrogel or juxtaposition of two separate hydrogel pieces. The healing is reversible and can be switched on and off via changes in pH, allowing external control over the healing process. Moreover, the hydrogels can sustain multiple cycles of healing and separation without compromising their mechanical properties and healing kinetics. Beyond revealing how secondary interactions could be harnessed to introduce new functions to chemically crosslinked polymeric systems, we also demonstrate various potential applications of such easy-to-synthesize, smart, self-healing hydrogels.
Keywords: adhesives; biomimetic materials; Hydrophobicity; molecular dynamics; smart materials

Regio- and stereoselective synthesis of new substituted tetrahydrocarbazoles and carbazoles using diels-alder reactions - Hingane, Dattatray G.; Goswami, Shailesh K.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Synthetic Communications, 2012)
Diels-Alder reactions of 3-vinylindoles were carried out with methyl acrylate and N-phenylmaleimide as dienophiles under microwave conditions to furnish unreported tetrahydrocarbazoles regio- and stereoselectively in good yields. Further dehydrogenation resulted in new substituted carbazoles.
Keywords: Carbazoles; regio- and stereoselective Diels-Alder reactions; tetrahydrocarbazoles

Self photostabilizing UV-durable MWCNT/polymer nanocomposites - Lonkar, Sunil P.; Kushwaha, Omkar S.; Leuteritz, Andreas; Heinrich, Gert; Singh, R. P. (RSC Advances, 2012)
A potentially active hindered amine light stabilizer (HALS) was successfully anchored onto multiwalled carbon nanotubes (MWCNTs) and used as a light-stabilizing yet reinforcing multifunctional nanofiller to obtain UV-durable polymer nanocomposites. The influence of such light stabilizing MWCNTs on the photo-oxidation behaviour and structure-properties of polypropylene (PP) was studied. The composites were prepared by solution mixing of MWCNTs followed by melt compounding with polypropylene (PP). The resulting composite exhibits excellent UV-durability showing an almost 20 fold increase in the induction period of photo-oxidation. Moreover, the hydrophobic HALS was found to be compatibilizing enough to achieve homogeneous dispersion of exfoliated nanotubes into a polymer matrix. The rheological characterizations predict the formation of a percolated network structure. The obtained nanocomposites present markedly improved mechanical properties which underline the reinforcing ability of functionalized MWCNTs. Overall combination of HALS and MWCNTs offers an attractive route to combine multifunctionality into new hybrid UV-durable polymer nanocomposites. Such materials may possess great potential for outdoors high performance applications.

Simple method for incorporating dynamic effects of intronic miRNA mediated regulation - Gokhale, Sucheta A.; Hariharan, Manoj; Brahmachari, Samir K.; Gadgil, Chetan J. (Molecular Biosystems, 2012)
The importance of microRNA (miRNA) in modulating gene expression at the post-transcriptional level is well known. Such regulation has been shown to influence the dynamics of several regulatory networks including the cell cycle. In this study we incorporated regulatory effects of intronic miRNA into an existing mathematical model of the cell cycle through the use of an existing `proxy' protein - the host protein. It was observed that the incorporation of intronic miRNA mediated regulation improved the performance of the model resulting in a closer match to experimental results. To test the universality of this approach we compared the effects of intronic miRNA mediated regulation and host protein mediated regulation. Further, we compared miRNA mediated and protein mediated positive and negative feedback regulations of the target protein. We found that the target protein profiles were predominantly similar. These observations show the applicability of our method for incorporating intronic miRNA mediated dynamic effects in models for regulation of gene expression.

Structural and surface morphological properties of chemically deposited Mo0.5W0.5S2 thin film - Patil, A. A.; Hankare, P. P.; Gaikwad, A. B.; Garadkar, K. M. (Journal of Materials Science-Materials in Electronics, 2012)
Preparation of layered type semiconductor Mo0.5W0.5S2- thin films has been successfully done by using chemical bath deposition method. Objective of the studies are related to structural, optical, morphological and electrical properties of the thin films. The preparation method is based on the reaction between tartarate complex of Mo and W with thiourea in an aqueous alkaline medium at 363 K. X-Ray diffraction reveals a polycrystalline film composed of both MoS2 and WS2 phases. The optical study shows that the band gap of the film is 1.6 eV. Electrical conductivity is high which is in the order of 10(-3)-10(-2) (Omega cm)(-1).

Surface species of supported ruthenium catalysts in selective hydrogenation of levulinic esters for bio-refinery application - Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V. (Catalysis Letters, 2012)
Several supported noble metal catalysts were screened for the hydrogenation of methyl levulinate to gamma-valerolactone (GVL). Among these catalysts 5 % Ru/C showed the highest conversion of 95 % of methyl levulinate with 91 % selectivity to GVL. A detailed characterization was carried out using TPR, XRD, XPS and BET techniques. XPS studies revealed that higher extent of Ru-0 species in case of carbon supported Ru was responsible for its higher hydrogenation activity as compared to Ru on other supports. Effect of process parameters such as temperature, H-2 pressure, catalyst and substrate concentration and metal loading on methyl LA conversion and selectivity to GVL also has been studied. 5 % Ru/C catalyst was found to be stable up to five reuses.
Keywords: 5 % Ru/C; Biofeedstock; gamma-Valerolactone; H-2-TPR; Hydrogenation; Methyl levulinate; XPS

Synthesis, spectroscopy, and electrochemical investigation of new conjugated polymers containing thiophene and 1,3,4-thiadiazole in the main chain - Patil, Prashant S.; Haram, Nanda S.; Pal, Ravindra R.; Periasamy, N.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2012)
Novel photoluminescent donoracceptor poly(p-phenylenevinylene)-type conjugated polymers containing thiophene and 1,3,4-thiadiazole units in the main chain were synthesized from 2,5-bis(5-bromomethyl-2-thienyl)-1,3,4-thiadiazole and 1,3/1,4-benzenedialdehyde by WittigHorner reaction. The synthesized polymers were characterized by the use of thermal analysis and spectroscopic (infrared, UV-visible absorption, and photoluminescence) measurement. The resultant material exhibited bluish green, green, and orange fluorescence in their solution and thin film and solid forms, respectively. The redox property of the polymers has also been studied by cyclic voltammetry. The optical and electrochemical studies reveal that these novel polymers are new promising materials for the development of efficient polymer light-emitting diodes. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: conjugated polymers; photoluminescence; thiophene and thiadiazole-containing polymer

Tuning spectral properties of phenothiazine based donor-pi-acceptor dyes for efficient dye-sensitized solar cells - Marszalek, Magdalena; Nagane, Satyawan; Ichake, Amol; Humphry-Baker, Robin; Paul, Vincent; Zakeeruddin, Shaik M.; Graetzel, Michael (Journal of Materials Chemistry, 2012)
Two novel metal-free organic donor-pi-acceptor dyes were synthesized using electron-rich 10-butyl-(2-methylthio)-10H-phenothiazine as a donor and cyanoacrylic acid as an acceptor. The spectral response of the dye was tuned by introducing a vinylene thiophene pi-bridge. Obtained optical and electrochemical properties of the dyes seemed to be promising in terms of employing them as light harvesters in dye-sensitized solar cells (DSCs). The efficiencies of the devices under standard AM 1.5G (100 mW cm(-2)) conditions reached 7.3% with volatile electrolyte. The differences in the photovoltaic parameters of these DSCs were explained by comparing the results of electrochemical impedance spectroscopy (EIS) measurements and transient photovoltage and photocurrent decay experiments.

Very practical and selective method for PMB protection of alcohols - Chavan, Subhash P.; Harale, Kishor R. (Tetrahedron Letters, 2012)
A very simple, practical and efficient one-step heterogeneous protocol for the PMB protection of alcohols using Amberlyst-15 has been developed. The stability and hazard issues regarding PMBCI and PMBBr are totally avoided by directly using anisyl alcohol for the protection. Alcohols are protected in very good yields. The selective mono-PMB protection of diols as well as di-PMB protection of diols was achieved in good yields, along with the demonstration of recyclability of the catalyst. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 4-Methoxybenzyl alcohol; 4-Methoxybenzyl protection; Amberlyst-15; Di-PMB protection; Mono-PMB protection

Alterations in the helicoverpa armigera midgut digestive physiology after ingestion of pigeon pea inducible leucine aminopeptidase - Lomate, Purushottam R.; Jadhav, Bhakti R.; Giri, Ashok P.; Hivrale, Vandana K. (Plos One, 2013)
Jasmonate inducible plant leucine aminopeptidase (LAP) is proposed to serve as direct defense in the insect midgut. However, exact functions of inducible plant LAPs in the insect midgut remain to be estimated. In the present investigation, we report the direct defensive role of pigeon pea inducible LAP in the midgut of Helicoverpa armigera (Lepidoptera: Noctuidae) and responses of midgut soluble aminopeptidases and serine proteinases upon LAP ingestion. Larval growth and survival was significantly reduced on the diets supplemented with pigeon pea LAP. Aminopeptidase activities in larvae remain unaltered in presence or absence of inducible LAP in the diet. On the contrary, serine proteinase activities were significantly decreased in the larvae reared on pigeon pea LAP containing diet as compared to larvae fed on diet without LAP. Our data suggest that pigeon pea inducible LAP is responsible for the degradation of midgut serine proteinases upon ingestion. Reduction in the aminopeptidase activity with LpNA in the H. armigera larvae was compensated with an induction of aminopeptidase activity with ApNA. Our findings could be helpful to further dissect the roles of plant inducible LAPs in the direct plant defense against herbivory.

Asymmetric routes to pentadec-1-en-4-ol: application to the syntheses of aculeatins F and epi-F, (R)- and (S)-5-hexadecanolide and a formal synthesis of solenopsin - Harbindu, Anand; Sharma, Brijesh M.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2013)
A short and simple route to the synthesis of pentadec-1-en-4-ol, an important synthetic building block for the aculeatins F and epi-F, insect pheromone 5-hexadecanolide, solenopsin and various other natural products has been developed via proline-catalyzed alpha-aminoxylation of an aldehyde and hydrolytic kinetic resolution of a terminal epoxide. While the synthesis of aculeatins F and epi-F has been accomplished using a FIFA promoted oxidative spirocyclization/dithiane deprotection reaction sequence and linchpin coupling as key steps, the synthesis of hexadecanolide and a formal synthesis of solenopsin was performed using ring-closing metathesis (RCM) as key step. (C) 2013 Elsevier Ltd. All rights reserved.

Band-like transport in high mobility unencapsulated single-layer MoS2 transistors - Jariwala, Deep; Sangwan, Vinod K.; Late, Dattatray J.; Johns, James E.; Dravid, Vinayak P.; Marks, Tobin J.; Lauhon, Lincoln J.; Hersam, Mark C. (Applied Physics Letters, 2013)
Ultra-thin MoS2 has recently emerged as a promising two-dimensional semiconductor for electronic and optoelectronic applications. Here, we report high mobility (>60 cm(2)/Vs at room temperature) field-effect transistors that employ unencapsulated single-layer MoS2 on oxidized Si wafers with a low level of extrinsic contamination. While charge transport in the sub-threshold regime is consistent with a variable range hopping model, monotonically decreasing field-effect mobility with increasing temperature suggests band-like transport in the linear regime. At temperatures below 100 K, temperature-independent mobility is limited by Coulomb scattering, whereas, at temperatures above 100 K, phonon-limited mobility decreases as a power law with increasing temperature. (C) 2013 AIP Publishing LLC.

Biocatalysis: fungi mediated novel and selective 12 beta- or 17 beta-hydroxylation on the basic limonoid skeleton - Haldar, Saikat; Kolet, Swati P.; Thulasiram, Hirekodathakallu V. (Green Chemistry, 2013)
Basic limonoids carrying a 4,4,8-trimethyl-17-furanylsteroid skeleton are a class of triterpenoids and well-known for their insecticidal as well as a vast array of pharmacological activities. Rare and synthetically challenging 12 beta- and 17 beta-hydroxylation was achieved on the basic limonoid skeleton to produce a novel series of hydroxylated limonoids using fungi-mediated biocatalysis. The fungal system belonging to the genera of Mucor efficiently converted azadiradione, epoxyazadiradione, gedunin and their derivatives into corresponding 12 beta- and/or 17 beta-hydroxy derivatives. The position and stereochemistry of hydroxylation was determined by rigorous spectroscopic and crystallographic studies. This fungi-mediated stereo- and regio-selective hydroxylation process was highly efficient and mild enough to sustain chemically sensitive functional groups around the basic limonoid skeleton. Modifications of specific functional groups and variation in biocatalyst were shown to bring selectivity among 12 beta- or 17 beta-hydroxylation.

Biocatalyst mediated production of 6 beta,11 alpha-dihydroxy derivatives of 4-ene-3-one steroids - Kolet, Swati P.; Niloferjahan, Siddiqui; Haldar, Saikat; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (Steroids, 2013)
Biotransformation of steroids with 4-ene-3-one functionality such as progesterone (I), testosterone (II), 17 alpha-methyltestosterone (III), 4-androstene-3,17-dione (IV) and 19-nortestosterone (V) were studied by using a fungal system belonging to the genera of Mucor (M881). The fungal system efficiently and quantitatively converted these steroids in regio- and stereo-selective manner into corresponding 6 beta,11 alpha-dihydroxy compounds. Time course experiments suggested that the transformation was initiated by hydroxylation at 6 beta- or 11 alpha-(10 beta-hydroxy in case of V) to form monohydroxy derivatives which upon prolonged incubation were converted into corresponding 613,11oc-dihydroxy derivatives. The fermentation studies carried out using 5 L table-top fermentor with substrates (I and II) clearly indicates that 6 beta,11 alpha-dihydroxy derivatives of steroids with 4-ene-3-one functionality can be produced in large scale by using M881. (C) 2013 Elsevier Ltd.
Keywords: 4-Ene-3-one steroids; Biotransformation; Mucor sp.

Biosynthesis of antinutritional alkaloids in solanaceous crops is mediated by clustered genes - Itkin, M.; Heinig, U.; Tzfadia, O.; Bhide, Amey J.; Shinde, B.; Cardenas, Pablo D.; Bocobza, S. E.; Unger, T.; Malitsky, Sergey; Finkers, R.; Tikunov, Y.; Bovy, A.; et al. (Science, 2013)
Steroidal glycoalkaloids (SGAs) such as alpha-solanine found in solanaceous food plants-as, for example, potato-are antinutritional factors for humans. Comparative coexpression analysis between tomato and potato coupled with chemical profiling revealed an array of 10 genes that partake in SGA biosynthesis. We discovered that six of them exist as a cluster on chromosome 7, whereas an additional two are adjacent in a duplicated genomic region on chromosome 12. Following systematic functional analysis, we suggest a revised SGA biosynthetic pathway starting from cholesterol up to the tetrasaccharide moiety linked to the tomato SGA aglycone. Silencing GLYCOALKALOID METABOLISM 4 prevented accumulation of SGAs in potato tubers and tomato fruit. This may provide a means for removal of unsafe, antinutritional substances present in these widely used food crops.

Characterization of a chemostable serine alkaline protease from Periplaneta americana - Sanatan, Prashant T.; Lomate, Purushottam R.; Giri, Ashok P.; Hivrale, Vandana K. (BMC Biochemistry, 2013)
Background: Proteases are important enzymes involved in numerous essential physiological processes and hold a strong potential for industrial applications. The proteolytic activity of insects' gut is endowed by many isoforms with diverse properties and specificities. Thus, insect proteases can act as a tool in industrial processes. Results: In the present study, purification and properties of a serine alkaline protease from Periplaneta americana and its potential application as an additive in various bio-formulations are reported. The enzyme was purified near to homogeneity by using acetone precipitation and Sephadex G-100 gel filtration chromatography. Enzyme activity was increased up to 4.2 fold after gel filtration chromatography. The purified enzyme appeared as single protein-band with a molecular mass of similar to 27.8 kDa in SDS-PAGE. The optimum pH and temperature for the proteolytic activity for purified protein were found around pH 8.0 and 60 degrees C respectively. Complete inhibition of the purified enzyme by phenylmethylsulfonyl fluoride confirmed that the protease was of serine-type. The purified enzyme revealed high stability and compatibility towards detergents, oxidizing, reducing, and bleaching agents. In addition, enzyme also showed stability towards organic solvents and commercial detergents. Conclusion: Several important properties of a serine protease from P. Americana were revealed. Moreover, insects can serve as excellent and alternative source of industrially important proteases with unique properties, which can be utilized as additives in detergents, stain removers and other bio-formulations. Properties of the P. americana protease accounted in the present investigation can be exploited further in various industrial processes. As an industrial prospective, identification of enzymes with varying essential properties from different insect species might be good approach and bioresource.
Keywords: Chemostability; Industrial catalyst; Insect proteases; Periplaneta americana; Serine alkaline protease

Chemically stable multilayered covalent organic nanosheets from covalent organic frameworks via mechanical delamination - Chandra, Suman; Kandambeth, Sharath; Biswal, Bishnu P.; Lukose, Binit; Kunjir, Shrikant M.; Chaudhary, Minakshi V.; BabaRao, Ravichandar; Heine, Thomas; Banerjee, Rahul (Journal of the American Chemical Society, 2013)
A series of five thermally and chemically stable functionalized covalent organic frameworks (COFs), namely, TpPa-NO2, TpPa-F-4, TpBD-(NO2)(2), TpBD-Me-2, and TpBD-(OMe)(2) were synthesized by employing the solvothermal aldehyde-amine Schiff base condensation reaction. In order to complete the series, previously reported TpPa-1, TpPa-2, and TpBD have also been synthesized, and altogether, eight COFs were fully characterized through powder X-ray diffraction (PXRD), Fourier transform IR (FT-IR) spectroscopy, C-13 solid-state NMR spectroscopy, and thermogravimetric analysis. These COFs are crystalline, permanently porous, and stable in boiling water, acid (9 N HCl), and base (3 N NaOH). The. synthesized COFs (all eight) were successfully delaminated using a simple, safe, and environmentally friendly mechanical grinding route to transform into covalent organic nanosheets (CONs) and were well characterized via transmission electron microscopy and atomic force microscopy. Further PXRD and FT-IR analyses confirm that these CONs retain their structural integrity throughout the delamination process and also remain stable in aqueous, acidic, and basic media like the parent COFs. These exfoliated CONs have graphene-like layered morphology (delaminated layers), unlike the COFs from which they were synthesized.

Compensatory proteolytic responses to dietary proteinase inhibitors from Albizia lebbeck seeds in the helicoverpa armigera larvae - Hivrale, Vandana K.; Lomate, Purushottam R.; Basaiyye, Shriniwas S.; Kalve, Neeta D. (Arthropod-Plant Interactions, 2013)
Plant proteinase inhibitors (PIs) have been shown to reduce the growth rates in larvae of numerous insect species. On the other hand, insects can also regulate their proteinases against plant PIs. In the present study, we report the compensatory activities of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) gut proteinases against the PIs of Albizia lebbeck seeds. Total of ten proteinase inhibitor bands were detected in the seed extract of A. lebbeck. Bioassays were conducted by feeding H. armigera larvae on diet containing partially purified PIs from A. lebbeck seeds. Results show that larval growth and survival was significantly reduced by A. lebbeck PIs. We found that higher activity H. armigera gut proteinase (HGP) isoforms observed in the midgut of control larvae were inhibited in the midgut of larvae fed on test diet. Some HGP isoforms were induced in the larvae fed on PI containing test diet; however, these isoforms showed lower activity in the larvae fed on control diet. Aminopeptidase activities were significantly increased in the midgut of larvae fed on test diet. A population of susceptible and resistant enzymes was observed in the midgut of H. armigera, when fed on diet containing PIs from A. lebbeck seeds. Our initial observations indicate that H. armigera can regulate its digestive proteinase activity against non-host plant PIs, too. It is important to study the exact biochemical and molecular mechanisms underlying this phenomenon in order to develop PI-based insect control strategies.
Keywords: Albizia lebbeck; Helicoverpa armigera; Midgut proteinases; Proteinase inhibitors; regulation

Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin

Diverted total syntheses of potent cell adhesion inhibitor peribysin E analogues - Handore, Kishor L.; Reddy, D. Srinivasa (Organic Letters, 2013)
Preliminary results from a program aimed at the creation of a focused library of analogues around the natural product peribysin E, a potent biologically active and structurally fascinating molecule, are reported. The total synthesis of (+/-)-peribysin E was accomplished using a short route. Eight new analogues of the natural compound have been accomplished by means of ``diverted total synthesis'' in less than 10 steps. The present effort highlights protecting-group-free total syntheses and the shortest route to access these functionally embellished hydrindanes.

Effect of carbon dioxide pressure on 4-t-butylphenol hydrogenation activity of supported rhodium catalyst - Hiyoshi, Norihito; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of the Japan Petroleum Institute, 2013)
Hydrogenation of 4-t-butylphenol over an activated carbon-supported rhodium catalyst in carbon dioxide solvent was analyzed based on phase observation with a view cell and calculations of the solubility of 4-t-butylphenol using the Peng-Robinson equation of state as a function of carbon dioxide pressure. The reaction experiments showed that the initial reaction rate of 4-t-butylphenol at 313 K under 2 MPa of hydrogen pressure was increased by the addition of carbon dioxide, especially above a total pressure of 11 MPa. Direct visual observation showed that the solubility of 4-t-butylphenol increased with higher carbon dioxide pressure. The calculations based on the Peng-Robinson equation of state also showed that the solubility of 4-t-butylphenol in the 4-t-butylphenol carbon dioxide hydrogen (2 MPa) system at 313 K significantly increased by addition of carbon dioxide above a total pressure of 11 MPa. We concluded that the increase in the hydrogenation rates was caused by the increased concentration of 4-t-butylphenol substrate in the carbon dioxide solvent.
Keywords: 4-t-Butylphenol hydrogenation; Carbon dioxide solvent; Peng-Robinson equation; Rhodium catalyst; Supercritical fluid

Enhanced field-emission behavior of layered MoS2 sheets - Kashid, Ranjit V.; Late, Dattatray J.; Chou, Stanley S.; Huang, Yi-Kai; De, Mrinmoy; Joag, Dilip S.; More, Mahendra A.; Dravid, Vinayak P. (Small, 2013)
Field emission studies are reported for the first time on layered MoS2 sheets at the base pressure of approximate to 1 x 10(-8) mbar. The turn-on field required to draw a field emission current density of 10 A/cm(2) is found to be 3.5 V/m for MoS2 sheets. The turn-on values are found to be significantly lower than the reported MoS2 nanoflowers, graphene, and carbon nanotube-based field emitters due to the high field enhancement factor (approximate to 1138) associated with nanometric sharp edges of MoS2 sheet emitter surface. The emission current-time plots show good stability over a period of 3 h. Owing to the low turn-on field and planar (sheetlike) structure, the MoS2 could be utilized for future vacuum microelectronics/nanoelectronic and flat panel display applications.

Enhancement of chemical stability and crystallinity in porphyrin-containing covalent organic frameworks by intramolecular hydrogen bonds - Kandambeth, Sharath; Shinde, Digambar Balaji; Panda, Manas K.; Lukose, Binit; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: covalent organic frameworks; hydrogen bonds; mesoporous materials; porphyrinoids; tautomerism

Evaluation of ethanol production by a new isolate of yeast during fermentation in synthetic medium and sugarcane bagasse hemicellulosic hydrolysate - Hande, Aparna; Mahajan, Siddharth A.; Prabhune, Asmita (Annals of Microbiology, 2013)
A new xylose fermenting yeast was isolated from over-ripe banana by enrichment in xylose-containing medium. The phylogenetic analysis of ITS1-5.8S-ITS2 region sequences of ribosomal RNA of isolate BY2 revealed that it shows affiliation to genus Pichia and clades with Pichia caribbica. In batch fermentation, Pichia strain BY2 fermented xylose, producing 15 g l(-1) ethanol from 30 g l(-1) xylose under shaking conditions at 28A degrees C, with ethanol yield of 0.5 g g(-1) and volumetric productivity of 0.31 g l(-1) h(-1). The optimum pH range for ethanol production from xylose by Pichia strain BY2 was 5-7. Pichia strain BY2 also produced 6.08 g l(-1) ethanol from 30 g l(-1) arabinose. Pichia strain BY2 can utilize sugarcane bagasse hemicellulose acid hydrolysate for alcohol production, efficiency of fermentation was improved by neutralization, and sequential use of activated charcoal adsorption method. Percent total sugar utilized and ethanol yield for the untreated hydrolysate was 17.14% w/v and 0.33 g g(-1), respectively, compared with 66.79% w/v and 0.45 g g(-1), respectively, for treated hemicellulose acid hydrolysate. This new yeast isolate showed ethanol yield of 0.45 g g(-1) and volumetric productivity of 0.33 g l(-1) h(-1) from sugarcane bagasse hemicellulose hydrolysate detoxified by neutralization and activated charcoal treatment, and has potential application in practical process of ethanol production from lignocellulosic hydrolysate.
Keywords: D-xylose; Ethanol; Pichia; Sugarcane bagasse hemicellulose

Expedient preparative isolation, quantification and characterization of limonoids from neem fruits - Haldar, Saikat; Phapale, Prasad B.; Kolet, Swati P.; Thulasiram, Hirekodathakallu V. (Analytical Methods, 2013)
Major basic limonoids from Neem fruits such as azadirone, epoxyazadiradione and azadiradione were isolated in preparative scale using an automated and rapid medium pressure liquid chromatography (MPLC)-based protocol. They were individually quantified using HPLC. An LC-ESI-MS/MS-based rapid identification technique was developed for the high-throughput screening of these limonoids in phytochemical extracts.

Formation of tertiary amides and H2 by dehydrogenative coupling of primary alcohols with secondary amines catalyzed by ruthenium bipyridine-based pincer complexes - Srimani, Dipankar; Balaraman, Ekambaram; Hu, Peng; Ben-David, Yehoshoa; Milstein, David (Advanced Synthesis & Catalysis, 2013)
Dehydrogenative coupling of primary alcohols with secondary amines to form tertiary amides and dihydrogen (H2) is efficiently catalyzed by bipyridyl-based ruthenium pincer complexes (0.2–1 mol%) under neutral conditions (in case of the dearomatized complexes), or with added catalytic amount of base. The reaction is sensitive to steric hindrance; in the case of amidation of bulky secondary amines a less sterically hindered complex is more efficient. Selective acylation of primary amines in the presence of secondary amines was also demonstrated.

HBGS (hydrate based gas separation) process for carbon dioxide capture employing an unstirred reactor with cyclopentane - Ho, Leong Chuan; Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Energy, 2013)
The effect of CP (cyclopentane) as a promoter/additive, in the HBGS (hydrate based gas separation) process for pre-combustion gas mixture was investigated by employing an unstirred reactor configuration. Gas uptake measurements were performed at two different temperatures (275.7 K and 285.7 K) and at an experimental pressure of 6.0 MPa to determine the kinetics of hydrate formation. Experiments were conducted with three different volumes (7.5, 15 and 22 ml) of CP and based on induction time and the rate of hydrate growth, 15 ml of CP was determined to be the optimal volume for carbon dioxide capture at 6.0 MPa and 275.7 K. In addition, the effect of a kinetic promoter, SDS (sodium dodecyl sulfate), was investigated. Surprisingly, no improvement in kinetic performance was observed at 6.0 MPa and 275.7 K in the presence of SDS and CP. From the study, it was found that at the optimal 15 ml CP (CP layer thickness of 1.8 mm), the average composition of carbon dioxide in the hydrate phase was 90.36 mol% with a separation factor of 17.82. Furthermore, the unstirred reactor also yielded better kinetic performance over the stirred tank reactor with the unstirred reactor having a 2.28 times higher average gas uptake. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Cyclopentane; Gas hydrates; Gas separation; Pre-combustion; Unstirred reactor

Hollow nanogold/meso-magnetite composite: pulsed laser synthesis, properties, and biosensing application - Chaudhari, Nilima; Warule, Sambhaji; Agrawal, Shailaja; Thakare, Vishal; Jouen, Samuel; Hannoyer, Beatrice; Kale, Bharat; Paknikar, Kishore; Ogale, Satishchandra B. (Journal of Nanoparticle Research, 2013)
A facile and template-free UV (Excimer) laser photolysis process is demonstrated to transform a Fe-complex into unique hollow Fe3O4 nanosphere morphology with each sphere having nanometric pores and an opening. Depending on the Fe-complex concentration and processing time interesting configurations are seen to evolve. When an identical process is applied to a mixture of Fe-complex and chloroauric acid an enthrallingly decorated Au-Fe3O4 nanostructure evolves, with Au nanoparticles surface-loaded on mesospheric Fe3O4. This room temperature process implemented under normal laboratory conditions is clearly versatile and applicable to heterojunction nanomaterials synthesis in a single-step process. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml. The test results demonstrate linear sensing response in the range of 10(3)-10(5) cfu/ml. We also show that these nanostructures can be used for simple electrical conductivity-based biosensing since they show dramatic conductivity change in a simple drop-cast test. A new laser-based approach to the synthesis of unique hollow sphere morphology of magnetite (Fe3O4) without and with Au nanoparticle decoration is presented. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml.
Keywords: E. coli cells; Fe-complex; Meso-magnetite; Nanobiotechnology; Nanocomposite; Pulse laser irradiation

Hysteresis and charge trapping in graphene quantum dots - Kalita, Hemen; Harikrishnan, V; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Aslam, Mohammed (Applied Physics Letters, 2013)
We report current hysteresis in response to applied voltage in graphene quantum dots of average diameter 4.5 +/- 0.55 nm, synthesized electrochemically using multiwalled carbon nanotubes. In response to step voltages, transient current decay, characteristic of deep and shallow level charge traps with time constants 186 ms and 6 s, is observed. Discharging current transients indicate charge storage of the order of 100 mu C. Trap states are believed to arise due to the fast physisorption of external adsorbates, which are found to have a significant effect on charge transport and changes the resistance of the prepared device by an order of 3. (C) 2013 American Institute of Physics.

Mechanochemical synthesis of chemically stable isoreticular covalent organic frameworks - Biswal, Bishnu P.; Chandra, Suman; Kandambeth, Sharath; Lukose, Binit; Heine, Thomas; Banerjeet, Rahul (Journal of the American Chemical Society, 2013)
Three thermally and chemically stable isoreticular covalent organic frameworks (COFs) were synthesized via room-temperature solvent-free mechanochemical grinding. These COFs were successfully compared with their solvothermally synthesized counterparts in all aspects. These solvent-free mechanochemically synthesized COFs have moderate crystallinity with remarkable stability in boiling water, acid (9 N HCl), and base [TpBD (MC) in 3 N NaOH and TpPa-2 (MC) in 9 N NaOH]. Exfoliation of COF layers was simultaneously observed with COF formation during mechanochemical synthesis. The structures thus obtained seemed to have a graphene-like layered morphology (exfoliated layers), unlike the parent COFs synthesized solvothermally.

Molecular mapping of leaf rust resistance gene Lr15 in hexaploid wheat - Dholakia, Bhushan B.; Rajwade, A. V.; Hosmani, P.; Khan, R. R.; Chavan, S.; Reddy, D. M. R.; Lagu, Meena D.; Bansal, Urmil K.; Saini, R. G.; Gupta, V. S. (Molecular Breeding, 2013)
Leaf rust is a widespread and commonly occurring rust disease of wheat. Genetic resistance is the most economical method of reducing losses due to leaf rust. Lr15 has been shown to be present on wheat chromosome 2D and is reported to be a seedling resistance gene. However, tightly linked markers associated with Lr15 have not been reported to date. To identify molecular markers linked to Lr15, an F-2 mapping population of Thatcher x Thatcher-Lr15 was generated. Available wheat simple sequence repeat markers were utilized in parental screening and polymorphic markers were used to analyze the entire population of 221 plants. Phenotypic evaluations of the F-2-derived F-3 progenies with Puccinia triticina Eriks. pathotype 162A (93R15) confirmed the monogenic inheritance of Lr15. The linkage group representing chromosome 2DS was constructed at LOD 4.0 which revealed the closest flanking markers Xgwm4562 and Xgwm102 at a distance of 3.1 and 9.3 cM, respectively. Furthermore, utilization of these flanking markers in combination has successfully identified wheat lines with or without Lr15. These markers could potentially be useful in gene pyramiding with other genes to enhance rust resistance in wheat.
Keywords: Disease resistance; Leaf rust; Marker-assisted selection; Simple sequence repeat; Wheat

One pot solvent free synthesis and in vitro antitubercular screening of 3-aracylphthalides against mycobacterium tuberculosis - Limaye, Rohan A.; Kumbhar, Virendra B.; Natu, Arun D.; Paradkar, Madhusudan V.; Honmore, Varsha S.; Chauhan, Rubia R.; Gample, Suvarna P.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2013)
One pot synthesis of 3-Aracylphthalide was accomplished in good yield by reacting 2-carboxy benzaldehyde with various aromatic methyl ketones in presence of methane sulphonic acid. Various phthalides thus obtained were characterized with spectral techniques. These phthalides were subjected to in vitro antitubercular screening against Mycobacterium tuberculosis H37Ra (MTB) by using XRMA protocol. Among the phthalides screened, four exhibited half maximal inhibitory concentration (IC50) in the range of 0.81-1.24 mu g/ml thereby providing potential lead compounds for future drug discovery studies. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 3-Aracylphthalide; Antitubercular activity; Methane sulphonic acid; One pot synthesis

One-pot fluorescent labeling protocol for complex hydroxylated bioactive natural products - Haldar, Saikat; Kumar, Santosh; Kolet, Swati P.; Patil, Harshal S.; Kumar, Dhiraj; Kundu, Gopal C.; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2013)
Tagging of small bioactive molecules with a fluorophore is a highly sensitive method to trace their cellular activities through real-time visual information. Here we disclose a 7-nitrobenzo-2-oxa-1,3-diazole (NBD)-based, high-yielding, one-pot labeling protocol for hydroxylated molecules using Yamaguchi coupling as the key reaction. This methodology was successfully applied on several sensitive and complex hydroxylated bioactive compounds including 7-deacetylazadiradione, simvastatin, camptothecin, andrographolide, cinchonine, beta-dihydroartemisinin, and azadirachtin A. Further, utility of this protocol was illustrated on the cytotoxic activity of azadiradione derivatives against several cancer cell lines through cell imaging of two qualified fluorescent probes.

Organophotocatalysis in nanostructured soft gel materials as tunable reaction vessels: comparison with homogeneous and micellar solutions - Bachl, Jurgen; Hohenleutner, Andreas; Dhar, Basab Bijayi; Cativiela, Carlos; Maitra, Uday; Koenig, Burkhard; Diaz, David Diaz (Journal of Materials Chemistry A, 2013)
Riboflavin tetraacetate-catalyzed aerobic photooxidation of 1-(4-methoxyphenyl)ethanol was investigated as a model reaction under blue visible light in different soft gel materials, aiming to establish their potential as reaction vessels for photochemical transformations. Three strategies involving different degrees of organization of the catalyst within the gel network were explored, and the results compared to those obtained in homogeneous and micellar solutions. In general, physical entrapment of both the catalyst and the substrate under optimized concentrations into several hydrogel matrices (including low-molecular-weight and biopolymer-based gels) allowed the photooxidation with conversions between 55 and 100% within 120 min (TOF similar to 0.045-0.08 min(-1); k(obs) similar to 0.011-0.028 min(-1)), albeit with first-order rates ca. 1-3-fold lower than in solution under comparable non-stirred conditions. Remarkably, the organogel made of a cyclohexane-based bisamide gelator in CH3CN not only prevented the photodegradation of the catalyst but also afforded full conversion in less than 60 min (TOF similar to 0.167 min(-1); k(obs) similar to 0.073 min(-1)) without the need of additional proton transfer mediators (e. g., thiourea) as it occurs in CH3CN solutions. In general, the gelators could be recycled without detriment to their gelation ability and reaction rates. Moreover, kinetics could be fine-tuned according to the characteristics of the gel media. For instance, entangled fibrillar networks with relatively high mechanical strength were usually associated with lower reaction rates, whereas wrinkled laminated morphologies seemed to favor the reaction. In addition, the kinetics results showed in most cases a good correlation with the aeration efficiency of the gel media.

Photopolymerization of bis-aromatic and alicyclic based solid urethane acrylate macromonomer in the presence of large excess of reactive diluent Kinetics and modeling - Harikrishna, Reghunathan; Ponrathnam, S.; Rajan, C. R.; Tambe, S. S. (Journal of Thermal Analysis and Calorimetry, 2013)
A solid urethane acrylate macromonomer with bis-aromatic as well as alicyclic moieties was synthesized and the kinetics of photopolymerization reactions were studied in the presence of varying concentration of photoinitiator and large excess of reactive diluent using photo DSC. The studies show that the rate of maximum polymerization was found to increase with increase in concentration of photoinitiator while a decrease was observed by an increase in temperature. The final conversion showed a decrease at highest isothermal condition due to vitrification. Estimation of kinetic parameters including applicability of autocatalytic and modified autocatalytic models were investigated by nonlinear regression. It was observed that the modified models gave a better fit with the experimental data and kinetic parameters showed a decrease with increase in temperature and an increase with increase in concentration of photoinitiator.
Keywords: Autocatalytic model; kinetics; Levenberg-Marquardt method; Photopolymerization

Phytosynthesis of silver nanoparticles by semecarpus anacardium L. leaf extract - Raju, D.; Hazra, Sulekha; Mehta, Urmil J. (Materials Letters, 2013)
Green synthesis of silver nanoparticles (AgNPs) using Semecmpus anacardium L leaf extract was studied. The reduction of silver (Ag+) ions was characterized by using UV-vis spectrophotometer showing formation of AgNPs within 15-20 mm. A time dependent reaction showed the increase in the nanoparticles (NPs) with time. Transmission electron microscopy (TEM) analysis showed that the synthesized AgNPs varied from 10 to 25 nm and has spherical shape. The Fourier transform infrared (FTIR) analysis showed that phenols and protein were responsible for the formation of the AgNPs. The energy dispersive spectroscopy (EDAX) analysis confirms the formed NPs were of silver. The quantification of AgNPs was studied by inductive coupled plasma spectrometry (ICP-AES). The important outcome of this work can be value addition to the medicinal plants in synthesis of NPs for biomedical applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: FTIR; Leaf extract; Nanoparticles; Semecarpus anacardium; synthesis; TEM

Polarizability of few electron quantum dots: extended coupled-cluster response approach - Heidari, Ideh; Vaval, Nayana; Pal, Sourav; Kanhere, Dilip G. (Chemical Physics Letters, 2013)
The dipole polarizability is studied for few electron quantum dots using extended coupled cluster linear response method (ECCLR). The polarizability of pure parabolic quantum dots depends only on the number of electrons and the parabolic confinement strength. We added impurity in a GAUSSIAN form to the external parabolic potential and used ECCLR to calculate polarizability. To examine the effect of external potential, we changed the parabolic confinement to square-well and repeated all calculations. We mainly looked at eigenvalue spectrum and charge density specially when the system shifts towards lower density regions. (C) 2012 Elsevier B. V. All rights reserved.

Proteomic analysis of protease resistant proteins in the diabetic rat kidney - Bansode, Sneha B.; Chougale, Ashok D.; Joshi, Rakesh S.; Giri, Ashok P.; Bodhankar, Subhash L.; Harsulkar, Abhay M.; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2013)
Glycation induced protein aggregation has been implicated in the development of diabetic complications and neurodegenerative diseases. These aggregates are known to be resistant to proteolytic digestion. Here we report the identification of protease resistant proteins from the streptozotocin induced diabetic rat kidney, which included enzymes in glucose metabolism and stress response proteins. These protease resistant proteins were characterized to be advanced glycation end products modified and ubiquitinated by immunological and mass spectrometry analysis. Further, diabetic rat kidney exhibited significantly impaired proteasomal activity. The functional analysis of identified physiologically important enzymes showed that their activity was reduced in diabetic condition. Loss of functional activity of these proteins was compensated by enhanced gene expression. Aggregation prone regions were predicted by in silico analysis and compared with advanced glycation end products modification sites. These findings suggested that the accumulation of protein aggregates is an inevitable consequence of impaired proteasomal activity and protease resistance due to advanced glycation end products modification. Molecular & Cellular Proteomics 12: 10.1074/mcp.M112.020651, 228-236, 2013.

Rational design of highly active “hybrid” phosphine-phosphinite pincer iridium catalysts for alkane metathesis - Nawara-Hultzsch, Agnieszka J.; Hackenberg, Jason D.; Punji, Benudhar; Supplee, Carolyn; Emge, Thomas J.; Bailey, Brad C.; Schrock, Richard R.; Brookhart, Maurice; Goldman, Alan S. (ACS Catalysis, 2013)
Both the bisphosphine and bisphosphinite pincer complexes (tBu4PCP)IrH2 and (tBu4POCOP)IrH2 can cocatalyze alkane metathesis in tandem with olefin metathesis catalysts, but the two complexes have different resting states during catalysis, suggesting that different steps are turnover-limiting in each case. This led to the hypothesis that a complex with intermediate properties would be catalytically more active than either of these two species. Accordingly, “hybrid” phosphine–phosphinite pincer ligands (PCOP) and the corresponding iridium complexes were synthesized (3c–e). In tandem with olefin-metathesis catalyst MoF12, (tBu4PCOP)IrH2 displays significantly higher activity for the metathesis of n-hexane than does (tBu4PCP)IrH2 or (tBu4POCOP)IrH2. (tBu2PCOPiPr2)IrH4 (3d) is even more active (>30-fold more active than (tBu4POCOP)IrH2) and affords nearly 4.6 M alkane products after 8 h at 125 °C.

Rationally designed CuFe2O4-mesoporous Al2O3 composite towards stable performance of high temperature water-gas shift reaction - Subramanian, Vijayanand; Gnanakumar, Edwin S.; Jeong, Dae-Woon; Han, Won-Bi; Gopinath, Chinnakonda S.; Roh, Hyun-Seog (Chemical Communications, 2013)
High temperature water-gas shift reaction was demonstrated for the first time on a CuFe2O4-mesoporous alumina nanocomposite between 350 and 550 degrees C with 70-80% CO-conversion using simulated waste derived syngas under realistic conditions. Despite high Al-content, the catalyst exhibited stable activity, which was attributed to the nano-architectured robust porous nature of alumina integrated with surrounding CuFe2O4.

Sensing behavior of atomically thin-layered MoS2 transistors - Late, Dattatray J.; Huang, Yi-Kai; Liu, Bin; Acharya, Jagaran; Shirodkar, Sharmila N.; Luo, Jiajun; Yan, Aiming; Charles, Daniel; Waghmare, Umesh V.; Dravid, Vinayak P.; Rao, C. N. R. (ACS Nano, 2013)
Most of recent research on layered chalcogenides is understandably focused on single atomic layers. However, it is unclear if single-layer units are the most ideal structures for enhanced gas solid interactions. To probe this issue further, we have prepared large-area MoS2 sheets ranging from single to multiple layers on 300 nm SiO2/Si substrates using the micromechanical exfoliation method. The thickness and layering of the sheets were identified by optical microscope, invoking recently reported specific optical color contrast, and further confirmed by AFM and Raman spectroscopy. The MoS2 transistors with different thicknesses were assessed for gas-sensing performances with exposure to NO2, NH3, and humidity in different conditions such as gate bias and light Irradiation. The results show that, compared to the single-layer counterpart, transistors of few MoS2 layers exhibit excellent sensitivity, recovery, and ability to be manipulated by gate bias and green light. Further, our ab initio DFT calculations on single-layer and bilayer MoS2 show that the charge transfer is the reason for the decrease in resistance in the presence of applied field.

Short synthesis of (2S,3S)-3-hydroxypipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Pawar, Kailash P. (Tetrahedron Letters, 2013)
A convenient synthesis of (2S,3S)-3-hydroxypipecolic acid starting from cheap and abundant L-(+)-tartaric acid has been achieved. The strategy employs selective ester reduction and reductive lactamization as key steps. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Reductive lactamization; Selective deprotection; Wittig reaction

Single pot conversion of furfuryl alcohol to levulinic esters and gamma-valerolactone in the presence of sulfonic acid functionalized ILs and metal catalysts - Hengne, Amol M.; Kamble, Sumit B.; Rode, Chandrashekhar V. (Green Chemistry, 2013)
Ionic liquids functionalized with acidic anions, HSO4, ClSO3H, PTSA, TFA (MIm), HSO4 and TFA (NMP) were found to efficiently (99% conversion) catalyze the alcoholysis of furfuryl alcohol (FAL) in the presence of methanol, ethanol, n-butanol and isopropyl alcohol (IPA) to the corresponding levulinic acid esters under mild temperature (90-130 degrees C) conditions. The extended alkyl chain length of [MIm] using 1,4-butane sultone enhanced the Bronsted acidity of [BMIm-SH][HSO4] catalyst resulting into the highest selectivity of >95% to Me-LA. An increase in both temperature and catalyst concentration increased the furfuryl alcohol conversion and selectivity to levulinate esters. In contrast, an increase in the substrate concentration from 5 to 15% caused a decrease in Me-LA selectivity due to accumulation of intermediate ethers of furfuryl alcohol. Using a combination of [BMIm-SH][HSO4] and 5% Ru/C catalyst, direct conversion of FAL to gamma-valerolactone (GVL) is shown for the first time. A complete conversion of FAL with the highest selectivity of 68% to GVL could be achieved under optimum conditions while higher Ru loading enhanced the GVL selectivity to 94% in the hydrogenation step of this tandem approach. Our catalyst system could be efficiently recycled five times retaining the original activity and selectivity levels.

Structural variations of D-pi-A dyes influence on the photovoltaic performance of dye-sensitized solar cells - Marszalek, Magdalena; Nagane, Satyawan; Ichake, Amol; Humphry-Baker, Robin; Paul, Vincent; Zakeeruddin, Shaik M.; Gratzel, Michael (RSC Advances, 2013)
Two new organic D-pi-A dyes containing identical pi-conjugated spacer and anchoring/acceptor moieties but different donor groups were designed and synthesized. These dyes containing didodecylcyclopentadithiophene (CPDT) as a spacer, cyanoacrylic acid as an acceptor and N-butyl-carbazole or N-butyl-phenothiazine moieties as electron donor groups are labelled as V4 and V11 dyes, respectively. The variation in the donor group of these two dyes, that influences the photophysical, electrochemical and photovoltaic parameters, was investigated. The highest photovoltaic conversion efficiency of 7.5% was obtained with V4 dye at AM 1.5 G full sunlight intensity (100 mWcm(-2)). Comparison of phenothiazine donor dyes with two different pi-conjugated spacers, CPDT (V11) and vinyl thiophene (V7) containing devices shows that the V-oc of V7 dye is lower than that of V11 due to the downward shift of the conduction band edge. Transient photovoltage and electrochemical impedance spectroscopy measurements were performed to explain the differences in the PV parameters by varying the donors and/or spacer groups.

Synthesis and antimicrobial activity of novel oxysterols from lanosterol - Shingate, Bapurao B.; Hazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (Tetrahedron, 2013)
Chemically diverse oxysterols and their synthetic manipulations were carried out from variety of Delta(8(9)_) lanosterol derivatives and evaluated for their in vitro antimicrobial activities. Most of the synthesized oxysterols exhibited significant antifungal activity against the tested strains. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Allylic oxidation; antibacterial activity; Antifungal activity; Dihydroxylation; Oxygenated steroids

Synthesis and characterization of poly(ether ether ketone)s and poly(ether ether ketone ketone) s containing pendant biphenyl and naphthyl groups - Honkhambe, Pandurang N.; Dhamdhere, Neelam A.; Tawade, Bhausaheb V.; Salunkhe, Manikrao M.; Wadgaonkar, Prakash P. (High Performance Polymers, 2013)
New poly(ether ether ketone)s (PEEKs) and poly(ether ether ketone ketone)s (PEEKKs) containing pendant biphenyl and naphthyl groups were synthesized by nucleophilic substitution reaction of each of the four bisphenols viz., 1-(4- biphenylyl)- 1,1- bis(4- hydroxyphenyl) ethane, 1-(4- biphenylyl)- 1,1- bis(3- methyl, 4- hydroxyphenyl) ethane, 4,4'-[1-(2- naphthalenyl) ethylidene] bis-phenol and 4,4'-[1-(2- naphthalenyl) ethylidene] bis-3-methylphenol with 4,4'- difluorobenzophenone and 1,3- bis(4- fluorobenzoyl) benzene in a solvent mixture of N,N-dimethylacetamide and toluene in the presence of anhydrous potassium carbonate. Inherent viscosities and number-average molecular weights of polymers were in the range of 0.42-0.86 dl/g and 2.40-7.55 x 10(4), respectively. PEEKs and PEEKKs were amorphous in nature and were readily soluble in a wide range of organic solvents and could be cast into flexible and tough films from chloroform solution. Glass transition temperature of PEEKs and PEEKKs were in the range of 180 degrees C -200 degrees C. T-10 values of PEEKs and PEEKKs were in the range of 424 degrees C-512 degrees C in nitrogen atmosphere, indicating their good thermal stability.
Keywords: biphenyl; bisphenol; naphthyl; poly(ether ether ketone ketone)s; poly(ether ether ketone)s; Polycondensation; Thermal properties

Synthesis and molecular structure of a zinc complex of the vitamin K-3 analogue phthiocol - Kathawate, Laxmi; Sproules, Stephen; Pawar, Omkar; Markad, Ganesh; Haram, Santosh K.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2013)
The complex [Zn(phthiocol)(2)(H2O)(2)]; 1, where phthiocol is 2-hydroxy-3-methyl-1,4-naphthoquinone, has been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-vis spectroscopy, thermogravimetric (TG) analysis, electrochemical and single crystal X-ray diffraction studies. The v(C=O) stretch shifts to lower frequencies upon complexation of phthiocol to Zn2+. H-1 NMR spectra show an upfield shift of the benzenoid ring protons in 1. There is a bathochromic shift of the LMCT band in the UV-vis spectra of 1. Single crystal X-ray structure of 1 show distorted octahedral geometry around Zn2+. Two phthiocol ligands are in plane with the metal, while water molecules are trans to this plane. Coordination of deprotonated phthiocol ligands is `trans, trans' to Zn2+. Intra as well as intermolecular interactions are observed in 1. Molecules of 1 show three dimensional network through C-H center dot center dot center dot O and O-H center dot center dot center dot O interactions. Additional anodic peaks are observed in cyclic voltammogram of phthiocol ligand due to oxidation of reduced species formed during reduction. One-electron reduction of 1 is shown to be reversible and DFT studies define this redox event as ligand-centered. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonding; Naphthoquinone; Phthiocol; Trans coordination; Vitamin K-3; Zinc complex

Synthesis and self-assembly of amphiphilic homoglycopolypeptide - Dhaware, Vinita; Shaikh, Ashif Y.; Kar, Mrityunjoy; Hotha, Srinivas; Sen Gupta, Sayam (Langmuir, 2013)
The synthesis of the amphiphilic homoglycopolypeptide was carried out by a combination of NCA polymerization and click chemistry to yield a well-defined Polypeptide having an amphiphilic carbohydrate on its side chain. The amphiphilicity of the carbohydrate was achieved by incorporation of an alkyl chain, at the C-6 position of the carbohydrate thus also rendering the homoglycopolypeptide amphiphilic. The homoglycopolypeptide formed multimicellar aggregates in water above a critical concentration of 0.9 mu M due to phase separation. The multimicellar aggregates were characterized by DLS, TEM, and AFM. It is proposed that hydrophobic interactions of the aliphatic chains at the 6-position of the sugar moieties drives the assembly of these rod-like homoglycopolypeptide into large;spherical aggregates. These multimicellar aggregates encapsulate both hydrophilic as well as hydrophobic dye as was confirmed by confocal microscopy. finally, amphiphilic random polypeptides containing 10% and 20% alpha-D-mannose in addition to glucose containing a, hydrophobic alkyl chain at its 6 position were synthesized by our methodology, and these polymers Were also found to assemble into spherical nanostructures. The spherical assemblies Of amphiphilic random glycopolypeptides containing 10% and 20% mannose were found to be surface bioactive and were found, to interact with the lectin Con-A.

Tetrazine templated method for the synthesis of ternary conjugates - Rao, Boddu Venkateswara; Dhokale, Snehal A.; Rajamohanan, Pattuparambil R.; Hotha, Srinivas (Chemical Communications, 2013)
Conjugation is an important reaction that enables coupling of molecules. Many protocols exist for the synthesis of binary conjugates from two different molecules or for the polyvalent display of a singlemolecule. There aren'tmanymethods for the synthesis of ternary conjugates. However, methods for ternary conjugation are important for understanding the interplay of interactions between three biomolecules (or any three molecules per se). A strategy for ternary bioconjugation using inverse electron demand Diels-Alder reaction with tetrazine is studied. Ternary conjugation was demonstrated by the reaction of a model glyco-peptide binary conjugate with a fluorescent tagged olefin.

Thermodynamic behavior of hydrophobically modified polyacrylamide containing random distribution of hydrophobes: experimental and theoretical investigations - Hourdet, Dominique; Ducouret, Guylaine; Varghese, Sony; Badiger, Manohar V.; Wadgaonkar, Prakash P. (Polymer, 2013)
Two series of Hydrophobically Modified Polyacrylamides (HMPAMs) were prepared by free radical copolymerization of trimethylsilylacrylamide with 3-pentadecylcyclohexylacrylamide (PDCAM) or dodecylacrylamide (DDAM) followed by removal of trimethylsilyl protecting groups. The solution properties of HMPAMs were studied in dilute aqueous solution by fluorescence spectroscopy, NMR and viscometry. The properties in aqueous solution of HMPAMs clearly displayed the formation of hydrophobic interactions between alkyl stickers. While dodecyl containing HMPAMs mainly showed a progressive collapse of the copolymer coil with the increasing fraction of hydrophobic moieties (weak intra-chain associations), pentadecylcyclohexyl groups containing HMPAMs exhibited a much lower solubility in water due to strong intra- and inter-chain associations. Experimental data were analyzed using the mean field theory developed by Semenov and Rubinstein (SR) for associating polymers. Using a set of realistic parameters, taking into account the solubility of the backbone, the fraction of stickers and the strength of hydrophobic attractions, we show that the SR model offers a quantitative description of the thermodynamic properties of HMPAMs in terms of individual and collective behavior of polymers chains; i.e. swelling and phase separation, respectively. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Associating polymer; Polyacrylamide; Self-assembling

Triazole-linked anthracenyl-appended calix[4]arene conjugate as receptor for Co(II): synthesis, spectroscopy, microscopy, and computational studies - Mummidivarapu, V. V. Sreenivasu; Hinge, Vijaya Kumar; Tabbasum, Khatija; Gonnade, Rajesh G.; Rao, Chebrolu P. (Journal of Organic Chemistry, 2013)
A new triazole-linked anthracenyl-appended calix[4]arene-1,3-diconjugate (L) has been synthesized and characterized, and its single crystal XRD structure has been established. Binding properties of L toward different biologically relevant metal ions have been studied by fluorescence and absorption spectroscopy in ethanol. L exhibits selective recognition of Co2+ and can detect down to a concentration of 55 ppb (0.92 mu M). The roles of the calix[4]arene platform as well as the preorganized binding core in L's selective recognition have been demonstrated by studying appropriate control molecules. The mode of binding of L with Co2+ has been modeled both by DFT and MD computational calculations. L and its Co2+ complex could be differentiated on the basis of the nanostructural features observed in AFM and TEM.

Biocatalyst mediated functionalization of salannin, an insecticidal limonoid - Haldar, Saikat; Kolet, Swati P.; Dandekar, Devdutta S.; Kale, Balaji S.; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (RSC Advances, 2014)
Transformation of salannin, an insecticidal C-seco limonoid was investigated using a fungal system, Cunninghamella echinulata. Salannin was efficiently converted into two metabolites, where the C-17 furan moiety was transformed into gamma-hydroxybutenolide (salanninolide) and N-(2-hydroxyethyl)-alpha,beta-unsaturated-gamma-lactam (salanninactam) analogues. Present studies have indicated salanninolide to be a metabolite in the C-seco limonoid biosynthetic pathway.

Biodegradable iron chelate for H2S abatement: modeling and optimization using artificial intelligence strategies - Hamid, Aashti; Deshpande, Aniruddha S.; Badhe, Yogesh P.; Barve, Prashant P.; Tambe, Sanjeev S.; Kulkarni, Bhaskar D. (Chemical Engineering Research & Design, 2014)
A batch reactor process for the abatement of a common pollutant, namely, H2S using Fe3+-malic acid chelate (Fe3+-MA) catalyst has been developed. Further, process modeling and optimization was conducted in the three stages with a view to maximize the H2S conversion: (i) sensitivity analysis of process inputs was performed to select the most influential process operating variables and parameters, (ii) an artificial neural network (ANN)-based data-driven process model was developed using the influential process variables and parameters as model inputs, and H2S conversion (%) as the model output, and (iii) the input space of the ANN model was optimized using the artificial immune systems (AIS) formalism. The AIS is a recently proposed stochastic nonlinear search and optimization method based on the human biological immune system and has been introduced in this study for chemical process optimization. The AIS-based optimum process conditions have been compared with those obtained using the genetic algorithms (GA) formalism. The AIS-optimized process conditions leading to high (approximate to 97%) H2S conversion, were tested experimentally and the results obtained thereby show an excellent match with the AIS-maximized H2S conversion. It was also observed that the AIS required lesser number of generations and function evaluations to reach the convergence when compared with the GA. (C) 2013 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Artificial immune systems; Artificial neural networks; Batch reactor; Genetic algorithms; Sensitivity analysis

Cationic charged helical glycopolypeptide using ring opening polymerization of 6-deoxy-6-azido-glyco-N-carboxyanhydride - Shaikh, Ashif Y.; Das, Soumen; Pati, Debasis; Dhaware, Vinita; Sen Gupta, Sayam; Hotha, Srinivas (Biomacromolecules, 2014)
Glycopolypeptides with a defined secondary structure are of significance in understanding biological phenomena. Synthetic glycopolypeptides, or polypeptides featuring pendant carbohydrate moieties, have been of particular interest in the field of tissue engineering and drug delivery. In this work, we have synthesized charged water-soluble glycopolypeptides that adopt a helical conformation in water. This was carried out by the synthesis of a glyco-N-carboxyanhydride (glyco-NCA) containing an azide group at the sixth position of the carbohydrate ring. Subsequently, the NCA was polymerized to obtain azide-containing glycopolypeptides having good control over molecular weight and polydispersity index (PDI) in high yields. We were also able to control the incorporation of the azide group by synthesizing random co-glycopolypeptide containing 6-deoxy-6-azido and regular 6-OAc functionalized glucose. This azide functionality allows for the easy attachment of a bioactive group, which could potentially enhance the biological activity of the glycopolypeptide. We were able to obtain water-soluble charged glycopolypeptides by both reducing the azide groups into amines and using CuAAC with propargylamine. These charged glycopolypeptides were shown to have a helical conformation in water. Preliminary studies showed that these charged glycopolypeptides showed good biocompatibility and were efficiently taken up by HepG2 cells.

Chitosan and chitosan-co-poly(epsilon-caprolactone) grafted multiwalled carbon nanotube transducers for vapor sensing - Rana, Vijay Kumar; Akhtar, Shamim; Chatterjee, Sudipta; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Nanoscience and Nanotechnology, 2014)
Vapor sensitive transducer films consisting of chitosan grafted (CNT-CS) and chitosan-co-polycaprolactone grafted (CNT-CS-PCL) multiwalled carbon nanotubes were prepared using a spray layer-by-layer technique. The synthesized materials (CNT-CS and CNT-CS-PCL) were characterized by Fourier transform infrared spectroscopy, C-13 CP/MAS solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis. Both CNT-CS and CNT-CS-PCL transducers were analyzed for the response of volatile organic compounds and toluene vapors. The ranking of the relative resistance (A(r)) for both chitosan based transducers were as follows: toluene < chloroform < ethanol < methanol. The CNT transducer (CNT-CS) was correlated selectively with an exponential law to the inverse of Flory-Huggins interaction parameters, chi(12). Dosing the films on the interdigitated electrodes with methanol, ethanol, chloroform and toluene vapors increased the film resistance of CNT-CS but decreased the resistance of CNT-CS-PCL compared to that of the reported transducers.
Keywords: Biocompatibility; Chitosan; MWCNTs; Poly(epsilon-caprolactone); Vapour Sensing

Concise account of the chemistry of valuable alkyl(methyl)maleic anhydrides - Deore, Prashant S.; Haval, Kishan P.; Gadre, Smita R.; N. P. Argade (Synthesis-Stuttgart, 2014)
A large number of significant bioactive natural and synthetic alkyl(methyl)maleic anhydrides are known in the contemporary literature. A broad range of suitably functionalized substrates have been tailored to accomplish concise and efficient syntheses of an array of alkyl(methyl)maleic anhydrides employing a variety of elegant synthetic strategies. This review presents a brief literature account of the isolation and activity of these important target compounds with a special emphasis on their synthesis.
Keywords: alkyl(methyl)maleic anhydrides; bioactivity; dimethylmaleic anhydride; isolation; nucleophilic reactions; Total synthesis

Concise account of various approaches for stereoselective construction of the C-20(H) stereogenic center in steroid side chain - Shingate, Bapurao B.; Hazra, Braja G. (Chemical Reviews, 2014)

Decoding the morphological diversity in two dimensional crystalline porous polymers - Halder, Arjun; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; Density functional calculations; Morphology

Design and synthesis of 3D porous diamondoid frameworks by cocrystallization - Tothadi, Srinu; Little, Marc A.; Hasell, Tom; Briggs, Michel E.; Chong, Samantha Y.; Cooper, Andrew I. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: cocrystals; crystal engineering; Porous Organic Cages

Development of a novel method to grow mono-/few-layered MoS2 films and MoS2-graphene hybrid films for supercapacitor applications - Patil, Sagar; Harle, Arti S.; Sathaye, Shivaram; Patil, Kashinath (CrystEngComm, 2014)
The controlled synthesis of highly crystalline MoS2 atomic layers remains a challenge for practical applications of this emerging material. We demonstrate a facile method to synthesize crystalline mono-layered/few-layered MoS2 thin films at the liquid-liquid interface which can be suitably transferred to the substrates. The films are characterized by XRD for their crystal structure and by SEM and TEM for the morphology. MoS2 nanosheet-graphene nanosheet (MoS2-GNS) hybrid films have been developed by the application of layer-by-layer (LbL) techniques. Cyclic voltammetry and other electrochemical characterization techniques reveal that the hybrid film electrode shows a specific capacitance of 282 F g(-1) at a scan rate of 20 mV s(-1). The as-obtained hybrid electrode is robust and exhibits much improved cycle life (>1000), retaining over 93% of its initial capacitance as revealed by galvanostatic charge/discharge studies. The confirmation of better performance as a supercapacitor of the composite was studied by electrochemical impedance spectroscopy. These results indicate that the MoS2-GNS hybrid is a promising candidate for the electrode material in supercapacitor applications.

Differential transcriptional activity of SAD, FAD2 and FAD3 desaturase genes in developing seeds of linseed contributes to varietal variation in alpha-linolenic acid content - Rajwade, Ashwini V.; Kadoo, Narendra Y.; Borikar, Sanjay P.; Harsulkar, Abhay M.; Ghorpade, Prakash B.; Gupta, Vidya S. (Phytochemistry, 2014)
Linseed or flax (Linum usitatissimum L.) varieties differ markedly in their seed a-linolenic acid (ALA) levels. Fatty acid desaturases play a key role in accumulating ALA in seed. We performed fatty acid (FA) profiling of various seed developmental stages of ten Indian linseed varieties including one mutant variety. Depending on their ALA contents, these varieties were grouped under high ALA and low ALA groups. Transcript profiling of six microsomal desaturase genes (SAD1, SAD2, FAD2, FAD2-2, FAD3A and FAD3B), which act sequentially in the fatty acid desaturation pathway, was performed using real-time PCR. We observed gene specific as well as temporal expression pattern for all the desaturases and their differential expression profiles corresponded well with the variation in FA accumulation in the two groups. Our study points to efficient conversion of intermediate FAs [stearic (SA), oleic (OA) and linoleic acids (LA)] to the final product, ALA, due to efficient action of all the desaturases in high ALA group. While in the low ALA group, even though the initial conversion up to OA was efficient, later conversions up to ALA seemed to be inefficient, leading to higher accumulation of OA and LA instead of ALA. We sequenced the six desaturase genes from the ten varieties and observed that variation in the amino acid (AA) sequences of desaturases was not responsible for differential ALA accumulation, except in the mutant variety TL23 with very low (<2%) ALA content. In TL23, a point mutation in the FAD3A gene resulted into a premature stop codon generating a truncated protein with 291 AA. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: ALA; Fatty acid desaturases; Fatty acids; Flax; Gene expression; Linseed

Enhanced kinetics for the clathrate process in a fixed bed reactor in the presence of liquid promoters for pre-combustion carbon dioxide capture - Babu, Ponnivalavan; Ho, Chie Yin; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
In this work, we present enhanced kinetics of hydrate formation for the clathrate process in the presence of two liquid promoters namely THF (tetrahydrofuran) and TBAB (tetra-n-butyl ammonium bromide) in a FBR (fixed bed reactor) for pre-combustion capture of CO2. Silica sand was used as a medium to capture CO2 from CO2/H-2 gas mixture by hydrate crystallisation. Experiments were performed at different temperatures (274.2 K and 279.2 K) and 6.0 MPa to determine the total gas uptake, induction time and rate of hydrate formation. The observed trends indicated that higher driving force resulted in higher gas consumption and significantly reduced induction time. For the same driving force, higher gas consumption and shorter induction time was achieved by THF as compared to TBAB. 5.53 mol% THF attained higher gas consumption than 1.0 mol% THF whereas 3.0 mol% TBAB attained lower gas consumption than 0.3 mol% TBAB. A highest gas uptake of 51.95 (+/- 5.183) mmol of gas/mol of water and a highest rate of 51.21(+/- 8.91) mol.min(-1).m(-3) were obtained for 5.53 mol% THF at 6.0 MPa and 279.2 K. Overall, this study indicated better hydrate formation kinetics with the use of THF in an FBR configuration for CO2 capture from a fuel gas mixture. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Fixed bed reactor; Gas hydrates; Pre-combustion capture; Promoters

Expedient preparative isolation and tandem mass spectrometric characterization of C-seco triterpenoids from neem oil - Haldar, Saikat; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Dandekar, Devdutta S.; Thulasiram, Hirekodathakallu V. (Journal of Chromatography A, 2014)
C-seco triterpenoids are widely bioactive class of natural products with high structural complexity and diversity. The preparative isolation of these molecules with high purity is greatly desirable, although restricted due to the complexity of natural extracts. In this article we have demonstrated a Medium Pressure Liquid Chromatography (MPLC) based protocol for the isolation of eight major C-seco triterpenoids of salannin skeleton from Neem (Azadirachta indica) oil. Successive application of normal phase pre-packed silica-gel columns for the fractionation followed by reverse phase in automated MPLC system expedited the process and furnished highly pure metabolites. Furthermore, eight isolated triterpenoids along with five semi-synthesized derivatives were characterized using ultra performance liquid chromatography-electrospray ionization-quadrupole/orbitrap-MS/MS spectrometry as a rapid and sensitive identification technique. The structure-fragment relationships were established on the basis of plausible mechanistic pathway for the generation of daughter ions. The MS/MS spectral information of the triterpenoids was further utilized for the identification of studied molecules in the complex extract of stem and bark tissues from Neem. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ESI(+)-quadrupole/orbitrap-MS/MS; MPLC; Neem oil; Preparative isolation; Salannin; Triterpenoids

Formation of a room temperature stable Fe-V(O) complex: reactivity toward unactivated C-H bonds - Ghosh, Munmun; Singh, Kundan K.; Panda, Chakadola; Weitz, Andrew; Hendrich, Michael P.; Collins, Terrence J.; Dhar, Basab B.; Sen Gupta, Sayam (Journal of American Chemical Society, 2014)
An Fe-V(O) complex has been synthesized from equimolar solutions of (Et4N)(2)[Fe-III(Cl)(biuretamide)] and mCPBA in CH3CN at room temperature. The Fe-V(O) complex has been characterized by UV-vis, EPR, Mossbauer, and HRMS and shown to be capable of oxidizing a series of alkanes having C-H bond dissociation energies ranging from 99.3 kcal mol(-1) (cyclohexane) to 84.5 kcal mori (cumene). Linearity in the Bell-Evans-Polayni graph and the finding of a large kinetic isotope effect suggest that hydrogen abstraction is engaged the rate-determining step.

Highly efficient chiral resolution of DL-arginine by cocrystal formation followed by recrystallization under preferential-enrichment conditions - Iwama, Sekai; Kuyama, Kazunori; Mori, Yuko; Manoj, Kochunnoonny; Gonnade, Rajesh G.; Suzuki, Katsuaki; Hughes, Colan E.; Williams, P. Andrew; Harris, Kenneth D. M.; Veesler, Stephane; Takahashi, Hiroki; Tsue, Hirohito; et al. (Chemistry-A European Journal, 2014)
An excellent chiral symmetry-breaking spontaneous enantiomeric resolution phenomenon, denoted preferential enrichment, was observed on recrystallization of the 1:1 cocrystal of dl-arginine and fumaric acid, which is classified as a racemic compound crystal with a high eutectic ee value (>95%), under non-equilibrium crystallization conditions. On the basis of temperature-controlled video microscopy and in situ time-resolved solid-state (CNMR)-C-13 spectroscopic studies on the crystallization process, a new mechanism of phase transition that can induce preferential enrichment is proposed.
Keywords: Amino acids; chiral resolution; cocrystals; Crystal growth; phase transitions

Influence of method of preparation on the activity of La-Ni-Ce mixed oxide catalysts for dry reforming of methane - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Surendar, M.; Lingaiah, N.; Rao, K. S. Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (RSC Advances, 2014)
La-Ni-x-Ce1-x mixed oxide catalysts were prepared by a sol-gel method varying the Ni composition (0 <= x <= 1). The catalysts were characterized by X-ray diffraction (XRD), inductively coupled plasma optical emission spectroscopy (ICP-OES), BET surface area, X-ray photoelectron spectroscopy (XPS), temperature-programmed reduction (TPR), H-2 chemisorption and Fourier transform infrared spectroscopy (FT-IR) techniques. CO2 reforming of methane was carried out at atmospheric pressure and 800 degrees C, maintaining a reactant CO2/CH4/N-2 ratio of 80/80/80 (total flow rate = 240 ml min(-1), GHSV of 28 800 h(-1)). The catalysts offered higher activity even at lower Ni compositions. LaNi0.4Ce0.6O3. showed the highest conversion of CH4 and CO2. The H-2/CO ratio in the syngas was stable at 0.85 +/- 0.02. The performance of the sol-gel catalysts was compared with that of the hydrothermally prepared catalysts, reported earlier. High surface area and better Ni dispersion were found to be the reasons for superior activity of the sol-gel catalysts.

Iodine-catalyzed aromatization of tetrahydrocarbazoles and its utility in the synthesis of glycozoline and murrayafoline A: a combined experimental and computational investigation - Humne, Vivek T.; Dangat, Yuvraj B.; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2014)
A new protocol for the aromatization of tetrahydrocarbazoles has been achieved using a catalytic amount of iodine, giving high yields. The role of iodine in the aromatization has been explained by DFT, and its wide scope is extended to the total synthesis of glycozoline and murrayafoline A. This method has proven to be tolerant of a broad range of functional groups.

Isolation, characterization and antihyperlipidemic activity of secoisolariciresinol diglucoside in poloxamer-407-induced experimental hyperlipidemia - Zanwar, Anand A.; Hegde, Mahabaleshwar V.; Rojatkar, Supada R.; Sonawane, Kiran B.; Rajamohanan, P. R.; Bodhankar, Subhash L. (Pharmaceutical Biology, 2014)
Context: Linum usitatissimum L. (Linaceae), commonly known as flaxseed, is a good source of dietary fiber and lignans. Earlier we reported cardioprotective, antihyperlipidemic, and in vitro antioxidant activity of flax lignan concentrate (FLC) obtained from flaxseed. Objectives: To isolate secoisolariciresinol diglucoside (SDG) from FLC and to evaluate the antihyperlipidemic activity of SDG in poloxamer-407 (P-407)-induced hyperlipidaemic mice. Material and methods: FLC was subjected to column chromatography and further subjected to preparative HPTLC to isolate SDG. The chemical structure of the isolated compound was elucidated by UV, IR, H-1 NMR, C-13 NMR, DEPT, COSY, HSQC, HMBC, ROESY, MS, and specific optical rotation was recorded. Further, we have investigated the antihyperlipidaemic effect of SDG (20 mg/kg) in P-407-induced hyperlipidaemic rats. Hyperlipidaemia was induced by intraperitoneal administration of P-407 (30% w/v). Serum lipid parameters such as total cholesterol (TC), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) levels were measured. Results and discussion: The structure and stereochemistry of the isolated compound were confirmed on the basis of 1D and 2D spectral data and characterized as SDG. Finally, isolated pure SDG was screened using a P-407-induced mice model for its antihyperlipidemic action using serum lipid parameters. The isolated SDG (20 mg/kg) significantly reduced serum cholesterol, triglyceride (p<0.001), very low-density lipoprotein (p<0.05), and non-significantly increased HDL-C. Conclusion: Finally, it was concluded unequivocally that SDG showed antihyperlipidaemic effects in P-407-induced hyperlipidaemic mice. Isolated pure SDG confirms that SDG is beneficial in the prevention of experimental hyperlipidemia in laboratory animals.
Keywords: column chromatography; flaxseed; Linum usitatissimum

Kinetics of photocationically curable formulations involving glycerol diglycidyl ether and phenyl glycidyl ether - Harikrishna, Reghunathan (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2014)
Kinetic analysis of formulations based on glycerol diglycidyl ether and phenyl glycidyl ether were carried out in the presence of sulfonium salt as initiator at 35 mW cm(-2) using photo differential scanning calorimeter and the final conversion was found to increase with an increase in phenyl glycidyl ether content. The effects of formulation monomer ratios at three different temperatures were studied. The variations in the observed kinetic parameters can be related to increase in mobility of reactive species with temperature, distance of counter ion from the propagating cationic center, as well as extent of crosslinking reaction which controlled the course and duration of the reaction. The applicability of autocatalytic kinetic model was also evaluated and the system underwent early gelation and the activation energy decreased with an increase in phenyl glycidyl ether content. Analysis of stable photocured films containing glycerol diglycidyl ether and phenyl glycidyl ether showed better thermal stability than rigid films obtained with glycerol diglycidyl ether.
Keywords: autocatalytic kinetic model; Cationic photopolymerization; Glycidyl ether; Photo DSC

Lipase mediated separation of triterpene structural isomers, alpha- and beta-amyrin - Haldar, Saikat; Kale, Balaji S.; Jadhav, Dipesh D.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2014)
Pentacyclic triterpenoids alpha- and beta-amyrin possess a wide range of biological and pharmacological activities. High structural similarity between these two structural isomers makes their chromatographic separation an ineffective and tedious choice. In this study, Candida rugosa lipase catalyzed separation protocol for the isolation of individual isomers has been developed. In the presence of vinyl acetate as the acyl donor, Candida rugosa lipase carried out acetylation of beta-amyrin more efficiently as compared to alpha-amyrin leading to a kinetic separation. The conditions of transesterification reaction were optimized systematically, which was utilized to separate alpha- and beta-amyrin from a mixture obtained from the latex of Plumeria obtusa. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Amyrin; Candida rugosa; Kinetic separation; Lipase; Structural isomer

Methane reforming with carbon dioxide over La-Ni-x-Ce1-x mixed oxide catalysts - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Upendar, K.; Lingaiah, N.; Rao, Kamaraju Seetha Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
La-Ni-x-Ce1-x mixed oxide (0 <= x <= 1) catalysts have been hydrothermally prepared, characterized by physico-chemical techniques and evaluated for CO2 reforming of methane. High conversions are achieved for both methane and carbon dioxide over the LaNi0.6Ce0.4O3 catalyst tested under the conditions of CO2/CH4/N-2 ratio of 80/80/80. (total flow rate = 240 mL/min), space velocity of 28,800 h(-1) and at a temperature of 800 degrees C. The H-2/CO ratio in the syngas is stable at 0.93 +/- 0.02. Exchanging Ni with Ce, rather than with La as reported in the literature, appears to be a better option for the improved performance of the catalysts.
Keywords: Carbon dioxide reforming; Catalysts; Cerium; Dry reforming; Hydrothermal synthesis; Lanthanum; Methane reforming; Mixed oxides; Nickel

Modeling chain-end scission using the fixed pivot technique - Ho, Yong Kuen; Doshi, Pankaj; Yeoh, Hak Koon; Ngoh, Gek Cheng (Chemical Engineering Science, 2014)
Chain-end scission of polymer molecules is the breakage of a fixed-size oligomer or monomer from either end of the macromolecule. A common example is the generation of the glucose monomer from the hydrolysis of starch by glucoamylase. Modeling the dynamics of chain-end scission from first principles by considering each molecular size is challenging due to the large number of differential equations to be solved. The Population Balance Modeling (PBM) is a helpful framework as it could be formulated to lump a few molecular sizes together. However, it is then not obvious how to accurately account for the temporal evolution of the low molecular weight species, which is often of the greatest industrial interest. Here, the Fixed Pivot (FP) technique - one of the methods to solve PBM equations was appropriately modified to address this difficulty. By treating the lower molecular size range as a discrete domain in conjunction with a continuous domain in the upper ranges, the modified FP technique not only retains its original strengths, but also captures accurately the distribution of oligomers including the monomer. The results, which were obtained at a fraction of computational expense, benchmarked very well against the exact solutions for a polymer with a broad size distribution at different Degrees of Polymerization up to similar to O(10(5)). To facilitate wider adoption, guidelines on choice of pivots and observations of the performance of the modified FP technique are also deliberated. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Chain-end scission; Fixed Pivot; Polymers; Population balance

Molecular structures and biological evaluation of 2-chloro-3-(n-alkylamino)-1,4-napthoquinone derivatives as potent antifungal agents - Pawar, Omkar; Patekar, Ashwini; Khan, Ayesha A.; Kathawate, Laxmi; Haram, Santosh K.; Markad, Ganesh; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Derivatives of 2-chloro-3-(n-alkylamino)-1,4-naphthoquinone (1-alkyl: methyl; L-1, ethyl; L-2, propyl; L-3 and butyl; L-4) have been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-visible spectroscopy, LC-MS and single crystal X-ray diffraction studies. Antifungal activity of L-1 to L-4 has been evaluated against Candida tropicalis, Candida albicans and Cladosporium herbarum. The intramolecular hydrogen bonding affects the N-H vibrational frequency in L-2 (3273 cm(-1)). The single crystal X-ray structure reveal that L-1 and L-3 crystallizes in triclinic P-1, whereas L-2 crystallizes in orthorhombic Pca2(1), space group. An extensive intra and intermolecular hydrogen bonding interactions were observed in L-1 to L-3 which leads to molecular association. Intramolecular N-H center dot center dot center dot O hydrogen bonding were observed in L-1 to L-3. Moreover pi-pi stacking interactions were observed between the quinonoid rings of L-1 and L-3, however no such interactions were observed in L-2. An electrochemical study showed molecular association of L-1 to L-4 in DMSO solution. Compounds L-1 to L-4 were found to be potent antifungal agents against all the three strains, especially against C. tropicalis. Amongst these promising antifungal candidates, L-1 showed better activity compared to the clinically administered antifungal drug Amphotericin B and Nitrofurantoin with MIC = 1.25 mu g ml(-1) and MIC = 0.025 mu g ml(-1) respectively against C. albicans. Structure and activity relationship (SAR) study suggest a LogP value of similar to 2.0 and the cyclic voltammetry studies reveals additional chemical processes for L-1, which exhibits maximum activity against all fungal strains. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Antifungal activity; LogP; Naphthosemiquinone; pi-pi stacking

Mucor hiemalis mediated 14 alpha-hydroxylation on steroids: In vivo and in vitro investigations of 14 alpha-hydroxylase activity - Kolet, Swati P.; Haldar, Saikat; Niloferjahan, Siddiqui; Thulasiram, Hirekodathakallu V. (Steroids, 2014)
Transformation of testosterone and progesterone into synthetically challenging 14 alpha-hydroxy derivatives was achieved by using fungal strain Mucor hiemalis. Prolonged incubation led to the formation of corresponding 6 beta/7 alpha,14 alpha-dihydroxy metabolites. The position and stereochemistry of newly introduced hydroxyl group was determined by detailed spectroscopic analyses. The time course experiment indicated that fungal strain initiated transformation by hydroxylation at 14 alpha-position followed by at 6 beta- or 7 alpha-positions. Studies using cell-free extracts suggest that the 14 alpha-hydroxylase activity is NADPH dependent and belongs to the cytochrome P450 family. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: 14 alpha-Hydroxylase; Biotransformation; Mucor hiemalis; Progesterone; Testosterone

Multi-walled CNT-induced phase behaviour of poly(vinylidene fluoride) and its electro-mechanical properties - Rath, Sangram K.; Dubey, Sachin; Kumar, G. Sudheer; Kumar, Sanjay; Patra, A. K.; Bahadur, Jitendra; Singh, A. K.; Harikrishnan, G.; Patro, T. Umasankar (Journal of Materials Science, 2014)
A simple two-step process was used to disperse acid functionalizedmulti-walled carbon nanotubes (CNTs) in poly(vinylidene fluoride) (PVDF). While the neat solvent-cast PVDF showed coexistence of alpha- and beta-phases; the composite films exhibited only beta-phase crystals. Further studies on the crystalline behaviour, using differential scanning calorimetry and small-angle X-ray scattering techniques showed an increase in the percentage of crystalline phase with CNT. The network formed by CNTs in the matrix reduced the macroscopic electrical resistivity of composite films. The dielectric constant increased with CNT loading. Further, these composites were investigated for its electromagnetic wave absorbance (EWA) and strain sensing properties. The EWA properties were studied in the X-band (6-12 GHz) region. A maximum of similar to 37 dB reflectivity loss at similar to 9.0 GHz was obtained in a similar to 25 mu m thick PVDF film containing only 0.25 wt% of functionalized CNT. Preliminary studies showed a systematic change in electrical resistance by the application of dynamic bending strain in nanocomposite film. The film also showed a significant improvement in mechanical stiffness owing to efficient stress transfer from matrix to filler, the property desirable for a good strain sensor. In view of the unique combination of EWA and electro-mechanical properties, the nanocomposite films are expected to serve as a multifunctional material for strain sensing in health monitoring as well as in radar absorption.

Photopolymerization kinetics of bis-aromatic based urethane acrylate macromonomers in the presence of reactive diluent - Harikrishna, Reghunathan; Ponrathnam, S.; Rajan, C. R. (Progress in Organic Coatings, 2014)
The present work deals with the photopolymerization of bis-aromatic based urethane acrylate macromonomers in the presence of excess end capping agent as reactive diluent and estimation of their kinetic parameters. Formulations were made by independently homogenizing the macromonomers with photoinitiators of three different classes. Three different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using photo DSC under polychromatic radiation. The heat flows against time were recorded for all formulations under isothermal condition and the rates of polymerization, peak maximum times as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, formulations with macromonomer containing propoxylated backbone showed higher conversions than the corresponding ethoxylated analogue. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic model are discussed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bimolecular termination model; kinetics; Macromonomer; Photopolymerization

Photopolymerization of high internal phase emulsions based on 2-ethylhexyl (meth)acrylates and ethylene glycol dimethacrylate - Harikrishna, Reghunathan; Shaikh, A. W.; Ponrathnam, S.; Rajan, C. R.; Bhongale, Sunil Sitaram (Designed Monomers and Polymers, 2014)
Photopolymerization of high internal phase emulsions based on 2-ethylhexyl (meth)acrylates and ethylene glycol dimethacrylate was carried out in presence of low concentration of different photoinitiators. The stable emulsions obtained by mixing with individual photoinitiators were subjected to low-intensity photopolymerization under UV-Visible lamp. Identical samples were irradiated for differing periods ranging from 2 to 10min at an interval of 2min. The percentage conversions of each monomer in the compositions with respect to the time of irradiation were determined using gas chromatography. It was observed that the formulations containing IRGACURE 819 showed the highest conversion while that containing IRGACURE 2959 showed the least conversion. The former showed high conversion due to the proximity of the absorption maxima of photoinitiator to the major emission line of mercury spectrum at 365nm while the latter showed least conversion due to non-availability of major absorption maxima within the irradiation range.
Keywords: (meth)acrylates; high internal phase emulsion; Photopolymerization; residual monomer analysis

Reaction kinetics and modeling of photoinitiated cationic polymerization of an alicyclic based diglycidyl ether - Harikrishna, Reghunathan; Ponrathnam, S.; Tambe, S. S. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2014)
Photoinitiated cationic polymerization of cycloaliphatic diepoxides had received tremendous attention, while studies with lesser polymerizable diglycidyl ethers are comparatively less reported. The present work deals with the photoinitiated cationic polymerization of cyclohexane dimethanol diglycidyl ether followed by estimation of kinetic parameters. The effects of concentration of photoinitiator and temperature on curing performance were studied using photo differential scanning calorimeter or photo DSC with polychromatic radiation. It was observed that the rate of polymerization as well as ultimate conversion increased with increasing concentration of photoinitiator and temperature. The influences of gelation as well as diffusional restrictions have remarkable effect on cure performance. The kinetic parameters as per autocatalytic kinetic model were studied by Levenberg-Marquardt nonlinear regression method instead of conventional linear method for obtaining more accurate values of apparent rate constant. It was observed that the model fits with data from initial stages to almost towards the end of the reaction. The activation energy was found to be higher than the values reported for more reactive cycloaliphatic diepoxides. The value of pre-exponential factor increased with increase in activation energy showing influence of gelation at early stages of reaction. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Autocatalytic model; kinetics; Levenberg-Marquardt method; Photopolymerization

Role of iron oxide impurities in electrocatalysis by multiwall carbon nanotubes: An investigation using a novel magnetically modified ITO electrodes - Samant, Kanchan M.; Joshi, Vrushali S.; Patil, Kashinath R.; Haram, Santosh K. (Bulletin of Materials Science, 2014)
The role of iron oxide impurities in the electrocatalytic properties of multiwall carbon nanotubes (MWCNTs) prepared by catalytic chemical vapour decomposition method (CCVD) is studied in detail. A novel magnetically modified electrodes have been developed by which MWCNTs were immobilized on indium-tin oxide (ITO) electrodes, without any chemical binders. The electro-catalytic oxidation of dopamine, and reduction of hydrogen peroxide have been studied by cyclic voltammetry on magnetically modified electrodes with (i) MWCNTs with occluded iron oxide impurities (Fe-MWCNTs), (ii) MWCNTs grown on iron oxide nanoparticle particulate films (Io-MWCNTs) and (iii) pristine iron oxide nanoparticle particulate film (Io-NPs). A shift towards less positive potentials for the oxidation of dopamine was observed which is in the order of Fe-MWCNTs < Io-MWCNTs < Io-NPs. Similarly, trend towards less negative potentials for the reduction of hydrogen peroxide was observed. Thus, the electrocatalytic activities displayed by MWCNTs have been attributed to the iron oxide impurities associated with it. The systematic variation was related to the nature of interaction of iron oxide nanoparticles with MWCNT surface.
Keywords: dopamine; Hydrogen peroxide; iron oxide nanoparticles; magnetically-modified electrode; Multiwall carbon nanotubes (MWCNTs)

Single-pot formation of THFAL via catalytic hydrogenation of FFR over Pd/MFI catalyst - Biradar, Narayan S.; Hengne, Amol M.; Birajdar, Shobha N.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (ACS Sustainable Chemistry & Engineering, 2014)
Furfural (FFR) was selectively hydrogenated in a single pot to tetrahydrofurfuryl alcohol (THFAL) over a Si MFI molecular sieve supported Pd catalyst. Studies on catalyst screening revealed that both the metal function and the support were critical for directing the selectivity to the ringhydrogenated product, THFAL. The structural feature of MFI as shown by XRD was completely retained in the used sample of the 3% Pd/MFI catalyst confirming its stability under reaction conditions. XRD, along with SEM characterization of the used samples, established retention of morphology of the structured silicate, suggesting a strong interaction between hexagonal porous silicate and Pd particles. The complete conversion of FFR with an enhanced selectivity of 95% to THFAL could be achieved by recycling the crude of the first hydrogenation experiment over the same 3% Pd/MFI catalyst.
Keywords: Biomass conversion; Hydrogenation; Pd/MFI; Recyclability; THFAL

Surface synergism of an Ag-Ni/ZrO2 nanocomposite for the catalytic transfer hydrogenation of bio-derived platform molecules - Hengne, Amol M.; Malawadkar, Atul V.; Biradar, Narayan S.; Rode, Chandrashekhar V. (RSC Advances, 2014)
Levulinic acid was completely and selectively converted to GVL, in the presence of formic acid over an Ag-Ni/ZrO2 catalyst. The synergism between Ag and Ni in transfer hydrogenation eliminates the need for external hydrogen, making the process safer. The magnetic nature of the catalyst offers easy recovery for efficient recycling. This approach is standardized for the hydrogenation of several C-3-C-6 platform molecules in an aqueous medium.

Tailoring the product dstribution with batch and continuous process options in catalytic hydrogenation of furfural - Biradar, Narayan S.; Hengne, Amol A.; Birajdar, Shobha N.; Swami, Rameshwar; Rode, Chandrashekhar V. (Organic Process Research & Development, 2014)
Various noble metal catalysts were screened in a batch operation for a furfural (FFR) single-step decarbonylation and hydrogenation reaction to obtain THF in high selectivity. Among these, the 3% Pd/C showed complete FFR conversion with a total of 80% selectivity to ring hydrogenated products including tetrahydrofuran (THF). The order of activity exhibited by other noble metals was Pt/C > Re/C > Ru/C. Although Pt/C exhibited the highest activity, its decarbonylation and ring hydrogenation ability were the least (24%) with a major product selectivity of 66% to furfuryl alcohol (FAL). Similarly, the Cu catalyst gave almost complete selectivity to FAL. In a continuous operation (23 g catalyst bed), the 3% Pd/C catalyst showed higher selectivity of >40% compared to THF alone with complete FFR conversion and on-stream activity of similar to 100 h. The reaction pathway elucidated from some control experiments revealed that the decarbonylation of FFR to furan over the Pd/C catalyst is a prerequisite for THF formation.

Titania nanoparticles stabilized HPA in SBA-15 for the intermolecular hydroamination of activated olefins - Sawant-Dhuri, Dhanashri; Balasubramanian, Veerappan V.; Ariga, Katsuhiko; Park, Dae-Hwan; Choy, Jin-Ho; Cha, Wang Soo; Al-deyab, Salem S.; Halligudi, Shivappa B.; Vinu, Ajayan (ChemCatChem, 2014)
A liquid phase hydroamination (HA) of alpha,beta-ethylenic compounds with amines was investigated with TiO2 nanoparticles stabilized 12-tungstophosphoric acid (TPA) in SBA-15. The catalysts were prepared by wet impregnation of TPA/TiO2 nanoparticles into the SBA-15 and calcined at different temperatures. The characterization results reveal that the textural properties and the acidity of the prepared catalysts can be finely controlled with the simple adjustment of the calcination temperature and the structure of the support, decorated with the TiO2 and TPA nanoparticles, was intact even after the modification. The prepared catalysts were investigated for HA of ethyl acrylate with different aromatic and aliphatic amines over a wide range of reaction conditions to optimize the yield and the selectivity of product. It was found that this process is 100% atom efficient and the catalytic performance depended significantly on the loading of TPA over the catalyst and the calcination temperature. Under optimized reaction conditions, the best catalyst, 15 wt% TPA/22.4 wt% TiO2/SBA-15 calcined at 1123 K, offered the highest conversion of p-ethylaniline (70%) with 100% chemo-selectivity to the anti-Markovnikov product, i.e., the mono-addition product. The reaction was heterogeneously catalyzed and no contribution from leached TPA into the reaction was observed.
Keywords: heteropoly acids; hydroamination; mesoporous materials; nanocatalysts

Total synthesis of (+/-)-nardoaristolone B and its analogues - Handore, Kishor L.; Reddy, D. Srinivasa (Organic Letters, 2014)
The first total synthesis of nardoaristolone B, a nor-sesquiterpenoid with an unusual fused ring system and having protective effects on the injury of neonatal rat cardiomyocytes, has been accomplished. Stereoselective synthesis of its novel analogues inlcuding exo-cyclopropyl ring fusion is also part of this disclosure. In addition, an alternate and more efficient one-step method to make a 3/5/6 tricyclic ring system using the Robinson annulation method has been developed toward the generation of a library of compounds around this skeleton.

Ambient temperature photocopolymerization of tetrahydrofurfuryl methacrylate and isobornyl methacrylate: reactivity ratios and thermal studies - Rajdeo, K. S.; Ponrathnam, S.; Pardeshi, S.; Chavan, Nayaku; Bhongale, Sunil Sitaram; Harikrishna, Reghunathan (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2015)
Photocopolymerization of heterocyclic monomer namely, tetrahydrofurfuryl methacrylate with bulky bicyclic monomer, isobornyl methacrylate with different feed ratios was carried out in bulk with low concentration of an -hydroxyl ketone based photoinitiator. The ambient temperature photocopolymerization was carried out by using a UV-Visible lamp with fixed low intensity of 0.4mW cm(-2) for a period of 6min. The residual monomer remained in the polymerization process were determined by using gas chromatography. The reactivity ratio values for the two monomers were calculated from the copolymer composition data by using Fineman-Ross, Kelen-Tudos, Extended Kelen-Tudos and Mao-Huglin methods. Individually, as well as the average of all the methods revealed that the monomer reactivity ratios of tetrahydrofurfuryl methacrylate were higher than isobornyl methacrylate. The dyad sequence distribution and dyad sequence lengths were calculated using the Igarashi and Pyun method and the sequence length distribution for tetrahydrofurfuryl methacrylate was observed to be higher with an increase in its feed content. This supports the reactivity ratio studies that a higher monomer reactivity ratio value for tetrahydrofurfuryl methacrylate was observed as compared to its comonomer. The thermal studies showed that the glass transition temperatures of the copolymers increased with an increase in isobornyl methacrylate content.
Keywords: Copolymer; methacrylates; micro structure; photocopolymerization; reactivity ratios; thermal studies

Association between serum albumin and glycated hemoglobin in Asian Indian subjects - Tiwari, Shalbha; Botahle, Manish; Hasan, Imtiaz; Kulkarni, Mahesh J.; Sayyad, Mehmood G.; Basu, Rita; Basu, Ananda; Unnikrishnan A. G. (Indian Journal of Endocrinology and Metabolism, 2015)
Protein glycation plays a significant role in diabetic complications. Glycated hemoglobin (HbA1c) is a known predictor of diabetes and its complications. Albumin, found to be profoundly glycated in diabetes, and its level could regulate plasma protein as well as hemoglobin glycation. We aimed to evaluate the association between variations in albumin level with HbA1c in the Asian Indian population. We screened data of 929 subjects who have had a simultaneous measurement of fasting plasma glucose (FPG), HbA1c and albumin levels via the same blood collection. Data were analyzed by SPSS for 610 subjects who met the study criteria. There was a significant negative correlation between HbA1c and albumin concentration (r = -0.284; P < 0.001). Univariate analysis showed the statistically significant decrease of average HbA1c but not for fasting plasma glucose (FPG) across increasing tertiles of albumin. Stepwise multiple regression model showed a significant correlation between HbA1c and serum albumin (P < 0.05), FPG (P < 0.001), hemoglobin (Hb) (P < 0.001) and serum globulin (P < 0.05). FPG was the strongest predictor (63.4%) of variation of HbA1c. The albumin concentration (r = -0.114) accounted for 0.3% (P < 0.05) of the total variance in HbA1c independent of age, body mass index, FPG, Hb, creatinine, total protein and globulin. It was also observed that HbA1c decreases with increasing albumin concentration in those having FPG between 100 to <126 mg/dl. Serum albumin negatively correlates with HbA1c in Asian Indians independent of other variables. This study suggests that predicting diabetes and its complication based on the HbA1c needs to be further investigated in Indian subjects.

Cationic photopolymerization kinetics of neat coating formulations involving poly(propylene glycol) diglycidyl ether and glycerol diglycidyl ether - Harikrishna, Reghunathan (Journal of Thermal Analysis and Calorimetry, 2015)
Kinetic analysis of formulations based on poly(propylene glycol) diglycidyl ether and glycerol diglycidyl ether was carried out using photodifferential scanning calorimeter. The effects of formulation monomer ratios at different temperatures were studied as photocalorimetric optimization studies of formulation ratios involving diglycidyl ethers are less reported. The nature of cure was found to depend more on the in situ physical parameters rather than on the mechanism of the reaction. The variations in the observed kinetic parameters can be related to interplay of mobility of reactive species, distance of counter ion and the diffusional restrictions. The final conversion was found to increase with increase in poly(propylene glycol) diglycidyl ether content, while the thermal stability increased with an increase in glycerol diglycidyl ether content. Autocatalytic kinetic model was also evaluated, and the system underwent early gelation. The studies show that the intermediate formulations are promising compositions for surface-coating applications.
Keywords: Coatings; Diglycidyl ether; kinetics; PhotoDSC; Photopolymerization

Cell line development for biomanufacturing processes: recent advances and an outlook - Le, Huong; Vishwanathan, Nandita; Jacob, Nitya M.; Gadgil, Mugdha; Hu, Wei-Shou (Biotechnology Letters, 2015)
At the core of a biomanufacturing process for recombinant proteins is the production cell line. It influences the productivity and product quality. Its characteristics also dictate process development, as the process is optimized to complement the producing cell to achieve the target productivity and quality. Advances in the past decade, from vector design to cell line screening, have greatly expanded our capability to attain producing cell lines with certain desired traits. Increasing availability of genomic and transcriptomic resources for industrially important cell lines coupled with advances in genome editing technology have opened new avenues for cell line development. These developments are poised to help biosimilar manufacturing, which requires targeting pre-defined product quality attributes, e.g., glycoform, to match the innovator's range. This review summarizes recent advances and discusses future possibilities in this area.
Keywords: Biomanufacturing; Biosimilars; Cell line development; CHO cells genomics; Genome editing; Transcriptomics

Chemical sensing in two dimensional porous covalent organic nanosheets - Das, Gobinda; Biswal, Bishnu P.; Kandambeth, Sharath; Venkatesh, V.; Kaur, Gagandeep; Addicoat, Matthew A.; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul (Chemical Science, 2015)
Two new imide-based crystalline, porous, and chemically stable covalent organic frameworks (COFs) (TpBDH and TfpBDH) have been successfully synthesized employing solvothermal crystallization route. Furthermore, thin layered covalent organic nanosheets (CONs) were derived from these bulk COFs by the simple liquid phase exfoliation method. These 2D CONs showcase increased luminescence intensity compared to their bulk counterparts (COFs). Notably, TfpBDH-CONs showcase good selectivity and prominent, direct visual detection towards different nitroaromatic analytes over TpBDH-CONs. Quite interestingly, TfpBDH-CONs exhibit a superior ``turn-on'' detection capability for 2,4,6-trinitrophenol (TNP) in the solid state, but conversely, they also show a ``turn-off'' detection in the dispersion state. These findings describe a new approach towards developing an efficient, promising fluorescence chemosensor material for both visual and spectroscopic detection of nitroaromatic compounds with very low [10(-5) (M)] analyte concentrations.

Chromerid genomes reveal the evolutionary path from photosynthetic algae to obligate intracellular parasites - Woo, Yong H.; Ansari, Hifzur; Otto, Thomas D.; Klinger, Christen M.; Kolisko, Martin; Michalek, Jan; Saxena, Alka; Shanmugam, Dhanasekaran; Tayyrov, Annageldi; Veluchamy, Alaguraj; Ali, Shahjahan; Bernal, Axel; et al. (Elife, 2015)
The eukaryotic phylum Apicomplexa encompasses thousands of obligate intracellular parasites of humans and animals with immense socio-economic and health impacts. We sequenced nuclear genomes of Chromera velia and Vitrella brassicaformis, free-living non-parasitic photosynthetic algae closely related to apicomplexans. Proteins from key metabolic pathways and from the endomembrane trafficking systems associated with a free-living lifestyle have been progressively and non-randomly lost during adaptation to parasitism. The free-living ancestor contained a broad repertoire of genes many of which were repurposed for parasitic processes, such as extracellular proteins, components of a motility apparatus, and DNA-and RNA-binding protein families. Based on transcriptome analyses across 36 environmental conditions, Chromera orthologs of apicomplexan invasion-related motility genes were co-regulated with genes encoding the flagellar apparatus, supporting the functional contribution of flagella to the evolution of invasion machinery. This study provides insights into how obligate parasites with diverse life strategies arose from a once free-living phototrophic marine alga.

Development of newer adsorbents: activated carbons derived from carbonized cassia fistula - Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Salvi, Monal S.; Jain, Saijal; Hadawale, Snehal D.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2015)
Development of newer adsorbent materials, especially from biomass, is most crucial to sustain growth of otherwise well established adsorption processes that already have hundreds of commercial adsorbents in practice. In the present study, newer adsorbents and their potential-carbonaceous adsorbents derived from the whole fruit of Cassia fistula (Golden shower) have been reported for applications in environmental pollution control using natural, renewable biomass as precursor. The potential of different forms of the derived adsorbents produced by thermal and chemical activation was examined for two representative cases, desulfurization of transportation fuels and wastewater treatment. The adsorbents were characterized by FTIR, XRD, XPS, and SEM techniques that indicate specific characteristics useful as an adsorbent. A successful application in the real industrial wastewater treatment and comparison with well recognized commercial adsorbents clearly highlights the utility of the developed newer adsorbents in separation science and technology.

Exploiting powder x-ray diffraction to establish the solvent-assisted solid-state supramolecular assembly of pillar[5]quinone - Shivakumar, Kilingaru I.; Yan, Yuncheng; Hughes, Colan E.; Apperley, David C.; Harris, Kenneth D. M.; Sanjayan, Gangadhar J. (Crystal Growth & Design, 2015)
We report the solvent-mediated supramolecular assembly of pillar[5]quinone (P[5]Q), a symmetric cyclamer containing five benzoquinone moieties bridged by five alternating methylene units. The supramolecular assembly of P[5]Q is shown to be facilitated by 1,1,2,2-tetrachloroethane (TCE) as solvent, producing a microcrystalline solvate material P[5]Q(.)2TCE with a fluffy texture. Optical and electron microscopy reveal that this material has a rod-shaped morphology, extending to several micrometers in length. Due to the microcrystalline nature of the material, structure determination was carried out directly from powder X-ray diffraction data, augmented by high-resolution solid-state C-13 NMR. The two crystallographically distinct TCE molecules occupy different types of void in the structure and have different dynamic properties. Crystallization of P[5]Q was attempted from a large number of different solvents, but only TCE was found to facilitate the formation of a crystalline phase. Indeed, features of the crystal structure suggest that the TCE component plays an important role in promoting the columnar assembly of P[5]Q molecules.

Gedunin and azadiradione: human pancreatic alpha-amylase inhibiting limonoids from neem (azadirachta indica) as anti-diabetic agents - Ponnusamy, Sudha; Haldar, Saikat; Mulani, Fayaj A.; Smita S. Zinjarde; Thulasiram, Hirekodathakallu; RaviKumar, Ameeta (Plos One, 2015)
Human pancreatic alpha-amylase (HPA) inhibitors offer an effective strategy to lower postprandial hyperglycemia via control of starch breakdown. Limonoids from Azadirachta indica known for their therapeutic potential were screened for pancreatic alpha-amylase inhibition, a known anti-diabetic target. Studies were carried out to reveal their mode of action so as to justify their hypoglycemic potential. Of the nine limonoids isolated/semi-synthesized from A. indica and screened for alpha-amylase inhibition, azadiradione and exhibited potential inhibition with an IC50 value of 74.17 and 68.38 mu M, respectively against HPA under in vitro conditions. Further screening on AR42J alpha-amylase secretory cell line for cytotoxicity and bioactivity revealed that azadiradione and gedunin exhibited cytotoxicity with IC50 of 11.1 and 13.4 mu M. Maximal secreted alpha-amylase inhibition of 41.8% and 53.4% was seen at 3.5 and 3.3 mu M, respectively. Michaelis-Menten kinetics suggested a mixed mode of inhibition with maltopentaose (K-i 42.2, 18.6 mu M) and starch (K-i' 75.8, 37.4 mu M) as substrate with a stiochiometry of 1: 1 for both azadiradione and gedunin, respectively. The molecular docking simulation indicated plausible p-alkyl and alkyl-alkyl interactions between the aromatic amino acids and inhibitors. Fluorescence and CD confirmed the involvement of tryptophan and tyrosine in ligand binding to HPA. Thermodynamic parameters suggested that binding is enthalpically and entropically driven with Delta G degrees of -21.25 kJ mol(-1) and -21.16 kJ mol(-1) for azadiradione and gedunin, respectively. Thus, the limonoids azadiradione and gedunin could bind and inactivate HPA (anti-diabetic target) and may prove to be lead drug candidates to reduce/control post-prandial hyperglycemia.

Gelation landscape engineering using a multi-reaction supramolecular hydrogelator system - Foster, Jamie S.; Zurek, Justyna M.; Almeida, Nuno M. S.; Hendriksen, Wouter E.; le Sage, Vincent A. A.; Lakshminarayanan, Vasudevan; Thompson, Amber L.; Banerjee, Rahul; Eelkema, Rienk; Mulvana, Helen; Paterson, Martin J.; van Esch, Jan H.; et al. (Journal of the American Chemical Society, 2015)
Simultaneous control of the kinetics and thermodynamics of two different types of covalent chemistry allows pathway selectivity in the formation of hydrogelating molecules from a complex reaction network. This can lead to a range of hydrogel materials with vastly different properties, starting from a set of simple starting compounds and reaction conditions. Chemical reaction between a trialdehyde and the tuberculosis drug isoniazid can form one, two, or three hydrazone connectivity products, meaning kinetic gelation pathways can be addressed. Simultaneously, thermodynamics control the formation of either a keto or an enol tautomer of the products, again resulting in vastly different materials. Overall, this shows that careful navigation of a reaction landscape using both kinetic and thermodynamic selectivity can be used to control material selection from a complex reaction network.

Green approach for the decoration of Pd nanoparticles on graphene nanosheets: an in situ process for the reduction of C-C double bonds and a reusable catalyst for the suzuki cross-coupling reaction - Hussain, Najrul; Borah, Ashwini; Darabdhara, Gitashree; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (New Journal of Chemistry, 2015)
A new strategy for in situ synthesis of palladium nanoparticles (Pd NPs) decorated on reduced graphene oxide (rGO) nanosheets with controlled size and shape is reported. This strategy was designed as three processes in one pot, namely, (a) reduction of graphene oxide, (b) formation of Pd NPs on the rGO nanosheets and (c) simultaneous reduction of olefin. In this synthesis process, a hydrogen atmosphere was used to develop the Pd NPs-rGO nanocatalyst, which is reusable and easily separable. The influence of the size and morphology of the Pd-rGO-H-2 catalyst on the catalytic activity in the Suzuki cross-coupling reaction was investigated by comparing with other catalysts, Pd-rGO-As and Pd-rGO-Gl, and they were synthesized by different reducing agents, ascorbic acid and glucose, respectively. The catalysts were characterized by electron microscopy (HRTEM, SEM), FT-IR, XRD and XPS. The Pd-rGO-H-2 catalyst was found to possess excellent catalytic activity and recyclability in the Suzuki cross-coupling reaction under mild reaction conditions.

Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions - Hussain, Najrul; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (Catalysis Science & Technology, 2015)
Highly stable Cu(0) nanoparticles were synthesized on reduced graphene oxide (rGO) sheets using a cost-effective and green method. The synthesized Cu(0)-nanoparticle-rGO composites exhibit excellent catalytic activity for the synthesis of symmetrical biaryls from arylboronic acids under microwave irradiation. The reaction proceeds smoothly in base-free conditions with easy recovery and reuse of the catalyst. The methodology is compatible with various functional groups and provides an attractive protocol for the synthesis of symmetrical biaryls with very good yields. HRTEM, XPS and XRD analyses showed the catalyst to be recyclable. The Cu(0) nanoparticles are stable in the rGO nanosheets, and the particle size distribution and oxidation state of the Cu(0) nanoparticle remain the same after performing the chemical reaction.

Heat transfer and mixing in flow through pinched pipe - Hasabnis, Nilesh S.; Totlani, Kartik A.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2015)
There is an increasing trend of using tubular reactors either with passive or active augmentation methods for process intensification. A new passive method with pinching of pipe' is proposed and investigated for its performance. In the present work, initially, flow in a pinched pipe was studied experimentally and the same was reproduced numerically. The computational model was then used to investigate influences of key geometrical parameters of pinched pipe configuration on pressure drop, heat transfer, and mixing. The simulated results obtained with the pinched pipe were compared with a straight pipe, and with a commonly-used passive augmentation method (twisted tape inserts). The pinched pipe configuration offers better performance and more flexibility in manipulating heat transfer and mixing in intensified devices.
Keywords: computational fluid dynamics (CFD); heat transfer; mixing; pinched pipe; pressure drop

Hierarchical CdS nanostructure by Lawesson's reagent and its enhanced photocatalytic hydrogen production - Pandit, Vikram U.; Arbuj, Sudhir S.; Hawaldar, Ranjit R.; Kshirsagar, Pradnya V.; Deshmukh, Amarsinh J.; Ambekar, Jalindar D.; Mulik, Uttam P.; Gosavi, Suresh W.; Kale, Bharat B. (RSC Advances, 2015)
Lawesson's reagent (LR) has been effectively exploited for the synthesis of hierarchical architectures of cadmium sulphide (CdS) nanostructures for the first time. The X-ray diffractograms of the as synthesised CdS nanostructures confirm the formation of hexagonal CdS. The broadness of the XRD peaks clearly indicates the nanocrystalline nature of CdS with average crystallite size of 4 nm. A FESEM study revealed the formation of hierarchical nanostructures, whereas a TEM study showed that the hierarchical arrangement is composed of nanosized CdS particles. A band-gap i.e. 2.4 eV was derived from diffuse reflectance spectroscopy. The photoluminescence spectrum showed an emission peak at 535 and 568 nm which can be attributed to band-edge emission and surface emissions or possible metal vacancies, respectively. Considering the band-gap within the visible region, the photocatalytic hydrogen evolution performance of these CdS nanostructures was performed under visible light irradiation from hydrogen sulphide and water, respectively. Utmost hydrogen evolution i.e. 14 136 mu mol h(-1) g(-1) and 2065 mu mol h(-1) g(-1) was observed over a naked CdS nanostructure via H2S and water decomposition, respectively. The amount of hydrogen obtained by H2S splitting is much higher as compared to earlier reports.

Inhibition effect of N,N-diglycidyl-4-glycidyloxy aniline on photosensitized cationic polymerization of formulations involving resorcinol diglycidyl ether and poly(propylene glycol)diglycidyl ether - Harikrishna, Reghunathan (Journal of Photochemistry and Photobiology A-Chemistry, 2015)
Cationic photopolymerization studies of poly(propylene glycol)diglycidyl ether with and without 25 wt% of resorcinol diglycidyl ether were carried out in presence of bis(4-methylphenyl)iodonium hexafluorophosphate as photoinitiator. Analyses were carried out using polychromatic radiation at different temperatures in a photo differential scanning calorimeter. The formulations showed an enhancement in the rate of polymerization on addition of resorcinol diglycidyl ether. The same formulations when subjected to photosensitized polymerization in presence of 1-chloro-4-propoxy-9H-thioxanthen-9-one, showed a reverse behavior in rate due to partial absorption of radiation by resorcinol diglycidyl ether. Studies carried out on by the addition of N,N-diglycidy1-4-glycidyloxy aniline as inhibitor on the photosensitized formulations showed higher scavenging activity by inhibitor. The addition of nitrogen containing epoxy monomer as inhibitor can lead to its possible crosslinking within the matrix on polymerization along with a decrease in rate of polymerization without compromising on the final observed conversion. This effect can occur readily for non vitrifying systems. Thus, this observation provides an insight into its possible usage in a rate controlled photopolymerizable epoxy formulations. The photopolymerization kinetics were found to depend on the nature of generation, propagation and scavenging of active centers which are heavily dependent on diffusional restrictions imparted by in situ viscosity of the system. The kinetic estimations as well as evaluation of autocatalytic kinetic model are investigated. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Glycidyl ether; Inhibition; kinetic model; kinetics; Photopolymerization; Photosensitization

Interlinked population balance and cybernetic models for the simultaneous saccharification and fermentation of natural polymers - Ho, Yong Kuen; Doshi, Pankaj; Yeoh, Hak Koon; Ngoh, Gek Cheng (Biotechnology and Bioengineering, 2015)
Simultaneous Saccharification and Fermentation (SSF) is a process where microbes have to first excrete extracellular enzymes to break polymeric substrates such as starch or cellulose into edible nutrients, followed by in situ conversion of those nutrients into more valuable metabolites via fermentation. As such, SSF is very attractive as a one-pot synthesis method of biological products. However, due to the co-existence of multiple biochemical steps, modeling SSF faces two major challenges. The first is to capture the successive chain-end and/or random scission of the polymeric substrates over time, which determines the rate of generation of various fermentable substrates. The second is to incorporate the response of microbes, including their preferential substrate utilization, to such a complex broth. Each of the above-mentioned challenges has manifested itself in many related areas, and has been competently but separately attacked with two diametrically different tools, i.e., the Population Balance Modeling (PBM) and the Cybernetic Modeling (CM), respectively. To date, they have yet to be applied in unison on SSF resulting in a general inadequacy or haphazard approaches to examine the dynamics and interactions of depolymerization and fermentation. To overcome this unsatisfactory state of affairs, here, the general linkage between PBM and CM is established to model SSF. A notable feature is the flexible linkage, which allows the individual PBM and CM models to be independently modified to the desired levels of detail. A more general treatment of the secretion of extracellular enzyme is also proposed in the CM model. Through a case study on the growth of a recombinant Saccharomyces cerevisiae capable of excreting a chain-end scission enzyme (glucoamylase) on starch, the interlinked model calibrated using data from the literature (Nakamura et al., Biotechnol. Bioeng. 53:21-25, 1997), captured features not attainable by existing approaches. In particular, the effect of various enzymatic actions on the temporal evolution of the polymer distribution and how the microbes respond to the diverse polymeric environment can be studied through this framework. Biotechnol. Bioeng. 2015;112: 2084-2105. (c) 2015 Wiley Periodicals, Inc.
Keywords: cybernetic modeling; population balance modeling; simultaneous saccharification and fermentation

Isolation, characterization and antifungal docking studies of wortmannin isolated from penicillium radicum - Singh, Vineeta; Praveen, Vandana; Tripathi, Divya; Haque, Shafiul; Somvanshi, Pallavi; Katti, S. B.; Tripathi, C. K. M. (Scientific Reports, 2015)
During the search for a potent antifungal drug, a cell-permeable metabolite was isolated from a soil isolate taxonomically identified as Penicillium radicum. The strain was found to be a potent antifungal agent. Production conditions of the active compound were optimized and the active compound was isolated, purified, characterized and identified as a phosphoinositide 3-kinase (PI3K) inhibitor, commonly known as wortmannin (Wtmn). This is very first time we are reporting the production of Wtmn from P. radicum. In addition to its previously discovered anticancer properties, the broad spectrum antifungal property of Wtmn was re-confirmed using various fungal strains. Virtual screening was performed through molecular docking studies against potential antifungal targets, and it was found that Wtmn was predicted to impede the actions of these targets more efficiently than known antifungal compounds such as voriconazole and nikkomycin i.e. 1) mevalonate-5-diphosphate decarboxylase (1FI4), responsible for sterol/isoprenoid biosynthesis; 2) exocyst complex component SEC3 (3A58) where Rho-and phosphoinositide-dependent localization is present and 3) Kre2p/Mnt1p a Golgi alpha1,2-mannosyltransferase (1S4N) involved in the biosynthesis of yeast cell wall glycoproteins). We conclude that Wtmn produced from P. radicum is a promising lead compound which could be potentially used as an efficient antifungal drug in the near future after appropriate structural modifications to reduce toxicity and improve stability.

Mechanically stable thermally cross linked poly(acrylic acid)/reduced graphene oxide aerogels - Ha, Heonjoo; Shanmuganathan, Kadhiravan; Ellison, Christopher J. (ACS Applied Materials & Interfaces, 2015)
Graphene oxide (GO) aerogels, high porosity (>99%) low density (similar to 3-10 mg cm(-3)) porous materials with GO pore walls, are particularly attractive due to their lightweight, high surface area, and potential use in environmental remediation, superhydrophobic and superoleophilic materials, energy storage, etc. However, pure GO aerogels are generally weak and delicate which complicates their handling and potentially limits their commercial implementation. The focus of this work Vas to synthesize highly elastic, mechanically stable aerogels that are robust and easy to handle without substantially sacrificing their high porosity or low density. To overcome this challenge, a small amount of readily available and, thermally cross-linkable poly(acrylic acid) (PAA) was intermixed with GO to enhance the mechanical integrity Of the aerogel without disrupting other desirable characteristic properties. This method is a simple straightforward procedure that does not include multistep or complicated chemical reactions, and it produces aerogels with mass densities of about 4-6 mg cm(-3) and >99.6% porosity-that can reversibly support up to 10 000 times their weight with full recovery of their original volume. Finally; pressure sensing capabilities were demonstrated and their oil absorption capacities were measured to be around 120 g oil per g aerogel(-1) which highlights their potential Use in practical applications.
Keywords: aerogels; environmental remediation; graphene; Nanocomposites; poly(acrylic acid)

Multifunctional polyaniline-tin oxide (PANI-SnO2) nanocomposite: synthesis, electrochemical, and field emission investigations - Patil, Sandip S.; Harpale, Kashmira V.; Koiry, Shankar P.; Patil, Kashinath R.; Aswal, Dinesh K.; More, Mahendra A. (Journal of Applied Polymer Science, 2015)
Synthesis of PANI-SnO2 nanocomposite has been performed using a simple two step chemical oxidative polymerization route. The structural, morphological and chemical properties of the as-synthesized PANI-SnO2 nanocomposite have been revealed by various characterization techniques such as SEM, TEM, XRD, FTIR, and XPS. Interestingly the as-synthesized PANI-SnO2 nanocomposite exhibits supercapacitance value of 721 F g(-1) with energy density 64 Wh kg(-1), which is noticed to be higher than that of pristine SnO2 and PANI nanostructures. Furthermore, the galvanostatic charge-discharge characteristics revealed pseudocapacitive nature of the PANI-SnO2 nanocomposite. The estimated values of charge transfer resistance and series resistance estimated from the Nyquist plot are found to be lower. Along with the supercapacitive nature, PANI-SnO2 nanocomposite showed promising field emission behavior. The threshold field, required to draw emission current density of 1 A/cm(2), is observed to be 0.90 V/m and emission current density of 1.2 mA/cm(2) has been drawn at applied field of approximate to 2.6 V/m. The emission current stability investigated at preset values of 0.02 and 0.1 mA/cm(2) is observed to be fairly stable over duration of more than 3 h. The enhanced supercapacitance values, as well as, the promising field emission characteristics are attributed to the synergic effect of SnO2 nanoparticles and PANI nanotubes. (c) 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41401.
Keywords: conducting polymers; Electrochemistry; nanostructured polymers; surfaces and interfaces

Novel hybrid nocodazole analogues as tubulin polymerization inhibitors and their antiproliferative activity - Kale, Sangram S.; Jedhe, Ganesh S.; Meshram, Sachin N.; Santra, Manas K.; Hamel, Ernest; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2015)
We describe the design, synthesis and SAR profiling of a series of novel combretastatin-nocodazole conjugates as potential anticancer agents. The thiophene ring in the nocodazole moiety was replaced by a substituted phenyl ring from the combretastatin moiety to design novel hybrid analogues. The hydroxyl group at the ortho position in compounds 2, 3 and 4 was used as the conformationally locking tool by anticipated six-membered hydrogen bonding. The bioactivity profiles of all compounds as tubulin polymerization inhibitors and as antiproliferative agents against the A-549 human lung cancer cell line were investigated Compounds 1 and 4 showed mu M IC50 values in both assays. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Anticancer; Colchicine; Nocodazole; Tubulin binding

Production of polyunsaturated fatty acids in recombinant lipomyces starkeyi through submerged fermentation - Salunke, Devyani; Manglekar, Rupali; Gadre, Ramchandra V.; Nene, Sanjay; Harsulkar, Abhay M. (Bioprocess and Biosystems Engineering, 2015)
Long chain polyunsaturated fatty acids (LCPUFA) are known to play an important role in human health and nutrition. Considering the limitation of LCPUFA sources, it is necessary to search new avenues for their production. Oleaginous yeasts are an attractive target for harvesting single cell oil, mainly because of the ease of cultivation with cheaper raw material. Lipomyces starkeyi is one such oleaginous yeast, which can accumulate oil to the extent of 60 % of its biomass and where genetic transformation can be achieved. In our earlier work, Delta 15 desaturase gene (AEP37840) from flax was transformed into L. starkeyi. In the present work, we report optimization of medium for the production of omega-3 enriched oil from this transformed yeast. A basic medium containing 20 g/l glucose as a carbon source and 10 g/l yeast extract as a nitrogen source was used during fermentation. At regular time intervals, glucose was fed to maintain high C:N ratio (65:10) during fermentation. Under the most favorable conditions, dry biomass and total lipid content were 18 and 7.29 g/l, respectively. Prior to genetic transformation, L. starkeyi contained 56.03 mg/l DHA along with 71.4 mg/l EPA and 42.2 mg/l ALA. Genetic engineering of this yeast resulted in a strain that produced 1080 mg/l DHA (17.4 %) along with 74.28 mg/l EPA and 126.72 mg/l ALA possibly through modification of PUFA biosynthetic pathway. To the best of our knowledge, this is a first report of DHA enrichment and opens up avenues for LCPUFA production through L. starkeyi.
Keywords: Fermentation; LCPUFA; Lipid production; Oleaginous yeast

Reduction of graphene oxide by 100 MeV Au ion irradiation and its application as H2O2 sensor - Hareesh, K.; Joshi, R. P.; Shateesh, B.; Asokan, K.; Kanjilal, D.; Late, Dattatray J.; Dahiwale, S. S.; Bhoraskar, Vasant N.; Haram, Santosh K.; Dhole, Sanjay D. (Journal of Physics D-Applied Physics, 2015)
Graphene oxide (GO) synthesized from a modified Hummer's method was reduced (referred, rGO) by using 100 MeV Au ion species and its response to the sense H2O2 was investigated. The changes in the atomic composition and structural properties of rGO after irradiation were studied using x-ray diffraction, Fourier transform infrared spectroscopy and x-ray photoelectron spectroscopy. These results suggested that the removal of the oxygen-containing functional groups and the improvement of the electrochemical performance of reduced graphene oxide (rGO) after ion irradiation. Raman spectroscopic results revealed the increase in the disorder parameter (I-D/I-G) after Au ion irradiation and also the formation of a large number of small sp(2) domains due to the electronic energy loss of ion beam. The resultant rGO was investigated for H2O2 sensing using electrochemical techniques and it showed a good response.
Keywords: electronic energy loss; GO; ion beam irradiation; reduction

Self-templated chemically stable hollow spherical covalent organic framework - Kandambeth, Sharath; Venkatesh, V.; Shinde, Digambar B.; Kumari, Sushma; Halder, Arjun; Verma, Sandeep; Banerjee, Rahul (Nature Communications, 2015)
Covalent organic frameworks are a family of crystalline porous materials with promising applications. Although active research on the design and synthesis of covalent organic frameworks has been ongoing for almost a decade, the mechanisms of formation of covalent organic frameworks crystallites remain poorly understood. Here we report the synthesis of a hollow spherical covalent organic framework with mesoporous walls in a single-step template-free method. A detailed time-dependent study of hollow sphere formation reveals that an inside-out Ostwald ripening process is responsible for the hollow sphere formation. The synthesized covalent organic framework hollow spheres are highly porous (surface area similar to 1,500m(2) g(-1)), crystalline and chemically stable, due to the presence of strong intramolecular hydrogen bonding. These mesoporous hollow sphere covalent organic frameworks are used for a trypsin immobilization study, which shows an uptake of 15.5 mu mol g(-1) of trypsin.

Solid state organic amine detection in a photochromic porous metal organic framework - Mallick, Arijit; Garai, Bikash; Addicoat, Matthew A.; Petkov, Petko St.; Heine, Thomas; Banerjee, Rahul (Chemical Science, 2015)
A new Mg(II) based photochromic porous metal-organic framework (MOF) has been synthesized bearing naphthalenediimide (NDI) chromophoric unit. This MOF (Mg-NDI) shows instant and reversible solvatochromic behavior in presence of solvents with different polarity. Mg-NDI also exhibits fast and reversible photochromism via radical formation. Due to the presence of electron deficient NDI moiety, this MOF exhibits selective organic amine (electron rich) sensing in solid state. The organic amine detection has been confirmed by photoluminescence quenching experiment and visual color change.

Stepwise isolation of low-valent, low-coordinate Sn and Pb mono- and dications in the coordination sphere of platinum - Braunschweig, Holger; Celik, Mehmet Ali; Dewhurst, Rian D.; Heid, Magdalena; Hupp, Florian; Sen, Sakya S. (Chemical Science, 2015)
Synthetic access to low-coordinate Pb mono- and dications is in general impeded due to their poor solubility and highly electrophilic nature. However, the electrophilicity of these cations can be tamed by attaching them to electron-rich transition metals. Following this principle we have isolated low-valent Pb mono- ([(Cy3P)(2)Pt-PbCl](2)[AlCl4](2), 8a) and dications ([(Cy3P)(2)Pt(Pb)][AlCl4](2), 11) in the coordination sphere of platinum. The same approach then has been implemented for the isolation of analogous low-valent Sn mono- (7a) and dications (10). An energy decomposition analysis (EDA-NOCV) was performed to investigate the nature of Pt-Pb and Pb-Cl bonding in [(Cy3P)(2)Pt(PbCl2)] (2), 8a and 11. The results show that the Pt-Pb bonds in 8a and 11 are electron-sharing in nature, whereas that of the precursor 2 is a dative bond. The breakdown of attractive interactions in 2, 8a and 11 reveals that the ionic interactions in the analyzed Pt-Pb and Pb-Cl bonds are always stronger than the covalent interactions, except for the Pb-Cl bond in 8a. The calculated D3 dispersion energies show that dispersion interactions play a key role in the thermodynamic stability of 2, 8a and 11.

Structural order of water molecules around hydrophobic solutes: length-scale dependence and solute-solvent coupling - Hande, Vrushali R.; Chakrabarty, Suman (Journal of Physical Chemistry B, 2015)
It has been suggested that the structure and thermodynamics of the water molecules in the hydration layer of simple hydrophobic solutes undergo an order disorder transition around a nanometer length-scale of the solute size. Using extensive atomistic molecular dynamics (MD) and replica exchange molecular dynamics (REMD) simulation studies, we have probed this order disorder transition around model hydrophobic solutes of varying size and shape (spherical, planar, and linear), as well as flexible hydrophobic homopolymer chains (n-alkanes), where the conformational fluctuations are likely to create both spatial and temporal heterogeneity on the solvent accessible surface. We have explored the structural response of the water molecules in the hydration shell due to the local variations of the length-scale (or curvature) upon hydrophobic collapse and/or local conformational changes of these polymers. We have shown that the tetrahedral order of the water molecules in the hydration shell is practically independent of the polymer size in the extended state of the polymer due to the availability of a subnanometer cross-sectional length-scale, allowing the water molecules to form hydrogen bonds around the polymer chain. Beyond a certain length of the polymer chains, the collapsed states (associated with larger solute length-scale) start to induce disorder in the surface water molecules. We demonstrate that the local structure (both local number density and tetrahedral order) of the hydration layer is dynamically coupled to the local topology of the polymer. Thus, we envisage that in a flexible (bio)polymer, the hydration shell properties will be sensitive to the local conformational state of the molecule (both spatially and temporally), and the overall observed water structure and dynamics will be dependent on the topological/chemical heterogeneity, and the time-scale of fluctuations in the local curvature (length-scale) of the solvent accessible surface. Moreover, we have demonstrated the direct coupling between the local density fluctuations of water and the local hydrophobic collapse of the polymer. For the extended state of the polymer, the local solvent density fluctuation is practically independent of the solute coordinate (length-scale), and the hydrophobic collapse of the polymer is prompted by a ``local dewetting'' process induced by these fluctuations.

Synthesis and characterization of PEPO grafted carboxymethyl guar and carboxymethyl tamarind as new thermo-associating polymers - Gupta, Nivika R.; Torris, Arun A. T.; Wadgaonkar, Prakash P.; Rajamohanan, P. R.; Ducouret, Guylaine; Hourdet, Dominique; Creton, Costantino; Badiger, Manohar V. (Carbohydrate Polymers, 2015)
New thermo associating polymers were designed and synthesized by grafting amino terminated poly(ethylene oxide-co-propylene oxide) (PEPO) onto carboxymethyl guar (CMG) and carboxymethyl tamarind (CMT). The grafting was performed by coupling reaction between-NH2 groups of PEPO and -COOH groups of CMG and CMT using water-soluble EDC/NHS as coupling agents. The grafting efficiency and the temperature of thermo-association, T-assoc in the copolymer were studied by NMR spectroscopy. The graft copolymers, CMG-g-PEPO and CMT-g-PEPO exhibited interesting thermo-associating behavior which was evidenced by the detailed rheological and fluorescence measurements. The visco-elastic properties (storage modulus, G'; loss modulus, G'') of the copolymer solutions were investigated using oscillatory shear experiments. The influence of salt and surfactant on the T-assoc was also studied by rheology, where the phenomenon of ``Salting out'' and ``Salting in'' was observed for salt and surfactant, respectively, which can give an easy access to tunable properties of these copolymers. These thermo-associating polymers with biodegradable nature of CMG and CMT can have potential applications as smart injectables in controlled release technology and as thickeners in cosmetics and pharmaceutical formulations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Carboxymethyl tamarind; Pluronics; Rheology; Solution behavior; Thermo-associating polymers

Themed issue on ``Organic field-effect transistors: interfacial phenomena and electronic properties'' - Krishnamoorthy, K.; Facchetti, Antonio F.; Hu, Wenping; Bao, Zhenan (Physical Chemistry Chemical Physics, 2015)

Total and semi-syntheses of antimicrobial thuggacin derivatives - Franke, Jana; Bock, Martin; Dehn, Richard; Fohrer, Joerg; Mhaske, Santosh B.; Migliorini, Antonella; Kanakis, Argyrios A.; Jansen, Rolf; Herrmann, Jennifer; Mueller, Rolf; Kirschning, Andreas (Chemistry-A European Journal, 2015)
The total and semi-synthesis of 13 new macrolactones derived from thuggacin, which is a secondary metabolite from the myxobacterium Sorangium cellulosum, are reported. The thuggacins have attracted much attention due to their strong antibacterial activity, particularly towards Mycobacterium tuberculosis. This study focuses on 1) thuggacin derivatives that cannot equilibrate by transacylation between the three natural thuggacins A-C, 2) the roles of the thiazole ring, and 3) the hexyl side chain at C2. Semi-synthetic O-methylation at C17 suppressed the transacylations without a substantial loss of antibacterial activity. Exchanging the C17-C25 side chain for simplified hydrophobic chains led to complete loss of antibacterial activity. Exchange of the thiazole by an oxazole ring or removal of the hexyl side chain at C2 had no substantial effect on the biological properties.
Keywords: antibiotics; lactones; Natural products; synthesis design; Total synthesis

Total syntheses and biological evaluation of (+/-)-botryosphaeridione, (+/-)-pleodendione, 4-epi-periconianone B, and analogues - Handore, Kishor L.; Jadhav, Prakash D.; Hazra, Bibhabasu; Basu, Anirban; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
The total syntheses of (+/-)-botryosphaeridione, (+/-)-pleodendione, (+/-)-hoaensieremodione, 4-epi-periconianone B, and their analogues have been accomplished for the first time. All the synthesized target compounds were screened in neural anti-inflammatory assays using LPS induced microglia cells (N9). Among them, compounds 1 and 21 were identified as potential lead compounds for further profiling.
Keywords: antineuroinflammatoty agents; bohyosphaeridione; Natural product; pleodendione; Total synthesis

Triterpenoid profiling and functional characterization of the initial genes involved in isoprenoid biosynthesis in neem (Azadirachta indica) - Pandreka, Avinash; Dandekar, Devdutta S.; Haldar, Saikat; Uttara, Vairagkar; Vijayshree, Shinde G.; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Thulasiram, Hirekodathakallu V. (BMC Plant Biology, 2015)
Background: Neem tree (Azadirachta indica) is one of the richest sources of skeletally diverse triterpenoids and they are well-known for their broad-spectrum pharmacological and insecticidal properties. However, the abundance of Neem triterpenoids varies among the tissues. Here, we delineate quantitative profiling of fifteen major triterpenoids across various tissues including developmental stages of kernel and pericarp, flower, leaf, stem and bark using UPLC-ESI (+)-HRMS based profiling. Transcriptome analysis was used to identify the initial genes involved in isoprenoid biosynthesis. Based on transcriptome analysis, two short-chain prenyltransferases and squalene synthase (AiSQS) were cloned and functionally characterized. Results: Quantitative profiling revealed differential abundance of both total and individual triterpenoid content across various tissues. RNA from tissues with high triterpenoid content (fruit, flower and leaf) were pooled to generate 79.08 million paired-end reads using Illumina GA.. platform. 41,140 transcripts were generated by d e novo assembly. Transcriptome annotation led to the identification of the putative genes involved in isoprenoid biosynthesis. Two short-chain prenyltransferases, geranyl diphosphate synthase (AiGDS) and farnesyl diphosphate synthase (AiFDS) and squalene synthase (AiSQS) were cloned and functionally characterized using transcriptome data. RT-PCR studies indicated five-fold and ten-fold higher relative expression level of AiSQS in fruits as compared to leaves and flowers, respectively. Conclusions: Triterpenoid profiling indicated that there is tissue specific variation in their abundance. The mature seed kernel and initial stages of pericarp were found to contain the highest amount of limonoids. Furthermore, a wide diversity of triterpenoids, especially C-seco triterpenoids were observed in kernel as compared to the other tissues. Pericarp, flower and leaf contained mainly ring-intact triterpenoids. The initial genes such as AiGDS, AiFDS and AiSQS involved in the isoprenoids biosynthesis have been functionally characterized. The expression levels of AiFDS and AiSQS were found to be in correlation with the total triterpenoid content in individual tissues.
Keywords: Azadirachta indica; Quantitative profiling; Transcriptome; Triterpenoids

Vanadium in borosilicate glass - Sengupta, Pranesh; Dey, Krishna K.; Halder, Rumu; Ajithkumar, Thalasseril G.; Abraham, Geogy; Mishra, Raman K.; Kaushik, Chetan P.; Dey, Goutam K. (Journal of the American Ceramic Society, 2015)
Understanding the role of V2O5 within borosilicate glass matrices is important for the development of novel matrices toward immobilization of sulfate containing high-level nuclear wastes. Present investigation shows, within sodium barium borosilicate glass matrix V2O5 can be homogeneously added up to 5mol% and beyond which it separates out into three phases, for example, (i) silica (ii) Barium (Ba) - Vanadium (V) oxide, and (iii) glass matrix. Si-29 MAS NMR (Nuclear Magnetic Resonance) studies of the samples show that below 5mol% V2O5 addition, silicate network is dominantly constituted of Q(2) and Q(3) structural units, whereas above this, the network gets more polymerized through formation of Q(3) and Q(4) units. In case of borate network, B-11 MAS NMR investigations revealed that the concentration of BO4 [(0B, 4Si)] unit increases gradually up to 5mol% and then it decreases at the cost of BO4 [(1B, 3Si)], BO3 (symmetric) and BO3 (asymmetric) units. Micro-Raman analyses of the samples showed that with additions of V2O5 in diluted concentrations, amorphous silicate network remained unaltered, whereas some amplification in signals corresponding to ring-type metaborate and VO5 units exists. It is therefore apparent from both MAS-NMR and micro-Raman studies that with V2O5 additions within the solubility limit (5mol%), borate network gets depolymerized leading to decrease in hardness from an average value of 5.0-4.2GPa.

Void fraction measurement using electrical capacitance tomography and high speed photography - Sardeshpande, Madhavi V.; Harinarayan, Sagar; Ranade, Vivek V. (Chemical Engineering Research & Design, 2015)
Gas-liquid flows are encountered in variety of industrial applications including boilers, distillation towers, chemical reactors, oil pipelines, nuclear reactors etc. The measurement of two-phase flow parameters such as flow regime and void fraction is considerably important and play an important role in characterization of the hydrodynamic behavior of such gas-liquid two phase systems. The void fraction is a dimensionless quantity and is often termed as ``holdup or fraction'' in two-phase flows. According to industrial applications; it is essential to develop measurement technique for void fraction measurement which can work in hot and opaque systems. Therefore, an attempt was made here to establish electrical capacitance tomography (ECT) facility for measuring void fraction and flow regimes as well as develop suitable data processing methodologies. In the present work, focus was to measure void fraction using ECT technique and compares it with conventional and high speed photography technique. Therefore, that will give guidelines of using ECT technique for hot and opaque systems like boiling flows. (C) 2014 The Institution of Chemical Engineers. Published by Elsevier BM. All rights reserved.
Keywords: ECT; Flow regimes; Two phase flow; Void fraction

Whole-cell mediated 11 beta-hydroxylation on the basic limonoid skeleton by cunninghamella echinulata - Haldar, Saikat; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2015)
Regio- and stereoselective 11 beta-hydroxylation was achieved on the basic limonoid skeleton through microbial transformation. Whole cells of Cunninghamella echinulata efficiently converted basic limonoids such as epoxyazadiradione, azadiradione, and gedunin to their 11 beta-hydroxy analogues as the sole metabolite. Fermentation conditions affecting the efficiency (96%) of biotransformation including substrate concentration, incubation period, pH, and temperature were optimized. The position and stereochemistry of hydroxyl functionality on the isolated metabolites were established through extensive spectroscopic and spectrometric studies (1D, 2D NMR, ESI-MS, and MS/MS).

Actinorectispora indica gen. nov., sp nov isolated from soil, a member of the family pseudonocardiaceae - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Al Ruwaili, Jamal; Hozzein, Wael N.; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2016)
The taxonomic positions of three Gram-stain-positive, aerobic strains, designated YIM 75722, 75726 and 75728(T), and isolated from a soil sample collected from Kurnool of Andhra Pradesh province, India, were assessed using a polyphasic approach. Growth was observed at pH 7.0-10.0 (optimum pH 7.0), 15-28 degrees C (optimum 28 degrees C) and 0-8% (w/v) NaCl (grew without NaCl). Strains showed cylindrical spores with straight-chain morphology on aerial mycelium, but did not reveal sporangium-like structures or fragmentation of the substrate mycelium. Whole-cell hydrolysates of all strains contained galactose and ribose as the diagnostic sugars and meso-diaminopimelic acid as the diamino acid. The predominant menaquinone was MK-9(H-4); MK-9 (H-6) and MK-10 (H-4) were present in smaller amounts. The phospholipid pattern consisted mainly of diphosphatidylglycerol, phosphatidylglycerol and phosphatidylcholine. The major fatty acids were i-C-15: 0, ai-C-15: 0, i-C-17 : 0 and ai-C-17 : 0. The genomic DNA G+C content was 68.0 mol%. Phylogenetic analysis, based on 16S rRNA gene sequences, revealed that strain YIM 75728(T) should be placed within the family Pseudonocardiaceae, in which the strain formed a distinct lineage. The combination of phylogenetic analysis, phenotypic characteristics and chemotaxonomic data support the conclusion that strain YIM 75728(T) represents a novel species of a novel genus of the family Pseudonocardiaceae for which the name Actinorectispora indica gen. nov., sp. nov., is proposed. Strain YIM 75728(T) (=DSM 45410(T)=CCTCC AA 209065(T)) is the type strain of Actinorectispora indica. Strain YIM 75728(T) was considered as the type strain over the other two strains based on the highest sequence read length of the strain.

Azadirachta indica triterpenoids promote osteoblast differentiation and mineralization in vitro and in vivo - Kushwaha, Priyanka; Khedgikar, Vikram; Haldar, Saikat; Gautam, Jyoti; Mulani, Fayaj A.; Thulasiram, Hirekodathakallu V.; Trivedi, Ritu (Bioorganic & Medicinal Chemistry Letters, 2016)
Terpenoids were isolated using chromatographic purification through solvent purification technique and identified as Azadirone (1), Epoxyazadiradione (2) Azadiradione (3) Gedunin (4) Nimbin (5) Salannin (6) Azadirachtin A (7) and Azadirachtin B (8) from Azadirachta indica. Out of eight compounds, only three compounds had osteogenic activity and enhanced osteoblast proliferation, differentiation and mineralization in osteoblast cells. Active compounds stimulated osteogenic genes ALP, RunX-2 and OCN expressions in vitro, but Azadirachtin A had a maximum ability to stimulate osteoblast differentiation and mineralization compared to other two active compounds. For in vivo study, Azadirachtin A injected subcutaneously in pups, which enhanced osteogenic gene expressions and promoted bone formation rate significantly. Here, we conclude that active compounds of Azadirachta indica have osteogenic activity and Azadirachtin A has a beneficial effects on bone. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: ALP and mineralization assay; Balb/c mice pups; Calvarial osteoblast cells; Gene expressions

Bicinchoninic acid-based colorimetric chemosensor for detection of low concentrations of cyanide - Biradar, Archana A.; Biradar, Ankush V.; Sun, Tiffany; Chan, Yung; Huang, Xiaoxi; Asefa, Tewodros (Sensors and Actuators B-Chemical, 2016)
Bicinchoninic acid (BCA) is reagent that is widely used to determine the concentration of proteins in solutions through the colored complex it forms with Cu(I) and the proteins. In this report, we present a new use for BCA, where a highly sensitive method for detection of cyanide ions in solutions by using Cu2+-BCA complex as the chemosensing agent is demonstrated. The detection of cyanide ions is achieved by taking advantage of the nucleophilic attack of the Cu2+-BCA complex by cyanide ions. Upon the addition of cyanide ions, the Cu2+-BCA complex undergoes transformations to free BCA via a series of equilibriums and, as a result, forms different Cu(II)-(BCA)(x)(CN)(y) species depending on the concentrations of cyanide ions in the solution. These different Cu(II)-(BCA)(x)(CN)(y) species, in turn, give different metal-to-ligand charge transfer electronic spectra and colors that are easily detectable both with naked eyes and UV-vis spectroscopy. As the cyanide ion concentration increases, the color of the solution containing the complexes changes from green to purple, red, yellow, and finally colorless, giving a corresponding blue shift in the absorption maxima on their UV-vis spectra. Through this process, the complexes enable detection of cyanide ions with a detection level of up to 0.06 ppm in solutions. Thus, this colorimetric technique based on Cu2+-BCA can make low concentrations of cyanide detectable, well before the concentrations possibly reach lethal amounts. Furthermore, the method is shown to give fast detection response with no interference from other anionic and cationic species and has the potential to be adopted for accurate and convenient analysis of cyanide ions in drinking water sources as well as industrial effluents. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: BCA; Bicinchoninic acid; Chemosensor; Colorimetric sensor; Copper; Cyanide

Chitosan-based lead ion-imprinted interpenetrating polymer network by simultaneous polymerization for selective extraction of lead(ii) - Hande, Pankaj E.; Kamble, Sanjay; Samui, Asit B.; Kulkarni, Prashant S. (Industrial & Engineering Chemistry Research, 2016)
In this study, we report the synthesis of a Pb(II) ion-imprinted interpenetrating polymer network (II-IPN) by simultaneous polymerization for selective extraction of Pb(II) from printed-circuit-board (PCB) recycling unit wastewater. Initially, a polymer network was synthesized by polymerization of methacrylic acid (monomer) and ethylene glycol dimethacrylate (cross-linker) and a second polymer network by chitosan (complexing monomer) and tetraethyl orthosilicate (cross-linker). The chemical structure and morphology of the II-IPN were analyzed using Fourier transform infrared, field-emission scanning electron microscopy, atomic force microscopy, and transmission electron microscopy. The interaction of the functionality in the II-IPN with Pb(II) through chelation was studied by X-ray photoelectron spectroscopy analysis. The maximum adsorption capacities for II-IPN and nonimprinted interpenetrating polymer network were 37.5 and 10.3 mg g(-1), respectively. The largest selectivity coefficient for Pb(II) in the presence of W(VI) was 161.58. The developed Pb(II) II-IPN was successfully employed for selective extraction of Pb(II) from PCB recycling unit wastewater.

Correlating Nitrile IR frequencies to local electrostatics quantifies noncovalent interactions of peptides and proteins - Deb, Pranab; Haldar, Tapas; Kashid, Somnath M.; Banerjee, Subhrashis; Chakrabarty, Suman; Bagchi, Sayan (Journal of Physical Chemistry B, 2016)
Noncovalent interactions, in particular the hydrogen bonds and nonspecific long-range electrostatic interactions are fundamental to biomolecular functions. A molecular understanding of the local electrostatic environment, consistently for both specific (hydrogen-bonding) and nonspecific electrostatic (local polarity) interactions, is essential for a detailed understanding of these processes. Vibrational Stark Effect (VSE) has proven to be an extremely useful method to measure the local electric field using infrared spectroscopy of carbonyl and nitrile based probes. The nitrile chemical group would be an ideal choice because of its absorption in an infrared spectral window transparent to biomolecules, ease of site-specific incorporation into proteins, and common occurrence as a substituent in various drug molecules. However, the inability of VSE to describe the dependence of IR frequency on electric field for hydrogen-bonded nitriles to date has severely limited nitrile's utility to probe the noncovalent interactions. In this work, using infrared spectroscopy and atomistic molecular dynamics simulations, we have reported for the first time a linear correlation between nitrile frequencies and electric fields in a wide range of hydrogen-bonding environments that may bridge the existing gap between VSE and H-bonding interactions. We have demonstrated the robustness of this field-frequency correlation for both aromatic nitriles and sulfur-based nitriles in a wide range of molecules of varying size and compactness, including small molecules in complex solvation environments, an amino acid, disordered peptides, and structured proteins. This correlation, when coupled to VSE, can be used to quantify noncovalent interactions, specific or nonspecific, in a consistent manner.

Decoding the morphological diversity in two dimensional crystalline porous polymers by core planarity modulation - Halder, Arjun; Kandambeth, Sharath; Biswal, Bishnu P.; Kaur, Gagandeep; Roy, Neha Chaki; Addicoat, Matthew A.; Salunke, Jagadish K.; Banerjee, Subhrashis; Vanka, Kumar; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul (Angewandte Chemie - International Edition, 2016)

Dietary flaxseed oil and fish oil ameliorates renal oxidative stress, protein glycation, and inflammation in streptozotocin-nicotinamide-induced diabetic rats - Jangale, Nivedita M.; Devarshi, Prasad P.; Bansode, Sneha B.; Kulkarni, Mahesh J.; Harsulkar, Abhay M. (Journal of Physiology and Biochemistry, 2016)
Protective and prophylactic effects of omega-3 fatty acids on oxidative stress and inflammation are well known. We assessed beneficial effects of flaxseed oil and fish oil on streptozotocin (65 mg/kg; i.p.)-nicotinamide (110 mg/kg; i.p.) induced diabetic rats by studying renal expression of antioxidant and inflammatory genes. Diabetic rats given 10 % flaxseed oil or 10 % fish oil diet for 35 days showed significant decrease in renal lipid peroxidation. Flaxseed oil diet resulted in up-regulation of renal superoxide dismutase-1 (SOD-1) (activity and expression) and glutathione peroxidase-1 (GPx-1) expression. Furthermore, both diets up-regulated catalase (CAT) (activity and expression) and down-regulated heme oxygenase-1 (HO-1) expression. Both diets were able to limit the renal advanced glycation end products (AGEs) formation and reduced receptor of AGE (RAGE) protein expression significantly. Expressions of interleukin-6 (IL-6) and NF-kappa B p65 subunit were down-regulated significantly by flaxseed oil or fish oil diet. The histological tubular injuries were also lowered by both diets. These results suggest that dietary omega-3 fatty acids may slow the progression of diabetic nephropathy (DN) associated with oxidative stress, glycation, and inflammation in the kidney.
Keywords: Diabetes; Fish oil; Flaxseed oil; Glycation; Kidney; Streptozotocin

Editorial: actinobacteria in special and extreme habitats: diversity, function roles, and environmental adaptations - Qin, Sheng; Li, Wen-Jun; Dastager, Syed Gulam; Hozzein, Wael N. (Frontiers in Microbiology, 2016)
Keywords: actinobacteria; activities; diversity; environmental adaptation; omics technologies; special and extreme environments

Electrostatic interactions are key to C=O n-pi* shifts: an experimental proof - Haldar, Tapas; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2016)
Carbonyl n-pi* transitions are known to undergo blue shift in polar and hydrogen-bonding solvents. Using semiempirical expressions, previous studies hypothesized several factors like change in dipole moment and hydrogen-bond strength upon excitation to cause the blue shift. Theoretically, ground-state electrostatics has been predicted to be the key to the observed shifts, however, an experimental proof has been lacking. Our experimental results demonstrate a consistent linear correlation between IR (ground-state phenomenon) and n-pi* frequency shifts (involves both ground and excited electronic-states) of carbonyls in hydrogen-bonded and non-hydrogen-bonded environments. The carbonyl hydrogen-bonding status is experimentally verified from deviation in n-pi*/fluorescence correlation. The IR/n-pi* correlation validates the key role of electrostatic stabilization of the ground state toward n-pi* shifts and demonstrates the electrostatic nature of carbonyl hydrogen bonds. n-pi* shifts show linear sensitivity to calculated electrostatic fields on carbonyls. Our results portray the potential for n-pi* absorption to estimate local polarity in biomolecules and to probe chemical reactions involving carbonyl activation/stabilization.

Encapsulation of yeast (Saccharomyces cereviciae) by spray drying for extension of shelf life - Chandralekha, A.; Tavanandi, A. Hrishikesh; Amrutha, N.; Hebbar, H. Umesh; Raghavarao, K. S. M. S.; Gadre, Ramchandra V. (Drying Technology, 2016)
The objective of the present work was to encapsulate yeast using different carrier materials and examine their efficacy in retaining viability of cells after spray drying. Slurry containing yeast cells along with known amount of carrier material (maltodextrin, corn starch, gum arabic, acacia gum, polyethylene glycol 8000, -cyclodextrin, and skimmed milk powder, one at a time) was added and served as feed. Among these carrier materials attempted, corn starch and maltodextrin showed the best results with respect to powder yield (59%, w/w) and cell survival (80.5%), respectively. However, considering both survival and powder yield (67 and 59% w/w, respectively), corn starch was observed to be the most suitable carrier material.
Keywords: Cell viability; Encapsulation; freeze-drying; spray drying; Yeast

Exploration of the presence of bulk-like water in AOT reverse micelles and water-in-oil nanodroplets: the role of charged interfaces, confinement size and properties of water - Hande, Vrushali R.; Chakrabarty, Suman (Physical Chemistry Chemical Physics, 2016)
The properties of water in a confined environment can be drastically different than the bulk water. In a confined system, e.g. the interior of a reverse micelle, there exist at least two distinct regions namely ``interfacial water'' characterized by markedly slower dynamics, and ``core water'', which may resemble bulk water for a larger size of the water pool. Using atomistic molecular dynamics simulations, we systematically investigate the presence of bulk-like water in AOT reverse micelles (RMs) with varying size given by w(0) = [H2O]/[AOT] = 10, 15 and 20. In order to understand the effect of the negatively charged interface of the RM, we have performed control studies for the model systems of water-in-oil (isooctane) nanodroplets with the same size of the water pool as the RM systems. In order to quantify the deviations from bulk-like behavior, we have used three kinds of structural order parameters, namely (i) number density to probe the local translational ordering, (ii) tetrahedral order and hydrogen bond distribution to probe the local orientational ordering, and (iii) dipolar orientation relative to the radial vector to capture the global orientational ordering of the water dipoles. We demonstrate that the size of the ``core water'' region that resembles bulk water decreases in the above order, i.e. orientational order parameters of water molecules are perturbed by the charged interface to a larger length scale as compared to the translational order. We have compared the translational and rotational dynamics of the water molecules for the interfacial and core regions to find that the slower dynamics persists even for the core water for the size range that we have studied although to a much lesser extent as compared to the interfacial water. Moreover, we demonstrate that the hydrophobic interface in the water-in-oil nanodroplets has a much weaker effect on the structure and dynamics of the confined water molecules as compared to the anionic RMs. Thus, the major contribution towards the structural ordering and slow dynamics of water in a charged RM system would originate from the strong electrostatic and hydrogen bonded interactions with the interface, and not due to the spatial confinement effect.

Field emission investigation of composites of polypyrrole with graphene oxide, reduced graphene oxide and graphene nanoribbons - Harpale, Kashmira; Bansode, Sanjeewani; More, Mahendra; Late, D. J. (2016 29th International Vacuum Nanoelectronics Conference (IVNC), 2016)
The monomer pyrrole has been polymerized by chemical route in the presence of graphene oxide (GO), reduced graphene oxide (rGO) and graphene nanoribbons (GNR) separately to prepare nanocomposites as Polypyrrole-GO (PGO), PPy-rGO (PRGO), PPy-GNR (PGNR), respectively. The morphological, chemical and structural characterization of the as-synthesized products was carried out using scanning electron microscopy (SEM), Raman and fourier transform infrared (FTIR) spectroscopy. Field emission (FE) studies of PGO, PRGO, PGNR emitters were performed at the base pressure of 1x10(-8) mbar in planar `diode' configuration. Onset and threshold field values corresponding to emission current densities of 1 and 100 mu A/cm(2) are observed to be 1.5 and 2.3V/mu m for PGO, 1.4 and 2.2 V/mu m for PRGO and lowest for PGNR as 0.9 and 1.2V/mu m, respectively. The maximum emission current density of 2.5 mA/cm(2) drawn for PGO at the applied electric field of 3.2V/mu m, 1.2 mA/cm(2) at 3.6V/mu m from the PRGO and 8 mA/cm(2) at the field of 2.2 V/mu m from the PGNR emitters. An emission current versus time (I-t) plot shows stable emission behavior for the preset current values.
Keywords: field emission; FTIR; polypyrrole; Raman

Field emission properties of highly ordered low-aspect ratio carbon nanocup arrays - Gupta, Bipin Kumar; Kedawat, Garima; Kumar, Pawan; Singh, Satbir; Suryawanshi, Sachin R.; Agrawal, Neetu; Gupta, Govind; Kim, Ah Ra; Gupta, R. K.; More, Mahendra A.; Late, Dattatray J.; Hahm, Myung Gwan (RSC Advances, 2016)
Herein, we design and develop a field emission device utilizing highly porous carbon nanocup (CNC) films. These three-dimensional (3D) low-aspect ratio CNC structures were fabricated by a combination of anodization and chemical vapor deposition techniques. The low turn-on fields of 2.30 V mu m(-1) were observed to draw an emission current density of 1 mu A cm(-2) and a maximum emission current density of similar to 1.802 mA cm(-2) drawn at an applied field of similar to 4.20 V mu m(-1). The enhanced field emission behavior observed from the CNC films is attributed to an excellent field enhancement factor of 1645. The observed field emission properties of CNC arrays are attributed to a synergistic combination of high aspect ratio, nano-sized radius of curvature, highly organized distribution of the emitters over the whole area of specimen and lower screening effect of the CNC arrays. These observations shed light on the effect of the stacking carbon layers of CNC on their electronic properties and open up possibilities to integrate new morphologies of graphitic carbon in nanotechnology applications. Thus, the low turn on field, high emission current density and better emission current stability enable CNC based future field emission applications.

Graphene oxide sheathed ZIF-8 microcrystals: engineered precursors of nitrogen-doped porous carbon for efficient oxygen reduction reaction (ORR) electrocatalysis - Thomas, Minju; Illathvalappi, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, Abdul Azeez Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (ACS Applied Materials & Interfaces, 2016)
Nitrogen containing mesoporous carbon obtained by the pyrolysis of graphene oxide (GO) wrapped ZIF-8 (Zeolitic Imidazolate Frameworks-8) micro crystals is demonstrated to be an efficient catalyst for the oxygen reduction reaction (ORR). ZIF-8 synthesis in the presence of GO sheets helped to realize layers of graphene oxide over ZIF-8 microcrystals and the sphere-like structures thus obtained, on heat treatment, transformed to highly porous carbon with a nitrogen content of about 6.12% and surface area of 502 m(2)/g. These catalysts with a typical micromeso porous architecture exhibited an onset potential of 0.88Vvs RHE in a four electron pathway and also demonstrated superior durability in alkaline medium compared to that of the commercial Pt/C catalyst. The N-doped porous carbon derived from GO sheathed ZIF-8 core shell structures could therefore be employed as an efficient electrocatalyst for fuel cell applications.
Keywords: alkaline fuel cell; graphene oxide; N-doped carbon; oxygen reduction reaction; porous carbon; ZIF-8

Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions (vol 5, pg 1251, 2015) - Hussain, Najrul; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (Catalysis Science & Technology, 2016)
Correction for ‘Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions’ by Najrul Hussain et al., Catal. Sci. Technol., 2015, 5, 1251–1260.

Identification of noreremophilane-based inhibitors of angiogenesis using zebrafish assays - Muthukumarasamy, Kalai Mangai; Handore, Kishor L.; Kakade, Dipti N.; Shinde, Madhuri V.; Ranjan, Shashi; Kumar, Naveen; Sehrawat, Seema; Sachidanandan, Chetana; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2016)

Immobilization of pectinase on reusable polymer support for clarification of apple juice - Rajdeo, Kishor; Harini, Tirunagari; Lavanya, Kuna; Fadnavis, Nitin W. (Food and Bioproducts Processing, 2016)
Pectinase (E.C.3.2.1.15) was successfully immobilized on recyclable polymer matrix. The immobilization matrix was prepared by reaction of polyethyleneimine (mol. wt. 70,000) with epoxy-activated acrylate copolymer DILBEAD-VWR. The enzyme pectinase was first adsorbed on the polymer at pH 7.0 via ion exchange and then stabilized by crosslinking with dextran aldehyde. While the free enzyme shows a pH-optimum of 5.0, the immobilized enzyme exhibited high level of activity in a broad pH range of pH 3.0-7.0. Although the thermal stability of free and immobilized enzymes was similar, at room temperature, the immobilized enzyme could be recycled more than 10 times with loss of less than 5% of its activity during clarification of apple juice. On the eventual loss of enzyme activity, the immobilized enzyme and dextran aldehyde can be easily removed from the polymer by a simple treatment with 1N HCl and the polymer can be reused for immobilization of a fresh batch of enzyme. This support also can be reused several times, making the process economically attractive. The properties of apple juice treated with immobilized enzyme were similar to those of that treated with free pectinase. (C) 2016 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Apple juice; Dextran aldehyde; Immobilization; Pectinase; Polyethyleneimine; Polymer

In situ electrochemical transformation of Ni3S2 and Ni3S2-Ni from sheets to nanodisks: towards efficient electrocatalysis for hydrogen evolution reaction (HER) - Busupalli, Balanagulu; Battu, Shateesh; Haram, Santosh K.; Bhagavatula L. V. Prasad (Chemistryselect, 2016)
Transition metal sulphides have been viewed as alternatives to platinum based electrocatalysts for HER. Herein, we report the preparation of Ni3S2 in conjunction with Ni in a novel nanosheet morphology and verified its performance for HER. During cyclic polarization, exotic morphological transformation of Ni-3 S-2-Ni from nanosheets to nanodisks has been noted. This change is accompanied with initial increase in over-potential that passed through maxima (similar to 100mV above the starting potential) and decreased to similar to 50mV below the starting value. Enhanced electrocatalytic activity due to the morphological changes from sheets to nanodisks has been attributed to the formation of more number of exposed edge-planes known to promote HER. Kinetic analysis based on Tafel slope displayed by this composite is comparable to that of Pt based catalysts.

In vitro and ex vivo antitubercular activity of diarylheptanoids from the rhizomes of alpinia officinarum hance - Honmore, Varsha S.; Rojatkar, Supada R.; Nawale, Laxman U.; Arkile, Manisha A.; Khedkar, Vijay M.; Natu, Arun D.; Sarkar, Dhiman (Natural Product Research, 2016)
Phytochemical investigation of methanol extract of the rhizomes of Alpinia officinarum Hance afforded four known diarylheptanoids 1,7-diphenylhept-4-en-3-one (1), 5-hydroxy-1,7-diphenyl-3-heptanone (2), 5-hydroxy-7-(4 ''-hydroxy-3 ''-methoxyphenyl)-1-phenyl-3-heptanone (3), and 7-(4 ''-hydroxy-3 ''-methoxyphenyl)-1-phenyl heptan-3-one (4).The acetate derivative of (4), 7-(4 ''-actetate-3 ''-methoxy phenyl)-1-phenyl heptan-3-one (5), was prepared. These diarylheptanoids exhibited promising in vitro and ex vivo antitubercular activity for the first time against dormant Mycobacterium tuberculosis H37Ra with the IC50 values between 0.3447.69 and 0.1322.91 mu M, respectively. All compounds showed comparable activity against Mycobacterium bovis BCG (dormant phage) and did not show any activity against two gram + ve and two gram -ve bacterial strains. These compounds were also weakly cytotoxic up to 300 mu M against three human cancer cell lines THP-1, Panc-1 and A549.

Interplaying intrinsic and extrinsic proton conductivities in covalent organic frameworks - Chandra, Suman; Kundu, Tanay; Dey, Kaushik; Addicoat, Matthew A.; Heine, Thomas; Banerjee, Rahul (Chemistry of Materials, 2016)
A sulfonic-acid-based covalent organic framework (TpPa-SO3H) has been synthesized that exhibits intrinsic proton conductivity under anhydrous conditions. The sulfonic acid groups are aligned on the two-dimensional (2D) layers at periodic intervals and promote the proton hopping inside the hexagonal one-dimensional channel. The intrinsic proton conductivity of TpPa-SO3H was measured as 1.7 X 10(-5) S cm(-1) at 120 degrees C under anhydrous conditions. To enhance the proton conductivity, we have synthesized a hybrid COF TpPa(SO3H-Py) by a ligand-based solid-solution approach that contains sulfonic acid as the acidic site, as well as pyridine as the basic site, in order to immobilize acidic proton carrier molecules. Impregnation of phytic acid molecules inside the framework increases the anhydrous proton conductivity up to 5 x 10(-4) S cm(-1) at 120 degrees C. Such an approach highlights the advantage and first-time use of hybrid COF for interplaying intrinsic to extrinsic proton conductivity.

Isolates of alpinia officinarum hance as COX-2 inhibitors: evidence from anti-inflammatory, antioxidant and molecular docking studies - Honmore, Varsha S.; Kandhare, Amit D.; Kadam, Parag P.; Khedkar, Vijay M.; Sarkar, Dhiman; Bodhankar, Subhash L.; Zanwar, Anand A.; Rojatkar, Supada R.; Natu, Arun D. (International Immunopharmacology, 2016)
Background: Inflammation triggered by oxidative stress can cause various ailments, such as cancer, rheumatoid arthritis, asthma, diabetes etc. In the last few years, there has been a renewed interest in studying the antioxidant and anti-inflammatory action of plant constituents such as flavonoids and diarylheptanoids. Aim: To evaluate the antioxidant, anti-inflammatory activity and the total phenolic content of isolated compounds from Alpinia officinarum rhizomes. Furthermore, molecular docking was performed to study the binding mode of these compounds into the active site of cyclooxygenase-2 (COX -2). Methods: A. officinarum rhizomes were extracted by maceration, using methanol. This extract was further fractionated by partitioning with hexane, chloroform and ethyl acetate and these fractions on further purification resulted in isolation of five pure compounds. Characterization was carried out by using H-1 NMR, C-13 NMR and MS. They were further evaluated for antioxidant and anti-inflammatory activity using carrageenan-induced paw edema model in rats. Molecular docking study was performed using Glide module integrated in Schrodinger molecular modeling software. Results: The compounds were identified as 1,7-diphenylhept-4-en-3-one (1), 5-hydroxy-1,7-diphenyl-3-heptanone (2), 3,5,7-trihydroxyflavone (Galangin, 3), 3,5,7-trihydroxy-4'-methoxyflavone (Kaempferide, 4) and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone (5). The compound-3 and compound-5 (10 mg/kg) showed significant (p < 0.001) antioxidant and anti-inflammatory potential. Moreover, total phenolic content was detected as 72.96 mg and 51.18 mg gallic acid equivalent respectively. All the five isolates were found to be good binders with COX-2 (average docking score -9.03). Conclusions: Galangin and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone exhibited anti-inflammatory and in-vitro antioxidant activity which may be due to presence of phenolic content in it. The molecular docking study revealed that these compounds have affinity towards COX-2 active site which can further be explored as selective COX-2 inhibitors. The results obtained in this work justify the use of A. officinarum in the treatment of inflammatory disorders like rheumatoid arthritis and inflammatory bowel diseases. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: 5-Hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone; Alpinia officinarum; Anti-inflammatory; Antioxidant; COX-2 inhibitors; Galangin

Isolation and virtual screening of antimicrobial prodigiosin pigment from oxalotrophic Serratia marcescens OX_R strain - Suryavanshi, M. V.; Waghmode, S. R.; Bharti, N.; Choudhari, P. B.; Hingamire, T. B.; Shouche, Y. S. (Journal of Applied Pharmaceutical Science, 2016)
Prodigiosin a multifaceted secondary metabolite produced by Serratia spp. having great potential as a pharmaceutical. In the present study we demonstrate that oxalate supplementation in peptone glycerol production media increased organoleptic characters and yield of prodigiosin pigment extracted from oxalotrophic Serratia marcescens OX_R isolated from Indian bat guano sample. The pigment was demonstrated in-vitro as an antibacterial agent against common opportunistic skin surface pathogen Staphylococcus aureus NCIM 5021 strain as killing activity by agar well diffusion method. The docking analysis and pharmacophore modelling indicated that the probable mechanism of action of the prodigiosin was against Staphylococcus aureus DNA gyrase protein. The pigment was also found to efficiently dye both cotton and latex polymer. In summary, we describe here an oxalotrophic Serratia marcescens which may serve as a potent and economical resource of prodigiosin which owing to its dyeing and anti-bacterial activities finds future avenues to be developed as dressing material for nosocomial subjects or burn victim patients.

Micropropagation of Semecarpus anacardium L. from mature tree-derived nodal explants - Panda, B. M.; Mehta, U. J.; Hazra, S. (Plant Biosystems, 2016)
A protocol was established for micropropagation of Semecarpus anacardium L. from mature tree-derived twigs. Sixty percent of aseptic cultures were obtained by surface sterilization with Bavistin, liquid detergent, and cefotaxime. Elongated twigs collected before flowering were optimum for in vitro culture initiation. Meristematic activity was triggered at all concentrations of thidiazuron (TDZ) incorporated into Woody Plant Medium. TDZ suppressed elongation of axillary buds, resulting into swollen meristems and upon its elimination multiple shoot primordia formation and differentiation were noted. Differentiation and shoot elongation were slower in explants pre-cultured with higher concentrations of TDZ. Swollen axillary meristems pre-cultured on TDZ (9.08 and 13.62 mu M) failed to differentiate, whereas TDZ at 2.27 mu M was optimal for shoot differentiation and elongation. Multiple bud induction was favored by 4.45 mu M of TDZ. Differentiation of multiple shoot primordia by repeated subculturing on growth regulator-free medium and rooting was 100% in filter-paper supported half-strength liquid medium containing 7.38mM IBA. Rooting was 90% in shoots placed directly in half-strength liquid medium with 2.46 mu M IBA. Rooted plantlets hardened in soil: sand mixture (1:1) were transferred to green house. Genetic uniformity of in vitro raised clones with mother plant was confirmed by Inter-Simple Sequence Repeat markers.

Modulation of charge carrier mobility by side-chain engineering of bi(thienylenevinylene)thiophene containing PPE-PPVs - Jadhav, Rupali R.; Camaioni, Nadia; Oppelt, Kerstin; Tinti, Francesca; Gazzano, Massimo; Fattori, Valeria; Wadgaonkar, Prakash P.; Rathgeber, Silke; Hoppe, Harald; Egbe, Daniel A. M. (RSC Advances, 2016)
Four 2-dimensional conjugated poly(p-phenylene-ethynylene)-alt-poly(p-phenylene-vinylene) polymers containing a lateral bi(thienylenevinylene)thiophene unit (BTE-PVs) were synthesised and characterised. The investigated polymers share the same conjugated structure, but differ in the anchoring positions of solubilising linear octyloxy/branched 2-ethylhexyloxy side-chains. UV-vis spectra of the polymers in dilute chloroform solutions and as thin films were studied. X-Ray diffraction patterns as well as the bulk charge transport of polymer films cast from chlorobenzene solutions were also investigated. A dramatic effect of the solubilising side-chains on the charge carrier mobility of BTE-PV films was observed, with bulk hole mobility values ranging between 1.3 x 10(-5) cm(2) V-1 s(-1) and 2.2 x 10(-2) cm(2) V-1 s(-1), which is not ascribable to evident structural variations of the polymer films. It is shown that the combination of linear octyloxy and branched 2-ethylhexyloxy side-chains is favorable for the charge transport properties of BTE-PVs, compared to the incorporation of only linear or only branched side-chains.

Molecular interaction of selected phytochemicals under the charged environment of Plasmodium falciparum chloroquine resistance transporter (PfCRT) model - Patel, Saumya K.; Khedkar, Vijay M.; Jha, Prakash C.; Jasrai, Yogesh T.; Pandya, Himanshu A.; George, Linz-Buoy; Highland, Hyacinth N.; Skelton, Adam A. (Journal of Biomolecular Structure & Dynamics, 2016)
Phytochemicals of Catharanthus roseus Linn. and Tylophora indica have been known for their inhibition of malarial parasite, Plasmodium falciparum in cell culture. Resistance to chloroquine (CQ), a widely used antimalarial drug, is due to the CQ resistance transporter (CRT) system. The present study deals with computational modeling of Plasmodium falciparum chloroquine resistance transporter (PfCRT) protein and development of charged environment to mimic a condition of resistance. The model of PfCRT was developed using Protein homology/analogy engine (PHYRE ver 0.2) and was validated based on the results obtained using PSI-PRED. Subsequently, molecular interactions of selected phytochemicals extracted from C. roseus Linn. and T. indica were studied using multiple-iterated genetic algorithm-based docking protocol in order to investigate the translocation of these legends across the PfCRT protein. Further, molecular dynamics studies exhibiting interaction energy estimates of these compounds within the active site of the protein showed that compounds are more selective toward PfCRT. Clusters of conformations with the free energy of binding were estimated which clearly demonstrated the potential channel and by this means the translocation across the PfCRT is anticipated.
Keywords: homology modeling; molecular dynamics; Plasmodium falciparum chloroquine; resistance transporter model

Next-generation ammonia pretreatment enhances cellulosic biofuel production - Sousa, Leonardo da Costa; Jin, Mingjie; Chundawat, Shishir P. S.; Bokade, Vijay V.; Tang, Xiaoyu; Azarpira, Ali; Lu, Fachuang; Avci, Utku; Humpula, James; Uppugundla, Nirmal; Gunawan, Christa; Pattathil, Sivakumar; et al. (Energy & Environmental Science, 2016)
A new liquid ammonia pretreatment methodology called Extractive Ammonia (EA) was developed to simultaneously convert native crystalline cellulose I-beta (CI) to a highly digestible cellulose IIII (CIII) allomorph and selectively extract up to B45% of the lignin from lignocellulosic biomass with near-quantitative retention of all polysaccharides. EA pretreated corn stover yielded a higher fermentable sugar yield compared to the older Ammonia Fiber Expansion (AFEX) process while using 60% lower enzyme loading. The EA process preserves extracted lignin functionalities, offering the potential to co-produce lignin-derived fuels and chemicals in the biorefinery. The single-stage EA fractionation process achieves high biofuel yields (18.2 kg ethanol per 100 kg untreated corn stover, dry weight basis), comparable to those achieved using ionic liquid pretreatments. The EA process achieves these ethanol yields at industrially-relevant conditions using low enzyme loading (7.5 mg protein per g glucan) and high solids loading (8% glucan, w/v).

Oxidation of linezolid by permanganate in acidic medium: Pd(II) catalysis, kinetics and pathways - Kulkarni, Raviraj M.; Hanagadakar, Manjunath S.; Malladi, Ramesh S.; Santhakumari, B.; Nandibewoor, Sharanappa T. (Progress in Reaction Kinetics and Mechanism, 2016)
The uncatalysed and Pd(II)-catalysed oxidation of linezolid (LNZ) by permanganate (PMGT) in acidic medium was carried out in the pH range from 3.0 to 6.0. The second order rate constants were found to decrease with increase in pH. The apparent second order rate constants for the uncatalysed reaction were, for example, k `'(app)= 6.32 dm(3) mol(-1) at pH 3.0 and k `'(app). = 2.64 dm(3) mol(-1) s(-1) at pH 6.0 and at 25 +/- 0.2 degrees C and for the Pd(II)-catalysed reaction the total apparent second order rate constants were k `'(app) = 75.5 dm(3) mol(-1) s(-1) at pH 3.0 and k `'(app). = 45.66 dm(3) mol(-1) s(-1) at pH 6.0 and at 25 +/- 0.2 degrees C. The rate constant of the Pd(II)-catalysed reaction was thus ten times higher than for the uncatalysed reaction. The oxidation products of the reaction were identified using high resolution LC-MS. The reaction progresses via formation of a Pd-LNZ complex, which reacts with acidic PMGT to form an intermediate compound, which then decomposes to give oxidised products. The dependence of the rate of reaction on various parameters, such as pH, temperature, [LNZ], [PMGT], [Pd(II)], dielectric constant and ionic strength were studied and activation parameters for the reaction were evaluated and discussed.

Pick and choose the spectroscopic method to calibrate the local electric field inside proteins - Haldar, Tapas; Kashid, Somnath M.; Deb, Pranab; Kesh, Sandeep; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2016)
Electrostatic interactions in proteins play a crucial role in determining the structure function relation in biomolecules. In recent years, fluorescent probes have been extensively employed to interrogate the polarity in biological cavities through dielectric constants or semiempirical polarity scales. A choice of multiple spectroscopic methods, not limited by fluorophores, along with a molecular level description of electrostatics involving solute-solvent interactions, would allow more flexibility to pick and choose the experimental technique to determine the local electrostatics within protein interiors. In this work we report that ultraviolet/visible-absorption, infrared-absorption, or C-13 NMR can be used to calibrate the local electric field in both hydrogen bonded and non-hydrogen bonded protein environments. The local electric field at the binding site of a serum protein has been determined using the absorption wavelength as well as the carbonyl stretching frequency of its natural steroid substrate, testosterone. Excellent agreement is observed in the results obtained from two independent spectroscopic techniques.

Polyhedral oligomeric silsesquioxane-containing thiol-ene fibers with tunable thermal and mechanical properties - Fang, Yichen; Ha, Heonjoo; Shanmuganathan, Kadhiravan; Ellison, Christopher J. (ACS Applied Materials & Interfaces, 2016)
Polyhedral oligomeric silsesquioxanes (POSS) are versatile inorganic-organic hybrid building blocks that have potential applications as reinforcement nanofillers, thermal stabilizers, and catalyst supports for metal nano particles. However, fabrication of fibrous materials with high POSS content has been a challenge because of the aggregation and solubility limits of POSS units. In this paper, we describe a robust and environmentally friendly fabrication approach of inorganic-organic hybrid POSS fibers by integrating UV initiated thiol-ene polymerization and centrifugal fiber spinning. The use of monomeric liquids in this approach not only reduces the consumption of heat energy and solvent, but it also promotes homogeneous mixing of organic and inorganic components that allows integration of large amount of POSS (up to 80 wt %) into the polymer network. The POSS containing thiol-ene fibers exhibited enhanced thermomechanical properties compared to purely organic analogs as revealed by substantial increases in residual weight and a factor of 4 increase in modulus after thermal treatment at 1000 degrees C. This simple fabrication approach combined with the tunability in fiber properties afforded by tailoring monomer composition make POSS containing thiol-ene fibers attractive candidates for catalyst supports and filtration media, particularly in high-temperature and harsh environments.
Keywords: cross-linked fiber; enhanced thermomechanical properties; inorganic-organic hybrid fiber; POSS; reactive centrifugal spinning; thiol-ene photopolymerization

PolyHIPE derived freestanding 3D carbon foam for cobalt hydroxide nanorods based highperformance supercapacitor - Patil, Umakant M.; Ghorpade, Ravindra V.; Nam, Min Sik; Nalawade, Archana C.; Lee, Sangrae; Han, Haksoo; Jun, Seong Chan (Scientific Reports, 2016)
The current paper describes enhanced electrochemical capacitive performance of chemically grown Cobalt hydroxide (Co(OH)(2)) nanorods (NRs) decorated porous three dimensional graphitic carbon foam (Co(OH)(2)/3D GCF) as a supercapacitor electrode. Freestanding 3D porous GCF is prepared by carbonizing, high internal phase emulsion (HIPE) polymerized styrene and divinylbenzene. The PolyHIPE was sulfonated and carbonized at temperature up to 850 degrees C to obtain graphitic 3D carbon foam with high surface area (389 m(2) g(-1)) having open voids (14 mu m) interconnected by windows (4 mu m) in monolithic form. Moreover, entangled Co(OH)(2) NRs are anchored on 3D GCF electrodes by using a facile chemical bath deposition (CBD) method. The wide porous structure with high specific surface area (520 m(2) g(-1)) access offered by the interconnected 3D GCF along with Co(OH)(2) NRs morphology, displays ultrahigh specific capacitance, specific energy and power. The Co(OH)(2)/3D GCF electrode exhibits maximum specific capacitance about similar to 1235 F g(-1) at similar to 1 Ag-1 charge-discharge current density, in 1 M aqueous KOH solution. These results endorse potential applicability of Co(OH)(2)/3D GCF electrode in supercapacitors and signifies that, the porous GCF is a proficient 3D freestanding framework for loading pseudocapacitive nanostructured materials.

Protein-dependent membrane interaction of a partially disordered protein complex with oleic acid : Implications for cancer lipidomics - Chaudhuri, Arunima; Prasanna, Xavier; Agiru, Priyanka; Chakraborty, Hirak; Rydstrom, Anna; Ho, James C. S.; Svanborg, Catharina; Sengupta, Durba; Chattopadhyay, Amitabha (Scientific Reports, 2016)
Bovine α-lactalbumin (BLA) forms cytotoxic complexes with oleic acid (OA) that perturbs tumor cell membranes, but molecular determinants of these membrane-interactions remain poorly understood. Here, we aim to obtain molecular insights into the interaction of BLA/BLA-OA complex with model membranes. We characterized the folding state of BLA-OA complex using tryptophan fluorescence and resolved residue-specific interactions of BLA with OA using molecular dynamics simulation. We integrated membrane-binding data using a voltage-sensitive probe and molecular dynamics (MD) to demonstrate the preferential interaction of the BLA-OA complex with negatively charged membranes. We identified amino acid residues of BLA and BLA-OA complex as determinants of these membrane interactions using MD, functionally corroborated by uptake of the corresponding α-LA peptides across tumor cell membranes. The results suggest that the α-LA component of these cytotoxic complexes confers specificity for tumor cell membranes through protein interactions that are maintained even in the lipid complex, in the presence of OA.

Radical beckmann rearrangement and its application in the formal total synthesis of antimalarial natural product isocryptolepine via C-H activation - Mahajan, Pankaj S.; Humne, Vivek T.; Tanpure, Subhash D.; Mhaske, Santosh B. (Organic Letters, 2016)
The Beckmann rearrangement of ketoximes, mediated by ammonium persulfate-dimethyl sulfoxide as a reagent, has been achieved under neutral conditions. Based on the radical trapping and O-18-labeling experiments, the transformation follows a mechanism involving a radical pathway. The scope and generality of the developed protocol has been demonstrated by 19 examples. The developed protocol and Pd-catalyzed intramolecular double C-H activation were used as key steps in the formal total synthesis of antimalarial natural product isocryptolepine.

Reductive cyclization of levulinic acid to gamma-valerolactone over non-noble bimetallic nanocomposite - Kadu, Brijesh S.; Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V.; Chikate, Rajeev C. (Industrial & Engineering Chemistry Research, 2016)
Bimetallic nanoparticles have diverse applications in catalytic processes owing to the differences in individual properties that contribute to their increased catalytic activity. To further improve the efficiency, they are dispersed in an inert support that enhances the catalytic activity toward organic transformations. In this study, we report simple, facile, and cost-effective chemical route for the fabrication of nanocomposites with Fe-Ni bimetallic nanoparticles supported on montmorillonite (MMT) possessing variation in the Fe and Ni content. These composites are characterized with X-ray diffraction, transmission electron microscopy surface area, and NH3-TPD. Fe Ni bimetallic nanoparticles are well-dispersed within MMT structure having particle sizes of about 30-40 nm. Among various compositions of Fe-Ni/MMT catalysts, composite with 25% Fe and 25% Ni exhibits >99% LA conversion with 98% selectivity to GVL within 1 h. IPA is found to be better solvent for levulinic acid (LA) to gamma-valerolactone (GVL) conversion, while substantial leaching of iron takes place when water is used as a solvent. It is observed that bimetallic sites are responsible for reduction of LA, while strong acidic sites of MMT are favoring subsequent cyclization to GVL. XPS analysis of fresh and reused Fe-Ni/MMT composites suggest that the catalyst surface does not undergo any chemical change during successive cycles, and the catalytic activity is retained up to six cycles. The plausible mechanism for LA to GVL conversion involves reductive cyclization processes through formation of levulinate ester that undergoes lactonization due to synergism in bimetallic nanoparticles and MMT clay.

Ru-TiO2 semiconducting nanoparticles for the photo-catalytic degradation of bromothymol blue - Kulkarni, R. M.; Malladi, R. S.; Hanagadakar, M. S.; Doddamani, M. R.; Santhakumari, B.; Kulkarni, S. D. (Journal of Materials Science-Materials in Electronics, 2016)
Photo-catalytic degradation of bromothymol blue (BTB) in an aqueous medium by Ru-TiO2 using UVC (254 nm) irradiation was investigated for a pH range of 4.0-8.0. The liquid impregnation method was used to synthesize 0.2, 0.4 and 0.8 % ruthenium doped TiO2 (Ru-TiO2) nanoparticles. The characterizations of resulting nanoparticles were done using X-ray diffraction, scanning electron microscopy, fourier transform infrared spectroscopy, transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy analysis. The crystallite sizes of doped and undoped nanoparticles were determined from X-ray diffraction spectra using Scherrer equation. The average crystallite size of undoped TiO2 was found to be 17.00 nm, whereas the crystallite sizes of 0.2, 0.4 and 0.8 % Ru-TiO2 were 16.67, 15.70 and 14.40 nm respectively. The TEM images confirm the particle sizes to be 10-40 nm. Pseudo-first order rate constants (k(obs)) determined were found to decrease with increase in pH. The effect of BTB Concentration, catalyst dosage, a percentage of doping of photo catalyst, pH and UV light intensity of BTB on the degradation rate were also examined.

Single pot transfer hydrogenation and aldolization of furfural over metal oxide catalysts - Biradar, Narayan S.; Hengne, Amol M.; Sakate, S. S.; Swami, R. K.; Rode, Chandrashekhar V. (Catalysis Letters, 2016)
One pot catalytic transfer hydrogenation (CTH) of furfural to furfuryl alcohol (FAL) by using hydrogen producing alcohols and simultaneous aldolization of carbonyl compounds produced during CTH, with furfural was achieved over non-noble metal oxides with bifunctional sites. Basic sites of MgO responsible for abstraction of proton showed complete conversion of furfural to give FAL and C8 monomer in a ratio of 3:1, respectively, the later altered to 1:1 by incorporating Al into MgO. Catalyst stability was established by its four cycles study. [GRAPHICS]
Keywords: Aldol; furfural; Furfuryl alcohol; Metal oxides; transfer hydrogenation

Solution-phase synthesis of the macrocyclic core of teixobactin - Dhara, Santu; Gunjal, Vidya B.; Handore, Kishor L.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
Towards the total chemical synthesis of the exceptionally potent antibiotic teixobactin, we synthesized the macrocyclic core of a natural product by using a solution-phase approach. The gramscale synthesis of L-allo-enduracididine and Shiina macrolactonization are highlights of the present disclosure.

Supramolecular metallogel that imparts self-healing properties to other gel networks - Feldner, Tobias; Haering, Marleen; Saha, Subhadeep; Esquena, Jordi; Banerjee, Rahul; Diaz, David Diaz (Chemistry of Materials, 2016)
A unique proton conductive and moldable supramolecular metallogel (CuA-Ox-gel) made upon mixing at room temperature well-defined stock solutions of Cu(OAc)(2). H2O and oxalic acid dehydrate was found to have self-healing properties. Remarkably, the system also displayed an unprecedented ability to impart self-healing properties to other gel networks lacking this capacity. A self-healed CuA-Ox metallogel was found to have essentially the same nanofibrillar morphology, thermal stability, rheological properties, and conductivity as the freshly prepared sample. The discovery also allowed the fabrication of self-healing conductive composites containing conductive carbonaceous materials. Overall, this work serves as a proof of concept for the transfer of self-healing properties between completely different gel networks.

Synthesis and study of calixarene-doped polypyrrole-TiO2/ZnO composites: antimicrobial activity and electrochemical sensors - Waghmode, Babasaheb J.; Husain, Zahid; Joshi, Meenal; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (Journal of Polymer Research, 2016)
The present communication describes the synthesis of an electroactive nanocomposite of calixarene- doped polypyrrole ( PPY) containing an oxide of Ti/ Zn. The additive TiO2/ ZnO serves as an oxidizing agent for the polymerization, thus avoiding the use of hazardous organic solvents while calixarene doping stabilizes the polymer. The materials synthesized herein were characterized by UV- visible spectroscopy, FT- IR spectroscopy, scanning electron microscopy ( SEM), transmission electron microscopy ( TEM), energy- dispersive X- ray spectroscopy ( EDX), X- ray photoelectron spectroscopy ( XPS), and cyclic voltammetry ( CV) of synthesized nanocomposites. It was revealed that the resulting calixarene- doped polypyrrole- TiO2/ ZnO nanocomposite has ( 1) long- time stability, ( 2) significant electrochemical activity for sensing formaldehyde, and ( 3) good antimicrobial activity.

Thermal stimuli-responsive behavior of pyrene end-functionalized PDMS through tunable P–P interactions - Ha, Heonjoo; Shanmuganathan, Kadhiravan; Fei, Yunping; Ellison, Christopher J. (Journal of Polymer Science Part B-Polymer Physics, 2016)
Pyrene end-functionalized, telechelic poly(dimethyl siloxane) (PDMS) materials were synthesized and their response to different thermal stimuli was evaluated. The incorporation of pyrene end groups introduces strong pi-pi interactions that facilitated a broad range of thermally responsive properties, in some circumstances forming pyrene nanocrystals that serve as physical crosslinks leading to elastic materials. By synthesizing different chain lengths, samples exhibiting a 7 orders of magnitude change in storage modulus in response to thermal stimuli were produced by modifying only the end-groups (0.6 wt % of all polymer segments). Repeated thermal cycling during rheological experiments revealed that pi-pi interaction and crystallization/melting kinetics of pyrene chain-ends plays a key role in their thermal responsiveness. The properties of these materials were tuned by adding free pyrene, neat PDMS, or graphene oxide (GO) nanoparticles, making them attractive for many applications (e.g., tunable damping materials, heat/light sensors, conductive gels, or light repositionable adhesives). For example, nanocomposites containing 1 wt % GO caused the melting temperature for pyrene crystal domains to more than double, and even induced pyrene end-group crystallization in samples that did not exhibit crystals in neat form. It is hypothesized that these features originate from pi-pi interactions between pyrene ends and GO surfaces. (C) 2015 Wiley Periodicals, Inc.

Total synthesis of (-)-nardoaristolone B - Ople, Rohini S.; Handore, Kishor L.; Kamat, Nidhi S.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
A stereoselective total synthesis of (-)-Nardoaristolone B, a nor-aristolane sesquiterpenoid natural product with an unusual 3/5/6 tricyclic ring system is described. The highlights of the present work includes use of (+)-(R)-Pulegone as a chiral-pool starting material, ring-closing metathesis, allylic oxidation and stereoselective cyclopropanation. In addition, a new analogue of Nardoaristolone B (minor product from the final step) was isolated in pure form and fully characterized with the help of single-crystal X-ray analysis.
Keywords: Chiral pool; cyclopropanation; Nardoaristolone B; Natural products; Total synthesis

Transfer hydrogenation of biomass-derived levulinic acid to gamma-valerolactone over supported Ni catalysts - Hengne, Amol M.; Kadu, Brijesh S.; Biradar, Narayan S.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (RSC Advances, 2016)
A sustainable process of catalytic transfer hydrogenation (CTH) of levulinic acid (LA) to gamma-valerolactone (GVL) was investigated over Ni on various supports (Al2O3, ZnO, MMT and SiO2) in the presence of isopropanol (IPA) as the H-donor. Among these, the montmorillonite (MMT) supported Ni catalyst showed almost complete LA conversion (>99%) and selectivity (>99%) to GVL within 1 h. XRD and XPS results showed that the concentration of the metallic species significantly enhanced (two to four times) in the recovered sample as compared to the freshly prepared Ni/MMT. This was due to the in situ reduction of Ni2+ species present on the catalyst surface, through liberated H-2 under the reaction conditions. The strong acid strength of MMT, evidenced by NH3-TPD and py-IR, facilitated the esterification of LA as well as cyclization to GVL. The conversion-selectivity pattern was found to decrease in the IPA-water mixture while, it remained unchanged in the IPA-acetone mixture. Our catalyst could be efficiently recycled up to five times with consistent CTH activity and selectivity to GVL. The plausible mechanism of LA to GVL conversion involves the formation of a levulinate ester with IPA that favours its simultaneous hydrogenation and cyclization in a spontaneous manner to give GVL and regenerating IPA for sustainability.

Access to fused tricyclic gamma-butyrolactones, a natural product -like scaffold - Kalmode, Hanuman P.; Handore, Kishor L.; Reddy, D. Srinivasa (Journal Of Organic Chemistry, 2017)
Serendipitous findings of an acid mediated skeletal rearrangement of bicydo-beta-ketoester having cyclopropyl ring to access fused tricyclic gamma-butyrolactones has been described. This novel transformation has been optimized to 30 mol% p-toluenesulfonic acid (p-TSA) in toluene using Dean Stark apparatus, where the aldol condensation, cyclopropyl ring opening followed by cyclization took place in a single-pot operation. The resulting tricyclic compounds are interesting chemotype with natural product resemblance and may find useful applications in the future.

Achmatowicz reaction: A versatile tool in bioactive natural products synthesis - Mahajan, Pankaj S.; Humne, Vivek T.; Mhaske, Santosh B. (Current Organic Chemistry, 2017)
Achmatowicz reaction has emerged as an efficient tool in organic synthesis since its discovery in 1971 by Achmatowicz Jr. The original protocol went through several advantageous variations. Biocatalytic and metal catalyzed versions of this reaction are some of the significant achievements, which further enhanced its effectiveness. The pyranone product of the Achmatowicz reaction is a versatile building block for the synthesis of bioactive scaffolds, drugs and natural products. The present review covers the application of the Achmatowicz reaction in the synthesis of natural products and bioactive molecules reported from 1971 to date. It has been divided into seven sections on the basis of the core structures of the natural products synthesized utilizing the Achmatowicz reaction. We believe that this comprehensive review will attract many more organic chemists to explore its utility in organic synthesis, especially in the synthesis of bioactive natural products as well as drugs in their efficient and atom economical synthesis.
Keywords: Achmatowicz reaction; carbohydrates; Furanols; Natural products; pyranones; Total synthesis

Aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups: synthesis and characterization - Bapat, Snehalata P.; Jadhav, Sushilkumar A.; Valsange, Nitin G.; Tawade, Bhausaheb V.; Honkhambe, Pandurang N.; Chavan, Nayaku N.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2017)
A new bisphenol, 1,1-bis-[(4-hydroxyphenyl)-1-(4-phenylsulfonyl) phenyl)] ethane (DPSBP) was synthesized starting from diphenylsulfide and was characterized by spectroscopic methods. DPSBP was polycondensed with isophthalic acid chloride (IPC), terephthalic acid chloride (TPC) and a mixture of IPC and TPC (50: 50 mol%) by phase-transfer catalysed interfacial polymerization method to obtain aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups. A series of copolyesters was also obtained by polycondensation of varying molar proportions of DPSBP and bisphenol-A (BPA) with TPC. (Co) polyesters exhibited inherent viscosities in the range 0.56-1.57 dLg(-1) and number average molecular weights (Mn) were in the range 28,650-80,230 g/mol. Polyesters dissolved readily in common organic solvents such as dichloromethane, chloroform, tetrahydrofuran and aprotic polar solvents such as N-methylpyrrolidone, and N, N-dimethylacetamide. Tough, transparent and flexible films of polyesters could be cast from their chloroform solutions. X-Ray diffraction studies indicated amorphous nature of aromatic polyesters. Polyesters showed T-g values in the range 223-257 degrees C while T-10 values were in the range of 469-484 degrees C indicating their excellent thermal stability.
Keywords: Aromatic polyesters; Bulky pendent group; solubility; thermal stability

Assessing therapeutic potential of molecules: molecular property diagnostic suite for tuberculosis - Gaur, A. S.; Bhardwaj, A.; Sharma, A.; John, L.; Vivek, M. R.; Tripathi, N.; Bharatam, P. V.; Kumar, R.; Janardhan, S.; Mori, A.; Banerji, A.; Lynn, A. M.; et al. (Journal of Chemical Sciences, 2017)
Abstract: Molecular Property Diagnostic Suite (MPDS TB) is a web tool (http://mpds.osdd.net) designed to assist the in silico drug discovery attempts towards Mycobacterium tuberculosis (Mtb). MPDS TB tool has nine modules which are classified into data library (1–3), data processing (4–5) and data analysis (6–9). Module 1 is a repository of literature and related information available on the Mtb. Module 2 deals with the protein target analysis of the chosen disease area. Module 3 is the compound library consisting of 110.31 million unique molecules generated from public domain databases and custom designed search tools. Module 4 contains tools for chemical file format conversions and 2D to 3D coordinate conversions. Module 5 helps in calculating the molecular descriptors. Module 6 specifically handles QSAR model development tools using descriptors generated in the Module 5. Module 7 integrates the AutoDock Vina algorithm for docking, while module 8 provides screening filters. Module 9 provides the necessary visualization tools for both small and large molecules. The workflow-based open source web portal, MPDS TB 1.0.1 can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. Graphical Abstract: SYNOPSIS: A web-based MPDS TB Galaxy tool is developed for assessing therapeutic potential of molecules. MPDS TB is categorized into Data Library, Data Processing and Data Analysis. It can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. [Figure not available: see fulltext.] © 2017, Indian Academy of Sciences.
Keywords: chemical analysis; Chemoinformatics; computational chemistry; Diagnosis; Drug discovery portal; Information analysis; Libraries; Molecular graphics; Molecules; Neglected diseases; Open science; Portals; tuberculosis; Web-based technology; Websites

Catalytic macroporous biohydrogels made of ferritin-encapsulated gold nanoparticles - Kumari, Sushma; Haring, Marleen; Sen Gupta, Sayam; Diaz, David Diaz (Chempluschem, 2017)
Reported is a modular approach for the incorporation and stabilization of gold nanoparticles inside a three-dimensional macroporous hydrogel made of ferritin. The strategy, which involves the dynamic templating of surfactant H-1 domains, demineralization, and remineralization helps to overcome aggregation and degradation issues usually associated with bare-metal-based nanocatalysts. The catalytic activity of the so-synthesized bionanocomposite hydrogel was demonstrated in both nitroaldol (Henry) and nitroreduction model reactions in aqueous solution at room temperature. An interesting synergistic effect between basic residues of the protein and the gold nanoparticles was found in the nitroaldol reaction when carried out in water in the presence of a phase-transfer catalyst. Furthermore, the reduction of 4-nitrophenol and 4-nitroaniline catalyzed by the nanocomposite scaffold in the presence of NaBH4 proceeded significantly faster than that using other known Au- and Ag-based catalysts under similar conditions.

Chitosan intercalated metal organic gel as a green precursor of fe entrenched and fe distributed N-doped mesoporous graphitic carbon for oxygen reduction reaction - Shijina, Kottarathil; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Yamaguchi, Takeo; Anilkumar, Gopinathan M.; Hareesh, U. S.; Sailaja, G. S. (Chemistryselect, 2017)
Herein, we present Metal-Organic Gel intercalated with chitosan, a `green'' precursor for the synthesis of intrinsic N-doped Fe entrenched (CHI-TMA-Fe-CW) and Fe distributed mesoporous graphitic carbon structures (CHI-TMA-Fe-CW-M1) with appreciable Oxygen Reduction Reaction (ORR) activity in alkaline medium. Modulation of the synthetic protocol as a function of reaction kinetics and gelation time while maintaining identical pyrolysis conditions (900 degrees C, flowing N-2 atmosphere) improves the microstructure, surface area and Fe distribution of the graphitic structures (CHI-TMA-Fe-CW-M1). CHI-TMA-Fe-CW has a Fe entrenched graphitic nanocapsule like morphology while Fe distributed mesoporous graphitic carbon sheets, with a specific surface area value of 565 m(2) g(-1) obtained by modulating the synthesis chemistry in CHI-TMA-Fe-CW-M1. The higher percentage of graphitic N in CHI-TMA-Fe-CW-M1 apparent from the XPS data validate that the modified synthetic method favours creation of more graphitic N sites contributing for better catalytic performance. CHI-TMA-Fe-CW-M1 catalyst exhibited comparable electrocatalytic activity with that of the commercially available Pt/C via an efficient four-electron-dominant ORR pathway with a positive onset potential value of 0.925 V vs RHE. Good durability of CHI-TMA-Fe-CW-M1 after 5000 cycles further confirm the prospects of MOG-chitosan and the feasibility to be used as a potential catalyst for ORR.
Keywords: electrocatalyst; fuel cell; Metal-Organic-Gel; oxygen reduction reaction

Direct C-N bond formation in an in situ ligand transformation reaction and formation of polymeric 1D cadmium(II) complexes with end-to-end bridging thiocyanate or selenocyanate ions: Synthesis, structures and theoretical studies - Sadhu, Mehul H.; Solanki, Ankita; Kundu, T.; Hingu, Vinayak; Ganguly, B.; Kumar, Sujit B. (Polyhedron, 2017)
Two new one-dimensional polymeric thiocyanato and selenocyanato bridged cadmium(II) complexes [Cd(dpip)(mu(1,3)-SCN)(2)](n) and [Cd(dpip)(mu(1,3)-SeCN)(2)](n), where dpip = 3,5-dimethy1-14(3-phenylimidazolidin-ly1)-methyl)-1H-pyrazole have been synthesized and characterized by elemental analysis, IR, 1H NMR and single crystal X-ray diffraction studies. The bidentate N-2-coordinated ligand dpip is formed from N-4-coor-dinated tetradentate ligand N,N-bis(3,5-dimethy1-1H-pyrazol-1-yOmethyl-N-2-phenylethane-1,2-diamine (bdpab) due to unusual transformation, removing one pyrazole group and formation of saturated imidazole ring during in situ complexation reaction. The 1D structures of the two complexes have been confirmed by single crystal X-ray diffraction studies and both NCS- and NCSe- act as end -to -end (-1,3) bridging ligands. The coordination environment around the cadmium center in the complexes are CdN4S2 and CdN4Se2, respectively and each cadmium(II) center has distorted octahedral geometry. The distortion in the molecules are due to two unequal Cd-N (organic ligand dpip) bond lengths and small bite angel of the unsymmetrical organic ligand. The DFT calculations performed with cadmium(II) complexes [Cd (dpip)(mu(1,3)-SCN)(2)](n) and [Cd(dpip)(mu(1,3)-SeCN)(2)](n) corroborated the observed crystal structures and the structural parameter were found to be in good agreement in both calculated and X-ray geometries. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: 1d Chain; Cd(Ii) Complexes; Cobalt(Ii); coordination polymers; Crystal-structure; Dft Pyrazole Based Ligand; Dinuclear; End-to-end Bridge; Infrared-spectra; Magnetic-properties; Metal; Ncs/Secn Ion; Nickel(Ii); Nitrogen Single Bond

Direct production of furfural in one-pot fashion from raw biomass using bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Hossain, Shahriar A.; Islam, Tofazzal; Alamri, Hatem R.; Alothman, Zeid A.; Yamauchi, Yusuke; Dhepe, Paresh L.; Wu, Kevin C. W. (Scientific Reports, 2017)
The conversion of raw biomass into C5-sugars and furfural was demonstrated with the one-pot method using Bronsted acidic ionic liquids (BAILs) without any mineral acids or metal halides. Various BAILs were synthesized and characterized using NMR, FT-IR, TGA, and CHNS microanalysis and were used as the catalyst for raw biomass conversion. The remarkably high yield (i.e. 88%) of C5 sugars from bagasse can be obtained using 1-methyl-3(3-sulfopropyl)-imidazolium hydrogen sulfate ([C3SO3HMIM][HSO4]) BAIL catalyst in a water medium. Similarly, the [C3SO3HMIM][HSO4] BAIL also converts the bagasse into furfural with very high yield (73%) in one-pot method using a water/toluene biphasic solvent system.

Draft genome sequence of lactobacillus plantarum strains E2C2 and E2C5 isolated from human stool culture - Suryavanshi, Mangesh V.; Paul, Dhiraj; Doijad, Swapnil P.; Bhute, Shrikant S.; Hingamire, Tejashri B.; Gune, Rahul P.; Shouche, Yogesh S. (Standards in Genomic Sciences, 2017)
Probiotic Lactobacillus species offer various health benefits, thus have been employed in treatment and prevention of various diseases. Due to the differences in the isolation source and the site of action, most of the lactobacilli tested in-vitro for probiotics properties fail to extend similar effects in-vivo. Consequently, the search of autochthonous, efficacious and probably population specific probiotics is a high priority in the probiotics research. In this regards, whole genome sequencing of as many Lactobacillus as possible will help to deepen our understanding of biology and their health effects. Here, we provide the genomic insights of two coherent oxalic acid tolerant Lactobacillus species (E2C2 and E2C5) isolated from two different healthy human gut flora. These two isolates were found to have higher tolerance towards oxalic acid (300 mM sodium oxalate). The draft genome of strain E2C2 consists of 3,603,563 bp with 3289 protein-coding genes, 94 RNA genes, and 43.99% GC content, while E2C5 contained 3,615,168 bp, 3293 coding genes (93.4% of the total genes), 95 RNA genes and 43.97% GC content. Based on 16S rRNA gene sequence analysis followed by in silico DNA-DNA hybridization studies, both the strains were identified as Lactobacillus plantarum belonging to family Lactobacillaceae within the phylum Firmicutes. Both the strains were genomically identical, sharing 99.99% CDS that showed 112 SNPs. Both the strains also exhibited deconjugation activity for the bile salts while genome analysis revealed that the L. plantarum strains E2C2 and E2C5 also have the ability to produce vitamins, biotin, alpha-and beta-glucosidase suggesting potential probiotic activities of the isolates. The description presented here is based on the draft genomes of strains E2C2 and E2C5 which are submitted to GenBank under the accession numbers LSST00000000.1 and LTCD00000000.1, respectively.

Dynamic metabolic reprogramming of steroidal glycol-alkaloid and phenylpropanoid biosynthesis may impart early blight resistance in wild tomato (Solanum arcanum Peralta) - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Panda, Sayantan; Meir, Sagit; Rogachev, Ilana; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Molecular Biology, 2017)
Alternaria solani severely affects tomato (Solanum lycopersicum L.) yield causing early blight (EB) disease in tropical environment. Wild relative, Solanum arcanum Peralta could be a potential source of EB resistance; however, its underlying molecular mechanism largely remains unexplored. Hence, non-targeted metabolomics was applied on resistant and susceptible S. arcanum accessions upon A. solani inoculation to unravel metabolic dynamics during different stages of disease progression. Total 2047 potential metabolite peaks (mass signals) were detected of which 681 and 684 metabolites revealed significant modulation and clear differentiation in resistant and susceptible accessions, respectively. Majority of the EB-triggered metabolic changes were active from steroidal glycol-alkaloid (SGA), lignin and flavonoid biosynthetic pathways. Further, biochemical and gene expression analyses of key enzymes from these pathways positively correlated with phenotypic variation in the S. arcanum accessions indicating their potential role in EB. Additionally, transcription factors regulating lignin biosynthesis were also up-regulated in resistant plants and electrophoretic mobility shift assay revealed sequence-specific binding of rSaWRKY1 with MYB20 promoter. Moreover, transcript accumulation of key genes from phenylpropanoid and SGA pathways along with WRKY and MYB in WRKY1 transgenic tomato lines supported above findings. Overall, this study highlights vital roles of SGAs as phytoalexins and phenylpropanoids along with lignin accumulation unrevealing possible mechanistic basis of EB resistance in wild tomato.

Efficient oxidation of ethyl benzene using in situ generated molybdenum acetylide oxo-peroxo complex as recyclable catalyst - Khomane, Sonali B.; Doke, Dhananjay S.; Dongare, M. K.; Halligudi, S. B.; Umbarkar, S. B. (Applied Catalysis A-General, 2017)
Selective oxidation of various alkanes/alkyl aromatics to corresponding carbonyl compounds has been carried out with very high conversion (similar to 98%) and selectivity (up to 100%) for carbonyl compounds using cyclopentadienyl molybdenum acetylide complex, CpMo(CO)(3)(C CPh) (1) as catalyst and tert-butyl hydrogen peroxide (TBHP) as an oxidant and turnover number (TON) of 88 was obtained with turnover frequency (TOF) of 2.45 h(-1). Mo acetylide oxo-peroxo species is formed in situ by reaction of 1 with TBHP during the course of reaction as catalytically active species. Interestingly even though the catalytically active species is homogeneous in nature it could be recycled very easily by recovering the catalytically active species as solid after addition of diethyl ether, and separating the products into organic phase. In the case of ethyl benzene oxidation, even after three recycles no appreciable loss in ethyl benzene conversion and acetophenone selectivity was observed. This complex showed high catalytic activity for the oxo functionalization of other alkyl aromatics and alkanes such as substituted ethyl benzenes, toluene as well as cyclohexane. TBHP was found to be more efficient oxidant than hydrogen peroxide for this oxidation. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Alkyl aromatics; Carbonyl compounds; Homogeneous catalysis; Molybdenum acetylide complex; Oxo-peroxo species

Engineering molecular topology: A pseudopeptidic macrocyclic figure-eight motif - Sharma, Sakshi; Thorat, Shridhar H.; Gonnade, Rajesh G.; Jasinski, Jerry P.; Butcher, Ray; Haridas, V. (European Journal of Organic Chemistry, 2017)
We herein present a rational-design strategy for the synthesis of molecules with figure-eight topology. The design concept is based on the incorporation of turn units in the back-bone of the macrocycle. The molecular structures and the folding are studied by X-ray crystallography and NMR, FT-IR, and CD spectroscopy.
Keywords: Macrocycles; noncovalent interactions; Pi interactions; topology; X-ray diffraction

Glucosylation of smoke-derived volatiles in grapevine (vitis vinifera) is catalyzed by a promiscuous resveratrol/guaiacol glucosyltransferase - Haratl, Katja; Huang, Fong-Chin; Giri, Ashok P.; Franz-Oberdorf, Katrin; Frotscher, Johanna; Shao, Yang; Hoffmann, Thomas; Schwab, Wilfried (Journal of Agricultural and Food Chemistry, 2017)
Vinification of grapes (Vitis vinifera) exposed to forest fire smoke can yield unpalatable wine due to the presence of taint compounds from smoke and the release of smoke derived volatiles from their respective glycosides during the fermentation process or in-mouth during consumption. To identify glycosyltransferases (GTs) involved in the formation of glycosidically bound smoke-derived volatiles we performed gene expression analysis of candidate GTs in different grapevine tissues. Second, substrates derived from bushfire smoke or naturally occurring in grapes were screened with the candidate recombinant GTs. A resveratrol GT (UGT72B27) gene, highly expressed in grapevine leaves and berries was identified to be responsible for the production of the phenolic glucosides. UGT72B27 converted the stilbene trans-resveratrol mainly to the 3-O-glucoside. Kinetic analyses yielded specificity constants (k(cat)/K-m) of 114, 17, 9, 8, and 2 mM(-1) s(-1) for guaiacol, trans-resveratrol, syringol, methylsyringol, and methylguaiacol, respectively. This knowledge will help to design strategies for managing the risk of producing smoke-affected wines.

Glycoprotein alpha-amylase inhibitor from Withania somnifera differentially inhibits various alpha-amylases and affects the growth and development of Tribolium castaneum - Kasar, Sainath S.; Marathe, Kiran R.; Bhide, Amey J.; Herwade, Abhijeet P.; Giri, Ashok P.; Maheshwari, Vijay L.; Pawar, Pankaj K. (PEST Management Science, 2017)
BACKGROUND: Identification and characterisation of plant defensive molecules enrich our resources to design crop protection strategies. In particular, plant-derived proteinaceous inhibitor(s) of insect digestive enzymes appear to be a safe, sustainable and attractive option. RESULTS: A glycoprotein having non-competitive alpha-amylase inhibitory activity with a molecular weight of 8.3 kDa was isolated and purified from seeds of Withania somnifera alpha-amylase inhibitor (WSAI). Its mass spectrometry analysis revealed 59% sequence coverage with Wrightide II-type alpha-amylase inhibitor from Wrightia religiosa. A dose-dependent inhibition of alpha-amylases from Aspergillus oryzae, Bacillus subtilis, Helicoverpa armigera and Tribolium castaneumwas recorded. Interestingly, WSAI did not inhibit human salivary alpha-amylase significantly. When adults of T. castaneum were fed with WSAI (1.6mg g(-1)), decrease inconsumption, growthandefficiency of conversion of ingested foodwas evident, along withover fourfold increases in feedingdeterrence index. Adecline inlarval residual alpha-amylase activity after feedingofWSAI resulted ina reduction in longevity of T. castaneum. CONCLUSION: The study reflects the significance of WSAI in affecting the overall growth and development of T. castaneum. Pre-and post-harvest pest resistive capability makes WSAI a potential candidate for insect pest management. Further, the effectiveness of this inhibitor could be explored either in formulations or through a transgenic approach. (C) 2016 Society of Chemical Industry

Identification of new anti-inflammatory agents based on nitrosporeusine natural products of marine origin - Philkhana, Satish Chandra; Verma, Abhishek Kumar; Jachak, Gorakhnath R.; Hazra, Bibhabasu; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2017)
Nitrosporeusines A and B are two recently isolated marine natural products with novel skeleton and exceptional biological profile. Interesting antiviral activity of nitrosporeusines and promising potential in curing various diseases, evident from positive data from various animal models, led us to investigate their anti-inflammatory potential. Accordingly, we planned and synthesized nitrosporeusines A and B in racemic as well as enantiopure forms. The natural product synthesis was followed by preparation of several analogues, and all the synthesized compounds were evaluated for in vitro and in vivo anti-inflammatory potential. Among them, compounds 25, 29 and 40 significantly reduced levels of nitric oxide (NO), reactive oxygen species (ROS) and pro-inflammatory cytokines. In addition, these compounds suppressed several pro-inflammatory mediators including inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), nuclear factor-kappa B (NF -kappa B), and thereby can be emerged as potent anti-inflammatory compounds. Furthermore, all possible isomers of lead compound 25 were synthesized, characterized and profiled in same set of assays and found that one of the enantiomer (-)-25a was superior among them. (C) 2017 Elsevier Masson SAS. All rights reserved.

Ionic hydrogenation-directed stereoselective construction of C-20(H) stereogenic center in steroid side chains: Scope and limitations - Shingate, Bapurao B.; Hazra, Braja G. (Tetrahedron, 2017)
Stereoselective synthesis of steroidal C-20 tertiary alcohols with n-butyl, vinyl, furyl, thienyl, thiazolyl, aryl and pyridyl side chains via Grignard reaction or organolithium reagents have been realized starting from readily available 16-dehydropregnenolone acetate. The ionic hydrogenation of steroidal C-20 tertiary alcohols having furyl, methylfuryl, thienyl, phenyl and 4-methoxyphenyl side chains, resulted into the deoxygenated product with C-20 natural configuration in excellent yields. However, the alkyl, thiazolyl and pyridyl incorporated steroidal C-20 tertiary alcohols were failed under the same reaction condition. The scope of ionic hydrogenation is further highlighted through the stereoselective reduction of steroidal C-20,21-ene compounds with furyl, thienyl and 4-methoxyphenyl side chains gave the saturated compounds with C-20 natural configuration

Magnetic reduced graphene oxide loaded hydrogels: highly versatile and efficient adsorbents for dyes and selective Cr(VI) ions removal - Halouane, Fatima; Oz, Yavuz; Meziane, Dalila; Barras, Alexandre; Juraszek, Jean; Singh, Santosh K.; Kurungot, Sreekumar; Shaw, Pankaj K.; Sanyal, Rana; Boukherroub, Rabah; Sanyal, Amitav; Szunerits, Sabine (Journal of Colloid and Interface Science, 2017)
The formation of composites of reduced graphene oxide (rGO) and magnetic nanoparticles (MP) has flourished in recent years as they combine the advantages of both nanomaterials. Most of these composite materials are prepared by in situ formation of MP onto rGO or by the post-adsorption onto rGO. We report here on a simple and highly controlled method for the fabrication of different magnetic 3D rGO-loaded hydrogels. Cellulose bound magnetic nanoparticles (MP@cellulose) were synthesized by chemical co-precipitation and loaded together with rGO into poly(ethylene glycol) dimethacrylate based hydrogels during their fabrication using photo-polymerization. The magnetic rGO-loaded hydrogels proved to be highly adaptable to different applications. The as-formed composites allowed for efficient dye removal with an adsorption capacity of 111.9 +/- 4 mg g(-1) in the case of methylene blue (MB). Integration of poly(ethyleneimine) (PEI) allowed for the selective capturing of Cr6+ ions with an adsorption capacity of 313 12 mg g-1. Most importantly, independent of the application, the magnetic rGO-loaded hydrogel can be regenerated without loss of its adsorption capacity. (C) 2017 Elsevier Inc. All rights reserved.

Mapping architectural and transcriptional alterations in non-lesional and lesional epidermis in vitiligo - Singh, Archana; Gotherwal, Vishvabandhu; Junni, Paivi; Vijayan, Vinaya; Tiwari, Manisha; Ganju, Parul; Kumar, Avinash; Sharma, Pankaj; Fatima, Tanveer; Gupta, Aayush; Holla, Ananthaprasad; Kar, Hemanta K.; et al. (Scientific Reports, 2017)
In vitiligo, chronic loss of melanocytes and consequent absence of melanin from the epidermis presents a challenge for long-term tissue maintenance. The stable vitiligo patches are known to attain an irreversible depigmented state. However, the molecular and cellular processes resulting in this remodeled tissue homeostasis is unclear. To investigate the complex interplay of inductive signals and cell intrinsic factors that support the new acquired state, we compared the matched lesional and non-lesional epidermis obtained from stable non-segmental vitiligo subjects. Hierarchical clustering of genome-wide expression of transcripts surprisingly segregated lesional and non-lesional samples in two distinct clades, despite the apparent heterogeneity in the lesions of different vitiligo subjects. Pathway enrichment showed the expected downregulation of melanogenic pathway and a significant downregulation of cornification and keratinocyte differentiation processes. These perturbations could indeed be recapitulated in the lesional epidermal tissue, including blunting of rete-ridges, thickening of stratum corneum and increase in the size of corneocytes. In addition, we identify marked increase in the putrescine levels due to the elevated expression of spermine/spermidine acetyl transferase. Our study provides insights into the intrinsic self-renewing ability of damaged lesional tissue to restore epidermal functionality in vitiligo.

Medium constituents mediated engineering for size and shape tuning of gold nanocrystallites - Suresh, Anil K.; Vijay, Veena; Hameed, Bahrudeen S.; Ramasamy, Sureshkumar; Sakthivel, Natarajan (Journal of Industrial and Engineering Chemistry, 2017)
The current investigation introduces the utilization of cell culture mediums as a novel source for the one plot synthesis as well as stabilization of metal nanoparticles. By varying the medium constituents we could control the size and shape distributions of the gold nanoparticles. Nanospheres of diameter 24 +/- 6 nm and 19 +/- 5 nm were produced using DMEM and M199 mediums respectively, nanoneedles of 150 +/- 50 nm using RPMI medium and nanoflowers of 60 +/- 25 nm using IMDM medium, with an overall yield of 91 +/- 2%. A remarkable decrease in the reaction duration (<3 min) was noted, irrespective of the growth mediums used. Fourier transform infrared spectroscopy and zeta potential measurements revealed them to have a common protenacious encapping agent with different overall surface charges of -23 +/- 3, -21 +/- 1, -24 +/- 2, and -20 +/- 1 mV for Au@DMEM, Au@RPMI, Au@IMDM and Au@M199 respectively. X-ray diffraction confirmed the purity and crystallinity of the particles with Bragg peaks at (111), (200), (220) and (311) for gold nanocrystals. This approach could lead to the creative utilization of novel eco-friendly sources for the production and size/shape control of nanoparticles. Moreover, the adopted methodology is absolutely green, robust and facile, offering new insights for sustainable synthesis for various biomedical and engineering applications. (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.

Modular assembly of porous organic cage crystals: isoreticular quasiracemates and ternary co-crystal - Tothadi, Srinu; Little, Marc A; Hasell, Tom; Briggs, Michael E.; Chong, Samantha Y.; Liu, Ming; Cooper, Andrew I. (CrystEngComm, 2017)
Small changes in molecular structure and crystallisation conditions can have a profound effect on the crystal packing of molecules. Increasing the system complexity-for example, by introducing multiple components-greatly increases the number of potential outcomes. Hence, the rational design of porous cocrystals with multiple components is challenging. Here, we report a family of isoreticular quasiracemate crystalline phases for porous organic cages, FT-RCC3-R center dot CCX-S (where X = 1, 2, or 4), that were prepared in a modular and predictable fashion. By using directional intermolecular interactions between cages, we were able to prepare a rare ternary co-crystal, (CC3-S(0.5)CC4-S-0.5)center dot(CC13-S(0.5)CC3-S(0.25)CC4-S-0.25).
Keywords: cocrystals; Frameworks; Gas-chromatography; Halogen Bonds; Hydrogen-bonds; Molecular Cage; Nanoparticles; Pores; porosity; Separation

Molecular level control of the capacitance of two-dimensional covalent organic frameworks: role of hydrogen bonding in energy storage materials - Chandra, S.; Chowdhury, D.R; Addicoat, M.; Heine, T.; Paul, A.; Banerjee, R. (Chemistry of Materials, 2017)
Two-dimensional redox-active covalent organic frameworks (COFs) are ideal materials for energy storage applications due to their high surface area, extended pi conjugated structure, tunable pore size, and adjustable functionalities. Herein, we report the synthesis and super capacitor application of two redox active COFs [TpPa-(OH)(2) and TpBD-(OH)(2)] along with the role of their redox active functional groups for the enrichment of specific capacitance. Of these COFs, TpPa-(OH)2 exhibited the highest specific capacitance of 416 F g(-1) at 0.5 A g(-1) current density in three electrode configuration while the highest specific capacitance was 214 F g(-1) at 0.2 A g(-1) current density in two electrode configuration. Superior specific capacitance was due to emergence of excellent pseudocapacitance by virtue of precise molecular level control over redox functionalities present in the COF backbone. This COF also demonstrated 66% capacitance retention after 10 000 cycles along with 43% accessibility of the redox-active hydroquinone (H2Q) moieties in three electrode configuration while the capacitance retention was 88% after 10 000 cycles in two electrode configuration. Exceptionally high specific capacitance of TpPa-(OH)(2) was due to the reversible proton-coupled electron transfer (2H(+)/2(e-)) of hydroquinone/benzoquinone (H(2)Q/Q) moieties wherein H(2)Q and Qhad comparable chemical stabilities during redox cycling that originated from H-bonding, which was supported by calculated structures.

Optimizing culture conditions for establishment of hairy root culture of semecarpus anacardium L. - Panda, Bhuban Mohan; Mehta, Urmil J.; Hazra, Sulekha (3 Biotech, 2017)
Semecarpus anacardium L. is a tree species which produces secondary metabolites of medicinal importance. Roots of the plant have been traditionally used in folk medicines. Different strains of Agrobacterium rhizogenes (A4, ATCC15834 and LBA 9402) were used for induction of hairy roots in in vitro grown tissues of the plant. Hairy root initiation was observed after 25-30 days of infection. Optimum transformation frequency of 61% was achieved on leaf explants with ATCC15834 strain. Infection time of 30 min resulted in greater transformation frequency compared to 10 and 20 min, respectively. The hairy roots cultured in growth regulator-free semi-solid woody plant medium differentiated into callus. Whole shoots infected with ATCC 15834 were found to produce more transformants upon co-cultivation for 4 (65%) and 5 (67%) days. Induction of hairy roots in stem explants infected with ATCC 15834 was lower (52%) compared to leaves (62%) after 4 days of co-cultivation. In A4 and LBA9402 strains transformation efficiency was 49 +/- 2.8% and 36 +/- 5.7% in shoots after 4 days of co-cultivation. Transformation frequency was higher in ATCC15834 strain, irrespective of explants. The hairy roots of S. anacardium elongated slowly upon transfer to half-strength liquid medium. After 3-4 passages in liquid medium slender hairy roots started differentiating which were separated from the original explants. Visible growth of the roots was observed in hormone-free liquid medium after 2-3 months of culturing. Polymerase chain reaction with gene-specific primers from rol A, B and C genes confirms the positive transformation events.
Keywords: Hairy root culture; In vitro culture; rol genes; Semecarpus anacardium; Transformation

Overcoming the lack of oral availability of cyclic hexapeptides: design of a selective and orally available ligand for the integrin alpha v beta 3 - Weinmueller, Michael; Rechenmacher, Florian; Marelli, Udaya Kiran; Reichart, Florian; Kapp, Tobias G.; Raeder, Andreas F. B.; Di Leva, Francesco Saverio; Marinelli, Luciana; Novellino, Ettore; Munoz-Felix, Jose M.; Hodivala-Dilke, Kairbaan; Schumacher, Adi; et al. (Angewandte Chemie-International Edition, 2017)
Ahighly systematic approach for the development of both orally bioavailable and bioactive cyclic N-methylated hexapeptides as high affinity ligands for the integrin alpha v beta 3 is based on two concepts: a) screening of systematically designed libraries with spatial diversity and b) masking of the peptide charge with a lipophilic protecting group. The key steps of the method are 1) initial design of a combinatorial library of Nmethylated analogues of the stem peptide cyclo(d-Ala-Ala(5)); 2) selection of cyclic peptides with the highest intestinal permeability; 3) design of sublibraries with the bioactive RGD sequence in all possible positions; 4) selection of the best ligands for RGD-recognizing integrin subtypes; 5) finetuning of the affinity and selectivity by additional Ala to Xaa substitutions; 6) protection of the charged functional groups according to the prodrug concept to regain intestinal and oral permeability; 7) proof of biological effects in mice after oral administration.

Proton conduction in a hydrogen-bonded complex of copper(II)-bipyridine glycoluril nitrate - Tayade, Sakharam B.; Dhavale, Vishal M.; Kumbhar, Avinash S.; Kurungot, Sreekumar; Loennecke, Peter; Hey-Hawkins, Evamarie; Pujari, Bhalchandra (Dalton Transactions, 2017)
Bipyridine glycoluril (BPG), a urea-fused bipyridine tecton, forms a square-pyramidal secondary building unit with copper(II) which further self-assembles to give a porous hydrogen-bonded complex. This complex displays a high proton conductivity of 4.45 x 10(-3) S cm(-1) at 90 degrees C and 95% relative humidity (RH). Chains consisting of coordinated water, solvent water and nitrate anions embedded in the complex are responsible for high proton conduction. The proton conduction pathway was corroborated by ab initio electronic structure calculations with molecular dynamics (MD) simulations using the Nudged Elastic Band (NEB) method. The theoretical activation energy estimated to be 0.18 eV is in close agreement with the experimental value of 0.15 eV which evidences a Grotthuss proton hopping mechanism. We thus demonstrate that the hydrogen-bonded complex encapsulating appropriate counter ions, coordinated water and solvent water molecules exhibts superprotonic conductivity.

Selective isolation and eradication of E. coli associated with urinary tract infections using anti-fimbrial modified magnetic reduced graphene oxide nanoheaters - Halouane, Fatima; Jijie, Roxana; Meziane, Dalila; Li, Chengnan; Singh, Santosh K.; Bouckaert, Julie; Jurazek, Jean; Kurungot, Sreekumar; Barras, Alexandre; Li, Musen; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
The fast and efficient elimination of pathogenic bacteria from water, food or biological samples such as blood remains a challenging task. Magnetic isolation of bacteria from complex media holds particular promise for water disinfection and other biotechnological applications employing bacteria. When it comes to infectious diseases such as urinary tract infections, the selective removal of the pathogenic species in complex media such as human serum is also of importance. This issue can only be accomplished by adding pathogen specific targeting sites onto the magnetic nanostructures. In this work, we investigate the potential of 2-nitrodopamine modified magnetic particles anchored on reduced graphene oxide (rGO) nanocomposites for rapid capture and efficient elimination of E. coli associated with urinary tract infections (UTIs) from water and serum samples. An optimized magnetic nanocarrier achieves a 99.9% capture efficiency even at E. coli concentrations of 1 x 10(1) cfu mL(-1) in 30 min. In addition, functionalization of the nanostructures with poly(ethylene glycol) modified pyrene units and anti-fimbrial E. coli antibodies allowed specific elimination of E. coli UTI89 from serum samples. Irradiation of the E. coli loaded nanocomposite with a near-infrared laser results in the total ablation of the captured pathogens. This method can be flexibly modified for any other pathogenic bacteria, depending on the antibodies used, and might be an interesting alternative material for a magnetic-based body fluid purification approach.

Spectroscopic and reactivity comparisons of a pair of bTAML complexes with Fe-V=O and Fe-IV=O units - Pattanayak, Santanu; Jasniewsk, Andrew J.; Rana, Atanu; Draksharapu, Apparao; Singh, Kundan K.; Weitz, Andrew; Hendrich, Michael; Que, Lawrence, Jr.; Dey, Abhishek; Sen Gupta, Sayam (Inorganic Chemistry, 2017)
In this report we compare the geometric and electronic structures and reactivities of [Fe-V(O)](-) and [Fe-IV(O)](2-) species supported by the same ancillary nonheme biuret tetraamido macrocyclic ligand (bTAML). Resonance Raman studies show that the Fe-O vibration of the [Fe-IV(O)](2-) complex 2 is at 798 cm(-1), compared to 862 cm(-1) for the corresponding [Fe-V(O)](-) species 3, a 64 cm(-1) frequency difference reasonably reproduced by density functional theory calculations. These values are, respectively, the lowest and the highest frequencies observed thus far for nonheme high-valent Fe-O complexes. Extended X-ray absorption fine structure analysis of 3 reveals an Fe-O bond length of 1.59 angstrom, which is 0.05 angstrom shorter than that found in complex 2. The redox potentials of 2 and 3 are 0.44 V (measured at pH 12) and 1.19 V (measured at pH 7) versus normal hydrogen electrode, respectively, corresponding to the [Fe-IV(O)](2-)/[Fe-III(OH)](2-) and [Fe-V(O)](-)/[Fe-IV(O)](2-) couples. Consistent with its higher potential (even after correcting for the pH difference), 3 oxidizes benzyl alcohol at pH 7 with a second-order rate constant that is 2500-fold bigger than that for 2 at pH 12. Furthermore, 2 exhibits a classical kinteic isotope effect (KIE) of 3 in the oxidation of benzyl alcohol to benzaldehyde versus a nonclassical KIE of 12 for 3, emphasizing the reactivity differences between 2 and 3.

Unraveling structure sensitivity in phenol hydrogenaton on Pd nanostructures - Haider, M. Ali; Seshadri, Sreedhala; Gupta, Shelaka; Khan, Tuhin; Prabhakaran, Vinod (253rd National Meeting of the American-Chemical-Society (ACS) on Advanced Materials, Technologies, Systems, and Processes, 2017)

Visible-light active catechol-metal oxide carbonaceous polymeric material for enhanced photocatalytic activity - Karthik, P.; Vinoth, R.; Selvam, P.; Balaraman, E.; Navaneethan, M.; Hayakawa, Y.; Neppolian, B. (Journal of Materials Chemistry A, 2017)
esigning new materials for sustainable energy and environmental applications is one of the prime focuses in chemical science. Here, an unprecedented visible-light active catechol-TiO2 carbonaceous polymer based organic-inorganic hybrid material was synthesized by a photosynthetic route. The visible light induced (> 400 nm) photosynthetic polymerization of catechol led to the formation of carbonaceous polymeric deposits on the surface of TiO2. The band gap energy of hybrids was shifted to the visible region by orbital hybridization between 3d(Ti) of TiO2 and 2p(O), pi(C) of catechol. The Tauc plot clearly revealed that 1.0 wt% catechol-TiO2 carbonaceous polymer remarkably tailored the optical band gap of TiO2 from 3.1 eV to 1.9 eV. The synthesized hybrid materials were thoroughly characterized and their photocatalytic activity was evaluated towards toxic Cr(VI) to relatively less toxic Cr(III) reduction under visible light irradiation (> 400 nm), and solar light-driven H-2 production through water splitting. Very interestingly, the hybrid material showed 5- and 10-fold enhanced activity for photocatalytic Cr(VI) reduction and solar light-driven H-2 production respectively compared with pure TiO2. Moreover, the hybrid materials showed enhanced stability during photocatalysis. Thus, the simple photosynthetic strategy for developing light harvesting organic-inorganic hybrid materials can open up potential applications in energy and environmental remediation.

Vitro study of novel microparticle based silk fibroin scaffold with osteoblast-like cells for load-bearing osteo-regenerative applications - Parekh, Nimisha Anant; Hushye, Chandni; Warunkar, Saniya; Gupta, Sayam Sen; Nisal, Anuya (RSC Advances, 2017)
Silk Fibroin (SF) is today considered to be one of the most favorable materials for bone tissue engineering. We have prepared novel SF microparticle based 3D scaffolds, with appropriate pore size, pore interconnectivity and porosity, excellent mechanical properties and tunable bioresorption, while retaining the inherent biocompatibility of SF. These properties make them ideal candidates for osteoregenerative applications. Here, we report the in vitro cell viability, cell adhesion and proliferation with osetoblastic differentiation of MG 63 osteoblast-like cell line on these scaffolds. In addition, we have also modified the surface of these scaffolds using collagen type I and chitosan biopolymers. Our results show that although the SF scaffold does support in vitro cell attachment, proliferation and differentiation, this performance can be further enhanced using the surface coating approach. Also, the ALP activity and bone mineralization was found to be particularly superior in the chitosan modified scaffolds.

ZnO–ZnS heterojunctions: a potential candidate for optoelectronics applications and mineralization of endocrine disruptors in direct sunlight - Perumal Devaraji; Maitri Mapa; Hasna M. Abdul Hakkeem; Vediappan Sudhakar; Kothandam Krishnamoorthy; Chinnakonda S. Gopinath (ACS Omega, 2017)
Simple solution combustion synthesis was adopted to synthesize ZnO–ZnS (ZSx) nanocomposites using zinc nitrate as an oxidant and a mixture of urea and thiourea as a fuel. A large thiourea/urea ratio leads to more ZnS in ZSx with heterojunctions between ZnS and ZnO and throughout the bulk; tunable ZnS crystallite size and textural properties are an added advantage. The amount of ZnS in ZSx can be varied by simply changing the thiourea content. Although ZnO and ZnS are wide band gap semiconductors, ZSx exhibits visible light absorption, at least up to 525 nm. This demonstrates an effective reduction of the optical band gap and substantial changes in its electronic structure. Raman spectroscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and secondary-ion mass spectrometry results show features due to ZnO and ZnS and confirm the composite nature with heterojunctions. The above mentioned observations demonstrate the multifunctional nature of ZSx. Bare ZSx exhibits a promising sunlight-driven photocatalytic activity for complete mineralization of endocrine disruptors such as 2,4-dichlorophenol and endosulphan. ZSx also exhibits photocurrent generation at no applied bias. Dye-sensitized solar cell performance evaluation with ZSx shows up to 4% efficiency and 48% incident photon conversion efficiency. Heterojunctions observed between ZnO and ZnS nanocrystallites in high-resolution transmission electron microscopy suggest the reason for effective separation of electron–hole pairs and their utilization.

Carbon fabric based solar steam generation for waste water treatment - Higgins, M. W.; Rahmaan, Shakeel A. R.; Devarapalli, Rami Reddy; Shelke, Manjusha V.; Jha, Neetu (Solar Energy, 2018)
Decontamination of waste water is one of the most practical techniques to tackle the worldwide clean water shortage. In recent times, solar steam based decontamination of contaminated water has been attested as a potential sustainable strategy to get clean water using renewable resources. Herein, we report the utilization of Carbon fabric and Titanium Nanorods on Carbon Fabric for solar steam based water purification techniques. The performance of Carbon Fabric was tested under different conditions and the results proved that Carbon Fabric has excellent light to heat conversion capabilities in both real and ideal conditions. Owing to the excellent performance of Carbon Fabric, it was used for purification of different types of contaminated water. About 99.9% of salt and 87% of organic contaminants were removed from saline water and organic waste water respectively, using a simple low cost carbon fabric based homemade prototype. We also present the application of Titanium Nanorods on carbon fabric for the efficient removal of dye molecules like Rhodamine B from contaminated water using solar driven interfacial steam generation mechanism.
Keywords: Desalination; Dye degradation; Solar steam; Waste water treatment

Co9Se8 nanoparticles as high capacity anode material for lithium-ion batteries - Kumar, Pushpendra; Hu, Lung-Hao (Materials Research Express, 2018)
Present investigation deal with the facile synthesis of Co9Se8 nanoparticles (NPs) and their application as the potential anode for lithium-ion battery (LIB). The primary size of the Co9Se8 NPs can be achieved between 10 similar to 25 nm while the secondary cluster size ranging from 150 similar to 200 nm as observed by transmission electron microscope (TEM). The specific capacity of Co9Se8 NPs LIB anode can reach around similar to 610 mAhg(-1) during charging (lithium ion released from Co9Se8 nanoparticles), and -730 mAhg(-1) during discharging (lithium ion intercalated) at an applied current density of similar to 100 mAg(-1). These values are significantly higher than that of the commercial graphite anode (theoretical capacity similar to 372 mAhg(-1)). The irreversibility of Co9Se8 anode (similar to 15%) is also significantly lower than that of most metal oxides and silicon-based anodes (irreversibility ranging between 30 similar to 50% or higher for Si). The reason for superior specific capacity and low irreversibility compared to metal oxides and silicon-based materials could be owing to the stable nano-cluster size which help to reduce the diffusion path and internal resistance to lithium ion.
Keywords: irreversibility; lithium-ion battery; lithium-ion diffusion; Nanoparticles; specific capacity

Colloidal Mn2+ doped 2D (n =1) lead bromide perovskites: efficient energy transfer and role of anion in doping mechanism - Haris, Muhammed; Bakthavatsalam, Rangarajan; Kundu, Janardan (ChemistrySelect, 2018)
Mn²⁺ doping directly into APbCl3 type 3D nanocrystals, manifesting host to dopant energy transfer, have been heavily reported for illumination and display applications. However, these doped 3D ABX3 systems have low/modest exciton binding energy. Strongly bound excitons in the doped system can enhance the dopant‐host carrier exchange interactions leading to efficient energy transfer. Reported here is a simple and facile synthesis of colloidal Mn²⁺ doped (Butylammonium/octylammonium)2PbBr4 2D (n=1) perovskites that demonstrate enhanced energy transfer from strongly bound excitons of the host material to the Mn²⁺ dopant ions resulting in intense orange‐yellow emission due to spin forbidden internal transition (⁴T1 → ⁶A1) with the highest quantum yield (Mn²⁺) of 36%. Consistent with experimental evidences presented here, mechanism of this thermally aided doping process in these 2D systems, very likely, involves halide vacancy and its diffusion that precedes the cation exchange (doping) process. Owing to the high quantum yield, stability in ambient atmosphere, simplicity and scalability of the synthetic procedure, Mn²⁺ doped 2D perovskites could be beneficial as color converting phosphor material and can be utilized to further explore their magneto‐optoelectronic properties.

CSGID solves structures and identifies phenotypes for five enzymes in toxoplasma gondii - Lykins, Joseph D.; Filippova, Ekaterina V; Halavaty, Andrei S.; Minasov, George; Zhou, Ying; Dubrovska, Ievgeniia; Flores, Kristin J.; Shuvalova, Ludmilla A.; Ruan, Jiapeng; El Bissati, Kamal; Dovgin, Sarah; Roberts, Craig W.; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Toxoplasma gondii, an Apicomplexan parasite, causes significant morbidity and mortality, including severe disease in immunocompromised hosts and devastating congenital disease, with no effective treatment for the bradyzoite stage. To address this, we used the Tropical Disease Research database, crystallography, molecular modeling, and antisense to identify and characterize a range of potential therapeutic targets for toxoplasmosis. Phosphoglycerate mutase II (PGMII), nucleoside diphosphate kinase (NDK), ribulose phosphate 3-epimerase (RPE), ribose-5-phosphate isomerase (RPI), and ornithine aminotransferase (OAT) were structurally characterized. Crystallography revealed insights into the overall structure, protein oligomeric states and molecular details of active sites important for ligand recognition. Literature and molecular modeling suggested potential inhibitors and druggability. The targets were further studied with vivoPMO to interrupt enzyme synthesis, identifying the targets as potentially important to parasitic replication and, therefore, of therapeutic interest. Targeted vivoPMO resulted in statistically significant perturbation of parasite replication without concomitant host cell toxicity, consistent with a previous CRISPR/Cas9 screen showing PGM, RPE, and RPI contribute to parasite fitness. PGM, RPE, and RPI have the greatest promise for affecting replication in tachyzoites. These targets are shared between other medically important parasites and may have wider therapeutic potential.

Cyclohexylation of resorcinol with cyclohexanol catalyzed by tungstophosphoric acid supported zirconia catalysts - Balasubramanian, V. V.; Devassay, B. M.; Halligudi, S. B.; Deepika, R.; Umbarakar, S. B.; Vinu, A. (Journal of Nanoscience and Nanotechnology, 2018)
We demonstrate a highly active and reusable heterogeneous catalyst system, tungstophosphoric acid (TPA) supported on zirconia (ZrO2), for the cyclohexylation of resorcinol by cyclohexanol to produce value added chemicals such as 2-cyclohexyl resorcinol, 4-cyclohexyl resorcinol and 3-Hydroxy cyclohexyl phenyl ether under liquid phase reaction condition. TPA/ZrO2 catalysts prepared with different TPA loadings (5-30 wt.%) by wet impregnation method and calcined in the temperature range of 650-850 degrees C were characterized by Nitrogen sorption analysis, XRD, FTIR, DTG and DTA, and P-31 MAS NMR spectroscopy. Among the catalysts studied, 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C gave the highest conversion of resorcinol (51.2%) with the selectivities for 3-Hydroxy cyclohexyl phenyl ether (53.9%) and 2-cyclohexyl resorcinol and 4-cyclohexyl resorcinol together (46.1%) under optimum reaction conditions. However, the selectivity of the products were controlled by varying the reaction conditions. At higher conversion of resorcinol (78.9%), only C-alkylated products were formed at 200 degrees C with 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C. The combination of TPA and ZrO2 coupled with calcination temperature offered an excellent platform for the conversion of resorcinol into O- or C-alkylated products.
Keywords: 15% TPA/ZrO2; Cyclohexanol; Cyclohexylation; Keggin TPA; Resorcinol

Cyclometallation of a germylene ligand by concerted metalation-deprotonation of a methyl group - Bakthavachalam, K.; Dutta, Sayan; Arivazhagan, C.; Raghavendra, Beesam; Haridas, Anagha; Sen, Sakya S.; Koley, Debasis; Ghosh, Sundargopal (Dalton Transactions, 2018)
The reaction of [CH{(CMe)(2,6-iPr(2)C(6)H(3)N)}(2)]GeCl with LiN(SiMe3)(2) was previously reported, which led to the formation of a hetero-fulvene type germylene, [CH{(CMe)(C?CH2)(2,6-iPr(2)C(6)H(3)N)}(2)]Ge through the deprotonation of the C-H bond from the methyl substituents. In this paper, we attempted the analogous reaction with (Dipp)NCMeCHCOMeGeCl using LiN(SiMe3)(2) which gave rise to a metathesis product, (Dipp)NCMeCHCOMeGeN(SiMe3)(2) (2). However, the reactions of 2 with [M2Cl2(-Cl)(2)((5)-Cp*)(2)] (M = Rh and Ir) resulted in cyclometallated Rh and Ir complexes through the activation of the C-H bond from the germylene ligand. The complexes were characterized by single crystal X-ray analysis, which authenticated the presence of Ge-Rh and Ge-Ir bonds. DFT studies have been performed to understand the mechanism.

Effect of sodium dodecyl sulfate surfactant on methane hydrate formation: a molecular dynamics study - Choudhary, Nilesh; Hande, Vrushali R.; Roy, Sudip; Chakrabarty, Suman; Kumar, Rajnish (Journal of Physical Chemistry B, 2018)
In experimental studies, it has been observed that the presence of sodium dodecyl sulfate (SDS) significantly increases the kinetics of hydrate formation and the final water-to-hydrate conversion ratio. In this study, we intend to understand the molecular mechanism behind the effect of SDS on the formation of methane hydrate through molecular dynamics simulation. Hydrate formation conditions similar to that of laboratory experiments were chosen to study hydrate growth kinetics in 1 wt % SDS solution. We also investigate the effect of interactions with isolated SDS molecules on methane hydrate growth. It was observed that the hydrophobic tail part of the SDS molecule favorably interacts with the growing hydrate surface and may occupy the partial hydrate cages while the head groups remain exposed to water.

Electrospinning of non-ionic cellulose ethers/polyvinyl alcohol nanofibers: characterization and applications - Wali, Ashwini; Zhang, Yucheng; Sengupta, Poulomi; Higaki, Yuji; Takahara, Atsushi; Badiger, Manohar V. (Carbohydrate Polymers, 2018)
The morphology of spin-coated films and electrospun fibers of ethyl hydroxy ethyl cellulose (EHEC), hydrophobically modified ethyl hydroxy ethyl cellulose (HM-EHEC) and their blends with Poly(vinyl alcohol) (PVA) was examined by AFM, SEM and contact angle measurements. These polysaccharides upon blending with PVA exhibited smooth surface which was evidenced by Atomic Force Microscopy (AFM) observation. The electrospinnability of above polysaccharides with PVA was demonstrated for the first time. The oriented fibers could be obtained using a rotating disc collector. Contact angles of spin-coated films and electrospun fibers were discussed in terms of hydrophobicity and wetting characteristics. Further, The nanofibers of EHEC/PVA were in-situ crosslinked using citric acid and were used for controlled release of an antibacterial drug, Chlorhexidine Digluconate (ChD). In-vitro studies of cytotoxicity, cell growth and cell proliferation were performed using L929 mouse fibroblast cells. These nanofiber mats show potential in drug delivery and as scaffolds in tissue engineering applications.
Keywords: cellulose; drug delivery; electrospinning; Ethyl hydroxy ethyl cellulose; Hydrophobically modified ethyl hydroxy ethyl; scaffold; Spin coating

Epoxyazadiradione suppresses breast tumor growth through mitochondrial depolarization and caspase-dependent apoptosis by targeting PI3K/Akt pathway - Kumar, Dhiraj; Haldar, Saikat; Gorain, Mahadeo; Kumar, Santosh; Mulani, Fayaj A.; Yadav, Amit S.; Miele, Lucio; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (BMC Cancer, 2018)
Background: Breast cancer is one of the most commonly diagnosed invasive cancers among women around the world. Among several subtypes, triple negative breast cancer (TNBC) is highly aggressive and chemoresistant. Treatment of TNBC patients has been challenging due to heterogeneity and devoid of well-defined molecular targets. Thus, identification of novel effective and selective agents against TNBC is essential. Methods: We used epoxyazadiradione to assess the cell viability, mitochondrial potential, ROS level, cell migration, apoptosis and protein expression in cell culture models of TNBC MDA-MB-231 and ER+MCF-7 breast cancer cells. The molecular mechanism was examined in two different type of breast cancer cells in response to epoxyazadiradione. We have also analyzed the effect of epoxyazadiradione on breast tumor growth using in vivo mice model. Results: In this study, we for the first time investigated that out of 10 major limonoids isolated from Azadirachta indica, epoxyazadiradione exhibits most potent anti-cancer activity in both TNBC and ER+breast cancer cells. Epoxyazadiradione induces apoptosis and inhibits PI3K/Akt-mediated mitochondrial potential, cell viability, migration and angiogenesis. It also inhibits the expression of pro-angiogenic and pro-metastatic genes such as Cox2, OPN, VEGF and MMP-9 in these cells. Furthermore, epoxyazadiradione attenuates PI3K/Akt- mediated AP-1 activation. Our in vivo data revealed that epoxyazadiradione suppresses breast tumor growth and angiogenesis in orthotopic NOD/SCID mice model. Conclusion: Our findings demonstrate that epoxyazadiradione inhibits PI3K/Akt-dependent mitochondrial depolarisation, induces apoptosis and attenuates cell migration, angiogenesis and breast tumor growth suggesting that this compound may act as a potent therapeutic agent for the management of breast cancer.
Keywords: Angiogenesis; Apoptosis; Breast cancer; Limonoids; Metastasis; PI3K

Evaluating antimalarial efficacy by tracking glycolysis in Plasmodium falciparum using NMR spectroscopy - Shivapurkar, Rupali; Hingamire, Tejashri; Kulkarni, Akshay S.; Rajamohanan, P. R.; Reddy, D. Srinivasa; Shanmugam, Dhanasekaran (Scientific Reports, 2018)
Glucose is an essential nutrient for Plasmodium falciparum and robust glycolytic activity is indicative of viable parasites. Using NMR spectroscopy, we show that P. falciparum infected erythrocytes consume similar to 20 times more glucose, and trophozoites metabolize similar to 6 times more glucose than ring stage parasites. The glycolytic activity, and hence parasite viability, can be measured within a period of 2 h to 5 h, using this method. This facilitates antimalarial bioactivity screening on ring and trophozoite stage parasites, exclusively. We demonstrate this using potent and mechanistically distinct antimalarial compounds such as chloroquine, atovaquone, cladosporin, DDD107498 and artemisinin. Our findings indicate that ring stage parasites are inherently more tolerant to antimalarial inhibitors, a feature which may facilitate emergence of drug resistance. Thus, there is a need to discover novel antimalarial compounds, which are potent and fast acting against ring stage parasites. The NMR method reported here can facilitate the identification of such molecules.

Fluorescent chemodosimeter for quantification of Cystathionine-y-synthase activity in plant extracts and imaging of endogenous biothiols - Agarwalla, Hridesh; Hoskere, Anila A.; Ali, Firoj; Pradhan, Swaraj Rashmi; Ganguly, Bishwajit; Pramanik, Sumit kumar; Das, Amitava (Chemical Communications, 2018)
A new reagent for quantification of CgS in plant extracts using a generalized methodology suitable for recognition of homocysteine (Hcy) with luminescence ON response.

Genetic and phytochemical investigations for understanding population variability of the medicinally important tree Saraca asoca to help develop conservation strategies - Hegde, Satisha; Pai, Sandeep Ramchandra; Bhagwat, Rasika M.; Saini, Archana; Rathore, Poonam Kanwar; Jalalpure, Sunil Satyappa; Hegde, Harsha Vasudev; Sugunan, Attayoor Purushottaman; Gupta, Vidya S.; Kholkute, Sanjiva D.; Roy, Subarna (Phytochemistry, 2018)
Saraca asoca (Roxb.) De Wilde (Caesalpiniaceae) is a highly traded IUCN red listed tree species used in Ayurvedic medicines for the treatment of various disorders, especially gynaecological problems. However, information about the genetic variations between populations and corresponding variation in specialized metabolites of S. asoca remains unclear. To address this issue, we analysed 11 populations of S. asoca with 106 accessions collected from Western Ghats of India using ISSR markers along with selected phytocompounds using RP-HPLC. Twenty primers were screened, out of which seven were selected for further analysis based on generation of clear polymorphic banding patterns. These seven ISSR primers produced 74 polymorphic loci. AMOVA showed 43% genetic variation within populations and 57% among the populations of S. asoca. To estimate the genetic relationships among S. asoca populations, UPGMA and Bayesian Models were constructed, which revealed two clusters of similar grouping patterns. However, excluding minor deviations, UPGMA and dissimilarity analysis showed close association of genotypes according to their geographical locations. Catechin (CAT), epicatechin (EPI) and gallic acid (GA) were quantified from bark and leaf samples of corresponding genotypes collected from 106 accessions. ROC plots depicted the sensitivity and specificity of the concentrations of tested phytocompounds at various cut-off points. Although, multiple logistic regression analysis predicted some association between few loci with GA, EPI and CAT, but PCA for phytochemical data failed to distinguish the populations. Overall, there were no significant trends observed to distinguish the populations based on these phytocompounds. Furthermore, the study advocates the delineate provenance regions of S. asoca genotypes/chemotype snapshots for in-situ conservation and ex-situ cultivation.

Glucose isomerization catalyzed by bone char and the selective production of 5-hydroxymethylfurfural in aqueous media - Matsagar, Babasaheb M.; Van Nguyen, Chi; Hossain, Md. Shahriar A.; Islam, Md. Tofazzal; Yamauchi, Yusuke; Dhepe, Paresh L.; Wu, Kevin C. -W. (Sustainable Energy & Fuels, 2018)
The selective production of 5-hydroxymethylfurfural (HMF) is important, and it is difficult with glucose substrates in a water solvent. Here we demonstrate a selective method for glucose-to-HMF conversion using the combined catalysis of bone char and 1-methyl-3-(3-sulfopropyl)-imidazolium hydrogen sulfate acidic ionic liquid catalysts with a high HMF selectivity (54%) in water.

High and reversible lithium ion storage in self-exfoliated triazole-triformyl phloroglucinol-basedcovalent organic nanosheets - Haldar, Sattwick; Roy, Kingshuk; Nandi, Shyamapada; Chakraborty, Debanjan; Puthusseri, Dhanya; Gawli, Yogesh; Ogale, Satishchandra; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2018)
Covalent organic framework (COF) can grow into self-exfoliated nanosheets. Their graphene/graphite resembling microtexture and nanostructure suits electrochemical applications. Here, covalent organic nanosheets (CON) with nanopores lined with triazole and phloroglucinol units, neither of which binds lithium strongly, and its potential as an anode in Li-ion battery are presented. Their fibrous texture enables facile amalgamation as a coin-cell anode, which exhibits exceptionally high specific capacity of approximate to 720 mA h g(-1) (@100 mA g(-1)). Its capacity is retained even after 1000 cycles. Increasing the current density from 100 mA g(-1) to 1 A g(-1) causes the specific capacity to drop only by 20%, which is the lowest among all high-performing anodic COFs. The majority of the lithium insertion follows an ultrafast diffusion-controlled intercalation (diffusion coefficient, D-Li(+) = 5.48 x 10(-11) cm(2) s(-1)). The absence of strong Li-framework bonds in the density functional theory (DFT) optimized structure supports this reversible intercalation. The discrete monomer of the CON shows a specific capacity of only 140 mA h g(-1) @50 mA g(-1) and no sign of lithium intercalation reveals the crucial role played by the polymeric structure of the CON in this intercalation-assisted conductivity. The potentials mapped using DFT suggest a substantial electronic driving-force for the lithium intercalation. The findings underscore the potential of the designer CON as anode material for Li-ion batteries.

High surface area nanoporous carbon derived from high quality jute from Bangladesh - Khan, Junayet Hossain; Lin, Jianjian; Young, Christine; Matsagar, Babasaheb M.; Wu, Kevin C. W.; Dhepe, Paresh L.; Islam, Md Tofazzal; Rahman, Md Mahbubur; Shrestha, Lok Kumar; Alshehri, Saad M.; Ahamad, Tansir; Salunkhe, Rahul R.; et al. (Materials Chemistry and Physics, 2018)
We report an economically viable and environment-friendly strategy for the preparation of nanoporous carbon (NC) from jute which is one of the most abundant natural fibers produced in Bangladesh and some South Asian countries. Nitrogen adsorption-desorption isotherms, X-ray diffraction, Raman spectroscopy, UV spectroscopy, and scanning/transmission electron microscopy were performed to characterize the obtained NC. Three different types of jute-derived NCs have been synthesized at three different temperatures, 700 degrees C, 800 degrees C and 900 degrees C. The NC prepared at 800 degrees C resulted in a high surface area (981 m(2) g(-2)) and was associated with the retention of the original fibrous shapes. This study shows a promising future for jute as a natural precursor for NCs for a myriad of applications ranging from water purification to gas separation to energy conversion and storage.
Keywords: Adsorbents; Graphitization; Jute; Nanoporous carbons; porous materials

High-performance field emission device utilizing vertically aligned carbon nanotubes-based pillar architectures - Gupta, Bipin Kumar; Kedawat, Garima; Gangwar, Amit Kumar; Nagpal, Kanika; Kashyap, Pradeep Kumar; Srivastava, Shubhda; Singh, Satbir; Kumar, Pawan; Suryawanshi, Sachin R.; Seo, Deok Min; Tripathi, Prashant; More, Mahendra A.; et al. (AIP Advances, 2018)
The vertical aligned carbon nanotubes (CNTs)-based pillar architectures were created on laminated silicon oxide/silicon (SiO2/Si) wafer substrate at 775 degrees C by using water-assisted chemical vapor deposition under low pressure process condition. The lamination was carried out by aluminum (Al, 10.0 nm thickness) as a barrier layer and iron (Fe, 1.5 nm thickness) as a catalyst precursor layer sequentially on a silicon wafer substrate. Scanning electron microscope (SEM) images show that synthesized CNTs are vertically aligned and uniformly distributed with a high density. The CNTs have approximately 2-30 walls with an inner diameter of 3-8 nm. Raman spectrum analysis shows G-band at 1580 cm(-1) and D-band at 1340 cm(-1). The G-band is higher than D-band, which indicates that CNTs are highly graphitized. The field emission analysis of the CNTs revealed high field emission current density (4mA/cm(2) at 1.2V/mu m), low turn-on field (0.6 V/mu m) and field enhancement factor (6917) with better stability and longer lifetime. Emitter morphology resulting in improved promising field emission performances, which is a crucial factor for the fabrication of pillared shaped vertical aligned CNTs bundles as practical electron sources. (c) 2018 Author(s).

In situ base release for pH maintenance can allow shake flasks to better mimic bioreactor performance for CHO cell culture - Maralingannavar, Vishwanathgouda; Shenoy, Bharath R.; Hazarika, Jahnabi; Unnikrishnan, Divya; Prabhu, Anuja; Maity, Sunit; Gadgil, Mugdha (Journal of Chemical Technology & Biotechnology, 2018)
BACKGROUNDShake flasks are widely used for evaluating mammalian cells in suspension. Lack of pH control can contribute to differences in culture performance between them and bioreactors. This study evaluates whether a previously reported in situ base releasing hydrogel (pHmH) to counter pH decrease can enable shake flask cultures to better mimic bioreactor cultures. RESULTSCompared with bioreactor culture, fed-batch cultures of a recombinant Chinese hamster ovary (CHO) cell-line in shake flasks without pHmH showed a decrease in pH to 6.6, accompanied by 40, 60 and 22% lower peak cell density, lactate accumulation, and immunoglobulin G (IgG) titer, respectively. Use of pHmH allowed shake flasks to maintain pH above 6.8 and reduced this difference to 20, 30, and 15%, respectively, thus enabling culture performance in shake flasks to better mimic the bioreactor. IgG glycosylation profiles were similar in identically fed cultures across all three platforms. Application of pHmH hydrogel during clone screening was evaluated by comparing correlation between titers for five recombinant CHO clones in bioreactors and shake flasks with and without pHmH; a higher correlation was found in shake flasks with pHmH than without. CONCLUSIONIn situ base release through hydrogel can allow identically fed fed-batch cultures in shake flasks to better mimic cell growth, lactate accumulation and IgG titers in bioreactors, without additional infrastructure. (c) 2018 Society of Chemical Industry.

Interlayer hydrogen-bonded covalent organic frameworks as high-performance supercapacitors - Halder, Arjun; Ghosh, Meena; Khayum, Abdul M.; Bera, Saibal; Addicoat, Matthew; Sasmal, Himadri Sekhar; Karak, Suvendu; Kurungot, Sreekumar; Banerjee, Rahul (Journal of the American Chemical Society, 2018)
Covalent organic frameworks (COFs) have emerged as promising electrode materials in supercapacitors (SCs). However, their insoluble powder-like nature, poor capacitive performance in pristine form, integrated with inferior electrochemical stability is a primary concern for their long-term use in electrochemical devices. Keeping this in perspective, herein we report a redox active and hydrogen bonded COF with ultrahigh stability in conc. H2SO4 (18 M), conc. HCl (12 M) and NaOH (9 M). The as-synthesized COF fabricated as thin sheets were efficiently employed as a free-standing supercapacitor electrode material using 3 M aq. H2SO4 as an electrolyte. Moreover, the pristine COF sheet showcased outstanding areal capacitance 1600 mF cm(-2) (gravimetric 169 F g(-1)) and excellent cyclic stability (>100 000) without compromising its capacitive performance or Coulombic efficiency. Moreover, as a proof-of-concept, a solid-state supercapacitor device was also assembled and subsequently tested.

Melamine formaldehyde-metal organic gel interpenetrating polymer network derived intrinsic Fe-N-doped porous graphitic carbon electrocatalysts for oxygen reduction reaction - Shijina, Kottarathil; llathvalappil, Rajith; Sumitha, N. S.; Sailaja, G. S.; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchig, Takeo; Hareesh, U. S. (New Journal of Chemistry, 2018)
Fe, N doped porous graphitic carbon electrocatalyst (Fe-MOG-MF-C), obtained by pyrolysis of an Interpenetrating Polymer Network (IPN) comprised of melamine formaldehyde (MF as hard segment) and Metal-Organic Gel (MOG as soft segment), exhibited significant Oxygen Reduction Reaction (ORR) activity in alkaline medium. BET surface area analysis of Fe-MOG-MF-C showed high surface area (821 m(2) g(-1)), while TEM, Raman and XPS results confirmed Fe and N co-doping. Furthermore, a modulated porous morphology with a higher degree of surface area (950 m(2) g(-1)) has been accomplished for the system (Fe-MOG-MFN-C) when aided by a sublimable porogen, such as naphthalene. XPS results further demonstrated that these systems exhibited a better degree of distribution of graphitic N and an onset potential value of 0.91 V vs. RHE in 0.1 M KOH solution following an efficient four-electron ORR pathway. The electrocatalytic activity of Fe-MOG-MFN-C is superior to that of Fe-MOG-MF-C by virtue of its higher graphitic N content and surface area. Thus, the study presents a new class of IPN derived MF-MOG nanocomposites with the potential to generate extended versions of in situ Fe-N doped porous graphitic carbon structures with superior ORR activity.

Methanol oxidation reaction on Pt based electrocatalysts modified ultramicroelectrode (UME): Novel electrochemical method for monitoring rate of CO adsorption - Joshi, Vrushali S.; Poudyal, Durgasha C.; Satpati, Ashis K.; Patil, Kashinath R.; Haram, Santosh K. (Electrochimica Acta, 2018)
Novel fast scan cyclic voltammetry (FSCV) based method has been developed to study methanol oxidation reaction on Pt nanoparticles (PtNPs) based catalysts. To support the cyclic voltammetry measurements at higher scan rates, micron-sized electrode geometries viz. PtNPs loaded on the single strand of carbon fiber (SSCF) and PtNPs decorated multiwalled carbon nanotubes (MWCNTs), loaded on commercial ultramicroelectrode (UME) have been employed. Deconvolution of the voltammograms obtained during methanol oxidation revealed three major anodic peaks. These peaks have been plausibly attributed to the electron transfer processes viz. methanol oxidation into CO/other intermediates, oxidation of these intermediates into CO2 and adsorption of un-oxidized CO on the catalyst surface. The peaks due to CO adsorption have been elucidated as a function of scan rates. The area under the peak as a function of time has been correlated to the rate of CO adsorption on these catalysts. The average rate of CO adsorption in methanol oxidation at Pt-SSCF and Pt-MWCNTs/UME are estimated to be 1.08 x 10(-8) mol cm(-2) s(-1) and 13.5 x 10(-8) mol cm(-2) s(-1) respectively. This novel method is proposed to generalize to any electrocatalysts of interest. (C) 2018 Published by Elsevier Ltd.

Morphological ensembles of N-doped porous carbon derived from ZIF-8/Fe-graphene nanocomposites: processing and electrocatalytic studies - Thomas, Minju; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (ChemistrySelect, 2018)
Engineering the active site density of porous carbon catalysts for enhanced electrocatalytic activity is the current focus in the quest for economically viable fuel cells. Herein, we synthesise ZIF-8/Fe-graphene composites for the formation of N and Fe co-doped carbon with diverse morphologies ranging from tubes and sheets to frameworks of carbon. A synthetic strategy involving the one pot synthesis of ZIF-8 based composites is accomplished by the reaction of 2-methylimidazole with mixed Zn/Fe salt solution containing graphene dispersions. The high temperature heat treatment of this precursor mix yielded micro-meso porous architectures of N, Fe co-doped carbon with dispersions of Fe/Fe3C. An onset potential value of 0.95 V and a half-wave potential of 0.82 V coupled with excellent durability and stability in alkaline medium indicated improved electrocatalytic performances over its commercial Pt/C counterpart. The appreciable electrocatalytic properties of the synthesized carbon are attributed to its morphological diversity, hybrid structure, high N doping and its heteroporous characteristics. The dispersed Fe/Fe3C and FeNx sites facilitated enhanced oxygen adsorption and the graphene inclusions in the composite provided retention of high nitrogen contents.
Keywords: electrocatalyst; fuel cell; N- Fe co-doped carbon; oxygen reduction reaction; ZIF-8

Multistimuli-responsive interconvertible low-molecular weight metallohydrogels and the in situ entrapment of CdS quantum dots therein - Bera, Saibal; Chakraborty, Amit; Karak, Suvendu; Halder, Arjun; Chatterjee, Soumyajyoti; Saha, Subhadeep; Banerjee, Rahul (Chemistry of Materials, 2018)
Two low molecular weight metallohydrogels (ZALA and CALA) have been synthesized from an amino-acid based ligand precursor (LA) and two different metal salts [zinc acetate dihydrate (ZA) and cadmium acetate dihydrate (CA), respectively. These two hydrogels show a unique chemically stimulated interconversion to each other via a reversible gel-sol gel pathway. This programmable gel-sol reversible system satisfies logic operations of a basic Boolean logic (INHIBIT) gate. Also, these hydrogels can be degraded into different MOF phases at room temperature spontaneously or in the presence of chloride and bromide salts (NaCl and NaBr.). CdS quantum dots can be grown inside the CALA gel matrix (CdS@CALA) in the presence of small amount of Na2S. This CdS doped gel exhibits time dependent tunable emission (white to yellow to orange) as a consequence of a slow agglomeration process of the entrapped quantum dots inside the gel matrix. This luminescence property also reflects the corresponding gel derived MOFs (obtained either by self-degradation of CdS@CALA or via anion induction) as well. This, to the best of our knowledge, is probably the simplest way to make a CdS quantum dot based composite material where CdS is entrapped within the gel and the gel-derived MOF matrix.

Phenazine-containing poly(phenylenevinylene): a new polymer with impressive field emission properties - Chhatre, Shraddha; Ichake, Amol; Harpale, Kashmira; Patil, Sumati; Deshpande, Aparna; More, Mahendra; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2018)
Phenazine-containing poly(phenylenevinylene) (P(PHN-PV)) was synthesized using Wittig-Horner polycondensation of the appropriately designed monomers viz. 5,10-dioctyl-5,10-dihydrophenazine-2,7-dicarbaldehyde and tetraethyl ((2,5-bis((2-ethylhexyl) oxy)-1,4 phenylene) bis(methylene)) bis(phosphonate). The design embraces the specific motivation of incorporating the nitrogen-containing heterocycle viz. .phenazine in poly(phenylenevinylene) backbone. P(PHN-PV) exhibited reversible redox properties. In the field emission measurements performed on the film of P(F'HN-PV), the turn-on field was observed to be 1.93 V/mu m for the current density of 10 mu A/cm(2). The maximum current density of similar to 4.87 mA/cm(2) was achieved at the applied field of 3.84 V/mu m. The emission current showed impressive stability for 6 h at a constant current of 1 mu A (current density of about 20 mu A/cm(2)). These results emphasize the role of phenazine heterocycle with lone pair of electrons on nitrogen in lowering the oxidation onset and in turn reduction of the turn-on voltage.
Keywords: field emission; Phenazine; Poly(phenylenevinylene)

Polycrystalline MnGe2 thin films on InAs(001) substrates - Gutierrez-Naranjo, David; Holguin-Momaca, Jose T.; Solis-Canto, Oscar O.; Gupta, Preeti; Poddar, Pankaj; Espinosa Magana, Francisco; Olive-Mendez, Sion F. (Thin Solid Films, 2018)
We report on the growth of MnGe2 thin films on InAs(001) substrates using radio frequency-magnetron cosputtering. Polycrystalline thin films were obtained at a substrate temperature of 353 K. X-ray diffractometry was used to identify the tetragonal MnGe2 phase (space group 14/mcm). Measurements of the magnetic field and temperature dependence of the magnetization revealed that the MnGe2 thin films are ferromagnetic with a magnetization of 280 kAm(-1) and a Curie temperature of 62 K. Additionally, an antiferromagnetic component is observed at low temperatures, which may arise atomic disorder at the grain boundaries between MnGe2 crystallites.

Polysulfide-triggered fluorescent indicator suitable for super-resolution microscopy and application in imaging - Hoskere, Anila A.; Sreedharan, Sreejesh; Ali, Firoj; Smythe, Carl G.; Thomas, Jim A.; Das, Amitava (Chemical Communications, 2018)
A new physiologically benign and cell membrane permeable BODIPY based molecular probe, MB-S-n, specifically senses intracellular hydrogen polysulfides (H2Sn, n > 1) localized in the endoplasmic reticulum. This reagent is suitable for mapping the intracellular distribution of H2Sn by wide-field as well as super-resolution Structured Illumination Microscopy (SIM).

Preparation of colourless phosphate glass by stabilising higher Fe[II] in microwave heating - Mandal, Ashis K.; Mandal, B.; Illath, Kavya; Ajithkumar, T. G.; Halder, A.; Sinha, P. K.; Sen, Ranjan (Scientific Reports, 2018)
Iron impurity in raw material remains a major challenge in producing colourless glass. In this investigation, we report microwave (MW) heating capable of altering Fe-redox ratio (Fe2+/Sigma Fe) enabling preparation of colourless phosphate glass. The effect of Sn concentration in retention of Fe[II] in glass melted in MW was compared with conventional glasses. Colourimetric study developing Fe2+-ferrozine colour complex reveals Fe-redox ratio >= 0.49 required to obtain colourless phosphate glass. In microwave heating, addition of 1 wt.% Sn metal powder can impart the desired effect whereas addition of 1.9 wt.% Sn metal powder is required in conventional heating. The correlation equation of Fe-redox ratio with concentration of Sn metal is found to be different in microwave and conventional heating. Thus, exploiting this different redox changes in MW heating optical properties can be tailored. Preservation of higher Fe[II] in MW melted glass is also confirmed by XPS and TGA. P-31 MAS NMR spectra suggest that transition from cross linked ultra phosphate to linear polymer metaphosphate network in incorporation of Sn is found different in glass prepared adopting microwave irradiation. (27)A1 MAS NMR spectra suggest higher relative content of Al6+ in glass obtained from MW heating. Energy consumption analysis revels 3.4 kWh in MW heating while 14 kWh in conventional glass melting using resistance heating. Further, glass melting in MW can be completed within 2 h unlike similar to 5 h needed in conventional. MW heating plays a significant role in improving properties to make colourless phosphate glass in addition to significant energy and time saving.

Repeated photoporation with graphene quantum dots enables homogeneous labeling of live cells with extrinsic markers for fluorescence microscopy - Liu, Jing; Xiong, Ranhua; Brans, Toon; Lippens, Saskia; Parthoens, Eef; Zanacchi, Francesca Cella; Magrassi, Raffaella; Singh, Santosh K.; Kurungot, Sreekumar; Szunerits, Sabine; Bove, Hannelore; Ameloot, Marcel; et al. (Light-Science & Applications, 2018)
In the replacement of genetic probes, there is increasing interest in labeling living cells with high-quality extrinsic labels, which avoid over-expression artifacts and are available in a wide spectral range. This calls for a broadly applicable technology that can deliver such labels unambiguously to the cytosol of living cells. Here, we demonstrate that nanoparticle-sensitized photoporation can be used to this end as an emerging intracellular delivery technique. We replace the traditionally used gold nanoparticles with graphene nanoparticles as photothermal sensitizers to permeabilize the cell membrane upon laser irradiation. We demonstrate that the enhanced thermal stability of graphene quantum dots allows the formation of multiple vapor nanobubbles upon irradiation with short laser pulses, allowing the delivery of a variety of extrinsic cell labels efficiently and homogeneously into live cells. We demonstrate high-quality time-lapse imaging with confocal, total internal reflection fluorescence (TIRF), and Airyscan super-resolution microscopy. As the entire procedure is readily compatible with fluorescence (super resolution) microscopy, photoporation with graphene quantum dots has the potential to become the long-awaited generic platform for controlled intracellular delivery of fluorescent labels for live-cell imaging.

Single pot selective hydrogenation of furfural to 2-methylfuran over carbon supported iridium catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K-W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Green Chemistry, 2018)
Various iridium supported carbon catalysts were prepared and screened for the direct hydrogenation of furfural (FFR) to 2-methyl furan (2-MF). Amongst these, 5% Ir/C showed excellent results with complete FFR conversion and highest selectivity of 95% to 2-MF at a very low H-2 pressure of 100 psig. Metallic (Ir degrees) and oxide (IrO2) phases of Ir catalyzed the first step hydrogenation involving FFR to FAL and subsequent hydrogenation to 2-MF, respectively. This was confirmed by XPS analysis and some control experiments. At a low temperature of 140 degrees C, almost equal selectivities of FAL (42%) and 2-MF (43%) were observed, while the higher temperature (220 degrees C) favored selective hydrodeoxygenation. At optimized temperature, 2-MF was formed selectively while higher pressure and higher catalyst loading favored ring hydrogenation of furfural rather than side chain hydrogenation. With the combination of several control experimental results and detailed catalyst characterization, a plausible reaction pathway has been proposed for the selective formation of 2-MF. The selectivity to various other products in FFR hydrogenation can be manipulated by tailoring the reaction conditions over the same catalyst.

Single step, phase controlled, large scale synthesis of ferrimagnetic iron oxide polymorph nanoparticles by thermal plasma route and their rheological properties - Raut, Suyog A.; Mutadak, Pallavi R.; Kumar, Shiv; Kanhe, Nilesh S.; Huprikar, Sameer; Pol, Harshawardhan V.; Phase, Deodatta M.; Bhoraskar, Sudha V.; Mathe, Vikas L. (Journal of Magnetism and Magnetic Materials, 2018)
In this paper we report single step large scale synthesis of highly crystalline iron oxide nanoparticles viz. magnetite (Fe3O4) and maghemite (gamma-Fe2O3) via gas phase condensation process, where micron sized iron metal powder was used as a precursor. Selective phases of iron oxide were obtained by variation of gas flow rate of oxygen and hence partial pressure of oxygen inside the plasma reactor. Most of the particles were found to possesses average crystallite size of about 20-30 nm. The DC magnetization curves recorded indicate almost super-paramagnetic nature of the iron oxide magnetic nanoparticles. Further, iron oxide nanoparticles were analyzed using Raman spectroscopy, X-ray photoelectron spectroscopy and Mossbauer spectroscopy. In order to explore the feasibility of these nanoparticles for magnetic damper application, rheological studies have been carried out and compared with commercially available Carbonyl Iron (CI) particles. The nanoparticles obtained by thermal plasma route show improved dispersion which is useful for rheological applications. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Iron oxide; magnetic properties; Nano-crystalline materials; Rheological properties; Thermal plasma

Specific stereoisomeric conformations determine the drug potency of cladosporin scaffold against malarial parasite - Das, Pronay; Babbar, Palak; Malhotra, Nipun; Sharma, Manmohan; Jachak, Goraknath R.; Gonnade, Rajesh G.; Shanmugam, Dhanasekaran; Harlos, Karl; Yogavel, Manickam; Sharma, Amit; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2018)
The dependence of drug potency on diastereomeric configurations is a key facet. Using a novel general divergent synthetic route for a three-chiral center antimalarial natural product cladosporin, we built its complete library of stereoisomers (cladologs) and assessed their inhibitory potential using parasite-, enzyme-, and structure-based assays. We show that potency is manifest via tetrahyropyran ring conformations that are housed in the ribose binding pocket of parasite lysyl tRNA synthetase (KRS). Strikingly, drug potency between top and worst enantiomers varied 500-fold, and structures of KRS-cladolog complexes reveal that alterations at C3 and C10 are detrimental to drug potency whereas changes at C3 are sensed by rotameric flipping of glutamate 332. Given that scores of antimalarial and anti-infective drugs contain chiral centers, this work provides a new foundation for focusing on inhibitor stereochemistry as a facet of antimicrobial drug development.

Structural and functional analysis of UGT92G6 suggests an evolutionary link between mono- and disaccharide glycoside-forming transferases - Huang, Fong-Chin; Giri, Ashok; Daniilidis, Melina; Sun, Guangxin; Härtl, Katja; Hoffmann, Thomas; Schwab, Wilfried (Plant and Cell Physiology, 2018)
Glycosylation mediated by UDP-dependent glycosyltransferase (UGT) is one of the most common reactions for the biosynthesis of small molecule glycosides. As glycosides have various biological roles, we characterized UGT genes from grapevine (Vitis vinifera). In silico analysis of VvUGT genes that were highly expressed in leaves identified UGT92G6 which showed sequence similarity to both monosaccharide and disaccharide glucoside-forming transferases. The recombinant UGT92G6 glucosylated phenolics, among them caffeic acid, carvacrol, eugenol and raspberry ketone, and also accepted geranyl glucoside and citronellyl glucoside. Thus, UGT92G6 formed mono- and diglucosides in vitro from distinct compounds. The enzyme specificity constant Vmax/Km ratios indicated that UGT92G6 exhibited the highest specificity towards caffeic acid, producing almost equal amounts of the 3- and 4-O-glucoside. Transient overexpression of UGT92G6 in Nicotiana benthamiana leaves confirmed the production of caffeoyl glucoside; however, the level of geranyl diglucoside was not elevated upon overexpression of UGT92G6, even after co-expression of genes encoding geraniol synthase and geraniol UGT to provide sufficient precursor. Comparative sequence and 3-D structure analysis identified a sequence motif characteristic for monoglucoside-forming UGTs in UGT92G6, suggesting an evolutionary link between mono- and disaccharide glycoside UGTs. Thus, UGT92G6 functions as a mono- and diglucosyltransferase in vitro, but acts as a caffeoyl glucoside UGT in N. benthamiana.

Structural elucidation of NASICON (Na3Al2P3O12) based glass electrolyte materials: effective influence of boron and gallium - Allu, Amarnath R. (RSC Advances, 2018)
Understanding the conductivity variations induced by compositional changes in sodium super ionic conducting (NASICON) glass materials is highly relevant for applications such as solid electrolytes for sodium (Na) ion batteries. In the research reported in this paper, NASICON-based NCAP glass (Na2.8Ca0.1Al2P3O12) was selected as the parent glass. The present study demonstrates the changes in the Na+ ion conductivity of NCAP bulk glass with the substitution of boron (NCABP: Na2.8Ca0.1Al2B0.5P2.7O12) and gallium (NCAGP: Na2.8Ca0.1Al2Ga0.5P2.7O12) for phosphorus and the resulting structural variations found in the glass network. For a detailed structural analysis of NCAP, NCABP and NCAGP glasses, micro-Raman and magic angle spinning-nuclear magnetic resonance (MAS-NMR) spectroscopic techniques (for 31P, 27Al, 23Na, 11B and 71Ga nuclei) were used. The Raman spectrum revealed that the NCAP glass structure is more analogous to the AlPO4 mesoporous glass structure. The 31P MAS-NMR spectrum illustrated that the NCAP glass structure consists of a high concentration of Q0 (3Al) units, followed by Q0 (2Al) units. The 27Al MAS-NMR spectrum indicates that alumina exists at five different sites, which include AlO4 units surrounded by AlO6 units, Al(OP)4, Al(OP)5, Al(OAl)6 and Al(OP)6, in the NCAP glass structure. The 31P, 27Al and 11B MAS-NMR spectra of the NCABP glass revealed the absence of B–O–Al linkages and the presence of B3–O–B4–O–P4 linkages which further leads to the formation of borate and borophosphate domains. The 71Ga MAS-NMR spectrum suggests that gallium cations in the NCAGP glass compete with the alumina cations and occupy four (GaO4), five (GaO5) and six (GaO6) coordinated sites. The Raman spectrum of NCAGP glass indicates that sodium cations have also been substituted by gallium cations in the NCAP glass structure. From impedance analysis, the dc conductivity of the NCAP glass (∼3.13 × 10−8 S cm−1) is slightly decreased with the substitution of gallium (∼2.27 × 10−8 S cm−1) but considerably decreased with the substitution of boron (∼1.46 × 10−8 S cm−1). The variation in the conductivity values are described based on the structural changes of NCAP glass with the substitution of gallium and boron.

Superprotonic conductivity in flexible porous covalent organic framework membranes - Banerjee, Rahul; Sasmal, Himadri Sekhar; Harshitha, B. A.; Bhange, Siddheshwar; Karak, Suvendu; Halder, Arjun; Kurungot, Sreekumar (Angewandte Chemie, 2018)
Poor mechanical stability of the polymer electrolyte membranes (PEMs) remains one of the bottlenecks towards improving the performance of the proton exchange membrane (PEM) fuel cells. The present work proposes a unique way to utilize crystalline covalent organic frameworks (COFs) as a self‐standing, highly flexible membrane to further boost the mechanical stability of the material without compromising its innate structural characteristics. The as‐synthesized p‐toluene sulfonic acid loaded covalent organic framework membranes (COFMs) showing the highest proton conductivity amongst all crystalline porous organic polymeric materials reported till date, as high as 7.8 x 10‐2 S cm‐1, have been further tested under real PEM operating conditions to ascertain their practical utilization as proton exchange membranes. Attainment of 24 mW cm‐2 power density, which is the highest among COFs and MOFs, highlights the possibilityof using a COF membrane over the other state‐of‐the‐art crystalline porous polymeric materials reported to date.

Synthetic control on structure/dimensionality and photophysical properties of low dimensional organic lead bromide perovskite - Haris, Muhammed P. U.; Bakthavatsalam, Rangarajan; Shaikh, Samir; Kore, Bhushan P.; Moghe, Dhanashree; Gonnade, Rajesh G.; Sarma, D. D.; Kabra, Dinesh; Kundu, Janardan (Inorganic chemistry, 2018)
Low dimensional lead halide perovskites have attracted huge research interest due to their structural diversity and remarkable photophysical properties. The ability to controllably change dimensionality/structure of perovskites remains highly challenging. Here, we report synthetic control on structure/dimensionality of ethylenediammonium (ED) lead bromide perovskite from a two dimensionally networked (2DN) sheet to a one dimensionally networked (1DN) chain structure. Intercalation of solvent molecules into the perovskite plays a crucial role in directing the final dimensionality/structure. This change in dimensionality reflects strongly in the observed differences in photophysical properties. Upon UV excitation, the 1DN structure emits white light due to easily formed “self-trapped” excitons. 2DN perovskites show band edge blue emission (∼410 nm). Interestingly, Mn2+ incorporated 2DN perovskites show a highly red-shifted Mn2+ emission peak at ∼670 nm. Such a long wavelength Mn2+ emission peak is unprecedented in the perovskite family. This report highlights the synthetic ability to control the dimensionality/structure of perovskite and consequently its photophysical properties.

Total synthesis and biological evaluation of cell adhesion inhibitors peribysin A and B: structural revision of peribysin B - Kalmode, Hanuman P.; Handore, Kishor L.; Rajput, Raveena; Shaikh, Samir R.; Gonnade, Rajesh G.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (Organic letters, 2018)
Total synthesis of potent cell-adhesion inhibitors peribysins A and B has been accomplished for the first time in racemic form. A Diels-Alder/aldol sequence to build the skeleton and decoration of the desired functionalities of the targeted natural products using highly stereoselective operations are the highlights. The structures of synthesized peribysins were fully characterized using spectral data and single-crystal X-ray analysis. Through this total synthesis, the initially proposed structure of peribysin B has been revised. Furthermore, the cell-adhesion inhibition potential of the scaffold (two peribysins + three analogues) was confirmed using anti-adhesion assay.

Tracing the biosynthetic origin of limonoids and their functional groups through stable isotope labeling and inhibition in neem tree (Azadirachta indica) cell suspension - Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Pandreka, Avinash; Kumar, Ashish; Nandikol, Sharvani S.; Haldar, Saikat; Thulasiram, Hirekodathakallu V. (BMC Plant Biology, 2018)
Background Neem tree serves as a cornucopia for triterpenoids called limonoids that are of profound interest to humans due to their diverse biological activities. However, the biosynthetic pathway that plant employs for the production of limonoids remains unexplored for this wonder tree. Results Herein, we report the tracing of limonoid biosynthetic pathway through feeding experiments using C-13 isotopologues of glucose in neem cell suspension. Growth and development specific limonoid spectrum of neem seedling and time dependent limonoid biosynthetic characteristics of cell lines were established. Further to understand the role of mevalonic acid (MVA) and methylerythritol phosphate (MEP) pathways in limonoid biosynthesis, Ultra Performance Liquid Chromatography (UPLC)- tandem mass spectrometry based structure-fragment relationship developed for limonoids and their isotopologues have been utilized. Analyses of labeled limonoid extract lead to the identification of signature isoprenoid units involved in azadirachtin and other limonoid biosynthesis, which are found to be formed through mevalonate pathway. This was further confirmed by treatment of cell suspension with mevinolin, a specific inhibitor for MVA pathway, which resulted in drastic decrease in limonoid levels whereas their biosynthesis was unaffected with fosmidomycin mediated plastidial methylerythritol 4-phosphate (MEP) pathway inhibition. This was also conspicuous, as the expression level of genes encoding for the rate-limiting enzyme of MVA pathway, 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGR) was comparatively higher to that of deoxyxylulose-phosphate synthase (DXS) of MEP pathway in different tissues and also in the in vitro grown cells. Thus, this study will give a comprehensive understanding of limonoid biosynthetic pathway with differential contribution of MVA and MEP pathways. Conclusions Limonoid biosynthesis of neem tree and cell lines have been unraveled through comparative quantification of limonoids with that of neem tree and through C-13 limonoid isotopologues analysis. The undifferentiated cell lines of neem suspension produced a spectrum of C-seco limonoids, similar to parental tissue, kernel. Azadirachtin, a C-seco limonoid is produced in young tender leaves of plant whereas in the hard mature leaves of tree, ring intact limonoid nimocinol accumulates in high level. Furthermore, mevalonate pathway exclusively contributes for isoprene units of limonoids as evidenced through stable isotope labeling and no complementation of MEP pathway was observed with mevalonate pathway dysfunction, using chemical inhibitors.

Ultrastable imine-based covalent organic frameworks for sulfuric acid recovery: an effect of interlayer hydrogen bonding - Halder, Arjun; Karak, Suvendu; Addicoat, Matthew; Bera, Saibal; Chakraborty, Amit; Kunjattu, Shebeeb H.; Pachfule, Pradip; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2018)
A rapid and scalable synthesis of six new imine-linked highly porous and crystalline COFs is presented that feature exceptionally high chemical stability in harsh environments including conc. H2SO4 (18M), conc. HCl (12M), and NaOH (9M). This is because of the presence of strong interlayer C-H center dot center dot center dot N hydrogen bonding among the individual layers, which provides significant steric hindrance and a hydrophobic environment around the imine (-C=N-) bonds, thus preventing their hydrolysis in such an abrasive environment. These COFs were further converted into porous, crystalline, self-standing, and crack-free COF membranes (COFMs) with extremely high chemical stability for their potential applications for sulfuric acid recovery. The as-synthesized COFMs exhibit unprecedented permeance for acetonitrile (280 Lm(-2) h(-1) bar(-1)) and acetone (260 Lm(-2) h(-1) bar(-1)).

Understanding conformational dynamics of complex lipid mixtures relevant to biology - Friedman, Ran; Khalid, Syma; Aponte-Santamaria, Camilo; Arutyunova, Elena; Becker, Marlon; Boyd, Kevin J.; Christensen, Mikkel; Coimbra, Joao T. S.; Concilio, Simona; Daday, Csaba; van Eerden, Floris J.; Fernandes, Pedro A.; et al. (Journal of membrane biology, 2018)
This is a perspective article entitled "Frontiers in computational biophysics: understanding conformational dynamics of complex lipid mixtures relevant to biology" which is following a CECAM meeting with the same name.

WRKY1 acts as a key component improving resistance against Alternaria solani in wild tomato, Solanum arcanum Peralta - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Biotechnology Journal, 2018)
Early blight (EB), caused by Alternaria solani, is a major threat to global tomato production. In comparison with cultivated tomato (Solanum lycopersicum), a wild relative, S.arcanum exhibits strong resistance against EB. However, molecular cascades operating during EB resistance in wild or cultivated tomato plants are largely obscure. Here, we provide novel insight into spatio-temporal molecular events in S.arcanum against A.solani. Transcriptome and co-expression analysis presented 33-WRKYs as promising candidates of which 12 SaWRKYs displayed differential expression patterns in resistant and susceptible accessions during EB disease progression. Among these, SaWRKY1 exhibited induced expression with significant modulation in xyloglucan endotrans hydrolase 5 (XTH5) and MYB2 expressions that correlated with the disease phenotypes. Electro-mobility shift assay confirmed physical interaction of recombinant SaWRKY1 to SaXTH5 and SaMYB2 promoters. Comparative WRKY1 promoter analysis between resistant and susceptible plants revealed the presence of crucial motifs for defence mechanism exclusively in resistant accession. Additionally, many defence-related genes displayed significant expression variations in both the accessions. Further, WRKY1 overexpressing transgenic plants exhibited higher levels of EB resistance while RNAi silencing lines had increased susceptibility to A.solani with altered expression of XTH5 and MYB2. Overall, these findings demonstrate the positive influence of WRKY1 in improving EB resistance in wild tomato and this could be further utilized as a potential target through genetic engineering to augment protection against A.solani in crop plants.
Keywords: Alternaria solani; early blight; Solanum arcanum; Tomato; WRKY1; XTH5

Azadirachtin-A from azadirachta indica impacts multiple biological targets in cotton bollworm helicoverpa armigera - Dawkar, Vishal V.; Barage, Sagar H.; Barbole, Ranjit S.; Fatangare, Amol; Grimalt, Susana; Haldar, Saikat; Heckel, David G.; Gupta, Vidya S.; Thulasiram, Hirekodathakallu V.; Svatos, Ales.; Giri, Ashok P. (ACS Omega, 2019)
Azadirachtin-A (AzaA) from the Indian neem tree (Azadirachta indica) has insecticidal properties; however, its molecular mechanism remains elusive. The ``targeted and nontargeted proteomic profiling'', metabolomics, matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) imaging, gene expression, and in silico analysis provided clues about its action on Helicoverpa armigera. Fourth instar H. armigera larvae fed on AzaA-based diet (AzaD) suffered from significant mortality, growth retardation, reduced larval mass, complications in molting, and prolonged development. Furthermore, death of AzaD-fed larvae was observed with various phenotypes like bursting, blackening, and half-molting. Liquid chromatography-mass spectrometry (LC-MS) data showed limited catabolic processing of ingested AzaA and dramatic alternations of primary metabolism in H. armigera. MALDI-TOF imaging indicated the presence of AzaA in midgut of H. armigera. In the gut, out of 79 proteins identified, 34 were upregulated, which were related to digestion, immunity, energy production, and apoptosis mechanism. On the other hand, 45 proteins were downregulated, including those from carbohydrate metabolism, lipid metabolism, and energy transfer. In the hemolymph, 21 upregulated proteins were reported to be involved in immunity, RNA processing, and mRNA-directed protein synthesis, while 7 downregulated proteins were implicated in energy transfer, hydrolysis, lipid metabolism, defense mechanisms, and amino acid storage-related functions. Subsequently, six target proteins were identified using labeled AzaA that interacted with whole insect proteins. In silico analysis suggests that AzaA could be efficiently accommodated in the hydrophobic pocket of juvenile hormone esterase and showed strong interaction with active site residues, indicating plausible targets of AzaA in H. armigera. Quantitative polymerase chain reaction analysis suggested differential gene expression patterns and partly corroborated the proteomic results. Overall, data suggest that AzaA generally targets more than one protein in H. armigera and hence could be a potent biopesticide.

Carbon derived from soft pyrolysis of a covalent organic framework as a support for small-sized RuO2 showing exceptionally low overpotential for oxygen evolution reaction - Chakraborty, Debanjan; Nandi, Shyamapada; Illathvalappil, Rajith; Mullangi, Dinesh; Maity, Rahul; Singh, Santosh K.; Haldar, Sattwick; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (ACS Omega, 2019)
Electrochemical water splitting is the most energy-efficient technique for producing hydrogen and oxygen, the two valuable gases. However, it is limited by the slow kinetics of the anodic oxygen evolution reaction (OER), which can be improved using catalysts. Covalent organic framework (COF)-derived porous carbon can serve as an excellent catalyst support. Here, we report high electrocatalytic activity of two composites, formed by supporting RuO2 on carbon derived from two COFs with closely related structures. These composites catalyze oxygen evolution from alkaline media with overpotentials as low as 210 and 217 mV at 10 mA/cm(2), respectively. The Tafel slopes of these catalysts (65 and 67 mV/dec) indicate fast kinetics compared to commercial RuO2. The observed activity is the highest among all RuO2-based heterogeneous OER catalysts-a touted benchmark OER catalyst. The high catalytic activity arises from the extremely small-sized (similar to 3-4 nm) RuO2 nanoparticles homogeneously dispersed in a micro-mesoporous (BET = 517 m(2)/g) COF-derived carbon. The porous graphenic carbon favors mass transfer, while its N-rich framework anchors the catalytic nanoparticles, making it highly stable and recyclable. Crucially, the soft pyrolysis of the COF enables the formation of porous carbon and simultaneous growth of small RuO2 particles without aggregation.

Covalent self-assembly in two dimensions: connecting covalent organic framework nanospheres into crystalline and porous thin films - Sasmal, Himadri Sekhar; Halder, Arjun; Kunjattu, Shebeeb; Dey, Kaushik; Nadol, Athulya; Ajithkumar, Thalasseril G.; Bedadur, Prachiti Ravindra; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Insolubility of covalent organic frameworks (COFs) in organic solvents is one of the major obstacles for the potential application of these extended networks such as drug delivery, sensing, optoelectronics, and semiconductor device fabrication. The present work proposes a unique way to make uniform, solution-processable, crystalline, and porous COF nanospheres directly from the homogeneous solution of amine and aldehyde via spatial and temporal control of the nucleation and growth. This strategy of direct nucleation simultaneously showcases the caliber to tune the size of the COF nanospheres from 25 to 570 nm. We have also demonstrated the concept of mesoscale covalent self-assembly of those solution-processable COF nanospheres in the liquid-liquid interface (DCM-water bilayer) for the very first time, transmuting them into self-standing COF thin films with long-range ordered arrangements in two dimensions. The crystalline and porous (with TpAzo showing highest S-BET of 1932 m(2) g(-1)) free-standing COF thin films could be fabricated in a wide range of thicknesses from as low as 21 nm to as high as 630 nm. Both beta-ketoenamine (TpAzo, TpDPP) and imine (TpOMeAzo, TpOMeDPP) linked COF thin films have been synthesized via mesoscale covalent self-assembly of the solution-processable COF nanospheres illustrating the generality of this eloquent methodology. Further, the solution processability has been tested and utilized to cast COF thin films uniformly in the inner and outer surface of an alumina hollow fiber membrane. The COF thin film-alumina hollow fiber membrane composites have showcased promising selective molecular separation of He and O-2, He and CO2, and He and N-2.

Cu/Cu2O nanoparticles supported on a phenol-pyridyl COF as a heterogeneous catalyst for the synthesis of unsymmetrical diynes via glaser-hay coupling - Chakraborty, Debanjan; Nandi, Shyamapada; Mullangi, Dinesh; Haldar, Sattwick; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (ACS Applied Materials & Interfaces, 2019)
Covalent organic frameworks (COFs) are a new class of porous crystalline polymers with a modular construct that favors fiinctionalization. COF pores can be used to grow nanoparticles (nPs) with dramatic size reduction, stabilize them as dispersions, and provide excellent nP access. Embedding substrate binding sites in COFs can generate host-guest synergy, leading to enhanced catalytic activity. In this report, Cu/Cu2O nPs (2-3 nm) are grown on a COF, which is built by linking a phenolic trialdehyde and a triamine through Schiff bonds. Their micropores restrict the nP to exceptionally small sizes (similar to 2-3 nm), and the pore walls decorated with strategically positioned hydrogen-bonding phenolic groups anchor the substrates via hydrogen-bonding, whereas the basic pyridyl sites serve as cationic species to stabilize the [CuclusterCl2](2-) type reactive intermediates. This composite catalyst shows high activity for Glaser-Hay heterocoupling reactions, an essential 1,3-diyne yielding reaction with widespread applicability in organic synthesis and material science. Despite their broad successes in homocoupled products, preparation of unsymmetrical 1,3-diynes is challenging due to poor selectivity. Here, our COF-based Cu catalyst shows elevated selectivity toward heterocoupling product(s) (Cu nP loading 0.0992 mol %; turn over frequency: similar to 4S-50; turn over number: similar to 17S-190). The reversible redox activity at the Cu centers has been demonstrated by carrying out X-ray photoelectron spectroscopy on the frozen reactions, whereas the crucial interactions between the substrates and the binding sites in their optimized configurations have been modeled using density functional theory methods. This report emphasizes the utility of COFs in developing a heterogeneous catalyst for a truly challenging organic heterocoupling reaction.
Keywords: Copper nanoparticles; Covalent organic framework; Glaser-Hay heterocoupling; heterogeneous catalysis; unsymmetrical diynes

Density functional theory-based study of the magnetic and optical properties of PbMO3 (M = Cr, Fe) using the modified BeckeJohnson mBJ functional - Mahmood, Q.; Hassan, M.; Bhamu, K.C.; Yaseen, M.; Ramay, S.M.; Mahmood, A. (Journal of Physics and Chemistry of Solids, 2019)
In this study, we employed the density functional theory (DFT) approach using WIEN2k code to study the magnetic and optical behaviors of PbCrO3 and PbFeO3 perovskites in both cubic and tetragonal phases. We determined the stability of the ferromagnetic state in terms of the enthalpy of formation, the half-metallic behavior, and spin polarization. The origin and nature of the ferromagnetic state were attributed to John-Teller distortion and a super-exchange mechanism. Comparisons of the calculated crystal field, John-Teller distortion, and exchange energies indicated the stability of the ferromagnetic nature. Due to strong hybridization, the magnetic moment was reduced at the Cr/Fe sites but generated at the nonmagnetic sites. The optical characteristics were explained by in-depth analyses of the polarization, plasmonic resonance, transparency, and other features in terms of the computed parameters.

Draft genome sequence of freshwater-derived streptomyces sp. strain BPSDS2, isolated from damte stream, northeast India - Zothanpuia; Passari, Ajit Kumar; Deka, Vinay; Rajput, Lakshmi P. M.; Priya, Purbajyoti; Dharne, Mahesh; Dastager, Syed; Mathew, Oommen K.; Hashem, Abeer; Abd_ Allah, Elsayed Fathi; Singh, Bhim Pratap (American Society for Microbiology, 2019)
We report the draft genome sequence of Streptomyces sp. strain BPSDS2, isolated from freshwater sediments in Northeast India. The draft genome has a size of 8.27 Mb and 7,559 protein-coding sequences.

Efficient removal of Arsenic (III) by novel micro and nano dialdehyde cellulose-cysteine complex extracted from wood pulp cellulose - Chen, Hui; Sharma, Sunil; Sharma, Priyanka; Yeh, Heidi; Hsiao, Benjamin (Abstracts of Papers of the American Chemical Society, 2019)

Efficient synergetic combination of H-USY and SnO2 for direct conversion of glucose into ethyl levulinate (Biofuel Additive) - Heda, Jidnyasa; Niphadkar, Prashant; Bokade, Vijay (Energy & Fuels, 2019)
Ethyl levulinate (EL), a biofuel additive for petroleum and biodiesel can also be used as a 100% fuel to replace petroleum diesel with the existing diesel engine. The major problem to make the EL process economical is the lack of a proper conversion technology to convert C-6 sugars such as glucose with higher yield of EL as well as process which can tolerate higher glucose concentration to increase productivity. The present study highlighted the catalytic synthesis of EL from glucose over synergetic combination of zeolite H-USY and Lewis acidic catalysts such as Sn-beta, TiO2, ZrO2, and SnO2. Because of the strong Lewis acidic nature and the subsequent enhancement in the isomerization rate from glucosides to fructosides, the synergetic combination of H-USY with SnO2 showed higher EL yield than the combination with other Lewis acidic catalysts. So far, the highest EL yield of 81% from glucose (50 g/L) at 180 degrees C in 3 h was achieved over the optimal combination of 95% H-USY and 5% SnO2 having strong/weak acidity and B/L ratios of 1.30 and 0.75, respectively. The study was further extended for establishing the proposed reaction mechanism without the formation of 5-hydroxymethyl furfural, levulinic acid, and formic acid which makes the overall process clean and green.

Estrogen receptor activation in response to Azadirachtin A stimulates osteoblast differentiation and bone formation in mice - Kushwaha, Priyanka; Ahmad, Naseer; Dhar, V. Yogeshwar; Verma, Ashwni; Haldar, Saikat; Mulani, Fayaj A.; Trivedi, Prabodh K.; Mishra, Prabhat R.; Thulasiram, V. Hirekodathakallu; Trivedi, Ritu (Journal of Cellular Physiology, 2019)
The positive effectsof the sex hormone in sustaining bone homeostasis areexercised by maintaining the equilibrium betweencell activity and apoptosis. In this regard, the importance of estrogen receptors in maintaining the bone is that it is anattractive drug target,if devoid of known side effects. In this study, we show that a natural pure compound Azadirachtin A (Aza A) isolated from Azadirachta indica binds selectively to a site in the estrogen receptor, identifying itself to bea selective tissue modifier. Using computational and medicinal chemistry, we show that Aza A binds potentially and selectively to estrogen receptor-alpha (ER alpha) as compared with ER beta. This preferential binding of Aza A to ER alpha with good pharmacokinetic distribution in the body forms metabolites, showing that it is well absorbed. In in vivo estrogen deficiency models for osteoporosis, Aza A at a much lower dose enhances new bone formation at both sites of the trabecular and cortical bone with increased bone strength and presentswith no hyperplastic effect in the uterus.
Keywords: ALP; Gene expression; micro-CT; mineralization; osteoblast cells

Evolution of ZnO nanostructures as hexagonal disk: Implementation as photoanode material and efficiency enhancement in Al: ZnO based dye sensitized solar cells - Parra, Mohammad Ramzan; Pandey, Padmini; Siddiqui, Hafsa; Sudhakar, Vediappan; Krishnamoorthy, Kothandam; Haque, Fozia Z. (Applied Surface Science, 2019)
Hexagon shaped pristine and Al doped ZnO nanodisks (NDs) with exposed +/- [0001] polar facets were successfully synthesized using modified sol-gel method without the involvement of any structural directing or capping agents. It was investigated that OH- ions in mixed solvent system is responsible for pore formation and inhibit the growth of ZnO along the direction of c-axis leading to a high percentage exposure of active +/- [0001] polar facets and encourage the formation of ZnO NDs. Crystallographic analysis revealed that crystallite size and lattice constants are decreased, with the addition of Al3+ ions. The results obtained from Raman, and XPS analysis further corroborated with the XRD results, revealed the successful incorporation of Al3+ ions into ZnO lattice. Optical study revealed the band gap tunability with the incorporation of Al ion as dopant. Enhanced power conversion efficiency (PCE) of 1.96% (J(sc) similar to 7.69 +/- 0.23 mA/cm(2)) was observed for Al: ZnO hexagonal NDs based DSSC. The increased PCE in Al: ZnO based DSSC can be attributed to the higher inner surface area for dye anchoring by the interconnected network of the disk-like structure. The obtained results were satisfactory and most importantly the synthesis procedure proposed in present work is excellent for the synthesis of perfectly hexagonal shaped disks under precised synthesis parameters. The device interface study was further conducted using electrochemical impedance spectroscopy which revealed better charge transport process and charge storage ability with the incorporation of Al3+ ions into ZnO lattice.
Keywords: dye sensitized solar cells; Hexagonal disks; Sol-gel method; ZnO

Experimental and theoretical charge density, intermolecular interactions and electrostatic properties of metronidazole - Kalaiarasi, Chinnasamy; George, Christy; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Poomani, Kumaradhas (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2019)
Metronidazole is a radiosensitizer; it crystallizes in the monoclinic system with space group P2(1)/c. The crystal structure of metronidazole has been determined from high-resolution X-ray diffraction measurements at 90 K with a resolution of (sin 0/lambda) max = 1.12 angstrom(-1). To understand the charge-density distribution and the electrostatic properties of metronidazole, a multipole model refinement was carried out using the Hansen-Coppens multipole formalism. The topological analysis of the electron density of metronidazole was performed using Bader's quantum theory of atoms in molecules to determine the electron density and the Laplacian of the electron density at the bond critical point of the molecule. The experimental results have been compared with the corresponding periodic theoretical calculation performed at the B3LYP/6-31G** level using CRYSTAL09. The topological analysis reveals that the N-O and C-NO2 exhibit less electron density as well as negative Laplacian of electron density. The molecular packing of crystal is stabilized by weak and strong inter- and intramolecular hydrogen bonding and H center dot center dot center dot H interactions. The topological analysis of O-H center dot center dot center dot N, C-H center dot center dot center dot O and H center dot center dot center dot H intra- and intermolecular interactions was also carried out. The electrostatic potential of metronidazole, calculated from the experiment, predicts the possible electrophilic and nucleophilic sites of the molecule; notably, the hydroxyl and the nitro groups exhibit large electronegative regions. The results have been compared with the corresponding theoretical results.
Keywords: atomic valence index; Electron density; Electrostatic potential; intermolecular interactions; metronidazole; radiosensitizer

Fundamentals and sensing applications of 2D materials - Hywel, Morgan; Rout, Chandra Sekhar; Late, Dattatray J. (Elsevier, 2019)
Fundamentals and Sensing Applications of 2D Materials provides a comprehensive understanding of a wide range of 2D materials. Examples of fundamental topics include: defect and vacancy engineering, doping and advantages of 2D materials for sensing, 2D materials and composites for sensing, and 2D materials in biosystems. A wide range of applications are addressed, such as gas sensors based on 2D materials, electrochemical glucose sensors, biosensors (enzymatic and non-enzymatic), and printed, stretchable, wearable and flexible biosensors. Due to their sub-nanometer thickness, 2D materials have a high packing density, thus making them suitable for the fabrication of thin film based sensor devices.

Hydrocarbon chain-length dependence of solvation dynamics in alcohol-based deep eutectic solvents: a two-dimensional infrared spectroscopic investigation - Chatterjee, Srijan; Ghosh, Deborin; Haldar, Tapas; Deb, Pranab; Sakpal, Sushil S.; Deshmukh, Samadhan H.; Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemistry B, 2019)
Deep eutectic solvents (DESs) have gained popularity in recent years as an environmentally benign, inexpensive alternative to organic solvents for diverse applications in chemistry and biology. Among them, alcohol-based DESs serve as useful media in various applications due to their significantly low viscosity as compared to other DESs. Despite their importance as media, little is known how their solvation dynamics change as a function of the hydrocarbon chain length of the alcohol constituent. In order to obtain insights into the chain-length dependence of the solvation dynamics, we have performed two-dimensional infrared spectroscopy on three alcohol-based DESs by systematically varying the hydrocarbon chain length. The results reveal that the solvent dynamics slows down monotonically with an increase in the chain length. This increase in the dynamic timescales also shows a strong correlation with the concomitant increase in the viscosity of DESs. In addition, we have performed molecular dynamics simulations to compare with the experimental results, thereby testing the capacity of simulations to determine the amplitudes and timescales of the structural fluctuations on fast timescales under thermal equilibrium conditions.

Inducing disorder in order: hierarchically porous covalent organic framework nanostructures for rapid removal of persistent organic pollutants - Karak, Suvendu; Dey, Kaushik; Torris, Arun; Halder, Arjun; Bera, Saibal; Kanheerampockil, Fayis; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
The key factor responsible for fast diffusion and mass transfer through a porous material is the availability of a widely open pore interior having complete accessibility from their surface. However, because of their highly stacked nature, ordered two-dimensional (2D) materials fail to find real-world applicability, as it is difficult to take advantage of their complete structure, especially the inner cores. In this regard, three-dimensional (3D) nanostructures constructed from layered two-dimensional crystallites could prove to be advantageous. However, the real challenge is to cultivate a porous nanostructure with ordered pores where the pores are surrounded by crystalline walls. Herein, a simple yet versatile in situ gas-phase foaming technique has been employed to address these cardinal issues. The use of baking soda leads to the continuous effervescence of CO2 during the crystallization of foam, which creates ripples and fluctuations on the surface of the 2D crystallites. The induction of ordered micropores within the disordered 3D architecture synergistically renders fast diffusion of various guests through the interconnected pore network. The high-density defects in the hierarchically porous structure help in ultrafast adsorption (<10 s) of various pollutants (removal efficiency of 99%) from water, all of which would lead to significant environmental benefit. The pseudo-second-order rate constant for the BPA pollutant is 182.3 g mg(-1) min(-1), which is the highest among all the literature reports to date. The high removal efficiency (highest efficiency of 94% and average efficiency of 70%) of a persistent organic pollutant has been attended for the first time.

Insect-repellent and mosquitocidal effects of noreremophilane- and nardoaristolone-based compounds - Handore, K. L.; Kalmode, H. P.; Sayyad, S.; Seetharamsingh, B.; Gathalkar, G.; Padole, S.; Pawar, P. V.; Joseph, M.; Sen, A.; Reddy, D. S. (ACS Omega, 2019)
Here, we disclose novel mosquito-repellent synthetic hydrindanes based on noreremophilanes and nardoaristolone B which show increased activity against adult females of Aedes aegypti. The noreremophilanes and nardoaristolone B with hydrindane skeleton are structurally related to nootkatone with decalin skeleton, a well-studied natural product extracted from a grape fruit. Out of our library of compounds synthesized based on the noreremophilanes and nardoaristolone B scaffolds, NDS-100598 (compound 20) exhibits higher repellent and knock-down effects at a very low concentration (0.25 mg/cm2), while a few analogues showed considerably enhanced activity compared to racemic nootkatone. This is the first report documenting insect-repellent and knock-down activity of the noreremophilanes class of compounds.

Mechanistic insights into enzymatic catalysis by trehalase from the insect gut endosymbiont Enterobacter cloacae - Adhav, Anmol; Harne, Shrikant; Bhide, Amey; Giri, Ashok; Gayathri, Pananghat; Joshi, Rakesh (FEBS Journal, 2019)
Energy metabolism in the diamondback moth Plutella xylostella is facilitated by trehalase, an enzyme which assists in trehalose hydrolysis, from the predominant gut bacterium Enterobacter cloacae. We report the biochemical and structural characterization of recombinant trehalase from E. cloacae (Px_EclTre). Px_EclTre showed K-M of 1.47 (+/- 0.05) mm, k(cat) of 6254.72 min(-1) and V-max 0.2 (+/- 0.002) mm center dot min(-1) at 55 degrees C and acidic pH. Crystal structures of Px_EclTre were determined in the ligand-free form and bound to the inhibitor Validoxylamine A. The crystal structure of the ligand-free form, unavailable until now for any other bacterial trehalases, enabled us to delineate the conformational changes accompanying ligand binding in trehalases. Multiple salt bridges were identified that potentially facilitated closure of a hood over the substrate-binding site. A cluster of five tryptophans lined the -1 substrate-binding subsite, interacted with crucial active site residues and contributed to both trehalase activity and stability. The importance of these residues in enzyme activity was further validated by mutagenesis studies. Many of these identified residues form part of signature motifs and other conserved sequences in trehalases. The structure analysis thus led to the assignment of the functional role to these conserved residues. This information can be further explored for the design of effective inhibitors against trehalases.
Keywords: Enterobacter cloacae; Plutella xylostella; structural analysis; trehalase; validoxylamine A

Mechanistic insights into the pathways of phenol hydrogenation on Pd nanostructures - Porwa, Govind; Gupta, Shelaka; Sreedhala, S.; Elizabeth, Joes; Ithan, Tuhin Suvra; Haider, M. Ali; Vinod, C. P. (ACS Sustainable Chemistry & Engineering, 2019)
Product selectivity in aqueous phase phenol hydrogenation on well-defined supported Pd nanostructures (spheres, cubes, and octahedra) was studied using defined experiments and density functional theory (DFT) simulations. On Pd spheres and octahedra, the reaction initially showed high selectivity (in the first 3 h, at 363 K and 5 bar H-2 pressure) toward the partially hydrogenated product cyclohexanone. On prolonged operation (>20 h of reaction time), a shift in the product selectivity (up to 100%) toward the completely hydrogenated product cyclohexanol was observed on Pd spheres and octahedra. In contrast, the reaction on Pd cubes, which only had {100} facets, showed a high selectivity (similar to 90%) toward the product cyclohexanone even after 40 h, at the same reaction conditions. Since the {111} facets are expected to be the majority sites on a spherical particle, we attribute the selectivity trend observed on spherical Pd particles to be primarily controlled by the selectivity trend on the Pd{111} facets. This observation was further confirmed on performing the hydrogenation reaction on a mixture of Pd cube and Pd octahedron particles in a ratio of 25:75 (representing the site ratio of a spherical particle). DFT simulations provided a mechanistic insight into the reactivity of the two different facets ({100} and {111}) toward phenol hydrogenation. The calculations revealed that the selectivity significantly depended on the activation barriers involved in cyclohexanone hydrogenation on the Pd{111} facets (77 and 57 kJ/mol) as compared to those on the Pd{100} facets (97 and 101 kJ/mol).
Keywords: Cyclohexanol; cyclohexanone; facet-dependent reactivity; phenol hydrogenation

Multimodal chromatography for purification of biotherapeutics - a review. - Halan, V.; Maity, S.; Bhambure, R.; Rathore, A. S. (Current Protein and Peptide Science, 2019)
Process chromatography forms the core of purification of biotherapeutics. The unparalleled selectivity that it offers over other alternatives combined with the considerable robustness and scalability make it the unit operation of choice in downstream processing. It is typical to have three to five chromatography steps in a purification process for a biotherapeutic. Generally, these steps offer different modes of separation such as ion-exchange, reversed phase, size exclusion, and hydrophobic interaction. In the past decade, multimodal chromatography has emerged as an alternative to the traditional modes. It involves use of more than one mode of separation and typically combines ion-exchange and hydrophobic interactions to achieve selectivity and sensitivity. Over the last decade, numerous authors have demonstrated the significant potential that multimode chromatography offers as a protein purification tool. This review aims to present key recent developments that have occurred on this topic together with a perspective on future applications of multimodal chromatography.

Neural anti-inflammatory natural product periconianone A: total synthesis and biological evaluation - Kalmode, Hanuman P.; Patil, Suhag S.; Handore, Kishor L.; Athawale, Paresh R.; Dandela, Rambabu; Verma, Abhishek Kumar; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2019)
Total synthesis of periconianone A, an eremophilane-type sesquiterpenoid with impressive neural anti-inflammatory potential, has been accomplished. Diels-Alder/aldol strategy to construct tetrahydro-naphthalene-2,6-dione scaffold, allylic oxidation of dienone using DBU/O-2 and postulated biomimetic aldol reaction to construct 6/6/6 tricyclic system are the highlights of the present synthesis. Furthermore, the synthesized (+/-)-periconianone A and two close analogs were tested for their neural anti-inflammatory activity using various assays. In the course of our study we found a structurally simplified analog is superior to (+/-)-periconianone A.
Keywords: Aldol; Allylic oxidation; Biological evaluation; Cytotoxicity; Diels-Alder; Periconianone A

Nonoxidative dehydrogenation of methanol to methyl formate through highly stable and reusable CuMgO-based catalysts - Yuan D. J.; Hengne, A. M.; Saih, Y.; Huang, K. W. (ACS Omega, 2019)
Nonoxidative dehydrogenation of methanol to methyl formate over a CuMgO-based catalyst was investigated. Although the active site is metallic copper (Cu0), the best reaction conditions were obtained by tuning the ratio of Cu/Mg and doping the catalyst with 1 wt % of Pd to achieve a very specific activity for methyl formate synthesis. On the basis of the CO2 temperature-programmed desorption study, the basic strength of the catalyst plays a role in the efficient conversion of methanol to methyl formate via dehydrogenation. These CuMgO-based catalysts show excellent thermal stability during the reaction and the regeneration processes. Approx. 80% methanol conversion with constant selectivity to methyl formate was achieved even after 4 rounds of usage for a total reaction time exceeding 200 h, indicative of their potential for practical applications.

One-pot three-component synthesis and photophysical properties of highly fluorescent novel 4-alkyl-3-aryl-2,6-dicyanoanilines by using tris(hydroxymethyl)aminomethane as a catalyst - Kudale, A. S.; Kamble, S. B.; Gore, A. H.; Pisal, M. M.; Salokhe, A. T.; Kolekar, G. B.; Helavi, V. B. (Chemical Data Collections, 2019)
Novel 4-alkyl-3-aryl-2,6-dicyanoanilines were synthesized by a multi-component one-step reaction of aromatic aldehyde, malononitrile and aliphatic aldehyde using tris(hydroxymethyl)aminomethane (THAM) as a catalyst under microwave (MW) irradiation or conventional heating. The optimized reaction condition involved use of 2.5 equivalents of THAM under MW irradiation at 140 W using 20% MW power for 5 min or conventional heating at 80 °C for 8 h in dimethylformamide. The photophysical properties including λmax, quantum yield and Stokes’ shifts of newly synthesized molecules were studied. All compounds exhibited quantum yield in the range of 0.04–0.52 with respect to standard quinine sulphate having quantum yield 0.54. The Stokes’ shifts of all compounds were found in the range of 41–105 nm. The current strategy provides operationally simple protocol using THAM as a catalyst to synthesize 4-alkyl-3-aryl-2,6-dicyanoanilines with diverse structural features to make them available for exploration of their photophysical as well as biological applications.

Pathways to defense metabolites and evading fruit bitterness in genus Solanum evolved through 2-oxoglutarate-dependent dioxygenases - Cardenas, Pablo D.; Sonawane, Prashant D.; Heinig, Uwe; Jozwiak, Adam; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Pliner, Margarita; Unger, Tamar; Wolf, Dalia; Ofner, Itai; Vilaprinyo, Ester; et al. (Nature Communications, 2019)
The genus Solanum comprises three food crops (potato, tomato, and eggplant), which are consumed on daily basis worldwide and also producers of notorious anti-nutritional steroidal glycoalkaloids (SGAs). Hydroxylated SGAs (i.e. leptinines) serve as precursors for leptines that act as defenses against Colorado Potato Beetle (Leptinotarsa decemlineata Say), an important pest of potato worldwide. However, SGA hydroxylating enzymes remain unknown. Here, we discover that 2-OXOGLUTARATE-DEPENDENT-DIOXYGENASE (2-ODD) enzymes catalyze SGA-hydroxylation across various Solanum species. In contrast to cultivated potato, Solanum chacoense, a widespread wild potato species, has evolved a 2-ODD enzyme leading to the formation of leptinines. Furthermore, we find a related 2-ODD in tomato that catalyzes the hydroxylation of the bitter a-tomatine to hydroxytomatine, the first committed step in the chemical shift towards downstream ripening-associated non-bitter SGAs (e.g. esculeoside A). This 2-ODD enzyme prevents bitterness in ripe tomato fruit consumed today which otherwise would remain unpleasant in taste and more toxic.

Population genetic and phytochemical dataset of Saraca asoca: a traditionally important medicinal tree - Hegde, Satisha; Pai, Sandeep Ramchandra; Bhagwat, Rasika M.; Sainia, Archana; Rathore, Poonam Kanwar; Jalalpure, Sunil Satyappa; Hegde, Harsha Vasudev; Sugunan, Attayoor Purushottaman; Gupta, Vidya S.; Kholkute, Sanjiva D.; Roy, Subarna (Data in Brief, 2019)
The data presented in this article is in support of the research paper “Genetic and phytochemical investigations for understanding population variability of the medicinally important tree Saraca asoca to help develop conservation strategies” Hegde et al., 2018. This article provides PCR based Inter-Simple Sequence Repeat (ISSR) and HPLC datasets of 106 individual samples of Saraca asoca collected from various geographical ranges of the Western Ghats of India. The ISSR data includes information on genetic diversity and images of population structures generated through amplified DNA products from samples of Saraca asoca leaf. Phytochemical data obtained from HPLC includes concentration (mg/g) of gallic acid (GA), catechin (CAT), and epicatechin (EPI). The data also presents information obtained from various statistical analysis viz. standard error of the mean values, distribution variables, prediction accuracy, and multiple logistic regression analysis.

Porosity switching in polymorphic porous organic cages with exceptional chemical stability - Bera, Saibal; Dey, Kaushik; Pal, Tapan K.; Halder, Arjun; Tothadi, Srinu; Karak, Suvendu; Addicoat, Matthew; Banerjee, Rahul (Angewandte Chemie-International Edition, 2019)
Porous solids that can be switched between different forms with distinct physical properties are appealing candidates for separation, catalysis, and host-guest chemistry. In this regard, porous organic cages (POCs) are of profound interest because of their solution-state accessibility. However, the application of POCs is limited by poor chemical stability. Synthesis of an exceptionally stable imine-linked (4+6) porous organic cage (TpOMe-CDA) is reported using 2,4,6-trimethoxy-1,3,5-triformyl benzene (TpOMe) as a precursor aldehyde. Introduction of the -OMe functional group to the aldehyde creates significant steric and hydrophobic characteristics in the environment around the imine bonds that protects the cage molecules from hydrolysis in the presence of acids or bases. The electronic effect of the -OMe group also plays an important role in enhancing the stability of the reported POCs. As a consequence, TpOMe-CDA reveals exceptional chemical stability in neutral, acidic and basic conditions, even in 12m NaOH. Interestingly, TpOMe-CDA exists in three different porous and non-porous polymorphic forms (, , and ) with respect to differences in crystallographic packing and the orientation of the flexible methoxy groups. All of the polymorphs retain their crystallinity even after treatment with acids and bases. All the polymorphs of TpOMe-CDA differ significantly in their properties as well as morphology and could be reversibly switched in the presence of an external stimulus.
Keywords: chemical stability; Morphology; organic cages; polymorphism; porosity switching

Preparation and activity of copper-gallium nanocomposite catalysts for carbon dioxide hydrogenation to methanol - Hengne, Amol M.; Yuan, Ding Jier; Date, Nandan S.; Saih, Youssef; Kamble, Sanjay P.; Rode, V. Chandrashekhar; Huang, Kuo-Wei (Industrial & Engineering Chemistry Research, 2019)
Copper (Cu) nanocomposite catalysts with gallium (Ga) and aluminum (Al) were prepared using the simultaneous coprecipitation digestion method. The catalysts were characterized by N-2 adsorption, N2O titration, XRD (X-ray diffraction), H-2-TPR (H-2 temperature-programmed reduction), XPS (X-ray photoelectron spectroscopy), and CO2-TPD (CO2 temperature-programmed desorption) techniques, and CO2 hydrogenation to methanol synthesis was performed. The use of Ga in Cu catalysts enhanced the weak basic sites more than the Cu catalysts with Al. With the CuGa nanocomposite formation, the catalyst showed a sequential reduction of CuO, for example, Cu+2 to Cu+ to Cu-0, and the Cu surface area was also high in comparison with CuAl. These findings confirmed that both the Cu surface area and CuO reducibility in the catalyst helped to boost the conversion of CO2, whereas selectivity to methanol was associated with the basicity of the catalyst. CuAl catalysts showed very poor selectivity to methanol despite CO formation, which could be due to the weak interaction of the CuAl nanocomposite catalysts compared to the CuGa nanocomposite catalysts.

Rapid and efficient sequestration of arsenic from contaminated water using hypertolerant Bacillus L-148 sp.: a two-step process - Bagade, Aditi; Nandre, Vinod; Ghosh, Sayanti; Battu, Shateesh; Haram, Santosh; Giri, Ashok; Kodam, Kisan (Green Chemistry, 2019)
A fast, robust and green bioreactor for arsenic sequestration from contaminated water was designed. In the two-tier bioreactor, bacterial arsenite detoxification (1 mM) was carried out followed by precipitation of arsenate in 5 min. The precipitate could be used for supercapacitor applications. This bioreactor yielded arsenic free water, therefore, this method can be adopted for scale-up. The combination of hypertolerant bacteria and fast precipitation indicates the robustness of this pilot bioreactor.

Semirational design and engineering of grapevine glucosyltransferases for enhanced activity and modified product selectivity - Joshi, Rakesh; Trinkl, Johanna; Haugeneder, Annika; Haertl, Katja; Franz-Oberdorf, Katrin; Giri, Ashok; Hoffmann, Thomas; Schwab, Wilfried (Glycobiology, 2019)
Uridine diphosphate-dependent glycosyltransferases (UGTs) catalyze the transfer of a diversity of sugars to several acceptor molecules and often exhibit distinct substrate specificity. Modulation of glycosyltransferases for increased catalytic activity and altered substrate or product specificity are the key manipulations for the biotechnological use of glycosyltransferases in various biosynthetic processes. Here, we have engineered the binding pocket of three previously characterized Vitis vinifera glycosyltransferases, UGT88F12, UGT72B27 and UGT92G6, by structure-guided in silico mutagenesis to facilitate the interactions of active site residues with flavonol glucosides and thus modify substrate specificity and activity. Site-directed mutagenesis at selected sites, followed with liquid chromatography-mass spectrometry based activity assays, exhibited that mutant UGTs were altered in product selectivity and activity as compared to the wild-type enzymes. Mutant UGTs produced larger amounts of flavonol di-monosaccharide glucosides, which imply that the mutations led to structural changes that increased the volume of the binding pocket to accommodate a larger substrate and to release larger products at ease. Mutants showed increased activity and modified product specificity. Thus, structure-based systematic mutations of the amino acid residues in the binding pocket can be explored for the generation of engineered UGTs for diverse biotechnological applications.
Keywords: flavonol; Glycosyltransferase; in silico analysis; Mutagenesis; selectivity

On the sensitivity of alginate rheology to composition - Suresh, Karthika; Haering, Marleen; Kumaraswamy, Guruswamy; Diaz Diaz, David (Soft Matter, 2019)
The linear response of alginate-phenyl boronic acid (Alg-PBA) esters shows a universal, composition-independent viscoelastic fluid-like behaviour. Reversible association of alginates governs their rheology at all compositions (viz. at all alginate concentrations and solution pH). However, their high strain behaviour is very sensitive to composition. Tuning composition affords liquids that neck to form filaments capable of being drawn to large elongations without failure. We interpret our data by invoking strain-dependent association and dissociation rates for the alginates. High association rates at high strain result in materials with viscoelastic liquid like behaviour.

Silk fibroin-sodium dodecyl sulfate gelation: molecular, structural, and rheological insights - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita; Nisal, Anuya; Ravindranathan, Sapna (Langmuir, 2019)
A gelling agent is necessary to accelerate sol to gel transition in an aqueous solution of silk fibroin (SF), which otherwise takes several days to complete. In this paper, we investigate the mechanism of gelation of Bornbyx mori SF by a model anionic surfactant, sodium dodecyl sulfate (SOS). Even though interactions between SDS and proteins have been extensively investigated, most of these studies have focused on globular proteins, which undergo denaturation. The interaction with a fibrous protein such as SF is different and results in an altered secondary structure leading to gelation. In this work, the concentration-dependent gelation process of the SF-SDS system is examined using rheology, SANS, FTIR, and NMR. We observed preferential binding of SDS to specific regions on the SF chain, which aids structural changes favoring beta-sheet formation. We propose a mechanism for the accelerated sol-gel transition in the SF-SDS system.

Stereoselective aromatic ring hydrogenation over supported rhodium catalysts in supercritical carbon dioxide solvent - Shirai, M.; Hiyoshi, N.; Rode, C. V. (Chemical Record, 2019)
The combination of supported rhodium metal catalysts and supercritical carbon dioxide solvent was effective for the stereoselective ring hydrogenations of aromatic compounds at low temperature. Higher solubility of hydrogen in supercritical carbon dioxide provides higher concentration of hydrogen on the rhodium surface, but lower that of the intermediate on rhodium surface, which suppresses the flipping of surface intermediate, leading to higher catalyst activities and cis selectivities to the corresponding ring-hydrogenated products as compared with those in organic solvents.

Synthesis of biphasic nanomaterials based on ZnO and SnO2: application towards photocatalytic degradation of acid red dye - Kudale, Ananada S.; Kamble, Santosh B.; Gore, Anil H.; Pisal, Mahesh M.; Salokhe, Anil T.; Kolekar, Govind B.; Helavi, Vasant B. (Nano-Structures & Nano-Objects, 2019)
Zn2SnO4/SnO2 and ZnO/SnO2 biphasic nanocatalysts have been synthesized by a facile solvothermal method using ethylene glycol (EG) as solvent in three different ways maintaining the pH of the solution at either 3 or 9 followed by calcination at 700 °C. The nanocatalysts are characterized by different techniques to investigate their structure, composition, morphology and optical properties. The XRD results indicate the formation of pristine biphasic composites. The UV-absorbance and photoluminescence spectra confirms the formation of biphasic composites as well as presence of large number of defects in the prepared nanocatalysts. The biphasic nanocomposites possess better photocatalytic activity towards the degradation of Acid Red-183 (AR-183) dye than pristine SnO2 and ZnO nanoparticles. This is mainly due to better charge separation, minimal recombination rate of charge carriers and defect-riched structures of nanocatalysts.

Transition-metal-free regioselective one-pot synthesis of aryl sulfones from sodium sulfinates via quinone imine ketal - Halder, P.; Humne, V. T.; Mhaske, S. B. (Journal of Organic Chemistry, 2019)
A novel, efficient, and regioselective transition-metal-free one-pot synthesis of aryl sulfones via the reactive quinone imine ketal intermediate is demonstrated using easily accessible bench-stable sulfinate salts. A broad range of functionality on p-anisidine substrates as well as sulfinate salts was tolerated under mild reaction conditions to provide the corresponding aryl sulfones in good to excellent yields.

Weak intermolecular interactions in covalent organic framework-carbon nanofiber based crystalline yet flexible devices - Mohammed, Abdul Khayum; Vijayakumar, Vidyanand; Halder, Arjun; Ghosh, Meena; Addicoat, Matthew; Bansode, Umesh; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2019)
<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">The redox-active and porous structural backbone of covalent organic frameworks (COFs) can facilitate high-performance electrochemical energy storage devices. However, the utilities of such 2D materials as supercapacitor electrodes in advanced self-charging power-pack systems have been obstructed due to the poor electrical conductivity and subsequent indigent performance. Herein, we report an effective strategy to enhance the electrical conductivity of COF thin sheets through the in situ solid-state inclusion of carbon nanofibers (CNF) into the COF precursor matrix. The obtained COF-CNF hybrids possess a significant intermolecular π···π interaction between COF and the graphene layers of the CNF. As a result, these COF-CNF hybrids (DqTp-CNF and DqDaTp-CNF) exhibit good electrical conductivity (0.25 × 10<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–3<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> S cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–1<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">), as well as high performance in electrochemical energy storage (DqTp-CNF: 464 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> at 0.25 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">). Also, the fabricated, mechanically strong quasi-solid-state supercapacitor (DqDaTp-CNF SC) delivered an ultrahigh device capacitance of 167 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> at 0.5 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">. Furthermore, we integrated a monolithic photovoltaic self-charging power pack by assembling DqDaTp-CNF SC with a perovskite solar cell. The fabricated self-charging power pack delivered excellent performance in the areal capacitance (42 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">) at 0.25 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> after photocharging for 300 s.

Zinc ion interactions in a two-dimensional covalent organic framework based aqueous zinc ion battery - Mohammed, Abdul Khayum; Ghosh, Meena; Vijayakumar, Vidyanand; Halder, Arjun; Nurhuda, Maryam; Kumar, Sushil; Addicoat, Matthew; Kurungot, Sreekumar; Banerjee, Rahul (Chemical Science, 2019)
<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">The two-dimensional structural features of covalent organic frameworks (COFs) can promote the electrochemical storage of cations like H<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, Li<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, and Na<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> through both faradaic and non-faradaic processes. However, the electrochemical storage of cations like Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ion is still unexplored although it bears a promising divalent charge. Herein, for the first time, we have utilized hydroquinone linked β-ketoenamine COF acting as a Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> anchor in an aqueous rechargeable zinc ion battery. The charge-storage mechanism comprises of an efficient reversible interlayer interaction of Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ions with the functional moieties in the adjacent layers of COF (−182.0 kcal mol<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">). Notably, due to the well-defined nanopores and structural organization, a constructed full cell, displays a discharge capacity as high as 276 mA h g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> at a current rate of 125 mA g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">.

2-D to 3-D conversion of WO3 nanostructures using structure directing agent for enhanced NO2 gas sensing performance - Beknalkar, S. A.; Patil, V. L.; Harale, N. S.; Suryawanshi, M. P.; Patil, A. P.; Patil, V. B.; Kim, J. H.; Patil, P. S. (Sensors and Actuators A-Physical, 2020)
An exotic 3-D tungsten oxide (WO3) microflower was synthesized via low-cost and environmental-friendly hydrothermal strategy. The effect of structure-directing agent on the formation of 3-D microflowers from a 2-D nanosheets of WO3 and its gas sensing behavior are investigated. The assynthesized WO3 powder was used in morphological, structural and phase studies by X-ray diffraction (XRD), scanning electron microscopy (SEM), FT-Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). The WO3 samples were found to be polycrystalline with monoclinic crystal structure. The SEM micrographs revealed the formation of 3-D microflowers made up of two-dimensional (2-D) multi-directional dendritic nanoplates. The potassium hydroxide (KOH) acts as a structure-directing agent in the formation of 3-D microflowers of WO3 sample. To further understand the formation of 3-D microflowers of WO3 sample, concentration-dependent experiments were carried out by varying KOH concentration and the formation mechanism was investigated. The synthesized WO3 microstructures were subjected to detailed gas sensing tests for different gases at an optimized temperature. A selective, sensitive gas response was obtained for WO3 gas sensor. The lower detection limit is about 1 ppm at 150 degrees C working temperature for an optimized WO3 gas sensor. The gas sensing results indicate that the 3-D microflower-like WO3 nanostructures are highly promising for applications as gas sensors. (C) 2020 Published by Elsevier B.V.
Keywords: Microflowers; NO2 detection; WO3

Advances in single-atom catalysts for lignin conversion - Halilu, Ahmed; Umar, Ahmad Abulfathi; Balarabe, Yahaya Umar; Haniffa, Mhd. Abd. Cader Mhd.; Munawar, Khadija; Sunku, Kiran; Sudarsanam, Putla (Advanced Heterogeneous Catalysts Volume 2: Applications at the Single-Atom Scale, 2020)
Single-atom catalysts (SACs) have drawn significant attention as promising surfaces for promoting observable reaction processes. As a guideline, SACs should have the proper nanoscale dimensionality to influence their effective and efficient performance, especially during lignin conversion to platform chemicals and other useful products. The development of SACs for functional applications still has many difficulties, such as harnessing and improving low-coordinated metal atoms to have controlled and observable activities per metal atom. Consequently, the need arises to ensure a decrease in the size of the metal particles and their uniform dispersion or coordination on a suitable support material. This has been an industrial target for a long time in the field of catalysis. Supported metal-based catalysts are not dimensionally uniform, thereby reducing their metal-atom efficiency and frequently leading to undesired side reactions that are sometimes difficult to observe. This makes the identification of the active sites responsible for the reaction of interest very difficult or even impossible. To ameliorate this challenge, the ultimate small-size limit for a metal particle is the SAC, which contains isolated metal atoms singly dispersed on any suitable support materials. It is expected that SACs should maximize the metal-atom efficiency with respect to the application, which is particularly significant for supported metal catalysts. Moreover, through uniform single-atom dispersion, SACs offer a great opportunity for achieving high activity and tuning selectivity to the desired product. This chapter provides a comprehensive overview of recent advances in using SACs for the conversion of lignin or lignin model compounds. The different support materials used for SACs, such as zeolites, metal oxides, and carbonaceous and siliceous materials, are discussed. This contribution also covers the catalytic reactions of lignin with an emphasis on cleaving its specific linkages, along with a systematic evaluation of SACs used in the relevant processes. The chapter also addressed key parameters essential for tailoring the particle size and acid–base and redox properties of the SACs used in lignin conversion. Special attention is paid to understanding the role of synthesis conditions in tailoring the size of SACs. It is expected that this contribution will provide future directions for practical SAC development and implementation in lignin conversion.

Antibacterial properties of glycosylated surfaces: variation of the glucosidal moiety and fatty acid conformation of grafted microbial glycolipids - Valotteau, Claire; Roelants, Sophie L. K. V.; Dhasaiyan, Prabhu; Zibek, Susanne; Guenther, Michael; Soetaert, Wim; Everaert, Bernd; Pradier, Claire-Marie; Babonneau, Florence; Baccile, Niki; Humblot, Vincent (Molecular Systems Design & Engineering, 2020)
Glycosylated surfaces can display antimicrobial properties. It has been shown that sophorolipids can be used to develop biocidal coatings against Gram-positive and Gram-negative bacteria, but with a limited efficiency so far. Therefore, it appears necessary to further investigate the surface antibacterial activity of a broader set of structurally related glycolipids. The present work explores the influence of the glucosidic moiety (gluco-, sophoro-, cellobio-) and the fatty acid backbone (saturated,cisortransmonounsaturated). We show that the fatty acid backbone plays an important role:cisderivative of sophorolipids (SL) grafted onto model gold surfaces has better biocidal properties than saturated (SL0) andtransmonounsaturated (SLt) molecules, which appear to be inefficient. The number of glucose units is also a key factor: a one-third decrease in antibacterial activity is observed when having one glucose unit (GL) compared to two (SL). Sugar acetylation (SLa) does not seem to have an impact on the biocidal properties of surfaces. These results are not limited to sophorolipids, with cellobioselipids (CL) leading to similar antibacterial observations.

Approach to nigericin derivatives and their therapeutic potential - Sahu, Amit Kumar; Said, Madhukar S.; Hingamire, Tejashri; Gaur, Megha; Khan, Abujunaid; Shanmugam, Dhanasekaran; Barvkar, Vitthal T.; Dharne, Mahesh S.; Bharde, Atul A.; Dastager, Syed G. (RSC Advances, 2020)
A new nigericin analogue that has been chemically modified was synthesized through a fluorination process from the parent nigericin, produced from a novel Streptomyces strain DASNCL-29. Fermentation strategies were designed for the optimised production of nigericin molecule and subjected for purification and structural analysis. The fermentation process resulted in the highest yield of nigericin (33% (w/w)). Initially, nigericin produced from the strain DASNCL-29 demonstrated polymorphism in its crystal structure, i.e., monoclinic and orthorhombic crystal lattices when crystallised with methanol and hexane, respectively. Furthermore, nigericin produced has been subjected to chemical modification by fluorination to enhance its efficacy. Two fluorinated analogues revealed that they possess a very potent antibacterial activity against Gram positive and Gram negative bacteria. To date, the nigericin molecule has not been reported for any reaction against Gram-negative bacteria, which are increasingly becoming resistant to antibiotics. For the first time, fluorinated analogues of nigericin have shown promising activity. In vitro cytotoxicity analysis of fluorinated analogues demonstrated tenfold lesser toxicity than the parent nigericin. This is the first type of study where the fluorinated analogues of nigericin showed very encouraging activity against Gram-negative organisms; moreover, they can be used as a candidate for treating many serious infections.

Bifunctional rice husk-derived SiO2-Cu-Al-Mg nanohybrid catalyst for one-pot conversion of biomass-derived furfural to furfuryl acetate - Hashim, Luqman H.; Halilu, Ahmed; Sudarsanam, Putla; Umar, Yahaya Balarabe; Bin Johan, Mohd Rafie; Bhargava, Suresh K. (Fuel, 2020)
Developing one-pot reaction methodologies, which typically require multifunctional catalyst systems, is crucial for sustainable production of bio-derived fuels and chemicals. This work reports one-pot hydrogenation-esterification of furfural to furfuryl acetate using a bifunctional metal-based nanohybrid catalyst, composed of rice husk (RH) derived SiO2, Cu, Al, and Mg species (RHSiO2-Cu-Al-Mg). For comparison, the catalytic efficiency of RHSiO2-Cu and RHSiO2-Cu-Al were tested under similar reaction conditions. Various analytical techniques were used to elucidate the physicochemical, textural, and acid-redox properties of the catalysts. It was found that the RHSiO2-Cu-Al-Mg catalyst contains an optimum amount of acid and redox sites, as illustrated by NH3-TPD and H-2-TPR studies, respectively. Especially, Mg addition played a vital role in tailoring acidity of the RHSiO2-Cu-Al catalyst to promote in-situ esterification of furfuryl alcohol with acetic acid to yield furfuryl acetate. As a result, the RHSiO2-Cu-Al-Mg catalyst exhibited the best performance in one-pot conversion of furfural to furfuryl acetate, outperforming various noble metal/silica based catalysts. This study offers potential opportunities for the rational design of novel, bifunctional heterogeneous catalysts for efficient production of bio-derived fuels and value added chemicals.
Keywords: Acid-redox sites; Bifunctional catalyst; Bio-oil upgrading; One-pot furfural conversion; Rice husk silica

Connecting microscopic structures, mesoscale assemblies, and macroscopic architectures in 3D-printed hierarchical porous covalent organic framework foams - Mohammed, Abdul Khayum; Usgaonkar, Saurabh; Kanheerampockil, Fayis; Karak, Suvendu; Halder, Arjun; Tharkar, Minakshi; Addicoat, Matthew; Ajithkumar, Thalasseril G.; Banerjee, Rahul (Journal of the American Chemical Society, 2020)
The induction of macro and mesopores into two-dimensional porous covalent organic frameworks (COFs) could enhance the exposure of the intrinsic micropores toward the pollutant environment, thereby, improving the performance. However, the challenge is to build a continuous hierarchically porous macro-architecture of crystalline organic materials in the bulk scale. In this regard, we have strategized a novel synthetic method to create hierarchically porous COF foams consisting of ordered micropores (2-2.2 nm) and disordered meso and macropores (50 nm to 200 mu m) as well as ordered macropores (1.5 mm to 2 cm). Herein, graphene oxide was used for creating disordered macro and mesopores in COF-GO foams. Considering the rheological features of the precursor hydrogel, we could integrate crystalline and porous COF-GO foams into self-supported three-dimensional (3D)-printed objects with the desired shapes and sizes. Therefore, we have engineered the 3D macro-architecture of COF-GO foams into complex geometries keeping their structural order and continuous porosity intact over a range of more than a million (10(-9) m to 10(-3) m). The interconnected 3D openings in these COF-GO foams further enhance the rapid and efficient uptake of organic and inorganic pollutants from water (>95% removal within 30 s). The abundant distribution of interconnected macroporous volume (55%) throughout the COF-GO foam matrix enhances the flow of water (1.13 x 10(-3) m.s(-1)) which results in efficient mass transport and adsorption.

Construction of unique SCF3-containing building blocks via allylic alkylation of Morita-Baylis-Hillman adducts - Halder, Priyanka; Pol, Mahesh D.; Ahire, Milind M.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2020)
Lewis base-catalyzed allylic alkylation of Morita-Baylis-Hillman adducts with alpha-SCF3 ketones has been demonstrated. The developed strategy provides efficient access to a series of highly functionalized scaffolds featuring trifluoromethanesufinyl motif on a stereogenic carbon.

Correlation between multifunctional properties of lead free Iron doped BCT perovskite ceramics - Redhu, Preeti; Punia, Rajesh; Hooda, Ashima; Malik, B. P.; Sharma, Geeta; Sharma, Preeti (Ceramics International, 2020)
Present study investigates the effect of Fe doping on structural, microstructural, dielectric, ferroelectric, piezoelectric and magnetic properties of Barium calcium titanate (BCT) ceramics synthesized by solid state reaction route. The polycrystalline tetragonal structure of prepared ceramics was confirmed from XRD study. Analysis done using Rietveld refinement reveals reduction in lattice parameters as well as unit cell volume on substitution of Fe3+ ions in BCT lattice. Occurrence of four distinct Raman bands viz. 297 cm(-1) -302 cm(-1), 473 cm(-1)-475 cm(-1), 516 cm(-1) -524 cm(-1) and 729 cm(-1) -733 cm(-1) in Raman spectroscopic studies confirms the tetragonal phase of prepared ceramic compositions which are in accordance with XRD study. The Scanning Electron Microscopy analysis revealed polyhedral shaped grains whose average grain size decreased with increase in Fe content (x) in BCT ceramics. A diffused frequency independent phase transition was observed in temperature dependent dielectric measurements. Dielectric properties improved significantly, with shifting of transition temperature, T c close to room temperature with Fe doping. These studiessuggest applications of these ceramics in the development of environment friendly dielectric materials meeting X7R MLCCs specifications. The ferroelectric and piezoelectric properties of these ceramic compositions were found to decrease with increase in Fe concentration. Feeble room temperature ferromagnetism was observed for composition x = 0.020.
Keywords: BCT; dielectric response; Fe doping; ferroelectric properties; Lead free ceramics; Magnetic measurements

Crystal-to-crystal synthesis of helically ordered polymers of trehalose by topochemical polymerization - Hema, Kuntrapakam; Gonnade, Rajesh G.; Sureshan, Kana M. (Angewandte Chemie-International Edition, 2020)
The synthesis of crystalline helical polymers of trehalose via topochemical azide-alkyne cycloaddition (TAAC) of a trehalose-based monomer is presented. An unsymmetrical trehalose derivative having azide and alkyne crystallizes in two different forms having almost similar packing. Upon heating, both the crystals undergo TAAC reaction to form crystalline polymers. Powder X-ray diffraction (PXRD) studies revealed that the monomers in both the crystals polymerize in a crystal-to-crystal fashion; circular dichroism (CD) studies of the product crystals revealed that the formed polymer is helically ordered. This solvent-free, catalyst-free polymerization method that eliminates the tedious purification of the polymeric product exemplifies the advantage of topochemical polymerization reaction over traditional solution-phase polymerization.
Keywords: Click reaction; helical polymers; polysaccharide; topochemical reactions; trehalose

Dioxolanone-anchored poly(allyl ether)-based cross-linked dual-salt polymer electrolytes for high-voltage lithium metal batteries - Vijayakumar, Vidyanand; Diddens, Diddo; Heuer, Andreas; Kurungot, Sreekumar; Winter, Martin; Nair, Jijeesh Ravi (ACS Applied Materials & Interfaces, 2020)
Novel cross-linked polymer electrolytes (XPEs) are synthesized by free-radical copolymerization induced by ultraviolet (UV)-light irradiation of a reactive solution, which is composed of a difunctional poly(ethylene glycol) diallyl ether oligomer (PEGDAE), a monofunctional reactive diluent 4-vinyl-1,3-dioxolan-2-one (VEC), and a stock solution containing lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) in a carbonate-free nonvolatile plasticizer, poly(ethylene glycol) dimethyl ether (PEGDME). The resulting polymer matrix can be represented as a linear polyethylene chain functionalized with cyclic carbonate (dioxolanone) moieties and cross-linked by ethylene oxide units. A series of XPEs are prepared by varying the [O]/[Li] ratio (24 to 3) of the stock solution and thoroughly characterized using physicochemical (thermogravimetric analysis-mass spectrometry, differential scanning calorimetry, NMR, etc.) and electrochemical techniques. In addition, quantum chemical calculations are performed to elucidate the correlation between the electrochemical oxidation potential and the lithium ion-ethylene oxide coordination in the stock solution. Later, lithium bis(fluorosulfonyl)imide (LiFSI) salt is incorporated into the electrolyte system to produce a dual-salt XPE that exhibits improved electrochemical performance, a stable interface against lithium metal, and enhanced physical and chemical characteristics to be employed against high-voltage cathodes. The XPE membranes demonstrated excellent resistance against lithium dendrite growth even after reversibly plating and stripping lithium ions for more than 1000 h with a total capacity of 0.5 mAh cm(-2). Finally, the XPE films are assembled in a lab-scale lithium metal battery configuration by using carbon-coated LiFePO4 (LFP) or LiNi0.8Co0.15Al0.05O2 (NCA) as a cathode and galvanostatically cycled at 20, 40, and 60 degrees C. Remarkably, at 20 degrees C, the NCA-based lithium metal cells displayed excellent cycling stability and good capacity retention (>50%) even after 1000 cycles.
Keywords: cross-linked polymer electrolyte; dual-salt electrolyte; high-voltage cathode; lithium metal battery; solvent-free photopolymerization

Effect of aromatic rings and substituent on the performance of lithium batteries with rylene imide cathodes - Aher, Jagdish; Graefenstein, Alexander; Deshmukh, Gunvant; Subramani, Kumar; Krueger, Bastian; Haensch, Mareike; Schwenzel, Julian; Krishnamoorthy, Kothandam; Wittstock, Gunther (ChemElectroChem, 2020)
Rylene imides (RIs) are attractive organic battery materials because of the inherent modularity of the molecules. While strong aggregation of RIs is disadvantageous for fast lithium-ion transport in the organic active material, decreasing the solubility of the RIs in battery electrolytes is essential to avoid performance fading. Therefore, the design and synthesis of RIs for lithium batteries is a non-trivial task that must, among other considerations, balance lithium-ion transport in the solid material vs. low solubility by controlling aggregation and packing. We have chosen triphenylamine (TPA) as a substituent which disrupts the aggregation but maintains a low solubility due to increased aromaticity of TPA. We have synthesized three RIs with one, two, and four aromatic units in the core. All of them showed stable specific capacity over 300 charge-discharge cycles. The batteries also showed specific capacities close to their theoretical capacities with 97-99 % coulombic efficiency. The maximum specific energy and specific power were 197 mWh g(-1) and 37 mW g(-1), respectively.
Keywords: lithium-ion batteries; organic cathode material; rylene imides; solubility; triphenylamine

Efficacy of octahedral molecular sieves for green and sustainable catalytic reactions - Lucas, Nishita; Gurrala, Lakshmiprasad; Halligudi, S. B. (Molecular Catalysis, 2020)
Sustainability and Green Chemistry has emerged as catchphrase in modern era and researchers worldwide have embraced it as new paradigm of development. In this context identifying potential materials able to curb multiple grave issues thus contributing towards sustainability is vital. Catalytic materials are quite potent for addressing current social, economic and environmental problems like harnessing alternative energy source, pollution prevention/remediation and manufacturing of commodity chemicals. Thus, the present review accentuates the efficacy of porous octahedral molecular sieves (OMS) as catalyst for such environmentally important reactions. It discusses about structural importance of OMS and their applications for green and sustainable catalytic reactions. Finally, the limitations are highlighted and future perspectives are presented which will ameliorate its catalytic utilization in energy and environmental domains.
Keywords: catalytic transformations; Lignocellulosic biomass; octahedral molecular sieves; platform chemicals; renewable feedstock

Electrostatic manifestation of micro-heterogeneous solvation structures in deep-eutectic solvents: a spectroscopic approach - Chatterjee, Srijan; Haldar, Tapas; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry B, 2020)
Deep eutectic solvents have emerged as inexpensive green alternatives to conventional solvents for diverse applications in chemistry and biology. Despite their importance as useful media in various applications, little is known about the microscopic solvation structures of deep eutectic solvents around solutes. Herein, we show that the electrostatic field, which can be estimated both from infrared experiments and theory, can act as a unified concept to report on the microscopic heterogeneous solvation of deep eutectic solvents. Using a fluorophore containing the carbonyl moiety as the solute and the electrostatic field as a descriptor of the solvation structure of the deep eutectic solvents, we report the residue-specific distribution, orientation, and hydrogen bonding in deep eutectic solvents constituting of choline chloride and alcohols of varying chain-lengths. We observe that an increase in alcohol chain-length not only affects the alcohol's propensity to form hydrogen bond to the solute but also alters the spatial arrangement of choline cations around the solute, thereby leading to a microheterogeneity in the solvation structure. Moreover, to extend our electrostatic field based strategy to other deep eutectic solvents, we report an emission spectroscopy based method. We show that this method can be applied, in general, to all deep eutectic solvents, irrespective of their constituents. Overall, this work integrates experiments with molecular dynamics simulations to provide insights into the heterogeneous DES solvation.

Enantio- and diastereocontrolled conversion of chiral epoxides to trans-cyclopropane carboxylates: application to the synthesis of cascarillic acid, grenadamide and L-(-)-CCG-II (vol 10, pg 6987, 2012) - Kumar, Pradeep; Dubey, Abhishek; Harbindu, Anand (Organic & Biomolecular Chemistry, 2020)

Fe3+ stabilized 3D cross-linked glycine-melamine formaldehyde networks as precursor for highly efficient oxygen reduction catalyst in alkaline media - Kottarathil, Shijina; Illathvalappil, Rajith; Nisa, S.; Sailaja, G. S.; Mohamed, Peer A.; Nair, Balagopal N.; Gopinathan, Anilkumar M.; Kurungot, Sreekumar; Yamaguchi, Takeo; Hareesh, U. S. (Materials Letters, 2020)
Development of inexpensive oxygen reduction electrocatalyst with high activity and durability is very important. Herein, iron carbide encapsulated pod-like graphitic carbon structures were prepared by simple pyrolysis involving Fe-glycine complex integrated melamine-formaldehyde resin precursor. The best catalyst among those studied, Fe-Gly 2 MF-C, possessing high degree of graphitization (I-D /I-G = 0.99) and enhanced specific surface area (205 m(2)/g) exhibited the highest ORR activity with a half-wave potential of 0.80 V in alkaline medium through the four-electron reduction pathway. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: fuel cell; Graphitic carbon alloy; Iron carbide; ORR

Highly efficient micro-meso acidic H-USY catalyst for one step conversion of wheat straw to ethyl levulinate (biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Mudliar, Sandeep; Bokade, Vijay (Microporous and Mesoporous Materials, 2020)
Ethyl Levulinate (EL), biofuel additive can blend up to 20% with biodiesel to improve its fuel properties. Till the date, there are reports on homogeneous catalysts (H2SO4, ionic liquid) for synthesis of EL from raw biomass like wheat straw. To best of our knowledge, there is no single report on heterogeneous catalyst for one step synthesis of EL directly from wheat straw. This work is a successful attempt to use heterogeneous micro-meso acidic H-USY (post dealumination and desilication) for direct one step conversion of wheat straw to EL with higher EL yield 24.5 wt%, which is probably the highest so far.
Keywords: Acidity; ethyl levulinate; H-USY; Micro-meso; Wheat straw

Influence of gold nanorods on the structure and photonic bandgap in a twist grain boundary phase with smectic C* blocks - Sahoo, Rajalaxmi; Rao, D. S. Shankar; Hiremath, Uma S.; Yelamaggad, V. C.; Shinde, Pravin; Bhagavatula L. V. Prasad; Prasad, S. Krishna (Journal of Molecular Liquids, 2020)
We describe the first report of the influence of gold nanorods (GNR) on the induced twist grain boundary smectic C* (TGBC*) phase in a binary mixture of achiral bent-core and chiral linear liquid crystals. The GNR concentration-dependent phase diagram of these nanocomposites shows that the thermal range of this twist grain boundary phase having smectic C* blocks phase increases by 50% for an intermediate composition compared to that for the host binary mixture without nanorods. The inclusion of the nanorods is seen to have substantial effect on the structural and photonic bandgap features of the TGBC* phase. For example, the helical periodidty gets altered in all the three dimensions: while those within the block undergo a huge increase, the one which is orthogonal to the blocks, shrinks. The spacing of the square grid pattern arising normal to the TGB helix direction increases for the nanocomposites getting even doubled for a certain composition, a feature evidenced by optical microscopy as well as optical diffraction. Xray diffraction clearly brings out the feature that the presence of GNR alters the thermal character of the transition between the TGBC* and the cholesteric phase. Quantitative analysis of the data indicates that the system would remain in the vicinity of a possible tricritical point, a behavior having wider ramifications to understand the underlying critical phenomenon. Based on the experimental observations, and capturing the essence of the reported adaptive defect core targeting mechanism we propose a model wherein GNRs get confined in the grain boundary region. This feature offers a potential to have periodic and anisotropic plasmonic structure arising out of the synergetic interactions between the metal nanorod and the twisted grain boundary structure. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: 3D photonic bandgap; Gold nanorods; Induced phase; TGBC* phase; Tricritical phenomena

Investigation of bond topological and electrostatic properties of plumbagin molecule: an experimental and theoretical charge density study - Kalaiarasi, Chinnasamy; Sivanandam, Magudeeswaran; Suganya, Suresh; Christy, George; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Kumaradhas, Poomani (Journal of Molecular Structure, 2020)
Plumbagin is a naturally occurring derivative with several medicinal properties including antioxidants, antifungal, antimalarial, leprosy and antitumor properties; their structural and electrostatic properties are yet to be determined. The crystal structure of plumbagin has been solved; it shows that the compound crystallizes in P2(1)/c space group with two molecules in the asymmetric unit. The electron density distribution of both molecules have determined from multipole model refinement. Among all the C-O bonds of both molecules (I & II), the OH group connected C-O bond and the methyl group connected C-C bond exhibits less electron density and the negative Laplacian of electron density as well. Further, the electrostatic potential (ESP) surface of two plumbagin molecules show some difference in their electronegative regions. The carbonyl O-atoms exhibit high electronegative ESP regions which are the key reactive locations of plumbagin when bind with the active site of target protein and in the ESP map, an aromatic pi-cloud also observed in one of the molecule. The electron density distribution of O-H center dot center dot center dot O intermolecular interactions between the molecules I and II, reveals that these interactions are found very stronger than the other interactions in the crystal. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Electron density; Electrostatic potential; intermolecular interactions; Plumbagin

Lauric acid sophorolipid: accelerating the gelation of silk fibroin - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita A.; Nisal, Anuya (ACS Omega, 2020)
Silk fibroin (SF) hydrogels find wide applications in tissue engineering. However, their scope has been limited due to the long gelation time in ambient conditions. This paper shows the reduction in gelation time of silk fibroin to minutes upon doping with a newly synthesized lauric acid sophorolipid (LASL). LASL comprises a fatty acid, lauric acid (with a 12-carbon aliphatic chain), that is derivatized by glucose molecules using a non-pathogenic yeast Candida bombicola. LASL was characterized using spectroscopic (Fourier transform infrared spectroscopy) and chromatographic (high-performance liquid chromatography, thin-layer chromatography, and high-resolution mass spectrometry) methods. This gelation of SF is comparable to the effect of an anionic surfactant, sodium dodecyl sulfate (SDS). The microstructure of SF-LASL hydrogels was investigated by small-angle neutron scattering (SANS) measurements and exhibited the beads-on-a-necklace model. The rheological properties of these hydrogels show similarity to SF-SDS hydrogels, therefore presenting a greener alternative for tissue engineering applications.

Ligand structure directed dimensionality reduction (2D -> 1D) in lead bromide perovskite - Bakthavatsalam, Rangarajan; Haris, Muhammed P. U.; Shaikh, Samir R.; Lohar, Amruta; Mohanty, Ashutosh; Moghe, Dhanashree; Sharma, Shivani; Biswas, Chinmoy; Raavi, Sai Santhosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Physical Chemistry C, 2020)
Low dimensional (2D, 1D) lead halide perovskites are currently attracting huge research interest due to their enabling properties. Demonstrating synthetic control on the dimensionality/ structure of these perovskites is highly challenging. Dimensionality in these perovskites is largely dictated by the nature/structure and composition of the incorporating ligands and the utilized synthetic conditions. Here, we demonstrate chemical composition based control on reduction of dimensionality (2D -> 1D) for lead bromide perovskite utilizing 2-(2-aminoethyl)isothiourea dihydrobromide as a common precursor ligand (Isothio Bromide). Controlling the hydrothermal reaction parameters (temperature, time) at a fixed precursor ratio affords corner-shared, contorted 2D sheet perovskite and corner-shared, contorted, chiral 1D chain perovskite. Such dimensionality reduction leads to contrasting photophysical properties: 1D chain perovskite shows long-lived and self-trapped broad band emission, whereas 2D perovskite shows short-lived, band edge emission with a long tail. Mechanistic studies and single crystal structure analysis reveal the incorporation of the utilized precursor ligand (Isothio Bromide) in 2D perovskite. Surprisingly, the 1D perovskite is found to be chiral (P2(1) space group) incorporating 2-(2-aminoethyldisulfanyl)ethanamine and ammonium ions as the achiral ligands generated in situ due to hydrothermal cleavage of the precursor (Isothio Bromide) ligand. Such structural and compositional change of the ligands, which manifests a different hydrogen bonding network in the resultant perovskite structure, plays a decisive role in dictating the final molecular formula and dimensionality/structure of the perovskite which largely controls their photophysical properties.

Lignocellulose-derived platform molecules: an introduction - Shinde, Suhas H.; Hengne, Amol; Rode, Chandrashekhar V. (Recent Advances in Development of Platform Chemicals, 2020)
Fossil feedstocks such as crude oil, natural gas, and coal are formed by natural anaerobic decomposition of buried organisms for a period of more than 650 million years. On the other hand, agrobiomass is quick to grow and becomes a renewable source of chemical and fuel production through processing in a biorefinery.
Keywords: Biomass; Biorefinery Cellulose; Lignocellulose Petrofinery; Platform molecules

Microstructure and yielding of capillary force induced gel - Huprikar, Sameer; Usgaonkar, Saurabh; Lele, Ashish K.; Orpe, Ashish V. (Rheologica Acta, 2020)
We have investigated the rheology and structure of a gel formed from a mixture of non-Brownian particles and two immiscible liquids. The suspension of particles in a liquid undergoes gelation upon the addition of a small content of second, wetting liquid which forms liquid bridges between particles leading to a sample spanning network. The rheology of this gel primarily exhibits a yield stress at low shear rates followed by a linear variation of shear stress at high shear rates. The apparent yield stress extracted from the flow curves increases rapidly with volume fraction of the second liquid before saturation, while it exhibits a monotonic increase with increasing particle concentration. Rescaling of the yield stress curves using suitable shift factors results in an empirical expression for the yield stress showing squared dependence on liquid fraction and a rapid increase with particle fraction above a certain value, both combined in a highly non-linear manner. The microstructural variations with changing secondary liquid content and particle fractions are captured using three-dimensional X-ray tomography technique. The microstructure is observed to show increased local compactness with increased liquid content and increased spatial homogeneity with increased particle fractions. The images from X-ray tomography are analysed to obtain the distributions of particle-particle bonds (coordination number) in the system which serve to explain the observed yield stress behaviour in a qualitative manner.
Keywords: Capillary force; Flow curve; gel; Microstructure; Rheology; Yield stress

Morphology and dynamics of self-assembled structures in mixed surfactant systems (SDS plus CAPB) in the context of methane hydrate growth - Hande, Vrushali; Choudhary, Nilesh; Chakrabarty, Suman; Kumar, Rajnish (Journal of Molecular Liquids, 2020)
Presence of small dosages of surfactants in the aqueous phase has been reported to enhance the rate of gas hydrate (clathrate) formation. In this work, using extensive atomistic molecular dynamics (MD) simulations, we have investigated how SDS (surfactant) aggregates in the presence/absence of CAPB (co-surfactant) at ambient conditions (temperature 298 K and pressure 1 bar) and at hydrate forming conditions (temperature 275 K and pressure 50 bar) resulting in altered growth kinetics of methane hydrate. We observe that SDS forms aggregates of different sizes and shapes depending on the thermodynamic condition starting from random distributions of the surfactants. In the presence of the CAPB co-surfactant, tightly packed mixed aggregates are formed. Using various structural order parameters, we demonstrate that shape of the aggregates deviates from spherical as well as cylindrical symmetry. During the aggregation process in presence of methane, the methane molecules get absorbed into the aggregates, enhance the aggregation kinetics and provide structural flexibility to the aggregates. This result is partly in agreement with previous experimental observations that SDS (with or without a co-surfactant) may form micelle-like structures under hydrate forming conditions and that methane gets absorbed by these aggregates leading to enhanced solubility of methane in the aqueous phase. Further, we have investigated the dynamics of shape fluctuations of the aggregates and observed that several distinct relaxation timescales exist in these heterogenous systems. (C) 2020 Elsevier B.V. All rights reserved.

Nanoporous covalent organic framework embedded with Fe/Fe3O4 nanoparticles as air-stable low-density nanomagnets - Kushwaha, Rinku; Kaleeswaran, Dhananjayan; Haldar, Sattwick; Chakraborty, Debanjan; Mullangi, Dinesh; Borah, Aditya; Vinod, Chathakudath P.; Murugavel, Ramaswamy; Vaidhyanathan, Ramanathan (ACS Applied Nano Materials, 2020)
Covalent organic frameworks (COFs) made of light atoms such as H, C, N, and O with a significant void-to-framework ratio are excellent low-density supports for nanoparticles (nPs). Their framework can be precoded with heteroatoms to ensure binding with metallic nanoclusters. With these advantages, if controlled amounts of magnetic nPs are anchored to them, they can yield low-density organic-inorganic nanomagnets. Their organic nature facilitates fusion with bulk materials such as paper/textile to enable bulk composites with well-dispersed low-density magnets, which have potential for defense and next-generation aviation applications. Herein, we have grown small Fe/Fe3O4 nPs (5-18 wt %) inside a COF. Interestingly, 300 mg of this organic-inorganic framework material (containing 50 mg of nPs) can lift a vial of similar to 15,000 mg (300 times heavier). Also, the hydrophobic COF wraps around the Fe/Fe3O4 nanocluster retaining its room-temperature magnetic character even after 1 year, while the naked nPs lose it within a few days because of air oxidation. Bulk composites with paper and polymers have been made using this low-density Fe-COF to demonstrate their processability.
Keywords: air-stable nanomagnets; Covalent organic framework; Fe/Fe3O4 nanoparticles; low-density nanomagnets; magnetic rayon; nanoporous COF

One pot hydrogenation of furfural to 2-methyl tetrahydrofuran over supported mono- and Bi-metallic catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K. -W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
2-Methyltetrahydrofuran is a valuable commercial product that can be obtained by direct hydrogenation of furfural. In the present study, among several carbon supported bimetallic Ir-Ni catalysts with different loadings screened, 4% Ir-4% Ni/C catalyst showed excellent activity in terms of direct conversion (99%) to 2-MeTHF with a maximum selectivity of similar to 74% at 220 degrees C and 750 psig, suppressing the formation of side chain as well as ring opening products. The catalytic activity was found to be mainly affected by catalyst preparation methods, metal loadings, surface composition, temperature, pressure and catalyst loading. HR-TEM and STEM revealed well dispersed Ir-Ni NPs having the particle sizes in the range of 2 to 5 nm. Different phases of Ir i. e. Ir degrees and IrO(2)as well as oxygen vacancies were found to be responsible for hydrogenation of furfural to 2-methyl furan while, Ni degrees and NiO were responsible for further hydrogenation to 2-MeTHF. The synergic effect between Ir and Ni was established through XPS, H-2-TPR analysis. With the help of some control experiments, the plausible reaction pathway was also proposed. The catalyst prepared by co-impregnation method found more effective than prepared by sequential addition method. At lower Ni loadings of 1% and 2%, low temperature of 160 degrees C as well as at low H(2)pressure of 250 psig, mixture of furfuryl alcohol and 2-methyl furan were formed selectively. Catalyst could be successfully reused up to 3 times without leaching of metals.
Keywords: 2-Methyltetrahydrofuran; Bimetallic catalyst; furfural; Hydrogenation; OER type mechanism

Preparation, spectroscopic characterization, theoretical investigations, and in vitro anticancer activity of Cd(II), Ni(II), Zn(II), and Cu(II) complexes of 4(3H)-quinazolinone-derived schiff base - Ashok, Ubale Panchsheela; Kollur, Shiva Prasad; Anil, Nishad; Arun, Bansode Prakash; Jadhav, Sanjay Namdev; Sarsamkar, Sanjay; Helavi, Vasant Baburao; Srinivasan, Asha; Kaulage, Sandeep; Veerapur, Ravindra; Al-Rashed, Sarah; Syed, Asad; et al. (Molecules, 2020)
Herein, we report the synthesis and characterization of a new Schiff base ligand 3-[[(E)-(3-hydroxyphenyl)-methylidene]amino]-2-methyl-quinazolin-4(3 H)-one (HAMQ) and its Cd(II), Ni(II), Zn(II), and Cu(II) complexes (C-1-C-4). The ligand HAMQ was synthesized by reacting 3-hydroxybenzaldehyde and 3-amino-2-methyl-4(3H)-quinazolinone in a 1:1 molar ratio. The structure of the ligand and its complexes (C-1-C-4) were evaluated using ultraviolet (UV)-visible (Vis) light spectroscopy, H-1-NMR, Fourier-transform infrared (FT-IR) spectroscopy, MS, elemental analysis, conductance data, and thermogravimetric analysis (TGA). The characterization results suggested that the bidentate ligand, HAMQ, coordinated to the metal center through the lactum oxygen and the azomethine nitrogen. Moreover, all the metal complexes were analyzed using powder X-ray diffraction studies, which revealed that all of them belong to a triclinic crystal system. The research was supplemented by density functional theory (DFT) studies on the IR and UV-Vis spectra, as well as the chemical reactivity of the HAMQ and its four metallic derivatives making use of conceptual density functional theory (CDFT) by means of KID (Koopmans in DFT) methodology. The synthesized complexes displayed significant in vitro anticancer activity against human cancer cell lines (HeLa and HCT-115).
Keywords: 3-quinolin-4(3H)-one; chemical reactivity properties; conceptual DFT; Metal complexes; spectral studies

Simultaneous determination of anthraquinone, flavonoids, and phenolic antidiabetic compounds from cassia auriculata seeds by validated UHPLC based MS/MS method - Girme, Aboli; Saste, Ganesh; Chinchansure, Ashish; Joshi, Swati; Kunkulol, Rahul; Hingorani, Lal; Patwardhan, Bhushan (Mass Spectrometry Letters, 2020)
A systematic isolation and characterization study for Cassia auriculata (CA) seeds resulted in identifying antidiabetic compounds 1,3,8-trihydroxyanthraquinone and quercetin, quercetin-3-O-rutinoside, gallic acid, caffeic acid, ferulic acid, and ellagic acid. The ultra-high-performance liquid chromatography based triple quadrupole mass spectrometry methodology was developed and validated for simultaneous identification and confirmation of these compounds from CA seeds. Multiple reaction monitoring (MRM) based quantification method was developed with MRM optimizer software for MS1 and MS2 mass analysis. The method was optimized on precursor ions and product ions with the ion ratio of each compound. The calibration curves of seven bioactive analytes showed excellent linearity (r2 ≥ 0.99). The quantitation results found precise (RSD, < 10 %) with good recoveries (84.58 to 101.42%). The matrix effect and extraction recoveries were found within the range (91.66 to 102.11%) for the CA seeds. This is the first MS/MS-based methodology applied to quantifying seven antidiabetic compounds in CA seeds and its extract for quality control purposes.

Spectroscopic evidences for the size dependent generation of pd species responsible for the low temperature CO oxidation activity on Pd-SBA-15 nanocatalyst - Soni, Yogita; Pradhan, Sumanta; Bamnia, Mahesh K.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.; Khan, Tuhin Suvra; Haider, M. A.; Vinod, C. P. (Applied Catalysis B-Environmental, 2020)
A comprehensive size dependent CO oxidation activity has been demonstrated for Pd-SBA-15 catalysts with Pd NPs of varying sizes such as 1-2, 4-6 and 7-10 nm. Pd-SBA-15 catalyst with smallest sized NPs (Pd-S-N) has been synthesized by modified deposition precipitation method recently developed in our lab. Pd-S-N catalyst (reduced at 400 degrees C) demonstrated CO oxidation activity with lower light off temperature (50 degrees C), clearly one of the best reported for a Pd-silica system. A detailed XPS and in-situ DRIFTS analyses further supported by XAS and DFT calculations reveal the presence of easily decomposable highvalent Pd-oxide on co-ordinatively unsaturated Pd sites (Pdcus). Weak binding of CO on Pdcus sites in small Pd NPs leaving sites for oxygen activation is attributed to the low temperature activity of Pd-S-N for CO oxidation.
Keywords: CO oxidation; high-valent Pd species; Pd nanoparticles; SBA-15; under coordinated Pd atoms

Study of interfacial adhesion between nickel-titanium shape memory alloy and a polymer matrix by laser surface pattern - Samal, Sneha; Tyc, Ondrej; Heller, Ludek; Sittner, Petr; Malik, Monika; Poddar, Pankaj; Catauro, Michelina; Blanco, Ignazio (Applied Sciences-Basel, 2020)
The aim of this article is to investigate the interfacial adhesion of Ni-Ti shape memory alloy with a polymer matrix of Poly (methyl methacrylate) (PMMA). The surface pattern on Ni-Ti plates was channeled by a solid state laser machine. The laser machine allows for creating channels on the Ni-Ti surface for infiltration of the PMMA matrix, which could be attached as an intra-surface locking pattern to the Ni-Ti surface. The influence of the PMMA matrix on the surface of the NiTi plate was evaluated by thermomechanical analysis (TMA) and dynamic mechanical analysis (DMA). The surface characterization was carried out by an optical microscope on the PMMA/NiTi composite after mechanical testing. During mechanical testing, the polymer displays the multiple cracks in the longitudinal direction that result in slipping and fracture. TMA and DMA analyses were performed on the Ni-Ti- and PMMA-coated Ni-Ti ribbon to observe elasticity and the storage modulus for both samples. Better adhesion than 80 % was observed in the Ni-Ti surface, in the laser surface pattern, in comparison to the free plain surface. However, the polymer acts as mechanical backing that caused a reduction in the shape-memory properties of the composite material.
Keywords: adhesion; mechanical properties; NiTi composites; NiTi plate; PMMA; Polymer; surface features

Template assisted synthesis of Ni,N co-doped porous carbon from Ni incorporated ZIF-8 frameworks for electrocatalytic oxygen reduction reaction - Priya K., Vaishna; Thomas, Minju; Illathvalappil, Rajith; K., Shijina; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (New Journal of Chemistry, 2020)
A heteroatom doped porous carbon electrocatalyst with enhanced oxygen reduction reaction (ORR) performance in alkaline medium was obtained by high temperature treatment of Ni incorporated ZIF-8 frameworks and its composite with g-C(3)N(4)as a supporting matrix template. The morphology and porosity of this heteroatom containing carbon were tuned by varying the Ni : Zn molar ratio in Ni/Zn ZIF-8 and Ni/Zn ZIF-8@g-C(3)N(4)composites. The template aided synthetic strategy using g-C(3)N(4)helped in the controlled decomposition of composites leading to a heteroporous sheet like architecture with increased nitrogen content. The Ni/Zn ZIF-8 sample on heat treatment in the 800-1000 degrees C temperature range led to the formation of Ni,N co-doped porous carbon (Ni-NPC) with Ni-C active sites. The defective sites induced by nickel carbide along with the distributed N atoms on the carbon surface enabled active O(2)adsorption sites. The high surface area, high degree of graphitisation as well as the defects created by well dispersed N and Ni on porous carbon matrices favoured charge separation leading to higher electrochemical ORR activity. The Ni,N co-doped carbon catalyst in alkaline medium exhibited a limiting current density of 5.2 mA cm(-2)with a half-wave potential of 0.76 Vvs.RHE in 0.1 M KOH. The catalyst also showed improved methanol tolerance and better stability compared to the standard Pt/C catalyst.

Triazine-based organic polymer-catalysed conversion of epoxide to cyclic carbonate under ambient CO2 pressure - Biswas, Tanmoy; Halder, Arjun; Paliwal, Khusboo S.; Mitra, Antarip; Tudu, Gouri; Banerjee, Rahul; Mahalingam, Venkataramanan (Chemistry-An Asian Journal, 2020)
In this work we have achieved epoxide to cyclic carbonate conversion using a metal-free polymeric catalyst under ambient CO2 pressure (1.02 atm) using a balloon setup. The triazine containing polymer (CYA-ANIS) was prepared from cyanuric chloride (CYA-Cl) and o-dianisidine (ANIS) in anhydrous DMF as solvent by refluxing under the N-2 gas environment. The presence of triazine and amine functional groups in the polymer results in the adsorption of CO2 up to 7 cc/g at 273 K. This inspired us to utilize the polymer for the conversion of a series of functionalised epoxides into their corresponding cyclic carbonates in the presence of tetrabutyl ammonium iodide (TBAI) as co-catalyst. The product has wide range of applications like solvent in lithium ion battery, precursor for polycarbonate, etc. The catalyst was efficient for the conversion of different mono and di-epoxides into their corresponding cyclic carbonates under atmospheric pressure in the presence of TBAI as co-catalyst. The study indicates that epoxide attached with electron withdrawing groups (like, CH2Cl, glycidyl ether, etc.) displayed better conversion compared to simple alkane chain attached epoxides. This is mainly due to the stabilization of electron rich intermediates produced during the reaction (e. g. epoxide ring opening or CO2 incorporation into the halo-alkoxide anion). This catalyst mixture was capable to maintain its reactivity up to five cycles without losing its activity. Post catalytic characterization clearly supports the heterogeneous and recyclable nature of the catalyst.
Keywords: CO2 fixation; cyclic carbonates; epoxides; Heterogeneouscatalyst; metal free catalyst; Triazinepolymer

Tris-heteroleptic ruthenium(II) polypyridyl complexes: Synthesis, structural characterization, photophysical, electrochemistry and biological properties - Bhat, Satish S.; Kumbhar, Avinash S.; Purandare, Neeraja; Khan, Ayesha; Grampp, Gunter; Loennecke, Peter; Hey-Hawkins, Evamarie; Dixit, Ruchi; Vanka, Kumar (Journal of Inorganic Biochemistry, 2020)
{Three water-soluble tris-heteroleptic ruthenium(II) polypyridyl complexes [Ru(bpy)(phen)(bpg)](2+) (1), [Ru (bpy)(dppz)(bpg)]2+ (2), and [Ru(phen)(dppz)(bpg)]2+ (3) (where bpy = 2,2'-bipyridine
Keywords: Circular dichroism; Cytotoxicity; fluorescence; Polypyridyl; ruthenium

Whole-cell phenotypic screening of medicines for malaria venture pathogen box identifies specific inhibitors of plasmodium falciparum late-stage development and egress - Patra, Alok Tanala; Hingamire, Tejashri; Belekar, Meenakshi A.; Xiong, Aoli; Subramanian, Gowtham; Bozdech, Zbynek; Preiser, Peter; Shanmugam, Dhanasekaran; Chandramohanadas, Rajesh (Antimicrobial Agents and Chemotherapy, 2020)
We report a systematic, cellular phenotype-based antimalarial screening of the Medicines for Malaria Venture Pathogen Box collection, which facilitated the identification of specific blockers of late-stage intraerythrocytic development of Plasmodium falciparum. First, from standard growth inhibition assays, we identified 173 molecules with antimalarial activity (50% effective concentration [EC50] <= 10 mu M), which included 62 additional molecules over previously known antimalarial candidates from the Pathogen Box. We identified 90 molecules with EC50 of <= 1 mu M, which had significant effect on the ring-trophozoite transition, while 9 molecules inhibited the trophozoite-schizont transition and 21 molecules inhibited the schizontring transition (with >= 50% parasites failing to proceed to the next stage) at 1 mu M. We therefore rescreened all 173 molecules and validated hits in microscopy to prioritize 12 hits as selective blockers of the schizont-ring transition. Seven of these molecules inhibited the calcium ionophore-induced egress of Toxoplasma gondii, a related apicomplexan parasite, suggesting that the inhibitors may be acting via a conserved mechanism which could be further exploited for target identification studies. We demonstrate that two molecules, MMV020670 and MMV026356, identified as schizont inhibitors in our screens, induce the fragmentation of DNA in merozoites, thereby impairing their ability to egress and invade. Further mechanistic studies would facilitate the therapeutic exploitation of these molecules as broadly active inhibitors targeting late-stage development and egress of apicomplexan parasites relevant to human health.
Keywords: DNA fragmentation; egress; Medicines for Malaria Venture; MMV; Pathogen Box; phenotypic screening; Plasmodium falciparum; schizonts; stage-specific inhibition

Accurate identification of bioactive meliaceae limonoids by UHPLC-MS/ms based structure-fragment relationships (SFRs) - Mulani, Fayaj A.; Nandikol, Sharvani S.; Haldar, Saikat; Thulasiram, V, Hirekodathakallu (ACS Omega, 2021)
Y Limonoids are bioactive plant specialized metabolites found in the Meliaceae family. The basic limonoids, i.e., azadiradione, epoxyazadiradione, and gedunin have been exploited for various bioactivities and therefore are the potential drug leads for tomorrow. However, their low abundance, structural similarity, and lack of adequate mass fragmentation data have hampered their accurate identification and quantification from various sources. In the present study, basic limonoids such as azadirone, azadiradione, epoxyazadiradione, and gedunin isolated from Neem were utilized for the synthesis of their derivatives and isotopologs. A total of 30 one compounds were used in this study among which five were isolated, two were biotransformed, and 24 were synthesized. Among the synthesized compounds nine are novel compounds including six deuterated analogs/isotopologs which are (1,3-H-2)-1,2dihydro-3 beta-hydroxyazadiradione (9), (1,3,16-H-2)-1,2-dihydro-3 beta-16 beta-dihydroxyazadiradione (10), 3 beta-hydroxyazadiradione (11), 3 beta-16 beta-dihydroxyazadiradione (12), (3-H-2)-3 beta-hydroxyazadiradione (13), (3,16-H-2)-3 beta-16 beta-dihydroxyazadiradione (14), (1,3,7-H-2)-1,2-dihydro-3 beta-hydroxy-7-deacetylazadiradione (15), 1,2,20,21,22,23-hexahydroazadiradione (17), and (1,3-H-2)-1,2-dihydro-3 beta-hydroxygedunin (29). These limonoids along with their semisynthesized derivatives were subjected to ultra high performance liquid chromatography mass spectrometry (UHPLC-MS/MS) and the fragmentation pathway was established based on structure-fragment relationships (SFRs), utilizing high resolution MS/MS data. We have developed a most reliable and easily reproducible protocol describing in depth analysis of SFRs based on the structural modifications and synthesis of isotopologs. Also, the MS/MS fragment library of these basic limonoids generated in this study acts as a fingerprint for accurate identification and quantification of limonoids by MS/MS analysis in various plant tissue extracts, phytopharmaceutical formulations and biological samples.

Annulation of enals with carbamoylpropiolates via NHC-catalyzed enolate pathway: access to functionalized maleimides/iso-maleimides and synthesis of aspergillus FH-X-213 - Viveki, Amol B.; Pol, Mahesh D.; Halder, Priyanka; Sonavane, Sameer R.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2021)
Herein we report the N-heterocyclic carbene (NHC)-catalyzed [3 + 2] annulation of alpha,beta-unsaturated aldehydes with carbamoylpropiolates via an unusual enolate pathway leading to the construction of highly functionalized maleimides or isomaleimides. The electronic effect imposed by the alkyl/aryl group present on the amide nitrogen of carbamoylpropiolates plays a crucial role in the selective formation of these important five-membered heterocyclic building blocks. The developed protocol is mild and tolerates a wide range of substituents on both substrates. The application of this protocol in the synthesis of the antibacterial natural product Aspergillus FH-X-213 has also been demonstrated.

Antitumor effects of Ir(III)-2H-indazole complexes for triple negative breast cancer - Panchangam, Rajeeva Lochana; Rao, Ramdas Nishanth; Balamurali, Musuvathi Motilal; Hingamire, Tejashri B.; Shanmugam, Dhanasekaran; Manickam, Venkatraman; Chanda, Kaushik (Inorganic Chemistry, 2021)
In this work, we have synthesized a series of novel C,N-cyclometalated 2H-indazole-ruthenium(II) and -iridium(III) complexes with varying substituents (H, CH3, isopropyl, and CF3) in the R4 position of the phenyl ring of the 2H-indazole chelating ligand. All of the complexes were characterized by 1H, 13C, high-resolution mass spectrometry, and elemental analysis. The methyl-substituted 2H-indazole-Ir(III) complex was further characterized by single-crystal X-ray analysis. The cytotoxic activity of new ruthenium(II) and iridium(III) compounds has been evaluated in a panel of triple negative breast cancer (TNBC) cell lines (MDA-MB-231 and MDA-MB-468) and colon cancer cell line HCT-116 to investigate their structure–activity relationships. Most of these new complexes have shown appreciable activity, comparable to or significantly better than that of cisplatin in TNBC cell lines. R4 substitution of the phenyl ring of the 2H-indazole ligand with methyl and isopropyl substituents showed increased potency in ruthenium(II) and iridium(III) complexes compared to that of their parent compounds in all cell lines. These novel transition metal-based complexes exhibited high specificity toward cancer cells by inducing alterations in the metabolism and proliferation of cancer cells. In general, iridium complexes are more active than the corresponding ruthenium complexes. The new Ir(III)-2H-indazole complex with an isopropyl substituent induced mitochondrial damage by generating large amounts of reactive oxygen species (ROS), which triggered mitochondrion-mediated apoptosis in TNBC cell line MDA-MB-468. Moreover, this complex also induced G2/M phase cell cycle arrest and inhibited cellular migration of TNBC cells. Our findings reveal the key roles of the novel C–N-cyclometalated 2H-indazole-Ir(III) complex to specifically induce toxicity in cancer cell lines through contributing effects of ROS-induced mitochondrial disruption along with chromosomal and mitochondrial DNA target inhibition.

Construction of IrO2@Mn3O4 core-shell heterostructured nanocomposites for high performance symmetric supercapacitor device - Beknalkar, S. A.; Teli, A. M.; Harale, N. S.; Shin, J. C.; Patil, P. S. (Journal of Alloys and Compounds, 2021)
In the present work, we have designed and synthesized nanocomposite of IrO2@Mn3O4 with two-step simple and scalable chemical routes. In this route, nanofibers of IrO2 were synthesized by a single nozzle electrospinning technique onto which Mn3O4 was overlaid by a simple SILAR route. The ratio of Mn3O4 and IrO2 was varied by varying the SILAR cycles onto electrospun IrO2 thin film as 20, 40, 60, and 80 cycles. The structural, morphological, and energy storage performance of IrO2@Mn3O4 composite elec-trodes were investigated. A 2 V kinetic potential with a rectangular-shaped cyclic voltammogram was observed for the IrO2@Mn3O4 electrodes. Moreover, the specific capacitance of 1027 F/g at 1 mA/cm(2) was observed for the optimized electrode which is superior as compared with other electrodes. The opti-mized electrode showed better current and voltage than the individual compounds which might be due to the synergic effect of IrO2 and Mn3O4. Finally, a PVA-LiClO4 gel electrolyte-based solid-state IrO2@ Mn3O4//IrO2@Mn3O4 symmetric device was fabricated. The symmetric device possessed an energy density of 81 Wh/kg with a power delivery of 714 W/kg which was capable to light up a green LED. Hence, the 2D transition metal oxides laminated on 1D metal oxides with high conductivity can be promising electrodes for future research. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: And nanoflakes; Charge storage kinetics; Electrochemical properties; electrospinning; IrO2@Mn3O4 nanocomposite; nanofibers; SILAR

CuO as a reactive and reusable reagent for the hydrogenation of nitroarenes - Rajendran, K.; Pandurangan, N.; Vinod, C. P.; Khan, Tuhin S.; Gupta, Shelaka; Haider, M. Ali; Jagadeesan, D. (Applied Catalysis B-Environmental, 2021)
{Copper oxide (CuO) is used as a reusable solid reagent for hydrogenation of nitroarenes to aminoarenes. The use of CuO resulted in 100 % conversion of 2.9 mmol of nitrobenzene to aniline in 45 s at room temperature using hydrazine hydrate as the reducing agent. During the reaction, CuO is converted to inactive metallic Cu which can be regenerated to active CuO by thermal oxidation. DFT simulations indicated facile formation of oxygen vacancies (EO
Keywords: Copper vacancy; CuO; Hydrogenation; Nitroarene reduction; Oxygen defects; Reactive solids

Curious case of aqueous warfarin: structural isomers or distinct excited states? - Sakpal, Sushil S.; Ghosh, Deborin; Manae, Meghna A.; Hazra, Anirban; Bagchi, Sayan (Journal of Physical Chemistry B, 2021)
Warfarin is a potent anti-coagulant drug and is on the World Health Organization's List of Essential Medicines. Additionally, it displays fluorescence enhancement upon binding to human serum albumin, making warfarin a prototype fluorescent probe in biology. Despite its biological significance, the current structural assignment of warfarin in aqueous solution is based on indirect evidence in organic solvents. Warfarin is known to exist in different isomeric forms-open-chain, hemiketal, and anionic forms-based on the solvent and pH. Moreover, warfarin displays a dual absorption feature in several solvents, which has been employed to study the ring-chain isomerism between its open-chain and hemiketal isomers. In this study, our pH-dependent experiments on warfarin and structurally constrained warfarin derivatives in aqueous solution demonstrate that the structural assignment of warfarin solely on the basis of its absorption spectrum is erroneous. Using a combination of steady-state and time-resolved spectroscopic experiments, along with quantum chemical calculations, we assign the observed dual absorption to two distinct pi ->pi* transitions in the 4-hydroxycoumarin moiety of warfarin. Furthermore, we unambiguously identify the isomeric form of warfarin that binds to human serum albumin in aqueous buffer.

Density functional theory-based study of the magnetic and optical properties of PbMO3 (M = Cr, Fe) using the modified BeckeJohnson mBJ functional (vol 128, pg 275, 2019) - Mahmood, Q.; Hassan, M.; Bhamu, K. C.; Yaseen, M.; Ramay, S. M.; Mahmood, A. (Journal of Physics and Chemistry of Solids, 2021)

Design and scale-up of continuous di-nitration reaction using pinched tube flow reactor - Hussain, Arshad; Sharma, Mrityunjay; Patil, Suneha; Acharya, Roopashree B.; Kute, Mahesh; Waghchaure, Aishwarya; Kulkarni, Amol A. (Journal of Flow Chemistry, 2021)
Scale-up of the di-nitration reaction for synthesis of selective herbicide pendimethalin using only nitric acid in continuous flow is presented in this work. This work showcases an approach for smooth scale-up for an herbicide for a production capacity of 50 kg/day using a pinched tube reactor. The approach begins with the batch experiments followed by flow synthesis using a 1/8-inchSS316 helical coil tube where kinetics of the di-nitration was determined, and process optimization was done. Systematic approach was followed for quantification of heat transfer, mass transfer and residence time distribution and scale-up. Detailed scale-up methodology is presented with effect of relevant parameters for successful scale-up. Modular pilot plant with inline quenching, extraction and separation are some of the salient features presented in this work.
Keywords: continuous flow; nitration; Pinched tube; RTD; scale-up

Direct oxidation of cyclohexane to adipic acid by a WFeCoO(OH) catalyst: role of bronsted acidity and oxygen vacancies - Vernekar, Dnyanesh; Dayyan, Mohammad; Ratha, Satyajit; Rode, V, Chandrashekhar; Haider, M. Ali; Khan, Tuhin Suvra; Jagadeesan, Dinesh (ACS Catalysis, 2021)
This work reports the catalytic activity of the trimetallic mixed-metal oxyhydroxide WFeCoO(OH) for the direct oxidation of cyclohexane to adipic acid (AA) without the use of concentrated HNO3. WFeCoO(OH) displayed a 40% conversion of cyclohexane and a 67% selectivity to AA under relatively milder conditions of temperature (90 degrees C) and pressure (1 atm). Experimental evidence confirmed the presence of acidic, basic, and redox sites on WFeCoO(OH). The detailed investigation revealed that doping W in the Co-FeO(OH) matrix increased the amount of surface lattice oxygen (OS-L) and caused a significant surge in acidity (5.1 mmol/g). The calculated deprotonation energy of WFeCoO(OH) was 1434 kJ/mol, and the trend in acidity was WCoO(OH) < WFeCoO(OH) < FeCoO(OH) similar to CoO(OH). Energy calculations showed that WFeCoO(OH) had a high propensity to generate oxygen vacancies by the loss of either a water molecule or an oxygen atom (-132.2 or -140.9 kJ/mol, respectively). Basicity was generated due to the presence of conjugate pairs of the surface hydroxyl groups. The combined action of the trifunctional acidic, basic, and redox-active metal centers along with the oxygen vacancies was responsible for the enhanced catalytic performance.
Keywords: Adipic Acid; deprotonation energy; metal oxyhydroxides; multifunctional catalysts; oxygen vacancies

Direct synthesis of mesoporous siliceous phosphotungstic acid and its superior catalytic activity on the cyclohexylation of phenol - Ilbeygi, Hamid; Sawant, Dhanashri P.; Ruban, Sujanya M.; Reshma, Kokane S.; Umbarkar, Shubhangi B.; Halligudi, Shivappa B.; Vinu, Ajayan (Journal of Physical Chemistry C, 2021)
The synthesis of highly active and reusable mesoporous siliceous phosphotungstic acid materials (mPTA-Si) which are prepared through a simple self-assembly between phosphotungstic acid (PTA), the polymeric surfactant, and the silica precursor assisted by KCl for cyclohexylation of phenol is reported. The surface area and the acidity of these materials are tuned with a simple adjustment of PTA in the silica framework. The prepared samples exhibit mesoporous structure with a high surface area, but the structure is collapsed when the loading of PTA is high. It is established that the Keggin structure of PTA is retained on the final mPTA-Si. mPTA-Si with different loadings of PTA are employed as the catalysts for the cyclohexylation of phenol under liquid phase conditions. Among the catalysts studied, 10.0-mPTA-8.3Si calcined at 350 degrees C is found to be highly active, selective, and recyclable and offers 100% conversion of phenol with the highest selectivity for p-cyclohexylphenol (96.8%).

Editorial special issue in the journal of flow chemistry: engineering aspects of flow chemistry - Kockmann, Norbert; Hartman, Ryan; Kulkarni, Amol (Journal of Flow Chemistry, 2021)

Effect of Mn2+ substitution into the hst lattice of ZnO via sol-gel route for boosting the dye-sensitized solar cells performance - Kumbhar, Deepak; Delekar, Sagar; Kumbhar, Sarita; Dhodamani, Ananta; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Chemical Papers, 2021)
In this study, Mn2+ ion is doped in ZnO lattice framework at 1, 3 and 5 wt % by a simple and low-cost sol-gel route to attain improved optoelectronic response. The structural investigation by XRD and Raman analysis explores the formation of hexagonal wurtzite framework with variations in lattice parameters comprising peak intensities favors the Mn doping. The extent of doping was supported by EDS analysis, while XPS confirms doping in + 2 chemical state. The optical investigation by UV-visible and PL provides prominent peaks that also specify peak shifting in order of doping level, while the significant hexagon-shaped nanoparticle (NP) formation was deduced in SEM and TEM micrographs. These proficient ZnO NPs have been deposited on fluorine-doped tin oxide (FTO) conducting glass plate by doctor-blade technique to get photoanodes. The electrical performance of these photoanodes especially photocurrent generation was investigated under standard AM 1.5 one sun illuminations. The highest photoconversion efficiency was attained for 3% Mn-doped ZnO photoanode after xanthene-based organic dye sensitization with output efficiency (eta%) of 0.25% higher than 0.03% of bare ZnO. The comparable ionic radii with exactly half-filled 3d orbital simply overlap with the ZnO valence bond responsible for enhanced overall structural and optical properties that beneficial for DSSCs performance.
Keywords: gel; Mixed dye; Mn-doped ZnO; Photoelectrochemical cell; Sol&#8211

Effect of Mn2+ substitution into the hst lattice of ZnO via sol-gel route for boosting the dye-sensitized solar cells performance (Apr, 10.1007/s11696-021-01615-w, 2021) - Kumbhar, Deepak; Delekar, Sagar; Kumbhar, Sarita; Dhodamani, Ananta; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Chemical Papers, 2021)

Electronic and optical properties of vacancy ordered double perovskites A(2)BX(6) (A=Rb, Cs; B=Sn, Pd, Pt; and X=Cl, Br, I): a first principles study - Faizan, Muhammad; Bhamu, K. C.; Murtaza, Ghulam; He, Xin; Kulhari, Neeraj; AL-Anazy, Murefah Mana; Khan, Shah Haidar (Scientific Reports, 2021)
The highly successful PBE functional and the modified Becke-Johnson exchange potential were used to calculate the structural, electronic, and optical properties of the vacancy-ordered double perovskites A(2)BX(6) (A=Rb, Cs; B=Sn, Pd, Pt; X=Cl, Br, and I) using the density functional theory, a first principles approach. The convex hull approach was used to check the thermodynamic stability of the compounds. The calculated parameters (lattice constants, band gap, and bond lengths) are in tune with the available experimental and theoretical results. The compounds, Rb2PdBr6 and Cs2PtI6, exhibit band gaps within the optimal range of 0.9-1.6 eV, required for the single-junction photovoltaic applications. The photovoltaic efficiency of the studied materials was assessed using the spectroscopic-limited-maximum-efficiency (SLME) metric as well as the optical properties. The ideal band gap, high dielectric constants, and optimum light absorption of these perovskites make them suitable for high performance single and multi-junction perovskite solar cells.

Enhanced photoelectrochemical cell performance of Co doped ZnO nanoparticles sensitized by affordable mixed dyes as sensitizer - Kumbhar, Deepak; Kumbhar, Sarita; Dhodamani, Anant; Delekar, Sagar; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Inorganic and Nano-Metal Chemistry, 2021)
In the present investigation, a simple sol-gel approach has been employed for the synthesis of hexagonal wurtzite ZnO nanoparticles (NPs). X-ray diffraction (XRD) rietveld study and Raman analysis reveal the mislaid of the mixed phases of ZnO NPs after doping. The scanning electron micrographs and transmission electron microscopy confirm the formation of hexagonal disk-shaped NPs. FTIR, PL, EDX, XPS validate optical and stoichiometric concentration of Co in ZnO lattice. UV-visible DRS study shows absorption edge with humps to the red region of the spectrum with increasing the absorption strength and shortening of band gap as the content of Co (II) increases. Finally, the prepared samples were coated on the surface of cleaned FTO substrate through a simple doctor blade technique and sensitized with prepared dye. The ZnO photoanode shows 0.036% of efficiency (eta%) while the photoanodes of Co doped samples expose the enhanced efficiencies of 0.29%, 0.389%, 0.089%.
Keywords: Co doped ZnO; mixed dyes as sensitizer; Photoelectrochemical cell; sol-gel

Exceptional capacitance enhancement of a non-conducting COF through potential-driven chemical modulation by redox electrolyte - Kushwaha, Rinku; Haldar, Sattwick; Shekhar, Pragalbh; Krishnan, Akshara; Saha, Jayeeta; Hui, Pramiti; Vinod, Chathakudath Prabhakaran; Subramaniam, Chandramouli; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2021)
Capacitors are the most practical high-storage and rapid charge-release devices. The number of ions stored per unit area and their interaction strength with the electrode dictates capacitor-performance. Microporous materials provide a high storage surface and optimal interactions. Adsorbing electron-rich and easily polarizable molecules into microporous electrodes is expected to boost Faradaic pseudo-activity. If such electrode-electrolyte interactions can be made as a potential-driven reversible process, the resulting capacitors would be adaptable and device-friendly. A composite covalent organic framework (COF)-carbon electrode with redox-active KI is combined in an H2SO4 electrolyte for the first time. This composite electrode benefits from the redox-functionality of COF and electronic conductivity of carbon, leading to superior capacitative activity. Operando spectro-electrochemical measurements reveal the existence of multiple polyiodide species, although the I-3(-) is the predominantly electroactive species adsorbing on the microporous triazine-phenol COF electrode. A systematic fabrication of the flexible solid-state devices using the COF-redox-electrolyte reveals a high areal capacitance of 270 +/- 11 mF cm(-2) and gravimetric capacitance of 57 +/- 8 F g(-1). The inclusion of KI in H2SO4 (electrolyte) yields an approximately eight-fold enhancement in solid-state gravimetric specific capacitance. The imine-COF retains 89% of its capacity even after 10 000 cycles.
Keywords: covalent organic frameworks; polyiodide; redox electrolytes; solid‐ state capacitors; Supercapacitors

Fabrication of high energy density supercapacitor device based on hollow iridium oxide nanofibers by single nozzle electrospinning - Beknalkar, S. A.; Teli, A. M.; Harale, N. S.; Patil, D. S.; Pawar, S. A.; Shin, J. C.; Patil, P. S. (Applied Surface Science, 2021)
Herein, we have synthesized iridium oxide (IrO2) nanofibers using electrospinning technique and optimization of annealing temperature is undertaken in order to obtain high quality IrO2 nanofibers. The annealing temperature is varied as 200, 300, 400 and 500 degrees C. The synthesized material has hollow nanofibrous morphology with average diameter similar to 45 nm. The formed nanofibers are amorphous in nature. The X-ray Photoelectron Spectroscopy (XPS) result revealed that synthesized iridium is in +4 oxidation state. The electrochemical performance of IrO2 electrodes showed 2 V potential window in three electrode system using 1 M Sodium sulphate (Na2SO4) aqueous electrolyte. The maximum specific capacitance is obtained for sample annealed at 400 degrees C (705F/g at 1 mA/cm(2)) which is due to the well-developed morphology with complete removal of polymer content. Moreover, a novel solid state symmetric IrO2/IrO2 supercapacitor with a high operating voltage of 2 V is built. The symmetric supercapacitor exhibits an energy density of 59 Wh/kg at a power density of 714 W/kg and an excellent cycling stability. These results demonstrate the potentialities of using IrO2 for symmetric supercapacitor for building high energy and power density devices.
Keywords: Aqueous electrolyte; Hollow iridium oxide nanofibers; Symmetric supercapacitor

Gold-catalysed nitroalkyne cycloisomerization - synthetic utility - Dhote, Pawan S.; Halnor, Swapnil V.; Ramana, Chepuri V. (Chemical Record, 2021)
The gold-catalysed intramolecular redox cyclization of o-alkynylnitrobenzens documented by Professors Naoki Asao and Yoshinori Yamamoto is an important discovery that has opened two complementary research domains. Advancing this cyclization with other metals as well as developing new methods around the products that result from this reaction is one aspect that has seen growing interest. On the other hand, the idea of generating alpha-oxo gold carbenes via oxygen transfer to alkynes has established another important aspect in gold-catalysis. In this account, we will be dealing with the first aspect, which revolves around the internal redox cyclization of nitroalkynes (trivially called as nitroalkyne cycloisomerization), focusing mainly on the gold-complexes and the synthetic methods developed around it from our group and from other groups, and also providing the details of similar transformations documented with other metals so that the complementary reactivity/diversity of these transformations could be appreciated.
Keywords: alpha-Oxo Gold Carbene; Anthranil; Gold-catalysis; Internal Redox Cyclization; Isatogen

Green antibacterial molecules: sophorolipids with varying fatty acid chain - Hirlekar, Swarali; Abhyankar, Isha; Kane, Kartiki; Trimukhe, Kalpana; Prabhune, Asmita; Nisal, Anuya (Trends in Biomaterials and Artificial Organs, 2021)
Antibiotic resistance is a rising problem of over the last decade making it difficult to treat infections caused by various pathogenic bacteria. To tackle this problem, newer antimicrobial strategies are being explored. Sophorolipids (SLs) are a class of biomolecules produced by a non-pathogenic yeast Starmarella bombicola (S. bombicold) with surfactant as well as potent broad spectrum antibacterial activity. In this work, we have successfully synthesized sophorolipids using different fatty acids with increasing chain length of hydrophobic tail; Lauric acid (C12)-LASL, Myristic acid (C14)-MASL, Palmitic acid (C16)-PASL and Stearic acid (C18)-SASL. We have used various techniques like FTIR, HRMS to characterize the synthesized SL. Further, we have measured properties like the critical micellar concentration for these biosurfactants and the SL's showed CMC less than or equal to 100 mg/L indicating excellent surface-active property. We have studied the antibacterial activity against gram-negative and gram-positive bacteria. Interestingly, the antibacterial activity was found to be more potent as the chain length of the fatty acid in the SL decreased. This trend was found to be reverse for toxicity towards mammalian cells. The shorter chain fatty acid SL's were found to be less cytotoxic. These results indicate that the sophorolipid candidates with shorter chain lengths would be beneficial for various biomedical applications such as tissue engineering, regenerative medicine and wound healing. Keywords: sophorolipid, biosurfactant, short chain fatty acid, antibacterial
Keywords: Antibacterial agents; Cells (Biology); Infection; Microbial drug resistance; Saturated fatty acids; Surface active agents

Green synthesis of methoxy-poly(ethylene glycol)-block-poly(l-lactide-co-glycolide) copolymer using zinc proline as a biocompatible initiator for irinotecan delivery to colon cancer in vivo - Giram, Prabhanjan S.; Wang, Julie Tzu-Wen; Walters, Adam A.; Rade, Priyanka P.; Akhtar, Muhammad; Han, Shunping; Faruqu, Farid N.; Abdel-Bar, Hend M.; Garnaik, Baijayantimala; Al-Jamal, Khuloud T. (Biomaterials Science, 2021)
Poly(lactic-co-glycolic acid) (PLGA) is the most commonly described biocompatible copolymer used in biomedical applications. In this work, a green synthetic approach based on the biocompatible zinc proline complex, as an initiator for PLGA synthesis, is reported for the first time for the synthesis of methoxy-poly(ethylene glycol)-block-poly(l-lactic-co-glycolic acid) (mPEG-PLGA). mPEG-PLGA with controlled molecular weight and narrow polydispersity was synthesised. Its potential for delivery of irinotecan (Ir), a poorly water-soluble chemotherapeutic drug used for the treatment of colon and pancreatic cancer, was studied. Nanoparticles of controlled size (140-160 nm), surface charge (similar to-10 mV), release properties and cytotoxicity against CT-26 (colon) and BxPC-3 (pancreatic) cancer cells, were prepared. Tumor accumulation was confirmed by optical imaging of fluorescently labelled nanoparticles. Unlike Tween (R) 80 coated NP-Ir, the Pluronic (R) F-127 coated NP-Ir exhibits significant tumor growth delay compared to untreated and blank formulation treated groups in the CT-26 subcutaneous tumor model, after 4 treatments of 30 mg irinotecan per kg dose. Overall, this proof-of-concept study demonstrates that the newly synthesized copolymer, via a green route, is proven to be nontoxic, requires fewer purification steps and has potential applications in drug delivery.

Hierarchical ITO nanofibers coated Mn3O(4) nanoplates core-shell nanocomposites for high performance all-solid-state symmetric supercapacitor device - Beknalkar, S. A.; Teli, A. M.; Harale, N. S.; Pawar, K. K.; Patil, D. S.; Shin, J. C.; Patil, P. S. (Ceramics International, 2021)
We have made a first attempt to build a novel Tin doped indium oxide@Manganese oxide (ITO@Mn3O4) nanocomposite electrode to overcome the detriments of Mn3O4 such as low conductivity and small potential window. Herein, we have synthesized the ITO@Mn3O4 nanocomposite by growing Mn3O4 nanoplates over ITO nanofibers synthesized by electrospinning technique. Benefitted from, the high conductivity and negative operating potential window of ITO exceptionally increased in the electrochemical performance of ITO@Mn3O4 was observed. The specific capacitance of optimized ITO@Mn3O4 nanocomposite reached up to 823 F/g at 1 mA/ cm2 in a wide potential window of 2 V using Na2SO4 electrolyte. To determine the practical feasibility an ITO@Mn3O4//ITO@Mn3O4 all-solid-state symmetric device was developed, which operated very well in a 2.2 V voltage window. It was found to deliver a maximum energy density of 88 Wh/kg and a power density of 550 W/ kg. This novel composite inferred the significance of using simple design to build a high-performance device.
Keywords: electrospinning; ITO@Mn3O4 nanocomposite; PVA-LiClO4; SILAR; Solid-state symmetric device

Hydrogenolysis of benzofuran using aqueous ethanol solution over graphite-supported platinum catalyst - Hiraishi, Yushi; Minakawa, Naohiro; Taniguchi, Kenkichi; Nagasawa, Yoshiyuki; Nanao, Hidetaka; Rode, V, Chandrashekhar; Sato, Osamu; Yamaguchi, Aritomo; Shirai, Masayuki (Journal of the Indian Chemical Society, 2021)
Graphite-supported platinum catalysts (Pt/G) were highly active for the hydrogenolysis of benzofuran to o-ethylphenol in aqueous ethanol solution at 523 K without using any external hydrogen gas. The hydrogenolysis activities and selectivity to o-ethylphenol in ethanol solution over Pt/G were higher than those with a conventional method using externally supplied hydrogen gas. Both water and ethanol were indispensable for the hydrogenolysis in aqueous ethanol solution at 523 K.
Keywords: Biomass conversion; Graphite support; Hydrogenolysis; platinum catalysts

Improving the optical and thermoelectric properties of Cs2InAgCl6 with heavy substitutional doping: a DFT insight - Bhamu, K. C.; Haque, Enamul; Praveen, C. S.; Kumar, Nandha; Yumnam, G.; Hossain, Md. Anwar; Sharma, Gautam (RSC Advances, 2021)
The next-generation indium-based lead-free halide material Cs2InAgCl6 is promising for photovoltaic applications due to its good air stability and non-toxic behavior. However, its wide bandgap (>3 eV) is not suitable for the solar spectrum and hence reduces its photoelectronic efficiency for device applications. Here we report a significant bandgap reduction from 2.85 eV to 0.65 eV via substitutional doping and its effects on the optoelectronic and opto-thermoelectric properties from a first-principles study. The results predict that Sn/Pb and Ga and Cu co-doping will enhance the density of states significantly near the valence band maximum (VBM) and thus reduce the bandgap via shifting the VBM upward, while alkali metals (K/Rb) slightly increase the bandgap. A strong absorption peak near the Shockley-Queisser limit is observed in the co-doped case, while in the Sn/Pb-doped case, we notice a peak in the middle of the visible region of the solar spectrum. The nature of the bandgap is indirect with Cu-Ga/Pb/Sn doping, and a significant reduction in the bandgap, from 2.85 eV to 0.65 eV, is observed in the case of Ga-Cu co-doping. We observe a significant increase in the power factor (PF) (2.03 mW m(-1) K-2) for the n-type carrier after Pb-doping, which is similar to 3.5 times higher than in the pristine case (0.6 mW m (-1) K-2) at 500 K.

In vitro antitubercular screening and in silico study of germacradienolide from blainvillea latifolia - Honmore, Varsha; Kalyankar, Vidya; Natu, Arun; Khedkar, Vijay; Sarkar, Dhiman; Rojatkar, Supada (Asian Journal of Chemistry, 2021)
Bioassay-guided isolation from acetone extract of Blainvillea latifolia yielded one compound. The acetone extract, fractions and the compound 1 were investigated for antitubercular activity against Mycobacterium tuberculosis H37Ra. Compound 1 showed the activity with IC50 and MIC values at 8.9 and >100 μg/mL. However, the acetone extract of Blainvillea latifolia was inactive against two Gram negative (E. coli, P. flurescence) and two Gram-positive (S. aureus, B. subtilis) bacterial strains. Hence, it was concluded that the extract and the compound 1 are specifically active against MTB and not against bacterial strains. Molecular docking study was performed against crucial mycobacterial target MtInhA to gain an insight into the binding mode and the thermodynamic interactions governing the binding affinity of this molecule.

Insights from a pan India Sero-epidemiological survey (Phenome-India Cohort) for SARS-CoV2 - Naushin, Salwa; Sardana, Viren; Ujjainiya, Rajat; Bhatheja, Nitin; Kutum, Rintu; Bhaskar, Akash Kumar; Pradhan, Shalini; Prakash, Satyartha; Khan, Raju; Rawat, Birendra Singh; Tallapaka, Karthik Bharadwaj; Anumalla, Mahesh; et al. (eLife, 2021)
To understand the spread of SARS-CoV2, in August and September 2020, the Council of Scientific and Industrial Research (India) conducted a serosurvey across its constituent laboratories and centers across India. Of 10,427 volunteers, 1058 (10.14%) tested positive for SARS-CoV2 anti-nucleocapsid (anti-NC) antibodies, 95% of which had surrogate neutralization activity. Three-fourth of these recalled no symptoms. Repeat serology tests at 3 (n = 607) and 6 (n = 175) months showed stable anti-NC antibodies but declining neutralization activity. Local seropositivity was higher in densely populated cities and was inversely correlated with a 30-day change in regional test positivity rates (TPRs). Regional seropositivity above 10% was associated with declining TPR. Personal factors associated with higher odds of seropositivity were high-exposure work (odds ratio, 95% confidence interval, p value: 2.23, 1.92-2.59, <0.0001), use of public transport (1.79, 1.43-2.24, <0.0001), not smoking (1.52, 1.16-1.99, 0.0257), non-vegetarian diet (1.67, 1.41-1.99, <0.0001), and B blood group (1.36, 1.15-1.61, 0.001).

MoSx surface-modified, hybrid core-shell structured LiFePO4 cathode for superior Li-ion battery applications - Hu, Lung-Hao; Kumar, Pushpendra (Journal of Alloys and Compounds, 2021)
A hybrid core-shell cathode, composed of MoSx shell and carbon-coated lithium iron phosphate core (MoSx@cLiFePO(4) or MoSx@c-LFP) is obtained by the post-annealing of a thermally decomposable ammonium thiomolybdate and commercial carbon-coated LiFePO4 (c-LFP) powder. The specific capacity of the commercially available amorphous carbon-coated LFP (c-LFP) is typically around 120-160 mAhg(-1), which is usually lower than the theoretical values similar to 170 mAhg(-1) due to the limited Li+ phase-boundary diffusion and low electrical conductivity. In the present investigation, we report that the specific capacity of surfacemodified (similar to 1.2 wt% of layered MoSx) c-LFP (MoSx@c-LFP) material can reach as high as similar to 228 mAhg(-1) delivering high gravimetric energy density similar to 750-770 Whkg(-1). The excess capacity can be attributed to the partial Li-ions intercalated/de-intercalated through the MoSx layers within a specific potential range (2.0-3.8 V). MoSx coating helps increase the c-LFP surface's stability by forming strong covalent bonding and is believed to enhance the electronic conduction by reducing the interparticle contact. During charge and discharge the hysteresis is substantially reduced by MoSx coating. The approach may open up a universal route to increase the cathode capacity, potentially attractive for further Li-ion battery research and industrial applications. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Ammonium thiomolybdate; Coulombic efficiency; Hybrid core-shell cathode; hysteresis; MoSx

PNA-mediated efflux inhibition as a therapeutic strategy towards overcoming drug resistance in Mycobacterium smegmatis - Ghosh, Saptarshi; Cotta, Karishma Berta; Hande, Aniket A.; Fernandes, Moneesha; Mehra, Sarika (Microbial Pathogenesis, 2021)
The emergence of antibiotic-resistant strains of Mycobacterium tuberculosis and the decelerating development of new and effective antibiotics has impaired the treatment of tuberculosis (TB). Efflux pump inhibitors (EPIs) have the potential to improve the efficacy of existing anti-TB drugs although with toxicity limitations. Peptide nucleic acids (PNAs), oligonucleotide mimics, by virtue of their high nucleic acid binding specificity have the capability to overcome this drawback. We, therefore, investigated the efflux pump inhibitory properties of a PNA designed against an efflux pump of Mycobacterium smegmatis. LfrA, an efflux pump found in M. smegmatis, is majorly involved in conferring innate drug resistance to this strain and, therefore, was selected as a target for gene silencing via PNA. qRT-PCR and EtBr assays confirmed the EPI activity of the anti-lfrA PNA. On testing the effect of the anti-lfrA PNA on the bactericidal activity of a fluoroquinolone, norfloxacin, we observed that 5 mu M of anti-lfrA PNA in combination with norfloxacin led to an enhanced killing of up to 2.5 log-fold against wild-type and a lab-generated multidrug resistant strain, exemplifying its potential in countering resistance. Improved efficacy was also observed against intra-macrophage mycobacteria, where the drug-PNA combination enhanced bacterial clearance by 1.3 log-fold. Further, no toxicity was observed with PNA concentrations up to 4 times higher than the efficacious anti-lfrA PNA concentration. Thus, PNA, as an adjuvant, presents a novel and viable approach to rejuvenate anti-TB therapeutics.
Keywords: Adjuvant; Antibiotic resistance; Antisense; Efflux pump; Gene silencing; Mycobacteria; Peptide nucleic acid (PNA)

Reactions of 2,3-dibromonaphthalene-1,4-dione and pyridyl amines: X-ray structures, DFT investigations, and selective detection of the Hg2+ and Ni2+ ions - Aggrwal, Gunjan; Salunke-Gawali, Sunita; Gejji, Shridhar P.; Nikalje, Milind; Chakravarty, Debamitra; Verma, Prakash L.; Gosavi-Mirkute, Prajkta; Harihar, Shital; Jadhav , Mahesh; Puranik, Vedavati G. (Engineered Science, 2021)
<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">In this work, the products formed by the reaction between 2,3-dibromonaphthalene-1,4-dione with (pyridine-2-yl)methanamine and (pyridine-4-yl)methanamine are discussed in detial. The products 2-amino-3-bromonaphthalene-1,4-dione (<span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">A<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">) and 2-aminonaphthalene-1,4-dione (<span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">B(1)<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">) obtained are characterized through 1H and 13C-NMR, FTIR, mass spectrometry, single-crystal X-ray diffraction experiments, which are in conjunction with wB97X based density functional theory. <span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">compound <span style="font-weight: 700; color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; background-color: rgb(217, 217, 217);">A<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);"> can effectively and selectively detect Hg2+ and Ni2+ ions, and proposes a potential mechanism of action<span style="color: rgb(51, 51, 51); font-family: "Open Sans", sans-serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(217, 217, 217);">.

Role of charge compensation mechanism and defect dipoles on properties of Mn doped BCT ceramics - Redhu, Preeti; Sharma, Preeti; Hooda, Ashima; Singh, Anupinder; Sharma, Geeta; Punia, Rajesh (Ceramics International, 2021)
Single-phase Mn doped Barium Calcium Titanate (BCT) (Ba0.80Ca0.20Ti1-xMnxO3; x = 0.000, 0.005, 0.010, 0.015 and 0.020) lead free ceramics have been prepared by conventional solid-state reaction method. XRD studies and Rietveld refinement confirmed the existence of tetragonal phase (P4mm) for all prepared ceramic compositions. The average grain size increased up to x = 0.005 and thereafter it decreased with increase in Mn content in BCT compositions. Analysis of temperature-dependent dielectric study revealed phase transformation from tetragonal to cubic phase and defect dipole induced anomaly in paraelectric region of temperature-dependent dielectric constant ( epsilon'-T) curve. Degree of diffusiveness increased with Mn doping in BCT ceramics as confirmed by evaluating diffused phase transition (DPT) parameters (gamma and delta(c)) by Power Law fitting and width of diffused phase transition (D') obtained from derivative of epsilon'-T curve. Ferroelectric (P-E loops) study revealed that ceramic composition with x = 0.015 Mn content showed the highest remnant polarization (P-r) and maximum polarization (P-max) of 14.10 mu C/cm(2) and 24.20 mu C/cm(2) respectively. Enhancement in energy storage properties with applied electric fields have been observed at room temperature. Maximum energy storage density W-rec similar to 190.89 mJ/cm(3) with an efficiency of 48.63% has been obtained for x = 0.015. A large piezoelectric charge coefficient (d(33)) of 460 pC/N has been obtained for x = 0.020. The room temperature magnetic measurements shows feeble ferromagnetism for Mn doped samples. These studies suggest the application of these ceramics for multilayer ceramic capacitors, energy storage, and high power applications..
Keywords: Defect dipoles; Dielectric anomaly; Energy storage; Ferroelectric materials; ferromagnetic materials; Lead-free ceramics; Mn doped BCT; piezoelectric; Williamson-Hall (W-H)

Supercapacitive performance of SILAR grown Mn3O4 nanoclusters: effect of cationic precursor concentration - Beknalkar, S. A.; Teli, A. M.; Harale, N. S.; Patil, D. S.; Sutar, J. R.; Shin, J. C.; Patil, P. S. (Chinese Journal of Physics, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Herein, we have investigated the effect of cationic precursor (manganese chloride tetrahydrate) concentration on the electrochemical performance of successive ionic layer adsorption and reaction (SILAR)-deposited Mn<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> thin films. The concentration of the cationic precursor was varied from 0.05 to 0.15 M, and its effect on physicochemical and electrochemical properties was studied. X-ray diffraction and X-ray photoelectron spectroscopy analyses confirmed that Mn<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> has a tetragonal structure with Mn<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2+<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and Mn<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3+<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> oxidation states. SEM micrographs revealed that nanoclusters of Mn<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> with an average size of ~200 nm were formed. Moreover, transmission electron microscopy analysis revealed that these nanoclusters were formed from tiny square nanoplates with a size of ~40 nm. Electrochemical studies of the synthesized Mn<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> thin films were recorded in a three-electrode system, which suggests that 0.1 M cationic precursor concentration has a good electrochemical signature with a specific capacitance of 470 F/g at 1 mA/cm<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> current density in 1 M Na<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">SO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> aqueous electrolyte. The cyclic stability offered was appreciable, with capacitive retention of 75% up to 10,000 CV cycles scanned at 100 mV/s. The charge storage kinetics of the SILAR-grown Mn<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> thin film were investigated. With systematic study we concluded that, the molarity of the cationic precursor plays a vital role in the porosity and microstructure which drastically affects the electrochemical performance.

Adsorption of toxic Pb(II) on activated carbon derived from agriculture waste (Mahogany fruit shell): isotherm, kinetic and thermodynamic study - Patil, Suryakant A.; Suryawanshi, Umesh P.; Harale, Namdev S.; Patil, Sandip K.; Vadiyar, Madgonda M.; Luwang, Meitram N.; Anuse, Mansing A.; Kim, Jin H.; Kolekar, Sanjay S. (International Journal of Environmental Analytical Chemistry, 2022)
An adsorbent, mahogany fruit shell activated carbon(MFSAC), was derived from environmental friendly raw material, i.e. agriculture waste and explored for bench scale adsorption of toxic Pb(II). A facile MFSAC material was synthesised using a chemical activation method using concentrated sulphuric acid as an impregnating (activating) reagent. So derived adsorbent material was characterised by FTIR, XRD, BET, SEM, EDAX, TGA and XPS techniques to know the properties and plausible adsorption mechanism. Bench scale adsorption of toxic Pb(II) and maximum adsorption capacity of MFSAC were exhibited through batch adsorption experiments. The effect of physico-chemical parameters such as pH (1-7), MFSAC amount (0.5-5.0 g L-1), Pb(II) concentration (200-1000 mgL(-1)), contact period (60-600 min) and orbital shaking speed (60-200 rpm) was studied for maximum removal of Pb(II) upto 99.70 +/- 0.17%. The experimental data follow the Langmuir adsorption isotherm with a maximum monolayer adsorption capacity 322.28 mg g(-1)and pseudo-second-order kinetic uptake rate. The thermodynamic and temperature study revealed that the adsorption process was spontaneous and endothermic in nature (Delta H-o = 43.37 kJ mole(-1), Delta S-o = 158.02 J mol(-1)K(-1)). Most importantly, the MFSAC adsorbent was successfully regenerated and reused with conspicuous performance up to five consecutive cycles. The bench-scale adsorption with simple synthesis route, good stability and remarkable regeneration capability makes the MFSAC as an encouraging adsorbent for wastewater treatment.
Keywords: activated carbon; Adsorption; mahogany fruit shell; Pb(II); sulphuric acid

Blue fluorescence of cyano-tryptophan predicts local electrostatics and hydrogen bonding in biomolecules - Haldar, Tapas; Chatterjee, Srijan; Alam, Md Nirshad; Maity, Pradip; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Cyano-tryptophan is an unnatural fluorescent amino acid that emits in the visible region. Along with the structural similarity with tryptophan, the unique photophysical properties of this fluorophore make it an ideal probe for biophysical research. Herein, combining fluorescence spectroscopy, infrared spectroscopy, and molecular dynamics simulations, we show that the cyano-tryptophan's emission energy quantifies the underlying bond-specific noncovalent interactions in terms of the electric field. We further report the use of fluorophore's emission energy to predict its hydrogen bond characteristics. We demonstrate that combining experiments with molecular dynamics simulations can provide the hydrogen bonding status of the nitrile moiety. In addition, we report a method to differentiate between aqueous and nonaqueous hydrogen-bonding partners. Using a phenomenological approach, we demonstrate that the presence of the cyano-indole moiety is responsible for the distinct correlations between the fluorophore's emission and the electrostatic forces on the nitrile bond. As indole is a privileged scaffold for both native amino acids and nucleobases, cyano-indoles will have many multifaceted applications.

Boosting electrochemical CO2 reduction to methane via tuning oxygen vacancy concentration and surface termination on a copper/ceria catalyst - Patra, Kshirodra Kumar; Liu, Zhu; Lee, Hojeong; Hong, Seungwon; Song, Hakhyeon; Abbas, Hafiz Ghulam; Kwon, Youngkook; Ringe, Stefan; Oh, Jihun (ACS Catalysis, 2022)
Metal oxides are a promising material for designing highly active and selective catalysts for the electrochemical reduction of carbon dioxide (CO2RR). Here, we designed a Cu/ceria catalyst with high selectivity of methane production at single-atomic Cu active sites. Using this, we report favorable design concepts that push the product selectivity of methane formation by combining detailed structural analysis, density functional theory (DFT), in situ Raman spectroscopy, and electrochemical measurements. We demonstrate that a higher concentration of oxygen vacancies on the catalyst surface, resulting from more available Cu+ sites, enables high selectivity for methane formation during CO2RR and can be controlled by the calcination temperature. The DFT calculation and in situ Raman studies indicate that pH controls the surface termination; a more alkaline pH generates hydroxylated surface motifs with more active sites for the hydrogen evolution reaction. These findings provide insights into designing an efficient metal oxide electrocatalyst by controlling the atomic structure via the reaction environment and synthesis conditions.
Keywords: copper-ceria; electrochemical CO2 reduction; electrolyte pH; gas diffusion electrode; methane production; Oxygen vacancy

Comparative analysis and structural modeling of elaeis oleifera FAD2, a fatty acid desaturase involved in unsaturated fatty acid composition of american oil palm - Ben Ayed, Rayda; Chirmade, Tejas; Hanana, Mohsen; Khamassi, Khalil; Ercisli, Sezai; Choudhary, Ravish; Kadoo, Narendra; Karunakaran, Rohini (Biology-Basel, 2022)
Simple Summary Palm oil has become the world's most important vegetable oil in terms of production quantity, and its overall demand is exponentially growing with the global population. The fatty acid composition and particularly the oleic/linoleic acid ratio are major factors influencing palm oil quality. In this study, we focused on FAD2, a fatty acid desaturase enzyme involved in the desaturation and conversion of oleic acid to linoleic acid in Elaeis oleifera, identified through in silico annotation analysis. Our phylogenetic and comparative studies revealed two SNP markers, SNP278 and SNP851, significantly correlated with the oleic/linoleic acid contents. Our study provides fundamental insights into the mechanism of fatty acids synthesis in oil palm and could support the application of molecular biology techniques to enhance the enzymatic activity and substrate affinity of EoFAD2. American oil palm (Elaeis oleifera) is an important source of dietary oil that could fulfill the increasing worldwide demand for cooking oil. Therefore, improving its production is crucial and could be realized through breeding and genetic engineering approaches aiming to obtain high-yielding varieties with improved oil content and quality. The fatty acid composition and particularly the oleic/linoleic acid ratio are major factors influencing oil quality. Our work focused on a fatty acid desaturase (FAD) enzyme involved in the desaturation and conversion of oleic acid to linoleic acid. Following the in silico identification and annotation of Elaeis oleifera FAD2, its molecular and structural features characterization was performed to better understand the mechanistic bases of its enzymatic activity. EoFAD2 is 1173 nucleotides long and encodes a protein of 390 amino acids that shares similarities with other FADs. Interestingly, the phylogenetic study showed three distinguished groups where EoFAD2 clustered among monocotyledonous taxa. EoFAD2 is a membrane-bound protein with five transmembrane domains presumably located in the endoplasmic reticulum. The homodimer organization model of EoFAD2 enzyme and substrates and respective substrate-binding residues were predicted and described. Moreover, the comparison between 24 FAD2 sequences from different species generated two interesting single-nucleotide polymorphisms (SNPs) associated with the oleic/linoleic acid contents.
Keywords: FAD2; Fatty acids; in silico annotation; linoleic acid ratio; oil palm; oleic; SNP; structural modeling

Comparative study of polycaprolactone electrospun fibers and casting films enriched with carbon and nitrogen sources and their potential use in water bioremediation - Alejandra Pompa-Monroy, Daniella; Leticia Iglesias, Ana; Gulam Dastager, Syed; Namdeo Thorat, Meghana; Olivas-Sarabia, Amelia; Valdez-Castro, Ricardo; Angelica Hurtado-Ayala, Lilia; Manuel Cornejo-Bravo, Jose; Lizeth Perez-Gonzalez, Graciela; Jesus Villarreal-Gomez, Luis (Membranes, 2022)
Augmenting bacterial growth is of great interest to the biotechnological industry. Hence, the effect of poly (caprolactone) fibrous scaffolds to promote the growth of different bacterial strains of biological and industrial interest was evaluated. Furthermore, different types of carbon (glucose, fructose, lactose and galactose) and nitrogen sources (yeast extract, glycine, peptone and urea) were added to the scaffold to determinate their influence in bacterial growth. Bacterial growth was observed by scanning electron microscopy; thermal characteristics were also evaluated; bacterial cell growth was measured by ultraviolet-visible spectrophotometry at 600-nm. Fibers produced have an average diameter between 313 to 766 nm, with 44% superficial porosity of the scaffolds, a glass transition around similar to 64 degrees C and a critical temperature of similar to 338 degrees C. The fibrous scaffold increased the cell growth of Escherichia coli by 23% at 72 h, while Pseudomonas aeruginosa and Staphylococcus aureus increased by 36% and 95% respectively at 48 h, when compared to the normal growth of their respective bacterial cultures. However, no significant difference in bacterial growth between the scaffolds and the casted films could be observed. Cell growth depended on a combination of several factors: type of bacteria, carbon or nitrogen sources, casted films or 3D scaffolds. Microscopy showed traces of a biofilm formation around 3 h in culture of P. aeruginosa. Water bioremediation studies showed that P. aeruginosa on poly (caprolactone)/Glucose fibers was effective in removing 87% of chromium in 8 h.
Keywords: bacterial growth; carbon source; electrospinning; nitrogen source; poly (caprolactone)

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis

Direct oxidation of bromo-derived Fischer-Borsche oxo-ring using molecular iodine with combined experimental and computational study - Humne, Vivek T.; Ghom, Monica H.; Naykode, Mahavir S.; Dangat, Yuvraj; Vanka, Kumar; Lokhande, Pradeep (Organic & Biomolecular Chemistry, 2022)
A direct oxidation of the bromo-derived Fischer-Borsche oxo-ring leading to carbazolequinone has been developed by using molecular iodine. This unprecedented transformation has been used for the modular synthesis of the anti-cardiotonic agent murrayaquinone. Furthermore, the present method has been generalized to a broad range of functional groups, with good to excellent yield.

Efficient synthesis of 5-(hydroxymethyl)furfural esters from polymeric carbohydrates using 5-(chloromethyl)furfural as a reactive intermediate - Bhat, Navya Subray; Hegde, Shobhita L.; Dutta, Saikat; Sudarsanam, Putla (ACS Sustainable Chemistry & Engineering, 2022)
This work reports an efficient, gram-scale synthesis of 5-(hydroxymethyl)furfural (HMF) esters using biomass-derived 5-(chloromethyl)furfural (CMF) as a reactive intermediate. The HMF-esters have potential applications as chemicalintermediates, fuel additives, and bioactive compounds. Initially, CMF was prepared in good yields directly from polymericcarbohydrates (starch, inulin, and cellulose) and cellulosic materials (cotton andfilter paper) using a biphasic batch reaction system,consisting of aqueous hydrochloric acid and 1,2-dichloroethane. The use of ZnCl2as an additive allowed the reaction to proceedunder milder conditions while significantly improving the isolated yield of CMF. The effects of reaction temperature, reaction time,extracting solvent, and ZnCl2loading on CMF yield were investigated. Microcrystalline cellulose was converted into CMF with a72% isolated yield under optimized reaction conditions (80 degrees C, 2 h). After that, CMF was transformed into various novel esters ofHMF in excellent isolated yields (>85%) by reacting with a slight excess amount of the triethylammonium salt of various alkyl/arylcarboxylic acids under solvent-free conditions
Keywords: catalysis; cellulose; furanics; HMF-esters; renewable synthesis

First-principles investigation of the electrocatalytic reduction of CO2 on zirconium-based single-, double-, and triple-atom catalysts anchored on a graphitic carbon nitride monolayer - Hassan, Afshana; Anis, Insha; Shafi, Sadaf; Assad, Assif; Rasool, Anjumun; Khanam, Romana; Bhat, Gulzar Ahmad; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (ACS Applied Nano Materials, 2022)
Conversion of carbon dioxide (CO2) with the help of an appropriate electrocatalyst with high stability, low onset potential, and exceptional selectivity is still one of the great tasks in the electrocatalytic reduction of CO2 to valuable chemicals. Herein, by means of systematic first-principles simulations, we investigate the CO2 reduction reaction (CO2RR) activity of zirconium-based single-, double-, and triple-atom (Zrn@C2N; n = 1-3) catalysts anchored on a graphitic carbon-nitride monolayer. In tune with the Sabatier principle, our results reveal that a moderate CO2 binding is vital for a low onset potential for the CO2RR. Consequently, based on rigorous free energy calculations, the Zr-based single-atom catalyst (SAC) is found to be most effective to convert CO2 to valuable products such as HCOOH and CH3OH. It is worth noting that CO2 reduction to HCOOH is spontaneous via the *HCOO intermediate on Zr1@C2N and involves a low onset potential of -0.23 V with respect to the reversible hydrogen electrode from the *COOH intermediate. Among all the catalysts evaluated computationally, the Zr SAC further reveals the lowest onset potential of -0.89 V for CH3OH formation. The results show that the Zr-based catalysts especially Zr1@C2N are found to effectively suppress the competitive hydrogen evolution reaction and promote the CO2RR. Moreover, all three catalysts exhibit high kinetic and thermal stability with negligible distortion due to which their structures can be retained very well up to 600 K. Thus, the current work may provide effective catalyst-design strategies for enhancing the electrocatalytic CO2RR performance of Zr-based materials.
Keywords: C1 and C2 products; CO2 reduction; first-principles simulations; hydrogen evolution reaction; onset potential; single-atom catalysts (SACs); Zrn@C2N catalysts

How far is ``Bulk Water'' from interfaces? depends on the nature of the surface and what we measure - Hande, Vrushali R.; Chakrabarty, Suman (Journal of Physical Chemistry B, 2022)
Using systematic molecular dynamics (MD) simulations, we revisit the question: At what distance from an interface do the properties of ``bulk water'' get recovered? We have considered three different kinds of interfaces: nonpolar (hydrophobic; isooctane-water interface), charged (negative; AOT bilayer), and polar (zwitterionic; POPC bilayer). In order to interrogate the extent of perturbation of the interfacial water molecules as a function of the distance from the interface, we utilize a diverse range of structural and dynamical parameters. To capture the structural perturbations, we look into local density (translational order), local tetrahedral order parameter, and dipolar orientation of the water molecules. We also explore the anisotropic diffusion of the water molecules in the direction perpendicular to the interface as well as the planar diffusion parallel to the interface in a distance dependent manner. In addition, the orientational time correlation functions have been computed to understand the extent of slowdown in the rotational dynamics. As expected, the electrostatic field emanating from the charged AOT interface seems to have the highest long-range effect on the orientational order and dynamics of the water molecules, whereas specific interactions like hydrogen bonding and electrostatic interaction lead to significant trapping and kinetic slowdown for both AOT and POPC (zwitterionic) very close to the interface. Our analysis highlights that not only the length-scale of perturbation depends on the nature of the interfaces and specific interactions but also the type of water property that we measure/calculate. Different water properties seem to have widely different length-scale of perturbation. Orientational order parameters seem to be perturbed to a much longer length-scale as compared to translational order parameters. The global orientational order of water can be perturbed even up to similar to 4-5 nm near the negatively charged AOT surface in the absence of any extra electrolyte. This observation has significant implication toward the interpretation of experimental measurements as well since different spectroscopic techniques would probe different parameters or water properties with possible mutual disagreement and inconsistency between different types of measurements. Thus, our study provides a broader and unifying perspective toward the aspect of ``context dependent'' structural and dynamical perturbation of ``interfacial water''.

Incorporating conducting polypyrrole into a polyimide COF for carbon-free ultra-high energy supercapacitor - Haldar, Sattwick; Rase, Deepak; Shekhar, Pragalbh; Jain, Chitvan; Vinod, Chathakudath Prabhakaran; Zhang, En; Shupletsov, Leonid; Kaskel, Stefan; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2022)
Redox-active covalent organic frameworks (COFs) store charges but possess inadequate electronic conductivity. Their capacitive action works by storing H+ ions in an acidic electrolyte and is typically confined to a small voltage window (0-1 V). Increasing this window means higher energy and power density, but this risks COF stability. Advantageously, COF's large pores allow the storage of polarizable bulky ions under a wider voltage thus reaching higher energy density. Here, a COF-electrode-electrolyte system operating at a high voltage regime without any conducting carbon or redox active oxides is presented. Conducting polypyrrole (Ppy) chains are synthesized within a polyimide COF to gain electronic conductivity (approximate to 10 000-fold). A carbon-free quasi-solid-state capacitor assembled using this composite showcases high pseudo-capacitance (358 mF cm(-2)@1 mA cm(-2)) in an aqueous gel electrolyte. The synergy among the redox-active polyimide COF, polypyrrole and organic electrolytes allows a wide-voltage window (0-2.5 V) leading to high energy (145 mu Wh cm(-2)) and power densities (4509 mu W cm(-2)). Amalgamating the polyimide-COF and the polypyrrole as one material minimizes the charge and mass transport resistances. Computation and experiments reveal that even a partial translation of the modules/monomers intrinsic electronics to the COF imparts excellent electrochemical activity. The findings unveil COF-confined polymers as carbon-free energy storage materials.
Keywords: carbon free capacitors; cation-anion co-storage; conductivity; high energy capacitors; polypyrrole doped COFs

Introduction to the themed collection on digitalization in reaction engineering - Galvanin, Federico; Hartman, Ryan L.; Kulkarni, Amol A.; Nieves-Remacha, Maria Jose (Reaction Chemistry & Engineering, 2022)

Machine learning-based approach to determine infection status in recipients of BBV152 (Covaxin) whole-virion inactivated SARS-CoV-2 vaccine for serological surveys - Singh, Prateek; Ujjainiya, Rajat; Prakash, Satyartha; Naushin, Salwa; Sardana, Viren; Bhatheja, Nitin; Singh, Ajay Pratap; Barman, Joydeb; Kumar, Kartik; Gayali, Saurabh; Khan, Raju; Rawat, Birendra Singh; et al. (Computers in Biology and Medicine, 2022)
Data science has been an invaluable part of the COVID-19 pandemic response with multiple applications, ranging from tracking viral evolution to understanding the vaccine effectiveness. Asymptomatic breakthrough infections have been a major problem in assessing vaccine effectiveness in populations globally. Serological discrimination of vaccine response from infection has so far been limited to Spike protein vaccines since whole virion vaccines generate antibodies against all the viral proteins. Here, we show how a statistical and machine learning (ML) based approach can be used to discriminate between SARS-CoV-2 infection and immune response to an inactivated whole virion vaccine (BBV152, Covaxin). For this, we assessed serial data on antibodies against Spike and Nucleocapsid antigens, along with age, sex, number of doses taken, and days since last dose, for 1823 Covaxin recipients. An ensemble ML model, incorporating a consensus clustering approach alongside the support vector machine model, was built on 1063 samples where reliable qualifying data existed, and then applied to the entire dataset. Of 1448 self-reported negative subjects, our ensemble ML model classified 724 to be infected. For method validation, we determined the relative ability of a random subset of samples to neutralize Delta versus wild-type strain using a surrogate neutralization assay. We worked on the premise that antibodies generated by a whole virion vaccine would neutralize wild type more efficiently than delta strain. In 100 of 156 samples, where ML prediction differed from self-reported uninfected status, neutralization against Delta strain was more effective, indicating infection. We found 71.8% subjects predicted to be infected during the surge, which is concordant with the percentage of sequences classified as Delta (75.6%-80.2%) over the same period. Our approach will help in real-world vaccine effectiveness assessments where whole virion vaccines are commonly used.
Keywords: BBV152; Covaxin; COVID-19; Ensemble methods; Infection; machine learning; SARS-CoV-2

Na-montmorillonite to Fe(II)-Mt using ferrous citrate/ascorbate obtained by dissolving iron powder - S. Chikkamath; J. Manjanna; N. Momin; B.G. Hegde; G.P. Nayaka; Aishwarya S. Kar; B.S. Tomar (Applied Clay Science, 2022)
Bentonite containing montmorillonite (Mt) as the major clay mineral is the potential buffer material of engineered barrier system in the deep geological repository for high-level waste management. The corrosion products of canister/or overpack material (carbon steel) may alter the basic characteristics of bentonite through Fe/clay interaction and formation of FeMt to certain extent. A convenient method is required for quantitative preparation of Fe(II)-Mt because the only few direct methods reported have some limitations. For this, weak ferrous complexes having good solubility to facilitate the cation-exchange with bentonite is essential. Therefore, Fe(II)-citrate, Fe(II)-ascorbate and Fe(II)-citrate/ascorbate were obtained here by dissolving the iron powder (Fe0) in citric acid (CA), ascorbic acid (AA) and their equimolar mixtures from 25 mM to 300 mM at 70 °C under N2 atmosphere. The redox potential was measured to monitor the dissolution of Fe0 in these mild organic acids. Higher dissolution of Fe0 occurred in CA + AA mixture. The dissolved iron in the form of ferrous complex was reasonably stable in inert atmosphere, Fe2+/Fetotal ≈ 1. The parent clay mineral (bentonite, NaMt) was treated with Fe(II) − cit/asc to form Fe(II) − Mt. through cation exchange process. The CEC and ferrous to ferric ratio of the Fe(II)-Mt was close to the stoichiometric amount. The XRF, XRD, ac impedance, FT-IR, TGA/DSC, XPS and FE-SEM are used for further characterization. In-situ complexation reaction of interlayer Fe2+ ions in Fe(II)-Mt with o-phenanthroline was also observed.
Keywords: Ascorbic acid; Bentonite; Citric acid; Cr(VI) reduction; Fe(II)-montmorillonite; Iron dissolution

Novel lignin as natural-biodegradable binder for various sectors-A review - Mili, Medha; Hashmi, Sayed Azhar Rasheed; Ather, Madeeha; Hada, Vaishnavi; Markandeya, Nishant; Kamble, Sanjay; Mohapatra, Mamata; Rathore, Sanjai Kumar Singh; Srivastava, Avanish Kumar; Verma, Sarika (Journal of Applied Polymer Science, 2022)
Lignin functions as an essential polymer in plants that forms the plant body's structural framework. The natural glue holds the cellulosic fibers together in the plant body, thereby providing rigidity and strength. Despite this, lignin shows promising relevance for biomaterial production due to its abundance, nontoxic nature and biodegradability. Considerably, adhesive components were derived from petroleum, which is increasingly more expensive. Hence, lignin, the natural glue in plant materials, gained much popularity because of its phenolic nature, making it an attractive substitute for adhesives. Lignin-based binders are produced through phenols substitution in phenol-formaldehyde resins with lignin due to their similar structural framework. Many researchers have confirmed the multifunctional applications of lignin, such as wood adhesive in fiber board, plywood and particleboard, a binder in printed wiring boards, abrasive tools, epoxy asphalts, epoxy wood composites, 3D printing, adhesive hydrogels, soil suppressants, lignocellulosic paper and coatings. This review presents a comprehensive description of the utilization of lignin-based binders for different applications. The present work highlights the discussion on the various methods by which lignin can be used to replace synthetic binders. This review focuses on global research work introducing lignin in different chemical adhesives for a more cost-effective and less harmful alternative.
Keywords: binder; biodegradable; lignin; multifunctional

Size-dependent order-disorder crossover in hydrophobic hydration: comparison between spherical solutes and linear alcohols - Hande, Vrushali; Chakrabarty, Suman (ACS Omega, 2022)
Theory and computer simulation studies have predicted that water molecules around hydrophobic molecules should undergo an order-disorder transition with increasing solute size around a 1 nm length scale. Some theories predict the formation of a clathrate-like ordered structure around smaller hydrophobic solutes (<1 nm) and the formation of disordered vapor-liquid interfaces around larger solutes (>1 nm) and surfaces. Experimental validation of these predictions has often been elusive and contradictory. High-resolution Raman spectroscopy has detected that water around small hydrophobic solutes shows a signature similar to that of bulk water at lower temperature (increased ordering and a stronger hydrogen-bonded network). Similarly, water around larger solutes shows an increasing population of dangling OH bonds very similar to higher temperature bulk water. Thus, the solute size dependence of the structure and dynamics of water around hydrophobic molecules seems to have an analogy with the temperature dependence in bulk water. In this work, using atomistic classical molecular dynamics (MD) simulations, we have systematically investigated this aspect and characterized this interesting analogy. Structural order parameters including the tetrahedral order parameter (Q), hydrogen bond distribution, and vibrational power spectrum highlight this similarity. However, in contrast to the experimental observations, we do not observe any length-dependent crossover for linear hydrophobic alcohols (n-alkanols) using classical MD simulations. This is in agreement with earlier findings that linear alkane chains do not demonstrate the length-dependent order-disorder transition due to the presence of a sub-nanometer length scale along the cross section of the chain. Moreover, the collapsed state of linear hydrocarbon chains is not significantly populated for smaller chains (number of carbons below 20). In the context of our computational results, we raise several pertinent questions related to the sensitivity of various structural and dynamical parameters toward capturing these complex phenomena of hydrophobic hydration.

Skin mimicking solid optical tissue phantom fulfillment and its characterization - Kumar, Ajay; Hinge, Sarika; Dixit, Hemant; Kanawade, Rajesh; Kulkarni, Gauri (Photonics in Dermatology and Plastic Surgery 2022, 2022)
Skin mimicking optical tissue phantoms are widely used in diagnostics systems for characterization, optimization, routine calibration and validation. In general, solid phantoms are more preferred in comparison to liquid phantoms. Therefore, our aim is to prepare and characterize the solid tissue phantoms having skin equivalent optical properties. In this work, we have used epoxy resin and hardener as a base material and titanium oxide (TiO2) nanoparticles and ink as a scatterer and absorber media, respectively. The total transmission (Tt), collimated transmission (Tc), and diffuse reflectance (Rd) spectra of the developed phantoms were measured with an integrating sphere installed in UV-VIS spectrometer within the wavelength range 400-700 nm. To characterize the optical properties such as absorption (mu(a)), reduced scattering (mu(s)'), and anisotropy factor (g) of the developed tissue phantoms, the numerical model based on Inverse Adding Doubling (IAD) has been used. With various concentrations of absorber and scatterer, a calibration curve was prepared. The calculated experimental optical properties from IAD matched with the predicted intrinsic optical properties of the skin. Thus, the preliminary results suggest that the recipe used in this study may be used as an alternative approach to developing skin mimicking solid optical phantom for diagnostics system applications.
Keywords: Absorption; anisotropy factor; scattering; skin mimicking; solid tissue phantom

SNP discovery and structural insights into OeFAD2 unravelling high oleic/linoleic ratio in olive oil - Ben Ayed, Rayda; Moreau, Fabienne; Ben Hlima, Hajer; Rebai, Ahmed; Ercisli, Sezai; Kadoo, Narendra; Hanana, Mohsen; Assouguem, Amine; Ullah, Riaz; Ali, Essam A. (Computational and Structural Biotechnology Journal, 2022)
Fatty Acid Desaturase 2 (FAD2), a key enzyme in the fatty acid biosynthesis pathway, is involved in the desaturation and conversion of oleic acid to linoleic acid. Therefore, it plays a crucial role in oleic/linoleic acid ratio and the quality of olive oil. DNA sequencing of 19 FAD2 genes from a set of olive oil varieties revealed several single-nucleotide polymorphisms (SNPs) and highlighted associations between some of the SNPs and saturated fatty acids contents. This was further confirmed by SNP-interaction and machine learning approach. Haplotype diversity analysis led to the discovery of three highly polymorphic SNPs and four haplotypes harboring differential oleic/linoleic acid ratios. Moreover, a combination of molecular modeling and docking experiments allowed a deeper and better understanding of the structure-function relationship of the FAD2 enzyme. Sequence patterns and variations involved in the regulation of the FAD2 activity were also identified. Furthermore, S82C and H213N substitutions in OeFAD2 make the Oueslati variety more interesting in terms of fatty acid profile and oleic acid level. (C) 2022 The Authors. Published by Elsevier B.V. on behalf of Research Network of Computational and Structural Biotechnology.
Keywords: docking; Fatty acid desaturase; Haplotype; machine learning; Oleic/linoleic acid ratio; Protein structure

Stacking herbicide detoxification and resistant genes improves glyphosate tolerance and reduces phytotoxicity in tobacco (Nicotiana tabacum L.) and rice (Oryza sativa L.) - Vennapusa, Amaranatha Reddy; Agarwal, Subham; Hm, Hanumanth Rao; Aarthy, Thiagarayaselvam; Babitha, K. C.; Thulasiram, V. Hirekodathakallu; Kulkarni, Mahesh J.; Melmaiee, Kalpalatha; Sudhakar, Chinta; Udayakumar, M.; Vemanna, Ramu S. (Plant Physiology and Biochemistry, 2022)
Glyphosate residues retained in the growing meristematic tissues or in grains of glyphosate-resistant crops affect the plants physiological functions and crop yield. Removing glyphosate residues in the plants is desirable with no penalty on crop yield and quality. We report a new combination of scientific strategy to detoxify glyphosate that reduces the residual levels and improve crop resistance. The glyphosate detoxifying enzymes Aldo-keto reductase (AKR1) and mutated glycine oxidase (mGO) with different modes of action were co-expressed with modified EPSPS, which is insensitive to glyphosate in tobacco (Nicotiana tabacum L.) and rice (Oryza sativa L.). The transgenic tobacco plants expressing individual PsAKR1, mGO, CP4-EPSPS, combinations of PsAKR1:CP4EPSPS, PsAKR1:mGO, and multigene with PsAKR1: mGO: CP4EPSPS genes were developed. The bio-efficacy studies of in-vitro leaf regeneration on different concentrations of glyphosate, seedling bioassay, and spray on transgenic tobacco plants demonstrate that glyphosate detoxification with enhanced resistance. Comparative analysis of the transgenic tobacco plants reveals that double and multigene expressing transgenics had reduced accumulation of shikimic acid, glyphosate, and its primary residue AMPA, and increased levels of sarcosine were observed in all PsAKR1 expressing transgenics. The multigene expressing rice transgenics showed improved glyphosate resis-tance with yield maintenance. In summary, results suggest that stacking genes with two different detoxification mechanisms and insensitive EPSPS is a potential approach for developing glyphosate-resistant plants with less residual content.
Keywords: Detoxification; Gene stacking; Glyphosate; Herbicide; Multigene; Residual toxicity; Resistant; rice; Tobacco; Transgenics

SUMOylation of dorsal attenuates Toll/NF-kappa B signaling - Hegde, Sushmitha; Sreejan, Ashley; Gadgil, Chetan J.; Ratnaparkhi, Girish S. (Genetics, 2022)
In Drosophila, Toll/NF-kappa B signaling plays key roles in both animal development and in host defense. The activation, intensity, and kinetics of Toll signaling are regulated by posttranslational modifications such as phosphorylation, SUMOylation, or ubiquitination that target multiple proteins in the Toll/NF-kappa B cascade. Here, we have generated a CRISPR-Cas9 edited Dorsal (DL) variant that is SUMO conjugation resistant. Intriguingly, embryos laid by dl(SCR) mothers overcome dl haploinsufficiency and complete the developmental program. This ability appears to be a result of higher transcriptional activation by DLSCR. In contrast, SUMOylation dampens DL transcriptional activation, ultimately conferring robustness to the dorso-ventral program. In the larval immune response, dl(SCR) animals show an increase in crystal cell numbers, stronger activation of humoral defense genes, and high cactus levels. A mathematical model that evaluates the contribution of the small fraction of SUMOylated DL (1-5%) suggests that it acts to block transcriptional activation, which is driven primarily by DL that is not SUMO conjugated. Our findings define SUMO conjugation as an important regulator of the Toll signaling cascade, in both development and host defense. Our results broadly suggest that SUMO attenuates DL at the level of transcriptional activation. Furthermore, we hypothesize that SUMO conjugation of DL may be part of a Ubc9-dependent mechanism that restrains Toll/NF-kappa B signaling.
Keywords: Drosophila; haploinsufficiency; innate immunity; SUMO; transcription

Tailored synthesis of ultra-stable Au@Pd nanoflowers with enhanced catalytic properties using cellulose nanocrystals - Hakkeem, Hasna M. Abdul; Babu, Aswathy; Shilpa, Nagaraju; Venugopal, Adithya A.; Mohamed, A. P.; Kurungot, Sreekumar; Pillai, Saju (Carbohydrate Polymers, 2022)
A green strategy for the synthesis of bimetallic core-shell Au@Pd nanoflowers (NFs) employing banana pseudostem-derived TEMPO-oxidized cellulose nanocrystals (TCNC) as both capping and shape-directing agent via seed-mediated method is presented. Flower-like nanostructures of Au@Pd bound to TEMPO-oxidized cellulose nanocrystals (TCNC-Au@Pd) were decorated on amino-functionalized graphene (NH2-RGO) without losing their unique structure, allowing them to be deployed as an efficient, reusable and a green alternative heterogeneous catalyst. The decisive role of TCNC in the structural metamorphosis of nanoparticle morphology were inferred from the structural and morphology analyses. According to our study, the presence of -OH rich TCNC appears to play a pivotal role in the structured evolution of intricate nanostructure morphology. The feasibility of the bio-supported catalyst has been investigated in two concurrently prevalent model catalytic reactions, namely the oxygen reduction reaction (ORR) and the reduction of 4-nitrophenol, the best model reactions in fuel cell and industrial catalytic applications, respectively.
Keywords: Au@Pd; catalysis; Cellulose nanocrystals; Nanoflowers; oxygen reduction reaction

Tantalum based single, double, and triple atom catalysts supported on g-C2N monolayer for effective nitrogen reduction reaction: a comparative DFT investigation - Rasool, Anjumun; Anis, Insha; Dixit, Mudit; Maibam, Ashakiran; Hassan, Afshana; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Catalysis Science & Technology, 2022)
Design of efficient and low cost electrocatalysts for the reduction of N-2 molecule to NH3 in a green manner remains a great challenge in the 21st century. Herein, we have used density functional theory based first principle simulations to systematically investigate the nitrogen reduction reaction (NRR) ability of single, double, and triple Ta-atom catalysts anchored to C2N monolayer. Our results demonstrate that the single and triple Ta-atom catalysts anchored to C2N monolayer act as superior catalysts for the NRR via alternating and distal pathways as compared to the Ru(0001) stepped surface. In particular, the triple Ta-atom catalyst anchored to C2N shows enhanced NRR performance with a limiting potential of -0.72 V which is comparable to the experimentally reported Ru based single atom catalyst. Further, all the three catalysts were found to be highly selective for NRR with an enhanced ability to suppress the competitive hydrogen evolution reaction. Electronic structure analysis revealed that the enhanced ability of Ta-3@C2N catalyst to effectively capture and reduce N-2 molecule could be attributed to the built up of localized d states near the fermi level, thereby aiding in strong electron transfer into the antibonding orbitals of N-2. Thus, our findings propose a highly active catalyst for the NRR with an emphasis on the importance of triple atom-based catalysts for electrocatalytic applications.

Two antibacterial spiro compounds from the roots of Artemisia pallens wall: evidence from molecular docking - Honmore, Varsha S.; Natu, Arun D.; Khedkar, Vijay M.; Arkile, Manisha A.; Sarkar, Dhiman; Rojatkar, Supada R. (Natural Product Research, 2022)
Bioassay-guided isolation from acetone extract of the roots of Artemisia pallens Wall yielded two spiro compounds (1 and 2). The structures of these compounds were determined on the basis of spectroscopic techniques such as IR, MS, 1 D and 2 D- NMR. The acetone extract, fractions and the isolated two compounds were investigated for their antibacterial activity against two gram negative (E. coli, P. aeruginosa) and two gram positive (S. aureus, B. subtilis) bacterial strains. Compound (2) showed the best spectra of activity with IC50 and MIC values between 2.48-3.08 and 12.78 - 21.77 mu M and Compound (1) with 2.57-3.69 and 38.17 - 80.57 mu M, respectively, for the four bacterial strains, whereas inactive against Mycobacterium tuberculosis. Molecular docking study could further help in understanding the various interactions between these compounds and DNA gyrase active site in detail and thereby could provide valuable insight into the mechanism of action.
Keywords: antibacterial activity; antimycobacterial activity; Artemisia pallens; Asteraceae; Molecular docking; spiro compound

Understanding the effect of sodium polyphosphate on improving the chemical stability of Ti3C2Tz MXene in water - Huang, Shuohan; Natu, Varun; Tao, Jingyi; Xia, Yumin; Mochalin, Vadym N.; Barsoum, Michel W. (Journal of Materials Chemistry A, 2022)
Degradation of MXenes in aqueous environments severely limits the application and industrialization of this large family of two-dimensional (2D) materials. Hydrolysis and oxidation are now considered as two main degradation mechanisms and while significant efforts have been directed to prolonging the shelf-life of MXenes, separating and studying their degradation mechanisms have lagged behind. Herein, gas analysis via gas chromatography and Raman spectroscopy were used to investigate the effect of sodium polyphosphate, PP, on the degradation of Ti3C2Tz MXene. Transmission and scanning electron microscopies, as well as X-ray photoelectron spectroscopywere also used as complimentary techniques to support conclusions derived from gas analysis and to confirm the extent of degradation via characterization of solid reaction products. Based on these studies we have determined that the addition of PP to an equal mass of Ti3C2Tz solution can effectively suppress hydrolysis and protect Ti3C2Tz from degradation.

Unravelling faradaic electrochemical efficiencies over Fe/Co spinel metal oxides using surface spectroscopy and microscopy techniques - Kashyap, Varchaswal; Pandikassala, Ajmal; Singla, Gourav; Khan, Tuhin Suvra; Haider, M. Ali; Vinod, C. P.; Kurungot, Sreekumar (Nanoscale, 2022)
Cobalt and iron metal-based oxide catalysts play a significant role in energy devices. To unravel some interesting parameters, we have synthesized metal oxides of cobalt and iron (i.e. Fe2O3, Co3O4, Co2FeO4 and CoFe2O4), and measured the effect of the valence band structure, morphology, size and defects in the nanoparticles towards the electrocatalytic hydrogen evolution reaction (HER), the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR). The compositional variations in the cobalt and iron precursors significantly alter the particle size from 60 to <10 nm and simultaneously the shape of the particles (cubic and spherical). The Tauc plot obtained from the solution phase ultraviolet (UV) spectra of the nanoparticles showed band gaps of 2.2, 2.3, 2.5 and 2.8 eV for Fe2O3, Co3O4, Co2FeO4 and CoFe2O4, respectively. Further, the valence band structure and work function analysis using ultraviolet photoelectron spectroscopy (UPS) and core level X-ray photoelectron spectroscopy (XPS) analyses provided better structural insight into metal oxide catalysts. In the Co3O4 system, the valence band structure favors the HER and Fe2O3 favors the OER. The composites Co2FeO4 and CoFe2O4 show a significant change in their core level (O 1s, Co 2p and Fe 2p spectra) and valence band structure. Co3O4 shows an overpotential of 370 mV against 416 mV for Fe2O3 at a current density of 2 mA cm(-2) for the HER. Similarly, Fe2O3 shows an overpotential of 410 mV against the 435 mV for Co3O4 at a current density of 10 mA cm(-2) for the OER. However, for the ORR, Co3O4 shows 70 mV improvement in the half-wave potential against Fe2O3. The composites (Co2FeO4 and CoFe2O4) display better performance compared to their respective parent oxide systems (i.e., Co3O4 and Fe2O3, respectively) in terms of the ORR half-wave potential, which can be attributed to the presence of the oxygen vacancies over the surface in these systems. This was further corroborated in density functional theory (DFT) simulations, wherein the oxygen vacancy formation on the surface of CoFe2O4(001) was calculated to be significantly lower (similar to 50 kJ mol(-1)) compared to Co3O4 (001). The band diagram of the nanoparticles constructed from the various spectroscopic measurements with work function and band gap provides in-depth understanding of the electrocatalytic process.

Water-controlled keto-enol tautomerization of a prebiotic nucleobase - Datar, Avdhoot; Paithankar, Harshad; Deb, Pranab; Chugh, Jeetender; Bagchi, Sayan; Mukherjee, Arnab; Hazra, Anirban (Journal of Physical Chemistry B, 2022)
Barbituric acid is believed to be a proto-RNA nucleobase that was used for biological information transfer on prebiotic earth before DNA and RNA in their present forms evolved. Nucleobases have various tautomeric forms and the relative stability of these forms is critical to their biological function. It has been shown that barbituric acid has a tri-keto form in the gas phase and an enol form in the solid state. However, its dominant tautomeric form in aqueous medium that is most relevant for biology has been investigated only to a limited extent and the findings are inconclusive. We have used multiple approaches, namely, molecular dynamics, quantum chemistry, NMR, and IR spectroscopy to determine the most stable tautomer of barbituric acid in solution. We find a delicate balance in the stability of the two tautomers, tri-keto and enol, which is tipped toward the enol as the extent of solvation by water increases.

Antibacterial and anti-HIV metabolites from marine streptomyces albus MAB56 isolated from Andaman and Nicobar Islands, India - Manikkam, Radhakrishnan; Murthy, Sangeetha; Palaniappan, Sivasankar; Kaari, Manigundan; Sahu, Amit Kumar; Said, Madhukar; Ganesan, Vijayalakshmi; Kannan, Sivakumar; Ramasamy, Balagurunathan; Thirugnanasambandan, Somasundaram; Dastager, Syed G.; Hanna, Luke Elizabeth; et al. (Applied Biochemistry and Biotechnology, 2023)
Marine-derived actinobacteria have tremendous potential to produce novel metabolites with diverse biological activities. The Andaman coast of India has a lot of microbial diversity, but it is still a relatively unknown ecology for isolating novel actinobacteria with beneficial bioactive compounds. We have isolated 568 actinobacterial strains from mangrove rhizosphere sediments and sponge samples. Crude extracts from 75 distinct strains were produced by agar surface fermentation and extracted using ethyl acetate. In the disc diffusion method, 25 actinobacterial strains showed antimicrobial activity; notably, the strain MAB56 demonstrated promising broad-spectrum activity. Strain MAB56 was identified as Streptomyces albus by cultural, microscopic, and molecular methods. Conditions for bioactive metabolites from MAB56 were optimized and produced in a lab-scale fermenter. Three active metabolites (C1, C2, and C3) that showed promising broad-spectrum antimicrobial activity were isolated through HPLC-based purification. Based on the UV, FT-IR, NMR, and LC-MS analysis, the chemical nature of the active compounds was confirmed as 12-methyltetradecanoic acid (C1), palmitic acid (C2), and tridecanoic acid (C3) with molecular formulae C14H28O2, C16H32O2, and C13H26O2, respectively. Interestingly, palmitic acid (C2) also exhibited anti-HIV activity with an IC50 value of < 1 mu g/ml. Our findings reveal that the actinobacteria from the Andaman marine ecosystems are promising for isolating anti-infective metabolites.
Keywords: actinobacteria; Andaman Islands; anti-HIV; Antibacterial; Bioactive metabolites

Antimalarial activity of anacardium occidentale leaf extracts against plasmodium falciparum transketolase (PfTK) - Kaushik, Meenakshi; Hoti, Sugeerappa L.; Saxena, Jitendra Kumar; Hingamire, Tejashri; Shanmugam, Dhanasekaran; Joshi, Rajesh K.; Metgud, Sharada C.; Ungar, Banappa; Singh, Ishwar; Hegde, Harsha V. (Acta Parasitologica, 2023)
BackgroundAs per estimates by WHO in 2021 almost half of the world's population was at risk of malaria and > 0.6 million deaths were attributed to malaria. Therefore, the present study was aimed to explore the antimalarial activity of extracts derived from the leaves of the plant Anacardium occidentale L., which has been used traditionally for the treatment of malaria. Different extracts of A.occidentale leaves were prepared and tested for their inhibitory activity against recombinant P. falciparum transketolase (rPfTK) enzyme, in vitro. Further, growth inhibitory activity against cultivated blood stage P. falciparum parasites (3D7 strain), was studied using SYBR Green fluorescence-based in vitro assays. Acute toxicity of the hydro alcoholic extracts of leaves of A. occidentale (HELA) at different concentrations was evaluated on mice and Zebra fish embryos. HELA showed 75.45 +/- 0.35% inhibitory activity against the recombinant PfTk and 99.31 +/- 0.08% growth inhibition against intra-erythrocytic stages of P. falciparum at the maximum concentration (50 mu g/ml) with IC50 of 4.17 +/- 0.22 mu g/ml. The toxicity test results showed that the heartbeat, somite formation, tail detachment and hatching of embryos were not affected when Zebra fish embryos were treated with 0.1 to 10 mu g/ml of the extract. However, at higher concentrations of the extract, at 48 h (1000 mu g/ml) and 96 h (100 mu g/ml and 1000 mu g/ml, respectively) there was no heartbeat in the fish embryos. In the acute oral toxicity tests performed on mice, the extract showed no toxicity up to 300 mg/kg body weight in mice.ConclusionThe hydro-alcoholic extract of leaves of A. occidentale L. showed potent antimalarial activity against blood stage P. falciparum. Based on the observed inhibitory activity on the transketolase enzyme of P. falciparum it is likely that this enzyme is the target for the development of bioactive molecules present in the plant extracts. The promising anti-malarial activity of purified compounds from leaves of A. occidentale needs to be further explored for development of new anti-malarial therapy.
Keywords: Anacardium occidentale L; Antimalarial activity; malaria; Plasmodium falciparum; Transketolase

Antiviral and ROS scavenging potential of Carica papaya Linn and Psidium guajava leaves extract against HIV-1 infection - Jadaun, Pratiksha; Shah, Prachibahen; Harshithkumar, R.; Said, Madhukar S.; Bhoite, Shubhangi P.; Bokuri, Sowmya; Ravindran, Selvan; Mishra, Neetu; Mukherjee, Anupam (BMC Complementary Medicine and Therapies, 2023)
Antiretroviral therapy is the only treatment option for HIV-infected patients; however, it has certain drawbacks in terms of developing multiple toxic side effects. Thus, there is a continuous need to explore safe and efficacious anti-retroviral agents. Carica papaya Linn and Psidium guajava are known for their various biological activities. In this study, we characterized the bioactive fractions of methanolic leaves extract from both plants using the High-resolution electrospray ionization mass spectrometry (HR-ESI-MS) technique, followed by the investigation of their potential as anti-HIV-1 and antioxidant agents through in vitro mechanistic assays. The anti-HIV-1 activity was examined in TZM-bl cells through luciferase gene assay against two different clades of HIV-1 strains, whereas the intracellular ROS generation was analyzed by Fluorescence-Activated Cell Sorting. Additionally, the mechanisms of action of these phyto-extracts were determined through the Time-of-addition assay. The characterization of Carica papaya Linn and Psidium guajava leaves extract through HR-ESI-MS fragmentation showed high enrichment of various alkaloids, glycosides, lipids, phenolic compounds, terpenes, and fatty acids like bioactive constituents. Both the phyto-extracts were found to be less toxic and exhibited potent antiviral activity against HIV-1 strains. Furthermore, the phyto-extracts also showed a decreased intracellular ROS in HIV-1 infected cells due to their high antioxidant potential. Overall, our study suggests the anti-HIV-1 potential of Carica papaya Linn and Psidium guajava leaves extract due to the synergistic action of multiple bioactive constituents.
Keywords: anti-HIV-1 activity; Anti-retroviral; Bioactive constituents; Carica papaya Linn; Cytotoxicity; HR-ESI-MS; Psidium guajava; reactive oxygen species

BAHD-type acyltransferase concludes the biosynthetic pathway of non-bitter glycoalkaloids in ripe tomato fruit - Sonawane, Prashant D.; Gharat, Sachin A.; Jozwiak, Adam; Barbole, Ranjit; Heinicke, Sarah; Almekias-Siegl, Efrat; Meir, Sagit; Rogachev, Ilana; O'Connor, Sarah E.; Giri, Ashok P.; Aharoni, Asaph (Nature Communications, 2023)
During tomato fruit ripening, bitter and toxic steroidal glycoalkaloids (SGAs) are converted to nonbitter and less toxic forms, but proposed acylating enzyme in pathway remain unknown. Here, authors report BAHD-type acyltransferase that catalyze acylation step in biosynthesis of non-bitter SGAs in tomato. Tomato is the highest value fruit and vegetable crop worldwide, yet produces & alpha;-tomatine, a renowned toxic and bitter-tasting anti-nutritional steroidal glycoalkaloid (SGA) involved in plant defense. A suite of modifications during tomato fruit maturation and ripening converts & alpha;-tomatine to the non-bitter and less toxic Esculeoside A. This important metabolic shift prevents bitterness and toxicity in ripe tomato fruit. While the enzymes catalyzing glycosylation and hydroxylation reactions in the Esculeoside A pathway have been resolved, the proposed acetylating step remains, to date, elusive. Here, we discovered that GAME36 (GLYCOALKALOID METABOLISM36), a BAHD-type acyltransferase catalyzes SGA-acetylation in cultivated and wild tomatoes. This finding completes the elucidation of the core Esculeoside A biosynthetic pathway in ripe tomato, allowing reconstitution of Esculeoside A production in heterologous microbial and plant hosts. The involvement of GAME36 in bitter SGA detoxification pathway points to a key role in the evolution of sweet-tasting tomato as well as in the domestication and breeding of modern cultivated tomato fruit.

Construction of the quinobenzoxazine core via gold-catalyzed dual annulation of azide-tethered alkynones with anthranils - Halnor, Swapnil V. V.; Dhote, Pawan S. S.; Ramana, Chepuri V. V. (Organic & Biomolecular Chemistry, 2023)
A new catalytic method for the construction of the quinobenzoxazine core has been developed employing the gold-catalyzed cyclization of o-azidoacetylenic ketones in the presence of anthranils. The overall process comprises of a gold-catalyzed 6-endo-dig cyclisation of o-azidoacetylenic ketone leading to a alpha-imino gold carbene and subsequent carbene transfer to anthranil leading to the 3-aryl-imino-quinoline-4-one intermediate, which undergoes 6 pi-electrocyclization and aromatization to form the central quinobenzoxazine core. This transformation provides a new approach to a diverse array of quinobenzoxazine structures, in addition to being scalable and having mild reaction conditions.

Covalent organic framework thin-film photodetectors from solution-processable porous nanospheres - Bag, Saikat; Sasmal, Himadri Sekhar; Chaudhary, Sonu Pratap; Dey, Kaushik; Blaette, Dominic; Guntermann, Roman; Zhang, Yingying; Poloz, Miroslav; Kuc, Agnieszka; Shelke, Ankita; Vijayaraghavan, Ratheesh K.; Ajithkumar, Thalasseril G.; et al. (Journal of the American Chemical Society, 2023)
The synthesis of homogeneous covalent organic framework (COF) thin films on a desired substrate with decent crystallinity, porosity, and uniform thickness has great potential for optoelectronic applications. We have used a solution-processable sphere transmutation process to synthesize 300 +/- 20 nm uniform COF thin films on a 2 x 2 cm2 TiO2-coated fluorine-doped tin oxide (FTO) surface. This process controls the nucleation of COF crystallites and molecular morphology that helps the nanospheres to arrange periodically to form homogeneous COF thin films. We have synthesized four COF thin films (TpDPP, TpEtBt, TpTab, and TpTta) with different functional backbones. In a close agreement between the experiment and density functional theory, the TpEtBr COF film showed the lowest optical band gap (2.26 eV) and highest excited-state lifetime (8.52 ns) among all four COF films. Hence, the TpEtBr COF film can participate in efficient charge generation and separation. We constructed optoelectronic devices having a glass/FTO/TiO2/COF-film/Au architecture, which serves as a model system to study the optoelectronic charge transport properties of COF thin films under dark and illuminated conditions. Visible light with a calibrated intensity of 100 mW cm-2 was used for the excitation of COF thin films. All of the COF thin films exhibit significant photocurrent after illumination with visible light in comparison to the dark. Hence, all of the COF films behave as good photoactive substrates with minimal pinhole defects. The fabricated out-of-plane photodetector device based on the TpEtBr COF thin film exhibits high photocurrent density (2.65 +/- 0.24 mA cm-2 at 0.5 V) and hole mobility (8.15 +/- 0.64 x10-3 cm2 V-1 S-1) compared to other as synthesized films, indicating the best photoactive characteristics.

Design and development of multi-functional graphitic carbon nitride heterostructures embedded with copper and iron oxide nanoparticles as versatile sensing platforms for environmental and agricultural applications - Khasim, Syed; Pasha, Apsar; Dastager, Syed G.; Panneerselvam, Chellasamy; Hamdalla, Taymour A.; Al-Ghamdi, S. A.; Alfadhli, S.; Makandar, Mohammad Basha; Albalawi, Jalal Bassam; Darwish, A. A. A. (Ceramics International, 2023)
In the recent past, agrotechnology has witnessed a tremendous change due to the advent of technologies employed towards enhancing the yield and quality of the crops. The application of nanotechnology in agriculture is promoting sustainable practices and smart farming. Currently, nanomaterial-based sensors are gaining considerable attention in agrotechnology, such sensors can detect the environmental conditions and support for crop growth and enhances the agricultural yield. Graphiticcarbon nitride (g-C3N4), a soft polymer belongs to a class of 2-D semiconductors which are affordable, metal-free, indispensable for sensing applications due to significant changes in their conductivity upon exposure to analyte molecules in nano-regime. Further, this g-C3N4 can be combined with other nano metal oxides to form nanocomposites with remarkable properties and superior performance. In this work we report development of high-performance sensors based on graphitic carbon nitride embedded with copper and iron oxide nanoparticles. These heterostructures offers tremendous improvement in the physical and chemical properties due to the synergetic interactions between various phases. The chemiresistive sensor fabricated from these nanocomposites exhibit excellent sensitivity towards monitoring methane gas @ ppb level, relative humidity (% RH), and soil moisture content. Owing to their excellent sensitivity, stability and selectivity, this graphitic carbon nitride embedded with Cu and Fe oxide nanoparticles could be potentially used as multifunctional sensors towards environmental monitoring and greenhouse conditions in agricultural applications.
Keywords: Agricultural sensors; CuO nanoparticles; Environmental monitoring; FeO nanoparticles; Graphitic carbon nitride

Effect of acidity and mesoporosity in H-USY on conversion of wheat straw to ethyl levulinate (Biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Nandanwar, Sachin; Bokade, Vijay (Journal of the Indian Chemical Society, 2023)
Cold flow properties of biodiesel can be improved by addition of additives especially ethyl levulinate (EL up to 20%). There are very limited information on synthesis of EL from actual raw biomass like wheat straw over heterogeneous catalyst. The present article elaborated on optimization of Acidity to Mesoporosity ratio in H-USY, which is crucial for its application in conversion of raw wheat straw to selective formation of EL in one-step. The acidity and mesoporosity is monitor by systematic post treatment of desilication and dealumination. Optimum acidity/mesoporosity ratio of 3.6 in HUSY resulted in to maximum EL yield of 24.5%, which is probably the highest so far.
Keywords: Acidity; Biofuel additive; Dealumination; Desilication; ethyl levulinate; H-USY; Mesoporosity; Wheat straw

Emergent stability in complex network dynamics - Meena, Chandrakala; Hens, Chittaranjan; Acharyya, Suman; Haber, Simcha; Boccaletti, Stefano; Barzel, Baruch (Nature Physics, 2023)
The stable functionality of networked systems is a hallmark of their natural ability to coordinate between their multiple interacting components. Yet, real-world networks often appear random and highly irregular, raising the question of what are the naturally emerging organizing principles of complex system stability. The answer is encoded within the system's stability matrix-the Jacobian-but is hard to retrieve, due to the scale and diversity of the relevant systems, their broad parameter space and their nonlinear interaction dynamics. Here we introduce the dynamic Jacobian ensemble, which allows us to systematically investigate the fixed-point dynamics of a range of relevant network-based models. Within this ensemble, we find that complex systems exhibit discrete stability classes. These range from asymptotically unstable (where stability is unattainable) to sensitive (where stability abides within a bounded range of system parameters). Alongside these two classes, we uncover a third asymptotically stable class in which a sufficiently large and heterogeneous network acquires a guaranteed stability, independent of its microscopic parameters and robust against external perturbation. Hence, in this ensemble, two of the most ubiquitous characteristics of real-world networks-scale and heterogeneity-emerge as natural organizing principles to ensure fixed-point stability in the face of changing environmental conditions. Despite looking highly irregular, most real-world networks exhibit natural stability to external perturbations. A study of the properties of the stability matrix of networks now sheds light on the principles underlying this emerging stability.

G4-binding drugs, chlorpromazine and prochlorperazine, repurposed against COVID-19 infection in hamsters - Roy, Shuvra Shekhar; Sharma, Shalu; Rizvi, Zaigham Abbas; Sinha, Dipanjali; Gupta, Divya; Rophina, Mercy; Sehgal, Paras; Sadhu, Srikanth; Tripathy, Manas Ranjan; Samal, Sweety; Maiti, Souvik; Scaria, Vinod; et al. (Frontiers in Molecular Biosciences, 2023)
The COVID-19 pandemic caused by SARS-CoV-2 has caused millions of infections and deaths worldwide. Limited treatment options and the threat from emerging variants underline the need for novel and widely accessible therapeutics. G-quadruplexes (G4s) are nucleic acid secondary structures known to affect many cellular processes including viral replication and transcription. We identified heretofore not reported G4s with remarkably low mutation frequency across >5 million SARS-CoV-2 genomes. The G4 structure was targeted using FDA-approved drugs that can bind G4s - Chlorpromazine (CPZ) and Prochlorperazine (PCZ). We found significant inhibition in lung pathology and lung viral load of SARS-CoV-2 challenged hamsters when treated with CPZ or PCZ that was comparable to the widely used antiviral drug Remdesivir. In support, in vitro G4 binding, inhibition of reverse transcription from RNA isolated from COVID-infected humans, and attenuated viral replication and infectivity in Vero cell cultures were clear in case of both CPZ and PCZ. Apart from the wide accessibility of CPZ/PCZ, targeting relatively invariant nucleic acid structures poses an attractive strategy against viruses like SARS-CoV-2, which spread fast and accumulate mutations quickly.
Keywords: Conserved motif; FDA-approved drugs; G-quadruplex binding drugs; hamster model of COVID-19; RNA G-quadruplex

Histidinal-based potent antimalarial agents - Meena, Chhuttan L.; Hingamire, Tejashri; Gupta, Tanya; Deshmukh, Bhagyashree; Karmodiya, Krishanpal; Joshi, Rakesh; Shanmugam, Dhanasekaran; Sanjayan, Gangadhar J. (ChemMedChem, 2023)
Herein we report the synthesis and evaluation of peptide-histidinal conjugated drug scaffolds, which have the potential to target the hemoglobin-degrading proteases falcipain-2/3 from the human malaria parasite. Scaffolds with various substitutions were tested for antimalarial activity, and compounds 8 g, 8 h, and 15 exhibited EC50 values of similar to 0.018 mu M, similar to 0.069 mu M, and similar to 0.02 mu M, respectively. Structure-based docking studies on falcipain-2/3 proteases (PDB:2GHU and PDB:3BWK) revealed that compounds 8 g, 8 h, and 15 interact strongly with binding sites of falcipain-2/3 in a substrate-like manner. In silico ADME studies revealed that the molecules of interest showed no or minimal violations of drug-likeness parameters. Further, phenotypic assays revealed that compound 8 g and its biotinylated version inhibit hemoglobin degradation in the parasite food vacuole. The identification of falcipain-2/3 targeting potent inhibitors of the malaria parasite can serve as a starting point for the development of lead compounds as future antimalarial drug candidates.
Keywords: artemisinin; chloroquine; digestive vacuole; docking; falcipains; falciparum; P

Hydroxide ion-conducting viologen-bakelite organic frameworks for flexible solid-state zinc-air battery applications - Rase, Deepak; Illathvalappil, Rajith; Singh, Himan Dev; Shekhar, Pragalbh; Leo, Liya S.; Chakraborty, Debanjan; Haldar, Sattwick; Shelke, Ankita; Ajithkumar, Thalasseril G.; Vaidhyanathan, Ramanathan (Nanoscale Horizons, 2023)
Adaptable polymer-based solid-state electrolytes can be a game-changer toward safe, lightweight flexible batteries. We present a robust Bakelite-type organic polymer covalently decked with viologen, triazine, and phenolic moieties. Its flexible structure with cationic viologen centers incorporates counter-balancing free hydroxide ions into the polymeric framework. By design, the aromatic groups and heteroatoms in the framework can be activated under an applied potential to prompt a push-pull drive, setting off the towing of hydroxide ions via weak electrostatic, van der Waals, and hydrogen-bond interactions. The frontier orbitals from a DFT-modeled structure certify this. The hydroxyl-polymer requires minimal KOH wetting to maintain a humid environment for Grotthuss-type transport. The hydroxide ion conductivity reaches a value of 1.4 x 10(-2) S cm(-1) at 80 degrees C and 95% RH, which is retained for over 15 h. We enhanced its practical utility by coating it as a thin solid-state separator-cum-electrolyte on readily available filter paper. The composite exhibits a conductivity of 4.5 x 10(-3) S cm(-1) at 80 degrees C and 95% RH. A zinc-air battery (ZAB) constructed using this polymer-coated paper as electrolyte yields a maximum power density of 115 mW cm(-2) and high specific capacitance of 435 mA h g(-1). The power density recorded for our ZAB is among the best reported for polymer electrolyte-based batteries. Subsequently, the flexible battery fabricated with IISERP-POF11_OH@FilterPaper exhibits an OCV of 1.44 V, and three batteries in series power a demo traffic signal. To underscore the efficiency of hydroxide ion transport through the complex multifunctional backbone of the polymer, we calculated the diffusion coefficient for OH- (Exp: 2.9 x 10(-5) cm(2) s(-1); Comp. 5.2 x 10(-6) cm(2) s(-1)) using electrochemical methods and MD simulations. Climbing-edge NEB calculations reveal a large energy barrier of 2.11 eV for Zn2+ to penetrate the polymer and identify hydroxide ions within the polymer, suggesting no undesirable Zn2+ crossover. Our findings assert the readily accessible C-C-linked cationic polymer's capacity as a solid-state electrolyte for ZABs and any anion-conducting membrane.

Novel Biogenic Synthesis of Pd/TiO@BC as an electrocatalytic and possible energy storage materials - Khasim, Syed; Dastager, Syed G.; Alahmdi, Mohammed Issa; Hamdalla, Taymour A.; Panneerselvam, Chellasamy; Makandar, Mohammad Basha (Ceramics International, 2023)
The standard approach towards synthesizing nanomaterials exercising chemical or physical techniques generally costs more and necessitates using toxic chemicals, which negatively affect the environment. For the first time, an investigation of a basic green synthesis approach for Phyto fabrication of Pd/TiO@BC nanocomposite via biomass of rice husk (Oryza sativa L) is conducted to sustain the green chemistry for synthesis of less toxic chemicals. XRD analysis revealed that the structure of Phyto synthesized Pd/TiO@BC is crystalline, while UV, FTIR, SEM and EDX analyses marked the victorious nanocomposite biosynthesis. We have investigated the electrocatalytic and biomedical applications of the novel nanocomposite Pd/TiO@BC at different environmental conditions. Testing the potential electrochemical properties of Pd/TiO@BC to eliminate the Congo red (CR) dye from wastewater marked its high removal efficiency, which attained 90% owing to the higher electron efficiency. Its sensitivity for CR was also examined, and acceptable degradation activity was observed. These Pd/TiO@BC proved to be beneficial in various fields, including electrochemistry, catalysis sensors, wastewater treatment, and nano-devices, and in the transformation of hazardous particles into less harmful substances. Its great potential for use as a supercapacitor is promised by its feature, including durability and compact stability. Significant guidelines could be extracted from the results, which are helpful in material size, synthesis, selection, and configuration design for various energy storage gadgets. The synthesis of high performance and economical materials through green chemistry is a novel approach towards effective energy storage and alteration procedure operation.
Keywords: Electro catalytic; Energy storage; Oryza sativa L biochar; Pd; PdNPs and TiONPs; TiO@BC

Photocatalytic C-N bond construction toward high-value nitrogenous chemicals - Li, Jie; Liu, Tengyu; Singh, Nittan; Huang, Zhuochun; Ding, Yan; Huang, Jinshu; Sudarsanam, Putla; Li, Hu (Chemical Communications, 2023)
The construction of carbon-nitrogen bonds is vital for producing versatile nitrogenous compounds for the chemical and pharmaceutical industries. Among developed synthetic approaches to nitrogenous chemicals, photocatalysis is particularly prominent and has become one of the emerging fields due to its unique advantages of eco-sustainable characteristics, efficient process integration, no need for high-pressure H2, and tunable synthesis methods for developing advanced photocatalytic materials. Here, the review focuses on potential photocatalytic protocols developed for the construction of robust carbon-nitrogen bonds in discrepant activation environments to produce high-value nitrogenous chemicals. The photocatalytic C-N bond construction strategies and involved reaction mechanisms are elucidated. This review focuses on potential photocatalytic protocols developed for the construction of robust carbon-nitrogen bonds in discrepant activation environments to produce high-value nitrogenous chemicals.

PIDA-mediated N-N bond formation to access pyrazolidine-3,5-diones: a novel process for uricosuric agents G-25671 and sulfinpyrazone - Halder, Priyanka; Mhaske, Santosh B. (Chemical Communications, 2023)
Traditionally, toxic and expensive hydrazine building blocks are required to construct pharmaceutically important pyrazolidine-3,5-diones. Herein, we have described a novel method for their synthesis based on metal-free oxidative dehydrogenative N-N bond formation by PIDA-mediated reaction of easily accessible dianilide precursors. The developed mild reaction protocol features a good functional group tolerance and scalability. The application of this method is demonstrated by offering a unique route for the synthesis of uricosuric agents G-25671 and sulfinpyrazone from inexpensive starting material aniline via smooth functionalization of the well-designed diversity-oriented cyclopropyl key intermediate.

Rh-catalyzed C-H functionalization of the (Pyrazol-5-yl)pyridine core of GBT-440 - Kalshetti, Rupali G.; Halnor, Swapnil V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2023)
The Rh-catalyzed cross dehydrogenative coupling (CDC)/alkylation of the pyrazolylpyridine unit of GBT-440 proceeded smoothly under ambient conditions and selectively on the pyrazole unit while directed by the pyridine. The scope of these reactions was established by employing simple as well as conjugated olefins for CDC and various diazo esters and the TIPS-EBX reagent for alkylation. At the outset, a focused small molecule library around the bis-heterocyclic core of GBT440 was developed via C-H functionalization.
Keywords: C-H activation; cross dehydrogenative coupling; diazo ester; GBT-440; Rh catalysis; TIPS-EBX

Solvation structure and dynamics of a small ion in an organic electrolyte - Kore, Shivshankar; Sahoo, Rudhi Ranjan; Santra, Binit; Sarkar, Archishman; Chowdhury, Tubai; Deshmukh, Samadhan H.; Hazarika, Sulagna; Chatterjee, Srijan; Bagchi, Sayan (Journal of Photochemistry and Photobiology A-Chemistry, 2023)
Organic carbonates are commonly used as electrolytes in commercial lithium-ion batteries. A detailed interpretation of the solvation structure and dynamics of the electrolyte around ions is necessary to understand the charge/discharge process in batteries. This work combines infrared absorption spectroscopy with quantum chemical calculations and molecular dynamics simulations to decipher the solvation structure of propylene carbonate, a cyclic carbonate, around the dissolved thiocyanate ion. Two dimensional infrared spectroscopy and polarization-selective pump probe spectroscopies have been utilized to extract the timescales of solvent fluctuation and the solute reorientational dynamics. The similarity in the slow timescales for the solute and the solvent dynamics signifies that similar processes control both dynamics.

Synthesis of advanced asbestos-free material using rice husk ash and marble waste for thermal insulation applications - Verma, Sarika; Bajpai, Harsh; Suresh, S.; Mili, Medha; Gupta, Ritesh Kumar; Shetty, Rohit; Kamble, Sanjay; Khan, Mohd. Akram; Hashmi, S. A. R.; Srivastava, A. K. (Biomass Conversion and Biorefinery, 2023)
The importance and utilization of advanced thermal insulating materials increase due to their broad and irreplaceable energy conservation role. This paper describes the novel way of achieving insulating material. In two waste by-products, namely rice husk ash (RHA), agriculture waste, and marble waste powder (MWP), industrial waste has been utilized to make asbestos-free advanced material for thermal insulation. A novel method for making asbestos-free advanced material for thermal insulation using RHA and marble waste's inherent characteristics has developed mechano-chemical for appropriate physico-chemical consolidation, densification, and ceramic processing route. The Si and Ca sources undergo a series of chemical transformations accompanied by mass transfer and thermal reactions during the synthesis process. The formation of this silicate compound occurs due to the presence of higher contents of CaO in marble waste powder (MWP) and silica in rice husk ash (RHA), resulting in thermal insulating characteristics in the advanced thermal insulation material (ATIM). Raman spectra of ATIM after heating at 1100 degrees C were mainly amorphous, which had a broad peak at 1072 cm(-1). This shows thermal transformation occurs after the heating process, the admixture of tailored powder, and fly ash (FA). The density of the ATIM is found to be 1150 kg/m(3). The phase transformation (glass transition temperature) was found in all the samples between 600 and 800 degrees C. The mechanical properties, namely the compressive strength and impact strength evaluation test, showed that the material meets the standard specifications for ceramic tiles. The thermal conductivity (W/mK) was calculated from different temperature 30, 50, 100,150, and 200 degrees C and found to be 0.571, 0.541, 0.516, 0.498, and 0.477, respectively. According to the test results, it is concluded that ATIM from MWP, RHA, and FA were excellent insulating components. The novel feature of the reported process is the development of non-toxic and asbestos-free thermal insulating low-cost material wherein chemically designed and mineralogically formulating desired phases lead to the homogeneous and effective thermal insulating matrix. The process is feasible, simple, cheap, and highly energy-efficient, increases production efficiency, and is environmentally friendly. The widespread use of advanced material for a broad application spectrum ranges from aerospace, automobile, electronics, transportation, construction, to other industries.
Keywords: Asbestos; Fly ash; Marble waste; Material; Rice husk ash; Thermal insulation

Thermally constructed stable Zn-doped NiCoOx-z alloy structures on stainless steel mesh for efficient hydrogen production via overall hydrazine splitting in alkaline electrolyte - Kashale, Anil Ashok; Rasal, Akash Sanjay; Hsu, Fei-Chien; Chen, ChangChun; Kulkarni, Sayali Nitin; Chang, Chun Hao; Chang, Jia-Yaw; Lai, Yuekun; Chen, I. -Wen Peter (Journal of Colloid and Interface Science, 2023)
Hydrogen has a high energy density of approximately 120 to 140 MJ kg(-1), which is very high compared to other natural energy sources. However, hydrogen generation through electrocatalytic water splitting is a high electricity consumption process due to the sluggish oxygen evolution reaction (OER). As a result, hydrogen generation through hydrazine-assisted water electrolysis has recently been intensively investigated. The hydrazine electrolysis process requires a low potential compared to the water electrolysis process. Despite this, the utilization of direct hydrazine fuel cells (DHFCs) as portable or vehicle power sources necessitates the development of inexpensive , effective anodic hydrazine oxidation catalysts. Here, we prepared oxygen-deficient zinc-doped nickel cobalt oxide (Zn-NiCoOx-z) alloy nanoarrays on stainless steel mesh (SSM) using a hydrothermal synthesis method followed by thermal treatment. Furthermore, the prepared thin films were used as electrocatalysts , the OER and hydrazine oxidation reaction (HzOR) activities were investigated in three-and two-electrode systems. In a three-electrode system, Zn-NiCoOx-z/SSM HzOR requires-0.116 V (vs RHE) potential to achieve a 50 mA cm(-2) current density, which is dramatically lower than the OER potential (1.493 V vs RHE). In a two-electrode system (Zn-NiCoOx-z/SSM(-)IIZn-NiCoOx-z/SSM(+)), the overall hydrazine splitting potential (OHzS) required to reach 50 mA cm(-2) is only 0.700 V, which is dramatically less than the required potential for overall water splitting (OWS). These excellent HzOR results are due to the binder-free oxygen-deficient Zn-NiCoOx-z/ SSM alloy nanoarray, which provides a large number of active sites and improves the wettability of cat-alysts after Zn doping. (C) 2023 Elsevier Inc. All rights reserved.
Keywords: Hydrazine Oxidation Reaction; hydrogen evolution reaction; Oxygen Evolution Reaction; Oxygen-Deficient Materials; Zinc Doping

Total and diverted total synthesis of pyrrolo-quinazolinone alkaloids and their analogues - Rasapalli, Sivappa; Huang, Yanchang; Sammeta, Vamshikrishna Reddy; Alshehry, Reem; Anver, Fazmina; Shivasankar, Krishnamoorthy; Chavan, Subash P. (ChemistrySelect, 2023)
A short and expeditious total and diverted total synthesis of luotonin, vasicinone, and their analogues has been achieved from the key tricyclic quinazolinone intermediate which was accessed from simple substituted anthranilamide obtained from the coupling of & beta;-alanate with isatoic anhydride followed by Dieckmann condensation chemistry of the resulting diester. The tricyclic ketone exhibited interesting chemical properties, e. g. keto-enol tautomerism. Friedlander condensation and Fischer-Indolization were employed for further annulations to access polycyclic alkaloids and their analogues. A short and expeditious total and diverted total synthesis of Luotonin, Vasicinone, and their analogues has been achieved from the key tricyclic quinazolinone ketone that was accessed via Dieckmann condensation chemistry of the diester which was in turn obtained from the isatoic anhydride followed by cyclodehydration. The keto-enol tautomerism of the tricyclic ketone has been studied through 1H NMR. Friedlander condensation and Fischer-Indolization were employed for further annulations on to the tricyclic ketone to yield luotonins and nor-rutaecarpines in good yields.image
Keywords: Luotonin; Quinazolinone; Rutaecarpine; Total synthesis; Vasicinone

Unlocking the potential of proton conductivity in guanidinium-based ionic covalent organic nanosheets (iCONs) through pore interior functionalization - Kumar, Sushil; Hu, Jiahui; Pandikassala, Ajmal; Kurungot, Sreekumar; Addicoat, Matthew A.; Szekely, Gyorgy (Applied Materials Today, 2023)
Recently, scientists have been exploring the incorporation of proton carriers such as water and phosphoric acid (PA) into the pores and channels of porous materials to enhance proton conduction performance. Ionic covalent organic nanosheets (iCONs) have been identified as promising functional materials due to their inbuilt ionic interfaces, which can facilitate strong interaction with counter ions present inside the pore structure and thus shorten ion transport pathways. However, there is a lack of research related to proton conductivity in iCONs loaded with PA. To address this, we prepared three functionalized guanidinium-based iCONs using a solvothermal condensation reaction between guanidinium amine (TG) and functionalized terephthaldehyde (Da, Dha, and Dma). PA was also incorporated into the iCON structure via ex situ loading to observe its effects on proton conduction performance. The results showed that both the iCONs and PA-iCONs were highly stable in water, organic solvents, acidic and basic media. Amongst these PA-iCONs, one with hydroxyl-functionalization (PA-DhaTG) displayed high proton conductivity at 90 degrees C and 95% relative humidity due to a Grotthuss mechanism for protons. These functionalized guanidinium-based iCONs could prove useful for applications in energy conversion devices.
Keywords: chemical stability; Functionalized pore interior; Guanidinium group; ionic covalent organic nanosheets; proton conductivity

Attempted synthesis of the central 2,2-disubstituted pseudoindoxyl core of Austamide via a [Au]-catalyzed nitroalkyne cycloisomerization and intramolecular [3+2]-cycloaddition - Halnor, Swapnil V.; Ramana, Chepuri V. (Tetrahedron, 2024)
Herein, we describe an Au-catalyzed cycloisomerization process of a nitroalkyne that was projected to construct the central 2,2-disubstituted pseudoindoxyl core of the natural product Austamide. Our intended strategy for forging the pseudoindoxyl core is based on the nitroalkyne cycloisomerization followed by a subsequent intramolecular [3 + 2] cycloaddition. However, the [3 + 2] cycloaddition occurred in an undesired manner, ultimately leading to a complex hexacyclic scaffold.
Keywords: Austamide; Gold catalysis; Intramolecular [3+2] cycloaddition; Nitroalkyne cycloisomerization

Biocatalysis enables the scalable conversion of biobased furans into various furfurylamines - Giri, Pritam; Lim, Seonga; Khobragade, Taresh P.; Pagar, Amol D.; Patil, Mahesh D.; Sarak, Sharad; Jeon, Hyunwoo; Joo, Sangwoo; Goh, Younghwan; Jung, Seohee; Jang, Yu-Jeong; Choi, Seung Beom; et al. (NATURE COMMUNICATIONS, 2024)
Keywords: Biomass; OMEGA-TRANSAMINASE; OXIDASE; Reductive amination; SPECIFICITY

Block copolymer self-assembly: exploitation of hydrogen bonding for nanoparticle morphology control via incorporation of triazine based comonomers by RAFT polymerization - Haque, Farah; Thompson, Steven W.; Ishizuka, Fumi; Kuchel, Rhiannon P.; Singh, Dharmendra; Sanjayan, Gangadhar J.; Zetterlund, Per B. (Small, 2024)
Synthesis of polymeric nanoparticles of controlled non-spherical morphology is of profound interest for a wide variety of potential applications. Self-assembly of amphiphilic diblock copolymers is an attractive bottom-up approach to prepare such nanoparticles. In the present work, RAFT polymerization is employed to synthesize a variety of poly(N,N-dimethylacrylamide)-b-poly[butyl acrylate-stat-GCB] copolymers, where GCB represents vinyl monomer containing triazine based Janus guanine-cytosine nucleobase motifs featuring multiple hydrogen bonding arrays. Hydrogen bonding between the hydrophobic blocks exert significant influence on the morphology of the resulting nanoparticles self-assembled in water. The Janus feature of the GCB moieties makes it possible to use a single polymer type in self-assembly, unlike previous work exploiting, e.g., thymine-containing polymer and adenine-containing polymer. Moreover, the strength of the hydrogen bonding interactions enables use of a low molar fraction of GCB units, thereby rendering it possible to use the present approach for copolymers based on common vinyl monomers for the development of advanced nanomaterials.

Breaking the inactivity of MXenes to drive Ampere-level selective oxygen evolution reaction in seawater - Gbadamasi, Sharafadeen; Loomba, Suraj; Haris, Muhammad; Khan, Muhammad Waqas; Maibam, Ashakiran; Mousavi, Seyed Mahdi; Mahmud, Sofiu; Thomsen, Lars; Tadich, Anton; BabaRao, Ravichandar; Xian, Jian; Mahmood, Nasir (MATERIALS SCIENCE & ENGINEERING R-REPORTS, 2024)
Keywords: 2D heterostructures; Metal-organic framework; Oxygen Evolution Reaction

Bridging the gap: an investigation of biosurfactants-polymer systems - Abhyankar, Isha; Hirlekar, Swarali; Prabhune, Asmita; Nisal, Anuya (Current Opinion in Colloid & Interface Science, 2024)
Biosurfactants (BSs) have been extensively researched due to their potential applications in various fields, including textiles, cosmetics, pharmaceuticals, agriculture, and oil remediation. These BSs possess a diverse range of physical, chemical, and biological properties. In recent years, researchers have combined these biosurfactants with both natural and synthetic polymers, resulting in the development of advanced material systems that exhibit a unique combination of properties. This review focuses on highlighting the recent advancements in these biosurfactant-polymer material systems and identifies existing gaps in the literature. The combination of biosurfactants with polymers has led to the formation of interpenetrated hydrogels, films, chemically modified surfaces, vesicles, functionalized nanofiber nonwoven mats, nano-formulations, and nano-assemblies. Some studies have also investigated the interactions between biosurfactants and polymer molecules. In most cases, non-specific, non-covalent interactions, such as electrostatic interactions, hydrogen bonding, and hydrophobic interactions have been found to govern the properties of these systems. Moreover, promising results have been achieved through the covalent modification of polymer surfaces, followed by functionalization using biosurfactant molecules. The literature demonstrates that these advanced materials could find applications in various fields, including drug delivery, bioremediation, biomedical materials, and as antimicrobial agents. These findings indicate the promising potential of biosurfactant-polymer systems for future advancements in these areas.

Co-incorporated N-doped micro-meso porous carbon as an electrocatalyst for oxygen reduction reaction and Zn-air battery - Priya, Vaishna K.; Kharabe, Geeta Pandurang; Barik, Sidharth; Mohamed, A. Peer; Kurungot, Sreekumar; Hareesh, Unnikrishnan Nair Saraswathy (Energy and Fuels, 2024)
Metal-organic frameworks are considered ideal precursors for the preparation of transition-metal, heteroatom-doped carbon catalysts that are perceived to be efficient electrocatalysts for energy storage devices. Herein, we demonstrate the synthesis of ZIF-67-derived Co-incorporated N-doped porous carbon catalysts supported on high surface area microporous carbon prepared from a lotus seed shell. The combination of the two carbon catalysts in different weight ratios resulted in Co-incorporated N-doped carbon sheets with tuned surface area and porosity, enabling enhanced oxygen reduction reaction (ORR) activity in an alkaline medium. The optimized carbon catalyst ZL 600 (3:1) exhibited a half-wave potential of 0.79 V vs RHE and a limiting current density of -4.38 mA cm(-2) in 0.1 M KOH solution with higher stability and methanol tolerance. The optimized sample ZL 600 (3:1) demonstrated as a cathode in a zinc-air battery exhibited an open circuit voltage of 1.29 V with a flat discharge profile at a current rate of 10 mA cm(-2). The homemade system produced a specific capacity of 610 mAh g(-1) and a peak power density of 111 mW cm(-2), comparable to the cathode made with Pt/C. The high micro-mesoporosity, pyridinic and pyrrolic nitrogen contents, as well as enriched Co-active centers protected by carbon sheets favorably contributed to the efficient ORR mechanism.

Copper-mediated [3+2] oxidative cyclization of oxime acetate and its utility in the formal synthesis of fentiazac - Jadhao, Nitin L.; Musale, Harish B.; Gajbhiye, Jayant M.; Humne, Vivek T. (Organic and biomolecular chemistry, 2024)
A new protocol for the direct synthesis of 2-aminothiazole has been developed from oxime acetate and readily available sodium thiocyanate using a copper catalyst. The present transformation has good functional group tolerance. Various thiazoles were smoothly synthesized in good to excellent yields. The applicability of the present method has been extended to the formal synthesis of the non-steroidal and anti-inflammatory drug, fentiazac via the Sandmeyer reaction and Suzuki coupling. The direct synthesis of 2-aminothiazole has been developed from oxime acetate using a copper catalyst. The applicability of the present method is used in the formal synthesis of fentiazac.
Keywords: Biological evaluation; C-H functionalization; Vinylazides

Effects of gamma irradiation on non-polar GaN films deposited on sapphire using pulsed laser deposition - Rajgoli, Tahir; Sant, Tushar; Jejurikar, Suhas M.; Hinge, Sandip; Banpurkar, Arun; Dahiwale, S. S.; Late, Datta (Applied Surface Science, 2024)
The GaN films/layers exposed to gamma-radiations is known to harvest defects and vacancies in the crystals producing donor, acceptor and recombination centers within the bandgap. Therefore it is important to investigate and study the gamma- ray irradiation effects on various physical and chemical properties of a material before any optoelectronic and/or electronic devices are being fabricated. To avoid Stark effect which is observed in most of the optoelectronic devices fabricated using GaN films grew along polar face, use of non-polar GaN films is suggested by researchers. To address such issues the article reports the investigations of physical and chemical properties of non-polar GaN films grown on polar substrate using pulsed laser deposition, which were exposed to the 60Co gamma rays varying dose values. Resistive nature against the impairment of the films caused by gamma-rays observed herewith is highly encouraging, suggesting the use of non-polar GaN films as radiations harden material suitable for fabricating new generation gamma-ray detectors. To our knowledge very limited information is available that report such investigations.
Keywords: Gallium nitride; Gamma rays; PL emission; pulsed laser deposition

Fabrication and evaluation of a spatially resolved fiber-optic probe for diffuse reflectance measurement for noninvasive diabetic foot ulcer diagnosis perspective - Kumar, Ajay; Hattale, Gangadhar; Pawar, Dnyandeo; Kanawade, Rajesh (Optical Engineering, 2024)
Timely diagnosis and monitoring of wound progression or healing are key to improving the long-term outcome of diabetic foot ulcers (DFU). Diffuse reflectance spectroscopy (DRS) has the potential to noninvasively diagnose the DFU in real time, as it detects changes in local blood volume fraction and oxygenation state level that occur when tissue becomes diseased or ulcerated. Since foot soles have a thicker epidermis and deeper blood vessels/capillaries than other parts of the body, a spatially resolved fiber-optic probe (SRFP) is needed to detect the optimal spatially resolved diffuse reflectance (SRDR) signal from the local site of the ulcer for DFU diagnosis. Therefore, herein, an SRFP consisting of a linear array of seven 400-mu m fibers with detector-source (D-S) fiber separation (rho) ranging from 0.8 to 4.8 mm was designed, fabricated, tested, and evaluated for SRDR measurement from a standard reflectance plate of barium sulfate (BaSO4) and foot sole of 27 healthy human subjects. The variation in SRDR spectra for each detector and source fiber pair measured with BaSO4 was found to be less than 1.6%. In-vivo measurements from the foot sole demonstrate that the fabricated probe has the ability to spatially resolve and distinguish the SRDR spectra from sites, namely, the fifth metatarsal, ball of great joint, calcaneum, and great toe. Experimentally and theoretically, the detector and source fiber pair of rho=1.6 and 2.4 mm were optimal for SRDR measurements from a human foot. To evaluate and validate the performance of SRFP in a context relevant to DFU diagnosis, further SRDS measurements were performed on the solid tissue phantoms that mimic the optical properties of the normal and diabetic foot sole, and their results are statistically found different. Preliminary results suggest that developed SRFP can be explored for DRS measurement from foot ulcer patients to confirm its potential clinical applicability.
Keywords: diabetic foot ulcer; diffuse reflectance spectroscopy; foot sole; spatially resolved fiber-optic probe; tissue phantom

Fuel from waste: electrosynthesizing ammonia directly from agricultural digestate through ligand isomerization - Mendhe, Rahul Mahadeo; Mondal, Ritwik; Kottaichamy, Alagar Raja; Haridas, Akshay; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thimmappa, Ravikumar; Thotiyl, Musthafa Ottakam (Green Chemistry, 2024)
We demonstrate that the catalytic metal centre for ammonia production can be selectively activated with only a slight alteration in ligand isomerization (alpha and beta isomers), making it practical and effective even for agricultural effluents. With almost 90% faradaic efficiency, the beta isomer generates approximately 0.64 mg h-1 cm-2 of ammonia. Energy-efficient ammonia recovery is made possible by the interfacial proton charge assembly that beta-isomerization creates, which attracts the reacting nitrate and repels the competing hydronium ions. With minimal energy consumption, this isomerization approach can interconvert agricultural effluents into ammonia fuel, reaching up to 84% of its theoretical yield and maintaining stability over 100 hours of continuous electrolysis. Ligand isomerization driven ammonia electrosynthesis from agricultural waste water.

Genome sequencing and protein modeling unraveled the 2AP biosynthesis in Bacillus cereus DB25 - Dhondge, Harshal V.; Barvkar, Vitthal T.; Dastager, Syed G.; Dharne, Mahesh S.; Rajput, Vinay; Pable, Anupama A.; Henry, Robert J.; Nadaf, Altafhusain B. (International Journal of Food Microbiology, 2024)
2-Acetyl-1-pyrroline (2AP) is an important and major flavor aroma compound responsible for the fragrance of basmati rice, cheese, wine, and several other food products. Biosynthesis of 2AP in aromatic rice and a few other plant species is associated with a recessive Betaine aldehyde dehydrogenase 2 (BADH2) gene. However, the literature is scant on the relationship between the functional BADH2 gene and 2AP biosynthesis in prokaryotic systems. Therefore, in the present study, we aimed to explore the functionality of the BADH2 gene for 2AP biosynthesis in 2AP synthesizing rice rhizobacterial isolate Bacillus cereus DB25 isolated from the rhizosphere of basmati rice (Oryza sativa L.). Full-length BcBADH2 sequence was obtained through whole genome sequencing (WGS) and further confirmed through traditional PCR and Sanger sequencing. Then the functionality of the BcBADH2 gene was evaluated in-silico through bioinformatics analysis and protein docking studies and further experimentally validated through enzyme assay. The sequencing and bioinformatics analysis results revealed a full-length 1485 bp BcBADH2 coding sequence without any deletion or premature stop codons. Full-length BcBADH2 was found to encode a fully functional protein of 54.08 kDa with pI of 5.22 and showed the presence of the conserved amino acids responsible for enzyme activity. The docking studies confirmed a good affinity between the protein and its substrate whereas the presence of BcBADH2 enzyme activity confirmed the functionality of BADH2 enzyme in B. cereus DB25. In conclusion, the findings of the present study suggest that B. cereus DB25 is able to synthesize 2AP despite a functional BADH2 gene and there may be a different molecular mechanism responsible for 2AP biosynthesis in bacterial systems, unlike that found in aromatic rice and other eukaryotic plant species.
Keywords: 2-Acetyl-1-pyrroline; Basmati rice flavor; Betaine aldehyde dehydrogenase 2; Protein-ligand docking; Rhizobacteria; Whole-genome sequence

Highly stereoselective diels-alder-based strategy for the synthesis of 3-epi-formicin A and 1-epi-formicin B - Khamkar, Sunil L.; Handore, Kishor L.; Shinde, Harish M.; Reddy, D. Srinivasa (Organic Letters, 2024)
The first enantioselective approach based on a highly stereoselective Diels-Alder reaction for the synthesis of 3-epi-formicin A and 1-epi-formicin B with rare N-acetylcysteamine-containing indenone thioesters is reported. The strategy utilizes a key Diels-Alder reaction to form the core hydrindane system with three contiguous stereocenters in very high levels of diastereo- and regioselectivity and one-pot oxidation/isomerization/dehydrogenation. The scope of this method was tested with different substrates to give cycloadducts in a highly diastereoselective manner.

Improved protein dynamics and hydration in the martini3 coarse-grain model - Kharche, Shalmali; Yadav, Manjul; Hande, Vrushali; Prakash, Shikha; Sengupta, Durba (Journal of Chemical Information and Modelling, 2024)
The Martini coarse-grain force-field has emerged as an important framework to probe cellular processes at experimentally relevant time- and length-scales. However, the recently developed version, the Martini3 force-field with the implemented Go model (Martini3Go), as well as previous variants of the Martini model have not been benchmarked and rigorously tested for globular proteins. In this study, we consider three globular proteins, ubiquitin, lysozyme, and cofilin, and compare protein dynamics and hydration with observables from experiments and all-atom simulations. We show that the Martini3Go model is able to accurately model the structural and dynamic features of small globular proteins. Overall, the structural integrity of the proteins is maintained, as validated by contact maps, radii of gyration (Rg), and SAXS profiles. The chemical shifts predicted from the ensemble sampled in the simulations are consistent with the experimental data. Further, a good match is observed in the protein-water interaction energetics, and the hydration levels of the residues are similar to atomistic simulations. However, the protein-water interaction dynamics is not accurately represented and appears to depend on the protein structural complexity, residue specificity, and water dynamics. Our work is a step toward testing and assessing the Martini3Go model and provides insights into future efforts to refine Martini models with improved solvation effects and better correspondence to the underlying all-atom systems.

In situ monitoring of competitive coformer exchange reaction by 1H MAS solid-state NMR - Hareendran, Chaithanya; Alsirawan, Bashir; Paradkar, Anant; Ajithkumar, T. G. (Molecualr Pharmaceutics, 2024)
In a competitive coformer exchange reaction, a recent topic of interest in pharmaceutical research, the coformer in a pharmaceutical cocrystal is exchanged with another coformer that is expected to form a cocrystal that is more stable. There will be a competition between coformers to form the most stable product through the formation of hydrogen bonds. This will cause destabilization of the pharmaceutical products during processing or storage. Therefore, it is important to develop a mechanistic understanding of this transformation by monitoring each and every step of the reaction, employing a technique such as H-1 nuclear magnetic resonance (NMR). In this study, an in situ monitoring of a coformer exchange reaction is carried out by H-1 magic angle spinning (MAS) solid-state NMR (SSNMR) at a spinning frequency of 60 kHz. The changes in caffeine maleic acid cocrystals on addition of glutaric acid and caffeine glutaric cocrystals on addition of maleic acid were monitored. In all of the reactions, it has been observed that caffeine glutaric acid Form I is formed. When glutaric acid was added to 2:1 caffeine maleic acid, the formation of metastable 1:1 caffeine glutaric acid Form I was observed at the start of the experiment, indicating that the centrifugal pressure is enough for the formation. The difference in the end product of the reactions with a similar reaction pathway of 1:1 and 2:1 reactant stoichiometry indicates that a complete replacement of maleic acid has occurred only in the 1:1 stoichiometry of the reactants. The polymorphic transition of caffeine glutaric acid Form II to Form I at higher temperatures was a crucial reason that triggered the exchange of glutaric acid with maleic acid in the reaction of caffeine glutaric acid and maleic acid. Our results are novel since the new reaction pathways in competitive coformer exchange reactions enabled understanding the remarkable role of stoichiometry, polymorphism, temperature, and centrifugal pressure.
Keywords: caffeine cocrystal; coformer exchange reaction; in situ monitoring; polymorphism; Solid-state NMR

Insights into the structure of sucralfate by advanced solid- and liquid-state NMR - Hareendran, Chaithanya; Ravindranathan, Sapna; Ajithkumar, T. G. (Molecualr Pharmaceutics, 2024)
Sucralfate, which is a sucrose octasulfate aluminum complex, is an active pharmaceutical ingredient (API) falling in the category of cytoprotective agents which are very effective for gastric and duodenal ulcers. On interaction with stomach acid, it ionizes into aluminum and sucrose octasulfate ions to form a protective layer over the ulcerated region inhibiting further attack from acid. The mechanism of action of sucralfate in the context of its structure is not well understood. Considering that at least two forms of this API are available in the market, there are no reports on the various forms of sucralfate and differences in their pharmacological action. We characterized the two forms of sucralfate using multinuclear, multidimensional solid-state NMR, and the results show significant structural differences between them arising from variation in the aluminum environment and the level of hydration. The impact of structural differences on pharmacological action was examined by studying acid-induced Al release by Al-27 liquid-state NMR. The sucralfate, European pharmaceutical standard, Form I, undergoes faster disruption in acid compared to Form II. The difference is explained on the basis of structural differences in the two forms which gives significant insights into the action of sucralfate in relation to its structure.
Keywords: (27)AlMQMAS; H-1-H-1 DQSQ; pharmacological action; solid-stateNMR; sucralfate

Iron salicylaldehydate conjugated metal-organic framework for quasi solid-state supercapacitor - Mohammed, Abdul Khayum; Pandikassala, Ajmal; Sanchez, Pilar Pena; Gaber, Safa Abdullah; Canossa, Stefano; Kurian, Maria; Xavier, Gigi; He, Yao; Gandara, Felipe; Kurungot, Sreekumar; Shetty, Dinesh (CHEMICAL ENGINEERING JOURNAL, 2024)
Keywords: Carbon; conductivity; ELECTROLYTE CONCENTRATION; performance; ROBUST

Kinetic H2S/CO2 selectivity in an exceptionally sterically hindered amine membrane - Rao, Shraavya; Deng, Xuepeng; Zou, Changlong; Prasad, Babul; Han, Yang; Lin, Li-Chiang; Ho, W. S. Winston (JOURNAL OF MATERIALS CHEMISTRY A, 2024)
Keywords: Absorption; COMPOSITE MEMBRANES; GAS STREAMS; H2S; Thin-Film

Lead-free Cs2AgBiCl6 double perovskite: experimental and theoretical insights into the self-trapping for optoelectronic applications - Rahane, Swati N.; Rahane, Ganesh K.; Mandal, Animesh; Jadhav, Yogesh; Godha, Akshat; Rokade, Avinash; Shah, Shruti; Hase, Yogesh; Waghmare, Ashish; Saykar, Nilesh G.; Roy, Anurag; Salgaonkar, Kranti N.; et al. (ACS Physical Chemistry Au, 2024)
Lead-free double perovskites (DPs) will emerge as viable and environmentally safe substitutes for Pb-halide perovskites, demonstrating stability and nontoxicity if their optoelectronic property is greatly improved. Doping has been experimentally validated as a powerful tool for enhancing optoelectronic properties and concurrently reducing the defect state density in DP materials. Fundamental understanding of the optical properties of DPs, particularly the self-trapped exciton (STEs) dynamics, plays a critical role in a range of optoelectronic applications. Our study investigates how Fe doping influences the structural and optical properties of Cs2AgBiCl6 DPs by understanding their STEs dynamics, which is currently lacking in the literature. A combined experimental–computational approach is employed to investigate the optoelectronic properties of pure and doped Cs2AgBiCl6 (Fe–Cs2AgBiCl6) perovskites. Successful incorporation of Fe3+ ions is confirmed by X-ray diffraction and Raman spectroscopy. Moreover, the Fe–Cs2AgBiCl6 DPs exhibit strong absorption from below 400 nm up to 700 nm, indicating sub-band gap state transitions originating from surface defects. Photoluminescence (PL) analysis demonstrates a significant enhancement in the PL intensity, attributed to an increased radiative recombination rate and higher STE density. The radiative kinetics and average lifetime are investigated by the time-resolved PL (TRPL) method; in addition, temperature-dependent PL measurements provide valuable insights into activation energy and exciton–phonon coupling strength. Our findings will not only deepen our understanding of charge carrier dynamics associated with STEs but also pave the way for the design of some promising perovskite materials for use in optoelectronics and photocatalysis.

Mitochondrial resilience and antioxidant defence against HIV-1: unveiling the power of Asparagus racemosus extracts and Shatavarin IV - Jadaun, Pratiksha; Harshithkumar, R.; Seniya, Chandrabhan; Gaikwad, Shraddha Y.; Bhoite, Shubhangi P.; Chandane-Tak, Madhuri; Borse, Swapnil; Chavan-Gautam, Preeti; Tillu, Girish; Mukherjee, Anupam (FRONTIERS IN MICROBIOLOGY, 2024)
Keywords: IN-SILICO; INHIBIT HIV-1

Morphology tuning via linker modulation: metal-free covalent organic nanostructures with exceptional chemical stability for electrocatalytic water splitting - Karak, Shayan; Koner, Kalipada; Karmakar, Arun; Mohata, Shibani; Nishiyama, Yusuke; Duong, Nghia Tuan; Thomas, Neethu; Ajithkumar, Thalasseril Govindankuttykaimal; Hossain, Munshi Sahid; Bandyopadhyay, Subhajit; Kundu, Subrata; Banerjee, Rahul (Advanced Materials, 2024)
The development of synthetic routes for the formation of robust porous organic polymers (POPs) with well-defined nanoscale morphology is fundamentally significant for their practical applications. The thermodynamic characteristics that arise from reversible covalent bonding impart intrinsic chemical instability in the polymers, thereby impeding their overall potential. Herein, a unique strategy is reported to overcome the stability issue by designing robust imidazole-linked POPs via tandem reversible/irreversible bond formation. Incorporating inherent rigidity into the secondary building units leads to robust microporous polymeric nanostructures with hollow-spherical morphologies. An in-depth analysis by extensive solid-state NMR (1D and 2D) study on H-1, C-13, and N-14 nuclei elucidates the bonding and reveals the high purity of the newly designed imidazole-based POPs. The nitrogen-rich polymeric nanostructures are further used as metal-free electrocatalysts for water splitting. In particular, the rigid POPs show excellent catalytic activity toward the oxygen evolution reaction (OER) with long-term durability. Among them, the most efficient OER electrocatalyst (TAT-TFBE) requires 314 mV of overpotential to drive 10 mA cm(-2) current density, demonstrating its superiority over state-of-the-art catalysts (RuO2 and IrO2).
Keywords: bi-functional electrocatalysts; chemically robust; hollow-spherical morphologies; imidazole-linked; inherent rigidity; metal-free; water splitting

Normal and diabetic foot sole skin mimicking tissue phantom fulfillment for spectroscopic-based DFU diagnostics perspective - Kumar, Ajay; Hattale, Gangadhar; Hinge, Sarika; Kulkarni, Gauri; Late, Dattatray J.; Kanawade, Rajesh (AIP ADVANCES, 2024)
Keywords: OPTICAL-PROPERTIES; STATE

One-pot production of liquid hydrocarbons by catalytic hydrodeoxygenation of lignocellulosic biomass using nickel loaded on zeolite-based supports - Siakpebru, Odiri K.; Uchagawkar, Anoop; Gurrala, Lakshmiprasad; Bartlett, Jared; Adamson, Piersen; Gorschak, Nicholas; Hassiba, Adam; Niphadkar, Prashant; Bokade, Vijay; Morais, Ana Rita C. (Energy & Fuels, 2024)
The synthesis of liquid hydrocarbons from lignocellulosic biomass has been achieved with notable success. However, these technologies often require multistep approaches and are energy intensive. Thus, there is a considerable economic and environmental benefit of process intensification by the synthesis of liquid hydrocarbons in a one-pot process. For the first time, we report direct conversion of raw poplar into liquid alkanes and aromatics (carbon yield of 15.6 +/- 0.6 wt %) with high selectivity toward C-7-C15 cycloalkanes (7.8 +/- 0.1 wt %) and low level of oxygenated compounds (<2.0 wt %) at 270 degrees C and 3 MPa initial H(2 )pressure for 6 h using 10% Ni/H-beta zeolite as a catalyst and cyclohexane as a solvent. The effect of temperature (250-270 degrees C), Ni loading (0-10%), and type of zeolite support (H-beta, ZSM-5, and USY) on process performance was also investigated. In addition, the 10% Ni/H-beta catalyst showed recyclability over two reactions, with a 17.6% decrease in liquid hydrocarbon yield after the first reaction. This approach has the potential to simplify the synthesis of liquid fuels from lignocellulosic biomass.

Photocatalytic CO2 reduction to syngas using nickel phosphide-loaded CdS under visible light irradiation - Yadav, Poonam; Kumar, Santosh; Velankanni, Nandhakumar; Kuehne, Thomas D.; Gosavi, Suresh; Raghupathy, Ramya Kormath Madam; Bhosale, Reshma; Held, Georg; Shelke, Manjusha; Ogale, Satishchandra (Journal of Physics-Energy, 2024)
Photocatalytic CO2 reduction is a sustainable pathway to produce syngas (H-2 + CO), which is a key feedstock for the production of several important liquid fuels on the industrial scale. However, achieving an appropriate tunable ratio of H-2:CO in syngas for commercial purposes is a challenging task. In this work, we present a low-cost and non-noble metal, phosphide-based co-catalyst-Ni2P-loaded cadmium sulfide (CdS) photocatalyst system, for photocatalytic CO2 reduction. As a co-catalyst, Ni2P fosters an efficient charge separation of photoexcited charges generated in the CdS production of syngas. In total, 3 wt.% Ni2P/CdS exhibited exceptional performance of 50.6 mu mol g(-1) h(-1) in the CO evolution rate and 115 mu mol g(-1) h(-1) in the H-2 evolution rate, with a syngas composition varying from 2 to 4 in the H-2:CO ratio. Furthermore, first-principles density functional theory calculations were performed to study the surface energetics of the catalyst system and the results are found to be consistent with our experimental findings. Indeed, they establish that the composite favors CO2 photoreduction into syngas more efficiently than pure surfaces.
Keywords: CdS; CO2 reduction; Photocatalysis; Syngas; transition metal phosphides

Rational design of zero-dimensional manganese(II) halide hybrids with suppressed melting temperatures - Singh, Shivangi; Marayathungal, Jumana Hasin; Das, Deep Kumar; Khan, Akram Aadil; Bakthavatsalam, Rangarajan; Hathwar, Venkatesha R.; Kundu, Janardan (JOURNAL OF PHYSICAL CHEMISTRY C, 2024)
Keywords: ORGANIC-INORGANIC PEROVSKITES; TRANSITION

Solid-state NMR method for characterization of pharmaceutical eutectics - Hareendran, Chaithanya; Shaligram, Parth S.; Gonnade, Rajesh; Ajithkumar, T. G. (Physical Chemistry Chemical Physics, 2024)
Pharmaceutical eutectics are extremely useful for designing formulations, and currently, there are no techniques other than differential scanning calorimetry (DSC) that can confirm their formation. In this study, we demonstrate that 1H fast magic angle spinning (MAS) solid-state NMR (SSNMR) experiments can confirm the formation of eutectics by detecting their intermolecular hydrogen bonding interactions. 2D 1H-1H double quantum single quantum (DQSQ) correlation SSNMR experiment is demonstrated which can confirm the formation of pharmaceutical eutectics for which there are no techniques other than differential scanning calorimetry (DSC).

Steroidal scaffold decorations in Solanum alkaloid biosynthesis - Lucier, Rosalind; Kamileen, Mohamed O.; Nakamura, Yoko; Serediuk, Sofiia; Barbole, Ranjit; Wurlitzer, Jens; Kunert, Maritta; Heinicke, Sarah; O'Connor, Sarah E.; Sonawane, Prashant D. (Molecular Plant, 2024)
Steroidal glycoalkaloids (SGAs) are specialized metabolites produced by hundreds of Solanum species, including important vegetable crops such as tomato, potato, and eggplant. Although it has been known that SGAs play important roles in defense in plants and ``anti-nutritional''effects (e.g., toxicity and bitterness) to humans, many of these molecules have documented anti-cancer, anti-microbial, antiinflammatory, anti-viral, and anti-pyretic activities. Among these, a-solasonine and a-solamargine isolated from black nightshade (Solanum nigrum) are reported to have potent anti-tumor, anti-proliferative, and anti-inflammatory activities. Notably, a-solasonine and a-solamargine, along with the core steroidal aglycone solasodine, are the most widespread SGAs produced among the Solanum plants. However, it is still unknown how plants synthesize these bioactive steroidal molecules. Through comparative metabolomictranscriptome-guided approach, biosynthetic logic, combinatorial expression in Nicotiana benthamiana, and functional recombinant enzyme assays, here we report the discovery of 12 enzymes from S. nigrum that converts the starting cholesterol precursor to solasodine aglycone, and the downstream a-solasonine, a-solamargine, and malonyl-solamargine SGA products. We further identified six enzymes from cultivated eggplant that catalyze the production of a-solasonine, a-solamargine, and malonyl-solamargine SGAs from solasodine aglycone via glycosylation and atypical malonylation decorations. Our work provides the gene tool box and platform for engineering the production of high-value, steroidal bioactive molecules in heterologous hosts using synthetic biology.
Keywords: a-solamargine; Biosynthetic pathway; malonyl-solamargine; Solanum; Specialized metabolites; steroidal glycoalkaloids

Synergistic humidity-responsive mechanical motion and proton conductivity in a cationic covalent organic framework - Das, Gobinda; Shinde, Dhanraj B.; Melapurakkal, Amrutha; Shelke, V, Manjusha; Garai, Bikash; Bazin, Philippe; Blal, Abdelhafid Ait; Benyettou, Farah; Prakasam, Thirumurugan; Halim, Rasha Abdul; Ibrahim, Fayrouzabou; Sharma, Sudhir Kumar; et al. (CHEM, 2024)
Keywords: ACTUATORS; Crystalline; DRIVEN; SOFT

Synthesis of Hofmann-based metal-organic frameworks incorporating a bis-pyrazole linker for various gas separations - Matthews, Brooke L.; Harvey-Reid, Nathan C.; Jangodaz, Elnaz; Scott, Victoria-Jayne; Polson, Matthew I. J.; Maibam, Ashakiran; BabaRao, Ravichandar; Telfer, Shane G.; Kruger, Paul E. (JOURNAL OF MATERIALS CHEMISTRY A, 2024)
Keywords: acetylene; C2H2/CH4; Ni; Purification; SPIN-CROSSOVER BEHAVIOR

Synthesis of tetracyclic benzoxazolo-indol-3-ones from isatogens and arynes through a [3+2]-cycloaddition and skeletal reorganization - Halnor, Swapnil V.; Singh, Maneesha; Dhote, Pawan S.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2024)
The construction of an unprecedented tetracyclic benzoxazolo-indol-3-one scaffold has been executed through the [3 + 2]-cycloaddition of isatogens with arynes. The initially formed benzisoxazolo-indol-3-one intermediate undergoes a skeletal reorganization through a 1,3-sigmatropic shift/retro-Mannich reaction with the net formation of one C-N and two C-O bonds. The Lewis acid-catalyzed allylation of some of the resulting benzoxazolo-indol-3-ones resulted in oxazepino-indolones with promising photophysical properties.

Temperature-controlled hydrothermal synthesis of α-MnO2 nanorods for catalytic oxidation of cyclohexanone - Jha, Ratnesh Kumar; Manikandan, Marimuthu; Prabu, Marimuthu; Vineeth, Nidhi R.; Dharmalingam, Praveen; Archana, Ramakrishnan; Harsha, Murudappa; Shankar, Sonu Ram; Bhatte, Kushal; Raja, Thirumalaiswamy (CHEMPLUSCHEM, 2024)
Keywords: Adipic Acid; conversion; MANGANESE OXIDES

Unravelling the prebiotic origins of the simplest α-ketoacids in cometary ices: a computational investigation - Dash, Soumya Ranjan; Pandya, Rinu; Singh, Geetika; Sharma, Himanshu; Das, Tamal; Haldar, Hritwik; Hotha, Srinivas; Vanka, Kumar (CHEMICAL COMMUNICATIONS, 2024)
Keywords: GLYOXYLATE; Hydrocarbons; Metabolism; Precursors

Water-chain mediated proton conductivity in mechanically flexible redox-active organic single crystals - Hossain, Munshi Sahid; Ghosh, Meena; Mondal, Amit; Ajmal, P.; Saha, Monochura; Reddy, C. Malla; Kurungot, Sreekumar; Bandyopadhyay, Subhajit (Journal of Materials Chemistry A, 2024)
Investigating electrochemical features of proton-conducting organic crystalline materials is relevant in developing efficient energy storage and conversion devices. However, the poor structural flexibility of the crystalline materials at the molecular level often impedes hydrogen bond reorganization of the proton carriers during proton migration, ultimately leading to low ionic conductivity. Here, we report crystals of azobenzene, functionalized with dipicolylamine at both ends (Azo-DPA), which contain an extended hydrogen-bonding network with water molecules in its structure. Interestingly, the crystals display remarkable mechanical flexibility explicitly probed by the nanoindentation technique. The mechanically flexible neutral organic crystals devoid of any acidic moieties (-COOH, -PO3H2, etc.) within the system, exhibit promising proton conductivity (1.63 x 10-4 S cm-1 at 30 degrees C under 95% relative humidity) which is almost 100 times better compared to the neutral organic systems reported to date. Mechanically flexible redox-active crystalline organic material (Azo-DPA) capable of impressive proton conduction was employed as an electrode material for the first time in an aqueous battery containing Zn2+ ions. The experimental and theoretical studies on the charge storage mechanism revealed the redox activity of the azo (-N 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 N-) centers involving reversible insertion/extraction of protons and Zn2+ ions. Ultimately, the electrode displayed a specific capacity similar to 49 mA h g-1 with almost 100% retention after 1400 cycles, encouraging the scope of redox-active organic crystalline materials for energy storage applications. Investigating the electrochemical features of proton-conducting flexible organic crystalline materials is crucial for the development of efficient energy storage and conversion devices.

Anionic 5-endo-dig cyclizations: an experimental investigation of in-plane aromaticity involving a non-enolate carbanion nucleophile - Nugent, Kristina M.; Hintze, Silas Q.; Maity, Pradip; Lepore, Salvatore D. (Organic Chemistry Frontiers, 2025)
Cyclitive additions of aliphatic carbanions to non-electrophilic carbon-carbon triple bonds under mild, transition-metal-free conditions are described for the first time. These results confirm theoretical models that invoke in-plane aromaticity to predict the favorability of 5-endo-dig reactions in these systems. In contrast to related Conia-ene cyclizations (5-enolexo-endo-dig), our results generally led to cyclic and allene products in near parity ratios across a broad range of substrates, suggesting that cyclization may proceed via an early ambimodal transition state. Experimental results are presented with a view to refining existing mechanistic models for this growing class of alkyne reactions.

Atomic Layer Deposition Grown Titania Phases (TiO2, TiO, Ti2O) and its Influence on Water Splitting Electrocatalysis - Swaminathan, Jayashree; Palani, Parthiban; Salpekar, Devashish; Hernandez, Francisco Carlos Robles; Ashokkumar, Meiyazhagan; Ajayan, Pulickel M. (Advanced Sustainable Systems, 2025)
The systematic engineering of atoms and the precise tuning of their arrangement can unlock a range of hidden yet remarkable properties of materials. In this study, different phases of titanium oxide, including TiO2, TiO, and Ti2O, are developed using the Atomic Layer Deposition (ALD) technique. Notably, a novel TiO(2 )electride with a pbcn space group is identified, and variations in stoichiometries, such as Ti1.80O, Ti2.05O, and Ti2.30O, are observed through Rietveld analysis of the corresponding X-ray Diffraction (XRD) data. High-resolution transmission electron microscopy (HRTEM) imaging further revealed line defects such as stacking faults and edge dislocations in Ti2O. The interplay of stoichiometric defects in Ti2O electrides leads to tunable electrocatalytic behavior, enabling transitions from oxygen evolution to hydrogen evolution reactions. Importantly, using Density functional theory (DFT), Paterson analysis, and Fourier electron density mapping, the exceptional metallic properties of Ti2O are rationalized as arising from its unique spatial electron density distribution. Overall, this work underscores the significance of atomic-level structure engineering and opens the door to a new class of titanium oxide catalysts for electrochemical water splitting.
Keywords: atomic layer deposition; defect engineering; defect-rich titania; Electrocatalytic water splitting; Ti2O electrides

Bio-based poly(isobornyl acrylate)-b-(citronellyl methacrylate) block copolymers by PET-RAFT polymerization: thiol-ene modification and adhesion studies - Hetkale, Pragati M.; Purohit, Poorvi M.; Nair, Kiran Sukumaran; Ambade, Ashootosh V. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2025)
In this study, poly(isobornyl acrylate)-b-poly(citronellyl methacrylate) (PIBA-b-PCMA) block copolymers were synthesized with controlled molecular weights and low dispersity using photoinduced electron transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization of isobornyl acrylate (IBA) and citronellyl methacrylate (CMA), both terpene-derived monomers. A series of block copolymers was obtained by varying the chain length of PCMA block. Kinetics study of the polymerization of IBA and CMA using 4-cyano-(((dodecylthio)carbonothioyl)thio)pentanoic acid (CDTPA) as chain transfer agent showed a linear plot of ln[M]0/[M]t vs time indicating first order reaction. Distinct glass transition temperatures were observed for the individual blocks and enhanced thermal stability was seen with increasing PCMA content. Post-polymerization modification of the polymer was demonstrated using thiol-ene reaction with the vinyl group in the pendent citronellyl moiety. Adhesion performance, evaluated through lap shear test on aluminum substrates, showed that the block copolymers achieved peak shear strengths of 1.74 MPa at a 38:62 PIBA:PCMA mole ratio.
Keywords: adhesion strength; Bio-based polymers; block copolymers; PET-RAFT polymerization; Thiol-ene reaction

Carbon capture from flue gases using an integrated membrane skid - Yang, Yutong; Han, Yang; Prasad, Babul; Pang, Ruizhi; Zou, Changlong; Ho, W. S. Winston (Journal of Membrane Science, 2025)
A prototype spiral-wound (SW) membrane module with a commercial-size diameter of 8 `' and a membrane area of 35 m(2) was fabricated using a new thin-film-composite facilitated transport membrane (FTM) scaled up to 21 `' in width by a continuous roll-to-roll coating process. This SW module was tested with an actual coal flue gas at the Center for Applied Energy Research (CAER) at the University of Kentucky, which exhibited an average CO2 permeance of 4269 GPU with a CO2/N-2 selectivity of 165 and remained stable for 100 h. The permeance and selectivity results are consistent with those determined from lab and scale-up flat-sheet samples. An integrated membrane skid was then constructed, where 2 SW membrane modules were arranged to form an enriching cascade. The 8 `'-diameter prototype SW module previously tested at CAER was installed as the primary CO2 capture stage, while a smaller SW module (5 `' diameter and 12 m(2) membrane area) was used to further enrich the CO2 to >95% purity. By using a simulated coal flue gas (13% CO2), the skid was operated at steady-state for 800 h with 91.0% of the CO2 removed from the flue gas, delivering 1.33 tonne/day CO2 product at 95.5% dry purity. The bench skid was then installed at the National Carbon Capture Center (NCCC), Wilsonville, AL and tested with an actual natural gas (NG) flue gas (8.6% CO2). 90-99% CO2 capture degrees were demonstrated during the parametric testing, and the skid was operated at steady state for 500 h cumulatively with 91.0% CO2 capture and >95% CO2 purity. A simulated natural gas combined cycle (NGCC) flue gas (4.3% CO2) slipstream was further provided by diluting the NG flue gas with air, and 90-99% CO2 capture degrees were also achieved with dry CO2 purities all above 95%. All these capture degrees and CO2 purities were in good agreement with their model predictions.
Keywords: Actual flue gas; carbon capture; Field trial; Integrated membrane skid; Membrane module

Ce[N(SiMe3)2]3(THF)3-catal yzed hydroboration of CO2, esters and epoxides with pinacolborane: selective synthesis of methanol in multigram scale - Hossain, Md Jabed; Shah, Brij Kumar; Dash, Soumya Ranjan; Vanka, Kumar; Khan, Shabana (Chemistry-A European Journal, 2025)
In this work, we have reduced CO2 with HBpin to afford borylated methanol product selectively in similar to 99 % yield using Ce[N(SiMe3)(2)](3)(THF)(3) as a catalyst. This led to multigram scale isolation of methanol obtained from CO2 reduction via the hydrolysis of borylated methanol, this establishes the potential of Ce[N(SiMe3)(2)](3)(THF)(3) as an efficient homogeneous catalyst for the bulk scale methanol synthesis. A practical application of this catalytic system was also shown by reducing CO2-containing motorbike exhaust efficiently and selectively. Further, C-O bond activation of esters and epoxides using HBpin and 1-2 mol % of Ce[N(SiMe3)(2)](3)(THF)(3) at 60 degrees C afforded the borylated alcohols in good to excellent yields, which can easily be hydrolysed to the eco-friendly corresponding alcohol. The stoichiometric experiments were performed to prove the formation of in-situ generated cerium hydride [Ce]-H as an active catalyst.
Keywords: Cerium; CO2 reduction; Epoxide; Ester; Hydroboration; Lanthanides

Diastereoselective synthesis of cyclic and spirocyclic quaternary carbons via iron-catalyzed ring contraction of cyclic ketones: a formal synthesis of perhydrohistrionicotoxin - Survase, Vijayanand U.; Rokade, Avinash D.; Handore, Kishor L. (Organic Letters, 2025)
The iron-catalyzed hydrogen atom transfer (HAT)-initiated Dowd-Beckwith rearrangement presents a new approach for synthesizing cyclic and spirocyclic quaternary carbons from readily available beta-keto esters and cyclic diketones with high yields. This reaction proceeds in a stereocontrolled manner, enabling the formation of synthetically valuable cyclic ketones with two contiguous stereocenters, including quaternary centers. This transformation introduces an innovative bond disconnection strategy for ring-contraction reactions. Additionally, a short formal synthesis of perhydrohistrionicotoxin was efficiently achieved using this methodology.

Dual agonist/antagonist modulation of α9-containing nicotinic acetylcholine receptors by 2-ammoniumethyl ethers of stilbenol and stilbenol analogues - Giraudo, Alessandro; Tae, Han-Shen; Hung, Andrew; Richter, Katrin; Shivankar, Bhavana; Armano, Edoardo; Grau, Veronika; Pallavicini, Marco; Adams, David J.; Bolchi, Cristiano (Journal of Medicinal Chemistry, 2025)
2-(Cyclohexyldimethylammoniumethyl)ether of 4-stilbenol (2), and its styryl-modified analogues 21 and 22, were identified as lead compounds from a series targeting human alpha 9 alpha 10, alpha 9, and alpha 7 nicotinic acetylcholine receptors (nAChRs). Compounds 2 and 21 exhibited potent, and subtype-selective modulation of alpha 9-containing receptors, with low nanomolar IC50 values and dual agonist/antagonist activity in a concentration-dependent manner. In contrast, compound 22 acted as a selective, pure antagonist. Molecular dynamics (MD) simulations of compound 21 supported a concentration-dependent allosteric mechanism, with orthosteric binding at low concentrations and vestibular site interaction at higher levels. In a human monocytic cell line, all three compounds inhibited ATP-induced IL-1 beta release at nanomolar concentrations. These findings identify alpha 9 alpha 10-selective ligands as promising scaffolds for the development of nonopioid analgesics and immunomodulators, with favorable selectivity over alpha 7 nAChRs to minimize CNS-related side effects.

Dynamic structure of the lipid bilayer and its modulation by small molecules - Sengupta, Durba; Huster, Daniel (Journal of Physical Chemistry B, 2025)

Efficient synthesis of functionalized alkylidenephthalides, butenolides, pyranones, and isocoumarins via I2-PPh3: synthesis of Thunberginols A and F - Abhang, Rohitkumar V.; Bhagwat, Prathamesh N.; Handore, Kishor L. (Organic & Biomolecular Chemistry, 2025)
A simple and efficient synthesis of functionalized alkylidenephthalides, butenolides, pyranones, and isocoumarins was achieved using I2-PPh3-Et3N reagent combination. The products obtained through this method act as versatile components in organic synthesis, enabling further modifications of functional groups. This method exhibits a wide substrate scope, employs straightforward and cost-effective reagents, eliminates the need for acidic, carbodiimide or other coupling agents, and operates at ambient temperature. Moreover, this methodology has been successfully applied to the synthesis of two natural products, Thunberginols A and F.

Europium oxide on carbon nitride for electrocatalytic glycerol oxidation coupled with hydrogen evolution reaction - Jana, Jayasmita; Sharma, Tata Sanjay Kanna; Ghanem, Mohamed A.; Choi, Won Mook; Gopinath, Chinnakonda S.; Hur, Seung Hyun (Separation and Purification Technology, 2025)
{The integration of the electrochemical glycerol oxidation reaction (GOR) with the hydrogen evolution reaction (HER) has emerged as a promising alternative to the sluggish oxygen evolution reaction (OER) in water splitting toward the development of renewable and clean energy sources. However, suitable electrodes that facilitate redox kinetics while increasing the selectivity of the desired product(s) are still required. Herein, a series of europium oxide (Eu2O3) anchored on graphitic carbon nitride (g-CN) nanoaggregates (g-CNEux
Keywords: carbon support; electrocatalysis; Glycerol; HER; Rare earth metal

Extraction of highly crystalline and thermally stable cellulose nanofiber from Heliconia psittacorum L.f. leaves - Paul, Sharon; Joseph, Anto; Hridhya, P. D.; Badawi, Michael; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Asrofi, Mochamad; Dominic, C. D. Midhun (International Journal of Biological Macromolecules, 2025)
Extracting cellulose nanofibers (CNF) from agro-waste is one of the promising and practical ways to develop sustainable nanocomposites. In this study, cellulose nanofibers were extracted from the leaves of Heliconia psittacorum for the first time. The combination of oxalic acid hydrolysis (5 wt%) and steam explosion was used for the isolation of CNF from the leaves of Heliconia psittacorum. The structural and chemical features of the prepared CNF were analyzed using various techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Solid state 13C Nuclear Magnetic Resonance Spectroscopy (13C NMR), Scanning Electron Microscopy (SEM), Energy Dispersive X ray analysis (EDX), Transmission electron Microscopy (TEM), X-Ray Diffraction (XRD) and Thermogravimetric analysis (TGA). TEM micrographs reported 15 to 40 nm diameter for the nanofibers synthesized. XRD analysis reported 91 % crystallinity index for CNF, whereas that of the untreated sample was 76 %. The maximum degradation of the CNF is reported at 355 degrees C, exceeds the untreated sample (316 degrees C). The tensile strength of the CNF derived paper was found to be 23 MPa. The recovered nanocellulose can be further utilized for various applications such as the automobile industry for developing lightweight parts, biosensors, super capacitors, absorption of greenhouse gases, wastewater treatment, and packaging applications.
Keywords: biomass valorization; Nanocellulose; Waste to resource

Facet dependence for solvent-modulated proton-coupled electron transfer in furfural acetalization on Pd nanostructures - Porwal, Govind; Dandekar, Pallavi; Gorai, Twinkle; Khan, Tuhin Suvra; Haider, M. Ali; Gupta, Shelaka; Vinod, C. P. (Chemical Engineering Journal, 2025)
Furfural dialkyl acetals prepared via acetalization reaction of furfural and alcohols are promising biofuels. Using defined experiments and density functional theory (DFT) simulations, the structure-dependent activity and selectivity for furfural acetalization reaction in the presence of alcohols (methanol, ethanol, propanol and butanol) as solvents was studied over well-defined supported Pd nanostructures (octahedra (111), cubes (100) and spheres (both (111) and (100)). Pd cubes supported over TiO2 in the presence of ethanol as a solvent (at 303 K and balloon pressure H-2) exhibited 78 % conversion and 100 % selectivity for furfural diethyl acetal product in a short time (similar to 180 min). In contrast, Pd octahedra (111) and Pd spheres showed low conversions (18 % and 6 %) at the same reaction conditions. Interestingly, when used as a solvent, methanol showed the highest conversion (90 %) and selectivity (100 %) for furfural acetalization over Pd cubes. DFT simulations provided mechanistic insight into the reactivity of the two different Pd facets (111) and (100) in the presence of alcohol molecules towards furfural acetalization reaction. A three-step reaction mechanism was proposed for furfural acetalization with alcohols: (i) alcohol hydroxyl-dehydrogenation (ii) hydrogenation of furfural carbonyl oxygen, and (iii) formation of hemiacetal product. For all three steps, Pd (100) exhibited low activation barriers (51.6, 26.7 and 76.2 kJ/mol) compared to Pd (111) surface (78.6, 35.8 and 92.2 kJ/mol) in the presence of ethanol. The activation barriers for the above steps were further reduced to 47.8, 23.9 and 64.6 kJ/mol on Pd (100) in the presence of methanol, explaining the experimental high reactivity aided by methanol. DFT calculations elucidated the role of the hydrogen bonding network between the solvent molecules and adsorbate, enabling proton-coupled electron transfer for accelerated reactions.
Keywords: Acetalization; DFT; facet-dependent reactivity; furfural; Furfural dialkyl acetals; solvent effect

Gold nanorods (GNRs): a golden nano compass to navigate breast cancer by multimodal imaging approaches - Varma, Sanjana; Bamb, Aagam Lalit; Haldar, Niladri; Gajbhiye, Virendra; Amalnerkar, Dinesh; Chaudhari, Bhushan Pradosh (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2025)
The ongoing rise in the incidences of breast cancer cases has concerned medical and scientific personnel around the world. Adequate treatment of cancer predominantly relies on the pertinent diagnosis of the type of cancer as well as other molecular and cellular details at the initial stage only. Surprisingly, up till now, there is no single, self-reliant imaging modality that helps to systematically find out the anatomical and functional events taking place inside the body. This resulted in the advent of the multimodal imaging concept, which encompasses the integration of complementary imaging modalities by designing multimodal imaging probes. Gold nanorods (GNRs) are extremely popular and effective nanoparticles for multimodal bioimaging due to their unique properties. Researchers have designed varieties of stable and biocompatible GNR-based probes for targeted and nontargeted multimodal imaging of breast cancer. However, there is a lack of investigations on the in vivo fate and the toxicity of GNRs. Thus, their preclinical to clinical translation can be attained by comprehensively determining the in vivo fate and toxicity of GNRs. The review provides details about the GNRs-based nanoprobes fabricated so far for breast cancer imaging, which, by consequent studies, can be taken up to clinical usage.
Keywords: Breast cancer; Gold nanorods; imaging probes; Multimodal Imaging

Heteroatom-synergistic effect on anchoring polysulfides in chalcone-linked nanographene covalent organic frameworks for high-performance Li―S batteries - Ranjeesh, Kayaramkodath Chandran; Javaregowda, Bharathkumar H.; Gaber, Safa; Bhauriyal, Preeti; Kumar, Sushil; Skorjanc, Tina; Finsgar, Matjaz; Heine, Thomas; Krishnamoorthy, Kothandam; Shetty, Dinesh (Advanced Science, 2025)
Lithium-sulfur (Li & horbar;S) batteries are an attractive option for future energy storage devices because they offer higher theoretical specific capacity, energy density, and cost-effectiveness than commercial lithium-ion batteries. However, the practical applications of Li & horbar;S batteries are significantly limited by the shuttle effect caused by intermediate lithium polysulfides (LiPSs) and slow redox kinetics. In this study, the molecular engineering of chalcone-linked, sp(2)-bonded nanographene-type covalent organic frameworks (COFs) as sulfur hosts is reported to enhance interactions with LiPSs, thereby effectively suppressing the shuttle effect. The developed sulfur-hosting cathode material demonstrated outstanding battery performance, surpassing most reported materials by achieving a specific capacity of 1228 mA h g(-1) at 0.5C, with 80% retention after 500 cycles and an average Coulombic Efficiency (C.E.) of 99%. Additionally, the mechanisms of sulfur immobilization, the subsequent conversion into lithium polysulfides (LiPSs), and their binding energies with COFs are investigated using density functional theory (DFT) calculations. These findings offer valuable insights into the structure-property relationships essential for developing more efficient sulfur-hosting cathodes.
Keywords: anion-pi interaction; covalent organic frameworks; lithium-sulfur battery; nanographene; polysulfide shuttle

Heteropolyacid-assisted efficient one-pot synthesis of ethyl levulinate from biorenewable feedstocks - Jagannivasan, Gopika; Haridas, Suja; Marimuthu, Banu; Mukundan, Swathi (Energy & Fuels, 2025)
Amid rising environmental concerns over fossil fuel dependence, biomass-derived alkyl levulinates, particularly ethyl levulinate (EL), have gained prominence due to their versatility in applications ranging from biofuels to lubricants and green solvents. This study presents an efficient, one-pot catalytic conversion of various carbohydrates (glucose, fructose, and sucrose) into EL using a tailored Keggin-type heteropolyacid catalyst with a vanadium-to-tungsten atom ratio of 1:11. Vanadium substitution imparts higher acidity and redox properties to the catalyst, which is reflected in the catalytic performance. The catalyst demonstrated outstanding performance, achieving high EL yields of 98 +/- 1% from sucrose, 93 +/- 2% from fructose, and 82 +/- 2% from glucose under batch processing conditions (180 degrees C, absolute ethanol solvent, 27 wt % catalyst, 2 h). The high yield of EL may be assigned to the presence of both Br & oslash;nsted and Lewis acid sites, which promotes key reactions like isomerization and ethanolysis. Moreover, a significant EL yield of 85 +/- 2% was obtained from cellulose feedstock, which showcases the efficiency of this catalyst. The use of absolute ethanol as solvent enhanced esterification prospects, preventing hydrolysis and promoting higher EL yields, while the presence of water as cosolvent favored the formation of levulinic acid. These findings demonstrate the potential of vanadium-substituted heteropolyacid catalysts for efficient biomass valorization, offering a sustainable pathway for the large-scale production of EL from renewable feedstocks.

Investigating the visible range photoresponse of an organic single-crystal analogue of the green fluorescent protein - Virole, Vishal; Dabke, Niteen; Verma, Sahil; Kumar, Ajay; Pandya, Rinu; Husale, Sudhir; Vanka, Kumar; Gonnade, Rajesh; Kanawade, Rajesh (Nanoscale, 2025)
The growing demand for lightweight, flexible, semi-transparent and low-cost photodetectors (PDs) in wearable electronics and optical communication systems has prompted studies to investigate organic materials as feasible alternatives to conventional inorganic PDs. However, modern organic PDs often face responsivity, detectivity, and photoresponse speed limitations, particularly in the visible range. Here, we present the photoresponse of an organic single-crystal analogue of the green fluorescent protein (GFP) chromophore photodetector, fabricated on a silicon nitride substrate. A significant increase in photocurrent was detected upon illumination with visible wavelengths (532 nm, 630 nm, and halogen light). A remarkably consistent and repeatable photoresponse was obtained during the ON and OFF illumination cycles. The device showed the dependence of photocurrent on the applied bias voltages. The measured photocurrent, responsivity, detectivity, rise time, decay time, noise equivalent power and external quantum efficiency are studied for different wavelengths. Strikingly, the fabricated device demonstrates excellent performance in the visible region compared to several conventional organic and inorganic PDs. The observed responsivity and detectivity values for the device are 98 mA W-1 and 7.94 x 108 Jones, respectively. Furthermore, the device also exhibits rapid photoresponse dynamics with a rise time of 180 ms and a decay time of 152 ms. The excellent photodetection features indicate that the single crystal GFP could serve as a versatile broadband material for future applications in optoelectronics.

LDH-dsRNA nanocarrier-mediated spray-induced silencing of juvenile hormone degradation pathway genes for targeted control of Helicoverpa armigera - Joshi, Kaumudi S.; Barvkar, Vitthal T.; Hadapad, Ashok B.; Hire, Ramesh S.; Joshi, Rakesh S. (International Journal of Biological Macromolecules, 2025)
Helicoverpa armigera, a devastating agricultural pest, poses significant threats to global crop productivity. Targeting the Juvenile Hormone (JH) degradation pathway may offer a promising approach for pest management, given its pivotal role in insect development and reproduction. In this study, we developed a nanoclay-based formulation of double-stranded RNA (dsRNA) targeting three key JH degradation pathway genes: Juvenile Hormone Esterase (HaJHE), Juvenile Hormone Epoxy Hydrolase (HaJHEH), and Juvenile Hormone Diol Kinase (HaJHDK). Expression analysis revealed tissue and stage-specific patterns of these genes, with qRT-PCR confirming high expression levels of specific isoforms in key developmental transition: the pre-pupal stage. Treatment with bacterially expressed dsRNAs achieved >50 % silencing of target genes, resulting in delay in larval-to-pupal transitions. Bioassay demonstrated that treatment with LDH-based dsRNA nanocarrier resulted in downregulation of target genes, causing developmental delays, including prolonged larval and pupal stages. Metabolomic analysis further indicated reduced accumulation of JH degradation pathway metabolites, highlighting the pathway-specific action of dsRNAs. Furthermore, combinatorial application of dsRNAs resulted in higher mortalities compared to individual dsRNA application. These results suggest that the application of the LDH-based dsRNA nanocarrier formulation against H. armigera JH degradation pathway for spray-induced gene silencing could serve as a potential insect management strategy.
Keywords: Development; dsRNA; Helicoverpa armigera; Juvenile hormone; Layered double hydroxide; Nanocarrier

Molecular insights into the oleic acid accumulation in safflower - Salunke, Gayatri; Badhe, Yogesh; Singh, Vrijendra; Ghorpade, Prakash; Hegde, Mahabaleshwar; Kadoo, Narendra (Journal of the American Oil Chemists Society, 2025)
Most of the Indian safflower (Carthamus tinctorius L.) varieties produce oil rich in linoleic acid (LA, similar to 75%) and low in oleic acid (OA, similar to 15%). In the fatty acid biosynthetic pathway, the fatty acid desaturase 2 (FAD2) enzyme converts OA to LA. Safflower is reported to have 12-20 FAD2 genes. Gene expression analysis of four FAD2 genes during seed development in a high LA variety, PBNS-12, revealed high expression of FAD2-1 at 21 days after flowering (DAF), correlating with high LA accumulation. Fatty acid profiling of 448 Indian safflower germplasm accessions revealed four lines to have high (58%-77%) OA content, with NASF-39 having the highest OA content. Interestingly, all four high OA lines showed the same mutation in the FAD2-1 gene. The DNA sequence of FAD2-1 from the four high OA lines showed a deletion of C at the +606 position, resulting in a premature stop codon at the +733 position and a truncated protein of 244 amino acids. Hence, despite the high expression levels of FAD2-1 in NASF-39 at 18-21 DAF, it exhibited high OA (77%). The dysfunctional nature of the truncated FAD2-1 in NASF-39 was evident in molecular docking studies with 1-stearoyl-2-oleoyl phosphatidylcholine. We also sequenced FATB, a thioesterase responsible for releasing stearic acid from acyl carrier protein for further desaturation to oleic acid, where an A773G substitution was observed. This resulted in E258G substitution in NASF-39 FATB compared to that of PBNS-12. This probably made the acyl-binding pocket of NASF-39 FATB unstable, contributing to high OA accumulation. Thus, the outcomes of this study can help develop super and ultra-high oleic safflower varieties through various genetics and genomics approaches.
Keywords: Carthamus tinctorius; FAD2; FATB; Fatty acid desaturase; fatty acid thioesterase; linoleic acid

Morphology rearrangement by mixing of internally hydrogen-bonded nanoparticles comprising triazine-based amphiphilic diblock copolymers - Haque, Farah; Thompson, Steven W.; Ishizuka, Fumi; van der Tol, Joost J. B.; Singh, Dharmendra; Sanjayan, Gangadhar J.; Zetterlund, Per B. (Macromolecules, 2025)
The self-assembly of block copolymers holds significant potential for designing functional nanoparticles in materials science, nanomedicine, and nanotechnology. While the self-assembly of amphiphilic diblock copolymers is relatively well understood, the influence of specific supramolecular interactions, particularly hydrogen bonding, in directing their morphological behavior remains largely unexplored. In this study, it was demonstrated that nanoparticles self-assembled in water/DMSO (75/25 vol/vol; 2 mg/mL) comprising amphiphilic diblock copolymers with a small amount of triazine-based guanine-cytosine (GCB) motifs incorporated in the hydrophobic block can undergo spontaneous rearrangement into new morphologies on mixing. For example, mixing spheres with vesicles resulted in spontaneous transformation into worms (nanofibers), and this transformation was accelerated at elevated temperature. The hydrogen bonding motif features three complementary hydrogen bonding sites on either side of the nucleobase unit, thereby having a Janus character. Amphiphilic diblock copolymers comprising dimethyl acrylamide (hydrophilic segment) and n-butyl acrylate (hydrophobic segment) were synthesized by reversible addition-fragmentation chain transfer (RAFT) polymerization with a variable content of acrylate monomer functionalized with the Boc-protected form of the GCB motif as part of the hydrophobic segment. The present work represents a completely new approach for controlling self-assembly processes, paving the way for the design of functional nanoparticles for a range of applications.

Multifunctional luminogens with synergy of aggregation-induced delayed fluorescence, two-photon absorption and photocurrent generation - Chatterjee, Abhijit; Narayanan, Sundaravalli; Thorat, Sachin; Malik, Ajay J.; Ambhore, Madan D.; Narayanan, Aswini; Sihag, Anil Kumar; Babu, Sukumaran Santhosh; Lahiri, Mayurika; Hazra, Partha (Chemical Communications, 2025)
In this study, we investigated the aggregation-induced delayed fluorescence (AIDF) properties of three luminogens - TN, TA, and TP. Our comprehensive theoretical analysis reveals a significant reduction in the Delta EST in their aggregated or solid-state, activating TADF, on a similar to mu s time-scale. Additionally, these luminogens demonstrate two-photon excited anti-Stokes photoluminescence emission and improved photocurrent generation, attributed to their strong charge transfer characteristics and longer singlet exciton lifetimes.

Mycobacteria-specific prodrug to overcome phenotypic AMR in mycobacterium tuberculosis - Kumar, T. Anand; Birua, Shalini; Mallojjala, Sharath Chandra; Mukherjee, Piyali; Singh, Samsher; Kaul, Grace; Ramachandran, Aparna; Akhir, Abdul; Chopra, Sidharth; Gadgil, Chetan J.; Hirschi, Jennifer S.; Singh, Amit; et al. (Journal of Medicinal Chemistry, 2025)
Most front-line tuberculosis (TB) drugs are ineffective against hypoxic nonreplicating Mycobacterium tuberculosis (Mtb), largely due to poor permeability, leading to reduced drug accumulation and target engagement. To overcome this phenotypic antimicrobial resistance (AMR), we developed nitroheteroaryl prodrugs for Moxifloxacin (MXF), a front-line TB drug. These prodrugs are activated by bacterial nitroreductases (NTR), which are overexpressed in hypoxic Mtb. NTR-mediated electron transfer and protonation facilitate rapid cleavage of the protective group, releasing active MXF. The lead prodrug exhibited comparable efficacy to MXF in replicating Mtb and significantly enhanced lethality in nonreplicating Mtb. Drug accumulation studies confirmed a modest but significant increase in MXF levels in nonreplicating Mtb treated with the prodrug, suggesting improved permeability. A mathematical model integrating growth and drug-killing kinetics further elucidated how permeability differences impact lethality. Together, these findings highlight enzyme-activated prodrugs as a promising strategy to address phenotypic AMR in Mtb

Nigericin-induced apoptosis in acute myeloid leukemia via mitochondrial dysfunction and oxidative stress - Arun, Bhavyadharshini; Gopinath, Prarthana; Jha, Anup; Tripathi, Nishtha; Dastager, Syed G.; Hasan, Syed K. (Oncology Research, 2025)
Background: Acute Myeloid Leukemia (AML) is a highly aggressive clonal hematological malignancy with limited treatment options. This study aimed to evaluate the therapeutic potential of nigericin, a polyether ionophore derived from Streptomyces DASNCL-29, as a mitochondrial-targeted agent for AML treatment. Methods: Nigericin was isolated from Streptomyces DASNCL-29 and characterized via chromatography and NMR. Its cytotoxicity was tested in MOLM13 (sensitive and venetoclax-resistant) and HL60 (sensitive and cytarabine-resistant) cells using the MTT assay. Mitochondrial dysfunction was assessed by measuring reactive oxygen species (ROS), mitochondrial membrane potential (Arum), and mitochondrial mass. Apoptosis was evaluated with Annexin V/PI assays and immunoblotting, while proteomic analysis was conducted using Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) to identify differentially regulated proteins. Results: Nigericin demonstrated potent cytotoxicity with IC50 values of 57.02 nM in MOLM13-sensitive, 35.29 nM in MOLM13-resistant, 20.49 nM in HL60-sensitive, and 1.197 nM in HL60-cytarabine-resistant cells. Apoptosis was confirmed by Annexin V/PI staining and caspase-3/PARP cleavage, along with MCL-1 downregulation. Mitochondrial dysfunction was evident from increased ROS, reduced Arum, and decreased mitochondrial mass. Proteomic profiling identified 264 dysregulated proteins, including a 3.8-fold upregulation of Succinate Dehydrogenase [Ubiquinone] Flavoprotein Subunit A (SDHA). Conclusion: Nigericin induces apoptosis in AML cells by disrupting mitochondrial function and enhancing oxidative stress. Its nanomolar potency highlights the need for further mechanistic studies and in vivo evaluations to explore its potential in AML treatment.
Keywords: Acute myeloid leukemia (AML); Antineoplastic agents; Apoptosis; Mitochondrial dysfunction; Nigericin

Optimisation of metallic bismuth nanoparticle supported Pt-Bi(x%)/C hybrid electrocatalyst for cost effective and efficient hydrogen production in alkaline media - Dokhe, Revati; Ugale, Atul; Dube, Onkar; Varpe, Vaibhav; Galave, Chaitanya; Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Kumar, Ajay; Husale, Sudhir; Natu, Varun; Shevate, Rahul; et al. (International Journal of Hydrogen Energy, 2025)
The present study employed a simple mechanochemical method followed by 24-h ultrasonication to synthesize oxide-free metallic bismuth (Bi) nanoparticles. This was further used to synthesize a Pt-Bi(x%)/C (NC-x) hybrid electrocatalyst for the hydrogen evolution reaction in alkaline media. X-ray photoelectron spectroscopy and contact angle measurements reveal, Bi modifies the electronic structure and surface morphology of the Pt/C electrocatalyst, thus enhancing reaction kinetics and active site availability. The relative three-electrode study reveals that optimised NC-20 electrocatalyst reduces the overpotentials by 10.44 % and enhances the current density by 53 % compared to commercial Pt/C. The practical applicability of the NC-20 electrocatalyst was studied with the 13 cm2 single cell anion exchange membrane electrolyser. The catalyst demonstrates promising performance where the current density of NC-20//IrO2 relatively increases by 22.6 % compared to standard Pt/ C//IrO2, and shows continuous production and stable performance when monitored for 30 h.
Keywords: AEM; Bismuth nanoparticles; electrocatalyst; Full cell electrolysis; hydrogen evolution reaction; water electrolysis

Probing the effect of fluorine on hydrogen bonding interactions in a pharmaceutical hydrate using Advanced Solid-State NMR - Hareendran, Chaithanya; Ajithkumar, T. G. (Molecular Pharmaceutics, 2025)
Structural studies of pharmaceutical hydrates are essential to understanding stability-related issues, especially during the heating process of formulation. A thorough understanding of the hydration and dehydration behavior of active pharmaceutical ingredient (API) hydrate is also important since phase transitions can occur during the formulation process. This is because dehydration could result in a considerable rearrangement in the structure if water-API hydrogen bonding is present. We perform advanced solid-state NMR experiments on regorafenib monohydrate to investigate the role of fluorine in hydrogen bonding interaction, and the results are compared to its anhydrous form and its structural analogue, namely, sorafenib. Our results show that significant structural changes could not be observed on dehydration. Based on our study, it can be concluded that the introduction of fluorine restricts the intramolecular hydrogen bonding and the asymmetry in the structure of regorafenib monohydrate is absent, in comparison to sorafenib.
Keywords: DQSQ; Hydrogenbonding; pharmaceutical hydrate; regorafenib; Solid-state NMR

Rational design of reduced graphene oxide/TiO2/gold nanorod nanocomposite for complete degradation of polystyrene microplastics in wastewater - UshaVipinachandran, Varsha; Naveenkumar, K.; Haroon, Kabir Hussain Badagoppam; Ashokan, Indhumathi; Sinha, Arup; Maity, Pradip; Bhunia, Susanta Kumar (Advanced Sustainable Systems, 2025)
Our planet is being devoured by plastic consumption every day. Water, soil, and air are deliberately polluted by the ingredients of these nondegradable plastics. Extensive usage of plastic has serious consequences in the environment, wildlife, and human health. A comprehensive approach to eradicate plastics from the planet is therefore imperative. Herein, a ternary nanocomposite subsumed of reduced graphene oxide (rGO), titanium dioxide (TiO2), and gold nanorods (AuNRs) is synthesized and effectively deployed to remove plastics from water as well as degradation of polymer film by both chemically and photocatalytically. The hydrothermally prepared nanocomposite completely removes polystyrene molecules from water, and 1.2 mg of plastic degradation is observed during the photolysis. Conversely, chemical degradation pathway induces the weight loss of 10.7 mg. Both Plasmon-induced interfacial charge transfer transition (PICTT) and Plasmon-induced hot electron transfer (PHET) assist the formation of reactive oxygen species (ROS) that collectively degrades the polymer strands. The spectrochemical and microscopic studies validate the degradation studies with cautious conclusions.
Keywords: chemical degradation; Photocatalysis; plasmonic hot electron; polystyrene microplastics; Reduced graphene oxide

Real-time estimation of blood oxygenation parameters from human foot sole during leg elevation: a preliminary study with diffuse reflectance spectroscopy - Kumar, Ajay; Lohchab, Viney; Pawar, Dnyandeo; Someshwar, Vimal; Mathe, Vikas; Husale, Sudhir; Kanawade, Rajesh (Optics and Laser Technology, 2025)
This study investigated the applicability of diffuse reflectance spectroscopy (DRS) for real-time and non-invasive measurement of blood oxygenation parameters (BOPs) such as reduced hemoglobin (RHb), oxyhemoglobin (HbO(2)), and oxygen saturation (SO2) from human foot sole during leg elevation. Seventeen (17) healthy male subjects aged between 21 to 39 years were included in this study. Diffuse reflectance spectra were recorded from measurement sites namely the 5th metatarsal, ball of great joint, calcaneum, and great toe of the human foot sole w.r.t. leg elevation angles such as 0(0), 15(0), 30(0), 45(0), and 60(0), respectively. The localized BOPs were derived from the recorded spectra. In addition, blood hemodynamic parameters (BHPs) such as heart rate (HR), SO2, perfusion index (PI), systolic blood pressure (SBP), and diastolic blood pressure (DBP) were also measured for each elevating angle. To study and assess the changes in BOPs and BHPs w.r.t. leg elevation, a One-way ANOVA test followed by a Tukey HSD post-hoc test was performed. We observed a statistically significant increase in RHb (p < 0.001) and a decrease in HbO(2) (p < 0.001) after 45 degrees of leg elevation, however, there was no statistically significant difference in SO2 (p = 0.74) and HR (p = 0.84) for each measurement site w.r.t. leg elevation, respectively. Furthermore, PI (p < 0.01), ankle SBP (p < 0.001) and DBP (p < 0.001) were decreased w.r.t. leg elevation. The obtained results are in agreement with the literature. The preliminary results suggest that DRS has the potential for real-time estimation of BOPs from the local sites of healthy human foot soles during leg elevation. Thus, it opens the possibility of DRS to monitor and evaluate the diagnosis and treatment of ischemia and edema during leg elevation of patients through BOPs measurement.
Keywords: diabetic foot ulcer; diffuse reflectance spectroscopy; Leg elevation; Oxygen saturation; Oxyhemoglobin; Reduced hemoglobin

Regioisomeric π-extended nanographene with long-lived phosphorescence afterglow - Kumar, Viksit; Venugopal, Geethu; Jadhav, Ashok Badrinarayan; Dongre, Sangram D.; Gonnade, Rajesh; Kumar, Jatish; Ruer, Paul C.; Hupp, Benjamin; Steffen, Andreas; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2025)
The cutouts of graphene sheets, particularly those with a nonplanar topology, present vast opportunities for advancement. Even a slight deviation from the planar structure can lead to intriguing (chiro)optical features for helically twisted nanographenes. In this context, we introduce two regioisomeric pi-extended nanographenes that exhibit distinct excited-state characteristics. The helicene structure and the photophysical features can be easily tuned by changing the connecting position of the nanographene to the carbazole core (2,7- and 3,6-). Single-crystal X-ray diffraction analysis confirmed the formation of nanographenes with bent and helical conformations. Both derivatives exhibited thermally activated delayed fluorescence at room temperature and phosphorescence at low temperatures. Notably, the nanographene with the bent structure displayed an impressive red afterglow lasting over 30seconds, in contrast to the very weak afterglow observed in the helical structure. DFT calculations revealed the existence of an isoenergetic higher triplet state (T-8) and comparatively weak spin-orbit coupling (T-1-S-0), thereby enabling the bent nanographene to exhibit a long-lived component and strong afterglow. Our findings highlight the significance of regioisomeric nanographenes with exceptional optical properties and offer a deeper understanding of the structure-property relationship in nonplanar nanographenes.
Keywords: Afterglow; CPL; Helicenes; nanographene; Phosphorescence; TADF

Scalable and sustainable reductive amidation of nitroarenes, nitroalkenes, and nitroalkyls with acyl saccharins in aqueous media - Khamkar, Sunil L.; Mohan, Rayala; Santhosh, J.; Shinde, Harish M.; Handore, Kishor L.; Mohan, S. Venkata; Reddy, D. Srinivasa (Communications Chemistry, 2025)
Amide bond formation is essential in both organic and medicinal chemistry, however, most existing methods present poor ecological efficiency. Here, we report a scalable and sustainable method for synthesizing N-substituted amides from nitroarenes, nitroalkenes, nitroalkyls, and acyl saccharin in aqueous media. This atom-efficient approach avoids column chromatography, offers high yield, and is compatible with various functional groups. It is applicable to synthesize Dispyrin, a bromopyrrole alkaloid, amide-based drugs, and agrochemicals, including paracetamol, with solvent and saccharin recycling. A comprehensive Life Cycle Assessment (LCA; ISO 14044) was conducted to evaluate the environmental impacts and sustainability of nine Active Pharmaceutical Ingredients (APIs) produced via Amidation Route (AR) and Saccharin Amidation Route (SAR). The study shows SAR methods reduce carbon footprints and environmental impacts compared to AR methods, being carbon-negative and resource-efficient. Additional reductions can be achieved through saccharin recycling and the integration of renewable energy sources, demonstrating saccharin-based processes potential to minimize environmental burdens in pharmaceutical synthesis.

Stereoselective strategies for the synthesis of functionalized cis-hydrindanes in natural product synthesis - Survase, Vijayanand U.; Handore, Kishor L. (European Journal of Organic Chemistry, 2025)
The cis-hydrindane motif is a bicyclic structure commonly found in many natural products that exhibit significant biological activity. This structural feature is present in a variety of bioactive compounds, particularly terpenoids, steroids, and alkaloids, which are known for their therapeutic potential, including anti-inflammatory, antimicrobial, antiviral, and anticancer properties. Due to its prevalence and biological relevance, the cis-hydrindane framework has attracted considerable attention from synthetic chemists, who have devoted substantial effort toward developing efficient and diverse methods for constructing this important motif. Many of the synthesized cis-hydrindane compounds have been used as key intermediates or building blocks in the total synthesis of complex natural products. This review provides an overview of strategic approaches for synthesizing functionalized cis-hydrindanes and its derivatives from 2000 to the present day, focusing on their application in natural product synthesis. By examining the diverse methods and their impact on natural product synthesis, this review will underscore the enduring importance of the cis-hydrindane framework in both synthetic organic chemistry and medicinal chemistry.
Keywords: annulation; Cis-hydrindane; Diel-Alder reaction; Natural products; Total synthesis

Steric hindrance modulated efficient thermally activated delayed fluorescence with non-linear optical, ferroelectric and piezoelectric properties - Dutta, Madhusudan; Chatterjee, Abhijit; Deka, Nilotpal; Tanwar, Riteeka; Mishra, Vishnu; Saha, Arindam; Mandal, Pankaj; Boomishankar, Ramamoorthy; Hazra, Partha (Chemical Science, 2025)
Multi-carbazole-based benzonitrile systems are efficient thermally activated delayed fluorescence (TADF) materials for organic light-emitting diodes (OLEDs). However, they suffer from low PLQY due to the large dihedral angle arising from steric crowding. Addressing this challenge, we demonstrate a potent strategy to engineer steric crowding in this work. To achieve our goal, we have designed three luminogens, namely, CzPHCN, tCzPHCN and Cz2CzPHCN based on phenanthrene-9,10-dicarbonitrile (PHCN), as an acceptor core to minimize the steric hindrance between the donor groups. Among the three luminogens, tCzPHCN exhibits a maximum PLQY of 86% and the highest RISC rate of 3.5 x 105 s-1, the underlying cause being the least dihedral angle of 45.72 degrees and suppressed intermolecular interaction due to the presence of the bulky tert-butyl group. Interestingly, our QM/MM calculations and experimental evidence suggest that the RISC process of both CzPHCN and tCzPHCN takes place via a hot exciton channel. Unlocking a new realm of applications, the unique non-centrosymmetric space group (Cmc21) of CzPHCN offers excellent SHG with a chi(2) value of 0.21 pm V-1 at 1320 nm. In addition to this, the molecule depicts good ferroelectric (PS = 0.32 mu C cm-2), piezoelectric energy harvesting (VOC = 2.8 V) and two-photon absorption properties.

Supercooled liquid phases of luminescent zero dimensional metal halide hybrids - Kumar Das, Deep; Marayathungal, Jumana Hasin; Palakkolil, Athira; Sarma, Dhritismita; Khan, Akram Aadil; Kumar, M. Praveen; Kudlu, Ashwath; Choudhary, Mahendra; Hathwar, Venkatesha R.; Pujala, Ravi Kumar; Mahata, Arup; Kundu, Janardan (Journal of Physical Chemistry Letters, 2025)
Chemical design of metal halide hybrids (MHHs) with suppressed melting point (T-m) allows access to glassy phases from their liquid-melts. Thermal phase change (crystal-melt-glass) properties of glassy MHHs (with glass transition temperature T-g > room temperature) have been exploited for device applications. However, room temperature stable supercooled liquid (SCL) MHHs (with T-g < room temperature), originating from glass-SCL phase change, remain inaccessible. Here, a molecular design strategy is reported to access ambient stable, melt-processable, SCL multimetallic bromide hybrids (Mn2+,Cd2+; Mn2+,Zn2+; Benzyltributylammonium) with low T-g (15-16 degrees C), low T-m (90-100 degrees C), green luminescence, and high optical transparency. Structural, optical, thermal, and computational analyses highlight chemical design principles and support dopant (Mn2+) based luminescence. Rheological measurements confirm the SCL phase that shows thermal hysteresis and estimate relaxation time scales. This work provides a new material platform showcasing enhanced melt-processability for fabrication of moldable devices, unravelling chemical makeup-property correlation and expanding the material phase types of MHHs.

Sustainable isolation of cellulose nanofibers with superior crystallinity and thermal stability from Terminalia catappa L. fruit peel waste - Harsha, R.; Mol, A. P. Princy; Paul, Sharon; Badawi, Michael; Ajithkumar, T. G.; Rao, H. Jeevan; Parameswaranpillai, Jyotishkumar; Nair, Ajalesh B.; Begum, P. M. Sabura; Dominic, C. D. Midhun (Biomass Conversion and Biorefinery, 2025)
Turning agricultural waste into value-added products is a key focus of sustainable development. Herein, cellulose nanofibers (CNF) were extracted from the pericarp of Terminalia catappa L. for the first time. The CNF was extracted by chlorine-free pretreatment methods followed by oxalic acid hydrolysis (5 wt%) assisted with steam explosion. The prepared CNF were characterized by Fourier transform infrared spectroscopy (FTIR), solid-state 13C nuclear magnetic resonance spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA and DTG). FTIR analysis confirmed the successful removal of lignin and hemicellulose during chemical treatment which was again validated by solid-state 13C NMR analysis. TEM image revealed that the diameter of the extracted nanofibers ranges from 14 to 18 nm. From XRD analysis, the crystallinity index of the CNF was 82%, while that of the raw sample was 62 %. The temperature at which the maximum degradation (Tmax) of CNF occurred was found to be 372 degrees C which is superior to that of the raw sample (334 degrees C). The extracted cellulose nanofibers were used to prepare cellulose paper, demonstrating a tensile strength of 1.1 MPa, indicating its potential suitability for biodegradable packaging applications.
Keywords: cellulose; Cellulose nanofiber; green synthesis; Waste to wealth

Sustainable UV absorbing bio-plastic films by valorisation of humins and chitosan - Lucas, Nishita; Tambe, Snehal S.; Parate, Roopa; Hengne, Amol; Rode, C. V.; Athawale, Anjali A. (International Journal of Biological Macromolecules, 2025)
Humins, an inevitable bio-refinery waste by-product of sugar dehydration have been efficiently utilized for the first time for developing biodegradable thin films for UV shielding. The films were prepared from chitosan, and humins, a novel combination, aiming towards simultaneous utilization of marine and bio-refinery waste, rendering simple, effective, robust UV absorbing films. The structure-activity relationship of these films were elucidated with the help of different analytical techniques like X-ray diffraction, Fourier transform infrared spectroscopy, Thermogravimetric analysis, UV-vis spectroscopy, Atomic force microscopy, Scanning electron microscopy, Tensile testing, Contact angle measurements and water absorption studies. Intrinsic biodegradability was studied using fungi i.e. Aspergillus niger. Different feedstocks (corncob, rice husk, glucose and xylose) were explored for generating humins. Amongst them, humins derived from xylose were utilized for the preparation of the bio-plastic films of chitosan. The results revealed that, addition of 5.0 % humins was observed to be an optimum concentration yielding films with excellent UV absorption, mechanical properties, and biodegradability. The current work is in perfect alignment with sustainability and green chemistry as it ameliorates waste valorization (lignocellulosic and marine altogether). Further, its innovation stems from the first-hand use of humins for UV absorption, novel combination of biopolymers, use of green raw materials.
Keywords: biodegradable; Chitosan; Humins; Thin films; UV absorption; Waste valorization

Synthesis of Readily Modifiable Amides from Aldehydes via an Organocatalytic Approach Using a CTAB Surfactant - Akhade, Akshay M.; Rokade, Avinash D.; Handore, Kishor L. (Journal of Organic Chemistry, 2025)
A simple and efficient organocatalytic method has been developed to access ``readily modifiable'' amides, including bench-stable N-acyl saccharin and various activated amides, from aldehydes by using CTAB- t BuOOH. A wide range of aromatic and aliphatic acyl saccharin are obtained from their respective aldehydes with moderate to good yields. The approach can be similarly applied toward the formation of N-acyl imidazole, N-acyl benzimidazole, N-methoxy-N-methylamide (Weinreb amide), N-ethyl-N-phenylbenzamide, N-acyl morpholine, N-acyl valerolactam, and N-acyl caprolactam. These compounds are frequently applied as reagents in organic transformations, including acyl coupling, decarbonylative coupling, radical coupling, and coupling that is free from transition metals, enabling the synthesis of new C-C, C-N, C-O, C-S, C-P, and C-B bonds.

Total biocatalytic synthesis of capsaicinoids using ferulic acid: a versatile two-step strategy for natural product diversification - Khobragade, Taresh P.; Giri, Pritam; Patil, Mahesh D.; Joo, Sangwoo; Cho, Sunga; Kim, Yechan; Ghosh, Rohan; Jeong, Sanghun; Maeng, Minyeong; Song, Min-Ho; Park, Jeong-Min; Lee, Eun Ho; et al. (Angewandte Chemie-International Edition, 2025)
The wide-ranging application of capsaicinoids, the active compounds in chili peppers, has driven increasing interest in the development of sustainable production strategies. However, capsaicinoid synthesis remains a challenge. The objective of this pioneering study is to report the total biocatalytic synthesis of structurally diverse capsaicinoids from bio-based ferulic acids. An X-ray crystallographic study elucidated the structural basis for the exceptional potential of a novel transaminase from Phaeobacter porticola (PPTA) to transform the highest ever reported concentration of vanillin (100-200 mM) to vanillylamine, with >99% conversion and modest conversion ranging from 48% to 79% for 300 to 500 mM substrate. Using PPTA in tandem with phenolic acid decarboxylase (PAD) and aromatic dioxygenase (ADO) further enabled the direct synthesis of vanillylamine from ferulic acid with >99% conversion. Furthermore, the integration of a multi-enzymatic cascade with carboxylic acid reductases (CARs) successfully synthesized structurally diverse capsaicinoids via amide bond formation between vanillylamine and free fatty acids, with excellent conversions ranging from 72% to >88%. A 50-mM enzymatic reaction afforded 95% and 80% conversion of vanillylamine and capsaicin, respectively.
Keywords: Capsaicinoids; Carboxylic acid reductase; Transaminase; Vanillylamine

Unravelling chain confinement and dynamics of weakly entangled polymers in one component nanocomposites - Kruteva, M.; Monkenbusch, M.; Sharma, A.; Allgaier, J.; Hoffmann, I.; Rosi, B.; Dulle, M.; Porcar, L.; Matsarskaia, O.; Richter, D. (Soft Matter, 2025)
Structure and dynamics of polymer chains grafted to a nanoparticle (NP) surface in one component nanocomposites (OCNC) are investigated by small angle scattering (SAXS, SANS) and neutron spin echo (NSE). The OCNC were realized by self-assembly of block-copolymers and subsequent cross-linking of the core. The sizes of the resulting NPs were narrowly distributed. Owing to equal core and shell volumes the melt structure is that of a concentrated colloidal dispersion of cores. The melt structure could be reasonably well described by a Percus-Yevick structure factor. In order to access more deeply the dynamics, three differently labeled materials with labels at the inner- or outer part and the whole graft were studied. The experimental data were evaluated in terms of models allowing for site dependent friction. For this purpose, the Langevin equation containing a friction profile was solved and the dynamic structure factor in terms of its eigenvalues and eigenvectors was compared to the data. The evaluation shows increased friction towards the grafting points. In addition, topological restrictions of motion due to the dense arrangements of micellar cores and the presence of neighboring chains were considered and compared with those of a corresponding melt. Assuming homogenous relaxation of all grafts did not yield a satisfactory data description, but rather at least two differently relaxing chain ensembles had to be considered.

Valorization of avocado peel waste: extraction and characterization of cellulose nanofibers for multifunctional applications - Varsha, P. V.; Neenu, K. V.; Begum, P. M. Sabura; Hounfodji, Jean Wilfried; Sankar, Sameera; Muraleedharan, Sneha; Kamath, Anjali N.; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Midhun, Dominic C. D. (Biomass Conversion and Biorefinery, 2025)
This study explored the utility of underutilized avocado peels for extracting cellulose nanofibers (CNFs). Mild oxalic acid hydrolysis assisted by steam explosion was employed after alkali hydrolysis and chlorine-free bleaching to prepare cellulose nanofibers. The structural, atomic, and elemental features of the extracted fibers were studied using Fourier transform infrared spectroscopy (FTIR), 13C solid-state nuclear magnetic resonance (13C NMR) spectroscopy, and energy dispersive X-ray (EDAX) analysis, respectively. The crystallinity index of the nanofibers was 87%, which was 53% greater than that of the crude sample. The elution of hemicellulose and lignin was evident from the scanning electron microscopy (SEM) images, and the nanofibers had a fiber diameter of 30–82 nm according to the transmission electron microscopy (TEM) analysis. The applied chemical treatment also elevated the thermal stability of the fibers. The extracted fibers can be applied in numerous fields, including electronics, packaging, automobiles, biomedicine, and cosmetics.

Concurrent glycerol oxidation and hydrogen production on Ce-Co oxide/carbon for sustainable biomass valorization - Jana, Jayasmita; Chowdhury, Somnath; Saha, Avishek; Kang, Sung Gu; Hur, Seung Hyun; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Integrating glycerol oxidation with water electrolysis offers a sustainable route for hydrogen production while enabling concurrent generation of industrially relevant C1-C3 value-added materials. This system replaces kinetically sluggish oxygen evolution reaction (OER) simultaneously delivering H-2 at the cathode with high turnover frequency, thereby lowering the overall cell voltage and enabling the valorization of glycerol, a major by-product of the biodiesel industry. However, the development of an efficient bifunctional electrocatalysts capable of driving cathodic as well as anodic half-cell reactions remains a key challenge. Herein, we present a cerium-cobalt oxide composite modified with an amorphous carbon layer (Ce,Co-O/C) as an effective bifunctional catalyst for glycerol-assisted water electrolysis. The interfacial electron distribution across the Co-Ce oxide heterojunction generated abundant redox-active sites and accelerates reaction kinetics, while the conductive carbon layer facilitates rapid charge transfer and imparts improved stability. Consequently, the Ce, Co-O/C catalyst exhibited high formate selectivity at 1.4 V (vs RHE) at room temperature and delivers a low cell voltage of 1.90 V at 100 mA cm(-2) in a symmetric Ce,Co-O/C vertical bar vertical bar Ce,Co-O/C system, maintaining operational stability over 100 h. This work provides a promising interface-engineering for designing self-supported bifunctional electrocatalysts toward integrated biomass assisted co-electrolysis systems.
Keywords: Amorphous carbon; biomass valorization; electrocatalysis; energy conversion; green hydrogen

Direct conversion of methane to formic acid over Au-Fe-NaZSM-5 at ambient pressure using H2O2 - Kumar, Pawan; Ahangar, Iqra; Kesarwani, Srishti; Urkude, Rajashri; Patil, Nita A. R.; Niphadkar, Prashant; Bokade, Vijay V.; Haider, M. Ali; Vinod, C. P. (Catalysis Science & Technology, 2026)
Direct conversion of methane to value-added products is a long-standing challenge. This report presents the one-step conversion of methane to oxygenates using H2O2 as an oxidant over an Au and Fe supported on NaZSM-5 (0.1Au0.1FeNZ) catalyst, which produces 4264 mu mol of oxygenates with 89% selectivity toward formic acid at 10 bar and 60 degrees C within 30 min in a batch process. The catalyst also produces 26.5 mu mol of oxygenates with 70% selectivity for formic acid at atmospheric pressure and 80 degrees C in a continuous flow process over 9 h of reaction time, making it the first report of such a process. The synergistic interaction of Au and Fe, with the crucial role of Na ions in the zeolite framework in driving the reaction, is revealed through various characterization tools like TEM, XPS, and XAS. Theoretical studies elucidate the active sites responsible for lowering the activation barrier for the crucial C-H activation step. Thus, the catalyst enables the conversion of methane into formic acid with high activity and selectivity, offering new possibilities for harnessing this potent greenhouse gas under process-friendly conditions that were previously unexplored.

Exploring the interplay of electron density distribution and electrostatic potential in the interaction of nilutamide and flutamide with androgen receptors using quantum crystallography - Balasubramanian, Hemalatha; Poomani, Kumaradhas; Kandasamy, Saravanan; Hathwar, Venkatesha R.; Gonnade, Rajesh G. (RSC Advances, 2026)
Prostate cancer is a malignant disease commonly found in men. Androgens support the growth and survival of prostate cancer cells. To control this growth and the spread of cancer cells, anti-androgen drugs are necessary to block androgen activity. Effective blocking of androgens depends mainly on the structure, intermolecular interactions and charge density distribution, electrostatic potential (ESP) and binding affinity of drug molecules. Nilutamide (NIL) and flutamide (FLU) are two structurally related non-steroidal anti-androgen drugs (NSAAs) which exhibit serious side effects. The present study explores the charge density distribution, electrostatic potential and intermolecular interactions of NIL and FLU determined from a high-resolution X-ray diffraction experiment and a solid-state quantum chemical theoretical study. Topological analysis of charge density reveals the electron density at the bond critical points of chemical bonds and intermolecular interactions. The electrostatic potential derived from the charge density distribution of both molecules in the crystal has been mapped, which allows a prediction of how the electrostatic interactions, hydrogen bonds, and van der Waals forces govern the binding of these two drug molecules with the androgen receptor at the electronic level. The ESP of interacting groups of both molecules in the androgen active site is approximated to the ESP of those groups in the crystals. The charge density distribution and the electrostatic potential of both molecules were compared. The difference in charge density is reflected in the ESP of NO2, CF3 and NH groups and the aromatic ring of both molecules, which is important for drug binding, metabolic stability and toxicity. A molecular docking simulation of both molecules with androgen receptors shows the difference in interactions and binding affinity in the binding pocket of the androgen receptor. The results of the high-resolution X-ray experiment and the advanced computational charge density study of NIL and FLU allows us to understand drug binding and is useful to relate their differing biological effects and toxicities at the electronic level. This information pertains to the design of a new potential androgen inhibitor with improved binding affinity and fewer side effects.

Exploring the role of large synthons in the design of bicomponent salts of cimetidine - Khatun, Saheba; Sar, Bandana; Hosmani, Girish Siddanagouda; Mishra, Manish Kumar; Ravi, Punna Rao; Mukherjee, Arijit (Crystal Growth & Design, 2026)
Cimetidine, a popular histamine H2-receptor antagonist, represents a complex structural landscape exhibiting multiple forms. Attempts to synthesize a bicomponent salt with fumaric acid suffered from crystallization challenges in the past, especially toward the growth of anhydrous single crystals. In this work, we address these crystallization challenges by adopting an alternative crystallization approach involving ionic liquids and analyzing the structural landscape with a large synthon-based approach. Two novel forms of cimetidine fumarate were isolated. The structural differences in the forms of cimetidine fumarate were further explored by using different coformers as structural probes.

Novel biosurfactant assisted biodegradation of polystyrene by Actinomycetes and its chemical understanding - Sakpal, Amrapali; Haq, Nazrul; Dasgupta, Santanu; Alanazi, Fars; Alsarra, Ibrahim A.; Alam, Mahboob; Dastager, Syed G. (Polymer Degradation and Stability, 2026)
The current study highlights the effective biodegradation of polystyrene by two actinobacterial strains, Glutamicibacter sp. K-1 and Rhodococcus sp. BG-30. FT-IR, Raman spectroscopy, and GPC data showed the degradation pattern of polystyrene. Additionally, GC-MS analysis showed that strain K-1 produced a variety of degradation by-products, including alkanes, 2,4-Di-ter-butyl phenol, 2-propenoic acid, tridecyl ester, and dibutyl phthalate, while strain BG-30 produced a greater amount of alkenes, phthalic acid, and isobutyl octyl esters. GPC detected a drop in polystyrene's average molecular weight (Mn), which suggests chain scission of the polymer. Changes in polystyrene's roughness and other morphological properties were shown by AFM and FE-SEM. The effects of a conventional rhamnolipid and a novel thermostable biosurfactant fatty alkene (0.1 % each) on the breakdown of polystyrene were examined. Strain K-1 and BG-30 resulted in increasing the degradation of polystyrene to 12 % (w/w) and 16 % (w/w), respectively in the presence of fatty alkene biosurfactant, there was 10 % (w/w) and 8 % (w/w), degradation in presence of rhamnolipid. To the best of our knowledge, degradation of polystyrene by Glutamicibacter sp. has been reported as a newly identified strain and use of a novel biosurfactant together revealed their potential in biodegradation of plastic to mitigate the plastic pollution using microbial resources.
Keywords: Biodegradation; Fatty alkene biosurfactant; Glutamicibacter sp.; Polystyrene; Rhamnolipid; Rhodococcus sp.

Palladium-catalyzed annulation of acyl saccharins with norbornene via CO shuttling - Rokade, Avinash D.; Teke, Nikhil M.; Handore, Kishor L. (Organic Letters, 2026)
Palladium-catalyzed annulation presents a new approach for synthesizing indanones from readily available N-acyl saccharins and bicyclic alkenes with high yields. This reaction proceeds via cleavage of the C-H, C-C, and C-N bonds of the acyl saccharin and the rearrangement of the carbonyl moiety by decarbonylation and CO reinsertion. This transformation introduces an innovative bond disconnection strategy for annulation reactions via CO shuttling. Additionally, it can also be applied in the synthesis of the CDC7 inhibitor and ferrocene indanone.

Phenylpropanoid-specific glycosyltransferases from mango and their potential role in defense - Vare, Tejas; Joshi, Rakesh; Liao, Jieren; Hoffmann, Thomas; Schwab, Wilfried; Giri, Ashok (Plant Physiology and Biochemistry, 2026)
Alphonso mango (Mangifera indica cv. Alphonso) is a cornerstone of India's fruit industry due to its distinct aroma and shelf-life characteristics. The uridine diphosphate-dependent glycosyltransferases (UGTs) play a crucial role in stabilising aroma and defense-related specialised metabolites in fruits. The present study explores the potential role of UGTs during mango ripening and Colletotrichum gloeosporioides infection. Gene expression analysis indicated that UGTs showed dynamic expression in skin and pulp during ripening. Phylogenetic analysis revealed substrate-driven divergence of UGTs, with MiUGT92A14 and MiUGT95B15 forming distinct clades associated with flavonoid glycosylation. Recombinant UGTs showed a higher preference for UDP-glucose, which is corroborated by the high accumulation of UDP-glucose during ripening. Furthermore, it was observed that MiUGT92A14 prefers phenolic acids as substrates, while MiGT95B15 shows flavonoid specificity. Spore germination assays demonstrated that both aglycones and their glycosylated derivatives suppressed early fungal morphogenesis, supporting a role for UGT-mediated glycosylation in maintaining defense-related metabolites in a bioactive yet non-toxic form during fruit ripening. Additionally, Colletotrichum gloeosporioides inhibition assays demonstrated that glycosylated products of selected UGTs exhibited equal or enhanced antifungal activity compared with their aglycone forms, indicating that glycosylation promotes the safe accumulation of antifungal compounds by reducing aglycone toxicity to the plant. These findings suggest that glycosylation of specific metabolites is a key for ripening process and to potentiate defence against fungal pathogen.
Keywords: Anthracnose; defense; Flavonoid; Glycoconjugates; Uridine diphosphate-dependent glycosyl-transferase

Photoluminescence decay lifetime study of hydrothermally synthesized highly porous ruthenium-silica composite for optical dissolved oxygen sensing application - Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Pandya, Rinu; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Vanka, Kumar; Saha, Avishek; Kanawade, Rajesh (ACS Applied Nano Materials, 2026)
Pore size and surface area of photoluminescence (PL)-based transition metal composites play crucial roles in facilitating oxygen diffusion, thereby enhancing the response and sensitivity of optical dissolved oxygen (DO) sensors. In this study, we successfully applied the hydrothermal method to synthesize a porous ruthenium composite embedded in a silica matrix, demonstrating its effectiveness for optical DO sensing applications. The ruthenium-silica (Ru-Si) composites were synthesized using Ru(bpy)3 2+ and tetraethyl orthosilicate (TEOS) as precursors, with reaction temperatures ranging from 120 degrees C to 200 degrees C over a fixed duration of 4 h. The structural, morphological, and compositional characterization techniques confirmed the successful synthesis and evaluated the porosity, surface features, and chemical structure of the resulting composites. The optimized Ru-Si composite exhibited the highest porosity, characterized by a specific surface area of 996.78 m2 g- 1, and exhibited the highest decay lifetime of 8.14 mu s in deionized (DI) water, compared to other composites. Importantly, we demonstrate an excellent linear response of the synthesized Ru-Si composite to DO concentrations ranging from 2.58 to 11.16 mg L-1, with a Stern-Volmer constant of 0.12. Furthermore, a density functional theory study was conducted to investigate the electronic transitions and to elucidate the oxygen quenching mechanism of the excited Ru composite with molecular oxygen. The calculated photophysical parameters of the composite show good agreement with the experimental results. Preliminary results suggest that the synthesized Ru-Si with high pore size and surface area could be an efficient and effective composite for use in DO sensing applications.
Keywords: Hydrothermal method; opticalDO sensor; oxygen quenching; photoluminescent; ruthenium composite

Polysulfone-based polymer carbon dot membrane for optical dissolved oxygen sensing application - Kadam, Rutuja; Hattale, Gangadhar; Virole, Vishal; Pal, Sanjivani; Abraham, Athira; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Banpurkar, Arun; Kanawade, Rajesh; Saha, Avishek (Chemistry-An Asian Journal, 2026)
The precise monitoring of dissolved oxygen (DO) is essential across industrial, environmental, and biomedical applications. However, the state-of-the-art DO sensing methods often suffer from inherent limitations, which hinder their effectiveness for real-time and long-term DO monitoring. Optical DO sensing, despite its advantages, utilizes expensive metal complexes and is prone to photobleaching and slow response time. Here, we introduce a novel polymer carbon dot (PCD) as a promising candidate for lifetime-based optical DO sensing. The PCD is a metal-free, nontoxic, fluorescent, long decay-lifetime material that is synthesized through hydrothermal method. Our fluorescent PCD exhibits high emission quantum yield (24.32%), long decay-lifetime (10.43 & micro;s), and a linear response to DO concentrations ranging from 0.7 to 12.7 mg/L, with a Stern-Volmer constant of 0.1115. Further, to obtain better oxygen diffusion, high porosity, optical transparency, and high flexibility, PCD was embedded into a polysulfone matrix (PSF_PCD). The PSF_PCD membrane shows better results for the decay lifetime (9.4 & micro;s), surface energy (40.26 mN/m), and average pore diameter of 5 nm. Hence, the obtained results demonstrate the applicability of the PCD in optical DO sensors for real-time and long-term monitoring of DO levels.
Keywords: decay lifetime; dissolved oxygen; Hydrothermal method; polymer carbon dots; polysulfone-based membrane

Unique microswitches positioned extracellular to the orthosteric binding site initiate activation in the β1-adrenergic receptor - Koulgi, Shruti; Harman, Thomas H.; Jones, Andrew J. Y.; Sonavane, Uddhavesh; Nietlispach, Daniel; Sengupta, Durba; Joshi, Manali (Journal of Chemical Information and Modeling, 2026)
Class A GPCRs are known to bind an astonishingly diverse set of agonists, ranging from ions and small molecules to peptides and large proteins that activate these receptors. Interestingly, despite this diversity, agonist binding is described to trigger a conserved activation pathway that propagates changes from beneath the orthosteric agonist-binding site toward the intracellular G protein-coupling site. This suggests the presence of receptor-specific residues upstream of the orthosteric agonist-binding site that not only enable recognition of the ligand but also trigger the common activation mechanism. Using the prototypical beta 1AR-G protein system, we employed microsecond time-scale atomistic molecular dynamics simulations together with NMR experiments to investigate how receptor-specific residues, in conjunction with agonist binding, initiate the conserved activation pathway. We identified state-dependent electrostatic and hydrophobic switches involving unique beta 1AR residues located above the orthosteric binding site, potentially linking them to receptor activation. Our simulations recapitulated the known common activation pathway and also uncovered beta 1AR-specific novel contacts. Additionally, we identified a unique water-mediated R-Y-Y switch near the intracellular end that could facilitate G protein coupling. Overall, based on our work, we propose how evolutionary variations in the extended ligand-binding site could enable receptor-specific agonist recognition, triggering and converging on the common activation mechanism and preserving G protein coupling fidelity.

Unlocking efficient water splitting through Fe-induced activity enhancement in NiCo2O4 bifunctional electrocatalysts - Sankar, K. N. Amba; Mahana, Debashrita; Mohan, S.; Gupta, Suryakant B.; Hussain, Amreen A. (Journal of Materials Science, 2026)
The development of efficient, durable and inexpensive bifunctional electrocatalysts is essential for advancing overall water splitting technologies. In this study, we present a novel strategy involving dilute Fe doping in NiCo2O4 (NCO) spinel structures to enhance their electrocatalytic activity and stability. Fe was introduced at varying concentrations, and the resulting Fe-doped NCO catalysts were systematically characterized to understand their structural, morphological, and surface properties. Comprehensive structural and surface analyses revealed the successful incorporation of Fe ions into the NCO lattice without altering its intrinsic spinel framework. Brunauer-Emmett-Teller (BET) analysis showed that the NCO-Fe1 sample exhibited the highest surface area (41.82 m2g-1) and the smallest pore size, facilitating enhanced ion diffusion and exposure of active sites. Electrochemical studies revealed a pronounced improvement in bifunctional catalytic activity for the NCO-Fe1 catalyst, which delivered low overpotentials of 228 mV for the hydrogen evolution reaction (HER) and 274 mV for the oxygen evolution reaction (OER) at 10 mAcm-2. The corresponding Tafel slopes of 151 mVdec-1 (HER) and 52.54 mVdec-1 (OER) indicate favourable reaction kinetics and efficient charge-transfer dynamics. Furthermore, the overall water-splitting device constructed using NCO-Fe1 electrodes required only 1.72 V at 10 mAcm-2 to sustain continuous operation, maintaining excellent durability over 300 h of testing without significant performance degradation. Hence, this study provides new insights into the role of dilute dopant engineering in multicomponent oxides and establishes NCO-Fe1 as a promising, high-performance, and durable bifunctional electrocatalyst for sustainable water-splitting applications.

Viscoelastic behaviors of hyaluronic derivatives as a function of pH, salt, and temperature - Kadam, Yogesh; Badiger, Manohar V.; Rajamohanan, Pattuparambil R.; Wadgaonkar, Prakash P.; Ducouret, Guylaine; Merland, Theo; Hourdet, Dominique (Journal of Polymer Science, 2026)
Hyaluronic acid and its derivatives are essential polysaccharides widely used in the bio-medical field for their applications in tissue engineering and controlled drug delivery. By revisiting the wide variety of rheological behavior of aqueous hyaluronan solutions as a function of pH, we develop in this work a comparative study between solutions of native hyaluronan (HA) and its derivative (HA-PEPO) obtained by grafting onto thermoresponsive side-chains of poly(ethylene oxide-co-propylene oxide) characterized by a phase transition around body temperature. Based on a large dataset obtained at a fixed polymer concentration, by changing either the chemical composition of the chain and/or the environmental conditions (pH, temperature, added salt), we show that the viscoelastic properties of hyaluronan solutions can be controlled over more than three decades of amplitude with the possibility to get either liquid or gel states, regardless of temperature, as well as sol/gel transitions induced by cooling or heating by the interplay between hydrogen bonds, hydrophobic interactions, and cation binding induced by potassium salts.
Keywords: hyaluronan; Hydrogel; pH-induced gelation; salt-induced gelation; thermoresponsive polymers; tissue engineering